23Na magnetic resonance imaging-determined tissue sodium in healthy subjects and hypertensive patients - Kopp, Christoph; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Mueller, Dominik N.; Schmieder, Roland; Cavallaro, Alexander Josef; Eckardt, Kai-Uwe; Uder, Michael; Luft, Friedrich C.; Titze, Jens (Hypertension, 2013)
High dietary salt intake is associated with hypertension; the prevalence of salt-sensitive hypertension increases with age. We hypothesized that tissue Na might accumulate in hypertensive patients and that aging might be accompanied by Na deposition in tissue. We implemented Na magnetic resonance imaging to measure Na content of soft tissues in vivo earlier, but had not studied essential hypertension. We report on a cohort of 56 healthy control men and women, and 57 men and women with essential hypertension. The ages ranged from 22 to 90 years. Na magnetic resonance imaging measurements were made at the level of the calf. We observed age-dependent increases in Na content in muscle in men, whereas muscle Na content did not change with age in women. We estimated water content with conventional MRI and found no age-related increases in muscle water in men, despite remarkable Na accumulation, indicating water-free Na storage in muscle. With increasing age, there was Na deposition in the skin in both women and men; however, skin Na content remained lower in women. Similarly, this sex difference was found in skin water content, which was lower in women than in men. In contrast to muscle, increasing Na content was paralleled with increasing skin water content. When controlled for age, we found that patients with refractory hypertension had increased tissue Na content, compared with normotensive controls. These observations suggest that Na magnetic resonance imaging could have utility in assessing the role of tissue Na storage for cardiovascular morbidity and mortality in longitudinal studies. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: aging; gender difference; hypertension; salt; sodium MRI

23Na Magnetic Resonance Imaging of the Lower Leg of Acute Heart Failure Patients during Diuretic Treatment - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Garlichs, Christoph; Janka, Rolf Matthias; Luft, Friedrich C.; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (PLoS ONE, 2015)
Na+ can be stored in muscle and skin without commensurate water accumulation. The aim of this study was to assess Na+ and H2O in muscle and skin with MRI in acute heart failure patients before and after diuretic treatment and in a healthy cohort.Nine patients (mean age 78 years; range 58-87) and nine age and gender-matched controls were studied. They underwent 23Na/1H-MRI at the calf with a custom-made knee coil. Patients were studied before and after diuretic therapy. 23Na-MRI gray-scale measurements of Na+-phantoms served to quantify Na+-concentrations. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na+-levels did not change during therapy. Mean Na+-concentrations in muscle and skin decreased after furosemide therapy (before therapy: 30.7±6.4 and 43.5±14.5 mmol/L; after therapy: 24.2±6.1 and 32.2±12.0 mmol/L; p?0.05 and p?0.01). Water content measurements did not differ significantly before and after furosemide therapy in muscle (p = 0.17) and only tended to be reduced in skin (p = 0.06). Na+-concentrations in calf muscle and skin of patients before and after diuretic therapy were significantly higher than in healthy subjects (18.3±2.5 and 21.1±2.3 mmol/L).23Na-MRI shows accumulation of Na+ in muscle and skin in patients with acute heart failure. Diuretic treatment can mobilize this Na+-deposition; however, contrary to expectations, water and Na+-mobilization are poorly correlated.
EVALuna2:3828

3D hydrogel-based microcapsules as an in vitro model to study tumorigenicity, cell migration and drug resistance. - Ertekin, Özlem; Monavari, Mahshid; Krüger, René; Fuentes Chandia, Miguel Angel; Parma, Beatrice; Letort, Gaelle; Tripal, Philipp; Boccaccini, Aldo R.; Boßerhoff, Anja Katrin; Ceppi, Paolo; Kappelmann-Fenzl, Melanie; Leal-Egaña, Aldo (Acta Biomaterialia, 2022)
In this work, we analyzed the reliability of alginate-gelatin microcapsules as artificial tumor model. These tumor-like scaffolds are characterized by their composition and stiffness (∼25 kPa), and their capability to restrict -but not hinder- cell migration, proliferation and release from confinement. Hydrogel-based microcapsules were initially utilized to detect differences in mechano-sensitivity between MCF7 and MDA-MB-231 breast cancer cells, and the endothelial cell line EA.hy926. Additionally, we used RNA-seq and transcriptomic methods to determine how the culture strategy (i.e. 2D v/s 3D) may pre-set the expression of genes involved in multidrug resistance, being then validated by performing cytotoxicological tests and assays of cell morphology. Our results show that both breast cancer cells can generate elongated multicellular spheroids inside the microcapsules, prior being released (mimicking intravasation stages), a behavior which was not observed in endothelial cells. Further, we demonstrate that cells isolated from 3D scaffolds show resistance to cisplatin, a process which seems to be strongly influenced by mechanical stress, instead of hypoxia. We finally discuss the role played by aneuploidy in malignancy and resistance to anticancer drugs, based on the increased number of polynucleated cells found within these microcapsules. Overall, our outcomes demonstrate that alginate-gelatin microcapsules represent a simple, yet very accurate tumor-like model, enabling us to mimic the most relevant malignant hints described in vivo, suggesting that confinement and mechanical stress need to be considered when studying pathogenicity and drug resistance of cancer cells in vitro. STATEMENT OF SIGNIFICANCE: In this work, we analyzed the reliability of alginate-gelatin microcapsules as an artificial tumor model. These scaffolds are characterized by their composition, elastic properties, and their ability to restrict cell migration, proliferation, and release from confinement. Our results demonstrate four novel outcomes: (i) studying cell migration and proliferation in 3D enabled discrimination between malignant and non-pathogenic cells, (ii) studying the cell morphology of cancer aggregates entrapped in alginate-gelatin microcapsules enabled determination of malignancy degree in vitro, (iii) determination that confinement and mechanical stress, instead of hypoxia, are required to generate clones resistant to anticancer drugs (i.e. cisplatin), and (iv) evidence that resistance to anticancer drugs could be due to the presence of polynucleated cells localized inside polymer-based artificial tumors.

3D Spheroids Versus 3D Tumor-Like Microcapsules: Confinement and Mechanical Stress May Lead to the Expression of Malignant Responses in Cancer Cells - Fuentes-Chandía, Miguel; Vierling, Andreas; Kappelmann-Fenzl, Melanie; Monavari, Mahshid; Letort, Gaelle; Höne, Lucas; Parma, Beatrice; Antara, Sharmin Khan; Ertekin, Özlem; Palmisano, Ralf; Dong, Meng; Böpple, Kathrin; et al. (Advanced Biology, 2021)
As 2D surfaces fail to resemble the tumoral milieu, current discussions are focused on which 3D cell culture strategy may better lead the cells to express in vitro most of the malignant hints described in vivo. In this study, this question is assessed by analyzing the full genetic profile of MCF7 cells cultured either as 3D spheroids-considered as “gold standard” for in vitro cancer research- or immobilized in 3D tumor-like microcapsules, by RNA-Seq and transcriptomic methods, allowing to discriminate at big-data scale, which in vitro strategy can better resemble most of the malignant features described in neoplastic diseases. The results clearly show that mechanical stress, rather than 3D morphology only, stimulates most of the biological processes involved in cancer pathogenicity, such as cytoskeletal organization, migration, and stemness. Furthermore, cells entrapped in hydrogel-based scaffolds are likely expressing other physiological hints described in malignancy, such as the upregulated expression of metalloproteinases or the resistance to anticancer drugs, among others. According to the knowledge, this study represents the first attempt to answer which 3D experimental system can better mimic the neoplastic architecture in vitro, emphasizing the relevance of confinement in cancer pathogenicity, which can be easily achieved by using hydrogel-based matrices.
CRIS-Team Scopus Importer:2021-05-28
Keywords: 3D cancer models; 3D cell culture; biomaterials for cancer research; solid stress; tumor-like microcapsules

3 Tesla (23)Na magnetic resonance imaging during aerobic and anaerobic exercise - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Janka, Rolf Matthias; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (Academic Radiology, 2015)
The aim of the work described here was to determine the feasibility of monitoring Na(+) concentration and distribution in muscle/skin during aerobic/anaerobic exercise with (23)Na magnetic resonance imaging (MRI).The Na(+) concentration and water content of muscle/skin of the left lower leg of six healthy subjects (mean age, 26 years; range, 22-30 years; three men and three women) were assessed before and after aerobic/anaerobic cycle ergometry and during recovery with 3-T (23)Na/(1)H MRI. (23)Na MRI was performed with a custom-made knee coil. A gradient echo sequence with an acquisition time of 3.25 minutes, echo time of 2.07 ms, repetition time of 100 ms, and spatial resolution of 3 × 3 × 30 mm(3) was applied. Phantoms with increasing sodium concentration served for quantification via linear extrapolation. Blood values were determined by blood gas analysis.The concentration of Na(+) significantly increased during anaerobic exercise in all muscle compartments except the medial gastrocnemius muscle, whereas no significant change was observed in most muscle compartments during aerobic exercise (only the soleus muscle exhibited a significant increase in Na(+) concentration during aerobic exercise: 1.6 ± 1.5 mmol/kg, 4.5%, P = .046). During anaerobic exercise, the mean Na(+) concentration of the triceps surae and the whole leg increased by 9.0% (3.1 ± 2.1 mmol/kg, P = .016) and 6.5% (2.2 ± 1.3 mmol/kg, P < .01). MRI revealed a water-independent increase in Na(+) concentration in most muscle compartments during anaerobic exercise. Na(+) concentration significantly decreased during recovery after anaerobic and aerobic exercise in all muscle compartments except the soleus. The Na(+) concentration of the skin did not significantly change during anaerobic/aerobic exercise.Sodium(23) MRI allows reliable and noninvasive visualization and quantification of Na(+) concentration and distribution in muscle and skin during exercise. (23)Na MRI can be used to gain new insights into Na(+) homeostasis, presumably leading to better comprehension of pathophysiology.
EVALuna2:3827

Acidification is an essential process of cold atmospheric plasma and promotes the anti-cancer effect on malignant melanoma cells - Schneider, Christin; Gebhardt, Lisa; Arndt, Stephanie; Karrer, Sigrid; Zimmermann, Julia L.; Fischer, Michael; Boßerhoff, Anja Katrin (Cancers, 2019)
(1) Background: Cold atmospheric plasma (CAP) is ionized gas near room temperature. The anti-cancer effects of CAP were confirmed for several cancer types and were attributed to CAP-induced reactive species. However, the mode of action of CAP is still not well understood. (2) Methods: Changes in cytoplasmic Ca2+ level after CAP treatment of malignant melanoma cells were analyzed via the intracellular Ca2+ indicator fura-2 AM. CAP-produced reactive species were determined by fluorescence spectroscopic and protein nitration by Western Blot analysis. (3) Results: CAP caused a strong acidification of water and solutions that were buffered with the so-called Good buffers, while phosphate-buffered solutions with higher buffer capacity showed minor pH reductions. The CAP-induced Ca2+ influx in melanoma cells was stronger in acidic pH than in physiological conditions. NO formation that is induced by CAP was dose-and pH-dependent and CAP-treated solutions only caused protein nitration in cells under acidic conditions. (4) Conclusions: We describe the impact of CAP-induced acidification on the anti-cancer effects of CAP. A synergistic effect of CAP-induced ROS, RNS, and acidic conditions affected the intracellular Ca2+ level of melanoma cells. As the microenvironment of tumors is often acidic, further acidification might be one reason for the specific anti-cancer effects of CAP.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Acidification; Calcium signaling; Cold atmospheric plasma; Malignant melanoma; Nitration

Adult hippocampal neurogenesis in Parkinson's disease: impact on neuronal survival and plasticity - Regensburger, Martin; Prots, Iryna; Winner, Beate (Neural Plasticity, 2014)
In Parkinson's disease (PD) and other synucleinopathies, chronic neurodegeneration occurs within different areas of the central nervous system leading to progressive motor and nonmotor symptoms. The symptomatic treatment options that are currently available do not slow or halt disease progression. This highlights the need of a better understanding of disease mechanisms and disease models. The generation of newborn neurons in the adult hippocampus and in the subventricular zone/olfactory bulb system is affected by many different regulators and possibly involved in memory processing, depression, and olfaction, symptoms which commonly occur in PD. The pathology of the adult neurogenic niches in human PD patients is still mostly elusive, but different preclinical models have shown profound alterations of adult neurogenesis. Alterations in stem cell proliferation, differentiation, and survival as well as neurite outgrowth and spine formation have been related to different aspects in PD pathogenesis. Therefore, neurogenesis in the adult brain provides an ideal model to study disease mechanisms and compounds. In addition, adult newborn neurons have been proposed as a source of endogenous repair. Herein, we review current knowledge about the adult neurogenic niches in PD and highlight areas of future research.
EVALuna2:26222

Age- and Sex-Dependent Changes of Intra-articular Cortical and Trabecular Bone Structure and the Effects of Rheumatoid Arthritis - Simon, David; Kleyer, Arnd; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Hueber, Axel; Haschka, Judith; Renner, Nina; Figueiredo, Camille; Neuhuber, Winfried; Buder, Thomas; Englbrecht, Matthias; et al. (Journal of Bone and Mineral Research, 2016)
The objective of this cross-sectional study was to define normal sex- and age-dependent values of intra-articular bone mass and microstructures in the metacarpal heads of healthy individuals by high-resolution peripheral quantitative computed tomography (HR-pQCT) and test the effect of rheumatoid arthritis (RA) on these parameters. Human cadaveric metacarpal heads were used to exactly define intra-articular bone. Healthy individuals of different sex and age categories and RA patients with similar age and sex distribution received HR-pQCT scans of the second metacarpal head and the radius. Total, cortical, and trabecular bone densities as well as microstructural parameters were compared between 1) the different ages and sexes in healthy individuals; 2) between metacarpal heads and the radius; and 3) between healthy individuals and RA patients. The cadaveric study allowed exact definition of the intra-articular (intracapsular) bone margins. These data were applied in measuring intra-articular and radial bone parameters in 214 women and men (108 healthy individuals, 106 RA patients). Correlations between intra-articular and radial bone parameters were good (r = 0.51 to 0.62, p < 0.001). In contrast to radial bone, intra-articular bone remained stable until age 60 years (between 297 and 312 mg HA/cm(3) ) but decreased significantly (p < 0.001) in women thereafter (237.5 ± 44.3) with loss of both cortical and trabecular bone. Similarly, RA patients showed significant (p < 0.001) loss of intra-articular total (263.0 ± 44.8), trabecular (171.2 ± 35.6), and cortical bone (610.2 ± 62.0) compared with sex- and age-adjusted controls. Standard sex- and age-dependent values for physiological intra-articular bone were defined. Postmenopausal state and RA led to significant decrease of intra-articular bone. © 2016 American Society for Bone and Mineral Research.
EVALuna:33251

Agonistic Autoantibodies to the β2-Adrenergic Receptor Involved in the Pathogenesis of Open-Angle Glaucoma - Juenemann, Anselm; Hohberger, Bettina; Rech, Jürgen; Sheriff, Ahmed; Fu, Qin; Schlötzer-Schrehardt, Ursula; Voll, Reinhard Edmund; Bartel, Sabine; Kalbacher, Hubert; Hoebeke, Johan; Rejdak, Robert; Horn, Folkert; et al. (Frontiers in Immunology, 2018)
Glaucoma is a frequent ocular disease that may lead to blindness. Primary open-angle glaucoma (POAG) and ocular hypertension (OHT) are common diseases with increased intraocular pressure (IOP), which are mainly responsible for these disorders. Their pathogenesis is widely unknown. We screened the sera of patients with POAG and OHT for the prevalence of autoantibodies (AAb) against G protein-coupled receptors (GPCRs) in comparison to controls. Employing frequency modulation of spontaneously contracting neonatal rat cardiomyocytes in vitro, agonistic GPCR AAb were to be detected in roughly 75% of the patients with POAG and OHT, however, not in controls. Using inhibitory peptides the AAb' target was identified as β2 adrenergic receptor (β2AR). The AAb interact with the second extracellular loop of β2AR. The peptides 181-187 and 186-192 were identified as binding sites of the AAb within the extracellular loop II. The binding of the AAb to β2ARs was verified by surface-plasmon-resonance analysis. The isotype of the AAb was (immunoglobulin) IgG3. In an additional pilot principal-of-proof study, including four patients with POAG, the removal of the AAb against the β2AR and other immunoglobulins G by immunoadsorption resulted in a transient reduction of IOP. These findings might indicate a possible role of agonistic AAb directed against β2ARs in the dynamics of aqueous humor and might support a contribution of adaptive autoimmunity in the etiopathogenesis of POAG and OHT.
EVALuna2:33846

Agreement Between 24-Hour Salt Ingestion and Sodium Excretion in a Controlled Environment - Lerchl, Kathrin; Rakova, Natalia; Dahlmann, Anke; Rauh, Manfred; Goller, Ulrike; Basner, Mathias; Dinges, David F.; Beck, Luis; Agureev, Alexander; Larina, Irina; Baranov, Victor; Morukov, Boris; et al. (Hypertension, 2015)
Accurately collected 24-hour urine collections are presumed to be valid for estimating salt intake in individuals. We performed 2 independent ultralong-term salt balance studies lasting 105 (4 men) and 205 (6 men) days in 10 men simulating a flight to Mars. We controlled dietary intake of all constituents for months at salt intakes of 12, 9, and 6 g/d and collected all urine. The subjects' daily menus consisted of 27 279 individual servings, of which 83.0% were completely consumed, 16.5% completely rejected, and 0.5% incompletely consumed. Urinary recovery of dietary salt was 92% of recorded intake, indicating long-term steady-state sodium balance in both studies. Even at fixed salt intake, 24-hour urine collection for sodium excretion (UNaV) showed infradian rhythmicity. We defined a ±25 mmol deviation from the average difference between recorded sodium intake and UNaV as the prediction interval to accurately classify a 3-g difference in salt intake. Because of the biological variability in UNaV, only every other daily urine sample correctly classified a 3-g difference in salt intake (49%). By increasing the observations to 3 consecutive 24-hour collections and sodium intakes, classification accuracy improved to 75%. Collecting seven 24-hour urines and sodium intake samples improved classification accuracy to 92%. We conclude that single 24-hour urine collections at intakes ranging from 6 to 12 g salt per day were not suitable to detect a 3-g difference in individual salt intake. Repeated measurements of 24-hour UNaV improve precision. This knowledge could be relevant to patient care and the conduct of intervention trials.
EVALuna2:3790

Alpha-synuclein activates BV2 microglia dependent on its aggregation state - Hoffmann, Alana; Ettle, Benjamin; Bruno, Ariane; Kulinich, Anna; Hoffmann, Anna-Carin; von Wittgenstein, Julia; Winkler, Jürgen; Xiang, Wei; Schlachetzki, Johannes (Biochemical and Biophysical Research Communications, 2016)
Synucleinopathies such as Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA) are defined by the presence of intracellular alpha-synuclein aggregates in neurons and/or oligodendrocytes. In addition, post mortem tissue analysis revealed profound changes in microglial morphology, indicating microglial activation and neuroinflammation. Thus, alpha-synuclein may directly activate microglia, leading to increased production of key pro-inflammatory cytokines like tumor necrosis factor-alpha (TNF-?) and interleukin-1beta (IL-1?), which in turn modulates the disease progression. The distinct alpha-synuclein species, which mediates the activation of microglia, is not well defined. We hypothesized that microglial activation depends on a specific aggregation state of alpha-synuclein. Here, we show that primarily human fibrillar alpha-synuclein increased the production and secretion of pro-inflammatory cytokines by microglial BV2 cells compared to monomeric and oligomeric alpha-synuclein. BV2 cells also preferentially phagocytosed fibrillar alpha-synuclein compared to alpha-synuclein monomers and oligomers. Microglial uptake of alpha-synuclein fibrils and the consequent activation were time- and concentration-dependent. Moreover, the degree of fibrillization determined the efficiency of microglial internalization. Taken together, our study highlights the specific crosstalk of distinct alpha-synuclein species with microglial cells.
EVALuna2:4715

Analysis of continuous neuronal activity evoked by natural speech with computational corpus linguistics methods - Schilling, Achim; Tomasello, Rosario; Henningsen-Schomers, Malte R.; Zankl, Alexandra; Surendra, Kishore; Haller, Martin; Karl, Valerie; Uhrig, Peter; Maier, Andreas; Krauß, Patrick (Language, Cognition and Neuroscience, 2020)
In the field of neurobiology of language, neuroimaging studies are generally based on stimulation paradigms consisting of at least two different conditions. Designing those paradigms can be very time-consuming and this traditional approach is necessarily data-limited. In contrast, in computational and corpus linguistics, analyses are often based on large text corpora, which allow a vast variety of hypotheses to be tested by repeatedly re-evaluating the data set. Furthermore, text corpora also allow exploratory data analysis in order to generate new hypotheses. By drawing on the advantages of both fields, neuroimaging and computational corpus linguistics, we here present a unified approach combining continuous natural speech and MEG to generate a corpus of speech-evoked neuronal activity.
CRIS-Team Scopus Importer:2020-08-21
Keywords: computational corpus linguistics; MEG/EEG; natural language processing (NLP); naturalistic continuous speech stimuli; neurobiology of language

A non-proliferative role of pyrimidine metabolism in cancer - Siddiqui, Aarif; Ceppi, Paolo (Molecular Metabolism, 2020)
Background: Nucleotide metabolism is a critical pathway that generates purine and pyrimidine molecules for DNA replication, RNA synthesis, and cellular bioenergetics. Increased nucleotide metabolism supports uncontrolled growth of tumors and is a hallmark of cancer. Agents inhibiting synthesis and incorporation of nucleotides in DNA are widely used as chemotherapeutics to reduce tumor growth, cause DNA damage, and induce cell death. Thus, the research on nucleotide metabolism in cancer is primarily focused on its role in cell proliferation. However, in addition to proliferation, the role of purine molecules is established as ligands for purinergic signals. However, so far, the role of the pyrimidines has not been discussed beyond cell growth. Scope of the review: In this review we present the key evidence from recent pivotal studies supporting the notion of a non-proliferative role for pyrimidine metabolism (PyM) in cancer, with a special focus on its effect on differentiation in cancers from different origins. Major conclusion: In leukemic cells, the pyrimidine catabolism induces terminal differentiation toward monocytic lineage to check the aberrant cell proliferation, whereas in some solid tumors (e.g., triple negative breast cancer and hepatocellular carcinoma), catalytic degradation of pyrimidines maintains the mesenchymal-like state driven by epithelial-to-mesenchymal transition (EMT). This review further broadens this concept to understand the effect of PyM on metastasis and, ultimately, delivers a rationale to investigate the involvement of the pyrimidine molecules as oncometabolites. Overall, understanding the non-proliferative role of PyM in cancer will lead to improvement of the existing antimetabolites and to development of new therapeutic options.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Cancer; Chemoresistance; Epithelial-to-mesenchymal transition; Pyrimidine metabolism

Antigen delivery to CD11c+CD8- dendritic cells induces protective immune responses against experimental melanoma in mice in vivo - Neubert, Kirsten; Lehmann, Christian; Heger, Lukas; Baranska, Anna; Staedtler, Anna Maria; Buchholz, Veit R.; Yamazaki, Sayuri; Heidkamp, Gordon Frederik; Eissing, Nathalie; Zebroski, Henry; Nussenzweig, Michel C.; Nimmerjahn, Falk; et al. (Journal of Immunology, 2014)
Dendritic cells (DCs) are central modulators of immune responses and, therefore, interesting target cells for the induction of antitumor immune responses. Ag delivery to select DC subpopulations via targeting Abs to DC inhibitory receptor 2 (DCIR2, clone 33D1) or to DEC205 was shown to direct Ags specifically to CD11c(+)CD8(-) or CD11c(+)CD8(+) DCs, respectively, in vivo. In contrast to the increasing knowledge about the induction of immune responses by efficiently cross-presenting CD11c(+)CD8(+) DCs, little is known about the functional role of Ag-presenting CD11c(+)CD8(-) DCs with regard to the initiation of protective immune responses. In this study, we demonstrate that Ag targeting to the CD11c(+)CD8(-) DC subpopulation in the presence of stimulating anti-CD40 Ab and TLR3 ligand polyinosinic-polycytidylic acid induces protective responses against rapidly growing tumor cells in naive animals under preventive and therapeutic treatment regimens in vivo. Of note, this immunization protocol induced a mixed Th1/Th2-driven immune response, irrespective of which DC subpopulation initially presented the Ag. Our results provide important information about the role of CD11c(+)CD8(-) DCs, which have been considered to be less efficient at cross-presenting Ags, in the induction of protective antitumor immune responses.
EVALuna2:19490

Apparent Diffusion Coefficient (ADC) Histogram Analysis in Parotid Gland Tumors: Evaluating a Novel Approach for Differentiation between Benign and Malignant Parotid Lesions Based on Full Histogram Distributions. - Hepp, Tobias; Wüst, Wolfgang; Heiß, Rafael; May, Matthias; Kopp, Markus; Wetzl, Matthias; Treutlein, Christoph; Uder, Michael; Wiesmüller, Marco (Diagnostics, 2022)
The aim of this study was to assess the diagnostic value of ADC distribution curves for differentiation between benign and malignant parotid gland tumors and to compare with mean ADC values. 73 patients with parotid gland tumors underwent head-and-neck MRI on a 1.5 Tesla scanner prior to surgery and histograms of ADC values were extracted. Histopathological results served as a reference standard for further analysis. ADC histograms were evaluated by comparing their similarity to a reference distribution using Chi2-test-statistics. The assumed reference distribution for benign and malignant parotid gland lesions was calculated after pooling the entire ADC data. In addition, mean ADC values were determined. For both methods, we calculated and compared the sensitivity and specificity between benign and malignant parotid gland tumors and three subgroups (pleomorphic adenoma, Warthin tumor, and malignant lesions), respectively. Moreover, we performed cross-validation (CV) techniques to estimate the predictive performance between ADC distributions and mean values. Histopathological results revealed 30 pleomorphic adenomas, 22 Warthin tumors, and 21 malignant tumors. ADC histogram distribution yielded a better specificity for detection of benign parotid gland lesions (ADChistogram: 75.0% vs. ADCmean: 71.2%), but mean ADC values provided a higher sensitivity (ADCmean: 71.4% vs. ADChistogram: 61.9%). The discrepancies are most pronounced in the differentiation between malignant and Warthin tumors (sensitivity ADCmean: 76.2% vs. ADChistogram: 61.9%; specificity ADChistogram: 81.8% vs. ADCmean: 68.2%). Using CV techniques, ADC distribution revealed consistently better accuracy to differentiate benign from malignant lesions ("leave-one-out CV" accuracy ADChistogram: 71.2% vs. ADCmean: 67.1%). ADC histogram analysis using full distribution curves is a promising new approach for differentiation between primary benign and malignant parotid gland tumors, especially with respect to the advantage in predictive performance based on CV techniques.
EVALuna2:506315

Approaches to Regularized Regression - A Comparison between Gradient Boosting and the Lasso - Hepp, Tobias; Schmid, Matthias; Gefeller, Olaf; Waldmann, Elisabeth; Mayr, Andreas (Methods of Information in Medicine, 2016)
Penalization and regularization techniques for statistical modeling have attracted increasing attention in biomedical research due to their advantages in the presence of high-dimensional data. A special focus lies on algorithms that incorporate automatic variable selection like the least absolute shrinkage operator (lasso) or statistical boosting techniques.Focusing on the linear regression framework, this article compares the two most-common techniques for this task, the lasso and gradient boosting, both from a methodological and a practical perspective.We describe these methods highlighting under which circumstances their results will coincide in low-dimensional settings. In addition, we carry out extensive simulation studies comparing the performance in settings with more predictors than observations and investigate multiple combinations of noise-to-signal ratio and number of true non-zero coeffcients. Finally, we examine the impact of different tuning methods on the results.Both methods carry out penalization and variable selection for possibly highdimensional data, often resulting in very similar models. An advantage of the lasso is its faster run-time, a strength of the boosting concept is its modular nature, making it easy to extend to other regression settings.Although following different strategies with respect to optimization and regularization, both methods imply similar constraints to the estimation problem leading to a comparable performance regarding prediction accuracy and variable selection in practice.
EVALuna2:5566

A Single-Molecule View on Cellular and Viral RNA Synthesis - Ostrofet, Eugeniu; Papini, Flavia Stal; Malinen, Anssi M.; Dulin, David (Biophysics of RNA-Protein Interactions, 2019)
RNA synthesis is at the heart of gene expression, the RNA products serving in cellular organisms as protein blueprints, structural/functional components of molecular machines or regulators of gene expression, and as the genetic material of nascent RNA viruses. Because of its importance, transcription—the process converting DNA to RNA—has been extensively studied at the single-molecule level; first in bacterial systems and quickly after in other domains of life. RNA replication in RNA viruses has recently become an important research topic in the single-molecule field, aiming not only to uncover its versatile mechanisms but also to develop new therapeutics against these devastating human pathogens. Here, we summarize the recent advances in cellular and viral RNA production using in vitro single-molecule techniques.<br
CRIS-Team WoS Importer:2020-07-17
Keywords: Single-molecule biophysics; Transcription; RNA virus; RNA replication; Cellular RNA polymerases; Viral RNA-dependent RNA polymerases; Optical tweezers; Magnetic tweezers; Fluorescence resonance energy transfer

Author Correction: Correction-free force calibration for magnetic tweezers experiments - Ostrofet, Eugeniu; Papini, Flavia Stal; Dulin, David (Scientific Reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.
EVALuna2:35236

Balancing wobbles in the body sodium - Titze, Jens; Rakova, Natalia; Kopp, Christoph; Dahlmann, Anke; Jantsch, Jonathan; Luft, Friedrich C. (Nephrology Dialysis Transplantation, 2016)
Sodium balance is achieved within a matter of days and everything that enters should come out; sodium stores are of questionable relevance and sodium accumulation is accompanied by weight gain. Careful balance studies oftentimes conflicted with this view, and long-term studies suggested that total body sodium (TBNa) fluctuates independent of intake or body weight. We recently performed the opposite experiment in that we fixed sodium intake for weeks at three levels of sodium intake and collected all urine made. We found weekly (circaseptan) patterns in sodium excretion that were inversely related to aldosterone and directly related to cortisol. TBNa was not dependent on sodium intake, but instead exhibited far longer (greater than or equal to monthly) infradian rhythms independent of extracellular water, body weight or blood pressure. To discern the mechanisms further, we delved into sodium magnetic resonance imaging (Na-MRI) to identify sodium storage clinically. We found that sodium stores are greater in men than in women, increase with age and are higher in hypertensive than normotensive persons. We have suggestive evidence that these sodium stores can be mobilized, also in dialysis patients. The observations are in accordance with our findings that immune cells regulate a hypertonic interface in the skin interstitium that could serve as a protective barrier. Returning to our balance studies, we found that due to biological variability in 24-h sodium excretion, collecting urine for a day could not separate 12, 9 or 6 g/day sodium intakes with the precision of tossing a coin. Every other daily urine sampling correctly classified a 3-g difference in salt intake less than half the time, making the gold standard 24-h urine collection of little value in predicting salt intake. We suggest that wobbles in expected outcomes can lead to novel clinical insights even with respect to banal salt questions.
EVALuna2:3836

Bile salt subspecies activate MRGX4 expressed on sensory neurons and cause itching in humans - Wolf, Katharina; Kühn, Helen; Leibl, Victoria; Gebhardt, Lisa; Glaudo, Markus; Reeh, Peter; Fischer, Michael J. M.; Neurath, Markus; Namer, Barbara; Kremer, Andreas (HEPATOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-25

Characterization and diagnostic application of genomic NPM-ALK fusion sequences in anaplastic large-cell lymphoma - Krumbholz, Manuela; Woessmann, Wilhelm; Zierk, Jakob; Seniuk, David; Ceppi, Paolo; Zimmermann, Martin; Singh, Vijay Kumar; Metzler, Markus; Damm-Welk, Christine (Oncotarget, 2018)
Nucleophosmin-anaplastic lymphoma kinase (NPM-ALK) fusion genes resulting from the translocation t(2;5)(p23;q35) are present in almost 90% of childhood ALK-positive anaplastic large-cell lymphomas (ALCL). Detection and quantification of minimal disseminated disease (MDD) by measuring NPM-ALK fusion transcript levels in the blood provide independent prognostic parameters. Characterization of the genomic breakpoints provides insights into the pathogenesis of the translocation and allows for DNA-based minimal disease monitoring. We designed a nested multiplex PCR assay for identification and characterization of genomic NPM-ALK fusion sequences in 45 pediatric ALCL-patients, and used the sequences for quantitative MDD monitoring. Breakpoint analysis indicates the involvement of inaccurate non-homologous end joining repair mechanisms in the formation of NPM-ALK fusions. Parallel quantification of RNA and DNA levels in the cellular fraction of 45 blood samples from eight patients with NPM-ALK-positive ALCL correlated, as did cell-free circulating NPM-ALK DNA copies in the plasma fraction of 37 blood samples. With genomic NPM-ALK fusion sequence quantification, plasma samples of ALCL patients become an additional source for MRD-assessment. Parallel quantification of NPM-ALK transcripts and fusion genes in ALCL cell lines treated with the ALK kinase inhibitor crizotinib illustrates the potential value of supplementary DNA-based quantification in particular clinical settings.
EVALuna2:34643

Cold atmospheric plasma causes a calcium influx in melanoma cells triggering CAP-induced senescence - Schneider, Christin; Gebhardt, Lisa; Arndt, Stephanie; Karrer, Sigrid; Zimmermann, Julia L.; Fischer, Michael; Boßerhoff, Anja Katrin (Scientific Reports, 2018)
Cold atmospheric plasma (CAP) is a promising approach in anti-cancer therapy, eliminating cancer cells with high selectivity. However, the molecular mechanisms of CAP action are poorly understood. In this study, we investigated CAP effects on calcium homeostasis in melanoma cells. We observed increased cytoplasmic calcium after CAP treatment, which also occurred in the absence of extracellular calcium, indicating the majority of the calcium increase originates from intracellular stores. Application of previously CAP-exposed extracellular solutions also induced cytoplasmic calcium elevations. A substantial fraction of this effect remained when the application was delayed for one hour, indicating the chemical stability of the activating agent(s). Addition of ryanodine and cyclosporin A indicate the involvement of the endoplasmatic reticulum and the mitochondria. Inhibition of the cytoplasmic calcium elevation by the intracellular chelator BAPTA blocked CAP-induced senescence. This finding helps to understand the molecular influence and the mode of action of CAP on tumor cells.
EVALuna2:185219

Complex reinnervation pattern after unilateral renal denervation in rats - Rodionova, Kristina; Fiedler, Christian; Günther, Franziska; Grouzmann, Eric; Neuhuber, Winfried; Fischer, Michael; Ott, Christian; Linz, Peter; Freisinger, Wolfgang; Heinlein, Sonja; Schmidt, Stefan; Schmieder, Roland; et al. (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2016)
Renal denervation (DNX) is a treatment for resistant arterial hypertension. Efferent sympathetic nerves regrow, but reinnervation by renal afferent nerves has only recently been shown in the renal pelvis of rats after unilateral DNX. We examined intrarenal perivascular afferent and sympathetic efferent nerves after unilateral surgical DNX. Tyrosine hydroxylase (TH), CGRP, and smooth muscle actin were identified in kidney sections from 12 Sprague-Dawley rats, to distinguish afferents, efferents, and vasculature. DNX kidneys and nondenervated kidneys were examined 1, 4, and 12 wk after DNX. Tissue levels of CGRP and norepinephrine (NE) were measured with ELISA and mass spectrometry, respectively. DNX decreased TH and CGRP labeling by 90% and 95%, respectively (P < 0.05) within 1 wk. After 12 wk TH and CGRP labeling returned to baseline with a shift toward afferent innervation (P < 0.05). Nondenervated kidneys showed a doubling of both labels within 12 wk (P < 0.05). CGRP content decreased by 72% [3.2 ± 0.3 vs. 0.9 ± 0.2 ng/gkidney; P < 0.05] and NA by 78% [1.1 ± 0.1 vs. 0.2 ± 0.1 pmol/mgkidney; P < 0.05] 1 wk after DNX. After 12 wk, CGRP, but not NE, content in DNX kidneys was fully recovered, with no changes in the nondenervated kidneys. The use of phenol in the DNX procedure did not influence this result. We found morphological reinnervation and transmitter recovery of afferents within 12 wk after DNX. Despite morphological evidence of sympathetic regrowth, NE content did not fully recover. These results suggest a long-term net surplus of afferent influence on the DNX kidney may be contributing to the blood pressure lowering effect of DNX.
EVALuna2:3840

Contractility measurements for cardiotoxicity screening with ventricular myocardial slices of pigs - Shi, Runzhu; Reichardt, Marius; Fiegle, Dominik; Küpfer, Linda; Czajka, Titus; Sun, Zhengwu; Salditt, Tim; Dendorfer, Andreas; Seidel, Thomas; Bruegmann, Tobias (Cardiovascular Research, 2023)
Aims Cardiotoxicity is one major reason why drugs do not enter or are withdrawn from the market. Thus, approaches are required to predict cardiotoxicity with high specificity and sensitivity. Ideally, such methods should be performed within intact cardiac tissue with high relevance for humans and detect acute and chronic side effects on electrophysiological behaviour, contractility, and tissue structure in an unbiased manner. Herein, we evaluate healthy pig myocardial slices and biomimetic cultivation setups (BMCS) as a new cardiotoxicity screening approach. Methods and results Pig left ventricular samples were cut into slices and spanned into BMCS with continuous electrical pacing and online force recording. Automated stimulation protocols were established to determine the force-frequency relationship (FFR), frequency dependence of contraction duration, effective refractory period (ERP), and pacing threshold. Slices generated 1.3 ± 0.14 mN/mm2 force at 0.5 Hz electrical pacing and showed a positive FFR and a shortening of contraction duration with increasing pacing rates. Approximately 62% of slices were able to contract for at least 6 days while showing stable ERP, contraction duration-frequency relationship, and preserved cardiac structure confirmed by confocal imaging and X-ray diffraction analysis. We used specific blockers of the most important cardiac ion channels to determine which analysis parameters are influenced. To validate our approach, we tested five drug candidates selected from the Comprehensive in vitro Proarrhythmia Assay list as well as acetylsalicylic acid and DMSO as controls in a blinded manner in three independent laboratories. We were able to detect all arrhythmic drugs and their respective mode of action on cardiac tissue including inhibition of Na+, Ca2+, and hERG channels as well as Na+/Ca2+ exchanger. Conclusion We systematically evaluate this approach for cardiotoxicity screening, which is of high relevance for humans and can be upscaled to medium-throughput screening. Thus, our approach will improve the predictive value and efficiency of preclinical cardiotoxicity screening.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Cardiac arrhythmia; Cardiotoxicity; Drug-induced long QT syndrome; Screening; Ventricular slices

Correction-free force calibration for magnetic tweezers experiments - Ostrofet, Eugeniu; Papini, Flavia Stal; Dulin, David (Scientific Reports, 2018)
Magnetic tweezers are a powerful technique to perform high-throughput and high-resolution force spectroscopy experiments at the single-molecule level. The camera-based detection of magnetic tweezers enables the observation of hundreds of magnetic beads in parallel, and therefore the characterization of the mechanochemical behavior of hundreds of nucleic acids and enzymes. However, magnetic tweezers experiments require an accurate force calibration to extract quantitative data, which is limited to low forces if the deleterious effect of the finite camera open shutter time (τsh) is not corrected. Here, we provide a simple method to perform correction-free force calibration for high-throughput magnetic tweezers at low image acquisition frequency (fac). By significantly reducing τsh to at least 4-fold the characteristic times of the tethered magnetic bead, we accurately evaluated the variance of the magnetic bead position along the axis parallel to the magnetic field, estimating the force with a relative error of 10% (standard deviation), being only limited by the bead-to-bead difference. We calibrated several magnets - magnetic beads configurations, covering a force range from 50 fN to 60 pN. In addition, for the presented configurations, we provide a table with the mathematical expressions that describe the force as a function of the magnets position.
EVALuna2:35237

Correction to: Consecutive-Day Ventricular and Atrial Cardiomyocyte Isolations from the Same Heart: Shifting the Cost–Benefit Balance of Cardiac Primary Cell Research (Cells, (2022), 11, 2, (233), 10.3390/cells11020233) - Greiner, Joachim; Schiatti, Teresa; Kaltenbacher, Wenzel; Dente, Marica; Semenjakin, Alina; Kok, Thomas; Fiegle, Dominik; Seidel, Thomas; Ravens, Ursula; Kohl, Peter; Peyronnet, Rémi; Rog-Zielinska, Eva A. (Cells, 2024)
In the original publication [1], there was an error in the Materials and Methods Section, Sub-Section 2.3. Cell Isolation. The concentration of the digestion solution was wrong. The correct concentration appears below. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated. Tissue was then rinsed twice in wash solution 1 (each 2 mL), and further digested with Liberase TL Research Grade (concentration: 0.23 mg/mL in 2.2 mL wash solution 1 supplemented with 5 µM CaCl2; Hoffmann-La Roche, Basel, Switzerland) for up to 45 min (ventricles)/15 min (atria).
CRIS-Team Scopus Importer:2024-07-12

Corrigendum to "Probing for Sparse and Fast Variable Selection with Model-Based Boosting" - Thomas, Janek; Hepp, Tobias; Mayr, Andreas; Bischl, Bernd (Computational and Mathematical Methods in Medicine, 2018)
[This corrects the article DOI: 10.1155/2017/1421409.].
EVALuna2:35692

CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome - Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Wiesmann da Silva Reis, André; Lie, Dieter Chichung; Winner, Beate; Turan, Sören (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B(+/-) hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B(+/-) hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.

Deep Brain Stimulation, Stereotactic Radiosurgery and High-Intensity Focused Ultrasound Targeting the Limbic Pain Matrix: A Comprehensive Review - Nüssel, Martin; Zhao, Yining; Knorr, Constantin; Regensburger, Martin; Stadlbauer, Andreas; Buchfelder, Michael; Del Vecchio, Alessandro; Kinfe, Thomas Mehari (Pain and Therapy, 2022)
Chronic pain (CP) represents a socio-economic burden for affected patients along with therapeutic challenges for currently available therapies. When conventional therapies fail, modulation of the affective pain matrix using reversible deep brain stimulation (DBS) or targeted irreversible thalamotomy by stereotactic radiosurgery (SRS) and magnetic resonance (MR)-guided focused ultrasound (MRgFUS) appear to be considerable treatment options. We performed a literature search for clinical trials targeting the affective pain circuits (thalamus, anterior cingulate cortex [ACC], ventral striatum [VS]/internal capsule [IC]). PubMed, Ovid, MEDLINE and Scopus were searched (1990-2021) using the terms "chronic pain", "deep brain stimulation", "stereotactic radiosurgery", "radioneuromodulation", "MR-guided focused ultrasound", "affective pain modulation", "pain attention". In patients with CP treated with DBS, SRS or MRgFUS the somatosensory thalamus and periventricular/periaquaeductal grey was the target of choice in most treated subjects, while affective pain transmission was targeted in a considerably lower number (DBS, SRS) consisting of the following nodi of the limbic pain matrix: the anterior cingulate cortex; centromedian-parafascicularis of the thalamus, pars posterior of the central lateral nucleus and internal capsule/ventral striatum. Although DBS, SRS and MRgFUS promoted a meaningful and sustained pain relief, an effective, evidence-based comparative analysis is biased by heterogeneity of the observation period varying between 3 months and 5 years with different stimulation patterns (monopolar/bipolar contact configuration; frequency 10-130 Hz; intensity 0.8-5 V; amplitude 90-330 mu s), source and occurrence of lesioning (radiation versus ultrasound) and chronic pain ethology (poststroke pain, plexus injury, facial pain, phantom limb pain, back pain). The advancement of neurotherapeutics (MRgFUS) and novel DBS targets (ACC, IC/VS), along with established and effective stereotactic therapies (DBS-SRS), increases therapeutic options to impact CP by modulating affective, pain-attentional neural transmission. Differences in trial concept, outcome measures, targets and applied technique promote conflicting findings and limited evidence. Hence, we advocate to raise awareness of the potential therapeutic usefulness of each approach covering their advantages and disadvantages, including such parameters as invasiveness, risk-benefit ratio, reversibility and responsiveness.
CRIS-Team WoS Importer:2022-05-13
Keywords: Limbic pain network; Deep brain stimulation; Magnetic resonance-guided focussed ultrasound; Stereotactic radiosurgery; Centromedian-parafascicular; Ventral striatum/anterior limb of the internal capsule; Anterior cingulate cortex; Central lateral nucleus of the thalamus; Chronic pain

Defects in ER-endosome contacts impact lysosome function in hereditary spastic paraplegia - Allison, Rachel; Edgar, James R.; Pearson, Guy; Rizo, Tania; Newton, Timothy; Guenther, Sven; Berner, Fiamma; Hague, Jennifer; Connell, James W.; Winkler, Jürgen; Lippincott-Schwartz, Jennifer; Beetz, Christian; et al. (The Journal of Cell Biology, 2017)
Contacts between endosomes and the endoplasmic reticulum (ER) promote endosomal tubule fission, but the mechanisms involved and consequences of tubule fission failure are incompletely understood. We found that interaction between the microtubule-severing enzyme spastin and the ESCRT protein IST1 at ER-endosome contacts drives endosomal tubule fission. Failure of fission caused defective sorting of mannose 6-phosphate receptor, with consequently disrupted lysosomal enzyme trafficking and abnormal lysosomal morphology, including in mouse primary neurons and human stem cell-derived neurons. Consistent with a role for ER-mediated endosomal tubule fission in lysosome function, similar lysosomal abnormalities were seen in cellular models lacking the WASH complex component strumpellin or the ER morphogen REEP1. Mutations in spastin, strumpellin, or REEP1 cause hereditary spastic paraplegia (HSP), a disease characterized by axonal degeneration. Our results implicate failure of the ER-endosome contact process in axonopathy and suggest that coupling of ER-mediated endosomal tubule fission to lysosome function links different classes of HSP proteins, previously considered functionally distinct, into a unifying pathway for axonal degeneration.
EVALuna2:9354

Detection of Cellular Senescence in Human Primary Melanocytes and Malignant Melanoma Cells In Vitro - Zimmermann, Tom; Pommer, Michaela; Kluge, Viola; Chiheb, Chafia; Mühlich, Susanne; Boßerhoff, Anja Katrin (Cells, 2022)
Detection and quantification of senescent cells remain difficult due to variable phenotypes and the absence of highly specific and reliable biomarkers. It is therefore widely accepted to use a combination of multiple markers and cellular characteristics to define senescent cells in vitro. The exact choice of these markers is a subject of ongoing discussion and usually depends on objective reasons such as cell type and treatment conditions, as well as subjective considerations including feasibility and personal experience. This study aims to provide a comprehensive comparison of biomarkers and cellular characteristics used to detect senescence in melanocytic systems. Each marker was assessed in primary human melanocytes that overexpress mutant BRAFV600E, as it is commonly found in melanocytic nevi, and melanoma cells after treatment with the chemotherapeutic agent etoposide. The combined use of these two experimental settings is thought to allow profound conclusions on the choice of senescence biomarkers when working with melanocytic systems. Further, this study supports the development of standardized senescence detection and quantification by providing a comparative analysis that might also be helpful for other cell types and experimental conditions.
CRIS-Team Scopus Importer:2022-05-13
Keywords: beta-galactosidase; melanocyte; melanoma; senescence

Diagnostic Utility of Interleukin-6 in Early-Onset Sepsis among Term Newborns: Impact of Maternal Risk Factors and CRP Evaluation. - Schleier, Maria; Lubig, Julia; Kehl, Sven; Hébert, Steven; Wölfle, Joachim; van der Donk, Adriana; Bär, Alisa; Reutter, Heiko Martin; Hepp, Tobias; Morhart, Patrick (Children, 2023)
(1) Background: Interleukin-6 (IL-6) levels act as an early infection marker preceding C-reactive protein (CRP) elevation. This study seeks to analyze IL-6 behavior in suspected early-onset sepsis (EOS) cases among term newborns, comparing it to that of CRP and evaluating IL-6's diagnostic utility. We also aim to assess the impact of maternal risk factors on EOS in term newborns, quantifying their influence for informed decision making. (2) Methods: The retrospective data analysis included 533 term newborns who were admitted to our hospital because of suspected EOS. IL-6, CRP, and the impact of maternal risk factors were analyzed in the context of EOS using binomial test, Chi-squared test, logistic and linear regression. (3) Results: In the cases of EOS, both IL-6 and CRP were elevated. The increase in CRP can be predicted by the initial increase in IL-6 levels. Among the assessed risk factors, intrapartum maternal fever (adjusted odds ratio 18.1; 95% CI (1.7-4.1)) was identified as the only risk factor significantly associated with EOS. (4) Conclusions: Employing IL-6 as an early infection marker enhanced EOS diagnostic precision due to its detectable early rise. However, caution is required, as elevations in IL-6 and CRP levels do not exclusively indicate EOS. Increased CRP levels in healthy newborns with maternal risk factors may be attributed to dynamics of vaginal labor.
EVALuna2:549522

Differential requirement of bone morphogenetic protein receptors Ia (ALK3) and Ib (ALK6) in early embryonic patterning and neural crest development. - Schille, Carolin; Heller, Jens; Schambony, Alexandra (Bmc Developmental Biology, 2016)
BACKGROUND:Bone morphogenetic proteins regulate multiple processes in embryonic development, including early dorso-ventral patterning and neural crest development. BMPs activate heteromeric receptor complexes consisting of type I and type II receptor-serine/threonine kinases. BMP receptors Ia and Ib, also known as ALK3 and ALK6 respectively, are the most common type I receptors that likely mediate most BMP signaling events. Since early expression patterns and functions in Xenopus laevis development have not been described, we have addressed these questions in the present study.RESULTS:Here we have analyzed the temporal and spatial expression patterns of ALK3 and ALK6; we have also carried out loss-of-function studies to define the function of these receptors in early Xenopus development. We detected both redundant and non-redundant roles of ALK3 and ALK6 in dorso-ventral patterning. From late gastrula stages onwards, their expression patterns diverged, which correlated with a specific, non-redundant requirement of ALK6 in post-gastrula neural crest cells. ALK6 was essential for induction of neural crest cell fate and further development of the neural crest and its derivatives.CONCLUSIONS:ALK3 and ALK6 both contribute to the gene regulatory network that regulates dorso-ventral patterning; they play partially overlapping and partially non-redundant roles in this process. ALK3 and ALK6 are independently required for the spatially restricted activation of BMP signaling and msx2 upregulation at the neural plate border, whereas in post-gastrula development ALK6 exerts a highly specific, conserved function in neural crest development.

Dual pathways to endochondral osteoblasts: a novel chondrocyte-derived osteoprogenitor cell identified in hypertrophic cartilage - Park, Jung; Gebhardt, Matthias; Golovchenko, Svitlana; Perez-Branguli, Francesc; Hattori, Takako; Hartmann, Christine; Zhou, Xin; Decrombrugghe, Benoit; Stock, Michael; Schneider, Holm; Mark, Klaus (Biology Open, 2015)
According to the general understanding, the chondrocyte lineage terminates with the elimination of late hypertrophic cells by apoptosis in the growth plate. However, recent cell tracking studies have shown that murine hypertrophic chondrocytes can survive beyond "terminal" differentiation and give rise to a progeny of osteoblasts participating in endochondral bone formation. The question how chondrocytes convert into osteoblasts, however, remained open. Following the cell fate of hypertrophic chondrocytes by genetic lineage tracing using BACCol10;Cre induced YFP-reporter gene expression we show that a progeny of Col10Cre-reporter labelled osteoprogenitor cells and osteoblasts appears in the primary spongiosa and participates - depending on the developmental stage - substantially in trabecular, endosteal, and cortical bone formation. YFP(+) trabecular and endosteal cells isolated by FACS expressed Col1a1, osteocalcin and runx2, thus confirming their osteogenic phenotype. In searching for transitory cells between hypertrophic chondrocytes and trabecular osteoblasts we identified by confocal microscopy a novel, small YFP(+)Osx(+) cell type with mitotic activity in the lower hypertrophic zone at the chondro-osseous junction. When isolated from growth plates by fractional enzymatic digestion, these cells termed CDOP (chondrocyte-derived osteoprogenitor) cells expressed bone typical genes and differentiated into osteoblasts in vitro. We propose the Col10Cre-labeled CDOP cells mark the initiation point of a second pathway giving rise to endochondral osteoblasts, alternative to perichondrium derived osteoprogenitor cells. These findings add to current concepts of chondrocyte-osteocyte lineages and give new insight into the complex cartilage-bone transition process in the growth plate.
EVALuna2:10200

Dysfunction of spatacsin leads to axonal pathology in SPG11-linked hereditary spastic paraplegia - Perez-Branguli, Francesc; Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Saul, Domenica; Rummel, Christine; Dorca-Arevalo, Jonatan; Regensburger, Martin; Graef, Daniela; Sock, Elisabeth; Blasi, Juan; et al. (Human Molecular Genetics, 2014)
Hereditary spastic paraplegias are a group of inherited motor neuron diseases characterized by progressive paraparesis and spasticity. Mutations in the spastic paraplegia gene SPG11, encoding spatacsin, cause an autosomal-recessive disease trait; however, the precise knowledge about the role of spatacsin in neurons is very limited. We for the first time analyzed the expression and function of spatacsin in human forebrain neurons derived from human pluripotent stem cells including lines from two SPG11 patients and two controls. SPG11 patients'-derived neurons exhibited downregulation of specific axonal-related genes, decreased neurite complexity and accumulation of membranous bodies within axonal processes. Altogether, these data point towards axonal pathologies in human neurons with SPG11 mutations. To further corroborate spatacsin function, we investigated human pluripotent stem cell-derived neurons and mouse cortical neurons. In these cells, spatacsin was located in axons and dendrites. It colocalized with cytoskeletal and synaptic vesicle (SV) markers and was present in synaptosomes. Knockdown of spatacsin in mouse cortical neurons evidenced that the loss of function of spatacsin leads to axonal instability by downregulation of acetylated tubulin. Finally, time-lapse assays performed in SPG11 patients'-derived neurons and spatacsin-silenced mouse neurons highlighted a reduction in the anterograde vesicle trafficking indicative of impaired axonal transport. By employing SPG11 patient-derived forebrain neurons and mouse cortical neurons, this study provides the first evidence that SPG11 is implicated in axonal maintenance and cargo trafficking. Understanding the cellular functions of spatacsin will allow deciphering mechanisms of motor cortex dysfunction in autosomal-recessive hereditary spastic paraplegia.
EVALuna2:4956

Easy performance of 6-color confocal immunofluorescence with 4-laser line microscopes - Eissing, Nathalie; Heger, Lukas; Baranska, Anna; Cesnjevar, Robert; Büttner, Maike; Söder, Stephan; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana (Immunology Letters, 2014)
Confocal laser scanning microscopy is an advanced technique for imaging tissue samples in vitro and in vivo at high optical resolution. The development of new fluorochrome variants do not only make it possible to perform multicolor flow cytometry of single cells, but in combination with high resolution laser scanning systems also to investigate the distribution of cells in lymphoid tissues by confocal immunofluorescence analyses, thus allowing the distinction of various cell populations directly in the tissue. Here, we provide a protocol for the visualization of at least six differently fluorochrome-labeled antibodies at the same time using a conventional confocal laser scanning microscope with four laser lines (405 nm, 488 nm, 555 nm, and 639 nm laser wavelength) in both murine and human tissue samples. We further demonstrate that compensation correction algorithms are not necessary to reduce spillover of fluorochromes into other channels when the used fluorochromes are combined according to their specific emission bands and the varying Stokes shift for co-excited fluorochromes with the same laser line.
EVALuna2:6626

Efficient and Easy Conversion of Human iPSCs into Functional Induced Microglia-like Cells - Lanfer, Jonas; Winner, Beate; Kaindl, Johanna; Krumm, Laura; Acera, Miguel Gonzalez; Neurath, Markus; Regensburger, Martin; Krach, Florian (International Journal of Molecular Sciences, 2022)
Current protocols converting human induced pluripotent stem cells (iPSCs) into induced microglia-like cells (iMGL) are either dependent on overexpression of transcription factors or require substantial experience in stem-cell technologies. Here, we developed an easy-to-use two-step protocol to convert iPSCs into functional iMGL via: (1) highly efficient differentiation of hematopoietic progenitor cells (HPCs) from iPSCs, and (2) optimized maturation of HPCs to iMGL. A sequential harvesting approach led to an increased HPC yield. The protocol implemented a freezing step, thus allowing HPC biobanking and flexible timing of differentiation into iMGL. Our iMGL responded adequately to the inflammatory stimuli LPS, and iMGL RNAseq analysis matched those of other frequently used protocols. Comparing three different coating modalities, we increased the iMGL yield by culturing on uncoated glass surfaces, thereby retaining differentiation efficiency and functional hallmarks of iMGL. In summary, we provide a high-quality, easy-to-use protocol, rendering generation and functional studies on iMGL an accessible lab resource.
CRIS-Team Scopus Importer:2022-04-29
Keywords: cell differentiation; immunology; microglia; neurology; pluripotent stem cells

EFhd2/Swiprosin-1 is a common genetic determinator for sensation-seeking/low anxiety and alcohol addiction - Mielenz, Dirk; Reichel, Martin; Jia, T.; Quinlan, E. B.; Stöckl, Thomas; Mettang, M.; Zilske, Daniel; Kirmizi Alsan, Elif; Schoenberger, P.; Praetner, M.; Huber, Sabine; Amato, Davide; et al. (Molecular Psychiatry, 2017)
In many societies, the majority of adults regularly consume alcohol. However, only a small proportion develops alcohol addiction. Individuals at risk often show a high sensation-seeking/low-anxiety behavioural phenotype. Here we asked which role EF hand domain containing 2 (EFhd2; Swiprosin-1) plays in the control of alcohol addiction-associated behaviours. EFhd2 knockout (KO) mice drink more alcohol than controls and spontaneously escalate their consumption. This coincided with a sensation-seeking and low-anxiety phenotype. A reversal of the behavioural phenotype with β-carboline, an anxiogenic inverse benzodiazepine receptor agonist, normalized alcohol preference in EFhd2 KO mice, demonstrating an EFhd2-driven relationship between personality traits and alcohol preference. These findings were confirmed in a human sample where we observed a positive association of the EFhd2 single-nucleotide polymorphism rs112146896 with lifetime drinking and a negative association with anxiety in healthy adolescents. The lack of EFhd2 reduced extracellular dopamine levels in the brain, but enhanced responses to alcohol. In confirmation, gene expression analysis revealed reduced tyrosine hydroxylase expression and the regulation of genes involved in cortex development, Eomes and Pax6, in EFhd2 KO cortices. These findings were corroborated in Xenopus tadpoles by EFhd2 knockdown. Magnetic resonance imaging (MRI) in mice showed that a lack of EFhd2 reduces cortical volume in adults. Moreover, human MRI confirmed the negative association between lifetime alcohol drinking and superior frontal gyrus volume. We propose that EFhd2 is a conserved resilience factor against alcohol consumption and its escalation, working through Pax6/Eomes. Reduced EFhd2 function induces high-risk personality traits of sensation-seeking/low anxiety associated with enhanced alcohol consumption, which may be related to cortex function.
EVALuna2:4036

Elementary immunology: Na(+) as a regulator of immunity - Schatz, Valentin; Neubert, Patrick; Schröder, Agnes; Binger, Katrina; Gebhard, Matthias; Mueller, Dominik N.; Luft, Friedrich C.; Titze, Jens; Jantsch, Jonathan (Pediatric Nephrology, 2017)
The skin can serve as an interstitial Na(+) reservoir. Local tissue Na(+) accumulation increases with age, inflammation and infection. This increased local Na(+) availability favors pro-inflammatory immune cell function and dampens their anti-inflammatory capacity. In this review, we summarize available data on how NaCl affects various immune cells. We particularly focus on how salt promotes pro-inflammatory macrophage and T cell function and simultaneously curtails their regulatory and anti-inflammatory potential. Overall, these findings demonstrate that local Na(+) availability is a promising novel regulator of immunity. Hence, the modulation of tissue Na(+) levels bears broad therapeutic potential: increasing local Na(+) availability may help in treating infections, while lowering tissue Na(+) levels may be used to treat, for example, autoimmune and cardiovascular diseases.
EVALuna2:3894

EuroHYP-1: European multicenter, randomized, phase III clinical trial of therapeutic hypothermia plus best medical treatment vs. best medical treatment alone for acute ischemic stroke - Van Der Worp, H. Bart; Macleod, Malcolm R.; Bath, Philip M. W.; Demotes, Jacques; Durand-Zaleski, Isabelle; Gebhardt, Bernd; Gluud, Christian; Kollmar, Rainer; Krieger, Derk W.; Lees, Kennedy R.; Molina, Carlos; Montaner, Joan; et al. (International Journal of Stroke, 2014)
Cooling reduced infarct size and improved neurological outcomes in animal studies modeling ischemic stroke, and also improved outcome in randomized clinical trials in patients with hypoxic-ischemic brain injury after cardiac arrest. Cooling awake patients with ischemic stroke has been shown feasible in phase II clinical trials.To determine whether systemic cooling to a target body temperature between 34·0 and 35·0°C, started within six-hours of symptom onset and maintained for 24 h, improves functional outcome at three-months in patients with acute ischemic stroke.International, multicenter, phase III, randomized, open-label clinical trial with blinded outcome assessment in 1500 patients aged 18 years or older with acute ischemic stroke and a National Institutes of Health Stroke Scale score of 6 up to and including 18. In patients randomized to hypothermia, cooling to a target body temperature of 34-35°C will be started within six-hours after symptom onset with rapid intravenous infusion of refrigerated normal saline or a surface cooling technique and maintained for 24 h with a surface or endovascular technique. Patients randomized to hypothermia will receive pethidine and buspirone to prevent shivering and discomfort.Score on the modified Rankin Scale at 91 days, as analyzed with ordinal logistic regression and expressed as a common odds ratio.With 750 patients per intervention group, this trial has 90% power to detect 7% absolute improvement at the 5% significance level. The full trial protocol is available at http://www.eurohyp1.eu. ClinicalTrials.gov Identifier: NCT01833312.
EVALuna2:22308

FcγRIIa genotype is associated with acute coronary syndromes as first manifestation of coronary artery disease - Raaz, Dorette; Herrmann, Martin; Ekici, Arif Bülent; Klinghammer, Lutz; Lausen, Berthold; Voll, Reinhard E.; Leusen, Jeanette H.W.; van de Winkel, Jan G.J.; Daniel, Werner; Reis, André; Garlichs, Christoph (Atherosclerosis, 2009)
Objective: Identification of clinically relevant determinants for acute coronary syndromes (ACS) promises reduction of ACS-associated mortality. C-reactive protein (CRP) has proved to be useful identifying people at risk for cardiovascular events. However, it is unknown whether genetic variants at Fcγ receptor IIa (FcγRIIa), the main receptor for CRP, are involved in CRP-related cardiovascular risk. We evaluated the potential impact of FcγRIIa through a genetic association study in patients with ACS. Methods and results: We conducted a genetic association study among 701 consecutive patients with first event of ACS compared to 467 patients with stable angina pectoris. All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa, where the arginine (R) allele results in an increased signal transduction upon CRP binding. In our study, the R/R131 genotype was significantly associated with ACS as the first manifestation of coronary artery disease (P = 1.2 × 10-9, odds ratio 2.86, 95% CI: 2.06-3.99) compared to the non-R/R131 genotype. Conclusions: Our data show a genetic association of the FcγRIIa R/R131 genotype with a more frequent occurrence of ACS as the first manifestation of coronary artery disease, probably mediated via its interaction with CRP. Genotyping of this FcγRIIa variant could help to improve risk stratification in the course of coronary disease in the future. © 2009 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Acute coronary syndrome; Fcγ receptor IIa; Gene polymorphism; Inflammation

Fibroblast Growth Factor 9/Fibroblast Growth Factor Receptor 3 Signaling Is Upstream of Several Profibrotic Pathways and Induces Fibroblast Activation and Tissue Fibrosis in SSc - Mallano, Tatjana; Distler, Alfiya; Dees, Clara; Huang, Jingang; Distler, Oliver; Schett, Georg; Distler, Jörg; Chakraborty, Debomita (2016)
EVALuna2:35061

Functional gait measures correlate to fear of falling, and quality of life in patients with Hereditary Spastic Paraplegia: A cross-sectional study - Gaßner, Heiko; List, Julia; Martindale, Christine; Regensburger, Martin; Klucken, Jochen; Winkler, Jürgen; Kohl, Zacharias (Clinical Neurology and Neurosurgery, 2021)
Objective: Gait impairment is the cardinal motor symptom in hereditary spastic paraplegias (HSPs) possibly linked to increased fear of falling and reduced quality of life (QoL). Disease specific symptoms in HSP are rated using the Spastic Paraplegia Rating Scale (SPRS). However, limited studies evaluated more objectively easy-to-apply gait measures by comparing these standardized assessments with patients’ self-perceived impairment and clinically established scores. Therefore, the aim of this study was to correlate functional gait measures with self-rating questionnaires for fear of falling and QoL, and with the SPRS as clinical gold standard. Methods: HSP patients (“pure” phenotype, n = 22) fulfilling the clinical diagnostic criteria for HSP and age-and gender-matched healthy subjects (n = 22) were included in this study. Motor impairment was evaluated using the SPRS, fear of falling by the Falls Efficacy Scale-International (FES-I), and QoL by SF-12. Functional gait measures included gait speed and step length (10-meter-walk-test), the Timed up and go test (TUG), and maximum walking distance (2-min-walking-test). Results: Functional gait measures correlated to fear of falling (gait speed: r = −0.726; step length: r = −0.689; TUG: r = 0.721; 2-min: r = −0.709) and the physical component of QoL (gait speed: r = 0.541; step length: r = 0.531; TUG: r = −0.512; 2-min: r = 0.548). Furthermore, FES-I (r = 0.767) and QoL (r = -0.728) correlated with the clinical gold standard (SPRS). Gait measures strongly correlated with SPRS (gait speed: r = −0.787; step length: r = −0.821; TUG: r = 0.756; 2-min: r = −0.791). Conclusion: Functional gait measures reflect fear of falling, QoL, and mobility in HSP. The metric, semi-quantitative gait measures complement the clinician's evaluation and support the clinical workup by more objective parameters.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Fear of falling; Gait analysis; Hereditary spastic paraplegia; Patient-reported outcome; Quality of life

Fundamentals of cell metabolism and cancer - Devendran, Ragunathan; Ramesh, Vignesh; Gnanasekaran, Prabu (Elsevier, 2022)
Cancer, a highly heterogeneous disease, arises from the spontaneous selection of advantageous molecular level processes favoring cell proliferation and growth. Uncontrolled cell proliferation and growth cause irregular nutrient turnover during tumor development. Cancer cells prime the metabolic rewiring to achieve a proliferative capacity for survival under such conditions. In other words, altered metabolism is the fundamental difference between normal and cancer cells. Interestingly, metabolic pathways serve as suitable and promising targets for therapeutics. Therefore, understanding the metabolism of the normal and cancerous state is essential to develop therapeutic strategies for cancer treatment. This chapter focus on the key metabolic processes taking place in the normal and cancerous cellular conditions, while the latter has re-routed metabolic pathways to support its growth and proliferation. Further, this chapter describes the dominant influence of metabolic processes role in regulating oncogenic signaling pathways and transcription factors to target the metabolic activity of cancer.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Amino acid metabolism; Cancer metabolism; Fatty acid metabolism; Glucose metabolism; Pentose phosphate pathway; Warburg effect

Gene dosage-dependent rescue of HSP neurite defects in SPG4 patients' neurons - Havlicek, Steven; Kohl, Zacharias; Mishra, Himanshu Kumar; Prots, Iryna; Eberhardt, Esther; Denguir, Naime; Wend, Holger; Ploetz, Sonja; Boyer, Leah; Marchetto, Maria C. N.; Aigner, Stefan; Sticht, Heinrich; et al. (Human Molecular Genetics, 2014)
The hereditary spastic paraplegias (HSPs) are a heterogeneous group of motorneuron diseases characterized by progressive spasticity and paresis of the lower limbs. Mutations in Spastic Gait 4 (SPG4), encoding spastin, are the most frequent cause of HSP. To understand how mutations in SPG4 affect human neurons, we generated human induced pluripotent stem cells (hiPSCs) from fibroblasts of two patients carrying a c.1684C>T nonsense mutation and from two controls. These SPG4 and control hiPSCs were able to differentiate into neurons and glia at comparable efficiency. All known spastin isoforms were reduced in SPG4 neuronal cells. The complexity of SPG4 neurites was decreased, which was paralleled by an imbalance of axonal transport with less retrograde movement. Prominent neurite swellings with disrupted microtubules were present in SPG4 neurons at an ultrastructural level. While some of these swellings contain acetylated and detyrosinated tubulin, these tubulin modifications were unchanged in total cell lysates of SPG4 neurons. Upregulation of another microtubule-severing protein, p60 katanin, may partially compensate for microtubuli dynamics in SPG4 neurons. Overexpression of the M1 or M87 spastin isoforms restored neurite length, branching, numbers of primary neurites and reduced swellings in SPG4 neuronal cells. We conclude that neurite complexity and maintenance in HSP patient-derived neurons are critically sensitive to spastin gene dosage. Our data show that elevation of single spastin isoform levels is sufficient to restore neurite complexity and reduce neurite swellings in patient cells. Furthermore, our human model offers an ideal platform for pharmacological screenings with the goal to restore physiological spastin levels in SPG4 patients.
EVALuna2:2420

Glucocorticoids preserve the t-tubular system in ventricular cardiomyocytes by upregulation of autophagic flux - Seidel, Thomas; Fiegle, Dominik; Baur, Tim J.; Ritzer, Anne; Nay, Sandra; Heim, Christian; Weyand, Michael; Milting, Hendrik; Oakley, Robert H.; Cidlowski, John A.; Volk, Tilmann (Basic Research in Cardiology, 2019)
A major contributor to contractile dysfunction in heart failure is remodelling and loss of the cardiomyocyte transverse tubular system (t-system), but underlying mechanisms and signalling pathways remain elusive. It has been shown that dexamethasone promotes t-tubule development in stem cell-derived cardiomyocytes and that cardiomyocyte-specific glucocorticoid receptor (GR) knockout (GRKO) leads to heart failure. Here, we studied if the t-system is altered in GRKO hearts and if GR signalling is required for t-system preservation in adult cardiomyocytes. Confocal and 3D STED microscopy of myocardium from cardiomyocyte-specific GRKO mice revealed decreased t-system density and increased distances between ryanodine receptors (RyR) and L-type Ca2+ channels (LTCC). Because t-system remodelling and heart failure are intertwined, we investigated the underlying mechanisms in vitro. Ventricular cardiomyocytes from failing human and healthy adult rat hearts cultured in the absence of glucocorticoids (CTRL) showed distinctively lower t-system density than cells treated with dexamethasone (EC50 1.1 nM) or corticosterone. The GR antagonist mifepristone abrogated the effect of dexamethasone. Dexamethasone improved RyR–LTCC coupling and synchrony of intracellular Ca2+ release, but did not alter expression levels of t-system-associated proteins junctophilin-2 (JPH2), bridging integrator-1 (BIN1) or caveolin-3 (CAV3). Rather, dexamethasone upregulated LC3B and increased autophagic flux. The broad-spectrum protein kinase inhibitor staurosporine prevented dexamethasone-induced upregulation of autophagy and t-system preservation, and autophagy inhibitors bafilomycin A and chloroquine accelerated t-system loss. Conversely, induction of autophagy by rapamycin or amino acid starvation preserved the t-system. These findings suggest that GR signalling and autophagy are critically involved in t-system preservation and remodelling in the heart.
CRIS-Team Scopus Importer:2019-11-08
Keywords: Autophagy; Calcium signalling; Excitation–contraction coupling; Glucocorticoid receptor; Heart failure; Remodelling; Transverse tubular system

GNA13 expression promotes drug resistance and tumor-initiating phenotypes in squamous cell cancers - Rasheed, Suhail Ahmed Kabeer; Leong, Hui Sun; Lakshmanan, Manikandan; Raju, Anandhkumar; Dadlani, Dhivya; Chong, Fui-Teen; Shannon, Nicholas B.; Rajarethinam, Ravisankar; Skanthakumar, Thakshayeni; Tan, Ern Yu; Hwang, Jacqueline Siok Gek; Lim, Kok Hing; et al. (Oncogene, 2017)
Treatment failure in solid tumors occurs due to the survival of specific subpopulations of cells that possess tumor-initiating (TIC) phenotypes. Studies have implicated G protein-coupled-receptors (GPCRs) in cancer progression and the acquisition of TIC phenotypes. Many of the implicated GPCRs signal through the G protein GNA13. In this study, we demonstrate that GNA13 is upregulated in many solid tumors and impacts survival and metastases in patients. GNA13 levels modulate drug resistance and TIC-like phenotypes in patient-derived head and neck squamous cell carcinoma (HNSCC) cells in vitro and in vivo. Blockade of GNA13 expression, or of select downstream pathways, using small-molecule inhibitors abrogates GNA13-induced TIC phenotypes, rendering cells vulnerable to standard-of-care cytotoxic therapies. Taken together, these data indicate that GNA13 expression is a potential prognostic biomarker for tumor progression, and that interfering with GNA13-induced signaling provides a novel strategy to block TICs and drug resistance in HNSCCs.
EVALuna2:32857

GSK3ss-Dependent Dysregulation of Neurodevelopment in SPG11-Patient Induced Pluripotent Stem Cell Model - Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Pérez-Brangulí, Francesc; Börstler, Tom; Anneser, Lukas; Minakaki, Georgia; Wend, Holger; Hampl, Martin; Leone, Marina; Brückner, Martina; et al. (Annals of Neurology, 2016)
Objective: Mutations in the spastic paraplegia gene 11 (SPG11), encoding spatacsin, cause the most frequent form of autosomal-recessive complex hereditary spastic paraplegia (HSP) and juvenile-onset amyotrophic lateral sclerosis (ALS5). When SPG11 is mutated, patients frequently present with spastic paraparesis, a thin corpus callosum, and cognitive impairment. We previously delineated a neurodegenerative phenotype in neurons of these patients. In the current study, we recapitulated early developmental phenotypes of SPG11 and outlined their cellular and molecular mechanisms in patient-specific induced pluripotent stem cell (iPSC)-derived cortical neural progenitor cells (NPCs).Methods: We generated and characterized iPSC-derived NPCs and neurons from 3 SPG11 patients and 2 age-matched controls.Results: Gene expression profiling of SPG11-NPCs revealed widespread transcriptional alterations in neurodevelopmental pathways. These include changes in cell-cycle, neurogenesis, cortical development pathways, in addition to autophagic deficits. More important, the GSK3ss-signaling pathway was found to be dysregulated in SPG11-NPCs. Impaired proliferation of SPG11-NPCs resulted in a significant diminution in the number of neural cells. The decrease in mitotically active SPG11-NPCs was rescued by GSK3 modulation.Interpretation: This iPSC-derived NPC model provides the first evidence for an early neurodevelopmental phenotype in SPG11, with GSK3ss as a potential novel target to reverse the disease phenotype.

Guidelines for mouse and human DC functional assays - Clausen, Bjoern E.; Amon, Lukas; Backer, Ronald A.; Berod, Luciana; Bopp, Tobias; Brand, Anna; Burgdorf, Sven; Chen, Luxia; Da, Meihong; Distler, Ute; Dress, Regine J.; Dudziak, Diana; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. Recent studies have provided evidence for an increasing number of phenotypically distinct conventional DC (cDC) subsets that on one hand exhibit a certain functional plasticity, but on the other hand are characterized by their tissue- and context-dependent functional specialization. Here, we describe a selection of assays for the functional characterization of mouse and human cDC. The first two protocols illustrate analysis of cDC endocytosis and metabolism, followed by guidelines for transcriptomic and proteomic characterization of cDC populations. Then, a larger group of assays describes the characterization of cDC migration in vitro, ex vivo, and in vivo. The final guidelines measure cDC inflammasome and antigen (cross)-presentation activity. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.<br

Harnessing mitochondrial metabolism and drug resistance in non-small cell lung cancer and beyond by blocking heat-shock proteins - Parma, Beatrice; Wurdak, Heiko; Ceppi, Paolo (Drug Resistance Updates, 2022)
Lung cancer is the leading cause of cancer-related deaths worldwide, with non-small cell lung cancer (NSCLC) being the predominant histological subtype. Despite the emergence of targeted and immune-based therapies that have considerably improved the clinical outcomes of selected patients, the overall NSCLC survival rate remains poor. NSCLC patients experience clinical relapse mainly because of chemoresistance. One promising therapeutic approach is targeting specific molecular vulnerabilities that are associated with the metabolic reprogramming of cancer cells. This strategy relies on evidence that cancer cells rewire their metabolism to sustain their uncon-trolled growth as well as invasive and metastatic properties, promoting adaptive resistance to chemo-radiotherapy. A critical component of this malignant transformation is the increased dependency on high levels of heat shock proteins (HSPs), which support the elevated protein folding demand and quality control of misfolded oncoproteins. Here, we provide an overview of the literature on metabolism reprogramming, dereg-ulation of mitochondrion and on the role of HSPs in promoting malignancy in lung and other cancer types. A particular focus is dedicated to the role of mitochondrial HSP60 (HSPD1) in NSCLC metabolism and drug resistance for the potential development of new resistance-defying anti-HSP drugs.
CRIS-Team WoS Importer:2022-11-25

Hemodialysis Patients with Cardiovascular Disease Reveal Increased Tissue Na+ Deposition - Friedrich, Anna Carolina; Linz, Peter; Nagel, Armin Michael; Rosenhauer, Daniela; Horn, Stephan; Schiffer, Mario; Uder, Michael; Kopp, Christoph; Dahlmann, Anke (Kidney & Blood Pressure Research, 2022)
BACKGROUND: The relationship between Na+ balance and cardiovascular disease (CVD) in hemodialysis (HD) patients is not yet fully understood. We hypothesized that HD patients co-diagnosed with CVD show increased tissue Na+ accumulation compared to HD patients without CVD. METHODS: In our observational study, 52 HD patients were divided into a group with (23 subjects) or without (29 subjects) a positive history of cardiovascular events. We used 23Na-magnetic resonance imaging (23Na-MRI) at 3.0 Tesla to quantify Na+ content in skin and muscle of both groups directly before and after HD. Additionally, total body fluid distribution was determined by bioimpedance spectroscopy (BIS) and laboratory parameters were assessed. RESULTS: Compared to HD patients without CVD, 23Na-MRI detected an increased Na+ content in skin (21.7 ± 7.3 vs. 30.2 ± 9.8 arbitrary units (a.u.), p < 0.01) and muscle tissue (21.5 ± 3.6 vs. 24.7 ± 6.0 a.u., p < 0.05) in patients with previous CVD events. Simultaneously measured fluid amount by BIS, includingexcess extracellular water (1.8 ± 1.7 vs. 2.2 ± 1.7 L, p = 0.44), was not significantly different between both groups. Tissue Na+ accumulation in HD-CVD patients was paralleled by a higher plasma concentration of the inflammation marker interleukin-6 (5.1, IQR 5.8 vs. 8.5, IQR 7.9 pg/mL, p < 0.05). CONCLUSION: In our cohort, HD patients with CVD showed higher tissue Na+ content than HD patients without CVD, while no difference in body water distribution could be detected between both groups. Our findings provide evidence that the history of a cardiovascular event is associated with disturbances in tissue Na+ content in HD patients.
CRIS-Team Scopus Importer:2022-03-25
Keywords: 23Na-magnetic resonance imaging; Cardiovascular disease; Hemodialysis; Tissue Na+

HIF-1 or HIF-2 induction is sufficient to achieve cell cycle arrest in NIH3T3 mouse fibroblasts independent from hypoxia - Hackenbeck, Thomas; Knaup, Karl; Schietke, Ruth; Schödel, Johannes; Willam, Carsten; Wu, Xiaoqing; Warnecke, Christina; Eckardt, Kai-Uwe; Wiesener, Michael Sean (Cell Cycle, 2009)
Hypoxia is a severe stress which induces physiological and molecular adaptations, where the latter is dominated by the Hypoxia-inducible transcription Factor (HIF). A well described response on cellular level upon exposure to hypoxia is a reversible cell cycle arrest, which probably renders the cells more resistant to the difficult environment. The individual roles of hypoxia itself and of the isoforms HIF-1α and HIF-2α in cell cycle regulation are poorly understood and discussed controversially. In order to characterize the isolated effect of both HIFα isoforms on the cell cycle we generated tetracycline inducible, HIF-1α and -2α expressing NIH3T3 cells. The cDNAs for HIFα were mutated to generate stable and active HIF under normoxia. Upon activation of both HIFα subunits, the total number of living cells was reduced and long-term stimulation of HIF led to complete loss of transgene expression, implicating a strong negative selection pressure. Equally, colony forming activity was reduced by activation of both HIFα subunits. Cell cycle analyses showed that HIF activation resulted in a prominent cell cycle arrest in G1-phase, similarly to the hypoxic effect. Both, HIF-1α and HIF-2α were able to induce the expression of the cyclin-dependent kinase inhibitor p27 on reporter gene and protein level. Our study shows that HIF-1 and HIF-2 can individually arrest the cell cycle independent from hypoxia. These findings have implications for the resistance of tumor cells to the environment and treatment, but also for physiological cells. Importantly, recent approaches to stabilize HIFα in normoxia could have deleterious effects on proliferating tissues. ©2009 Landes Bioscience.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Cell cycle regulation; G; Hypoxia; Hypoxia-inducible factor (HIF); p27; Tetracycline-inducible; Tumor resistance; Tumorigenesis; VHL

HIF activation protects from acute kidney injury - Weidemann, Alexander; Bernhardt, Wanja M.; Klanke, Bernd; Daniel, Christoph; Buchholz, Björn; Campean, Valentina; Amann, Kerstin Ute; Warnecke, Christina; Wiesener, Michael S.; Eckardt, Kai-Uwe; Willam, Carsten (Journal of the American Society of Nephrology, 2008)
The contribution of hypoxia to cisplatin-induced renal tubular injury is controversial. Because the hypoxia-inducible factor (HIF) pathway is a master regulator of adaptation to hypoxia, we measured the effects of cisplatin on HIF accumulation in vitro and in vivo, and tested whether hypoxic preconditioning is protective against cisplatin-induced injury. We found that cisplatin did not stabilize HIF-1 alpha protein in vitro or in vivo under normoxic conditions. However, hypoxic preconditioning of cisplatin-treated proximal tubular cells in culture reduced apoptosis in an HIF-1 alpha-dependent fashion and increased cell proliferation as measured by BrdU incorporation. In vivo, rats preconditioned with carbon monoxide before cisplatin administration had significantly better renal function than rats kept in normoxic conditions throughout. Moreover, the histomorphological extent of renal damage and tubular apoptosis was reduced by the preconditional treatment. Therefore, development of pharmacologic agents to induce renal HIF might provide a new approach to ameliorate cisplatin-induced nephrotoxicity.

High Fat Diet Alleviates Antigen-Induced Arthritis Severity in Male Mice By Enhancing Both Treg and B10 Cells - Luo, Yubin; Engdahl, Cecilia; Yi Zaho,; Liu, Yi; Schett, Georg; Bozec, Aline (2016)
EVALuna2:35060

High salt intake reprioritizes osmolyte and energy metabolism for body fluid conservation - Kitada, Kento; Daub, Steffen; Zhang, Yahua; Klein, Janet D.; Nakano, Daisuke; Pedchenko, Tetyana; Lantier, Louise; Larocque, Lauren M.; Marton, Adriana; Neubert, Patrick; Schröder, Agnes; Rakova, Natalia; et al. (Journal of Clinical Investigation, 2017)
Natriuretic regulation of extracellular fluid volume homeostasis includes suppression of the renin-angiotensin-aldosterone system, pressure natriuresis, and reduced renal nerve activity, actions that concomitantly increase urinary Na+ excretion and lead to increased urine volume. The resulting natriuresis-driven diuretic water loss is assumed to control the extracellular volume. Here, we have demonstrated that urine concentration, and therefore regulation of water conservation, is an important control system for urine formation and extracellular volume homeostasis in mice and humans across various levels of salt intake. We observed that the renal concentration mechanism couples natriuresis with correspondent renal water reabsorption, limits natriuretic osmotic diuresis, and results in concurrent extracellular volume conservation and concentration of salt excreted into urine. This water-conserving mechanism of dietary salt excretion relies on urea transporter-driven urea recycling by the kidneys and on urea production by liver and skeletal muscle. The energy-intense nature of hepatic and extrahepatic urea osmolyte production for renal water conservation requires reprioritization of energy and substrate metabolism in liver and skeletal muscle, resulting in hepatic ketogenesis and glucocorticoid-driven muscle catabolism, which are prevented by increasing food intake. This natriuretic-ureotelic, water-conserving principle relies on metabolism-driven extracellular volume control and is regulated by concerted liver, muscle, and renal actions.
EVALuna2:34241

High spatiotemporal resolution data from a custom magnetic tweezers instrument - Ostrofet, Eugeniu; Papini, Flávia S.; Dulin, David (Data in Brief, 2020)
Gene expression is achieved by enzymes as RNA polymerases that translocate along nucleic acids with steps as small as a single base pair, i.e., 0.34 nm for DNA. Deciphering the complex biochemical pathway that describes the activity of such enzymes requires an exquisite spatiotemporal resolution. Magnetic tweezers are a powerful single molecule force spectroscopy technique that uses a camera-based detection to enable the simultaneous observation of hundreds of nucleic acid tethered magnetic beads at a constant force with subnanometer resolution [1,2]. High spatiotemporal resolution magnetic tweezers have recently been reported [3–5]. We present data acquired using a bespoke magnetic tweezers instrument that is able to perform either in high throughput or at high resolution. The data reports on the best achievable resolution for surface-attached polystyrene beads and DNA tethered magnetic beads, and highlights the influence of mechanical stability for such assay. We also present data where we are able to detect 0.3 nm steps along the z-axis using DNA tethered magnetic beads. Because the data presented here are in agreement with the best resolution obtained with magnetic tweezers, they provide a useful benchmark comparison for setup adjustment and optimization.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Force spectroscopy; High spatiotemporal resolution; Magnetic tweezers; Single molecule biophysics

High throughput magnetic tweezers to characterize inhibitors of RNA virus replication - Dulin, David (Virologie, 2019)
CRIS-Team WoS Importer:2020-01-07

High-yield fabrication of DNA and RNA constructs for single molecule force and torque spectroscopy experiments - Papini, Flávia S.; Seifert, Mona; Dulin, David (Nucleic Acids Research, 2019)
Single molecule biophysics experiments have enabled the observation of biomolecules with a great deal of precision in space and time, e.g. nucleic acids mechanical properties and protein-nucleic acids interactions using force and torque spectroscopy techniques. The success of these experiments strongly depends on the capacity of the researcher to design and fabricate complex nucleic acid structures, as the outcome and the yield of the experiment also strongly depend on the high quality and purity of the final construct. Though the molecular biology techniques involved are well known, the fabrication of nucleic acid constructs for single molecule experiments still remains a difficult task. Here, we present new protocols to generate high quality coilable double-stranded DNA and RNA, as well as DNA and RNA hairpins with ∼500-1000 bp long stems. Importantly, we present a new approach based on single-stranded DNA (ssDNA) annealing and we use magnetic tweezers to show that this approach simplifies the fabrication of complex DNA constructs, such as hairpins, and converts more efficiently the input DNA into construct than the standard PCR-digestion-ligation approach. The protocols we describe here enable the design of a large range of nucleic acid construct for single molecule biophysics experiments.
CRIS-Team Scopus Importer:2019-12-20

Human Induced Pluripotent Stem Cell-Derived Pericytes as Scalable and Editable Source to Study Direct Lineage Reprogramming Into Induced Neurons - Menon, Radhika; Petrucci, Linda; Lohrer, Benjamin; Zhang, Jingzhong; Schulze, Markus; Schichor, Christian; Winner, Beate; Winkler, Jürgen; Riemenschneider, Markus J.; Kühn, Ralf; Falk, Sven; Karow, Marisa (Cellular Reprogramming, 2023)
Studying human somatic cell-to-neuron conversion using primary brain-derived cells as starting cell source is hampered by limitations and variations in human biopsy material. Thus, delineating the molecular variables that allow changing the identity of somatic cells, permit adoption of neuronal phenotypes, and foster maturation of induced neurons (iNs) is challenging. Based on our previous results that pericytes derived from the adult human cerebral cortex can be directly converted into iNs (Karow et al., 2018; Karow et al., 2012), we here introduce human induced pluripotent stem cell (hiPSC)-derived pericytes (hiPSC-pericytes) as a versatile and more uniform tool to study the pericyte-to-neuron conversion process. This strategy enables us to derive scalable cell numbers and allows for engineering of the starting cell population such as introducing reporter tools before differentiation into hiPSC-pericytes and subsequent iN conversion. Harvesting the potential of this approach, we established hiPSC-derived human-human neuronal cocultures that not only allow for independent manipulation of each coculture partner but also resulted in morphologically more mature iNs. In summary, we exploit hiPSC-based methods to facilitate the analysis of human somatic cell-to-neuron conversion.
CRIS-Team Scopus Importer:2023-11-03
Keywords: direct lineage reprogramming; induced neurons; organoids; pericytes

Human SPG11 cerebral organoids reveal cortical neurogenesis impairment - Pérez-Brangulí, Francesc; Buchsbaum, Isabel; Pozner, Tatyana; Regensburger, Martin; Fan, Wenqiang; Schray, Annika; Börstler, Tom; Mishra, Himanshu Kumar; Gräf, Daniela; Kohl, Zacharias; Winkler, Jürgen; Berninger, Benedikt; et al. (Human Molecular Genetics, 2018)
SPG11 linked hereditary spastic paraplegia is a complex monogenic neurodegenerative disease that in addition to spastic paraplegia is characterized by childhood onset cognitive impairment, thin corpus callosum and enlarged ventricles. We have previously shown impaired proliferation of SPG11 neural progenitor cells (NPCs). For delineation of potential defect in SPG11 brain development we employ 2D culture systems and 3D human brain organoids derived from SPG11 patients' iPSC and controls. We reveal that an increased rate of asymmetric divisions of neural progenitor cells leads to proliferation defect, causing premature neurogenesis. Correspondingly, SPG11 organoids appeared smaller than controls and had larger ventricles as well as thinner germinal wall. Premature neurogenesis and organoid size were rescued by GSK3-inhibititors including the FDA-approved tideglusib. These findings shed light on the neurodevelopmental mechanisms underlying disease pathology.
EVALuna2:36370

Hypoxia-inducible protein 2 is a novel lipid droplet protein and a specific target gene of hypoxia-inducible factor-1 - Gimm, Tina; Wiese, Melanie; Teschemacher, Barbara; Deggerich, Anke; Schödel, Johannes; Knaup, Karl; Hackenbeck, Thomas; Hellerbrand, Claus; Amann, Kerstin Ute; Wiesener, Michael; Höning, Stefan; Eckardt, Kai-Uwe; et al. (The FASEB Journal, 2010)
Hypoxia-inducible protein 2 (HIG2) has been implicated in canonical Wnt signaling, both as target and activator. The potential link between hypoxia and an oncogenic signaling pathway might play a pivotal role in renal clear-cell carcinoma characterized by constitutive activation of hypoxia-inducible factors (HIFs), and hence prompted us to analyze HIG2 regulation and function in detail. HIG2 was up-regulated by hypoxia and HIF inducers in all cell types and mouse organs investigated and abundantly expressed in renal clear-cell carcinomas. Promoter analyses, gel shifts, and siRNA studies revealed that HIG2 is a direct and specific target of HIF-1, but not responsive to HIF-2. Surprisingly, HIG2 was not secreted, and HIG2 overexpression neither stimulated proliferation nor activated Wnt signaling. Instead, we show that HIG2 decorates the hemimembrane of lipid droplets, whose number and size increase on hypoxic inhibition of fatty acid β-oxidation, and colocalizes with the lipid droplet proteins adipophilin and TIP47. Normoxic overexpression of HIG2 was sufficient to increase neutral lipid deposition in HeLa cells and stimulated cytokine expression. HIG2 could be detected in atherosclerotic arteries and fatty liver disease, suggesting that this ubiquitously inducible HIF-1 target gene may play an important functional role in diseases associated with pathological lipid accumulation. © FASEB.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Gene expression; Lipid metabolism; Promoter; Renal clear-cell carcinoma

Identification of novel MRGX2-agonists triggering mast cell degranulation and potentially mediating drug-induced pruritus - Kühn, Helen; Wolf, Katharina; Boehm, F.; Glaudo, Markus; Gebhardt, Lisa; Ectors, Philipp; Agelopoulos, K.; Zahn, Dirk; Staender, S.; Kremer, Andreas (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

IL-36R signalling activates intestinal epithelial cells and fibroblasts and promotes mucosal healing in vivo - Scheibe, Kristina; Backert, Ingo; Wirtz, Stefan; Hueber, Axel; Schett, Georg; Vieth, Michael; Probst, Hans Christian; Bopp, Tobias; Neurath, Markus; Neufert, Clemens (Gut, 2016)
Interleukin (IL)-36R signalling plays a proinflammatory role in different organs including the skin, but the expression of IL-36R ligands and their molecular function in intestinal inflammation are largely unknown.We studied the characteristics of IL-36R ligand expression in IBDs and experimental colitis. The functional role of IL-36R signalling in the intestine was addressed in experimental colitis and wound healing models in vivo by using mice with defective IL-36R signalling (IL-36R-/-) or Myd88, neutralising anti-IL-36R antibodies, recombinant IL-36R ligands and RNA-seq genome expression analysis.Expression of IL-36? and IL-36? was significantly elevated in active human IBD and experimental colitis. While IL-36? was predominantly detected in nuclei of the intestinal epithelium, IL-36? was mainly found in the cytoplasm of CD14(+) inflammatory macrophages. Functional studies showed that defective IL-36R signalling causes high susceptibility to acute dextran sodium sulfate colitis and impairs wound healing. Mechanistically, IL-36R ligands released upon mucosal damage activated IL-36R(+) colonic fibroblasts via Myd88 thereby inducing expression of chemokines, granulocyte-macrophage colony-stimulating factor (GM-CSF) and IL-6. Moreover, they induced proliferation of intestinal epithelial cells (IECs) and expression of the antimicrobial protein lipocalin 2. Finally, treatment of experimental intestinal wounds with IL-36R ligands significantly accelerated mucosal healing in vivo.IL-36R signalling is activated upon intestinal damage, stimulates IECs and fibroblasts and drives mucosal healing. Modulation of the IL-36R pathway emerges as a potential therapeutic strategy for induction of mucosal healing in IBD.
EVALuna2:2028

Immune cells control skin lymphatic electrolyte homeostasis and blood pressure - Wiig, Helge; Schröder, Agnes; Neuhofer, Wolfgang; Jantsch, Jonathan; Kopp, Christoph; Karlsen, Tine V.; Boschmann, Michael; Goss, Jennifer; Bry, Maija; Rakova, Natalia; Dahlmann, Anke; Brenner, Sven; et al. (Journal of Clinical Investigation, 2013)
The skin interstitium sequesters excess Na+ and Cl- in salt-sensitive hypertension. Mononuclear phagocyte system (MPS) cells are recruited to the skin, sense the hypertonic electrolyte accumulation in skin, and activate the tonicity-responsive enhancer-binding protein (TONEBP, also known as NFAT5) to initiate expression and secretion of VEGFC, which enhances electrolyte clearance via cutaneous lymph vessels and increases eNOS expression in blood vessels. It is unclear whether this local MPS response to osmotic stress is important to systemic blood pressure control. Herein, we show that deletion of TonEBP in mouse MPS cells prevents the VEGFC response to a high-salt diet (HSD) and increases blood pressure. Additionally, an antibody that blocks the lymph-endothelial VEGFC receptor, VEGFR3, selectively inhibited MPS-driven increases in cutaneous lymphatic capillary density, led to skin Cl- accumulation, and induced salt-sensitive hypertension. Mice overexpressing soluble VEGFR3 in epidermal keratinocytes exhibited hypoplastic cutaneous lymph capillaries and increased Na+, Cl-, and water retention in skin and salt-sensitive hypertension. Further, we found that HSD elevated skin osmolality above plasma levels. These results suggest that the skin contains a hypertonic interstitial fluid compartment in which MPS cells exert homeostatic and blood pressure-regulatory control by local organization of interstitial electrolyte clearance via TONEBP and VEGFC/VEGFR3-mediated modification of cutaneous lymphatic capillary function.
EVALuna2:7617

Impact of renal denervation on tissue Na(+) content in treatment-resistant hypertension - Ott, Christian; Kopp, Christoph; Dahlmann, Anke; Schmid, Andrea; Linz, Peter; Hammon, Matthias; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Titze, Jens; Schmieder, Roland; Cavallaro, Alexander Josef (Clinical Research in Cardiology, 2017)
Renal denervation (RDN) has been introduced for reducing blood pressure (BP) in treatment-resistant hypertension (TRH). The precise mechanism how RDN exerts its BP-lowering effects are not yet fully understood. It is widely accepted that sodium (Na(+)) plays a crucial role in the pathogenesis of hypertensive disease. However, there is increasing evidence of osmotically inactive Na(+) storage. We investigated the impact of RDN on Na(+) homeostasis using estimation of salt intake, and measurement of tissue Na(+) content.In a study 41 patients with TRH (office BP >=140/90 mmHg and diagnosis confirmed by 24-h ambulatory BP monitoring) underwent RDN. Tissue Na(+) content was assessed non-invasively with 3.0 T magnetic resonance imaging before and 6 months after RDN. In addition, 24-h urinary Na(+) excretion as an estimate of salt intake and spot urine Na(+)/K(+) excretion were assessed. The study was registered at http://www.clinicaltrials.gov (ID: NCT01687725).There was a significant fall in BP (office: -17 ± 20/-10 ± 12 mmHg; 24-h: -11 ± 13/-6 ± 9 mmHg, all p < 0.001) 6 months after RDN. In contrast, tissue Na(+) content of the muscle (20.1 ± 3.9 vs. 20.7 ± 4.0 mmol/L, p = 0.229) and skin (24.4 ± 6.5 vs. 24.8 ± 6.6 mmol/L, p = 0.695) did not change after RDN. Moreover, there was also no change in salt intake after RDN, whereas Na(+)/K(+) ratio only acutely increased.Although RDN resulted in a substantial reduction of BP, tissue Na(+) content of the muscle and skin was not mobilized and reduced. These data indicate that the BP reduction after RDN is unrelated to Na(+) homeostasis.
EVALuna2:3743

Impact of Swiprosin-1/Efhd2 on Adult Hippocampal Neurogenesis - Regensburger, Martin; Prots, Iryna; Reimer, Dorothea; Brachs, Sebastian; Loskarn, Sandra; Lie, Dieter Chichung; Mielenz, Dirk; Winner, Beate (Stem Cell Reports, 2018)
Swiprosin-1/Efhd2 (Efhd2) is highly expressed in the CNS during development and in the adult. EFHD2 is regulated by Ca2+ binding, stabilizes F-actin, and promotes neurite extension. Previous studies indicated a dysregulation of EFHD2 in human Alzheimer's disease brains. We hypothesized a detrimental effect of genetic ablation of Efhd2 on hippocampal integrity and specifically investigated adult hippocampal neurogenesis. Efhd2 was expressed throughout adult neuronal development and in mature neurons. We observed a severe reduction of the survival of adult newborn neurons in Efhd2 knockouts, starting at the early neuroblast stage. Spine formation and dendrite growth of newborn neurons were compromised in full Efhd2 knockouts, but not upon cell-autonomous Efhd2 deletion. Together with our finding of severe hippocampal tauopathy in Efhd2 knockout mice, these data connect Efhd2 to impaired synaptic plasticity as present in Alzheimer's disease and identify a role of Efhd2 in neuronal survival and synaptic integration in the adult hippocampus.
EVALuna2:34019

Impaired excitability of renal afferent innervation after exposure to the inflammatory chemokine CXCL1 - Ditting, Tilmann; Freisinger, Wolfgang; Rodionova, Kristina; Schatz, Johannes; Lale, Nena; Heinlein, Sonja; Linz, Peter; Ott, Christian; Schmieder, Roland; Scrogin, Karie E.; Veelken, Roland (American Journal of Physiology-Renal Physiology, 2016)
Recently, we showed that renal afferent neurons exhibit a unique firing pattern, i.e., predominantly sustained firing, upon stimulation. Pathological conditions such as renal inflammation likely alter excitability of renal afferent neurons. Here, we tested whether the proinflammatory chemokine CXCL1 alters the firing pattern of renal afferent neurons. Rat dorsal root ganglion neurons (Th11-L2), retrogradely labeled with dicarbocyanine dye, were incubated with CXCL1 (20 h) or vehicle before patch-clamp recording. The firing pattern of neurons was characterized as tonic, i.e., sustained action potential (AP) firing, or phasic, i.e., <5 APs following current injection. Of the labeled renal afferents treated with vehicle, 58.9% exhibited a tonic firing pattern vs. 7.8%, in unlabeled, nonrenal neurons (P < 0.05). However, after exposure to CXCL1, significantly more phasic neurons were found among labeled renal neurons; hence the occurrence of tonic neurons with sustained firing upon electrical stimulation decreased (35.6 vs. 58.9%, P < 0.05). The firing frequency among tonic neurons was not statistically different between control and CXCL1-treated neurons. However, the lower firing frequency of phasic neurons was even further decreased with CXCL1 exposure [control: 1 AP/600 ms (1-2) vs. CXCL1: 1 AP/600 ms (1-1); P < 0.05; median (25th-75th percentile)]. Hence, CXCL1 shifted the firing pattern of renal afferents from a predominantly tonic to a more phasic firing pattern, suggesting that CXCL1 reduced the sensitivity of renal afferent units upon stimulation.
EVALuna2:3740

Increased salt consumption induces body water conservation and decreases fluid intake - Rakova, Natalia; Kitada, Kento; Lerchl, Kathrin; Dahlmann, Anke; Birukov, Anna; Daub, Steffen; Kopp, Christoph; Pedchenko, Tetyana; Zhang, Yahua; Beck, Luis; Johannes, Bernd; Marton, Adriana; et al. (Journal of Clinical Investigation, 2017)
BACKGROUND: The idea that increasing salt intake increases drinking and urine volume is widely accepted. We tested the hypothesis that an increase in salt intake of 6 g/d would change fluid balance in men living under ultra-long-term controlled conditions. METHODS: Over the course of 2 separate space flight simulation studies of 105 and 205 days' duration, we exposed 10 healthy men to 3 salt intake levels (12, 9, or 6 g/d). All other nutrients were maintained constant. We studied the effect of salt-driven changes in mineralocorticoid and glucocorticoid urinary excretion on day-to-day osmolyte and water balance. RESULTS: A 6-g/d increase in salt intake increased urine osmolyte excretion, but reduced free-water clearance, indicating endogenous free water accrual by urine concentration. The resulting endogenous water surplus reduced fluid intake at the 12-g/d salt intake level. Across all 3 levels of salt intake, half-weekly and weekly rhythmical mineralocorticoid release promoted free water reabsorption via the renal concentration mechanism. Mineralocorticoid-coupled increases in free water reabsorption were counterbalanced by rhythmical glucocorticoid release, with excretion of endogenous osmolyte and water surplus by relative urine dilution. A 6-g/d increase in salt intake decreased the level of rhythmical mineralocorticoid release and elevated rhythmical glucocorticoid release. The projected effect of salt-driven hormone rhythm modulation corresponded well with the measured decrease in water intake and an increase in urine volume with surplus osmolyte excretion. CONCLUSION: Humans regulate osmolyte and water balance by rhythmical mineralocorticoid and glucocorticoid release, endogenous accrual of surplus body water, and precise surplus excretion. FUNDING: Federal Ministry for Economics and Technology/DLR; the Interdisciplinary Centre for Clinical Research; the NIH; the American Heart Association (AHA); the Renal Research Institute; and the TOYOBO Biotechnology Foundation. Food products were donated by APETITO, Coppenrath und Wiese, ENERVIT, HIPP, Katadyn, Kellogg, Molda, and Unilever.
EVALuna2:34240

Individually Tailored Predictions of Flare Probability for Rheumatoid Arthritis Patients on Biologic DMARDs Based on Machine Learning Stacking Meta-Classifier - Vodencarevic, Asmir; Simon, David; Hartmann, Fabian; Reiser, Michaela; Hueber, Axel; Tascilar, Koray; Kleyer, Arnd; Zimmermann-Rittereiser, Marcus; Schett, Georg (ARTHRITIS & RHEUMATOLOGY, 2019)
CRIS-Team WoS Importer:2020-02-07

Inefficient clearance of dying cells in patients with SLE: Anti-dsDNA autoantibodies, MFG-E8, HMGB-1 and other players - Kruse, Kristin; Janko, Christina; Urbonaviciute, Vilma; Mierke, Claudia T.; Winkler, Thomas; Voll, Reinhard E.; Schett, Georg; Munoz, Luis E.; Herrmann, Martin (Apoptosis, 2010)
Systemic lupus erythematosus (SLE) is a complex disease resulting from inflammatory responses of the immune system against several autoantigens. Inflammation is conditioned by the continuous presence of autoantibodies and leaked autoantigens, e.g. from not properly cleared dying and dead cells. Various soluble molecules and biophysical properties of the surface of apoptotic cells play significant roles in the appropriate recognition and further processing of dying and dead cells. We exemplarily discuss how Milk fat globule epidermal growth factor 8 (MFG-E8), biophysical membrane alterations, High mobility group box 1 (HMGB1), C-reactive protein (CRP), and anti-nuclear autoantibodies may contribute to the etiopathogenesis of the disease. Up to date knowledge about these key elements may provide new insights that lead to the development of new treatment strategies of the disease. © 2010 Springer Science+Business Media, LLC.
Keywords: ANA; Biophysical features; Clearance; CRP; HMGB-1; MFG-E8; Phosphatidylserine; Plasma membrane

Infiltrating T lymphocytes reduce myeloid phagocytosis activity in synucleinopathy model - Sommer, Annika; Fadler, Tanja; Dorfmeister, Eva; Hoffmann, Anna-Carin; Xiang, Wei; Winner, Beate; Prots, Iryna (Journal of Neuroinflammation, 2016)
Synucleinopathies comprise a group of neurodegenerative diseases associated with abnormal accumulation of ?-synuclein. One of the key factors that contribute to the progression of synucleinopathies is neuroinflammation. However, the role of lymphocytes in synucleinopathies like Parkinson's disease (PD) remains largely unclear.To investigate how lymphocytes impact synucleinopathies, human wild-type ?-synuclein (WTS) transgenic mice were crossed with mice lacking mature lymphocytes (Rag2(-/-)). In this in vivo model, we quantified ?-synuclein aggregation in the substantia nigra (SN) and striatum and determined the numbers of innate and adaptive immune cells in the central nervous system (CNS). The activation state of resident and infiltrated CNS myeloid cells (M1 vs. M2) was further classified by gene and protein expression analyses. The impact of T and B lymphocytes on the phagocytic activity of microglia in the presence of ?-synuclein aggregates was addressed in BV2 microglia in vitro.Compared to WTS(+) Rag2(+/+) mice, where T but not B lymphocytes infiltrated the CNS, decreased amounts of ?-synuclein aggregates were found in WTS(+) Rag2(-/-) mice devoid of mature lymphocytes. The presence of T lymphocytes did not alter the number of Iba1(+) microglia but increased the frequency of the CD11b(+) CD45(hi) population in the CNS, indicative of an increased number of infiltrated macrophages. Moreover, the M1 phenotype was more prominent in WTS(+) Rag2(+/+) mice, whereas the M2 activation state was dominating in the absence of lymphocytes in WTS(+) Rag2(-/-) mice. In vitro, in the presence of T but not B lymphocytes, significantly less ?-synuclein was phagocytosed by BV2 microglia, further supporting the prevalence of the M1 phenotype in the presence of T lymphocytes.Peripheral T lymphocytes strongly contribute to increased ?-synuclein pathology via modulation of CNS myeloid cell function. In the presence of T lymphocytes, microglia phagocytosis of aggregated ?-synuclein is reduced, which increases the severity of synucleinopathy.
EVALuna2:4741

Inhibition of SARS-CoV-2 polymerase by nucleotide analogs from a single-molecule perspective - Seifert, Mona; Bera, Subhas Chandra; Van Nies, Pauline; Kirchdoerfer, Robert N.; Shannon, Ashleigh; Le, Thi-Tuyet-Nhung; Meng, Xiangzhi; Xia, Hongjie; Wood, James M.; Harris, Lawrence D.; Papini, Flavia S.; Arnold, Jamie J.; et al. (eLife, 2021)
eLife digest To multiply and spread from cell to cell, the virus responsible for COVID-19 (also known as SARS-CoV-2) must first replicate its genetic information. This process involves a 'polymerase' protein complex making a faithful copy by assembling a precise sequence of building blocks, or nucleotides. The only drug approved against SARS-CoV-2 by the US Food and Drug Administration (FDA), remdesivir, consists of a nucleotide analog, a molecule whose structure is similar to the actual building blocks needed for replication. If the polymerase recognizes and integrates these analogs into the growing genetic sequence, the replication mechanism is disrupted, and the virus cannot multiply. Most approaches to study this process seem to indicate that remdesivir works by stopping the polymerase and terminating replication altogether. Yet, exactly how remdesivir and other analogs impair the synthesis of new copies of the virus remains uncertain. To explore this question, Seifert, Bera et al. employed an approach called magnetic tweezers which uses a magnetic field to manipulate micro-particles with great precision. Unlike other methods, this technique allows analogs to be integrated under conditions similar to those found in cells, and to be examined at the level of a single molecule. The results show that contrary to previous assumptions, remdesivir does not terminate replication; instead, it causes the polymerase to pause and backtrack (which may appear as termination in other techniques). The same approach was then applied to other nucleotide analogs, some of which were also found to target the SARS-CoV-2 polymerase. However, these analogs are incorporated differently to remdesivir and with less efficiency. They also obstruct the polymerase in distinct ways. Taken together, the results by Seifert, Bera et al. suggest that magnetic tweezers can be a powerful approach to reveal how analogs interfere with replication. This information could be used to improve currently available analogs as well as develop new antiviral drugs that are more effective against SARS-CoV-2. This knowledge will be key at a time when treatments against COVID-19 are still lacking, and may be needed to protect against new variants and future outbreaks.
CRIS-Team WoS Importer:2021-10-29

Integrative transcriptome analysis of triple negative breast cancer profiles for identification of druggable targets - Arumugam, Poornima; Ramesh, Vignesh; Sampathkumar, Banupriya; Perumalsamy, Haribalan; Balusamy, Sri Renukadevi; Suganya, Kanagaraj; Balraj, Sudha; Nachimuthu, S. Kumar; Sundaravadivelu, Sumathi (Journal of biomolecular structure & dynamics, 2023)
As triple negative breast cancer (TNBC) lacks a specific target, exploration of abnormally expressed genes during the progression of TNBC is important for a better understanding of tumorigenesis and to find a specific target. We intended to figure out genes associated with TNBC, which can provide unique insights into gene dysregulation in TNBC while also pointing to new possible therapeutic targets for TNBC. A meta-analysis of multiple TNBC mRNA profiles was performed to identify consistently differentially expressed genes (CDGs). The pathways involved in modulating these genes were analyzed by MsigDB, and the interaction map was constructed. These CDGs were evaluated for their expression in cell lines, and drugs that could modulate the expression of CDGs were obtained using the connectivity map. CDGs were docked with doxorubicin and anethole, which is a phytocompound. The expression of selected CDGs was analyzed in MDA-MB-231 cells after treatment with doxorubicin and anethole. We found 45 CDGs, out of which 36 were upregulated and 9 were downregulated. MDA-MB-231 cell line was found to have high expression of CDGs, and drug that could modulate the expression of CDGs was doxorubicin. Docking results revealed that anethole and doxorubicin had good interaction with the CDGs especially with the genes AURKA, CDC6, DEPDC1, KIF23, KPNA2, MELK, CTNNB1, FLI1 and E2F1. Gene expression studies of the selected CDGs showed that the synergistic effect of anethole and doxorubicin effectively downregulated the expression. The CDGs identified from multiple cohorts have clinical significance and may be effectively exploited in the targeted therapy for TNBC. Communicated by Ramaswamy H. Sarma.
CRIS-Team Scopus Importer:2023-02-03
Keywords: anethole; docking; doxorubicin; transcriptomic profiles; Triple negative breast cancer

Interfering with nucleotide excision by the coronavirus 3 '-to-5 ' exoribonuclease - Chinthapatla, Rukesh; Sotoudegan, Mohamad; Srivastava, Pankaj; Anderson, Thomas K.; Moustafa, Ibrahim M.; Passow, Kellan T.; Kennelly, Samantha A.; Moorthy, Ramkumar; Dulin, David; Feng, Joy Y.; Harki, Daniel A.; Kirchdoerfer, Robert N.; et al. (Nucleic Acids Research, 2022)
Some of the most efficacious antiviral therapeutics are ribonucleos(t)ide analogs. The presence of a 3 '-to-5 ' proofreading exoribonuclease (ExoN) in coronaviruses diminishes the potency of many ribonucleotide analogs. The ability to interfere with ExoN activity will create new possibilities for control of SARS-CoV-2 infection. ExoN is formed by a 1:1 complex of nsp14 and nsp10 proteins. We have purified and characterized ExoN using a robust, quantitative system that reveals determinants of specificity and efficiency of hydrolysis. Double-stranded RNA is preferred over single-stranded RNA. Nucleotide excision is distributive, with only one or two nucleotides hydrolyzed in a single binding event. The composition of the terminal basepair modulates excision. A stalled SARS-CoV-2 replicase in complex with either correctly or incorrectly terminated products prevents excision, suggesting that a mispaired end is insufficient to displace the replicase. Finally, we have discovered several modifications to the 3 '-RNA terminus that interfere with or block ExoN-catalyzed excision. While a 3 '-OH facilitates hydrolysis of a nucleotide with a normal ribose configuration, this substituent is not required for a nucleotide with a planar ribose configuration such as that present in the antiviral nucleotide produced by viperin. Design of ExoN-resistant, antiviral ribonucleotides should be feasible.
CRIS-Team WoS Importer:2023-01-06

Interleukin-6 secretion upon acute psychosocial stress as a potential predictor of psychotherapy outcome in posttraumatic stress disorder - Rhein, Cosima; Hepp, Tobias; Kraus, Olga; von Majewski, Kristin; Lieb, Marietta; Rohleder, Nicolas; Erim, Yesim (Journal of Neural Transmission, 2021)
Posttraumatic stress disorder (PTSD) is a severe mental disorder that can develop after a traumatic event. PTSD has been reported to be associated with activation of the innate immune system, as measured by increased levels of pro-inflammatory cytokines. While it is well known that PTSD patients display increased levels of interleukin 6 (IL-6) when compared with healthy controls, the relationship between cytokine secretion and treatment outcome has been hardly investigated yet. The aim of this study was to assess the potential association of inflammatory activation and therapy outcome in PTSD. Before therapeutic intervention, we applied the Trier Social Stress Test (TSST) as a method to elicit psychosocial stress and an acute inflammatory response. IL-6 levels were measured in blood plasma of PTSD patients at different time points before and after the TSST. Severity of depressive, trauma-related, and somatic symptoms was assessed before and 8 weeks after trauma-focused treatment in a multimodal day clinic setting. We showed that high reactivity of IL-6 to psychosocial stress at the beginning of the therapy was associated with a negative therapy outcome in PTSD, especially regarding depressive symptoms. This study suggests plasma IL-6 reactivity as a potential molecular marker to predict treatment outcome in PTSD.
CRIS-Team Scopus Importer:2021-05-28
Keywords: BDI-II; Interleukin 6; Posttraumatic stress disorder; Psychotherapy; Therapy outcome; Trier Social Stress Test

Intracellular alpha-synuclein affects early maturation of primary oligodendrocyte progenitor cells - Ettle, Benjamin; Reiprich, Simone; Deußer, Janina; Schlachetzki, Johannes; Xiang, Wei; Prots, Iryna; Masliah, Eliezer; Winner, Beate; Wegner, Michael; Winkler, Jürgen (Molecular and Cellular Neuroscience, 2014)
Myelin loss is a widespread neuropathological hallmark of the atypical parkinsonian disorder multiple system atrophy (MSA). On a cellular level, MSA is characterized by alpha-synuclein (aSyn)-positive glial cytoplasmic inclusions (GCIs) within mature oligodendrocytes leading to demyelination as well as axonal and neuronal loss. Oligodendrocyte progenitor cells (OPCs) represent a proliferative cell population distributed throughout the adult mammalian central nervous system. During remyelination, OPCs are recruited to sites of demyelination, differentiate, and finally replace dysfunctional mature oligodendrocytes. However, comprehensive studies investigating OPCs and remyelination processes in MSA are lacking. In the present study, we therefore investigate the effect of human aSyn (h-aSyn) on early primary rat OPC maturation. Upon lentiviral transduction, h-aSyn expressing OPCs exhibit fewer and shorter primary processes at the initiation of differentiation. Until day 4 of a 6day differentiation paradigm, h-aSyn expressing OPCs further show a severely delayed maturation evidenced by reduced myelin gene expression and increased levels of the progenitor marker platelet derived growth factor receptor-alpha (PDGFR?). Matching these results, OPCs that take up extracellular recombinant h-aSyn exhibit a similar delayed differentiation. In both experimental setups however, myelin gene expression is restored at day 6 of differentiation paralleled by decreased intracellular h-aSyn levels indicating a reverse correlation of h-aSyn and the differentiation potential of OPCs. Taken together, these findings suggest a tight link between the intracellular level of h-aSyn and maturation capacity of primary OPCs.
EVALuna2:4696

Kdm6b and Pmepa1 as Targets of Bioelectrically and Behaviorally Induced Activin A Signaling - Link, Andrea; Kurinna, Svitlana; Havlicek, Steven; Lehnert, Sandra; Reichel, Martin; Kornhuber, Johannes; Winner, Beate; Huth, Tobias; Zheng, Fang; Werner, Sabine; Alzheimer, Christian (Molecular Neurobiology, 2016)
The transforming growth factor-? (TGF-?) family member activin A exerts multiple neurotrophic and protective effects in the brain. Activin also modulates cognitive functions and affective behavior and is a presumed target of antidepressant therapy. Despite its important role in the injured and intact brain, the mechanisms underlying activin effects in the CNS are still largely unknown. Our goal was to identify the first target genes of activin signaling in the hippocampus in vivo. Electroconvulsive seizures, a rodent model of electroconvulsive therapy in humans, were applied to C57BL/6J mice to elicit a strong increase in activin A signaling. Chromatin immunoprecipitation experiments with hippocampal lysates subsequently revealed that binding of SMAD2/3, the intracellular effectors of activin signaling, was significantly enriched at the Pmepa1 gene, which encodes a negative feedback regulator of TGF-? signaling in cancer cells, and at the Kdm6b gene, which encodes an epigenetic regulator promoting transcriptional plasticity. Underlining the significance of these findings, activin treatment also induced PMEPA1 and KDM6B expression in human forebrain neurons generated from embryonic stem cells suggesting interspecies conservation of activin effects in mammalian neurons. Importantly, physiological stimuli such as provided by environmental enrichment proved already sufficient to engender a rapid and significant induction of activin signaling concomitant with an upregulation of Pmepa1 and Kdm6b expression. Taken together, our study identified the first target genes of activin signaling in the brain. With the induction of Kdm6b expression, activin is likely to gain impact on a presumed epigenetic regulator of activity-dependent neuronal plasticity.
EVALuna2:2488

Ketos: Clinical decision support and machine learning as a service – A training and deployment platform based on Docker, OMOP-CDM, and FHIR Web Services - Gründner, Julian; Schwachhofer, Thorsten; Sippl, Phillip; Wolf, Nicolas; Erpenbeck, Marcel; Gulden, Christian; Kapsner, Lorenz A.; Zierk, Jakob; Mate, Sebastian; Stürzl, Michael; Croner, Roland; Prokosch, Hans-Ulrich; et al. (PLoS ONE, 2019)
Background and objective To take full advantage of decision support, machine learning, and patient-level prediction models, it is important that models are not only created, but also deployed in a clinical setting. The KETOS platform demonstrated in this work implements a tool for researchers allowing them to perform statistical analyses and deploy resulting models in a secure environment. Methods The proposed system uses Docker virtualization to provide researchers with reproducible data analysis and development environments, accessible via Jupyter Notebook, to perform statistical analysis and develop, train and deploy models based on standardized input data. The platform is built in a modular fashion and interfaces with web services using the Health Level 7 (HL7) Fast Healthcare Interoperability Resources (FHIR) standard to access patient data. In our prototypical implementation we use an OMOP common data model (OMOP-CDM) database. The architecture supports the entire research lifecycle from creating a data analysis environment, retrieving data, and training to final deployment in a hospital setting. Results We evaluated the platform by establishing and deploying an analysis and end user application for hemoglobin reference intervals within the University Hospital Erlangen. To demonstrate the potential of the system to deploy arbitrary models, we loaded a colorectal cancer dataset into an OMOP database and built machine learning models to predict patient outcomes and made them available via a web service. We demonstrated both the integration with FHIR as well as an example end user application. Finally, we integrated the platform with the open source DataSHIELD architecture to allow for distributed privacy preserving data analysis and training across networks of hospitals. Conclusion The KETOS platform takes a novel approach to data analysis, training and deploying decision support models in a hospital or healthcare setting. It does so in a secure and privacy-preserving manner, combining the flexibility of Docker virtualization with the advantages of standardized vocabularies, a widely applied database schema (OMOP-CDM), and a standardized way to exchange medical data (FHIR).
CRIS-Team Scopus Importer:2019-10-11

Knockdown of Lamin B1 and the Corresponding Lamin B Receptor Leads to Changes in Heterochromatin State and Senescence Induction in Malignant Melanoma - Lämmerhirt, Lisa; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Pommer, Michaela; Zimmermann, Tom; Kluge, Viola; Matthies, Alexander Oliver; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2022)
Modifications in nuclear structures of cells are implicated in several diseases including cancer. They result in changes in nuclear activity, structural dynamics and cell signalling. However, the role of the nuclear lamina and related proteins in malignant melanoma is still unknown. Its molecular characterisation might lead to a deeper understanding and the development of new therapy approaches. In this study, we analysed the functional effects of dysregulated nuclear lamin B1 (LMNB1) and its nuclear receptor (LBR). According to their cellular localisation and function, we revealed that these genes are crucially involved in nuclear processes like chromatin organisation. RNA sequencing and differential gene expression analysis after knockdown of LMNB1 and LBR revealed their implication in important cellular processes driving ER stress leading to senescence and changes in chromatin state, which were also experimentally validated. We determined that melanoma cells need both molecules independently to prevent senescence. Hence, downregulation of both molecules in a BRAFV600E melanocytic senescence model as well as in etoposide-treated melanoma cells indicates both as potential senescence markers in melanoma. Our findings suggest that LMNB1 and LBR influence senescence and affect nuclear processes like chromatin condensation and thus are functionally relevant for melanoma progression.
CRIS-Team Scopus Importer:2022-08-05
Keywords: chromatin state; heterochromatin foci; LBR; LMNB1; melanoma; nuclear lamina; senescence

Light and sound - emerging imaging techniques for inflammatory bowel disease - Knieling, Ferdinand; Waldner, Maximilian (World Journal of Gastroenterology, 2016)
Patients with inflammatory bowel disease are known to have a high demand of recurrent evaluation for therapy and disease activity. Further, the risk of developing cancer during the disease progression is increasing from year to year. New, mostly non-radiant, quick to perform and quantitative methods are challenging, conventional endoscopy with biopsy as gold standard. Especially, new physical imaging approaches utilizing light and sound waves have facilitated the development of advanced functional and molecular modalities. Besides these advantages they hold the promise to predict personalized therapeutic responses and to spare frequent invasive procedures. Within this article we highlight their potential for initial diagnosis, assessment of disease activity and surveillance of cancer development in established techniques and recent advances such as wide-view full-spectrum endoscopy, chromoendoscopy, autofluorescence endoscopy, endocytoscopy, confocal laser endoscopy, multiphoton endoscopy, molecular imaging endoscopy, B-mode and Doppler ultrasound, contrast-enhanced ultrasound, ultrasound molecular imaging, and elastography.
EVALuna2:2167

Longitudinal Assessment of Examiner Experience and the Accuracy of Sonographic Fetal Weight Estimation at Term - Faschingbauer, Florian; Heimrich, Jutta; Raabe, Eva; Kehl, Sven; Schneider, Michael; Schmid, Matthias; Beckmann, Matthias; Hepp, Tobias; Luebke, Anika; Mayr, Andreas; Schild, Ralf L. (Journal of Ultrasound in Medicine, 2017)
OBJECTIVES: To evaluate the influence of examiner experience on the accuracy of sonographic weight estimation and to further analyze examiners' individual learning curves. METHODS: In this multicenter study, 4613 sonographic weight estimations performed by 18 examiners at the beginning of their ultrasound training were included. To assess the effect of experience on the accuracy of weight estimation, a multivariable mixed regression model analysis was performed, with percentage error and absolute percentage error as outcome variables and the examiner, the examiner's experience (number of examinations), birth weight, gestational age, scan-to-delivery interval, and maternal body mass index as fixed effects and the perinatal center as random intercepts. To further analyze the individual learning curves of the examiners, the cumulative summation technique was used. RESULTS: Regression analyses showed a significant influence of the number of examinations on the accuracy of sonographic weight estimation after adjustment for the above-mentioned parameters (P < .001). A typical learning curve with improving accuracy was found until approximately 200 examinations. Between 200 and 300 examinations, the diagnostic performance started to deteriorate again, with a continuous decrease until the end of the study period. Cumulative summation charts representing individual learning curves varied greatly between different examiners. CONCLUSIONS: These findings indicate the great importance of continuous quality control systems in sonographic weight estimation.
EVALuna2:34214

Lysophosphatidic acid activates satellite glia cells and Schwann cells - Robering, Jan Willem; Gebhardt, Lisa; Wolf, Katharina; Kühn, Helen; Kremer, Andreas; Fischer, Michael Jochen Marco (Glia, 2019)
Pruritus is a common and disabling symptom in patients with hepatobiliary disorders, particularly in those with cholestatic features. Serum levels of lysophosphatidic acid (LPA) and its forming enzyme autotaxin were increased in patients suffering from hepatic pruritus, correlated with itch severity and response to treatment. Here we show that in a culture of dorsal root ganglia LPA 18:1 surprisingly activated a large fraction of satellite glia cells, and responses to LPA 18:1 correlated inversely with responses to neuronal expressed transient receptor potential channels. LPA 18:1 caused only a marginal activation of heterologously expressed TRPV1, and responses in dorsal root ganglion cultures from TRPV1-deficient mice were similar to controls. LPA 18:1 desensitized subsequent responsiveness to chloroquine and TGR5 agonist INT-777. The LPA 18:1-induced increase in cytoplasmatic calcium stems from the endoplasmatic reticulum. LPA receptor expression in dorsal root ganglia and Schwann cells, LPAR1 immunohistochemistry, and pharmacological results indicate a signaling pathway through LPA receptor 1. Peripheral rat Schwann cells, which are of glial lineage as the satellite glia cells, were also responsive to LPA 18:1. Summarizing, LPA 18:1 primarily activates rather glial cells than neurons, which may subsequently modulate neuronal responsiveness and sensory sensations such as itch and pain.
CRIS-Team WoS Importer:2019-04-04

Magnetic resonance-determined sodium removal from tissue stores in hemodialysis patients - Dahlmann, Anke; Dörfelt, Kathrin; Eicher, Florian; Linz, Peter; Kopp, Christoph; Mössinger, Irina; Horn, Stephan; Bueschges-Seraphin, Beatrix; Wabel, Peter; Hammon, Matthias; Eckardt, Kai-Uwe; Kotanko, Peter; et al. (Kidney International, 2015)
We have previously reported that sodium is stored in skin and muscle. The amounts stored in hemodialysis (HD) patients are unknown. We determined whether (23)Na magnetic resonance imaging (sodium-MRI) allows assessment of tissue sodium and its removal in 24 HD patients and 27 age-matched healthy controls. We also studied 20 HD patients before and shortly after HD with a batch dialysis system with direct measurement of sodium in dialysate and ultrafiltrate. Age was associated with higher tissue sodium content in controls. This increase was paralleled by an age-dependent decrease of circulating levels of vascular endothelial growth factor-C (VEGF-C). Older (>60 years) HD patients showed increased sodium and water in skin and muscle and lower VEGF-C levels compared with age-matched controls. After HD, patients with low VEGF-C levels had significantly higher skin sodium content compared with patients with high VEGF-C levels (low VEGF-C: 2.3 ng/ml and skin sodium: 24.3 mmol/l; high VEGF-C: 4.1 ng/ml and skin sodium: 18.2 mmol/l). Thus, sodium-MRI quantitatively detects sodium stored in skin and muscle in humans and allows studying sodium storage reduction in ESRD patients. Age and VEGF-C-related local tissue-specific clearance mechanisms may determine the efficacy of tissue sodium removal with HD. Prospective trials on the relationship between tissue sodium content and hard end points could provide new insights into sodium homeostasis, and clarify whether increased sodium storage is a cardiovascular risk factor.
EVALuna2:3717

Mechanism of assembly of an elongation-competent SARS-CoV-2 replication transcription complex - Klein, Misha; Bera, Subhas Chandra; Anderson, Thomas K.; Wang, Bing; Papini, Flavia S.; Arnold, Jamie J.; Cameron, Craig E.; Depken, Martin; Kirchdoerfer, Robert N.; Artsimovitch, Irina; Dulin, David (Biophysical Journal, 2023)
CRIS-Team Scopus Importer:2023-02-24

Metabolic impairment of non-small cell lung cancers by mitochondrial HSPD1 targeting - Parma, Beatrice; Ramesh, Vignesh; Gollavilli, Paradesi Naidu; Siddiqui, Aarif; Pinna, Luisa; Schwab, Annemarie; Marschall, Sabine; Zhang, Shuman; Pilarsky, Christian; Napoli, Francesca; Volante, Marco; Urbanczyk, Sophia; et al. (Journal of Experimental & Clinical Cancer Research, 2021)
Background The identification of novel targets is of paramount importance to develop more effective drugs and improve the treatment of non-small cell lung cancer (NSCLC), the leading cause of cancer-related deaths worldwide. Since cells alter their metabolic rewiring during tumorigenesis and along cancer progression, targeting key metabolic players and metabolism-associated proteins represents a valuable approach with a high therapeutic potential. Metabolic fitness relies on the functionality of heat shock proteins (HSPs), molecular chaperones that facilitate the correct folding of metabolism enzymes and their assembly in macromolecular structures. Methods Gene fitness was determined by bioinformatics analysis from available datasets from genetic screenings. HSPD1 expression was evaluated by immunohistochemistry from formalin-fixed paraffin-embedded tissues from NSCLC patients. Real-time proliferation assays with and without cytotoxicity reagents, colony formation assays and cell cycle analyses were used to monitor growth and drug sensitivity of different NSCLC cells in vitro. In vivo growth was monitored with subcutaneous injections in immune-deficient mice. Cell metabolic activity was analyzed through extracellular metabolic flux analysis. Specific knockouts were introduced by CRISPR/Cas9. Results We show heat shock protein family D member 1 (HSPD1 or HSP60) as a survival gene ubiquitously expressed in NSCLC and associated with poor patients' prognosis. HSPD1 knockdown or its chemical disruption by the small molecule KHS101 induces a drastic breakdown of oxidative phosphorylation, and suppresses cell proliferation both in vitro and in vivo. By combining drug profiling with transcriptomics and through a whole-genome CRISPR/Cas9 screen, we demonstrate that HSPD1-targeted anti-cancer effects are dependent on oxidative phosphorylation and validated molecular determinants of KHS101 sensitivity, in particular, the creatine-transporter SLC6A8 and the subunit of the cytochrome c oxidase complex COX5B. Conclusions These results highlight mitochondrial metabolism as an attractive target and HSPD1 as a potential theranostic marker for developing therapies to combat NSCLC.
CRIS-Team WoS Importer:2021-08-20

Mild Salt-Sensitive Hypertension in Genetically Determined Low Nephron Number is Associated with Chloride but Not Sodium Retention - Benz, Kerstin; Schlote, Julia; Daniel, Christoph; Kopp, Christoph; Dahlmann, Anke; Schröder, Agnes; Cordasic, Nada; Klanke, Bernd; Hilgers, Karl Friedrich; Titze, Jens; Amann, Kerstin Ute (Kidney & Blood Pressure Research, 2018)
BACKGROUND/AIMS: One potential pathomechanism how low nephron number leads to hypertension in later life is altered salt handling. We therefore evaluated changes in electrolyte and water content in wildtype (wt) and GDNF+/- mice with a 30% reduction of nephron number. METHODS: 32 GDNF+/- and 36 wt mice were fed with low salt (LSD, 0.03%, normal drinking water) or high salt (HSD, 4%, 0.9% drinking water) diet for 4 weeks. Blood pressure was continuously measured by telemetry in a subgroup. At the end of the experiment and after standardized ashing processes electrolyte- and water contents of the skin and the total body were determined. RESULTS: We found higher blood pressure in high salt treated GDNF+/-compared to wt mice. Of interest, we could not confirm an increase in total-body sodium as predicted by prevailing explanations, but found increased total body and skin chloride that interestingly correlated with relative kidney weight. CONCLUSION: We hereby firstly report significant total body and skin chloride retention in salt sensitive hypertension of GDNF+/-mice with genetically determined lower nephron number. Thus, in contrast to the prevailing opinion our data argue for the involvement of non-volume related mechanisms.
EVALuna2:34423

Mixture density networks for the indirect estimation of reference intervals - Hepp, Tobias; Zierk, Jakob; Rauh, Manfred; Metzler, Markus; Seitz, Sarem (BMC Bioinformatics, 2022)
Background: Reference intervals represent the expected range of physiological test results in a healthy population and are essential to support medical decision making. Particularly in the context of pediatric reference intervals, where recruitment regulations make prospective studies challenging to conduct, indirect estimation strategies are becoming increasingly important. Established indirect methods enable robust identification of the distribution of “healthy” samples from laboratory databases, which include unlabeled pathologic cases, but are currently severely limited when adjusting for essential patient characteristics such as age. Here, we propose the use of mixture density networks (MDN) to overcome this problem and model all parameters of the mixture distribution in a single step. Results: Estimated reference intervals from varying settings with simulated data demonstrate the ability to accurately estimate latent distributions from unlabeled data using different implementations of MDNs. Comparing the performance with alternative estimation approaches further highlights the importance of modeling the mixture component weights as a function of the input in order to avoid biased estimates for all other parameters and the resulting reference intervals. We also provide a strategy to generate partially customized starting weights to improve proper identification of the latent components. Finally, the application on real-world hemoglobin samples provides results in line with current gold standard approaches, but also suggests further investigations with respect to adequate regularization strategies in order to prevent overfitting the data. Conclusions: Mixture density networks provide a promising approach capable of extracting the distribution of healthy samples from unlabeled laboratory databases while simultaneously and explicitly estimating all parameters and component weights as non-linear functions of the covariate(s), thereby allowing the estimation of age-dependent reference intervals in a single step. Further studies on model regularization and asymmetric component distributions are warranted to consolidate our findings and expand the scope of applications.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Distributional regression; Latent class regression; Mixture density networks; Reference intervals

Modulation of urelumab glycosylation separates immune stimulatory activity from organ toxicity - Reitinger, Carmen; Ipsen Escobedo, Andrea; Hornung, Chiara; Heger, Lukas; Dudziak, Diana; Lux, Anja; Nimmerjahn, Falk (Frontiers in Immunology, 2022)
Checkpoint control and immunomodulatory antibodies have become important tools for modulating tumor or self-reactive immune responses. A major issue preventing to make full use of the potential of these immunomodulatory antibodies are the severe side-effects, ranging from systemic cytokine release syndrome to organ-specific toxicities. The IgG Fc-portion has been demonstrated to contribute to both, the desired as well as the undesired antibody activities of checkpoint control and immunomodulatory antibodies via binding to cellular Fcγ-receptors (FcγR). Thus, choosing IgG subclasses, such as human IgG4, with a low ability to interact with FcγRs has been identified as a potential strategy to limit FcγR or complement pathway dependent side-effects. However, even immunomodulatory antibodies on the human IgG4 background may interact with cellular FcγRs and show dose limiting toxicities. By using a humanized mouse model allowing to study the immunomodulatory activity of human checkpoint control antibodies in vivo, we demonstrate that deglycosylation of the CD137-specific IgG4 antibody urelumab results in an amelioration of liver toxicity, while maintaining T cell stimulatory activity. In addition, our results emphasize that antibody dosing impacts the separation of side-effects of urelumab from its therapeutic activity via IgG deglycosylation. Thus, glycoengineering of human IgG4 antibodies may be a possible approach to limit collateral damage by immunomodulatory antibodies and allow for a greater therapeutic window of opportunity.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD137; Fc-receptors; glycosylation; therapeutic antibody; urelumab

Monovalent Salt Dependence of the Bacterial RNA Polymerase Open Complex Dynamics - Bera, Subhas Chandra; Seifert, Mona; Ostrofet, Eugeniu; Spermann, Monika; Papini, Flavia Stal; Malinen, Anssi M.; Dulin, David (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

Multispectral optoacoustic tomography enables assessment of disease activity in paediatric inflammatory bowel disease - Regensburger, Adrian; Eckstein, Markus; Wetzl, Matthias; Raming, Roman; Paulus, Lars-Philip; Bühler, Adrian; Nedoschill, Emmanuel; Danko, Vera; Jüngert, Jörg; Wagner, Alexandra; Schnell, Alexander; Rückel, Aline; et al. (Photoacoustics, 2024)
Multispectral optoacoustic tomography (MSOT) allows non-invasive molecular disease activity assessment in adults with inflammatory bowel disease (IBD). In this prospective pilot-study, we investigated, whether increased levels of MSOT haemoglobin parameters corresponded to inflammatory activity in paediatric IBD patients, too. 23 children with suspected IBD underwent MSOT of the terminal ileum and sigmoid colon with standard validation (e.g. endoscopy). In Crohn‘s disease (CD) and ulcerative colitis (UC) patients with endoscopically confirmed disease activity, MSOT total haemoglobin (HbT) signals were increased in the terminal ileum of CD (72.1 ± 13.0 a.u. vs. 32.9 ± 15.4 a.u., p = 0.0049) and in the sigmoid colon of UC patients (62.9 ± 13.8 a.u. vs. 35.1 ± 16.3 a.u., p = 0.0311) as compared to controls, respectively. Furthermore, MSOT haemoglobin parameters correlated well with standard disease activity assessment (e.g. SES-CD and MSOT HbT (rs =0.69, p = 0.0075). Summarizing, MSOT is a novel technology for non-invasive molecular disease activity assessment in paediatric patients with inflammatory bowel disease.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Multispectral optoacoustic tomography; Optoacoustic imaging; Paediatric inflammatory bowel disease

Multispectral Optoacoustic Tomography in Crohn's Disease: Noninvasive Imaging of Disease Activity - Waldner, Maximilian; Knieling, Ferdinand; Egger, Cornelia; Morscher, Stefan; Claussen, Jing; Vetter, Marcel; Kielisch, Christian; Fischer, Sören; Pfeifer, Lukas; Hagel, Alexander; Görtz, Rüdiger; Wildner, Dane; et al. (Gastroenterology, 2016)
EVALuna2:2071

Na-23-MRI reveals sodium accumulation in skin of patients with relapsing-remitting multiple sclerosis - Huhn, K.; Linz, Peter; Pemsel, F.; Waschbisch, Anne; Lee, De-Hyung; Kopp, C.; Uder, Michael; Titze, J.; Mueller, D. N.; Linker, Ralf (2015)
EVALuna2:14485

NCOA3 AMPLIFIES PROFIBROTIC TRANSCRIPTIONAL PROGRAMS IN SYSTEMIC SCLEROSIS - Dees, Clara; Pötter, Sebastian; Fuchs, Maximilian; Bergmann, Christina; Matei, Alexandru-Emil; Györfi, Andrea-Hermina; Soare, A.; Ramming, Andreas; Ceppi, Paolo; Schett, Georg; Kunz, Meik; Distler, H. W. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

New software analyses increase the reliability of measurements of retinal arterioles morphology by scanning laser Doppler flowmetry in humans - Harazny, Joanna M.; Raff, Ulrike; Welzenbach, Juergen; Ott, Christian; Ritt, Martin; Lehmann, Maria; Michelson, Georg; Schmieder, Roland; Lehmann, Maria (Journal of Hypertension, 2011)
The investigation of the retinal arterioles offers the unique opportunity to analyze in vivo arteriolar remodeling in arterial hypertension in humans. We analyzed the reliability of assessing retinal arteriolar morphology with our new version of the software analyses for scanning laser Doppler flowmetry.In the test-retest reliability study, 10 eyes of 10 healthy persons were measured during 5 days under routine laboratory conditions with the Heidelberg Retinal Flowmetry. In a second study, interobserver and intraobserver reliability was analyzed from retinal images of 18 patients with three types of arterial hypertension by three readers and the most experienced reader analyzed all images twice on two different days. Images were analyzed by the old and the newly developed software versions. To characterize the reliability, the coefficients of variation were calculated.The test-retest study analyzed with the new program showed that the variation coefficients of vessel and lumen diameter, wall thickness, wall/lumen ratio and new calculated parameter: lumen/vessel diameter ratio of retinal arterioles were significantly less than 10%, with the exception of the wall cross-sectional area (12.5%). The interobserver and intraobserver reliability showed in nearly all circumstances coefficients of variations of less than 10% and did not differ across various readers and patient groups.The new software 'SLDF version 4.0' clearly improved the reliability of assessing the structural parameters of the retinal arterioles. The application delivers reliable measurements of the retinal arteriolar structure in vivo in human
EVALuna2:3487

Observation of two-step aggregation kinetics of amyloid-beta proteins from fractal analysis - Mukhopadhyay, Soham; Bera, Subhas Chandra; Ramola, Kabir (Physical Biology, 2022)
Self-aggregation in proteins has long been studied and modeled due to its ubiquity and importance in many biological contexts. Several models propose a two step aggregation mechanism, consisting of linear growth of fibrils and secondary growth involving branch formation. Single molecule imaging techniques such as total internal reflection fluorescence (TIRF) microscopy can provide direct evidence of such mechanisms, however, analyzing such large data-sets is challenging. In this paper, we analyze for the first time, images of growing amyloid fibrils obtained from TIRF microscopy using the techniques of fractal geometry, which provides a natural framework to disentangle the two types of growth mechanisms at play. We find that after an initial linear growth phase, identified by a plateau in the average fractal dimension with time, the occurrence of branching events leads to a further increase in the fractal dimension, with a final saturation value approximate to 2. This provides direct evidence of the two-step nature of the aggregation kinetics of amyloid-beta proteins, with an initial linear elongation phase followed by branching at later times.
CRIS-Team WoS Importer:2022-05-13

Oligomer-prone E57K-mutant alpha-synuclein exacerbates integration deficit of adult hippocampal newborn neurons in transgenic mice - Regensburger, Martin; Schreglmann, Sebastian R.; Stoll, Svenja; Rockenstein, Edward; Loskarn, Sandra; Xiang, Wei; Masliah, Eliezer; Winner, Beate (Brain Structure & Function, 2017)
In the adult mammalian hippocampus, new neurons are constantly added to the dentate gyrus. Adult neurogenesis is impaired in several neurodegenerative mouse models including ?-synuclein (a-syn) transgenic mice. Among different a-syn species, a-syn oligomers were reported to be the most toxic species for neurons. Here, we studied the impact of wild-type vs. oligomer-prone a-syn on neurogenesis. We compared the wild-type a-syn transgenic mouse model (Thy1-WTS) to its equivalent transgenic for oligomer-prone E57K-mutant a-syn (Thy1-E57K). Transgenic a-syn was highly expressed within the hippocampus of both models, but was not present within adult neural stem cells and neuroblasts. Proliferation and survival of newly generated neurons were unchanged in both transgenic models. Thy1-WTS showed a minor integration deficit regarding mushroom spine density of newborn neurons, whereas Thy1-E57K exhibited a severe reduction of all spines. We conclude that cell-extrinsic a-syn impairs mushroom spine formation of adult newborn neurons and that oligomer-prone a-syn exacerbates this integration deficit. Moreover, our data suggest that a-syn reduces the survival of newborn neurons by a cell-intrinsic mechanism during the early neuroblast development. The finding of increased spine pathology in Thy1-E57K is a new pathogenic function of oligomeric a-syn and precedes overt neurodegeneration. Thus, it may constitute a readout for therapeutic approaches.
EVALuna2:4766

Pain relief in a neuropathy patient by lacosamide: Proof of principle of clinical translation from patient-specific iPS cell-derived nociceptors - Namer, Barbara; Schmidt, Diana; Eberhardt, Esther; Maroni, Michele; Dorfmeister, Eva; Kleggetveit, Inge Petter; Kaluza, Luisa; Meents, Jannis; Gerlach, Aaron; Lin, Zhixin; Winterpacht, Andreas; Dragicevic, Elena; et al. (EBioMedicine, 2018)
BACKGROUND: Small fiber neuropathy (SFN) is a severe and disabling chronic pain syndrome with no causal and limited symptomatic treatment options. Mechanistically based individual treatment is not available. We report an in-vitro predicted individualized treatment success in one therapy-refractory Caucasian patient suffering from SFN for over ten years. METHODS: Intrinsic excitability of human induced pluripotent stem cell (iPSC) derived nociceptors from this patient and respective controls were recorded on multi-electrode (MEA) arrays, in the presence and absence of lacosamide. The patient's pain ratings were assessed by a visual analogue scale (10: worst pain, 0: no pain) and treatment effect was objectified by microneurography recordings of the patient's single nerve C-fibers. FINDINGS: We identified patient-specific changes in iPSC-derived nociceptor excitability in MEA recordings, which were reverted by the FDA-approved compound lacosamide in vitro. Using this drug for individualized treatment of this patient, the patient's pain ratings decreased from 7.5 to 1.5. Consistent with the pain relief reported by the patient, microneurography recordings of the patient's single nerve fibers mirrored a reduced spontaneous nociceptor (C-fiber) activity in the patient during lacosamide treatment. Microneurography recordings yielded an objective measurement of altered peripheral nociceptor activity following treatment. INTERPRETATION: Thus, we are here presenting one example of successful patient specific precision medicine using iPSC technology and individualized therapeutic treatment based on patient-derived sensory neurons.
EVALuna2:35119

Pattern of Functional TTX-Resistant Sodium Channels Reveals a Developmental Stage of Human iPSC- and ESC-Derived Nociceptors - Eberhardt, Esther; Havlicek, Steven; Schmidt, Diana; Link, Andrea; Neacsu, Cristian; Kohl, Zacharias; Hampl, Martin; Kist, Andreas; Klinger, Alexandra; Nau, Carla; Schüttler, Jürgen; Alzheimer, Christian; et al. (Stem Cell Reports, 2015)
Human pluripotent stem cells (hPSCs) offer the opportunity to generate neuronal cells, including nociceptors. Using a chemical-based approach, we generated nociceptive sensory neurons from HUES6 embryonic stem cells and retrovirally reprogrammed induced hPSCs derived from fibroblasts. The nociceptive neurons expressed respective markers and showed tetrodotoxin-sensitive (TTXs) and -resistant (TTXr) voltage-gated sodium currents in patch-clamp experiments. In contrast to their counterparts from rodent dorsal root ganglia, TTXr currents of hPSC-derived nociceptors unexpectedly displayed a significantly more hyperpolarized voltage dependence of activation and fast inactivation. This apparent discrepancy is most likely due to a substantial expression of the developmentally important sodium channel NAV1.5. In view of the obstacles to recapitulate neuropathic pain in animal models, our data advance hPSC-derived nociceptors as a better model to study developmental and pathogenetic processes in human nociceptive neurons and to develop more specific small molecules to attenuate pain.
EVALuna2:2465

Pausing controls branching between productive and non-productive pathways during initial transcription in bacteria - Dulin, David; Bauer, David L. V.; Malinen, Anssi M.; Bakermans, Jacob J. W.; Kaller, Martin; Morichaud, Zakia; Petushkov, Ivan; Depken, Martin; Brodolin, Konstantin; Kulbachinskiy, Andrey; Kapanidis, Achillefs N. (Nature Communications, 2018)
Transcription in bacteria is controlled by multiple molecular mechanisms that precisely regulate gene expression. It has been recently shown that initial RNA synthesis by the bacterial RNA polymerase (RNAP) is interrupted by pauses; however, the pausing determinants and the relationship of pausing with productive and abortive RNA synthesis remain poorly understood. Using single-molecule FRET and biochemical analysis, here we show that the pause encountered by RNAP after the synthesis of a 6-nt RNA (ITC6) renders the promoter escape strongly dependent on the NTP concentration. Mechanistically, the paused ITC6 acts as a checkpoint that directs RNAP to one of three competing pathways: productive transcription, abortive RNA release, or a new unscrunching/scrunching pathway. The cyclic unscrunching/scrunching of the promoter generates a long-lived, RNA-bound paused state; the abortive RNA release and DNA unscrunching are thus not as tightly linked as previously thought. Finally, our new model couples the pausing with the abortive and productive outcomes of initial transcription.
EVALuna2:34307

Periarticular Bone Loss in Arthritis Is Induced By Autoantibodies Against Citrullinated Vimentin - Engdahl, Cecilia; Bang, Holger; Dietel, Katharina; Lang, Stefanie; Harre, Ulrike; Schett, Georg (2016)
EVALuna2:33224

Phosphorylation Modulates the Subcellular Localization of SOX11 - Balta, Elli-Anna; Wittmann, Marie-Theres; Jung, Matthias; Sock, Elisabeth; Häberle, Benjamin; Heim, Birgit; Von Zweydorf, Felix; Heppt, Jana; von Wittgenstein, Julia; Gloeckner, Christian Johannes; Lie, Dieter Chichung (Frontiers in Molecular Neuroscience, 2018)
SOX11 is a key Transcription Factor (TF) in the regulation of embryonic and adult neurogenesis, whose mutation has recently been linked to an intellectual disability syndrome in humans. SOX11's transient activity during neurogenesis is critical to ensure the precise execution of the neurogenic program. Here, we report that SOX11 displays differential subcellular localizations during the course of neurogenesis. Western-Blot analysis of embryonic mouse brain lysates indicated that SOX11 is post-translationally modified by phosphorylation. Using Mass Spectrometry, we found 10 serine residues in the SOX11 protein that are putatively phosphorylated. Systematic analysis of phospho-mutant SOX11 resulted in the identification of the S30 residue, whose phosphorylation promotes nuclear over cytoplasmic localization of SOX11. Collectively, these findings uncover phosphorylation as a novel layer of regulation of the intellectual disability gene Sox11.
EVALuna2:35742

Polyhydroxyphenylvalerate/polycaprolactone nanofibers improve the life-span and mechanoresponse of human IPSC-derived cortical neuronal cells - Cerrone, Federico; Pozner, Tatyana; Siddiqui, Aarif; Ceppi, Paolo; Winner, Beate; Rajendiran, Murugan; Babu, Ramesh; Ibrahim, Hossam S.; Rodriguez, Brian J.; Winkler, Jürgen; Murphy, Keith J.; O'Connor, Kevin E. (Materials Science and Engineering C, 2020)
The physico-chemical characteristics of the extracellular matrix (ECM) cause mechanical cues that could elicit responses in the survival rate of cortical neuronal cells. Efficient neurite outgrowth in vitro, is critical for successful cultivation of cortical neuronal cells and the potential for attempts at regeneration of the central nervous system (CNS) in vivo. Relatively soft and hydrophilic, microbially synthesized aromatic polyester, polyhydroxyphenylvalerate (PHPV) was blended 50:50 with the stiff and hydrophobic polycaprolactone (PCL) and electrospun in microfibers for use in a 3D (CellCrown™) configuration and in a 2D coverslip coated configuration. This blend allows a 2.3-fold increase in the life-span of human induced pluripotent stem derived cortical neuronal cells (hiPS) compared to pure PCL fibers. HiPS-derived cortical neuronal cells grown on PHPV/PCL fibers show a 3.8-fold higher cumulative neurite elaboration compared to neurites grown on PCL fibers only. 96% of cortical neuronal cells die after 8 days of growth when plated on PCL fibers alone while >83% and 55% are alive on PHPV/PCL fibers on day 8 and day 17, respectively. An increased migration rate of cortical neuronal cells is also promoted by the blend compared to the PCL fibers alone. The critical survival rate improvement of hiPS derived cortical neuronal cells on PHPV/PCL blend holds promise in using these biocompatible nanofibers as implantable materials for regenerative purposes of an active cortical neuronal population after full maturation in vitro.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Cortical neurons; Electrospinning; HiPSC; Mechanoresponse; Neuroregeneration; Polyhydroxyalkanoates

Polymorphisms in the Hsp70 gene locus are genetically associated with systemic lupus erythematosus - Fuernrohr, Barbara G.; Wach, Sven; Kelly, Jennifer A.; Haslbeck, Martin; Weber, Christian K.; Stach, Christian M.; Hueber, Axel J.; Graef, Daniela; Spriewald, Bernd M.; Manger, Karin; Herrmann, Martin; Kaufman, Kenneth M.; et al. (Annals of the Rheumatic Diseases, 2010)
Background: Heat shock proteins (Hsps) play a role in the delivery and presentation of antigenic peptides and are thought to be involved in the pathogenesis of multifactorial diseases. Objective: To investigate genes encoding cytosolic Hsp70 proteins for associations of allelic variants with systemic lupus erythematosus (SLE). Methods: Case-control studies of two independent Caucasian SLE cohorts were performed. In a haplotype-tagging single-nucleotide polymorphism approach, common variants of HspA1L, HspA1A and HspA1B were genotyped and principal component analyses were performed for the cohort from the Oklahoma Medical Research Foundation (OMRF). Relative quantification of mRNA was carried out for each Hsp70 gene in healthy controls. Conditional regression analysis was performed to determine if allelic variants in Hsp70 act independently of HLA-DR3. Results: On analysis of common genetic variants of HspA1L, HspA1A and HspA1B, a haplotype significantly associated with SLE in the Erlangen-SLE cohort was identified, which was confirmed in the OMRF cohort. Depending on the cohorts, OR ranging from 1.43 to 1.88 and 2.64 to 3.16 was observed for individuals heterozygous and homozygous for the associated haplotype, respectively. Patients carrying the risk haplotype or the risk allele more often displayed autoantibodies to Ro and La in both cohorts. In healthy controls bearing this haplotype, the amount of HspA1A mRNA was significantly increased, whereas total Hsp70 protein concentration was not altered. Conclusions: Allelic variants of the Hsp70 genes are significantly associated with SLE in Caucasians, independently of HLA-DR3, and correlate with the presence of autoantibodies to Ro and La. Hence, the Hsp70 gene locus appears to be involved in SLE pathogenesis.

Polyol pathway links glucose metabolism to the aggressiveness of cancer cells - Schwab, Annemarie; Siddiqui, Aarif; Vazakidou, Maria Eleni; Napoli, Francesca; Böttcher, Martin; Menchicchi, Bianca; Raza, Umar; Saatci, Ozge; Krebs, Angela; Ferrazzi, Fulvia; Rapa, Ida; Dettmer-Wilde, Katja; et al. (Cancer Research, 2018)
Cancer cells alter their metabolism to support their malignant properties. In this study, we report that the glucose-transforming polyol pathway (PP) gene aldo-keto-reductase-1-member-B1 (AKR1B1) strongly correlates with epithelial-to-mesenchymal transition (EMT). This association was confirmed in samples from lung cancer patients and from an EMT-driven colon cancer mouse model with p53 deletion. In vitro, mesenchymal-like cancer cells showed increased AKR1B1 levels, and AKR1B1 knockdown was sufficient to revert EMT. An equivalent level of EMT suppression was measured by targeting the downstream enzyme sorbitol-dehydrogenase (SORD), further pointing at the involvement of the PP. Comparative RNA sequencing confirmed a profound alteration of EMT in PP-deficient cells, revealing a strong repression of TGF-? signature genes. Excess glucose was found to promote EMT through autocrine TGF-? stimulation, while PP-deficient cells were refractory to glucose-induced EMT. These data show that PP represents a molecular link between glucose metabolism, cancer differentiation, and aggressiveness, and may serve as a novel therapeutic target.
EVALuna2:10237

Posttranslational modification and mutation of histidine 50 trigger alpha synuclein aggregation and toxicity - Xiang, Wei; Menges, Stefanie; Schlachetzki, Johannes; Meixner, Holger; Hoffmann, Anna-Carin; Schlötzer-Schrehardt, Ursula; Becker, Cord-Michael; Winkler, Jürgen; Klucken, Jochen; Klucken, Jochen (Molecular Neurodegeneration, 2015)
Aggregation and aggregation-mediated formation of toxic alpha synuclein (aSyn) species have been linked to the pathogenesis of sporadic and monogenic Parkinson's disease (PD). A novel H50Q mutation of aSyn, resulting in the substitution of histidine by glutamine, has recently been identified in PD patients. We have previously shown that the lipid peroxidation product 4-hydroxy-2-nonenal (HNE) induces the formation of HNE-aSyn adducts, thereby promoting aSyn oligomerization and increasing its extracellular toxicity to human dopaminergic neurons. Intriguingly, we identified histidine 50 (H50) of aSyn as one of the HNE modification target residues. These converging lines of evidence support the hypothesis that changes in H50 via posttranslational modification (PTM) and mutation trigger the formation of aggregated, toxic aSyn species, which interfere with cellular homeostasis. In the present study, we aim to elucidate 1) the role of H50 in HNE-mediated aSyn aggregation and toxicity, and 2) the impact of H50 mutation on aSyn pathology. Besides the PD-related H50Q, we analyze a PD-unrelated control mutation, in which H50 is replaced by an arginine residue (H50R).Analysis of HNE-treated aSyn revealed that H50 is the most susceptible residue of aSyn to HNE modification and is crucial for HNE-mediated aSyn oligomerization. Overexpression of aSyn with substituted H50 in H4 neuroglioma cells reduced HNE-induced cell damage, indicating a pivotal role of H50 in HNE modification-induced aSyn toxicity. Furthermore, we showed in vitro that H50Q/R mutations substantially increase the formation of high density and fibrillar aSyn species, and potentiate the oligomerization propensity of aSyn in the presence of a nitrating agent. Cell-based experiments also revealed that overexpression of H50Q aSyn in H4 cells promotes aSyn oligomerization. Importantly, overexpression of both H50Q/R aSyn mutants in H4 cells significantly increased cell death when compared to wild type aSyn. This increase in cell death was further exacerbated by the application of H2O2.A dual approach addressing alterations of H50 showed that either H50 PTM or mutation trigger aSyn aggregation and toxicity, suggesting an important role of aSyn H50 in the pathogenesis of both sporadic and monogenic PD.
EVALuna2:4709

Preventive Care in Type 2 Diabetes: Results of a Randomized, Controlled Trial in Community Pharmacies - Prax, Katja; Schmiedel, Karin; Hepp, Tobias; Schlager, Helmut; Friedland, Kristina (Diabetes Care, 2021)
CRIS-Team WoS Importer:2021-09-03

Probing the salt dependence of the torsional stiffness of DNA by multiplexed magnetic torque tweezers - Kriegel, Franziska; Ermann, Niklas; Forbes, Ruaridh; Dulin, David; Dekker, Nynke H.; Lipfert, Jan (Nucleic Acids Research, 2017)
The mechanical properties of DNA fundamentally constrain and enable the storage and transmission of genetic information and its use in DNA nanotechnology. Many properties of DNA depend on the ionic environment due to its highly charged backbone. In particular, both theoretical analyses and direct single-molecule experiments have shown its bending stiffness to depend on salt concentration. In contrast, the salt-dependence of the twist stiffness of DNA is much less explored. Here, we employ optimized multiplexed magnetic torque tweezers to study the torsional stiffness of DNA under varying salt conditions as a function of stretching force. At low forces (<3 pN), the effective torsional stiffness is 10% smaller for high salt conditions (500 mM NaCl or 10 mM MgCl2) compared to lower salt concentrations (20 mM NaCl and 100 mM NaCl). These differences, however, can be accounted for by taking into account the known salt dependence of the bending stiffness. In addition, the measured high-force (6.5 pN) torsional stiffness values of C = 103 ± 4 nm are identical, within experimental errors, for all tested salt concentration, suggesting that the intrinsic torsional stiffness of DNA does not depend on salt.
EVALuna2:26368

Propofol-related urine discoloration in a patient with fatal atypical intracerebral hemorrhage treated with hypothermia - Regensburger, Martin; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Staykov, Dimitre (SpringerPlus, 2014)
Introduction: Mild therapeutic hypothermia is an increasingly recognised treatment option to reduce perihemorrhagic edema in severe intracerebral hemorrhage. Case description: We report the case of a 77-year old woman with atypical intracerebral hemorrhage that was treated with mild hypothermia in addition to osmotic therapy. The patient’s urine subsequently showed a green discoloration. Urine discoloration was completely reversible upon discontinuation of propofol. Discussion and evaluation: Propofol-related urine discoloration may have been provoked by hypothermia. Due to the benign nature of this side effect, propofol should be stopped and gastrointestinal function should be supported. Conclusion: More studies are needed to show a causal role of hypothermia and related decreased enzymatic function.
CRIS-Team Scopus Importer:2021-08-17
Keywords: Enterohepatic circulation; Hypothermia; Intracerebral hemorrhage; Liver enzyme function; Urine discoloration

Quantitative parameters of bacterial RNA polymerase open-complex formation, stabilization and disruption on a consensus promoter - Bera, Subhas Chandra; America, Pim P. B.; Maatsola, Santeri; Seifert, Mona; Ostrofet, Eugeniu; Cnossen, Jelmer; Spermann, Monika; Stal Papini, Flavia; Depken, Martin; Malinen, Anssi M.; Dulin, David (Nucleic Acids Research, 2022)
Transcription initiation is the first step in gene expression, and is therefore strongly regulated in all domains of life. The RNA polymerase (RNAP) first associates with the initiation factor sigma to form a holoenzyme, which binds, bends and opens the promoter in a succession of reversible states. These states are critical for transcription regulation, but remain poorly understood. Here, we addressed the mechanism of open complex formation by monitoring its assembly/disassembly kinetics on individual consensus lacUV5 promoters using high-throughput single-molecule magnetic tweezers. We probed the key protein-DNA interactions governing the open-complex formation and dissociation pathway by modulating the dynamics at different concentrations of monovalent salts and varying temperatures. Consistent with ensemble studies, we observed that RNAP-promoter open (RPO) complex is a stable, slowly reversible state that is preceded by a kinetically significant open intermediate (RPI), from which the holoenzyme dissociates. A strong anion concentration and type dependence indicates that the RPO stabilization may involve sequence-independent interactions between the DNA and the holoenzyme, driven by a non-Coulombic effect consistent with the non-template DNA strand interacting with sigma and the RNAP beta subunit. The temperature dependence provides the energy scale of open-complex formation and further supports the existence of additional intermediates.
CRIS-Team WoS Importer:2022-07-22

Recombinant Adenosine Deaminase Ameliorates Inflammation, Vascular Disease, and Fibrosis in Preclinical Models of Systemic Sclerosis - Zhang, Yun; Zhu, Honglin; Layritz, Florian; Luo, Hui; Wohlfahrt, Thomas; Chen, Chih-Wei; Soare, Alina; Bergmann, Christina; Ramming, Andreas; Groeber, Florian; Reuter, Christian; Fornasini, Gianfranco; et al. (Arthritis and Rheumatology, 2020)
Objective: Systemic sclerosis (SSc) is characterized by fibrosis, vascular disease, and inflammation. Adenosine signaling plays a central role in fibroblast activation. We undertook this study to evaluate the therapeutic effects of adenosine depletion with PEGylated adenosine deaminase (PEG-ADA) in preclinical models of SSc. Methods: The effects of PEG-ADA on inflammation, vascular remodeling, and tissue fibrosis were analyzed in Fra-2 mice and in a B10.D2→BALB/c (H-2d) model of sclerodermatous chronic graft-versus-host disease (GVHD). The effects of PEG-ADA were confirmed in vitro in a human full-thickness skin model. Results: PEG-ADA effectively inhibited myofibroblast differentiation and reduced pulmonary fibrosis by 34.3% (with decreased collagen expression) (P = 0.0079; n = 6), dermal fibrosis by 51.8% (P = 0.0006; n = 6), and intestinal fibrosis by 17.7% (P = 0.0228; n = 6) in Fra-2 mice. Antifibrotic effects of PEG-ADA were also demonstrated in sclerodermatous chronic GVHD (reduced by 38.4%) (P = 0.0063; n = 8), and in a human full-thickness skin model. PEG-ADA treatment decreased inflammation and corrected the M2/Th2/group 2 innate lymphoid cell 2 bias. Moreover, PEG-ADA inhibited proliferation of pulmonary vascular smooth muscle cells (reduced by 40.5%) (P < 0.0001; n = 6), and prevented thickening of the vessel walls (reduced by 39.6%) (P = 0.0028; n = 6) and occlusions of pulmonary arteries (reduced by 63.9%) (P = 0.0147; n = 6). Treatment with PEG-ADA inhibited apoptosis of microvascular endothelial cells (reduced by 65.4%) (P = 0.0001; n = 6) and blunted the capillary rarefication (reduced by 32.5%) (P = 0.0199; n = 6). RNA sequencing demonstrated that treatment with PEG-ADA normalized multiple pathways related to fibrosis, vasculopathy, and inflammation in Fra-2 mice. Conclusion: Treatment with PEG-ADA ameliorates the 3 cardinal features of SSc in pharmacologically relevant and well-tolerated doses. These findings may have direct translational implications, as PEG-ADA has already been approved by the Food and Drug Administration for the treatment of patients with ADA-deficient severe combined immunodeficiency disease.
CRIS-Team Scopus Importer:2020-07-10

"Recurrence Resonance" in Three-Neuron Motifs - Krauß, Patrick; Prebeck, Karin; Schilling, Achim; Metzner, Claus (Frontiers in Computational Neuroscience, 2019)
Stochastic Resonance (SR) and Coherence Resonance (CR) are non-linear phenomena, in which an optimal amount of noise maximizes an objective function, such as the sensitivity for weak signals in SR, or the coherence of stochastic oscillations in CR. Here, we demonstrate a related phenomenon, which we call "Recurrence Resonance" (RR): noise can also improve the information flux in recurrent neural networks. In particular, we show for the case of three-neuron motifs with ternary connection strengths that the mutual information between successive network states can be maximized by adding a suitable amount of noise to the neuron inputs. This striking result suggests that noise in the brain may not be a problem that needs to be suppressed, but indeed a resource that is dynamically regulated in order to optimize information processing.
CRIS-Team WoS Importer:2019-10-01

Reduction of Tissue Na+ Accumulation After Renal Transplantation - Dahlmann, Anke; Linz, Peter; Zucker, Isabelle; Haag, Viktor; Jantsch, Jonathan; Dienemann, Thomas; Nagel, Armin Michael; Neubert, Patrick; Rosenhauer, Daniela; Rauh, Manfred; Horn, Stephan; Müller, Dominik N.; et al. (Kidney International Reports, 2021)
Introduction: Chronic kidney disease (CKD) engenders salt-sensitive hypertension. Whether or not tissue Nathorn accumulation is increased in CKD patients remains uncertain. How tissue Nathorn is affected after renal transplantation has not been assessed.
CRIS-Team WoS Importer:2021-10-01

Renal tubular HIF-2α expression requires VHL inactivation and causes fibrosis and cysts - Schietke, Ruth E.; Hackenbeck, Thomas; Tran, Maxine; Guenther, Regina; Klanke, Bernd; Warnecke, Christina; Knaup, Karl X.; Shukla, Deepa; Rosenberger, Christian; Koesters, Robert; Bachmann, Sebastian; Betz, Peter; et al. (PLoS ONE, 2012)
The Hypoxia-inducible transcription Factor (HIF) represents an important adaptive mechanism under hypoxia, whereas sustained activation may also have deleterious effects. HIF activity is determined by the oxygen regulated α-subunits HIF-1α or HIF-2α. Both are regulated by oxygen dependent degradation, which is controlled by the tumor suppressor "von Hippel-Lindau" (VHL), the gatekeeper of renal tubular growth control. HIF appears to play a particular role for the kidney, where renal EPO production, organ preservation from ischemia-reperfusion injury and renal tumorigenesis are prominent examples. Whereas HIF-1α is inducible in physiological renal mouse, rat and human tubular epithelia, HIF-2α is never detected in these cells, in any species. In contrast, distinct early lesions of biallelic VHL inactivation in kidneys of the hereditary VHL syndrome show strong HIF-2α expression. Furthermore, knockout of VHL in the mouse tubular apparatus enables HIF-2α expression. Continuous transgenic expression of HIF-2α by the Ksp-Cadherin promotor leads to renal fibrosis and insufficiency, next to multiple renal cysts. In conclusion, VHL appears to specifically repress HIF-2α in renal epithelia. Unphysiological expression of HIF-2α in tubular epithelia has deleterious effects. Our data are compatible with dedifferentiation of renal epithelial cells by sustained HIF-2α expression. However, HIF-2α overexpression alone is insufficient to induce tumors. Thus, our data bear implications for renal tumorigenesis, epithelial differentiation and renal repair mechanisms. © 2012 Schietke et al.

Reply to: Osteoporosis: An Independent Determinant of Bone Erosions in Rheumatoid Arthritis? - Simon, David; Simon, Christoph; Kleyer, Arnd; Schett, Georg (Journal of Bone and Mineral Research, 2017)
We thank Rossini and colleagues for their letter (1) commenting on our article (2) "Age- and Sex-Dependent Changes of intra-articular Cortical and Trabecular Bone Structure and the Effects of Rheumatoid Arthritis". In fact, we could not more agree with the view of the authors and congratulate them for this concise summary of the key mechanism involved in bone loss of rheumatoid arthritis. In addition, we think that this letter raises two important points related to inflammatory bone loss: First, Rossini and colleagues point out that bone loss in rheumatoid arthritis arises from a combination of (i) factors specific to rheumatoid arthritis, in particular inflammation and autoimmunity and (ii) more common factors related to age, sex and menopausal status. Hence, age, postmenopausal state and inflammation/autoimmunity join efforts to trigger bone disease in patients with rheumatoid arthritis. Our data support this concept by showing age-, sex- and disease- associated changes of intra-articular bone mass and microstructures, which is likely the most sensitive indicator of bone loss in the context of arthritis. This article is protected by copyright. All rights reserved.
EVALuna2:13426

Role of the receptor Mas in macrophage-mediated inflammation in vivo - Hammer, Anna; Yang, Guang; Friedrich, Juliane; Kovacs, Agnes; Lee, De-Hyung; Grave, Katharina; Joerg, Stefanie; Alenina, Natalia; Grosch, Janina; Winkler, Jürgen; Gold, Ralf; Bader, Michael; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Recently, an alternative renin-angiotensin system pathway has been described, which involves binding of angiotensin-(1-7) to its receptor Mas. The Mas axis may counterbalance angiotensin-II-mediated proinflammatory effects, likely by affecting macrophage function. Here we investigate the role of Mas in murine models of autoimmune neuroinflammation and atherosclerosis, which both involve macrophage-driven pathomechanisms. Mas signaling affected macrophage polarization, migration, and macrophage-mediated T-cell activation. Mas deficiency exacerbated the course of experimental autoimmune encephalomyelitis and increased macrophage infiltration as well as proinflammatory gene expression in the spleen and spinal cord. Furthermore, Mas deficiency promoted atherosclerosis by affecting macrophage infiltration and migration and led to increased oxidative stress as well as impaired endothelial function in ApoE-deficient mice. In summary, we identified the Mas axis as an important factor in macrophage function during inflammation of the central nervous and vascular system in vivo. Modulating the Mas axis may constitute an interesting therapeutic target in multiple sclerosis and/or atherosclerosis.
EVALuna2:22496

Role of α-synuclein in adult neurogenesis and neuronal maturation in the dentate gyrus. - Winner, Beate; Regensburger, Martin; Prots, Iryna; Winkler, Jürgen; et al. (Journal of Neuroscience, 2012)
α-Synuclein has been reported to be important in modulating brain plasticity and to be a key protein in neurodegenerative diseases, including Lewy body dementia (LBD). We investigated how α-synuclein levels modulate adult neurogenesis and the development of dendritic arborization and spines in the dentate gyrus, in which new neurons are constantly added. In the human hippocampus, levels of endogenous α-synuclein were increased in LBD, and the numbers of SOX2-positive cells were decreased. We investigated whether newly generated neurons were modulated by endogenous α-synuclein, and we found increased adult neurogenesis in α/β-synuclein knock-out mice. In contrast, overexpression of human wild-type α-synuclein (WTS) decreased the survival and dendritic development of newborn neurons. Endogenous α-synuclein expression levels increased the negative impact of WTS on dendrite development, suggesting a toxic effect of increasing amounts of α-synuclein. To attempt a rescue of the dendritic phenotype, we administered rolipram to activate the cAMP response element-binding protein pathway, which led to a partial rescue of neurite development. The current work provides novel insights into the role of α-synuclein in adult hippocampal neurogenesis.

Salt-dependent chemotaxis of macrophages - Mueller, Silke; Quast, Thomas; Schröder, Agnes; Hucke, Stephanie; Klotz, Luisa; Jantsch, Jonathan; Gerzer, Rupert; Hemmersbach, Ruth; Kolanus, Waldemar (PLoS ONE, 2013)
Besides their role in immune system host defense, there is growing evidence that macrophages may also be important regulators of salt homeostasis and blood pressure by a TonEBP-VEGF-C dependent buffering mechanism. As macrophages are known to accumulate in the skin of rats fed under high salt diet conditions and are pivotal for removal of high salt storage, the question arose how macrophages sense sites of high sodium storage. Interestingly, we observed that macrophage-like RAW264.7 cells, murine bone marrow-derived macrophages and peritoneal macrophages recognize NaCl hypertonicity as a chemotactic stimulus and migrate in the direction of excess salt concentration by using an in vitro transwell migration assay. While RAW264.7 cells migrated toward NaCl in a dose-dependent fashion, no migratory response toward isotonic or hypotonic media controls, or other osmo-active agents, e.g. urea or mannitol, could be detected. Interestingly, we could not establish a specific role of the osmoprotective transcription factor TonEBP in regulating salt-dependent chemotaxis, since the specific migration of bone marrow-derived macrophages following RNAi of TonEBP toward NaCl was not altered. Although the underlying mechanism remains unidentified, these data point to a thus far unappreciated role for NaCl-dependent chemotaxis of macrophages in the clearance of excess salt, and suggest the existence of novel NaCl sensor/effector circuits, which are independent of the TonEBP system.
EVALuna2:7634

Signatures of Nucleotide Analog Incorporation by an RNA-Dependent RNA Polymerase Revealed Using High-Throughput Magnetic Tweezers - Dulin, David; Arnold, Jamie J.; Van Laar, Theo; Oh, Hyung-Suk; Lee, Cheri; Perkins, Angela L.; Harki, Daniel A.; Depken, Martin; Cameron, Craig E.; Dekker, Nynke H. (Cell Reports, 2017)
RNA viruses pose a threat to public health that is exacerbated by the dearth of antiviral therapeutics. The RNA-dependent RNA polymerase (RdRp) holds promise as a broad-spectrum, therapeutic target because of the conserved nature of the nucleotide-substrate-binding and catalytic sites. Conventional, quantitative, kinetic analysis of antiviral ribonucleotides monitors one or a few incorporation events. Here, we use a high-throughput magnetic tweezers platform to monitor the elongation dynamics of a prototypical RdRp over thousands of nucleotide-addition cycles in the absence and presence of a suite of nucleotide analog inhibitors. We observe multiple RdRp-RNA elongation complexes; only a subset of which are competent for analog utilization. Incorporation of a pyrazine-carboxamide nucleotide analog, T-1106, leads to RdRp backtracking. This analysis reveals a mechanism of action for this antiviral ribonucleotide that is corroborated by cellular studies. We propose that induced backtracking represents a distinct mechanistic class of antiviral ribonucleotides.
EVALuna2:26367

Single-Molecule Magnetic Tweezers Characterization of MTERF1 as a Directional Roadblock - Ostrofet, Eugeniu; Papini, Flavia Stal; Johnson, Britney; Arnold, Jamie J.; Cameron, Craig E.; Dulin, David (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

Skin sodium measured with ²³Na MRI at 7.0 T - Linz, Peter; Santoro, Davide; Renz, Wolfgang; Rieger, Jan; Ruehle, Anjuli; Ruff, Jan; Deimling, Michael; Rakova, Natalia; Muller, Dominik N.; Luft, Friedrich C.; Titze, Jens; Niendorf, Thoralf (NMR in Biomedicine, 2015)
Skin sodium (Na(+) ) storage, as a physiologically important regulatory mechanism for blood pressure, volume regulation and, indeed, survival, has recently been rediscovered. This has prompted the development of MRI methods to assess Na(+) storage in humans ((23) Na MRI) at 3.0 T. This work examines the feasibility of high in-plane spatial resolution (23) Na MRI in skin at 7.0 T. A two-channel transceiver radiofrequency (RF) coil array tailored for skin MRI at 7.0 T (f = 78.5 MHz) is proposed. Specific absorption rate (SAR) simulations and a thorough assessment of RF power deposition were performed to meet the safety requirements. Human skin was examined in an in vivo feasibility study using two-dimensional gradient echo imaging. Normal male adult volunteers (n = 17; mean ± standard deviation, 46 ± 18 years; range, 20-79 years) were investigated. Transverse slices of the calf were imaged with (23) Na MRI using a high in-plane resolution of 0.9 × 0.9 mm(2) . Skin Na(+) content was determined using external agarose standards covering a physiological range of Na(+) concentrations. To assess the intra-subject reproducibility, each volunteer was examined three to five times with each session including a 5-min walk and repositioning/preparation of the subject. The age dependence of skin Na(+) content was investigated. The (23) Na RF coil provides improved sensitivity within a range of 1 cm from its surface versus a volume RF coil which facilitates high in-plane spatial resolution imaging of human skin. Intra-subject variability of human skin Na(+) content in the volunteer population was <10.3%. An age-dependent increase in skin Na(+) content was observed (r = 0.78). The assignment of Na(+) stores with (23) Na MRI techniques could be improved at 7.0 T compared with current 3.0 T technology. The benefits of such improvements may have the potential to aid basic research and clinical applications designed to unlock questions regarding the Na(+) balance and Na(+) storage function of skin.
EVALuna2:3754

SoxD transcription factor deficiency in Schwann cells delays myelination in the developing peripheral nervous system - Ittner, Ella; Hartwig, Anna; Elsesser, Olga; Wüst, Hannah; Fröb, Franziska; Wedel, Miriam; Schimmel, Margit; Tamm, Ernst R.; Wegner, Michael; Sock, Elisabeth (Scientific Reports, 2021)
The three SoxD proteins, Sox5, Sox6 and Sox13, represent closely related transcription factors with important roles during development. In the developing nervous system, SoxD proteins have so far been primarily studied in oligodendroglial cells and in interneurons of brain and spinal cord. In oligodendroglial cells, Sox5 and Sox6 jointly maintain the precursor state, interfere with terminal differentiation, and thereby ensure the proper timing of myelination in the central nervous system. Here we studied the role of SoxD proteins in Schwann cells, the functional counterpart of oligodendrocytes in the peripheral nervous system. We show that Schwann cells express Sox5 and Sox13 but not Sox6. Expression was transient and ceased with the onset of terminal differentiation. In mice with early Schwann cell-specific deletion of both Sox5 and Sox13, embryonic Schwann cell development was not substantially affected and progressed normally into the promyelinating stage. However, there was a mild and transient delay in the myelination of the peripheral nervous system of these mice. We therefore conclude that SoxD proteins—in stark contrast to their action in oligodendrocytes—promote differentiation and myelination in Schwann cells.
CRIS-Team Scopus Importer:2021-07-16

Specific phenotype and function of CD56-expressing innate immune cell subsets in human thymus - Gerstner, Stephanie; Köhler, Wolfgang; Heidkamp, Gordon Frederik; Purbojo, Ariawan; Uchida, Shizuka; Ekici, Arif Bülent; Heger, Lukas; Luetke-Eversloh, Merlin; Schubert, Ralf; Bader, Peter; Klingebiel, Thomas; Koehl, Ulrike; et al. (Journal of Leukocyte Biology, 2016)
Whereas innate immune cells, such as NK and innate lymphoid cells (ILCs), have been characterized in different human tissues, knowledge on the thymic CD56-expressing cell subsets is limited. In this study, the rare subpopulations of thymic CD56(+)CD3(-) cells from samples of >100 patients have been successfully analyzed. The results revealed fundamental differences between thymic and peripheral blood (PB) CD56(+)CD3(-) cells. Thymic tissues lacked immunoregulatory CD56(high)CD16(dim) NK cells but showed two Eomes(+)CD56(dim) subsets on which common NK cell markers were significantly altered. CD56(dim)CD16(high) cells expressed high amounts of NKG2A, NKG2D, and CD27 with low CD57. Conversely, CD56(dim)CD16(dim) cells displayed high CD127 but low expression of KIR, NKG2D, and natural cytotoxicity receptors (NCRs). Thymic CD56(+)CD3(-) cells were able to gain cytotoxicity but were especially immunoregulatory cells, producing a broad range of cytokines. Finally, one population of thymic CD56(+) cells resembled conventional NK cells, whereas the other represented a novel, noncanonical NK subset.
EVALuna2:9311

Spooky sodium balance - Titze, Jens; Dahlmann, Anke; Lerchl, Kathrin; Kopp, Christoph; Rakova, Natalia; Schröder, Agnes; Luft, Friedrich C. (Kidney International, 2014)
Current teaching states that when sodium intake is increased from low to high levels, total-body sodium (TBNa) and water increase until daily sodium excretion again equals intake. When sodium intake is reduced, sodium excretion briefly exceeds intake until the excess TBNa and water are eliminated, at which point sodium excretion again equals intake. However, careful balance studies oftentimes conflict with this view and long-term studies suggest that TBNa fluctuates independent of intake or body weight. We recently performed the opposite experiment in that we fixed sodium intake for several weeks at three levels of sodium intake and collected all urine made. We found weekly (circaseptan) patterns in sodium excretion that were inversely related to aldosterone and directly to cortisol. TBNa was not dependent on sodium intake but instead exhibited far longer (>= monthly) infradian rhythms independent of extracellular water, body weight, or blood pressure. The findings are consistent with our ideas on tissue sodium storage and its regulation that we developed on the basis of animal research. We are implementing (23)Na-magnetic resonance imaging (MRI) to pursue open questions on sodium balance in patients. Our findings could be relevant to therapeutic strategies for hypertension and target-organ damage.
EVALuna2:3656

Swiprosin-1/EFhd2-another piece in the puzzle of tauopathy? - Regensburger, Martin; Mielenz, Dirk; Winner, Beate (Aging-Us, 2018)
EVALuna2:35785
Keywords: Neurodegeneration; Swiprosin-1; EFhd2; Adult neurogenesis

Synergistic effect of anethole and doxorubicin alleviates cell proliferation, cell cycle arrest, and ER stress and promotes ROS-mediated apoptosis in triple-negative breast cancer cells - Arumugam, Poornima; Sampathkumar, Banupriya; Perumalsamy, Haribalan; Balusamy, Sri Renukadevi; Ramesh, Vignesh; Sundaravadevel, Sumathi (Journal of Biochemical and Molecular Toxicology, 2021)
The heterogeneity and poor prognosis of triple-negative breast cancer (TNBC) have limited the treatment options and made clinical management challenging. This has nurtured a major effort to discover druggable molecular targets. Currently, chemotherapy is the primary treatment strategy for this disease. Doxorubicin is the most frequently used chemotherapeutic drug for TNBC and due to the fact that chemotherapeutic drugs have a lot of side effects, we evaluated the synergistic effect of the phytocompound anethole and doxorubicin. The cytotoxic effect of anethole in combination with doxorubicin on MDA-MB-231 cells was evaluated by various parameters, including apoptosis, cell cycle analysis, DNA damage, and cell proliferation. Furthermore, mitochondrial membranepotential (MMP), endoplasmic reticulum (ER) stress, and reactive oxygen species (ROS) levels were also evaluated in the cells treated with/without anethole and doxorubicin. Expression of the apoptotic proteins was evaluated by Western blot analysis. Initial evaluation of cytotoxicity of anethole on MDA-MB-231 cells demonstrated preferential suppression of cell proliferation and when treated along with doxorubicin it showed enhanced cytotoxicity with a synergistic effect. Cell cycle analysis revealed arrest at different stages of the cell cycle, such as sub G0-G1, G0-G1, S, and G2M in various treatment groups and apoptotic cell death was subsequently evident with propidium iodide (PI) staining. The synergistic action of anethole and doxorubicin effectively induced mitochondrial membrane potential loss, which, in turn, led to a burst of ROS production, which eventually produced unfolded protein response by damaging the ER. Synergistic anticancer effect was observed on exposure of MDA-MB-231 cells to anethole and doxorubicin in inducing cell death.
CRIS-Team WoS Importer:2021-10-08

Targeting EMT in Cancer with Repurposed Metabolic Inhibitors - Ramesh, Vignesh; Brabletz, Thomas; Ceppi, Paolo (Trends in Cancer, 2020)
Epithelial-to-mesenchymal transition (EMT) determines the most lethal features of cancer, metastasis formation and chemoresistance, and therefore represents an attractive target in oncology. However, direct targeting of EMT effector molecules is, in most cases, pharmacologically challenging. Since emerging research has highlighted the distinct metabolic circuits involved in EMT, we propose the use of metabolism-specific inhibitors, FDA approved or under clinical trials, as a drug repurposing approach to target EMT in cancer. Metabolism-inhibiting drugs could be coupled with standard chemo- or immunotherapy to combat EMT-driven resistant and aggressive cancers.
CRIS-Team Scopus Importer:2020-07-24
Keywords: chemoresistance; drug repurposing; epithelial–mesenchymal transition; metabolic inhibitor; partial EMT

Temperature controlled high-throughput magnetic tweezers show striking difference in activation energies of replicating viral RNA-dependent RNA polymerases - Seifert, Mona; van Nies, Pauline; Papini, Flávia S.; Arnold, Jamie J.; Poranen, Minna M.; Cameron, Craig E.; Depken, Martin; Dulin, David (Nucleic Acids Research, 2020)
RNA virus survival depends on efficient viral genome replication, which is performed by the viral RNA dependent RNA polymerase (RdRp). The recent development of high throughput magnetic tweezers has enabled the simultaneous observation of dozens of viral RdRp elongation traces on kilobases long templates, and this has shown that RdRp nucleotide addition kinetics is stochastically interrupted by rare pauses of 1-1000 s duration, of which the short-lived ones (1-10 s) are the temporal signature of a low fidelity catalytic pathway. We present a simple and precise temperature controlled system for magnetic tweezers to characterize the replication kinetics temperature dependence between 25°C and 45°C of RdRps from three RNA viruses, i.e. the double-stranded RNA bacteriophage Φ6, and the positive-sense single-stranded RNA poliovirus (PV) and human rhinovirus C (HRV-C). We found that Φ6 RdRp is largely temperature insensitive, while PV and HRV-C RdRps replication kinetics are activated by temperature. Furthermore, the activation energies we measured for PV RdRp catalytic state corroborate previous estimations from ensemble pre-steady state kinetic studies, further confirming the catalytic origin of the short pauses and their link to temperature independent RdRp fidelity. This work will enable future temperature controlled study of biomolecular complex at the single molecule level.
CRIS-Team Scopus Importer:2020-06-16

Temperature-Dependent Twist of Double-Stranded RNA Probed by Magnetic Tweezer Experiments and Molecular Dynamics Simulations - Dohnalová, Hana; Seifert, Mona; Matoušková, Eva; Klein, Misha; Stal Papini, Flavia; Lipfert, Jan; Dulin, David; Lankaš, Filip (Journal of Physical Chemistry B, 2024)
RNA plays critical roles in the transmission and regulation of genetic information and is increasingly used in biomedical and biotechnological applications. Functional RNAs contain extended double-stranded regions, and the structure of double-stranded RNA (dsRNA) has been revealed at high resolution. However, the dependence of the properties of the RNA double helix on environmental effects, notably temperature, is still poorly understood. Here, we use single-molecule magnetic tweezer measurements to determine the dependence of the dsRNA twist on temperature. We find that dsRNA unwinds with increasing temperature, even more than DNA, with ΔTwRNA = −14.4 ± 0.7°/(°C·kbp), compared to ΔTwDNA = −11.0 ± 1.2°/(°C·kbp). All-atom molecular dynamics (MD) simulations using a range of nucleic acid force fields, ion parameters, and water models correctly predict that dsRNA unwinds with rising temperature but significantly underestimate the magnitude of the effect. These MD data, together with additional MD simulations involving DNA and DNA-RNA hybrid duplexes, reveal a linear correlation between the twist temperature decrease and the helical rise, in line with DNA but at variance with RNA experimental data. We speculate that this discrepancy might be caused by some unknown bias in the RNA force fields tested or by as yet undiscovered transient alternative structures in the RNA duplex. Our results provide a baseline to model more complex RNA assemblies and to test and develop new parametrizations for RNA simulations. They may also inspire physical models of the temperature-dependent dsRNA structure.
CRIS-Team Scopus Importer:2024-02-16

The Ca2+ sensor protein swiprosin-1/EFhd2 is present in neurites and involved in kinesin-mediated transport in neurons - Purohit, Pavitra; Perez-Branguli, Francesc; Prots, Iryna; Borger, Eva; Gunn-Moore, Frank; Welzel, Oliver; Loy, Kristina; Wenzel, Eva Maria; Groemer, Teja W.; Brachs, Sebastian; Holzer, Max; Buslei, Rolf; et al. (PLoS ONE, 2014)
Swiprosin-1/EFhd2 (EFhd2) is a cytoskeletal Ca2+ sensor protein strongly expressed in the brain. It has been shown to interact with mutant tau, which can promote neurodegeneration, but nothing is known about the physiological function of EFhd2 in the nervous system. To elucidate this question, we analyzed EFhd2-/-/lacZ reporter mice and showed that lacZ was strongly expressed in the cortex, the dentate gyrus, the CA1 and CA2 regions of the hippocampus, the thalamus, and the olfactory bulb. Immunohistochemistry and western blotting confirmed this pattern and revealed expression of EFhd2 during neuronal maturation. In cortical neurons, EFhd2 was detected in neurites marked by MAP2 and co-localized with pre- and post-synaptic markers. Approximately one third of EFhd2 associated with a biochemically isolated synaptosome preparation. There, EFhd2 was mostly confined to the cytosolic and plasma membrane fractions. Both synaptic endocytosis and exocytosis in primary hippocampal EFhd2-/- neurons were unaltered but transport of synaptophysin-GFP containing vesicles was enhanced in EFhd2-/- primary hippocampal neurons, and notably, EFhd2 inhibited kinesin mediated microtubule gliding. Therefore, we found that EFhd2 is a neuronal protein that interferes with kinesin-mediated transport.
EVALuna2:7246

The Effect of Nintedanib versus Mycopheolate Mofetil in the FRA2 Mouse Model of Systemic Sclerosis Associated Interstitial Lung Disease - Thuong Trin-Minh,; Zhang, Yun; Distler, Jörg; Wollin, Lutz (ARTHRITIS & RHEUMATOLOGY, 2019)
CRIS-Team WoS Importer:2020-02-07

The Nuclear Receptor Nr4a1 Acts as a Microglia Rheostat and Serves as a Therapeutic Target in Autoimmune-Driven Central Nervous System Inflammation - Rothe, Tobias; Ipseiz, Natacha; Faas, Maria; Lang, Stefanie; Perez-Branguli, Francesc; Metzger, Daniel; Ichinose, Hiroshi; Winner, Beate; Schett, Georg; Krönke, Gerhard (Journal of Immunology, 2017)
Microglia cells fulfill key homeostatic functions and essentially contribute to host defense within the CNS. Altered activation of microglia, in turn, has been implicated in neuroinflammatory and neurodegenerative diseases. In this study, we identify the nuclear receptor (NR) Nr4a1 as key rheostat controlling the activation threshold and polarization of microglia. In steady-state microglia, ubiquitous neuronal-derived stress signals such as ATP induced expression of this NR, which contributed to the maintenance of a resting and noninflammatory microglia phenotype. Global and microglia-specific deletion of Nr4a1 triggered the spontaneous and overwhelming activation of microglia and resulted in increased cytokine and NO production as well as in an accelerated and exacerbated form of experimental autoimmune encephalomyelitis. Ligand-induced activation of Nr4a1 accordingly ameliorated the course of this disease. Our current data thus identify Nr4a1 as regulator of microglia activation and potentially new target for the treatment of inflammatory CNS diseases such as multiple sclerosis.
EVALuna2:13374

The nucleotide addition cycle of the SARS-CoV-2 polymerase - Bera, Subhas Chandra; Seifert, Mona; Kirchdoerfer, Robert N.; Van Nies, Pauline; YIBULAYIN, WUBULIKASIMU; Quack, Salina; Papini, Flavia S.; Arnold, Jamie J.; Canard, Bruno; Cameron, Craig E.; Depken, Martin; Dulin, David (Cell Reports, 2021)
Coronaviruses have evolved elaborate multisubunit machines to replicate and transcribe their genomes. Central to these machines are the RNA-dependent RNA polymerase subunit (nsp12) and its intimately associated cofactors (nsp7 and nsp8). We use a high-throughput magnetic-tweezers approach to develop a mechanochemical description of this core polymerase. The core polymerase exists in at least three catalytically distinct conformations, one being kinetically consistent with incorporation of incorrect nucleotides. We provide evidence that the RNA-dependent RNA polymerase (RdRp) uses a thermal ratchet instead of a power stroke to transition from the pre- to post-translocated state. Ultra-stable magnetic tweezers enable the direct observation of coronavirus polymerase deep and long-lived backtracking that is strongly stimulated by secondary structures in the template. The framework we present here elucidates one of the most important structure-dynamics-function relationships in human health today and will form the grounds for understanding the regulation of this complex.
CRIS-Team Scopus Importer:2021-09-10
Keywords: backtracking; high-throughput/ultra-stable magnetic tweezers; nucleotide addition cycle; polymerase mechanochemistry; SARS-CoV-2 polymerase; single-molecule biophysics

The phosphatase Pgam5 antagonizes Wnt/β-catenin signaling in embryonic anterior-posterior axis patterning - Rauschenberger, Verena; Bernkopf, Dominic; Krenn, Sabrina; Jalal, Kowcee; Heller, Jens; Behrens, Jürgen; Gentzel, Marc; Schambony, Alexandra (Development, 2017)
Keywords: Anteriorposterior patterning; Dvl2; Pgam5; Phosphatase; Wnt; Xenopus

The proteasome inhibitor bortezomib depletes plasma cells and protects mice with lupus-like disease from nephritis - Neubert, Kirsten; Meister, Silke; Moser, Katrin; Weisel, Florian; Maseda, Damian; Amann, Kerstin Ute; Wiethe, Carsten; Winkler, Thomas; Kalden, Joachim; Manz, Rudolf A.; Voll, Reinhard E. (Nature Medicine, 2008)
Autoantibody-mediated diseases like myasthenia gravis, autoimmune hemolytic anemia and systemic lupus erythematosus represent a therapeutic challenge. In particular, long-lived plasma cells producing autoantibodies resist current therapeutic and experimental approaches. Recently, we showed that the sensitivity of myeloma cells toward proteasome inhibitors directly correlates with their immunoglobulin synthesis rates. Therefore, we hypothesized that normal plasma cells are also hypersensitive to proteasome inhibition owing to their extremely high amount of protein biosynthesis. Here we show that the proteasome inhibitor bortezomib, which is approved for the treatment of multiple myeloma, eliminates both short- and long-lived plasma cells by activation of the terminal unfolded protein response. Treatment with bortezomib depleted plasma cells producing antibodies to double-stranded DNA, eliminated autoantibody production, ameliorated glomerulonephritis and prolonged survival of two mouse strains with lupus-like disease, NZB/W F1 and MRL/lpr mice. Hence, the elimination of autoreactive plasma cells by proteasome inhibitors might represent a new treatment strategy for antibody-mediated diseases. © 2008 Nature Publishing Grou

The role of miR-200b/c in balancing EMT and proliferation revealed by an activity reporter - Gollavilli, Paradesi Naidu; Parma, Beatrice; Siddiqui, Aarif; Yang, Hai; Ramesh, Vignesh; Napoli, Francesca; Schwab, Annemarie; Natesan, Ramakrishnan; Mielenz, Dirk; Asangani, Irfan Ahmed; Brabletz, Thomas; Pilarsky, Christian; et al. (Oncogene, 2021)
Since their discovery, microRNAs (miRNAs) have been widely studied in almost every aspect of biology and medicine, leading to the identification of important gene regulation circuits and cellular mechanisms. However, investigations are generally focused on the analysis of their downstream targets and biological functions in overexpression and knockdown approaches, while miRNAs endogenous levels and activity remain poorly understood. Here, we used the cellular plasticity-regulating process of epithelial-to-mesenchymal transition (EMT) as a model to show the efficacy of a fluorescent sensor to separate cells with distinct EMT signatures, based on miR-200b/c activity. The system was further combined with a CRISPR-Cas9 screening platform to unbiasedly identify miR-200b/c upstream regulating genes. The sensor allows to infer miRNAs fundamental biological properties, as profiling of sorted cells indicated miR-200b/c as a molecular switch between EMT differentiation and proliferation, and suggested a role for metabolic enzymes in miR-200/EMT regulation. Analysis of miRNAs endogenous levels and activity for in vitro and in vivo applications could lead to a better understanding of their biological role in physiology and disease.
CRIS-Team Scopus Importer:2021-03-19

The SGLT2 inhibitor empagliflozin reduces tissue sodium content in patients with chronic heart failure: results from a placebo-controlled randomised trial - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Nöh, Lisa; Schiffer, Mario; Uder, Michael; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2022)
Introduction: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have cardiovascular protective properties in addition to the metabolic effects and represent a cornerstone of treating patients with chronic heart failure (CHF). We hypothesised that empagliflozin reduces tissue sodium content in patients with CHF. Methods: In a double-blind, randomised (2:1), placebo-controlled, parallel-group, clinical trial, 74 patients with NYHA class II–III CHF and an ejection fraction of 49% or less received empagliflozin 10 mg once daily or placebo for 3 months. In each patient, tissue sodium content of the lower leg was assessed non-invasively by sodium-MRI (23Na-MRI) at baseline, after 1 and 3 months of treatment. Results: After 1 and 3 months treatment with empagliflozin (n = 48), a significant decrease in skin sodium content was observed (1 month: 22.8 ± 6.1 vs. 21.6 ± 6.0 AU, p = 0.039; 3 months: 22.9 ± 6.1 vs. 21.6 ± 6.1 AU, p = 0.013), while there was no change in muscle sodium and muscle water content. In direct comparison, the change in skin sodium content between baseline and 3 months was − 1.3 ± 3.5 AU in the empagliflozin group versus 0.6 ± 3.5 AU in the placebo group (p for between-group difference = 0.022). No significant difference regarding change in muscle sodium and in muscle water content was observed after 3 months treatment between the two groups. Conclusion: This trial showed a significant decrease in skin sodium content after 1 and 3 months of treatment with empagliflozin. The decrease in skin sodium content may reflect a decrease in subclinical micro-oedema or/and in non-osmotic bound tissue sodium, both reported to impair left ventricular function. Trial registration number: NCT03128528 (http://www.clinicaltrials.gov). Trial registration date: 25th April 2017.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Chronic heart failure; Empagliflozin; Magnetic resonance imaging; SGLT2 inhibitor; Sodium; Tissue sodium content

The temporal expression pattern of alpha-synuclein modulates olfactory neurogenesis in transgenic mice - Schreglmann, Sebastian R.; Regensburger, Martin; Rockenstein, Edward; Masliah, Eliezer; Xiang, Wei; Winkler, Jürgen; Winner, Beate (PLoS ONE, 2015)
Adult neurogenesis mirrors the brain´s endogenous capacity to generate new neurons throughout life. In the subventricular zone/ olfactory bulb system adult neurogenesis is linked to physiological olfactory function and has been shown to be impaired in murine models of neuronal alpha-Synuclein overexpression. We analyzed the degree and temporo-spatial dynamics of adult olfactory bulb neurogenesis in transgenic mice expressing human wild-type alpha-Synuclein (WTS) under the murine Thy1 (mThy1) promoter, a model known to have a particularly high tg expression associated with impaired olfaction.Survival of newly generated neurons (NeuN-positive) in the olfactory bulb was unchanged in mThy1 transgenic animals. Due to decreased dopaminergic differentiation a reduction in new dopaminergic neurons within the olfactory bulb glomerular layer was present. This is in contrast to our previously published data on transgenic animals that express WTS under the control of the human platelet-derived growth factor ? (PDGF) promoter, that display a widespread decrease in survival of newly generated neurons in regions of adult neurogenesis, resulting in a much more pronounced neurogenesis deficit. Temporal and quantitative expression analysis using immunofluorescence co-localization analysis and Western blots revealed that in comparison to PDGF transgenic animals, in mThy1 transgenic animals WTS is expressed from later stages of neuronal maturation only but at significantly higher levels both in the olfactory bulb and cortex.The dissociation between higher absolute expression levels of alpha-Synuclein but less severe impact on adult olfactory neurogenesis in mThy1 transgenic mice highlights the importance of temporal expression characteristics of alpha-Synuclein on the maturation of newborn neurons.
EVALuna2:4712

Thymidylate synthase drives the phenotypes of epithelial-to-mesenchymal transition in non-small cell lung cancer - Siddiqui, Mohammad Aarif; Gollavilli, Paradesi Naidu; Ramesh, Vignesh; Parma, Beatrice; Schwab, Annemarie; Vazakidou, Maria Eleni; Natesan, Ramakrishnan; Saatci, Ozge; Rapa, Ida; Bironzo, Paolo; Schuhwerk, Harald; Asangani, Irfan Ahmed; et al. (British Journal of Cancer, 2020)
Background: Epithelial-to-mesenchymal transition (EMT) enhances motility, stemness, chemoresistance and metastasis. Little is known about how various pathways coordinate to elicit EMT’s different functional aspects in non-small cell lung cancer (NSCLC). Thymidylate synthase (TS) has been previously correlated with EMT transcription factor ZEB1 in NSCLC and imparts resistance against anti-folate chemotherapy. In this study, we establish a functional correlation between TS, EMT, chemotherapy and metastasis and propose a network for TS mediated EMT. Methods: Published datasets were analysed to evaluate the significance of TS in NSCLC fitness and prognosis. Promoter reporter assay was used to sort NSCLC cell lines in TSHIGH and TSLOW. Metastasis was assayed in a syngeneic mouse model. Results: TS levels were prognostic and predicted chemotherapy response. Cell lines with higher TS promoter activity were more mesenchymal-like. RNA-seq identified EMT as one of the most differentially regulated pathways in connection to TS expression. EMT transcription factors HOXC6 and HMGA2 were identified as upstream regulator of TS, and AXL, SPARC and FOSL1 as downstream effectors. TS knock-down reduced the metastatic colonisation in vivo. Conclusion: These results establish TS as a theranostic NSCLC marker integrating survival, chemo-resistance and EMT, and identifies a regulatory network that could be targeted in EMT-driven NSCLC. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2020-10-16

Thymidylate synthase is functionally associated with ZEB1 and contributes to the epithelial-to-mesenchymal transition of cancer cells - Siddiqui, Aarif; Vazakidou, Maria Eleni; Schwab, Annemarie; Napoli, Francesca; Fernandez-Molina, Cristina; Rapa, Ida; Stemmler, Marc; Volante, Marco; Brabletz, Thomas; Ceppi, Paolo (Journal of Pathology, 2017)
Thymidylate synthase (TS) is a fundamental enzyme of nucleotide metabolism and one of the oldest anti-cancer targets. Beginning from the analysis of gene array data from the NCI-60 panel of cancer cell lines, we identified a significant correlation at both gene and protein level between TS and the markers of epithelial-to-mesenchymal transition (EMT), a developmental process that allows cancer cells to acquire features of aggressiveness, like motility and chemoresistance. TS levels were found to be significantly augmented in mesenchymal-like compared to epithelial-like cancer cells, to be regulated by EMT induction, and to negatively correlate with micro-RNAs (miRNAs) usually expressed in epithelial-like cells and known to actively suppress EMT. Transfection of EMT-suppressing miRNAs reduced TS levels, and a specific role for miR-375 in targeting the TS 3'-untranslated region was identified. A particularly relevant association was found between TS and the powerful EMT driver ZEB1, the shRNA-mediated knockdown of which up-regulated miR-375 and reduced TS cellular levels. The TS-ZEB1 association was confirmed in clinical specimens from lung tumours and in a genetic mouse model of pancreatic cancer with ZEB1 deletion. Interestingly, TS itself appeared to have a regulatory role in EMT in cancer cells, as TS knockdown could directly reduce the EMT phenotype, the migratory ability of cells, the expression of stem-like markers, and chemoresistance. Taken together, these data indicate that the TS enzyme is functionally linked with EMT and cancer differentiation, with several potential translational implications. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
EVALuna2:10226

Thymidylate synthase maintains the de-differentiated state of triple negative breast cancers - Siddiqui, Aarif; Gollavilli, Paradesi Naidu; Schwab, Annemarie; Vazakidou, Maria Eleni; Ersan, Pelin G.; Ramakrishnan, Mallika; Pluim, Dick; Coggins, Siana A.; Saatci, Ozge; Annaratone, Laura; HM Schellens, Jan; Kim, Baek; et al. (Cell Death and Differentiation, 2019)
Cancer cells frequently boost nucleotide metabolism (NM) to support their increased proliferation, but the consequences of elevated NM on tumor de-differentiation are mostly unexplored. Here, we identified a role for thymidylate synthase (TS), a NM enzyme and established drug target, in cancer cell de-differentiation and investigated its clinical significance in breast cancer (BC). In vitro, TS knockdown increased the population of CD24 + differentiated cells, and attenuated migration and sphere-formation. RNA-seq profiling indicated repression of epithelial-to-mesenchymal transition (EMT) signature genes upon TS knockdown, and TS-deficient cells showed an increased ability to invade and metastasize in vivo, consistent with the occurrence of a partial EMT phenotype. Mechanistically, TS enzymatic activity was found essential for maintenance of the EMT/stem-like state by fueling a dihydropyrimidine dehydrogenase—dependent pyrimidine catabolism. In patient tissues, TS levels were found significantly higher in poorly differentiated and in triple negative BC, and strongly correlated with worse prognosis. The present study provides the rationale to study in-depth the role of NM at the crossroads of proliferation and differentiation, and depicts new avenues for the design of novel drug combinations for the treatment of BC.
CRIS-Team Scopus Importer:2019-08-30

Tissue sodium storage: evidence for kidney-like extrarenal countercurrent systems? - Hofmeister, Lucas H.; Perisic, Stojan; Titze, Jens (Pflügers Archiv: European Journal of Physiology, 2015)
Recent evidence from chemical analysis of tissue electrolyte and water composition has shown that body Na(+) content in experimental animals is not constant, does not always readily equilibrate with water, and cannot be exclusively controlled by the renal blood purification process. Instead, large amounts of Na(+) are stored in the skin and in skeletal muscle. Quantitative non-invasive detection of Na(+) reservoirs with sodium magnetic resonance imaging ((23)NaMRI) suggests that this mysterious Na(+) storage is not only an animal research curiosity but also exists in humans. In clinical studies, tissue Na(+) storage is closely associated with essential hypertension. In animal experiments, modulation of reservoir tissue Na(+) content leads to predictable blood pressure changes. The available evidence thus suggests that the patho(?)-physiological process of Na(+) storage might be of relevance for human health and disease.
EVALuna2:3756

TRPA1-dependent calcium transients and CGRP release in DRG neurons require extracellular calcium - Gebhardt, Lisa; Kichko, Tetyana; Fischer, Michael J.M.; Reeh, Peter (The Journal of Cell Biology, 2020)
Shang et al. (2016. J. Cell Biol.https://doi.org/10.1083/jcb.201603081) reported that activation of lysosomal TRPA1 channels led to intracellular calcium transients and CGRP release from DRG neurons. We argue that both findings are more likely due to influx of insufficiently buffered extracellular calcium rather than lysosomal release.
CRIS-Team Scopus Importer:2020-06-02

X-linked inhibitor of apoptosis protein (XIAP) inhibition in systemic sclerosis (SSc) - Bergmann, Christina; Hallenberger, Ludwig; Chenguiti Fakhouri, Sara; Chenguiti Fakhouri, Sara; Merlevede, Benita; Brandt, Adrian; Dees, Clara; Zhu, Honglin; Zehender, Ariella; Zhou, Xiang; Schwab, Annemarie; Chen, Chih-Wei; et al. (Annals of the Rheumatic Diseases, 2021)
X-linked inhibitor of apoptosis protein (XIAP) is a multifunctional protein with important functions in apoptosis, cellular differentiation and cytoskeletal organisation and is emerging as potential target for the treatment of various cancers. The aim of the current study was to investigate the role of XIAP in the pathogenesis of systemic sclerosis (SSc). The expression of XIAP in human skin samples of patients with SSc and chronic graft versus host disease (cGvHD) and healthy individuals was analysed by quantitative PCR, immunofluorescence (IF) and western blot. XIAP was inactivated by siRNA-mediated knockdown and pharmacological inhibition. The effects of XIAP inactivation were analysed in cultured fibroblasts and in the fibrosis models bleomycin-induced and topoisomerase-I-(topoI)-induced fibrosis and in Wnt10b-transgenic mice. The expression of XIAP, but not of other inhibitor of apoptosis protein family members, was increased in fibroblasts in SSc and sclerodermatous cGvHD. Transforming growth factor beta (TGF-β) induced the expression of XIAP in a SMAD3-dependent manner. Inactivation of XIAP reduced WNT-induced fibroblast activation and collagen release. Inhibition of XIAP also ameliorated fibrosis induced by bleomycin, topoI and overexpression of Wnt10b in well-tolerated doses. The profibrotic effects of XIAP were mediated via WNT/β-catenin signalling. Inactivation of XIAP reduces binding of β-catenin to TCF to in a TLE-dependent manner to block WNT/β-catenin-dependent transcription. Our data characterise XIAP as a novel link between two core pathways of fibrosis. XIAP is overexpressed in SSc and cGvHD in a TGF-β/SMAD3-dependent manner and in turn amplifies the profibrotic effects of WNT/β-catenin signalling on fibroblasts via transducin-like enhancer of split 3. Targeted inactivation of XIAP inhibits the aberrant activation of fibroblasts in murine models of SSc.
CRIS-Team Scopus Importer:2021-05-07
Keywords: fibroblasts; pulmonary fibrosis; scleroderma; systemic

α-Synuclein deficiency promotes neuroinflammation by increasing Th1 cell-mediated immune responses - Ettle, Benjamin; Kuhbandner, Kristina; Joerg, Stefanie; Hoffmann, Alana; Winkler, Jürgen; Linker, Ralf (Journal of Neuroinflammation, 2016)
Increased ?-synuclein immunoreactivity has been associated with inflammatory activity in multiple sclerosis (MS) lesions, but the function of ?-synuclein in neuroinflammation remains unknown. The aim of this study was to examine the role of ?-synuclein in immunological processes in murine experimental autoimmune encephalomyelitis (EAE) as a model of MS.We studied EAE in wildtype (aSyn(+/+)) and ?-synuclein knockout (aSyn(-/-)) mice on a C57BL/6N background. In the spleen and spinal cord of aSyn(+/+) mice, we observed a gradual reduction of ?-synuclein expression during EAE, starting already in the pre-symptomatic disease phase. Compared to aSyn(+/+) mice, aSyn(-/-) mice showed an earlier onset of symptoms but no differences in symptom severity at the peak of disease. Earlier symptom onset was accompanied by increased spinal cord infiltration of CD4(+) T cells, predominantly of interferon-?-producing T helper 1 (Th1) cells, and reduced infiltration of regulatory T cells, whereas antigen-presenting cells were unaltered. Pre-symptomatically, aSyn(-/-) mice exhibited hyperproliferative CD4(+) splenocytes consistent with increased splenic interleukin-2 mRNA expression, resulting in increased numbers of Th1 cells in the spleen at the onset of symptoms.Our findings indicate a functional role of ?-synuclein in early EAE by increasing Th1 cell-mediated immune response.
EVALuna2:22458

5-Azacytidine prevents relapse and produces long-term complete remissions in leukemia xenografts treated with Moxetumomab pasudotox - Müller, Fabian; Cunningham, Tyler; Stookey, Stephanie; Tai, Chin-Hsien; Burkett, Sandra; Jailwala, Parthav; Stevenson, Maryalice Stetler; Cam, Margaret C.; Wayne, Alan S.; Pastan, Ira (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Moxetumomab pasudotox (Moxe) is a chimeric protein composed of an anti-CD22 Fv fused to a portion of Pseudomonas exotoxin A and kills CD22-expressing leukemia cells. It is very active in hairy-cell leukemia, but many children with relapsed/refractory acute lymphoblastic leukemia (ALL) either respond transiently or are initially resistant. Resistance to Moxe in cultured cells is due to low expression of diphthamide genes (DPH), but only two of six ALL blast samples from resistant patients had low DPH expression. To develop a more clinically relevant model of resistance, we treated NSG mice bearing KOPN-8 or Reh cells with Moxe. More than 99.9% of the cancer cells were killed by Moxe, but relapse occurred from discrete bone marrow sites. The resistant cells would no longer grow in cell culture and showed major chromosomal changes and changes in phenotype with greatly decreased CD22. RNA deep sequencing of resistant KOPN-8 blasts revealed global changes in gene expression, indicating dedifferentiation toward less-mature B cell precursors, and showed an up-regulation of myeloid genes. When Moxe was combined with 5-azacytidine, resistance was prevented and survival increased to over 5 months in the KOPN-8 model and greatly improved in the Reh model. We conclude that Moxe resistance in mice is due to a new mechanism that could not be observed using cultured cells and is prevented by treatment with 5-azacytidine.
EVALuna2:34163

Aberrant NOVA1 function disrupts alternative splicing in early stages of amyotrophic lateral sclerosis - Krach, Florian; Wheeler, Emily C.; Regensburger, Martin; Börstler, Tom; Wend, Holger; Vu, Anthony Q.; Wang, Ruth; Reischl, Stephanie; Boldt, Karsten; Batra, Ranjan; Aigner, Stefan; Ravits, John; et al. (Acta Neuropathologica, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal disease characterized by aberrant alternative splicing (AS). Nuclear loss and cytoplasmic accumulation of the splicing factor TDP-43 in motor neurons (MN) are hallmarks of ALS at late stages of the disease. However, it is unknown if altered AS is present before TDP-43 pathology occurs. Here, we investigate altered AS and its origins in early stages of ALS using human induced pluripotent stem cell-derived motor neurons (MNs) from sporadic and familial ALS patients. We find high levels of the RNA-binding proteins NOVA1, NOVA2, and RBFOX2 in the insoluble protein fractions and observe that AS events in ALS-associated MNs are enriched for binding sites of these proteins. Our study points to an early disrupted function of NOVA1 that drives AS changes in a complex fashion, including events caused by a consistent loss of NOVA1 function. NOVA1 exhibits increased cytoplasmic protein levels in early stage MNs without TDP-43 pathology in ALS postmortem tissue. As nuclear TDP-43 protein level depletes, NOVA1 is reduced. Potential indications for a reduction of NOVA1 also came from mice over-expressing TDP-43 lacking its nuclear localization signal and iPSC-MN stressed with puromycin. This study highlights that additional RBP-RNA perturbations in ALS occur in parallel to TDP-43.
CRIS-Team WoS Importer:2022-07-08

A Case Report of Severe Delirium after Amantadine Withdrawal - Marxreiter, Franz; Winkler, Jürgen; Uhl, Martin; Madzar, Dominik (Case Reports in Neurology, 2017)
Amantadine is frequently used in addition to dopaminergic substances like dopamine agonists or L-Dopa in advanced Parkinson disease (PD). However, adverse effects like hallucinations limit its use. PD patients developing severe psychotic symptoms upon treatment with either dopaminergic substances and/or amantadine need to stop intake of any psychotropic substance. Here, we report the case of a 71-year-old PD patient without previously known cognitive impairment. He presented with drug-induced psychotic symptoms due to changes in his therapeutic regimen (increase in COMT inhibitors, newly introduced MAO B inhibitors). Also, amantadine had been part of his long-term medication for more than 2 years. The severity of his psychotic symptoms required a L-Dopa monotherapy. After changing his medication, the patient developed severe delirium that resolved rapidly after i.v. amantadine infusion, suggesting an amantadine withdrawal syndrome. Amantadine withdrawal syndrome is a rare adverse event that may present even in PD patients without cognitive impairment. This case report highlights the need for a gradual withdrawal of amantadine even if acute and severe psychotic symptoms are present. Moreover, this is the first report of a cognitively unimpaired patient developing an amantadine withdrawal syndrome.
EVALuna2:36314

A conserved Eph family receptor-binding motif on the gH/gL complex of Kaposi's sarcoma-associated herpesvirus and rhesus monkey rhadinovirus - Grosskopf, Anna K.; Enßer, Armin; Neipel, Frank; Jungnickl, Doris; Schlagowski, Sarah; Desrosiers, Ronald C.; Hahn, Alexander S. (PLoS Pathogens, 2018)
Kaposi's sarcoma-associated herpesvirus (KSHV) is a human oncogenic virus associated with Kaposi's sarcoma and two B-cell malignancies. The rhesus monkey rhadinovirus (RRV) is a virus of nonhuman primates that is closely related to KSHV. Eph family receptor tyrosine kinases (Ephs) are cellular receptors for the gH/gL glycoprotein complexes of both KSHV and RRV. Through sequence analysis and mutational screens, we identified conserved residues in the N-terminal domain of KSHV and RRV glycoprotein H that are critical for Eph-binding in vitro. Homology-based structural predictions of the KSHV and RRV gH/gL complexes based on the Epstein-Barr-Virus gH/gL crystal structure located these amino acids in a beta-hairpin on gH, which is likely stabilized by gL and is optimally positioned for protein-protein interactions. Guided by these predictions, we generated recombinant RRV and KSHV strains mutated in the conserved motif as well as an RRV gL null mutant. Inhibition experiments using these mutants confirmed that disruption of the identified Eph-interaction motif or of gL expression resulted in complete detargeting from Ephs. However, all mutants were infectious on all cell types tested, exhibiting normal attachment but a reduction in infectivity of up to one log order of magnitude. While Eph-binding-negative RRV mutants were replication-competent on fibroblasts, their infectivity was comparatively more reduced on endothelial cells with a substantial subpopulation of endothelial cells remaining resistant to infection. Together, this provides evidence for a cell type-specific use of Ephs by RRV. Furthermore, our results demonstrate that gL is dispensable for infection by RRV. Its deletion caused a reduction in infectivity similar to that observed after mutation of Eph-binding residues in gH. Our findings would be compatible with an ability of KSHV and RRV to use other, less efficient entry mediators in lieu of Ephs, although these host factors may not be uniformly expressed by all cells.
EVALuna2:35289

Adhesion GPCR Gpr126 (Adgrg6) Expression Profiling in Zebrafish, Mouse, and Human Kidney. - Cazorla-Vázquez, Salvador; Kösters, Peter; Bertz, Simone; Pfister, Frederick; Daniel, Christoph; Dedden, Mark; Zundler, Sebastian; Jobst-Schwan, Tilman; Amann, Kerstin Ute; Engel, Felix (Cells, 2023)
Adhesion G protein-coupled receptors (aGPCRs) comprise the second-largest class of GPCRs, the most common target for approved pharmacological therapies. aGPCRs play an important role in development and disease and have recently been associated with the kidney. Several aGPCRs are expressed in the kidney and some aGPCRs are either required for kidney development or their expression level is altered in diseased kidneys. Yet, general aGPCR function and their physiological role in the kidney are poorly understood. Here, we characterize in detail Gpr126 (Adgrg6) expression based on RNAscope® technology in zebrafish, mice, and humans during kidney development in adults. Gpr126 expression is enriched in the epithelial linage during nephrogenesis and persists in the adult kidney in parietal epithelial cells, collecting ducts, and urothelium. Single-cell RNAseq analysis shows that gpr126 expression is detected in zebrafish in a distinct ionocyte sub-population. It is co-detected selectively with slc9a3.2, slc4a4a, and trpv6, known to be involved in apical acid secretion, buffering blood or intracellular pH, and to maintain high cytoplasmic Ca2+ concentration, respectively. Furthermore, gpr126-expressing cells were enriched in the expression of potassium transporter kcnj1a.1 and gcm2, which regulate the expression of a calcium sensor receptor. Notably, the expression patterns of Trpv6, Kcnj1a.1, and Gpr126 in mouse kidneys are highly similar. Collectively, our approach permits a detailed insight into the spatio-temporal expression of Gpr126 and provides a basis to elucidate a possible role of Gpr126 in kidney physiology.
EVALuna2:539836
Keywords: adhesion GPCR; kidney development; Gpr126; parietal epithelial cell; collecting duct; urothelium; ionocytes; zebrafish; RNAscope

ADSCs and adipocytes are the main producers in the autotaxin-lysophosphatidic acid axis of breast cancer and healthy mammary tissue in vitro - Schmid, Rafael; Wolf, Katharina; Robering, Jan Willem; Strauss, Selina; Strissel, Pamela; Strick, Reiner; Rübner, Matthias; Fasching, Peter; Horch, Raymund E.; Kremer, Andreas; Boos, Anja; Weigand, Annika (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common malignancy in women affecting one out of eight females throughout their lives. Autotaxin (ATX) is upregulated in breast cancer which results in increased lysophosphatidic acid (LPA) formation within the tumor. This study's aim was to identify the role of different mammary cell populations within the ATX-LPA axis. METHODS: Epithelial-cell-adhesion-molecule-positive (EpCAM) and -negative cells from breast tumors, adipose-derived stem cells (ADSCs) of tumor-adjacent and tumor-distant mammary fat were isolated and compared to healthy ADSCs, mammary epithelial cells (HMECs), and mesenchymal cells (MES) of healthy mammary tissue (n = 4 each) and further to well-established breast (cancer) cell lines. RESULTS: mRNA expression analyses revealed that ADSCs and MES largely expressed LPA receptor 1 (LPAR1) while epithelial cells mainly expressed LPAR6. LPA 18:1 activated all the cell populations and cell lines by rise in cytosolic free calcium concentrations. MES and ADSCs expressed ATX whereas epithelial cells did not. ADSCs revealed the highest expression in ATX with a significant decline after adipogenic differentiation in healthy ADSCs, whereas ATX expression increased in ADSCs from tumor patients. Breast (cancer) cell lines did not express ATX. Transmigration of MES was stimulated by LPA whereas an inhibitory effect was observed in epithelial cells with no differences between tumors and healthy cells. Triple-negative breast cancer (TNBC) cell lines were also stimulated and the transmigration partly inhibited using the LPA receptor antagonist Ki16425. CONCLUSIONS: We here show that each mammary cell population plays a different role in the ATX-LPA axis with ADSCs and adipocytes being the main source of ATX in tumor patients in our experimental setting. Inhibitors of this axis may therefore present a valuable target for pharmacological therapies.
EVALuna2:35125

Adult alcohol drinking and emotional tone are mediated by neutral sphingomyelinase during development in males - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Cerebral Cortex, 2022)
Alcohol use, abuse, and addiction, and resulting health hazards are highly sex-dependent with unknown mechanisms. Previously, strong links between the SMPD3 gene and its coded protein neutral sphingomyelinase 2 (NSM) and alcohol abuse, emotional behavior, and bone defects were discovered and multiple mechanisms were identified for females. Here we report strong sex-dimorphisms for central, but not for peripheral mechanisms of NSM action in mouse models. Reduced NSM activity resulted in enhanced alcohol consumption in males, but delayed conditioned rewarding effects. It enhanced the acute dopamine response to alcohol, but decreased monoaminergic systems adaptations to chronic alcohol. Reduced NSM activity increased depression- and anxiety-like behavior, but was not involved in alcohol use for the self-management of the emotional state. Constitutively reduced NSM activity impaired structural development in the brain and enhanced lipidomic sensitivity to chronic alcohol. While the central effects were mostly opposite to NSM function in females, similar roles in bone-mediated osteocalcin release and its effects on alcohol drinking and emotional behavior were observed. These findings support the view that the NSM and multiple downstream mechanism may be a source of the sex-differences in alcohol use and emotional behavior.
CRIS-Team WoS Importer:2022-04-15
Keywords: neutral sphingomyelinase; osteocalcin; depression; alcohol; anxiety

A human periodontal ligament fibroblast cell line as a new model to study periodontal stress - Weider, Matthias; Schröder, Agnes; Docheva, Denitsa; Rodrian, Gabriele; Enderle, Isabel; Seidel, Corinna Lesley; Andreev, Darja; Wegner, Michael; Bozec, Aline; Deschner, James; Kirschneck, Christian; Proff, Peter; et al. (International Journal of Molecular Sciences, 2020)
The periodontal ligament (PDL) is exposed to different kinds of mechanical stresses such as bite force or orthodontic tooth movement. A simple and efficient model to study molecular responses to mechanical stress is the application of compressive force onto primary human periodontal ligament fibroblasts via glass disks. Yet, this model suffers from the need for primary cells from human donors which have a limited proliferative capacity. Here we show that an immortalized cell line, PDL-hTERT, derived from primary human periodontal ligament fibroblasts exhibits characteristic responses to glass disk-mediated compressive force resembling those of primary cells. These responses include induction and secretion of pro-inflammatory markers, changes in expression of extracellular matrix-reorganizing genes and induction of genes related to angiogenesis, osteoblastogenesis and osteoclastogenesis. The fact that PDL-hTERT cells can easily be transfected broadens their usefulness, as molecular gain- and loss-of-function studies become feasible.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Bone remodeling; Cell culture techniques; Mechanical loading; Orthodontic tooth movement

Alpha-synuclein prevents the formation of spherical mitochondria and apoptosis under oxidative stress - Winner, Beate; Menges, Stefanie; Minakaki, Georgia; Schaefer, Patrick; Meixner, Holger; Prots, Iryna; Schlötzer-Schrehardt, Ursula; Friedland, Kristina; Outeiro, Tiago F.; Winklhofer, Konstanze F.; Von Arnim, Christine A. F.; Xiang, Wei; et al. (Scientific Reports, 2017)
Oxidative stress (OS), mitochondrial dysfunction, and dysregulation of alpha-synuclein (aSyn) homeostasis are key pathogenic factors in Parkinson's disease. Nevertheless, the role of aSyn in mitochondrial physiology remains elusive. Thus, we addressed the impact of aSyn specifically on mitochondrial response to OS in neural cells. We characterize a distinct type of mitochondrial fragmentation, following H2O2 or 6-OHDA-induced OS, defined by spherically-shaped and hyperpolarized mitochondria, termed "mitospheres". Mitosphere formation mechanistically depended on the fission factor Drp1, and was paralleled by reduced mitochondrial fusion. Furthermore, mitospheres were linked to a decrease in mitochondrial activity, and preceded Caspase3 activation. Even though fragmentation of dysfunctional mitochondria is considered to be a prerequisite for mitochondrial degradation, mitospheres were not degraded via Parkin-mediated mitophagy. Importantly, we provide compelling evidence that aSyn prevents mitosphere formation and reduces apoptosis under OS. In contrast, aSyn did not protect against Rotenone, which led to a different, previously described donut-shaped mitochondrial morphology. Our findings reveal a dichotomic role of aSyn in mitochondrial biology, which is linked to distinct types of stress-induced mitochondrial fragmentation. Specifically, aSyn may be part of a cellular defense mechanism preserving neural mitochondrial homeostasis in the presence of increased OS levels, while not protecting against stressors directly affecting mitochondrial function.

Alternative NF-kappa B Signaling Discriminates Induction of the Tumor Marker Fascin by the Viral Oncoproteins Tax-1 and Tax-2 of Human T-Cell Leukemia Viruses - Heym, Stefanie; Mohr, Caroline; Engelbrecht, Hanna C.; Fleckenstein, Bernhard; Thoma-Kreß, Andrea (Cancers, 2022)
Simple Summary:& nbsp;The actin-bundling protein Fascin is upregulated in many types of cancers, including adult T-cell leukemia/lymphoma, a tumor induced by the oncogenic retrovirus human T-cell leukemia virus type 1 (HTLV-1). Transcriptional regulation of Fascin is heterogeneous between different cell types and tissues, and Fascin is usually expressed at low levels in T-cells. We have previously shown that a single viral oncoprotein, Tax-1 of HTLV-1, is a potent inducer of Fascin in T-cells depending on classical NF-kappa B signaling. In this study, we discovered that transcriptional activation of Fascin by viral oncoproteins depends on activity of both the classical and the alternative NF-kappa B signaling cascade. Comparisons between Tax-1 and Tax-2 from the closely related but non-oncogenic HTLV-2 revealed that alternative NF-kappa B signaling discriminates transcriptional induction of Fascin by the Tax proteins encoded by HTLVs. Together, Tax-1 and Tax-2 proteins are useful tools to study oncogenic signaling in T-cells.& nbsp;Transcriptional regulation of the actin-bundling protein and tumor marker Fascin is highly diverse depending on cell and tumor type. Previously, we discovered that the viral oncoprotein Tax-1 of human T-cell leukemia virus type 1 (HTLV-1) considerably enhances Fascin expression in T-cells, depending on classical NF-kappa B signaling. In this study, we asked if the non-oncogenic Tax-2 of the related HTLV-2 is still able to induce Fascin by using luciferase assays, immunoblot, and qPCR. We found that Tax-2 only slightly induces Fascin expression compared to Tax-1; however, both Tax-1 and Tax-2 comparably activated a 1.6 kb fragment in the human Fascin promoter including Tax-responsive elements. Furthermore, we identified a link between Tax-induced activity of the alternative NF-kappa B pathway and Fascin induction. While treatment with the second mitochondria-derived activator of caspases (SMAC)-mimetic AZD5582, a compound known to robustly activate alternative NF-kappa B signaling, did not induce Fascin, combination of AZD5582 with activation of classical NF-kappa B signaling by Tax-2 significantly induced Fascin expression. In conclusion, our data demonstrate that both classical and alternative NF-kappa B activity are necessary for strong Fascin induction by the viral Tax oncoproteins, thus, shedding new light on the regulation of Fascin in T-cells and during viral transformation.
CRIS-Team WoS Importer:2022-03-11
Keywords: Fascin; tumor virus; HTLV-1; human T-cell leukemia virus type 1; alternative NF-κB; viral oncoprotein; Tax-1; Tax-2

Alternative Splice Forms of CYLD Mediate Ubiquitination of SMAD7 to Prevent TGFB Signaling and Promote Colitis - Tang, Yilang; Reissig, Sonja; Glasmacher, Elke; Regen, Tommy; Wanke, Florian; Nikolaev, Alexei; Gerlach, Katharina; Popp, Vanessa; Karram, Khalad; Fantini, Massimo C.; Schattenberg, Jam M.; Galle, Peter R.; et al. (Gastroenterology, 2019)
BACKGROUND & AIMS: The CYLD lysine 63 deubiquitinase gene (CYLD) encodes tumor suppressor protein that is mutated in familial cylindromatosus, and variants have been associated with Crohn disease (CD). Splice forms of CYLD that lack exons 7 and 8 regulate transcription factors and functions of immune cells. We examined the expression of splice forms of CYLD in colon tissues from patients with CD and their effects in mice. METHODS: We performed immunohistochemical analyses of colon tissues from patients with untreated CD and patients without inflammatory bowel diseases (controls). We obtained mice that expressed splice forms of CYLD (sCYLD mice) without or with SMAD7 (sCYLD/SMAD7 mice) from transgenes and CYLD-knockout mice (with or without transgenic expression of SMAD7) and performed endoscopic analyses. Colitis was induced in Rag1(-/-) mice by transfer of CD4(+) CD62L(+) T cells from C57/Bl6 or transgenic mice. T cells were isolated from mice and analyzed by flow cytometry and quantitative realtime polymerase chain reaction and intestinal tissues were analyzed by histology and immunohistochemistry. CYLD forms were expressed in mouse embryonic fibroblasts, primary T cells, and HEK293T cells, which were analyzed by immunoblot, mobility shift, and immunoprecipitation assays. RESULTS: The colonic lamina propria from patients with CD was infiltrated by T cells and had higher levels of sCYLD (but not full-length CYLD) and SMAD7 than tissues from controls. Incubation of mouse embryonic fibroblasts and T cells with transforming growth factor b increased their production of sCYLD and decreased full-length CYLD. Transgenic expression of sCYLD and SMAD7 in T cells prevented the differentiation of regulatory T cells and T-helper type 17 cells and increased the differentiation of T-helper type 1 cells. The same effects were observed in colon tissues from sCYLD/SMAD7 mice but not in those from CYLD-knockout SMAD7 mice. The sCYLD mice had significant increases in the numbers of T-helper type 1 cells and CD44high CD62Llow memory-effector CD4(+) T cells in the spleen and mesenteric lymph nodes compared with wild-type mice; sCYLD/SMAD7 mice had even larger increases. The sCYLD/ SMAD7 mice spontaneously developed severe colitis, with infiltration of the colon by dendritic cells, neutrophils, macrophages, and CD4(+) T cells and increased levels of Ifng, Il6, Il12a, Il23a, and Tnf mRNAs. Co-transfer of regulatory T cells from wild-type, but not from sCYLD/SMAD7, mice prevented the induction of colitis in Rag1(-/-) mice by CD4(+) T cells. We found increased levels of poly-ubiquitinated SMAD7 in sCYLD CD4(+)T cells. CYLD formed a nuclear complex with SMAD3, whereas sCYLD recruited SMAD7 to the nucleus, which inhibited the expression of genes regulated by SMAD3 and SMAD4. We found that sCYLD mediated lysine 63-linked ubiquitination of SMAD7. The sCYLD-SMAD7 complex inhibited transforming growth factor beta signaling in CD4(+)T cells. CONCLUSIONS: Levels of the spliced form of CYLD are increased in colon tissues from patients with CD. sCYLD mediates ubiquitination and nuclear translocation of SMAD7 and thereby decreases transforming growth factor beta signaling in T cells. This prevents immune regulatory mechanisms and leads to colitis in mice.
CRIS-Team WoS Importer:2019-02-21

Alternative Wnt-signaling axis leads to a break of oncogene-induced senescence - Kluge, Viola; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Zimmermann, Tom; Pommer, Michaela; Kuphal, Silke; Boßerhoff, Anja Katrin (Cell Death & Disease, 2024)
Oncogene-induced senescence (OIS) is an important process that suppresses tumor development, but the molecular mechanisms of OIS are still under investigation. It is known that BRAFV600E-mutated melanocytes can overcome OIS and develop melanoma, but the underlying mechanism is largely unknown. Using an established OIS model of primary melanocytes transduced with BRAFV600E, YAP activity was shown to be induced in OIS as well as in melanoma cells compared to that in normal epidermal melanocytes. This led to the assumption that YAP activation itself is not a factor involved in the disruption of OIS. However, its role and interaction partners potentially change. As Wnt molecules are known to be important in melanoma progression, these molecules were the focus of subsequent studies. Interestingly, activation of Wnt signaling using AMBMP resulted in a disruption of OIS in BRAFV600E-transduced melanocytes. Furthermore, depletion of Wnt6, Wnt10b or β-catenin expression in melanoma cells resulted in the induction of senescence. Given that melanoma cells do not exhibit canonical Wnt/β-catenin activity, alternative β-catenin signaling pathways may disrupt OIS. Here, we discovered that β-catenin is an interaction partner of YAP on DNA in melanoma cells. Furthermore, the β-catenin–YAP interaction changed the gene expression pattern from senescence-stabilizing genes to tumor-supportive genes. This switch is caused by transcriptional coactivation via the LEF1/TEAD interaction. The target genes with binding sites for LEF1 and TEAD are involved in rRNA processing and are associated with poor prognosis in melanoma patients. This study revealed that an alternative YAP-Wnt signaling axis is an essential molecular mechanism leading to OIS disruption in melanocytes. (Figure presented.).
CRIS-Team Scopus Importer:2024-03-01

A miRNA181a/NFAT5 axis links impaired T cell tolerance induction with autoimmune type 1 diabetes - Serr, Isabelle; Scherm, Martin G.; Zahm, Adam M.; Schug, Jonathan; Flynn, Victoria K.; Hippich, Markus; Kaelin, Stefanie; Becker, Maike; Achenbach, Peter; Nikolaev, Alexei; Gerlach, Katharina; Liebsch, Nicole; et al. (Science Translational Medicine, 2018)
Molecular checkpoints that trigger the onset of islet autoimmunity or progression to human type 1 diabetes (T1D) are incompletely understood. Using T cells from children at an early stage of islet autoimmunity without clinical T1D, we find that a microRNA181a (miRNA181a)-mediated increase in signal strength of stimulation and costimulation links nuclear factor of activated T cells 5 (NFAT5) with impaired tolerance induction and autoimmune activation. We show that enhancing miRNA181a activity increases NFAT5 expression while inhibiting FOXP3+ regulatory T cell (T-reg) induction in vitro. Accordingly, Treg induction is improved using T cells from NFAT5 knockout (NFAT5ko) animals, whereas altering miRNA181a activity does not affect T-reg induction in NFAT5ko T cells. Moreover, high costimulatory signals result in phosphoinositide 3-kinase (PI3K)-mediated NFAT5, which interferes with FoxP(3+) Treg induction. Blocking miRNA181a or NFAT5 increases Treg induction in murine and humanized models and reduces murine islet autoimmunity in vivo. These findings suggest targeting miRNA181a and/or NFAT5 signaling for the development of innovative personalized medicines to limit islet autoimmunity.
EVALuna2:33886

A monoclonal Trd chain supports the development of the complete set of functional γδ T cell lineages - Hahn, Anne Maria; Vogg, Lisa; Brey, Stefanie; Schneider, Andrea; Schäfer, Simon; Palmisano, Ralf; Pavlova, Anna; Sandrock, Inga; Tan, Likai; Fichtner, Alina S.; Prinz, Immo; Ravens, Sarina; et al. (Cell Reports, 2023)
The clonal selection theory describes key features of adaptive immune responses of B and T cells. For αβ T cells and B cells, antigen recognition and selection principles are known at a detailed molecular level. The precise role of the antigen receptor in γδ T cells remains less well understood. To better understand the role of the γδ T cell receptor (TCR), we generate an orthotopic TCRδ transgenic mouse model. We demonstrate a multi-layered functionality of γδ TCRs and diverse roles of CDR3δ-mediated selection during γδ T cell development. Whereas epithelial populations using Vγ5 or Vγ7 chains are almost unaffected in their biology in the presence of the transgenic TCRδ chain, pairing with Vγ1 positively selects γδ T cell subpopulations with distinct programs in several organs, thereby distorting the repertoire. In conclusion, our data support dictation of developmental tropism together with adaptive-like recognition principles in a single antigen receptor.
CRIS-Team Scopus Importer:2023-03-24
Keywords: CP: Immunology

A monocyte gene expression signature in the early clinical course of Parkinson's disease - Schlachetzki, Johannes; Prots, Iryna; Tao, Jenhan; Chun, Hyun B.; Saijo, Kaoru; Gosselin, David; Winner, Beate; Glass, Christopher K.; Winkler, Jürgen (Scientific Reports, 2018)
Microglia are the main immune cells of the brain and express a large genetic pattern of genes linked to Parkinson's disease risk alleles. Monocytes like microglia are myeloid-lineage cells, raising the questions of the extent to which they share gene expression with microglia and whether they are already altered early in the clinical course of the disease. To decipher a monocytic gene expression signature in Parkinson's disease, we performed RNA-seq and applied the two-sample Kolmogorov-Smirnov test to identify differentially expressed genes between controls and patients with Parkinson's disease and changes in gene expression variability and dysregulation. The gene expression profiles of normal human monocytes and microglia showed a plethora of differentially expressed genes. Additionally, we identified a distinct gene expression pattern of monocytes isolated from Parkinson's disease patients at an early disease stage compared to controls using the Kolmogorov-Smirnov test. Differentially expressed genes included genes involved in immune activation such as HLA-DQB1, MYD88, REL, and TNF-alpha. Our data suggest that future studies of distinct leukocyte subsets are warranted to identify possible surrogate biomarkers and may lead to the identification of novel interventions early in the disease course.
EVALuna2:35780

Amphiregulin Regulates Melanocytic Senescence - Pommer, Michaela; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2021)
Oncogene-induced senescence (OIS) is a decisive process to suppress tumor development, but the molecular details of OIS are still under investigation. Using an established OIS model of primary melanocytes transduced with BRAF V600E and compared to control cells, amphiregulin (AREG) was shown to be induced. In addition, AREG expression was observed in nevi, which by definition, are senescent cell clusters, compared to melanocytes. Interestingly, treatment of melanocytes with recombinant AREG did induce senescence. This led to the assumption that extracellular AREG has an important function in this process. Inhibition of the epidermal growth factor receptor (EGFR) using Gefitinib identified AREG as one of EGFR ligands responsible for senescence. Furthermore, depletion of AREG expression in senescent BRAF V600E melanocytes resulted in a significant reduction of senescent melanocytes. This study reveals AREG as an essential molecular component of signaling pathways leading to senescence in melanocytes.
CRIS-Team Scopus Importer:2021-03-05
Keywords: amphiregulin; AREG; normal human primary melanocytes; OIS; oncogene induced senescence

An aggregon in conductin/axin2 regulates Wnt/β-catenin signaling and holds potential for cancer therapy - Bernkopf, Dominic; Brückner, Martina; Hadjihannas, Michel; Behrens, Jürgen (Nature Communications, 2019)
The paralogous scaffold proteins axin and conductin/axin2 are key factors in the negative regulation of the Wnt pathway transcription factor β-catenin, thereby representing interesting targets for signaling regulation. Polymerization of axin proteins is essential for their activity in suppressing Wnt/β-catenin signaling. Notably, conductin shows less polymerization and lower activity than axin. By domain swapping between axin and conductin we here identify an aggregation site in the conductin RGS domain which prevents conductin polymerization. Induction of conductin polymerization by point mutations of this aggregon results in enhanced inhibition of Wnt/β-catenin signaling. Importantly, we identify a short peptide which induces conductin polymerization via masking the aggregon, thereby enhancing β-catenin degradation, inhibiting β-catenin-dependent transcription and repressing growth of colorectal cancer cells. Our study reveals a mechanism for regulating signaling pathways via the polymerization status of scaffold proteins and suggests a strategy for targeted colorectal cancer therapy.
CRIS-Team Scopus Importer:2019-09-27

An alternative splicing modulator decreases mutant HTT and improves the molecular fingerprint in Huntington’s disease patient neurons - Krach, Florian; Stemick, Judith; Börstler, Tom; Weiss, Alexander; Lingos, Ioannis; Reischl, Stephanie; Meixner, Holger; Ploetz, Sonja; Farrell, Michaela; Hehr, Ute; Kohl, Zacharias; Winner, Beate; et al. (Nature Communications, 2022)
Huntington’s disease (HD) is a neurodegenerative disorder caused by poly-Q expansion in the Huntingtin (HTT) protein. Here, we delineate elevated mutant HTT (mHTT) levels in patient-derived cells including fibroblasts and iPSC derived cortical neurons using mesoscale discovery (MSD) HTT assays. HD patients’ fibroblasts and cortical neurons recapitulate aberrant alternative splicing as a molecular fingerprint of HD. Branaplam is a splicing modulator currently tested in a phase II study in HD (NCT05111249). The drug lowers total HTT (tHTT) and mHTT levels in fibroblasts, iPSC, cortical progenitors, and neurons in a dose dependent manner at an IC50 consistently below 10 nM without inducing cellular toxicity. Branaplam promotes inclusion of non-annotated novel exons. Among these Branaplam-induced exons, there is a 115 bp frameshift-inducing exon in the HTT transcript. This exon is observed upon Branaplam treatment in Ctrl and HD patients leading to a profound reduction of HTT RNA and protein levels. Importantly, Branaplam ameliorates aberrant alternative splicing in HD patients’ fibroblasts and cortical neurons. These findings highlight the applicability of splicing modulators in the treatment of CAG repeat disorders and decipher their molecular effects associated with the pharmacokinetic and -dynamic properties in patient-derived cellular models.
CRIS-Team Scopus Importer:2022-11-25

Analysis of SARS-CoV-2 Spike Protein Variants with Recombinant Reporter Viruses Created from a Bacmid System - Cordsmeier, Arne; Jungnickl, Doris; Herrmann, Alexandra; Korn, Klaus; Enßer, Armin (International Journal of Molecular Sciences, 2023)
SARS-CoV-2, the causative agent of COVID-19, has spread around the world with more than 700 million cases and 6.8 million deaths. Various variants of concern (VoC) have emerged due to mutations and recombination and concurrent selection for increased viral fitness and immune evasion. The viral protein that primarily determines the pathogenicity, infectivity, and transmissibility is the Spike protein. To analyze the specific impact of variant Spike proteins on infection dynamics, we constructed SARS-CoV-2 with a uniform B.1 backbone but with alternative Spike proteins. In addition, ORF6 was replaced by EYFP as a biological safety measure, and for use of this well-established reporter. We show that namely the delta variant Spike proteins cause a distinct phenotype from the wild type (B.1, D614G) and other variants of concern. Furthermore, we demonstrate that the omicron BA.1 Spike results in lower viral loads and a less efficient spread in vitro. Finally, we utilized viruses with the two different reporters EYFP and mCherry to establish a competitive growth assay, demonstrating that most but not all Spike variant viruses were able to outcompete wild type SARS-CoV-2 B.1.
CRIS-Team Scopus Importer:2023-05-26
Keywords: SARS-CoV-2; Spike protein; variants of concern

Analysis of the expression pattern of the schizophrenia-risk and intellectual disability gene TCF4 in the developing and adult brain suggests a role in development and plasticity of cortical and hippocampal neurons - Jung, Matthias; Häberle, Benjamin; Tschaikowsky, Tristan; Wittmann, Marie-Theres; Balta, Elli-Anna; Stadler, Vivien-Charlott; Zweier, Christiane; Dörfler, Arnd; Gloeckner, Christian Johannes; Lie, Dieter Chichung (Molecular Autism, 2018)
Background: Haploinsufficiency of the class I bHLH transcription factor TCF4 causes Pitt-Hopkins syndrome (PTHS), a severe neurodevelopmental disorder, while common variants in the TCF4 gene have been identified as susceptibility factors for schizophrenia. It remains largely unknown, which brain regions are dependent on TCF4 for their development and function. Methods: We systematically analyzed the expression pattern of TCF4 in the developing and adult mouse brain. We used immunofluorescent staining to identify candidate regions whose development and function depend on TCF4. In addition, we determined TCF4 expression in the developing rhesus monkey brain and in the developing and adult human brain through analysis of transcriptomic datasets and compared the expression pattern between species. Finally, we morphometrically and histologically analyzed selected brain structures in Tcf4-haploinsufficient mice and compared our morphometric findings to neuroanatomical findings in PTHS patients. Results: TCF4 is broadly expressed in cortical and subcortical structures in the developing and adult mouse brain. The TCF4 expression pattern was highly similar between humans, rhesus monkeys, and mice. Moreover, Tcf4 haploinsufficiency in mice replicated structural brain anomalies observed in PTHS patients. Conclusion: Our data suggests that TCF4 is involved in the development and function of multiple brain regions and indicates that its regulation is evolutionary conserved. Moreover, our data validate Tcf4-haploinsufficient mice as a model to study the neurodevelopmental basis of PTHS.
EVALuna:34022

Analysis of the human SOX10 mutation Q377X in mice and its implications for genotype-phenotype correlation in SOX10-related human disease. - Truch, Kathrin; Arter, Juliane; Turnescu, Tanja; Weider, Matthias; Hartwig, Anna; Tamm, Ernst R.; Sock, Elisabeth; Wegner, Michael (Human Molecular Genetics, 2018)
UnivIS-Import:2018-09-11:Pub.2018.med.IB.LPCIPDBI.analys

An endemic–epidemic beta model for time series of infectious disease proportions - Lu, Junyi; Meyer, Sebastian (Journal of Applied Statistics, 2021)
Time series of proportions of infected patients or positive specimens are frequently encountered in disease control and prevention. Since proportions are bounded and often asymmetrically distributed, conventional Gaussian time series models only apply to suitably transformed proportions. Here we borrow both from beta regression and from the well-established HHH model for infectious disease counts to propose an endemic–epidemic beta model for proportion time series. It accommodates the asymmetric shape and heteroskedasticity of proportion distributions and is consistent for complementary proportions. Coefficients can be interpreted in terms of odds ratios. A multivariate formulation with spatial power-law weights enables the joint estimation of model parameters from multiple regions. In our application to a flu activity index in the USA, we find that the endemic–epidemic beta model provides a better fit than a seasonal ARIMA model for the logit-transformed proportions. Furthermore, a multivariate approach can improve regional forecasts and reduce model complexity in comparison to univariate beta models stratified by region.
CRIS-Team Scopus Importer:2021-08-20
Keywords: beta regression; epidemic modelling; influenza-like illness; Multivariate time series; seasonality

Angiocrine Regulation of Epithelial Barrier Integrity in Inflammatory Bowel Disease - Stürzl, Michael; Kunz, Meik; Krug, Susanne M.; Naschberger, Elisabeth (Frontiers in Medicine, 2021)
Inflammatory bowel disease describes chronic inflammatory disorders. The incidence of the disease is rising. A major step in disease development is the breakdown of the epithelial cell barrier. Numerous blood vessels are directly located underneath this barrier. Diseased tissues are heavily vascularized and blood vessels significantly contribute to disease progression. The gut-vascular barrier (GVB) is an additional barrier controlling the entry of substances into the portal circulation and to the liver after passing the first epithelial barrier. The presence of the GVB rises the question, whether the vascular and endothelial barriers may communicate bi-directionally in the regulation of selective barrier permeability. Communication from epithelial to endothelial cells is well-accepted. In contrast, little is known on the respective backwards communication. Only recently, perfusion-independent angiocrine functions of endothelial cells were recognized in a way that endothelial cells release specific soluble factors that may directly act on the epithelial barrier. This review discusses the putative involvement of angiocrine inter-barrier communication in the pathogenesis of IBD.
CRIS-Team Scopus Importer:2021-08-27
Keywords: angiocrine; angiogenesis; barrier; endothelial; epithelial; inflammation; inflammatory bowel disease

Animal models of psychoactive drug use and addiction - Present problems and future needs for translational approaches - Müller, Christian P. (Behavioural Brain Research, 2018)
Drug addiction is a psychiatric disorder based on a dysfunction of the brain. It frequently develops from a controlled drug consumption and drug instrumentalization (DI). Thereby, DI is the use of a drug to improve specific non-drug related behaviors, beyond the drug's direct positive or negative reinforcing effects. Currently available pharmacotherapies for drug addiction show low effect size and rather limited long-term efficacy, which suggests that current theories on addiction are still insufficient in how they capture the phenomenon and how they allow predictions for highly efficient treatments. This opinion review attempts a critical analysis of some aspects of current addiction neuroscience using animal models. As a result, (1) animal models that cover previously neglected types of drug memories in controlled drug use are suggested. (2) Animal models for drug instrumentalization are warranted. Animal models of drug addiction should consider that addiction develops predominantly in individuals with mental and/or environmental challenges. It is suggested (3) to preferentially use animal models with similar mental and environmental challenges to model the transition of controlled to compulsive drug use. (4) Animal models should in the future also capture the important aspect of the motivation to self-medicate in order to ameliorate a negative emotional/physical state. Potential pharmaco-treatments of addiction, in order to later achieve compliance in humans, should be tested for their systemic self-administration in order to self-medicate a drug-induced aversive state. This may allow a better understanding of the fundamental differences between an organism that shows controlled psychoactive drug consumption as an integral part of a 'normal' behavioral repertoire and one in a pathological condition with compulsive drug abuse.
EVALuna2:36576

A novel human stem cell model for Coffin-Siris syndrome-like syndrome reveals the importance of SOX11 dosage for neuronal differentiation and survival - Turan, Sören; Börstler, Tom; Kavyanifar, Atria; Loskarn, Sandra; Reis, André; Winner, Beate; Lie, Dieter Chichung (Human Molecular Genetics, 2019)
The SOXC transcription factors Sox4, Sox11 and Sox12, are critical neurodevelopmental regulators that are thought to function in a highly redundant fashion. Surprisingly, heterozygous missense mutations or deletions of SOX11 were recently detected in patients with Coffin-Siris syndrome-like syndrome (CSSLS), a neurodevelopmental disorder associated with intellectual disability, demonstrating that in humans SOX11 haploinsufficiency cannot be compensated and raising the question of the function of SOX11 in human neurodevelopment. Here, we describe the generation of SOX11(+/-) heterozygous human embryonic stem cell (hESC) lines by CRISPR/Cas9 genome engineering. SOX11 haploinsufficiency impaired the generation of neurons and resulted in a proliferation/differentiation imbalance of neural precursor cells and enhanced neuronal cell death. Using the SOX11(+/-) hESC model we provide for the first time experimental evidence that SOX11 haploinsufficiency is sufficient to impair key processes of human neurodevelopment, giving a first insight into the pathophysiology of CSSLS and SOX11 function in human neurodevelopment.
CRIS-Team WoS Importer:2019-11-12

A novel immunoregulatory function of beta-2-microglobulin as a promoter of myeloid derived suppressor cell induction - Bruns, Heiko; Jitschin, Simon; Gamali, Sara; Saul, Domenica; Böttcher, Martin; Mackensen, Andreas; Jitschin, Regina; Mougiakakos, Dimitrios (Leukemia, 2019)
EVALuna2:35231

A novel positive feedback-loop between the HTLV-1 oncoprotein Tax and NF-κB activity in T-cells - Millen, Sebastian; Meretuk, Lina; Göttlicher, Tim; Schmitt, Sonja; Fleckenstein, Bernhard; Thoma-Kreß, Andrea (Retrovirology, 2020)
BACKGROUND: Human T-cell leukemia virus type 1 (HTLV-1) infects primarily CD4+ T-lymphocytes and evoques severe diseases, predominantly Adult T-Cell Leukemia/ Lymphoma (ATL/L) and HTLV-1-associated Myelopathy/ Tropical Spastic Paraparesis (HAM/TSP). The viral transactivator of the pX region (Tax) is important for initiating malignant transformation, and deregulation of the major signaling pathway nuclear factor of kappa B (NF-κB) by Tax represents a hallmark of HTLV-1 driven cancer. RESULTS: Here we found that Tax mutants which are defective in NF-κB signaling showed diminished protein expression levels compared to Tax wildtype in T-cells, whereas Tax transcript levels were comparable. Strikingly, constant activation of NF-κB signaling by the constitutive active mutant of inhibitor of kappa B kinase (IKK2, IKK-β), IKK2-EE, rescued protein expression of the NF-κB defective Tax mutants M22 and K1-10R and even increased protein levels of Tax wildtype in various T-cell lines while Tax transcript levels were only slightly affected. Using several Tax expression constructs, an increase of Tax protein occurred independent of Tax transcripts and independent of the promoter used. Further, Tax and M22 protein expression were strongly enhanced by 12-O-Tetradecanoylphorbol-13-Acetate [TPA; Phorbol 12-myristate 13-acetate (PMA)]/ ionomycin, inducers of NF-κB and cytokine signaling, but not by tumor necrosis factor alpha (TNF-α). On the other hand, co-expression of Tax with a dominant negative inhibitor of κB, IκBα-DN, or specific inhibition of IKK2 by the compound ACHP, led to a vast decrease in Tax protein levels to some extent independent of Tax transcripts in transiently transfected and Tax-transformed T-cells. Cycloheximide chase experiments revealed that co-expression of IKK2-EE prolongs the half-life of M22, and constant repression of NF-κB signaling by IκBα-DN strongly reduces protein stability of Tax wildtype suggesting that NF-κB activity is required for Tax protein stability. Finally, protein expression of Tax and M22 could be recovered by NH4Cl and PYR-41, inhibitors of the lysosome and the ubiquitin-activating enzyme E1, respectively. CONCLUSIONS: Together, these findings suggest that Tax's capability to induce NF-κB is critical for protein expression and stabilization of Tax itself. Overall, identification of this novel positive feedback loop between Tax and NF-κB in T-cells improves our understanding of Tax-driven transformation.
CRIS-Team Scopus Importer:2020-09-25
Keywords: HTLV-1; IKK2; M22; NF-κB; Protein stability; Tax-1

Antibodies Targeting KSHV gH/gL Reveal Distinct Neutralization Mechanisms - Fricke, Thomas; Großkopf, Anna K.; Enßer, Armin; Backovic, Marija; Hahn, Alexander S. (Viruses, 2022)
Kaposi’s sarcoma herpesvirus (KSHV) is associated with a significant disease burden, in particular in Sub-Sahara Africa. A KSHV vaccine would be highly desirable, but the mechanisms underlying neutralizing antibody responses against KSHV remain largely unexplored. The complex made of glycoproteins H and L (gH/gL) activates gB for the fusion of viral and cellular membranes in all herpesviruses. KSHV gH/gL also interacts with cellular Eph family receptors. To identify optimal antigens for vaccination and to elucidate neutralization mechanisms, we primed mice with recombinantly expressed, soluble gH/gL (gHecto/gL) that was either wildtype (WT), lacking defined glycosylation sites or bearing modified glycosylation, followed by boosts with WT gHecto/gL. We also immunized with a gL-gHecto fusion protein or a gHecto-ferritin/gL nanoparticle. Immune sera neutralized KSHV and inhibited EphA2 receptor binding. None of the regimens was superior to immunization with WT gHecto/gL with regard to neutralizing activity and EphA2 blocking activity, the gL-gHecto fusion protein was equally effective, and the ferritin construct was inferior. gH/gL-targeting sera inhibited gB-mediated membrane fusion and inhibited infection also independently from receptor binding and gL, as demonstrated by neutralization of a novel KSHV mutant that does not or only marginally incorporate gL into the gH/gL complex and infects through an Eph-independent route.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Fusion; GH/gL; Herpesvirus entry; HHV-8; KSHV; Neutralizing antibodies

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signalling - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Kiessling, M.; Soulat, Didier; Krug, A.; Ravetch, J. V.; Leusen, J. H.; Nimmerjahn, Falk; Dudziak, Diana (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2016)
Created from Fastlane, WoS look-up

Antipruritic effect of bezafibrate and serum autotaxin measures in patients with primary biliary cholangitis - Kremer, Andreas; Le Cleac'H, Aline; Lemoinne, Sara; Wolf, Katharina; De Chaisemartin, Luc; Chollet-Martin, Sylvie; Humbert, Lydie; Rainteau, Dominique; Poupon, Raoul; Rousseau, Alexandra; Chazouilleres, Olivier; Corpechot, Christophe (Gut, 2019)
CRIS-Team WoS Importer:2019-11-29

Anti-trafficking agents in the treatment of inflammatory bowel disease - Zundler, Sebastian; Wiendl, Maximilian; Neurath, Markus (Current Opinion in Gastroenterology, 2019)
Purpose of review To describe the latest developments in the field of anti-trafficking agents (ATAs), a class of therapeutics with growing importance in the field of inflammatory bowel diseases (IBDs) that specifically inhibit steps of immune cell trafficking. Recent findings Several translational and clinical studies have further shaped the knowledge about the mechanisms and effects of the anti-α4β7 integrin antibody vedolizumab. In parallel, new ATAs like the anti-β7 integrin antibody etrolizumab and the anti-MAdCAM-1 antibody ontamalimab are investigated in phase III clinical trials and might soon increase the therapeutic armamentarium in IBD. Summary ATAs have unique mechanisms of action and can meanwhile be considered an indispensable column of IBD therapy. Further efforts are necessary to elucidate complex mechanistic aspects, to exactly define their role in relation to other therapeutic approaches and to identify novel treatment targets as well as biomarkers for personalized medicine.
CRIS-Team Scopus Importer:2019-10-01
Keywords: etrolizumab; gut homing; ontamalimab; trafficking; vedolizumab

Antiviral Strategies Using Natural Source-Derived Sulfated Polysaccharides in the Light of the COVID-19 Pandemic and Major Human Pathogenic Viruses - Ray, Bimalendu; Ali, Imran; Jana, Subrata; Mukherjee, Shuvam; Pal, Saikat; Ray, Sayani; Schütz, Martin; Marschall, Manfred (Viruses, 2022)
Only a mere fraction of the huge variety of human pathogenic viruses can be targeted by the currently available spectrum of antiviral drugs. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has highlighted the urgent need for molecules that can be deployed quickly to treat novel, developing or re-emerging viral infections. Sulfated polysaccharides are found on the surfaces of both the susceptible host cells and the majority of human viruses, and thus can play an important role during viral infection. Such polysaccharides widely occurring in natural sources, specifically those converted into sulfated varieties, have already proved to possess a high level and sometimes also broad-spectrum antiviral activity. This antiviral potency can be determined through multifold molecular pathways, which in many cases have low profiles of cytotoxicity. Consequently, several new polysaccharide-derived drugs are currently being investigated in clinical settings. We reviewed the present status of research on sulfated polysaccharide-based antiviral agents, their structural characteristics, structure–activity relationships, and the potential of clinical application. Furthermore, the molecular mechanisms of sulfated polysaccharides involved in viral infection or in antiviral activity, respectively, are discussed, together with a focus on the emerging methodology contributing to polysaccharide-based drug development.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Antiviral activities and mechanisms; Antiviral efficacy; Drug structure-activity relationship; Emerging viral infections; Heparin mimetics; In vivo studies; Major human pathogenic viruses; Sulfated polysaccharides; Virus entry as a target

An Update on Statistical Boosting in Biomedicine - Mayr, Andreas; Hofner, Benjamin; Waldmann, Elisabeth; Hepp, Tobias; Meyer, Sebastian; Gefeller, Olaf (Computational and Mathematical Methods in Medicine, 2017)
Statistical boosting algorithms have triggered a lot of research during the last decade. They combine a powerful machine learning approach with classical statistical modelling, offering various practical advantages like automated variable selection and implicit regularization of effect estimates. They are extremely flexible, as the underlying base-learners (regression functions defining the type of effect for the explanatory variables) can be combined with any kind of loss function (target function to be optimized, defining the type of regression setting). In this review article, we highlight the most recent methodological developments on statistical boosting regarding variable selection, functional regression, and advanced time-to-event modelling. Additionally, we provide a short overview on relevant applications of statistical boosting in biomedicine.
EVALuna2:34211

A placental specific miRNA miR-517a-3p exerts anti-human cytomegalovirus activity - Hamilton, Stuart T.; Hahn, Friedrich; Sonntag, Eric; Marschall, Manfred; Rawlinson, William D. (Placenta, 2021)
Human cytomegalovirus congenital infection is the leading non-genetic cause of fetal malformation in developed countries. There are currently no safe antivirals for use during pregnancy. Placental trophoblast cells specifically secrete exosomes containing miRNA from the chromosome 19 miRNA cluster (C19MC) which confer viral resistance to recipient cells. We show the highly expressed C19MC miRNA miR-517a-3p inhibits HCMV replication and viral protein expression in both fibroblast and trophoblast cell cultures (71.6% and 50.4% inhibition of HCMV DNA at 7 days post infection respectively; p < 0.05). This naturally occurring molecule has potential for opening-up antiviral therapeutic strategies for pregnancy.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Antivirals; Congenital infection; Cytomegalovirus; Placenta; Pregnancy

A polycystin-2 protein with modified channel properties leads to an increased diameter of renal tubules and to renal cysts - Grosch, Melanie; Brunner, Katrin; Ilyaskin, Alexandr; Schober, Michael; Staudner, Tobias; Schmied, Denise; Stumpp, Tina; Schmidt, Kerstin N.; Madej, M. Gregor; Dantas Pessoa, Thaissa; Othmen, Helga; Kubitza, Marion; et al. (Journal of Cell Science, 2021)
Mutations in the PKD2 gene cause autosomal-dominant polycystic kidney disease but the physiological role of polycystin-2, the protein product of PKD2, remains elusive. Polycystin-2 belongs to the transient receptor potential (TRP) family of non-selective cation channels. To test the hypothesis that altered ion channel properties of polycystin-2 compromise its putative role in a control circuit controlling lumen formation of renal tubular structures, we generated a mouse model in which we exchanged the pore loop of polycystin-2 with that of the closely related cation channel polycystin-2L1 (encoded by PKD2L1), thereby creating the protein polycystin-2poreL1. Functional characterization of this mutant channel in Xenopus laevis oocytes demonstrated that its electrophysiological properties differed from those of polycystin-2 and instead resembled the properties of polycystin-2L1, in particular regarding its permeability for Ca2+ ions. Homology modeling of the ion translocation pathway of polycystin-2poreL1 argues for a wider pore in polycystin-2poreL1 than in polycystin-2. In Pkd2poreL1 knock-in mice in which the endogenous polycystin-2 protein was replaced by polycystin-2poreL1 the diameter of collecting ducts was increased and collecting duct cysts developed in a strain-dependent fashion.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Autosomal-dominant polycystic kidney disease; Electrophysiology; Knock-in mice; Lumen formation; PKD2; Polycystin-2; Tubular diameter; Xenopus laevis oocytes

Application of machine learning algorithms for multiparametric MRI-based evaluation of murine colitis - Ellmann, Stephan; Langer, Victoria; Britzen-Laurent, Nathalie; Hildner, Kai; Huber, Carina; Tripal, Philipp; Seyler, Lisa; Waldner, Maximilian; Uder, Michael; Stürzl, Michael; Bäuerle, Tobias (PLoS ONE, 2018)
Magnetic resonance imaging (MRI) allows non-invasive evaluation of inflammatory bowel disease (IBD) by assessing pathologically altered gut. Besides morphological changes, relaxation times and diffusion capacity of involved bowel segments can be obtained by MRI. The aim of this study was to assess the use of multiparametric MRI in the diagnosis of experimentally induced colitis in mice, and evaluate the diagnostic benefit of parameter combinations using machine learning. This study relied on colitis induction by Dextran Sodium Sulfate (DSS) and investigated the colon of mice in vivo as well as ex vivo. Receiver Operating Characteristics were used to calculate sensitivity, specificity, positive- and negative-predictive values (PPV and NPV) of these single values in detecting DSS-treatment as a reference condition. A Model Averaged Neural Network (avNNet) was trained on the multiparametric combination of the measured values, and its predictive capacity was compared to those of the single parameters using exact binomial tests. Within the in vivo subgroup (n = 19), the avNNet featured a sensitivity of 91.3% (95% CI: 86.6-96.0%), specificity of 92.3% (95% CI: 85.1-99.6%), PPV of 96.9% (94.0-99.9%) and NPV of 80.0% (95% CI: 69.9-90.1%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.003) and performing significantly worse compared to none of the single values. Within the ex vivo subgroup (n = 30), the avNNet featured a sensitivity of 87.4% (95% CI: 82.6-92.2%), specificity of 82.9% (95% CI: 76.1-89.7%), PPV of 88.9% (84.3-93.5%) and NPV of 80.8% (95% CI: 73.8-87.9%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.015), exceeded by none of the single parameters. In experimental mouse colitis, multiparametric MRI and the combination of several single measured values to an avNNet can significantly increase diagnostic accuracy compared to the single parameters alone. This pilot study will provide new avenues for the development of an MR-derived colitis score for optimized diagnosis and surveillance of inflammatory bowel disease.
EVALuna2:35135

A role for MALT1 activity in Kaposi's sarcoma-associated herpes virus latency and growth of primary effusion lymphoma - Bonsignore, L.; Passelli, K.; Pelzer, C.; Perroud, M.; Konrad, A.; Thurau, Mathias; Stürzl, Michael; Dai, L.; Trillo-Tinoco, Jimena; Del Valle, L.; Qin, Z.; Thome, Margot (Leukemia, 2017)
Primary effusion lymphoma (PEL) is an incurable malignancy that develops in immunodeficient patients as a consequence of latent infection of B-cells with Kaposi's sarcoma-associated herpes virus (KSHV). Malignant growth of KSHV-infected B cells requires the activity of the transcription factor nuclear factor (NF)-?B, which controls maintenance of viral latency and suppression of the viral lytic program. Here we show that the KSHV proteins K13 and K15 promote NF-?B activation via the protease mucosa-associated lymphoid tissue lymphoma translocation protein-1 (MALT1), a key driver of NF-?B activation in lymphocytes. Inhibition of the MALT1 protease activity induced a switch from the latent to the lytic stage of viral infection, and led to reduced growth and survival of PEL cell lines in vitro and in a xenograft model. These results demonstrate a key role for the proteolytic activity of MALT1 in PEL, and provide a rationale for the pharmacological targeting of MALT1 in PEL therapy.
EVALuna2:15308

Artesunate-derived monomeric, dimeric and trimeric experimental drugs - Their unique mechanistic basis and pronounced antiherpesviral activity - Hahn, Friedrich; Fröhlich, Tony; Frank, Theresa; Bertzbach, Luca D.; Kohrt, Stephan; Kaufer, Benedikt B.; Stamminger, Thomas; Tsogoeva, Svetlana; Marschall, Manfred (Antiviral Research, 2018)
Human cytomegalovirus (HCMV) is a major human pathogen and is associated with severe pathology, such as life-threatening courses of infection in immunocompromised individuals and neonates. Currently, antiviral therapy is still hampered by a considerable toxicity of the available drugs and induction of viral resistance. Recently, we and others reported the very potent antiviral activity of the broad antiinfective drug artesunate in vitro and in vivo. Here, we investigated further optimized analogs including monomeric, dimeric and trimeric derivatives belonging to this highly interesting chemical group of experimental drugs (sesquiterpenes/trioxanes) and compared these to the previously identified trimeric artesunate compound TF27. We could demonstrate that (i) seven of the eight investigated monomeric, dimeric and trimeric artesunate derivatives, i.e. TF79, TF85, TF87, TF93.2.4, TF111, TF57a and TF57ab, exerted a strong anti-HCMV activity in primary human fibroblasts, (ii) the EC50 values ranged in the low to sub-micromolar concentrations and indicated a higher antiviral potency than the recently described artesunate analogs, (iii) one trimeric compound, TF79, showed a very promising EC50 of 0.03 +/- 0.00 mu M, which even exceled the antiviral potency of TF27 (EC50 0.04 +/- 0.01 mu M), (iv) levels of cytotoxicity (quantitative measurement of lactate dehydrogenase release) were low in a range between 100 and 30 mu M and thus different from antiviral concentrations, (v) an analysis of protein expression levels indicated a potent block of viral protein expression, and (vi) data from a NF-kappa B reporter cell system strongly suggested that these compounds share the same antiviral mechanism. Taken together, our data on these novel compounds strongly encourages our earlier concept on the oligomerization and hybridization of artesunate analogs, providing an excellent platform for the generation of antiherpesviral drugs.
EVALuna2:35282

A Stat6/Pten Axis Links Regulatory T Cells with Adipose Tissue Function - Kaelin, Stefanie; Becker, Maike; Ott, Verena B.; Serr, Isabelle; Hosp, Fabian; Mollah, Mohammad M. H.; Keipert, Susanne; Lamp, Daniel; Rohner-Jeanrenaud, Francoise; Flynn, Victoria K.; Scherm, Martin G.; Nascimento, Lucas F. R.; et al. (Cell Metabolism, 2017)
Obesity and type 2 diabetes are associated with metabolic defects and adipose tissue inflammation. Foxp3+ regulatory T cells (Tregs) control tissue homeostasis by counteracting local inflammation. However, if and how T cells interlink environmental influences with adipocyte function remains unknown. Here, we report that enhancing sympathetic tone by cold exposure, beta3-adrenergic receptor (ADRB3) stimulation or a short-term high-calorie diet enhances Treg induction in vitro and in vivo. CD4+ T cell proteomes revealed higher expression of Foxp3 regulatory networks in response to cold or ADRB3 stimulation in vivo reflecting Treg induction. Specifically, Ragulator-interacting protein C17orf59, which limits mTORC1 activity, was upregulated in CD4+ T cells by either ADRB3 stimulation or cold exposure, suggesting contribution to Treg induction. By loss- and gain-of-function studies, including Treg depletion and transfers in vivo, we demonstrated that a T cell-specific Stat6/Pten axis links cold exposure or ADRB3 stimulation with Foxp3+ Treg induction and adipose tissue function. Our findings offer a new mechanistic model in which tissue-specific Tregs maintain adipose tissue function.
EVALuna2:33893

ATP citrate lyase (ACLY)-dependent immunometabolism in mucosal T cells drives experimental colitis in vivo - Schulz-Kuhnt, Anja; Rühle, Katharina; Javidmehr, Asal; Döbrönti, Michael; Biwank, Jana; Knittel, Selina; Neidlinger, Peter; Leupold, Jannik; Liu, Lijuan; Dedden, Mark; Taudte, Regina Verena; Geßner, Arne; et al. (Gut, 2024)
Objective Mucosal T cells play a major role in inflammatory bowel disease (IBD). However, their immunometabolism during intestinal inflammation is poorly understood. Due to its impact on cellular metabolism and proinflammatory immune cell function, we here focus on the enzyme ATP citrate lyase (ACLY) in mucosal T cell immunometabolism and its relevance for IBD. Design ACLY expression and its immunometabolic impact on colitogenic T cell function were analysed in mucosal T cells from patients with IBD and in two experimental colitis models. Results ACLY was markedly expressed in colon tissue under steady-state conditions but was significantly downregulated in lamina propria mononuclear cells in experimental dextran sodium sulfate-induced colitis and in CD4+ and to a lesser extent in CD8+ T cells infiltrating the inflamed gut in patients with IBD. ACLY-deficient CD4+ T cells showed an impaired capacity to induce intestinal inflammation in a transfer colitis model as compared with wild-type T cells. Assessment of T cell immunometabolism revealed that ACLY deficiency dampened the production of IBD-relevant cytokines and impaired glycolytic ATP production but enriched metabolites involved in the biosynthesis of phospholipids and phosphatidylcholine. Interestingly, the short-chain fatty acid butyrate was identified as a potent suppressor of ACLY expression in T cells, while IL-36α and resolvin E1 induced ACLY levels. In a translational approach, in vivo administration of the butyrate prodrug tributyrin downregulated mucosal infiltration of ACLYhigh CD4+ T cells and ameliorated chronic colitis. Conclusion ACLY controls mucosal T cell immunometabolism and experimental colitis. Therapeutic modulation of ACLY expression in T cells emerges as a novel strategy to promote the resolution of intestinal inflammatio

At the Forefront of the Mucosal Barrier: The Role of Macrophages in the Intestine - Ruder, Barbara; Becker, Christoph (Cells, 2020)
Macrophages are part of the innate immunity and are key players for the maintenance of intestinal homeostasis. They belong to the group of mononuclear phagocytes, which exert bactericidal functions and help to clear apoptotic cells. Moreover, they play essential roles for the maintenance of epithelial integrity and tissue remodeling during wound healing processes and might be implicated in intestinal tumor development. Macrophages are antigen-presenting cells and secrete immune-modulatory factors, like chemokines and cytokines, which are necessary to activate other intestinal immune cells and therefore to shape immune responses in the gut. However, overwhelming activation or increased secretion of pro-inflammatory cytokines might also contribute to the pathogenesis of inflammatory bowel disease. Presently, intestinal macrophages are in the center of intense studies, which might help to develop new therapeutic strategies to counteract the development or treat already existing inflammatory diseases in the gut. In this review, we focus on the origin of intestinal macrophages and, based on current knowledge, discuss their role in the gut during homeostasis and inflammation, as well as during intestinal wound healing and tumor development.
CRIS-Team Scopus Importer:2020-10-16
Keywords: IBD; inflammation; intestine; macrophages; phagocytosis

Autophagy inhibition promotes SNCA/alpha-synuclein release and transfer via extracellular vesicles with a hybrid autophagosome-exosome-like phenotype - Minakaki, Georgia; Menges, Stefanie; Kittel, Agnes; Emmanouilidou, Evangelia; Schäffner, Iris; Barkovits, Katalin; Bergmann, Anna; Rockenstein, Edward; Adame, Anthony; Marxreiter, Franz; Mollenhauer, Brit; Galasko, Douglas; et al. (Autophagy, 2017)
The autophagy-lysosome pathway (ALP) regulates intracellular homeostasis of the cytosolic protein SNCA/alpha-synuclein and is impaired in synucleinopathies, including Parkinson disease and dementia with Lewy bodies (DLB). Emerging evidence suggests that ALP influences SNCA release, but the underlying cellular mechanisms are not well understood. Several studies identified SNCA in exosome/extracellular vesicle (EV) fractions. EVs are generated in the multivesicular body compartment and either released upon its fusion with the plasma membrane, or cleared via the ALP. We therefore hypothesized that inhibiting ALP clearance 1) enhances SNCA release via EVs by increasing extracellular shuttling of multivesicular body contents, 2) alters EV biochemical profile, and 3) promotes SNCA cell-to-cell transfer. Indeed, ALP inhibition increased the ratio of extra- to intracellular SNCA and upregulated SNCA association with EVs in neuronal cells. Ultrastructural analysis revealed a widespread, fused multivesicular body-autophagosome compartment. Biochemical characterization revealed the presence of autophagosome-related proteins, such as LC3-II and SQSTM1. This distinct "autophagosome-exosome-like" profile was also identified in human cerebrospinal fluid (CSF) EVs. After a single intracortical injection of SNCA-containing EVs derived from CSF into mice, human SNCA colocalized with endosome and neuronal markers. Prominent SNCA immunoreactivity and a higher number of neuronal SNCA inclusions were observed after DLB patient CSF EV injections. In summary, this study provides compelling evidence that a) ALP inhibition increases SNCA in neuronal EVs, b) distinct ALP components are present in EVs, and c) CSF EVs transfer SNCA from cell to cell in vivo. Thus, macroautophagy/autophagy may regulate EV protein composition and consequently progression in synucleinopathies.
EVALuna2:4781

Autotaxin activity predicts transplant-free survival in primary sclerosing cholangitis - Dhillon, Amandeep K.; Kremer, Andreas; Kummen, Martin; Boberg, Kirsten M.; Elferink, Ronald P.Oude; Karlsen, Tom H.; Beuers, Ulrich; Vesterhus, Mette; Hov, Johannes R. (Scientific Reports, 2019)
Autotaxin has been associated with liver disease severity and transplant-free survival. This study aimed to validate autotaxin as a biomarker in two cohorts of Norwegian large-duct PSC patients, one discovery panel (n = 165) and one validation panel (n = 87). Serum activity of autotaxin was measured in diluted sera by a fluorometric enzymatic assay. Patients reaching an end-point, liver transplantation or death, (discovery panel: n = 118 [71.5%]; validation panel: n = 35 [40.2%]), showed higher autotaxin activity compared with the other patients, P < 0.001 and P = 0.004, respectively. Kaplan-Meier survival analyses showed a strong association between increasing autotaxin activity and shorter liver transplant-free survival (discovery panel: P < 0.001, validation panel: P = 0.001). There was no relationship between autotaxin activity and the presence of inflammatory bowel disease or occurrence of hepatobiliary malignancy. In a multivariable analysis, high autotaxin activity was associated with an increased risk of liver transplantation or death (hazard ratio 2.03 (95% confidence interval 1.21–3.40), P < 0.01), independent from Mayo risk score, an in-house enhanced liver fibrosis score and interleukin-8 in serum. In conclusion, increased serum autotaxin activity is associated with reduced liver transplant-free survival independent from Mayo risk score and markers of inflammation and fibrosis.
CRIS-Team Scopus Importer:2019-06-21

A Whole-Slide Image Managing Library Based on Fastai for Deep Learning in the Context of Histopathology: Two Use-Cases Explained - Neuner, Christoph; Coras, Roland; Blümcke, Ingmar; Popp, Alexander; Schlaffer, Sven-Martin; Wirries, Andre; Buchfelder, Michael; Jabari, Samir (Applied Sciences, 2022)
Background: Processing whole-slide images (WSI) to train neural networks can be intricate and labor intensive. We developed an open-source library dealing with recurrent tasks in the processing of WSI and helping with the training and evaluation of neuronal networks for classification tasks. Methods: Two histopathology use-cases were selected and only hematoxylin and eosin (H&E) stained slides were used. The first use case was a two-class classification problem. We trained a convolutional neuronal network (CNN) to distinguish between dysembryoplastic neuroepithelial tumor (DNET) and ganglioglioma (GG), two neuropathological low-grade epilepsy-associated tumor entities. Within the second use case, we included four clinicopathological disease conditions in a multilabel approach. Here we trained a CNN to predict the hormone expression profile of pituitary adenomas. In the same approach, we also predicted clinically silent corticotroph adenoma. Results: Our DNET-GG classifier achieved an AUC of 1.00 for the ROC curve. For the second use case, the best performing CNN achieved an area under the curve (AUC) of 0.97 for the receiver operating characteristic (ROC) for corticotroph adenoma, 0.86 for silent corticotroph adenoma, and 0.98 for gonadotroph adenoma. All scores were calculated with the help of our library on predictions on a case basis. Conclusions: Our comprehensive and fastai-compatible library is helpful to standardize the workflow and minimize the burden of training a CNN. Indeed, our trained CNNs extracted neuropathologically relevant information from the WSI. This approach will supplement the clinicopathological diagnosis of brain tumors, which is currently based on cost-intensive microscopic examination and variable panels of immunohistochemical stainings.
CRIS-Team WoS Importer:2022-02-18

Axin phosphorylation in condensates counteracts tankyrase-mediated degradation - Klement, Katharina; Brückner, Martina; Bernkopf, Dominic (Journal of Cell Science, 2023)
Axin is a central negative regulator of the proto-oncogenic Wnt/β-catenin signaling pathway, as axin condensates provide a scaffold for the assembly of a multiprotein complex degrading β-catenin. Axin in turn is degraded via tankyrase. Consequently, small molecule tankyrase inhibitors block Wnt signaling by stabilizing axin, revealing potential for cancer therapy. Here, we discover phosphorylation of axin by casein kinase 1α (CK1α) at an N-terminal CK1 consensus motif, which was antagonized by protein phosphatase 1 (PP1). Axin condensates promoted phosphorylation by enriching CK1α over PP1. Importantly, the phosphorylation took place within the tankyrase-binding site, hindered axin-tankyrase interaction electrostatically and/or sterically, and counteracted tankyrase-mediated degradation of axin. Thus, the presented data propose a novel mechanism regulating axin stability, with implications for Wnt signaling, cancer therapy and self-organization of biomolecular condensates.<br
Keywords: Axin; Wnt signaling; Biomolecular condensates; Tankyrase

Aβ1-16 controls synaptic vesicle pools at excitatory synapses via cholinergic modulation of synapsin phosphorylation - Anni, Daniela; Weiss, Eva-Maria; Guhathakurta, Debarpan; Akdas, Enes Yagiz; Klueva, Julia; Zeitler, Stefanie; Andres-Alonso, Maria; Huth, Tobias; Fejtová, Anna (Cellular and Molecular Life Sciences, 2021)
Amyloid beta (Aβ) is linked to the pathology of Alzheimer’s disease (AD). At physiological concentrations, Aβ was proposed to enhance neuroplasticity and memory formation by increasing the neurotransmitter release from presynapse. However, the exact mechanisms underlying this presynaptic effect as well as specific contribution of endogenously occurring Aβ isoforms remain unclear. Here, we demonstrate that Aβ1-42 and Aβ1-16, but not Aβ17-42, increased size of the recycling pool of synaptic vesicles (SV). This presynaptic effect was driven by enhancement of endogenous cholinergic signalling via α7 nicotinic acetylcholine receptors, which led to activation of calcineurin, dephosphorylation of synapsin 1 and consequently resulted in reorganization of functional pools of SV increasing their availability for sustained neurotransmission. Our results identify synapsin 1 as a molecular target of Aβ and reveal an effect of physiological concentrations of Aβ on cholinergic modulation of glutamatergic neurotransmission. These findings provide new mechanistic insights in cholinergic dysfunction observed in AD.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Alpha7 nicotinic acetylcholine receptor; Amyloid beta; Synapsin 1; Synaptic vesicle dynamics

Baseline levels of dynamic CD4+ T cell adhesion to MAdCAM-1 correlate with clinical response to vedolizumab treatment in ulcerative colitis: a cohort study - Allner, Clarissa; Melde, Michaela; Becker, Elisabeth; Fuchs, Friederike; Mühl, Laura; Klenske, Entcho; Müller, Lisa; Morgenstern, Nadine; Fietkau, Konstantin; Hirschmann, Simon; Atreya, Raja; Atreya, Imke; et al. (BMC Gastroenterology, 2020)
BACKGROUND: While the number of therapeutic options for treating inflammatory bowel diseases (IBD) is increasing, evidence for rational treatment decisions is scarce in many cases. In particular, appropriate biomarkers to predict the response to the anti-α4β7 integrin antibody vedolizumab are currently lacking. METHODS: We performed a cohort study with 21 patients suffering from ulcerative colitis (UC), in which first-time treatment with vedolizumab was initiated. CD4+ T cells were isolated from the peripheral blood and dynamic adhesion to recombinant mucosal vascular addressin cell adhesion molecule (MAdCAM-)1 in vitro as well as the effect of vedolizumab on such adhesion in vitro was determined. The expression of α4β1 integrin on peripheral blood CD4+ T cells was quantified by flow cytometry. Electronic patient records were reviewed to determine clinical response to vedolizumab. RESULTS: Dynamic adhesion of peripheral blood CD4+ T cells to MAdCAM-1 and the reduction of adhesion following vedolizumab treatment in vitro were higher and the change in α4β1 expression on CD4+ T cells was different in vedolizumab responders and non-responders. Responders could be identified with high specificity and positive-predictive value. CONCLUSIONS: Determining dynamic adhesion of CD4+ T cells to MAdCAM-1 and the in vitro response to vedolizumab before treatment initiation or dynamic integrin regulation in the early course of treatment seem to be promising tools to predict the clinical response to vedolizumab therapy. Larger prospective studies are warranted.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Adhesion; Gut homing; Inflammatory bowel diseases; T cells; Vedolizumab

BMP6-induced modulation of the tumor micro-milieu - Stieglitz, David; Lamm, Susanne; Braig, Simone; Feuerer, Lena; Kuphal, Silke; Dietrich, Peter; Arndt, Stephanie; Echtenacher, Bernd; Hellerbrand, Claus; Karrer, Sigrid; Boßerhoff, Anja Katrin (Oncogene, 2019)
Melanoma is the deadliest form of skin cancer with rising incidence, creating a significant health problem. We discovered increased expression of bone morphogenetic protein 6 (BMP6) in melanoma cells and tissues, and observed that BMP6 deficiency caused significantly delayed tumor onset and decelerated tumor progression in a melanoma mouse model. Moreover, we determined that BMP6 inhibits dermal mast cell recruitment and found that mast cell-derived mediators significantly reduced melanoma growth in vitro. In line with this, mast cell deficiency accelerated tumor onset and progression in a melanoma mouse model. Analysis of human melanoma tissues revealed a strong negative correlation between melanoma proliferation and mast cell infiltration. This study elucidates a novel role of BMP6-induced modulation of the tumor microenvironment.
EVALuna2:106826

Boosting joint models for longitudinal and time-to-event data - Waldmann, Elisabeth; Taylor-Robinson, David; Klein, Nadja; Kneib, Thomas; Pressler, Tania; Schmid, Matthias; Mayr, Andreas (Biometrical Journal, 2017)
Joint models for longitudinal and time-to-event data have gained a lot of attention in the last few years as they are a helpful technique clinical studies where longitudinal outcomes are recorded alongside event times. Those two processes are often linked and the two outcomes should thus be modeled jointly in order to prevent the potential bias introduced by independent modeling. Commonly, joint models are estimated in likelihood-based expectation maximization or Bayesian approaches using frameworks where variable selection is problematic and that do not immediately work for high-dimensional data. In this paper, we propose a boosting algorithm tackling these challenges by being able to simultaneously estimate predictors for joint models and automatically select the most influential variables even in high-dimensional data situations. We analyze the performance of the new algorithm in a simulation study and apply it to the Danish cystic fibrosis registry that collects longitudinal lung function data on patients with cystic fibrosis together with data regarding the onset of pulmonary infections. This is the first approach to combine state-of-the art algorithms from the field of machine-learning with the model class of joint models, providing a fully data-driven mechanism to select variables and predictor effects in a unified framework of boosting joint models.
EVALuna2:34173

Break on through: The role of innate immunity and barrier defence in atopic dermatitis and psoriasis - Hawerkamp, Heike C.; Caoimhe, Fahy; Fallon, Padraic G.; Schwartz, Christian (Skin Health and Disease, 2022)
The human skin can be affected by a multitude of diseases including inflammatory conditions such as atopic dermatitis and psoriasis. Here, we describe how skin barrier integrity and immunity become dysregulated during these two most common inflammatory skin conditions. We summarise recent advances made in the field of the skin innate immune system and its interaction with adaptive immunity. We review gene variants associated with atopic dermatitis and psoriasis that affect innate immune mechanisms and skin barrier integrity. Finally, we discuss how current and future therapies may affect innate immune responses and skin barrier integrity in a generalized or more targeted approach in order to ameliorate disease in patients.<br

Built to Last? Reproducibility and Reusability of Deep Learning Algorithms in Computational Pathology. - Wagner, Sophia J.; Matek, Christian; Shetab Boushehri, Sayedali; Boxberg, Melanie; Lamm, Lorenz; Sadafi, Ario; Winter, Dominik J.E.; Marr, Carsten; Peng, Tingying (Modern Pathology, 2024)
Recent progress in computational pathology has been driven by deep learning. While code and data availability are essential to reproduce findings from preceding publications, ensuring a deep learning model's reusability is more challenging. For that, the codebase should be well-documented and easy to integrate into existing workflows and models should be robust toward noise and generalizable toward data from different sources. Strikingly, only a few computational pathology algorithms have been reused by other researchers so far, let alone employed in a clinical setting. To assess the current state of reproducibility and reusability of computational pathology algorithms, we evaluated peer-reviewed articles available in PubMed, published between January 2019 and March 2021, in 5 use cases: stain normalization; tissue type segmentation; evaluation of cell-level features; genetic alteration prediction; and inference of grading, staging, and prognostic information. We compiled criteria for data and code availability and statistical result analysis and assessed them in 160 publications. We found that only one-quarter (41 of 160 publications) made code publicly available. Among these 41 studies, three-quarters (30 of 41) analyzed their results statistically, half of them (20 of 41) released their trained model weights, and approximately a third (16 of 41) used an independent cohort for evaluation. Our review is intended for both pathologists interested in deep learning and researchers applying algorithms to computational pathology challenges. We provide a detailed overview of publications with published code in the field, list reusable data handling tools, and provide criteria for reproducibility and reusability.
EVALuna2:546414

Caspase-8 in endothelial cells maintains gut homeostasis and prevents small bowel inflammation in mice - Tisch, Nathalie; Mogler, Carolin; Stojanovic, Ana; Luck, Robert; Korhonen, Emilia A.; Ellerkmann, Alexander; Adler, Heike; Singhal, Mahak; Schermann, Geza; Erkert, Lena; Patankar, Jay; Karakatsani, Andromachi; et al. (Embo Molecular Medicine, 2022)
The gut has a specific vascular barrier that controls trafficking of antigens and microbiota into the bloodstream. However, the molecular mechanisms regulating the maintenance of this vascular barrier remain elusive. Here, we identified Caspase-8 as a pro-survival factor in mature intestinal endothelial cells that is required to actively maintain vascular homeostasis in the small intestine in an organ-specific manner. In particular, we find that deletion of Caspase-8 in endothelial cells results in small intestinal hemorrhages and bowel inflammation, while all other organs remained unaffected. We also show that Caspase-8 seems to be particularly needed in lymphatic endothelial cells to maintain gut homeostasis. Our work demonstrates that endothelial cell dysfunction, leading to the breakdown of the gut-vascular barrier, is an active driver of chronic small intestinal inflammation, highlighting the role of the intestinal vasculature as a safeguard of organ function.
CRIS-Team Scopus Importer:2022-05-13
Keywords: caspase-8; chronic intestinal inflammation; endothelium; necroptosis; vascular homeostasis

CCL19‐positive lymph node stromal cells govern the onset of inflammatory arthritis via tropomyosin receptor kinase - Schälter, Fabian; Azizov, Vugar; Frech, Michael; Dürholz, Kerstin; Schmid, Eva; Hendel, Anna; Sarfati, Ilann; Maeda, Yuichi; Sokolova, Maria; Miyagawa, Ippei; Focke, Kristin; Sarter-Zaiss, Kerstin; et al. (Arthritis and Rheumatology, 2024)
Objectives To assess the role of CCL19+ lymph node stromal cells of the joint draining popliteal lymph node (pLN) for the development of arthritis. Methods CCL19+ lymph node stromal cells were spatiotemporally depleted for 5 days in the pLN before the onset of collagen-induced arthritis (CIA) using Ccl19-Cre x iDTR mice. In addition, therapeutic treatment with recombinant CCL19-IgG, locally injected in the footpad, was used to confirm the results. RNA sequencing of lymph node stromal cells combined with T cell co-culture assays using tropomyosin receptor kinase (Trk) family inhibitors together with in vivo local pLN siRNA treatments were used to elucidate the pathway by which CCL19+ lymph node stromal cells initiate the onset of arthritis. Results Spatiotemporal depletion of CCL19+ lymph node stromal cells prevented disease onset in CIA mice. These inhibitory effects could be mimicked by local CCL19-IgG treatment. The mRNA sequencing analyses showed that CCL19+ lymph node stromal cells downregulated the expression of the tropomyosin receptor kinase A (TrkA) just before disease onset. Blocking TrkA in lymph node stromal cells led to increased T cell proliferation in in vitro co-culture assays. Similar effects were observed with the pan-Trk inhibitor Larotrectinib in co-cultures of lymph node stromal cells of rheumatoid arthritis patients and T cells. Finally, local pLN treatment with TrkA inhibitor and TrkA siRNA led to exacerbated arthritis scores. Conclusions CCL19+ lymph node stromal cells are crucially involved in the development of inflammatory arthritis. Therefore, targeting of CCL19+ lymph node stromal cells via TRK kinases could provide a tool to prevent arthriti

CD200+ fibroblasts form a pro-resolving mesenchymal network in arthritis - Rauber, Simon; Mohammadian, Hashem; Schmidkonz, Christian; Atzinger, Armin; Soare, Alina; Treutlein, Christoph; Kemble, Samuel; Mahony, Christopher B.; Geisthoff, Manuel; Angeli, Mario Raphael; Raimondo, Maria Gabriella; Xu, Cong; et al. (Nature Immunology, 2024)
Fibroblasts are important regulators of inflammation, but whether fibroblasts change phenotype during resolution of inflammation is not clear. Here we use positron emission tomography to detect fibroblast activation protein (FAP) as a means to visualize fibroblast activation in vivo during inflammation in humans. While tracer accumulation is high in active arthritis, it decreases after tumor necrosis factor and interleukin-17A inhibition. Biopsy-based single-cell RNA-sequencing analyses in experimental arthritis show that FAP signal reduction reflects a phenotypic switch from pro-inflammatory MMP3+/IL6+ fibroblasts (high FAP internalization) to pro-resolving CD200+DKK3+ fibroblasts (low FAP internalization). Spatial transcriptomics of human joints indicates that pro-resolving niches of CD200+DKK3+ fibroblasts cluster with type 2 innate lymphoid cells, whereas MMP3+/IL6+ fibroblasts colocalize with inflammatory immune cells. CD200+DKK3+ fibroblasts stabilized the type 2 innate lymphoid cell phenotype and induced resolution of arthritis via CD200–CD200R1 signaling. Taken together, these data suggest a dynamic molecular regulation of the mesenchymal compartment during resolution of inflammation.
Created from Fastlane, Scopus look-up

CD33/CD3-bispecific T-cell engaging (BiTE®) antibody construct targets monocytic AML myeloid-derived suppressor cells - Jitschin, Regina; Saul, Domenica; Braun, Martina; Tohumeken, Sehmus; Kischel, Roman; Lutteropp, Michael; Dos Santos, Cedric; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (Journal for ImmunoTherapy of Cancer, 2018)
Acute myeloid leukemia (AML) is the most common acute leukemia amongst adults with a 5-year overall survival lower than 30%. Emerging evidence suggest that immune alterations favor leukemogenesis and/or AML relapse thereby negatively impacting disease outcome. Over the last years myeloid derived suppressor cells (MDSCs) have been gaining momentum in the field of cancer research. MDSCs are a heterogeneous cell population morphologically resembling either monocytes or granulocytes and sharing some key features including myeloid origin, aberrant (immature) phenotype, and immunosuppressive activity. Increasing evidence suggests that accumulating MDSCs are involved in hampering anti-tumor immune responses and immune-based therapies. Here, we demonstrate increased frequencies of CD14+ monocytic MDSCs in newly diagnosed AML that co-express CD33 but lack HLA-DR (HLA-DRlo). AML-blasts induce HLA-DRlo cells from healthy donor-derived monocytes in vitro that suppress T-cells and express indoleamine-2,3-dioxygenase (IDO). We investigated whether a CD33/CD3-bispecific BiTE® antibody construct (AMG 330) with pre-clinical activity against AML-blasts by redirection of T-cells can eradicate CD33+ MDSCs. In fact, T-cells eliminate IDO+CD33+ MDSCs in the presence of AMG 330. Depletion of total CD14+ cells (including MDSCs) in peripheral blood mononuclear cells from AML patients did not enhance AMG 330-triggered T-cell activation and expansion, but boosted AML-blast lysis. This finding was corroborated in experiments showing that adding MDSCs into co-cultures of T- and AML-cells reduced AML-blast killing, while IDO inhibition promotes AMG 330-mediated clearance of AML-blasts. Taken together, our results suggest that AMG 330 may achieve anti-leukemic efficacy not only through T-cell-mediated cytotoxicity against AML-blasts but also against CD33+ MDSCs, suggesting that it is worth exploring the predictive role of MDSCs for responsiveness towards an AMG 330-based therapy.
EVALuna2:35089

CD83 acts as immediate early response gene in activated macrophages and exhibits specific intracellular trafficking properties - Langguth, Pia; Peckert, Katrin; Beck, Philipp; Kuhnt, Christine; Draßner, Christina; Deinzer, Andrea; Steinkasserer, Alexander; Wild, Andreas (Biochemical and Biophysical Research Communications, 2023)
Macrophages (MΦ) are remarkably plastic cells, which assume phenotypes in every shade between a pro-inflammatory classical activation, and anti-inflammatory or resolving activation. Therefore, elucidation of mechanisms involved in shaping MΦ plasticity and function is key to understand their role during immunological balance. The immune-modulating CD83 molecule is expressed on activated immune cells and various tissue resident MΦ, rendering it an interesting candidate for affecting MΦ biology. However, in-depth analyses of the precise kinetics and trafficking of CD83 within pro-inflammatory, LPS activated bone-marrow-derived MΦ have not been performed. In this study, we show that activation with LPS leads to a very fast and strong, but transient increase of CD83 expression on these cells. Its expression peaks within 2 h of stimulation and is thereby faster than the early activation antigen CD69. To trace the CD83 trafficking through MΦs, we employed multiple inhibitors, thereby revealing a de novo synthesis and transport of the protein to the cell surface followed by lysosomal degradation, all within 6 h. Moreover, we found a similar expression kinetic and trafficking in human monocyte derived MΦ. This places CD83 at a very early point of MΦ activation suggesting an important role in decisions regarding the subsequent cellular fate.
CRIS-Team Scopus Importer:2023-02-10
Keywords: CD83; expression; intracellular trafficking; lipopolysaccharide; macrophages

CD83 expressed by macrophages is an important immune checkpoint molecule for the resolution of inflammation - Peckert-Maier, Katrin; Langguth, Pia; Strack, Astrid; Stich, Lena; Mühl-Zürbes, Petra; Kuhnt, Christine; Drassner, Christina; Zinser, Elisabeth; Wrage, Marius; Mattner, Jochen; Steinkasserer, Alexander; Royzman, Dmytro; et al. (Frontiers in Immunology, 2023)
Excessive macrophage (M phi) activation results in chronic inflammatory responses or autoimmune diseases. Therefore, identification of novel immune checkpoints on M phi, which contribute to resolution of inflammation, is crucial for the development of new therapeutic agents. Herein, we identify CD83 as a marker for IL-4 stimulated pro-resolving alternatively activated M phi (AAM). Using a conditional KO mouse (cKO), we show that CD83 is important for the phenotype and function of pro-resolving M phi. CD83-deletion in IL-4 stimulated M phi results in decreased levels of inhibitory receptors, such as CD200R and MSR-1, which correlates with a reduced phagocytic capacity. In addition, CD83-deficient M phi upon IL-4 stimulation, show an altered STAT-6 phosphorylation pattern, which is characterized by reduced pSTAT-6 levels and expression of the target gene Gata3. Concomitantly, functional studies in IL-4 stimulated CD83 KO M phi reveal an increased production of pro-inflammatory mediators, such as TNF-alpha, IL-6, CXCL1 and G-CSF. Furthermore, we show that CD83-deficient M phi have enhanced capacities to stimulate the proliferation of allo-reactive T cells, which was accompanied by reduced frequencies of Tregs. In addition, we show that CD83 expressed by M phi is important to limit the inflammatory phase using a full-thickness excision wound healing model, since inflammatory transcripts (e.g. Cxcl1, Il6) were increased, whilst resolving transcripts (e.g. Ym1, Cd200r, Msr-1) were decreased in wounds at day 3 after wound infliction, which reflects the CD83 resolving function on M phi also in vivo. Consequently, this enhanced inflammatory milieu led to an altered tissue reconstitution after wound infliction. Thus, our data provide evidence that CD83 acts as a gatekeeper for the phenotype and function of pro-resolving M phi.
CRIS-Team WoS Importer:2023-03-17

CD83 expression is essential for Treg cell differentiation and stability - Döbbeler, Marina; Koenig, Christina; Krzyzak, Lena; Seitz, Christine; Wild, Andreas; Ulas, Thomas; Bassler, Kevin; Kopelyanskiy, Dmitry; Butterhof, Alina; Kuhnt, Christine; Kreiser, Simon; Stich, Lena; et al. (JCI Insight, 2018)
Foxp3-positive regulatory T cells (Tregs) are crucial for the maintenance of immune homeostasis and keep immune responses in check. Upon activation, Tregs are transferred into an effector state expressing transcripts essential for their suppressive activity, migration, and survival. However, it is not completely understood how different intrinsic and environmental factors control differentiation. Here, we present for the first time to our knowledge data suggesting that Treg-intrinsic expression of CD83 is essential for Treg differentiation upon activation. Interestingly, mice with Treg-intrinsic CD83 deficiency are characterized by a proinflammatory phenotype. Furthermore, the loss of CD83 expression by Tregs leads to the downregulation of Treg-specific differentiation markers and the induction of an inflammatory profile. In addition, Treg-specific conditional knockout mice showed aggravated autoimmunity and an impaired resolution of inflammation. Altogether, our results show that CD83 expression in Tregs is an essential factor for the development and function of effector Tregs upon activation. Since Tregs play a crucial role in the maintenance of immune tolerance and thus prevention of autoimmune disorders, our findings are also clinically relevant.
EVALuna2:36212

Cell death in the gut epithelium and implications for chronic inflammation - Patankar, Jay V.; Becker, Christoph (Nature Reviews Gastroenterology & Hepatology, 2020)
The intestinal epithelium has one of the highest rates of cellular turnover in a process that is tightly regulated. As the transit-amplifying progenitors of the intestinal epithelium generate 300 cells per crypt every day, regulated cell death and sloughing at the apical surface keeps the overall cell number in check. An aberrant increase in the rate of intestinal epithelial cell (IEC) death underlies instances of extensive epithelial erosion, which is characteristic of several intestinal diseases such as inflammatory bowel disease and infectious colitis. Emerging evidence points to a crucial role of necroptosis, autophagy and pyroptosis as important modes of programmed cell death in the intestine in addition to apoptosis. The mode of cell death affects tissue restitution responses and ultimately the long-term risks of intestinal fibrosis and colorectal cancer. A vicious cycle of intestinal barrier breach, misregulated cell death and subsequent inflammation is at the heart of chronic inflammatory and infectious gastrointestinal diseases. This Review discusses the underlying molecular and cellular underpinnings that control programmed cell death in IECs, which emerge during intestinal diseases. Translational aspects of cell death modulation for the development of novel therapeutic alternatives for inflammatory bowel diseases and colorectal cancer are also discussed.
CRIS-Team Scopus Importer:2020-07-24

Cellular Mechanisms of Etrolizumab Treatment in Inflammatory Bowel Disease - Lichnog, Charlotte; Klabunde, Sha; Becker, Emily; Fuh, Franklin; Tripal, Philipp; Atreya, Raja; Klenske, Entcho; Erickson, Rich; Chiu, Henry; Reed, Chae; Chung, Shan; Neufert, Clemens; et al. (Frontiers in Pharmacology, 2019)
Background: Anti-integrin therapy is a new frontline strategy in the treatment of inflammatory bowel diseases (IBD). The anti-beta 7 integrin antibody etrolizumab is currently being investigated for safety and efficacy in Crohn's disease (CD) and ulcerative colitis (UC) in several phase III trials. Mechanistically, etrolizumab is known to block beta 7 integrin ligand binding and reduces intestinal trafficking of beta 7-expressing cells. Etrolizumab blocks beta 7 integrin ligand binding and reduces beta 7-positive lymphocyte migration and retention in the inflamed gut mucosa, but the exact mechanisms by which this inhibition occurs are not fully understood.
CRIS-Team WoS Importer:2019-02-21

Cellular plasticity and myeloid inflammation in the adult brain are independent of the transcriptional modulator DREAM - Masanetz, Rebecca Katharina; Baum, Wolfgang; Schett, Georg; Winkler, Jürgen; Süß, Patrick (Neuroscience Letters, 2023)
The downstream regulatory element antagonist modulator (DREAM) modulates ion channel function and gene transcription. Functionally, DREAM is implicated in physiological and pathological processes including cell proliferation, inflammation, and nociception. Despite its multiple functions and robust expression in forebrain tissue, neurons and glial cells, the role of DREAM in regard to cellular plasticity and tumor necrosis factor (TNF)-mediated inflammation is largely unexplored. Here, we demonstrate that adult hippocampal neurogenesis as well as the density and plasticity of glial cells in the hippocampus and thalamus are independent of the presence of DREAM. Further, DREAM deletion does not alter the regional myeloid response and inflammatory gene expression induced by chronic peripheral inflammation in mice overexpressing human TNF. Our data suggest that despite their highly dynamic regulation, neural cell plasticity and adult neurogenesis in the hippocampus do not depend on the multifunctional protein DREAM. Furthermore, TNF-mediated myeloid inflammation in the brain persists in the absence of DREAM.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Adult hippocampal neurogenesis; DREAM; Glia; Neuroinflammation; Pain; Proliferation

Centrosomal microtubule nucleation regulates radial migration of projection neurons independently of polarization in the developing brain - Vinopal, Stanislav; Dupraz, Sebastian; Alfadil, Eissa; Pietralla, Thorben; Bendre, Shweta; Stiess, Michael; Falk, Sven; Ortega, German Camargo; Maghelli, Nicola; Tolic, Iva M.; Smejkal, Jiri; Goetz, Magdalena; et al. (Neuron, 2023)
Cortical projection neurons polarize and form an axon while migrating radially. Even though these dynamic processes are closely interwoven, they are regulated separately-the neurons terminate their migration when reaching their destination, the cortical plate, but continue to grow their axons. Here, we show that in rodents, the centrosome distinguishes these processes. Newly developed molecular tools modulating centrosomal microtubule nucleation combined with in vivo imaging uncovered that dysregulation of centro-somal microtubule nucleation abrogated radial migration without affecting axon formation. Tightly regu-lated centrosomal microtubule nucleation was required for periodic formation of the cytoplasmic dilation at the leading process, which is essential for radial migration. The microtubule nucleating factor g-tubulin decreased at neuronal centrosomes during the migratory phase. As distinct microtubule networks drive neuronal polarization and radial migration, this provides insight into how neuronal migratory defects occur without largely affecting axonal tracts in human developmental cortical dysgeneses, caused by mutations in g-tubulin.
CRIS-Team WoS Importer:2023-05-26

Centrosomal protein TRIM43 restricts herpesvirus infection by regulating nuclear lamina integrity - Full, Florian; Van Gent, Michiel; Sparrer, Konstantin M. J.; Chiang, Cindy; Zurenski, Matthew A.; Scherer, Myriam; Brockmeyer, Norbert H.; Heinzerling, Lucie; Stürzl, Michael; Korn, Klaus; Stamminger, Thomas; Enßer, Armin; et al. (Nature Microbiology, 2019)
Tripartite motif (TRIM) proteins mediate antiviral host defences by either directly targeting viral components or modulating innate immune responses. Here we identify a mechanism of antiviral restriction in which a TRIM E3 ligase controls viral replication by regulating the structure of host cell centrosomes and thereby nuclear lamina integrity. Through RNAi screening we identified several TRIM proteins, including TRIM43, that control the reactivation of Kaposi's sarcoma-associated herpesvirus. TRIM43 was distinguished by its ability to restrict a broad range of herpesviruses and its profound upregulation during herpesvirus infection as part of a germline-specific transcriptional program mediated by the transcription factor DUX4. TRIM43 ubiquitinates the centrosomal protein pericentrin, thereby targeting it for proteasomal degradation, which subsequently leads to alterations of the nuclear lamina that repress active viral chromatin states. Our study identifies a role of the TRIM43-pericentrin-lamin axis in intrinsic immunity, which may be targeted for therapeutic intervention against herpesviral infections.
EVALuna2:35255

Changes in Gastrointestinal Microbiome Composition in PD: A Pivotal Role of Covariates - Cosma-Grigorov, Alexandra; Meixner, Holger; Mrochen, Anne; Wirtz, Stefan; Winkler, Jürgen; Marxreiter, Franz (Frontiers in Neurology, 2020)
Altered gut microbiota may trigger or accelerate alpha-synuclein aggregation in the enteric nervous system in Parkinson's disease (PD). While several previous studies observed gut microbiota alterations in PD, findings like diversity indices, and altered bacterial taxa itself show a considerable heterogeneity across studies. We recruited 179 participants, of whom 101 fulfilled stringent inclusion criteria. Subsequently, the composition of the gut microbiota in 71 PD patients and 30 healthy controls was analyzed, sequencing V3–V4 regions of the bacterial 16S ribosomal RNA gene in fecal samples. Our goal was (1) to evaluate whether gut microbiota are altered in a southern German PD cohort, (2) to delineate the influence of disease duration, stage, and motor impairment, and (3) to investigate the influence of PD associated covariates like constipation and coffee consumption. Aiming to control for a large variety of covariates, strict inclusion criteria were applied. Finally, propensity score matching was performed to correct for, and to delineate the effect of remaining covariates (non-motor symptom (NMS) burden, constipation, and coffee consumption) on microbiota composition. Prior to matching altered abundances of distinct bacterial classes, orders, families, and genera were observed. Both, disease duration, and stage influenced microbiome composition. Interestingly, levodopa equivalent dose influenced the correlation of taxa with disease duration, while motor impairment did not. Applying different statistical tests, and after propensity score matching to control for NMS burden, constipation and coffee consumption, Faecalibacterium and Ruminococcus were most consistently reduced in PD compared to controls. Taken together, similar to previous studies, alterations of several taxa were observed in PD. Yet, further controlling for PD associated covariates such as constipation and coffee consumption revealed a pivotal role of these covariates. Our data highlight the impact of these PD associated covariates on microbiota composition in PD. This suggests that altered microbiota may mediate the protective effect of i.e., coffee consumption and the negative effect of constipation in PD.
CRIS-Team Scopus Importer:2020-10-16
Keywords: biomarker; constipation; covariates; gut; microbiome; non-motor symptoms; Parkinson's disease

Characterization and Manipulation of the Crosstalk Between Dendritic and Natural Killer Cells Within the Tumor Microenvironment - Jacobs, Benedikt; Gebel, Veronika; Heger, Lukas; Greze, Victoria; Schild, Hansjorg; Dudziak, Diana; Ullrich, Evelyn (Frontiers in Immunology, 2021)
Cellular therapy has entered the daily clinical life with the approval of CAR T cell therapeutics and dendritic cell (DCs) vaccines in the US and the EU. In addition, numerous other adoptive cellular products, including natural killer (NK) cells, are currently evaluated in early phase I/ II clinical trials for the treatment of cancer patients. Despite these promising accomplishments, various challenges remain to be mastered in order to ensure sustained therapeutic success. These include the identification of strategies by which tumor cells escape the immune system or establish an immunosuppressive tumor microenvironment (TME). As part of the innate immune system, DCs and NK cells are both present within the TME of various tumor entities. While NK cells are well known for their intrinsic anti-tumor activity by their cytotoxicity capacities and the secretion of pro-inflammatory cytokines, the role of DCs within the TME is a double-edged sword as different DC subsets have been described with either tumor-promoting or -inhibiting characteristics. In this review, we will discuss recent findings on the interaction of DCs and NK cells under physiological conditions and within the TME. One focus is the crosstalk of various DC subsets with NK cells and their impact on the progression or inhibition of tumor growth. In addition, we will provide suggestions to overcome the immunosuppressive outcome of the interaction of DCs and NK cells within the TME.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cellular therapies; DC-NK cell interaction; dendritic cells; NK cells; tumor microenvironment

Characterization of glycolysis-related gene expression in malignant melanoma - Koch, Andreas; Ebert, Eva Vanessa; Seitz, Tatjana; Dietrich, Peter; Berneburg, Mark; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Pathology Research and Practice, 2020)
Malignant melanoma exhibits a distinct metabolic phenotype with high glycolytic activity. Previously, we have shown that glucose transporter isoform 1 (GLUT1) favors growth and metastasis of malignant melanoma. In this study, we investigated the expression of GLUT1 and the further glycolysis-related genes hexokinase 1 and 2 (HK1, HK2), lactate dehydrogenase A (LDH-A) and monocarboxylate transporters 1 and 4 (MCT1, MCT4) in eleven human melanoma cell lines under normoxic and hypoxic conditions. Furthermore, a set of 25 human malignant melanoma tissue samples was analyzed. Under hypoxic conditions, we could observe a significant upregulation of hypoxia-inducible factor 1 alpha (HIF-1a) target genes GLUT1, HK2 and LDH-A, but not MCT4. While under normoxic conditions the expression of glycolysis-related genes showed no correlation with origin or BRAF mutation status, GLUT1 expression was significantly elevated in metastatic and BRAF-V600E mutated melanoma cell lines under hypoxic conditions. Furthermore, GLUT1 expression in human melanoma tissue samples correlated significantly with HK1, LDH-A and MCT1 expression, confirming a glycolytic phenotype. Notably, Cyclin D1 expression, which is used as a prognostic marker for the outcome of melanoma patients, as it is associated with proliferation and invasiveness of melanoma, significantly correlated with GLUT1, HK1, LDH-A and MCT1 expression. In summary, our findings provide further evidence that enhanced glycolytic activity in melanoma favors disease progression and is an attractive therapeutic target for this highly aggressive tumor.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Cyclin D1; GLUT1; Glycolysis; HK1; HK2; LDH-A; MCT1; MCT4; Melanoma

Characterization of the Protein Tyrosine Phosphatase LmPRL-1 Secreted by Leishmania major via the Exosome Pathway - Leitherer, Sabine; Clos, Joachim; Liebler-Tenorio, Elisabeth M.; Schleicher, Ulrike; Bogdan, Christian; Soulat, Didier (Infection and Immunity, 2017)
Similar to other intracellular pathogens, Leishmania parasites are known to evade the antimicrobial effector functions of host immune cells. To date, however, only a few virulence factors have been described for Leishmania major, one of the causative agents of cutaneous leishmaniasis. Here, we have characterized the expression and function of an L. major phosphatase, which we termed LmPRL-1. This enzyme shows a strong structural similarity to the human phosphatases of regenerating liver (PRL-1, -2, and -3) that regulate the proliferation, differentiation, and motility of cells. The biochemical characterization of the L. major phosphatase revealed that the enzyme is redox sensitive. When analyzing the subcellular localization of LmPRL-1 in promastigotes, amastigotes, and infected macrophages, we found that the phosphatase was predominantly expressed and secreted by promastigotes via the exosome route. Finally, we observed that ectopic expression of LmPRL-1 in L. major led to an increased number of parasites in macrophages. From these data, we conclude that the L. major phosphatase LmPRL-1 contributes to the intracellular survival of the parasites in macrophages.
EVALuna2:7751

Characterizing Intraindividual Podocyte Morphology In Vitro with Different Innovative Microscopic and Spectroscopic Techniques - Kraus, Annalena; Rose, Victoria; Krüger, René; Sarau, George; Kling, Lasse; Schiffer, Mario; Christiansen, Silke; Müller-Deile, Janina (Cells, 2023)
Podocytes are critical components of the glomerular filtration barrier, sitting on the outside of the glomerular basement membrane. Primary and secondary foot processes are characteristic for podocytes, but cell processes that develop in culture were not studied much in the past. Moreover, protocols for diverse visualization methods mostly can only be used for one technique, due to differences in fixation, drying and handling. However, we detected by single-cell RNA sequencing (scRNAseq) analysis that cells reveal high variability in genes involved in cell type-specific morphology, even within one cell culture dish, highlighting the need for a compatible protocol that allows measuring the same cell with different methods. Here, we developed a new serial and correlative approach by using a combination of a wide variety of microscopic and spectroscopic techniques in the same cell for a better understanding of podocyte morphology. In detail, the protocol allowed for the sequential analysis of identical cells with light microscopy (LM), Raman spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM). Skipping the fixation and drying process, the protocol was also compatible with scanning ion-conductance microscopy (SICM), allowing the determination of podocyte surface topography of nanometer-range in living cells. With the help of nanoGPS Oxyo®, tracking concordant regions of interest of untreated podocytes and podocytes stressed with TGF-β were analyzed with LM, SEM, Raman spectroscopy, AFM and SICM, and revealed significant morphological alterations, including retraction of podocyte process, changes in cell surface morphology and loss of cell-cell contacts, as well as variations in lipid and protein content in TGF-β treated cells. The combination of these consecutive techniques on the same cells provides a comprehensive understanding of podocyte morphology. Additionally, the results can also be used to train automated intelligence networks to predict various outcomes related to podocyte injury in the future.
CRIS-Team Scopus Importer:2023-05-26
Keywords: atomic force microscopy; filopodia; foot processes; light microscopy; nanoGPS tracking; podocytes; Raman spectroscopy; scanning electron microscopy; scanning ion-conductance microscopy; single-cell RNA sequencing

Characterizing the interaction between the htlv-1 transactivator tax-1 with transcription elongation factor ell2 and its impact on viral transactivation - Kohrt, Stephan; Strobel, Sarah; Mann, Melanie; Sticht, Heinrich; Fleckenstein, Bernhard; Thoma-Kreß, Andrea (International Journal of Molecular Sciences, 2021)
The human T-cell leukemia virus type 1 (HTLV-1)-encoded transactivator and oncoprotein Tax-1 is essential for HTLV-1 replication. We recently found that Tax-1 interacts with transcription elongation factor for RNA polymerase II 2, ELL2, which enhances Tax-1-mediated transactivation of the HTLV-1 promotor. Here, we characterize the Tax-1:ELL2 interaction and its impact on viral transactivation by confocal imaging, co-immunoprecipitation, and luciferase assays. We found that Tax-1 and ELL2 not only co-precipitate, but also co-localize in dot-like structures in the nucleus. Tax-1:ELL2 complex formation occurred independently of Tax-1 point mutations, which are crucial for post translational modifications (PTMs) of Tax-1, suggesting that these PTMs are irrelevant for Tax-1:ELL2 interaction. In contrast, Tax-1 deletion mutants lacking either N-terminal (aa 1–37) or C-terminal regions (aa 150–353) of Tax-1 were impaired in interacting with ELL2. Contrary to Tax-1, the related, non-oncogenic Tax-2B from HTLV-2B did not interact with ELL2. Finally, we found that ELL2-R1 (aa 1–353), which carries an RNA polymerase II binding domain, and ELL2-R3 (aa 515–640) are sufficient to interact with Tax-1; however, only ELL2-truncations expressing R1 could enhance Tax-1-mediated transactivation of the HTLV-1 promoter. Together, this study identifies domains in Tax-1 and ELL2 being required for Tax-1:ELL2 complex formation and for viral transactivation.
CRIS-Team Scopus Importer:2021-12-24
Keywords: ELL2; HTLV-1; Human T-cell leukemia virus type 1; Tax-1; Tax-2; Transcription elongation factor for RNA polymerase II; Viral oncoprotein; Viral transactivation

Chemically induced mouse models of acute and chronic intestinal inflammation - Wirtz, Stefan; Popp, Vanessa; Kindermann, Markus; Gerlach, Katharina; Weigmann, Benno; Fichtner-Feigl, Stefan; Neurath, Markus (Nature Protocols, 2017)
Inflammatory bowel diseases (IBDs) result in diarrhea and abdominal pain with further potential complications such as tissue fibrosis and stenosis. Animal models help in understanding the immunopathogenesis of IBDs and in the design of novel therapeutic concepts. Here we present an updated version of a protocol we published in 2007 for key models of acute and chronic forms of colitis induced by 2,4,6-trinitro-benzene sulfonic acid (TNBS), oxazolone and dextran sulfate sodium (DSS). This protocol update describes an adaptation of the existing protocol that modifies the technique. This protocol has been used to generate improved mouse models that better reflect the nature of IBDs in humans. In TNBS and oxazolone colitis models, topical administration of hapten reagents results in T-cell-mediated immunity against haptenized proteins and luminal antigens. By contrast, to generate DSS colitis models, mice orally receive DSS, causing death of epithelial cells, compromising barrier function and causing subsequent inflammation. The analysis of the acute colitis models can be performed within 1-2 weeks, whereas that of the chronic models may take 2-4 months. The strengths of the acute models are that they are based on the analysis of short-lasting barrier alterations, innate immune effects and flares. The advantages of the chronic models are that they may offer better insight into adaptive immunity and complications such as neoplasia and tissue fibrosis. The protocol requires basic skills in laboratory animal research.
EVALuna2:33810

Chromatin-Remodeling Factor SPOC1 Acts as a Cellular Restriction Factor against Human Cytomegalovirus by Repressing the Major Immediate Early Promoter - Reichel, Anna; Stilp, Anne-Charlotte; Scherer, Myriam; Reuter, Nina; Lukassen, Sören; Kasmapour, Bahram; Schreiner, Sabrina; Cicin-Sain, Luka; Winterpacht, Andreas; Stamminger, Thomas (Journal of Virology, 2018)
The cellular protein SPOC1 (survival time-associated PHD [plant homeodomain] finger protein in ovarian cancer 1) acts as a regulator of chromatin structure and the DNA damage response. It binds H3K4me2/3-containing chromatin and promotes DNA condensation by recruiting corepressors such as KAP-1 and H3K9 methyltransferases. Previous studies identified SPOC1 as a restriction factor against human adenovirus (HAdV) infection that is antagonized by E1B-55K/E4-orf6-dependent proteasomal degradation. Here, we demonstrate that, in contrast to HAdV-infected cells, SPOC1 is transiently upregulated during the early phase of human cytomegalovirus (HCMV) replication. We show that the expression of immediate early protein 1 (IE1) is sufficient and necessary to induce SPOC1. Additionally, we discovered that during later stages of infection, SPOC1 is downregulated in a glycogen synthase kinase 3β (GSK-3β)-dependent manner. We provide evidence that SPOC1 overexpression severely impairs HCMV replication by repressing the initiation of viral immediate early (IE) gene expression. Consistently, we observed that SPOC1-depleted primary human fibroblasts displayed an augmented initiation of viral IE gene expression. This occurs in a multiplicity of infection (MOI)-dependent manner, a defining hallmark of intrinsic immunity. Interestingly, repression requires the presence of high SPOC1 levels at the start of infection, while later upregulation had no negative impact, suggesting distinct temporal roles of SPOC1 during the HCMV replicative cycle. Mechanistically, we observed a highly specific association of SPOC1 with the major immediate early promoter (MIEP), strongly suggesting that SPOC1 inhibits HCMV replication by MIEP binding and the subsequent recruitment of heterochromatin-building factors. Thus, our data add SPOC1 as a novel factor to the endowment of a host cell to restrict cytomegalovirus infections.IMPORTANCE Accumulating evidence indicates that during millennia of coevolution, host cells have developed a sophisticated compilation of cellular factors to restrict cytomegalovirus infections. Defining this equipment is important to understand cellular barriers against viral infection and to develop strategies to utilize these factors for antiviral approaches. So far, constituents of PML nuclear bodies and interferon gamma-inducible protein 16 (IFI16) were known to mediate intrinsic immunity against HCMV. In this study, we identify the chromatin modulator SPOC1 as a novel restriction factor against HCMV. We show that preexisting high SPOC1 protein levels mediate a silencing of HCMV gene expression via a specific association with an important viral cis-regulatory element, the major immediate early promoter. Since SPOC1 expression varies between cell types, this factor may play an important role in tissue-specific defense against HCMV.
EVALuna2:34842

Chronic intestinal inflammation in mice expressing viral Flip in epithelial cells - Ruder, Barbara; Murtadak, Vinay; Stürzl, Michael; Wirtz, Stefan; Distler, Ute; Tenzer, Stefan; Mahapatro, Mousumi; Greten, Florian R.; Hu, Yinling; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; et al. (Mucosal Immunology, 2018)
Viruses are present in the intestinal microflora and are currently discussed as a potential causative mechanism for the development of inflammatory bowel disease. A number of viruses, such as Human Herpesvirus-8, express homologs to cellular FLIPs, which are major contributors for the regulation of epithelial cell death. In this study we analyzed the consequences of constitutive expression of HHV8-viral FLIP in intestinal epithelial cells (IECs) in mice. Surprisingly, expression of vFlip disrupts tissue homeostasis and induces severe intestinal inflammation. Moreover vFlipIEC-tg mice showed reduced Paneth cell numbers, associated with excessive necrotic cell death. On a molecular level vFlip expression altered classical and alternative NFκB activation. Blocking of alternative NFκB signaling by deletion of Ikka in vivo largely protected mice from inflammation and Paneth cell loss induced by vFLIP. Collectively, our data provide functional evidence that expression of a single viral protein in IECs can be sufficient to disrupt epithelial homeostasis and to initiate chronic intestinal inflammation.
EVALuna2:35131

Circulating Adaptive Immune Cells Expressing the Gut Homing Marker α4β7 Integrin Are Decreased in COVID-19 - Müller, Tanja; Becker, Elisabeth; Wiendl, Maximilian; Schulze, Lisa; Voskens, Caroline; Kremer, Andreas; Neurath, Markus; Zundler, Sebastian; Völkl, Simon (Frontiers in Immunology, 2021)
Background: Infection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a wide range of symptoms including gastrointestinal manifestations, and intestinal epithelial cells are a target of the virus. However, it is unknown how the intestinal immune system contributes to systemic immune responses in coronavirus disease 2019 (COVID-19). Methods: We characterized peripheral blood lymphocytes from patients with active COVID-19 and convalescent patients as well as healthy controls by flow cytometry. Results: The frequency and absolute number of circulating memory T and B cells expressing the gut homing integrin α4β7 integrin was reduced during COVID-19, whether gastrointestinal symptoms were present or not. While total IgA-expressing B cells were increased, gut-imprinted B cells with IgA expression were stable. Conclusion: COVID-19 is associated with a decrease in circulating adaptive immune cells expressing the key gut homing marker α4β7 suggesting that these cells are preferentially recruited to extra-intestinal tissues independently of α4β7 or that the systemic immune response against SARS-CoV-2 is at least numerically dominated by extraintestinal, particularly pulmonary, immune cell priming.
CRIS-Team Scopus Importer:2021-05-21
Keywords: COVID-19; gut homing; integrins; SARS-CoV-2 infection; T cell trafficking

Citrullination licenses calpain to decondense nuclei in neutrophil extracellular trap formation - Goesswein, Stefanie; Lindemann, Aylin; Mahajan, Aparna; Maueröder, Christian; Martini, Eva; Patankar, Jay; Schett, Georg; Becker, Christoph; Wirtz, Stefan; Naumann-Bartsch, Nora; Bianchi, Marco E.; Greer, Peter A.; et al. (Frontiers in Immunology, 2019)
Neutrophils respond to various stimuli by decondensing and releasing nuclear chromatin characterized by citrullinated histones as neutrophil extracellular traps (NETs). This achieves pathogen immobilization or initiation of thrombosis, yet the molecular mechanisms of NET formation remain elusive. Peptidyl arginine deiminase-4 (PAD4) achieves protein citrullination and has been intricately linked to NET formation. Here we show that citrullination represents a major regulator of proteolysis in the course of NET formation. Elevated cytosolic calcium levels trigger both peptidylarginine deiminase-4 (PAD4) and calpain activity in neutrophils resulting in nuclear decondensation typical of NETs. Interestingly, PAD4 relies on proteolysis by calpain to achieve efficient nuclear lamina breakdown and chromatin decondensation. Pharmacological or genetic inhibition of PAD4 and calpain strongly inhibit chromatin decondensation of human and murine neutrophils in response to calcium ionophores as well as the proteolysis of nuclear proteins like lamin B1 and high mobility group box protein 1 (HMGB1). Taken together, the concerted action of PAD4 and calpain induces nuclear decondensation in the course of calcium-mediated NET formation.
CRIS-Team Scopus Importer:2019-11-15
Keywords: Calpain; Cell death; Chromatin; Citrullination; Neutrophil; Nucleus; PAD4

Class switch towards non-inflammatory, spike-specific IgG4 antibodies after repeated SARS-CoV-2 mRNA vaccination - Irrgang, Pascal; Gerling, Juliane; Kocher, Katharina; Lapuente, Dennis; Steininger, Philipp; Habenicht, Katharina Marie; Wytopil, Monika; Beileke, Stephanie; Schäfer, Simon; Zhong, Jahn; Ssebyatika, George; Krey, Thomas; et al. (Science immunology, 2022)
RNA vaccines are efficient preventive measures to combat the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. High levels of neutralizing SARS-CoV-2 antibodies are an important component of vaccine-induced immunity. Shortly after the initial two mRNA vaccine doses, the immunoglobulin G (IgG) response mainly consists of the proinflammatory subclasses IgG1 and IgG3. Here, we report that several months after the second vaccination, SARS-CoV-2–specific antibodies were increasingly composed of noninflammatory IgG4, which were further boosted by a third mRNA vaccination and/or SARS-CoV-2 variant breakthrough infections. IgG4 antibodies among all spike-specific IgG antibodies rose, on average, from 0.04% shortly after the second vaccination to 19.27% late after the third vaccination. This induction of IgG4 antibodies was not observed after homologous or heterologous SARS-CoV-2 vaccination with adenoviral vectors. Single-cell sequencing and flow cytometry revealed substantial frequencies of IgG4-switched B cells within the spike-binding memory B cell population [median of 14.4%; interquartile range (IQR) of 6.7 to 18.1%] compared with the overall memory B cell repertoire (median of 1.3%; IQR of 0.9 to 2.2%) after three immunizations. This class switch was associated with a reduced capacity of the spike-specific antibodies to mediate antibody-dependent cellular phagocytosis and complement deposition. Because Fc-mediated effector functions are critical for antiviral immunity, these findings may have consequences for the choice and timing of vaccination regimens using mRNA vaccines, including future booster immunizations against SARS-CoV-2.<br

CLEC10A Is a Specific Marker for Human CD1c+ Dendritic Cells and Enhances Their Toll-Like Receptor 7/8-Induced Cytokine Secretion - Heger, Lukas; Balk, Silke; Lühr, Jennifer; Heidkamp, Gordon Frederik; Lehmann, Christian; Hatscher, Lukas; Purbojo, Ariawan; Hartmann, Arndt; Garcia-Martin, Fayna; Nishimura, Shin-Ichiro; Cesnjevar, Robert; Nimmerjahn, Falk; et al. (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are major players for the induction of immune responses. Apart from plasmacytoid DCs (pDCs), human DCs can be categorized into two types of conventional DCs: CD141+ DCs (cDC1) and CD1c+ DCs (cDC2). Defining uniquely expressed surface markers on human immune cells is not only important for the identification of DC subpopulations but also a prerequisite for harnessing the DC subset-specific potential in immunomodulatory approaches, such as antibody-mediated antigen targeting. Although others identified CLEC9A as a specific endocytic receptor for CD141+ DCs, such a receptor for CD1c+ DCs has not been discovered, yet. By performing transcriptomic and flow cytometric analyses on human DC subpopulations from different lymphohematopoietic tissues, we identified CLEC10A (CD301, macrophage galactose-type C-type lectin) as a specific marker for human CD1c+ DCs. We further demonstrate that CLEC10A rapidly internalizes into human CD1c+ DCs upon binding of a monoclonal antibody directed against CLEC10A. The binding of a CLEC10A-specific bivalent ligand (the MUC-1 peptide glycosylated with N-acetylgalactosamine) is limited to CD1c+ DCs and enhances the cytokine secretion (namely TNFα, IL-8, and IL-10) induced by TLR 7/8 stimulation. Thus, CLEC10A represents not only a candidate to better define CD1c+ DCs-due to its high endocytic potential-CLEC10A also exhibits an interesting candidate receptor for future antigen-targeting approaches.
EVALuna2:34257

Clinical experiences and predictors of success of treatment with vedolizumab in IBD patients: a cohort study - Mühl, Laura; Becker, Elisabeth; Müller, Tanja; Atreya, Raja; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (BMC Gastroenterology, 2021)
Background: Vedolizumab has become a standard treatment for the inflammatory bowel diseases ulcerative colitis (UC) and Crohn’s disease (CD). However, there is an ongoing debate on the ideal individual treatment algorithms and means to predict treatment response are not routinely established. Aims: We aimed to describe our experiences with vedolizumab at a large German tertiary referral center and to identify clinical predictors of success of vedolizumab treatment. Methods: We performed a retrospective single-center cohort study employing univariable and multivariable analyses as well as Kaplan–Meier analyses of persistence on treatment. Results: 36% and 35% of the patients with UC and CD, respectively, reached clinical remission after 17 weeks. Patients with lower clinical disease activity were more likely to achieve remission. The median persistence on treatment was 33 months for UC and 29 months for CD. Conclusion: Our study confirms that vedolizumab is an efficient option for the treatment of UC and CD. Clinical parameters of disease activity may help to predict the success of treatment.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Inflammatory bowel diseases; Real-world data; Vedolizumab

Combinatorial drug treatments reveal promising anticytomegaloviral profiles for clinically relevant pharmaceutical kinase inhibitors (PKIs) - Wild, Markus; Kicuntod, Jintawee; Seyler, Lisa; Wangen, Christina; Bertzbach, Luca D.; Conradie, Andelé M.; Kaufer, Benedikt B.; Wagner, Sabrina; Michel, Detlef; Eickhoff, Jan; Tsogoeva, Svetlana; Bäuerle, Tobias; et al. (International Journal of Molecular Sciences, 2021)
Human cytomegalovirus (HCMV) is a human pathogenic herpesvirus associated with a variety of clinical symptoms. Current antiviral therapy is not always effective, so that improved drug classes and drug-targeting strategies are needed. Particularly host-directed antivirals, including pharmaceutical kinase inhibitors (PKIs), may help to overcome problems of drug resistance. Here, we focused on utilizing a selection of clinically relevant PKIs and determined their anticytomegaloviral efficacies. Particularly, PKIs directed to host or viral cyclin-dependent kinases, i.e., abemaciclib, LDC4297 and maribavir, exerted promising profiles against human and murine cytomegaloviruses. The anti-HCMV in vitro activity of the approved anti-cancer drug abemaciclib was confirmed in vivo using our luciferase-based murine cytomegalovirus (MCMV) animal model in immunocompetent mice. To assess drug combinations, we applied the Bliss independence checkerboard and Loewe additivity fixed-dose assays in parallel. Results revealed that (i) both affirmative approaches provided valuable information on anti-CMV drug efficacies and interactions, (ii) the analyzed combinations comprised additive, synergistic or antagonistic drug interactions consistent with the drugs’ antiviral mode-of-action, (iii) the selected PKIs, especially LDC4297, showed promising inhibitory profiles, not only against HCMV but also other α-, β-and γ-herpesviruses, and specifically, (iv) the combination treatment with LDC4297 and maribavir revealed a strong synergism against HCMV, which might open doors towards novel clinical options in the near future. Taken together, this study highlights the potential of therapeutic drug combinations of current developmental/preclinical PKIs.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Activity in vitro and in vivo; Antiviral drugs; Combinatorial drug analyses; Human cytomegalovirus; New synergistic combinations; Pharmaceutical kinase inhibitors (PKIs)

Combined Artificial Intelligence Approaches Analyzing 1000 Conservative Patients with Back Pain-A Methodological Pathway to Predicting Treatment Efficacy and Diagnostic Groups - Wirries, Andre; Geiger, Florian; Hammad, Ahmed; Redder, Andreas; Oberkircher, Ludwig; Ruchholtz, Steffen; Blümcke, Ingmar; Jabari, Samir (Diagnostics, 2021)
Patients with back pain are common and present a challenge in everyday medical practice due to the multitude of possible causes and the individual effects of treatments. Predicting causes and therapy efficien cy with the help of artificial intelligence could improve and simplify the treatment. In an exemplary collective of 1000 conservatively treated back pain patients, it was investigated whether the prediction of therapy efficiency and the underlying diagnosis is possible by combining different artificial intelligence approaches. For this purpose, supervised and unsupervised artificial intelligence methods were analyzed and a methodology for combining the predictions was developed. Supervised AI is suitable for predicting therapy efficiency at the borderline of minimal clinical difference. Non-supervised AI can show patterns in the dataset. We can show that the identification of the underlying diagnostic groups only becomes possible through a combination of different AI approaches and the baseline data. The presented methodology for the combined application of artificial intelligence algorithms shows a transferable path to establish correlations in heterogeneous data sets when individual AI approaches only provide weak results.
CRIS-Team WoS Importer:2021-12-10

Combined de‐repression of chemoresistance associated mitogen‐activated protein kinase 14 and activating transcription factor 2 by loss of microrna‐622 in hepatocellular carcinoma - Fritz, Valerie; Malek, Lara; Gaza, Anne; Wormser, Laura; Appel, Majken; Kremer, Andreas; Thasler, Wolfgang E.; Neurath, Markus; Hellerbrand, Claus; Boßerhoff, Anja Katrin; Dietrich, Peter; Siebler, Jürgen (Cancers, 2021)
Chemoresistance is a major hallmark driving the progression and poor prognosis of hepatocellular carcinoma (HCC). Limited chemoresponse of HCC was demonstrated to be mediated by mitogen‐activated protein kinase 14 (MAPK14) and activating transcription factor 2 (ATF2). Recently, we have demonstrated loss of control of RAS‐RAF‐ERK‐signaling as a consequence of miR‐622 downregulation in HCC. However, the majority of target genes of this potent tumorsuppressive microRNA had remained elusive. The MAPK14‐ATF2‐axis represents a collateral pathway ensuring persisting ERK‐activation in the presence of sorafenib‐mediated RAF-inhibition. In contrast to the function of the MAPK14‐ATF2‐axis, both the expression and regulation of MAPK14 and ATF2 in human HCC remained to be clarified. We found combined overexpression of MAPK14 and ATF2 in human HCC cells, tissues and in sorafenib resistant cell lines. High expression of MAPK14 and ATF2 was associated with reduced overall survival in HCC patients. Deciphering the molecular mechanism promoting combined upregulation of MAPK14 and ATF2 in HCC, we revealed that miR‐622 directly targets both genes, resulting in combined de‐repression of the MAPK14‐ATF2‐axis. Together, miR‐622 represents a superior regulator of both RAS‐RAF‐ERK as well as MAPK14‐ATF2‐signaling pathways in liver cancer.
CRIS-Team Scopus Importer:2021-03-19
Keywords: HCC; Hepatocellular carcinoma; Liver cancer; MAPK14; MicroRNA; MiR‐622; RAS

Combined effects of PLK1 and RAS in hepatocellular carcinoma reveal rigosertib as promising novel therapeutic "dual-hit" option - Dietrich, Peter; Freese, Kim; Mahli, Abdo; Thasler, Wolfgang Erwin; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Oncotarget, 2018)
Inhibition of RAS-RAF-ERK-signaling is a major mechanism mediated by the multi-kinase inhibitors sorafenib and regorafenib, the only effective therapeutic approaches for advanced hepatocellular carcinoma (HCC). This underlines the importance of RAS-RAF-ERK-signaling in HCC. Most RAS isoforms were not yet described to play crucial roles in HCC. However, several studies indicate that the HRAS isoform can function as potent oncogene in HCC, but pharmacologic RAS inhibition has not yet been investigated. Moreover, the cell cycle promoting polo-like kinase 1 (PLK1) is an increasingly recognized therapeutic target in HCC that can be activated by RAS-RAF-signaling. A recently developed small molecule inhibitor, ON-01910 ("rigosertib", RGS), was shown to interfere with both RAS- and PLK1-signaling. The aim of this study was to analyze the effects of RGS in HCC and to assess PLK1 and HRAS expression in HCC. RGS treatment reduced cell proliferation and induced cell cycle arrest in human HCC cell lines in vitro. Moreover, RGS strongly inhibited both ERK- and AKT-activation in HCC cells, indicating disruption of RAS-signaling. Analysis of HCC patient data showed that PLK1 and HRAS expression levels are upregulated during HCC development and in advanced HCC, respectively. High expression levels of PLK1 significantly correlated with poor patient survival. Moreover, high expression of both PLK1 and HRAS revealed combined effects on patient outcome. This underscores the importance of these genes and associated pathways in HCC. We newly demonstrate the therapeutic potential of RGS in HCC by inhibition of both PLK1 activation and major RAS-pathways, revealing a novel therapeutic "dual-hit" approach for HCC.
EVALuna2:34067

Comparative Transcriptomics of IBD Patients Indicates Induction of Type 2 Immunity Irrespective of the Disease Ideotype - Gonzalez Acera, Miguel; Patankar, Jay; Diemand, Leonard; Siegmund, Britta; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Frontiers in Medicine, 2021)
Inflammatory cytokines initiate and sustain the perpetuation of processes leading to chronic inflammatory conditions such as inflammatory bowel diseases (IBD). The nature of the trigger causing an inflammatory reaction decides whether type 1, type 17, or type 2 immune responses, typically characterized by the respective T- helper cell subsets, come into effect. In the intestine, Type 2 responses have been linked with mucosal healing and resolution upon an immune challenge involving parasitic infections. However, type 2 cytokines are frequently elevated in certain types of IBD in particular ulcerative colitis (UC) leading to the assumption that Th2 cells might critically support the pathogenesis of UC raising the question of whether such elevated type 2 responses in IBD are beneficial or detrimental. In line with this, previous studies showed that suppression of IL-13 and other type 2 related molecules in murine models could improve the outcomes of intestinal inflammation. However, therapeutic attempts of neutralizing IL-13 in ulcerative colitis patients have yielded no benefits. Thus, a better understanding of the role of type 2 cytokines in regulating intestinal inflammation is required. Here, we took a comparative transcriptomic approach to address how Th2 responses evolve in different mouse models of colitis and human IBD datasets. Our data show that type 2 immune-related transcripts are induced in the inflamed gut of IBD patients in both Crohn's disease and UC and across widely used mouse models of IBD. Collectively our data implicate that the presence of a type 2 signature rather defines a distinct state of intestinal inflammation than a disease-specific pathomechanism.
CRIS-Team Scopus Importer:2021-06-25
Keywords: chronic inflammation; IBD; intestine; type 2 immunity; ulcerative colitis

Complementary roles of murine NaV1.7, NaV1.8 and NaV1.9 in acute itch signalling - Kühn, Helen; Kappes, Leonie; Wolf, Katharina; Gebhardt, Lisa; Neurath, Markus; Reeh, Peter; Fischer, Michael J.M.; Kremer, Andreas (Scientific Reports, 2020)
Acute pruritus occurs in various disorders. Despite severe repercussions on quality of life treatment options remain limited. Voltage-gated sodium channels (NaV) are indispensable for transformation and propagation of sensory signals implicating them as drug targets. Here, NaV1.7, 1.8 and 1.9 were compared for their contribution to itch by analysing NaV-specific knockout mice. Acute pruritus was induced by a comprehensive panel of pruritogens (C48/80, endothelin, 5-HT, chloroquine, histamine, lysophosphatidic acid, trypsin, SLIGRL, β-alanine, BAM8-22), and scratching was assessed using a magnet-based recording technology. We report an unexpected stimulus-dependent diversity in NaV channel-mediated itch signalling. NaV1.7−/− showed substantial scratch reduction mainly towards strong pruritogens. NaV1.8−/− impaired histamine and 5-HT-induced scratching while NaV1.9 was involved in itch signalling towards 5-HT, C48/80 and SLIGRL. Furthermore, similar microfluorimetric calcium responses of sensory neurons and expression of itch-related TRP channels suggest no change in sensory transduction but in action potential transformation and conduction. The cumulative sum of scratching over all pruritogens confirmed a leading role of NaV1.7 and indicated an overall contribution of NaV1.9. Beside the proposed general role of NaV1.7 and 1.9 in itch signalling, scrutiny of time courses suggested NaV1.8 to sustain prolonged itching. Therefore, NaV1.7 and 1.9 may represent targets in pruritus therapy.
CRIS-Team Scopus Importer:2020-02-21

Composition of TWIST1 dimers regulates fibroblast activation and tissue fibrosis - Palumbo-Zerr, Katrin; Soare, Alina; Zerr, Pawel; Liebl, Andrea; Mancuso, Rossella; Tomcik, Michal; Sumova, Barbora; Dees, Clara; Chen, Chih-Wei; Wohlfahrt, Thomas; Mallano, Tatjana; Distler, Alfiya; et al. (Annals of the Rheumatic Diseases, 2017)
TWIST1 is a member of the class B of basic helix-loop-helix transcription factors that regulates cell lineage determination and differentiation and has been implicated in epithelial-to-mesenchymal transition. Here, we aimed to investigate the role of TWIST1 for the activation of resident fibroblasts in systemic sclerosis (SSc).The expression of Twist1 in fibroblasts was modulated by forced overexpression or siRNA-mediated knockdown. Interaction of Twist1, E12 and inhibitor Of differentiation (Id) was analysed by co-immunoprecipitation. The role of Twist1 in vivo was evaluated using inducible, conditional knockout mice with either ubiquitous or fibroblast-specific depletion of Twist1. Mice were either challenged with bleomycin or overexpressing a constitutively active transforming growth factor (TGF)? receptor I.The expression of TWIST1 was increased in fibroblasts in fibrotic human and murine skin in a TGF?/SMAD3-dependent manner. TWIST1 in turn enhanced TGF?-induced fibroblast activation in a p38-dependent manner. The stimulatory effects of TWIST1 on resident fibroblasts were mediated by TWIST1 homodimers. TGF? promotes the formation of TWIST1 homodimers by upregulation of TWIST1 and by induction of inhibitor of DNA-binding proteins, which have high affinity for E12/E47 and compete against TWIST1 for E12/E47 binding. Mice with selective depletion of Twist1 in fibroblasts are protected from experimental skin fibrosis in different murine models to a comparable degree as mice with ubiquitous depletion of Twist1.Our data identify TWIST1 as a central pro-fibrotic factor in SSc, which facilitates fibroblast activation by amplifying TGF? signalling. Targeting of TWIST1 may thus be a novel approach to normalise aberrant TGF? signalling in SSc.
EVALuna2:13273

Continuous monitoring of SARS-CoV-2 seroprevalence in children using residual blood samples from routine clinical chemistry - Wachter, Felix; Regensburger, Adrian; Peter, Antonia Sophia; Knieling, Ferdinand; Wagner, Alexandra; Simon, David; Hörning, André; Wölfle, Joachim; Überla, Klaus; Neubert, Antje; Rauh, Manfred (Clinical Chemistry and Laboratory Medicine, 2022)
Objectives The assessment of SARS-CoV-2 infections in children is still challenging, but essential for appropriate political decisions. The aim of this study was to investigate whether residual blood samples can be used for SARS-CoV-2 seroprevalence monitoring in pediatrics. Methods In this repeated cross-sectional cohort study, anonymous residual blood samples from pediatric patients aged 0-17 years were collected in three time-periods (Oct.-Nov. 2020, April 2021, and June-July 2021) and analyzed for SARS-CoV-2 Spike protein (anti-S) and nucleocapsid (anti-N) antibodies using commercial antibody assays. 28 reactive samples were used to compare antibody levels with a pseudotyped neutralization assay. The results were further compared to the official national COVID-19 surveillance data to calculate the number of unreported cases. Results In total, n=2,626 individual blood samples were analyzed. In this unvaccinated pediatric cohort anti-S and anti-N antibody seroprevalence increased over the three time periods (anti-S: 1.38-9.16%, and 14.59%; anti-N: 1.26%, to 6.19%, and 8.56%). Compared to the national surveillance data this leads to a 3.93-5.66-fold increase in the number of unreported cases. However, a correlation between the cumulative incidence of the individual provinces and our assigned data was found (r=0.74, p=0.0151). In addition, reactive samples with anti-S and anti-N and samples with only anti-S showed neutralization capabilities (11/14 and 8/14, respectively). Anti-S levels were not significantly different between age groups and sexes (all p>0.05). Conclusions The present study suggests that residual blood samples from routine laboratory chemistry could be included in the estimation of the total SARS-CoV-2 seroprevalence in children.
CRIS-Team WoS Importer:2022-03-11
Keywords: COVID-19; pediatrics; prevalence; SARS-CoV-2

Contrast-Enhanced Multispectral Optoacoustic Tomography for Functional Assessment of the Gastrointestinal Tract - Paulus, Lars-Philip; Bühler, Adrian; Wagner, Alexandra; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Rother, Ulrich; Eckstein, Markus; Lang, Werner; Hörning, André; et al. (Advanced Science, 2023)
Real-time imaging and functional assessment of the intestinal tract and its transit pose a significant challenge to conventional clinical diagnostic methods. Multispectral optoacoustic tomography (MSOT), a molecular-sensitive imaging technology, offers the potential to visualize endogenous and exogenous chromophores in deep tissue. Herein, a novel approach using the orally administered clinical-approved fluorescent dye indocyanine green (ICG) for bedside, non-ionizing evaluation of gastrointestinal passage is presented. The authors are able to show the detectability and stability of ICG in phantom experiments. Furthermore, ten healthy subjects underwent MSOT imaging at multiple time points over eight hours after ingestion of a standardized meal with and without ICG. ICG signals can be visualized and quantified in different intestinal segments, while its excretion is confirmed by fluorescent imaging of stool samples. These findings indicate that contrast-enhanced MSOT (CE-MSOT) provides a translatable real-time imaging approach for functional assessment of the gastrointestinal tract.
CRIS-Team Scopus Importer:2023-06-30
Keywords: indocyanine green; intestine; multispectral optoacoustic tomography; optoacoustics; photoacoustics

Contrast-Enhanced µCT for Visualizing and Evaluating Murine Intestinal Inflammation - Jung, Dennis; Heiß, Rafael; Kramer, Viktoria; Thoma, Oana-Maria; Regensburger, Adrian; Rascher, Wolfgang; Uder, Michael; Neurath, Markus; Knieling, Ferdinand; Waldner, Maximilian (Theranostics, 2018)
Rationale: To develop a simple and fast protocol for the assessment of acute and chronic experimental intestinal inflammation using contrast-enhanced µCT. Methods: For the imaging studies, an acute 2% and 3% dextran sodium sulfate (n = 15, female, 8-12 weeks) and a chronic adoptive transfer colitis model (n = 10, female, 8-9 weeks) were established over 9 days or 6 weeks, respectively. Throughout the experiments, longitudinal measurement of murine intestinal wall thickness and time dependent perfusion was performed on a small animal µCT system (90 kV, 160 μA, FOV: 60 mm, scan time: 17 s, image size: 512x512, layer thickness: 118 µm) between 0.5 and 30 min after intravenous bolus injection of an iodine contrast agent. Weight development, small animal endoscopy, and histological ex vivo analysis were compared to contrast-enhanced µCT imaging findings. Results: Murine intestinal wall thickness was significantly increased in inflamed colons of acute colitis at day 9 in comparison to pre-inflamed state. Perfusion analysis revealed a late contrast enhancement in acute inflamed colons and the renal medulla at day 9 compared to control mice. An increasing intestinal wall thickness was monitored 3, 5 and 6 weeks after on-set of chronic colitis in comparison to controls. A good correlation with endoscopic (r = 0.75, p < 0.0001) and histologic degree of inflammation (r = 0.83, p = 0.04) was found. Conclusion: Contrast-enhanced µCT is a simple and fast method to assess acute intestinal inflammation and to monitor disease progression in experimental models of chronic colitis. According to our findings, one single contrast-enhanced µCT-scan is a valid non-invasive modality to quantify the degree of inflammation in the entire digestive tract in murine inflammatory models.
EVALuna2:35195

Corrigendum to "Proposal for a Novel Histological Scoring System as a Potential Grading Approach for Muscle-invasive Urothelial Bladder Cancer Correlating with Disease Aggressiveness and Patient Outcomes" [European Urology Oncology (2023)]. - Eckstein, Markus; Matek, Christian; Wagner, Paul; Erber, Ramona; Büttner-Herold, Maike; Wild, Peter J.; Taubert, Helge; Wach, Sven; Sikic, Danijel; Wullich, Bernd; Geppert, Carol-Immanuel; Compérat, Eva M.; et al. (European Urology Oncology, 2023)
EVALuna2:542094

CSF1R-Mediated Myeloid Cell Depletion Prolongs Lifespan But Aggravates Distinct Motor Symptoms in a Model of Multiple System Atrophy - Battis, Kristina; Florio, Jazmin B.; Mante, Michael; Lana, Addison; Naumann, Isabel; Gauer, Carina; Lambrecht, Vera; Müller, Sarina Katrin; Cobo, Isidoro; Fixsen, Bethany; Kim, Ha Yeon; Masliah, Eliezer; et al. (Journal of Neuroscience, 2022)
As the CNS-resident macrophages and member of the myeloid lineage, microglia fulfill manifold functions important for brain development and homeostasis. In the context of neurodegenerative diseases, they have been implicated in degenerative and regenerative processes. The discovery of distinct activation patterns, including increased phagocytosis, indicated a damaging role of myeloid cells in multiple system atrophy (MSA), a devastating, rapidly progressing atypical parkinsonian disorder. Here, we analyzed the gene expression profile of microglia in a mouse model of MSA (MBP29-ha-syn) and identified a disease-associated expression profile and upregulation of the colony-stimulating factor 1 (Csf1). Thus, we hypothesized that CSF1 receptor-mediated depletion of myeloid cells using PLX5622 modifies the disease progression and neuropathological phenotype in this mouse model. Intriguingly, sex-balanced analysis of myeloid cell depletion in MBP29-ha-syn mice revealed a two-faced outcome comprising an improved survival rate accompanied by a delayed onset of neurological symptoms in contrast to severely impaired motor functions. Furthermore, PLX5622 reversed gene expression profiles related to myeloid cell activation but reduced gene expression associated with transsynaptic signaling and signal release. While transcriptional changes were accompanied by a reduction of dopaminergic neurons in the SNpc, striatal neuritic density was increased upon myeloid cell depletion in MBP29-ha-syn mice. Together, our findings provide insight into the complex, two-faced role of myeloid cells in the context of MSA emphasizing the importance to carefully balance the beneficial and adverse effects of CSF1R inhibition in different models of neurodegenerative disorders before its clinical translation.
CRIS-Team Scopus Importer:2022-11-04
Keywords: colony-stimulating factor 1 receptor; motor function; multiple system atrophy; myeloid cells; neuron-micro-glia interaction; PLX5622

CTCF variants in 31 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum - Konrad, Enrico; Nardini, N.; Blyth, M.; Prescott, K.; Bouman, A. M.; Brilstra, E. H.; Caliebe, A.; Ibitoye, R.; Chang, V. Y.; Gupta, A.; Le Guyader, G.; Jamra, R. A.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2021-10-18

CTCF variants in 39 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum - Konrad, Enrico; Nardini, Niels; Caliebe, Almuth; Nagel, Inga; Young, Dana; Horvath, Gabriella; Santoro, Stephanie L.; Shuss, Christine; Ziegler, Alban; Bonneau, Dominique; Kempers, Marlies; Pfundt, Rolph; et al. (Genetics in Medicine, 2019)
Purpose: Pathogenic variants in the chromatin organizer CTCF were previously reported in seven individuals with a neurodevelopmental disorder (NDD). Methods: Through international collaboration we collected data from 39 subjects with variants in CTCF. We performed transcriptome analysis on RNA from blood samples and utilized Drosophila melanogaster to investigate the impact of Ctcf dosage alteration on nervous system development and function. Results: The individuals in our cohort carried 2 deletions, 8 likely gene-disruptive, 2 splice-site, and 20 different missense variants, most of them de novo. Two cases were familial. The associated phenotype was of variable severity extending from mild developmental delay or normal IQ to severe intellectual disability. Feeding difficulties and behavioral abnormalities were common, and variable other findings including growth restriction and cardiac defects were observed. RNA-sequencing in five individuals identified 3828 deregulated genes enriched for known NDD genes and biological processes such as transcriptional regulation. Ctcf dosage alteration in Drosophila resulted in impaired gross neurological functioning and learning and memory deficits. Conclusion: We significantly broaden the mutational and clinical spectrum of CTCF-associated NDDs. Our data shed light onto the functional role of CTCF by identifying deregulated genes and show that Ctcf alterations result in nervous system defects in Drosophila.
Keywords: chromatin organization; CTCF; Drosophila melanogaster; intellectual disability; neurodevelopmental disorders

Cutting Edge: Homeostasis of Innate Lymphoid Cells Is Imbalanced in Psoriatic Arthritis - Soare, Alina; Weber, Stefanie; Maul, Lisa; Rauber, Simon; Gheorghiu, Ana Maria; Luber, Markus; Houssni, Ismail; Kleyer, Arnd; von Pickardt, Gero; Gado, Manuel; Simon, David; Rech, Jürgen; et al. (Journal of Immunology, 2018)
Innate lymphoid cells (ILC) have a high potency for cytokine production independent of specific Ag stimulation. Imbalance of ILC subsets may influence cytokine production in humans and hence be associated with the development of inflammatory disease. Evidence for an imbalance of ILC homeostasis in human disease, however, is very limited to date. In this study we show that psoriatic arthritis (PsA), a severe disease of the joints depending on the activation of the IL-23/IL-17 pathway, is characterized by a skewed ILC homeostasis. Circulating ILC3s as potent source of IL-17/IL-22 were elevated in active PsA, whereas ILC2s, which produce proresolving cytokines, were decreased. The ILC2/ILC3 ratio was significantly correlated with clinical disease activity scores and the presence of imaging signs of joint inflammation and bone damage. Multivariable analysis showed that a high ILC2/ILC3 ratio is associated with remission in PsA, suggesting that specific alterations of ILC homeostasis control disease activity in PsA.
EVALuna2:13524

CXCR4 blockade reduces the severity of murine heart allograft rejection by plasmacytoid dendritic cell-mediated immune regulation - Fu, Jian; Lehmann, Christian; Wang, Xinning; Wahlbuhl, Mandy; Allabauer, Ida; Wilde, Benjamin; Amon, Lukas; Dolff, Sebastian; Cesnjevar, Robert; Kribben, Andreas; Wölfle, Joachim; Rascher, Wolfgang; et al. (Scientific Reports, 2021)
Allograft-specific regulatory T cells (Treg cells) are crucial for long-term graft acceptance after transplantation. Although adoptive Treg cell transfer has been proposed, major challenges include graft-specificity and stability. Thus, there is an unmet need for the direct induction of graft-specific Treg cells. We hypothesized a synergism of the immunotolerogenic effects of rapamycin (mTOR inhibition) and plerixafor (CXCR4 antagonist) for Treg cell induction. Thus, we performed fully-mismatched heart transplantations and found combination treatment to result in prolonged allograft survival. Moreover, fibrosis and myocyte lesions were reduced. Although less CD3+ T cell infiltrated, higher Treg cell numbers were observed. Noteworthy, this was accompanied by a plerixafor-dependent plasmacytoid dendritic cells-(pDCs)-mobilization. Furthermore, in vivo pDC-depletion abrogated the plerixafor-mediated Treg cell number increase and reduced allograft survival. Our pharmacological approach allowed to increase Treg cell numbers due to pDC-mediated immune regulation. Therefore pDCs can be an attractive immunotherapeutic target in addition to plerixafor treatment.
CRIS-Team Scopus Importer:2021-12-24

Cyclin‐Dependent Kinases (CDKs) and the Human Cytomegalovirus‐Encoded CDK Ortholog pUL97 Represent Highly Attractive Targets for Synergistic Drug Combinations - Wild, Markus; Hahn, Friedrich; Brückner, Nadine; Schütz, Martin; Wangen, Christina; Wagner, Sabrina; Sommerer, Markus; Strobl, Stefan; Marschall, Manfred (International Journal of Molecular Sciences, 2022)
Human cytomegalovirus (HCMV) is a pathogenic human herpesvirus associated with serious, potentially life‐threatening symptoms in the immunocompromised or immunonaïve host. The limitations encountered by antiviral therapy options currently available include a narrow panel of accessible targets, the induction of viral drug resistance as well as severe drug dosage‐mediated side‐effects. Improved drug‐targeting strategies to resolve these issues are the focus of our investigations. In particular, pharmaceutical kinase inhibitors (PKIs), either directed to host kinases or directed to the viral protein kinase pUL97, have been considered to overcome these restrictions. Recently, we reported the identification of a synergistic combination of two PKIs directed to host cyclin‐dependent kinase 7 (CDK7) and viral CDK ortholog pUL97. Here, we substantiate these findings with the following results: (i) true drug synergy was exhibited by various chemical classes of PKI pairs directed to pUL97 and CDK7; (ii) no putative amplification of cytotoxicity by these drug combinations was observed; (iii) a reduction in drug dosage levels for synergistic combinations was defined on a quantitative basis and compared to monotreatments; (iv) the quantities of target proteins CDK7 and pUL97 expressed in HCMV‐infected cells were assessed by confocal imaging, indicating a strong down‐modulation of CDK7 levels as a result of synergistic drug treatment; (v) the functional importance of these target kinases, both binding to cyclin H, was illustrated by assessing HCMV replication under the viral genomic deletion of ORF‐UL97 or cellular cyclin knock‐out; (vi) new combinations of HCMV‐specific drug synergy were demonstrated for solely host‐directed treatments using PKIs against CDK2, CDK7, CDK8 and/or CDK9 and (vii) a triple PKI combination provided further support for the synergy approach. With these combined findings, this study highlights the potential of therapeutic drug combinations of approved, developmental and preclinical PKIs for expanding future options for anti‐HCMV therapy.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Antiviral drug; Antiviral drug synergism; Cyclin‐dependent kinase (CDK); Direct‐acting antiviral (DAA); Drug combinations; Host‐directed antiviral (HDA); Human cytomegalovirus; New synergistic drug‐target combinations; Pharmaceutical kinase inhibitor (PKI); Viral CDK pUL97 (vCDK)

Cyst growth in ADPKD is prevented by pharmacological and genetic inhibition of TMEM16A in vivo - Cabrita, Ines; Kraus, Andre; Scholz, Julia Katharina; Skoczynski, Kathrin; Schreiber, Rainer; Kunzelmann, Karl; Buchholz, Björn (Nature Communications, 2020)
In autosomal dominant polycystic kidney disease (ADPKD) multiple bilateral renal cysts gradually enlarge, leading to a decline in renal function. Transepithelial chloride secretion through cystic fibrosis transmembrane conductance regulator (CFTR) and TMEM16A (anoctamin 1) are known to drive cyst enlargement. Here we demonstrate that loss of Pkd1 increased expression of TMEM16A and CFTR and Cl− secretion in murine kidneys, with TMEM16A essentially contributing to cyst growth. Upregulated TMEM16A enhanced intracellular Ca2+ signaling and proliferation of Pkd1-deficient renal epithelial cells. In contrast, increase in Ca2+ signaling, cell proliferation and CFTR expression was not observed in Pkd1/Tmem16a double knockout mice. Knockout of Tmem16a or inhibition of TMEM16A in vivo by the FDA-approved drugs niclosamide and benzbromarone, as well as the TMEM16A-specific inhibitor Ani9 largely reduced cyst enlargement and abnormal cyst cell proliferation. The present data establish a therapeutic concept for the treatment of ADPKD.
CRIS-Team Scopus Importer:2020-09-04

Cytokine-Mediated Crosstalk between Immune Cells and Epithelial Cells in the Gut - Mahapatro, Mousumi; Erkert, Lena; Becker, Christoph (Cells, 2021)
Cytokines are small proteins that are secreted by a vast majority of cell types in the gut. They not only establish cell-to-cell interactions and facilitate cellular signaling, but also regulate both innate and adaptive immune responses, thereby playing a central role in genetic, inflammatory, and infectious diseases of the gut. Both, immune cells and gut epithelial cells, play important roles in intestinal disease development. The epithelium is located in between the mucosal immune system and the gut microbiome. It not only establishes an efficient barrier against gut microbes, but it also signals information from the gut lumen and its composition to the immune cell compartment. Communication across the epithelial cell layer also occurs in the other direction. Intestinal epithelial cells respond to immune cell cytokines and their response influences and shapes the microbial community within the gut lumen. Thus, the epithelium should be seen as a translator or a moderator between the microbiota and the mucosal immune system. Proper communication across the epithelium seems to be a key to gut homeostasis. Indeed, current genome-wide association studies for intestinal disorders have identified several disease susceptibility loci, which map cytokine signatures and their related signaling genes. A thorough understanding of this tightly regulated cytokine signaling network is crucial. The main objective of this review was to shed light on how cytokines can orchestrate epithelial functions such as proliferation, cell death, permeability, microbe interaction, and barrier maintenance, thereby safeguarding host health. In addition, cytokine-mediated therapy for inflammation and cancer are discussed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: cytokines; gut homeostasis; IBD; immunity; inflammation; signaling

Cytomegalovirus cyclin-dependent kinase ortholog vCDK/pUL97 undergoes regulatory interaction with human cyclin H and CDK7 to codetermine viral replication efficiency - Schütz, Martin; Wangen, Christina; Sommerer, Markus; Kögler, Melanie; Eickhoff, Jan; Degenhart, Carsten; Klebl, Bert; Naing, Zin; Egilmezer, Ece; Hamilton, Stuart T.; Rawlinson, William D.; Sticht, Heinrich; et al. (Virus Research, 2023)
Human cytomegalovirus (HCMV) infection is shaped by a tightly regulated interplay between viral and cellular proteins. Distinct kinase activities, such as the viral cyclin-dependent kinase ortholog (vCDK) pUL97 and cellular CDK7 are both crucial for efficient viral replication. Previously, we reported that both kinases, vCDK/pUL97 and CDK7, interact with cyclin H, thereby achieving an enhanced level of kinase activity and overall functionality in viral replication. Here we provide a variety of novel results, as generated on a methodologically extended basis, and present a concept for the codetermination of viral replication efficiency through these kinase activities: (i) cyclin H expression, in various human cell types, is substantially upregulated by strains of HCMV including the clinically relevant HCMV Merlin; (ii) vCDK/pUL97 interacts with human cyclin H in both HCMV-infected and plasmid-transfected cell systems; (iii) a doxycycline-inducible shRNA-dependent knock-down (KD) of cyclin H significantly reduces pUL97 activity (qSox in vitro kinase assay); (iv) accordingly, pUL97 in vitro kinase activity is seen significantly increased upon addition of recombinant cyclin H; (v) as a point of specific importance, human CDK7 activity shows an increase by vCDK/pUL97-mediated trans-stimulation (whereas pUL97 is not stimulated by CDK7); (vi) phosphosite-specific antibodies indicate an upregulated CDK7 phosphorylation upon HCMV infection, as mediated through a pUL97-specific modulatory effect (i.e. shown by pUL97 inhibitor treatment or pUL97-deficient viral mutant); (vii) finally, an efficient KD of cyclin H in primary fibroblasts generally results in an impaired HCMV replication efficiency as measured on protein and genomic levels. These results show evidence for the codetermination of viral replication by vCDK/pUL97, cyclin H and CDK7, thus supporting the specific importance of cyclin H as a central regulatory factor, and suggesting novel targeting options for antiviral drugs.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Codetermination of viral replication; Cyclin H knock-down; Functional importance of cyclin H; Human cytomegalovirus; Modulation of vCDK/pUL97 activity in vitro; Options for antiviral drug targeting; pUL97-mediated CDK7 trans-stimulation; vCDK/pUL97–cyclin binding; Viral cyclin-dependent kinase (CDK) ortholog

D-2-hydroxyglutarate interferes with HIF-1α stability skewing T-cell metabolism towards oxidative phosphorylation and impairing Th17 polarization - Böttcher, Martin; Renner, Kathrin; Berger, Raffaela; Mentz, Kristin; Thomas, Simone; Cardenas-Conejo, Zugey Elizabeth; Dettmer, Katja; Oefner, Peter J.; Mackensen, Andreas; Kreutz, Marina; Mougiakakos, Dimitrios (OncoImmunology, 2018)
D-2-hydroxyglutarate (D-2HG) is released by various types of malignant cells including acute myeloid leukemia (AML) blasts carrying isocitrate dehydrogenase (IDH) gain-of-function mutations. D-2HG acting as an oncometabolite promotes proliferation, anoikis, and differentiation block of hematopoietic cells in an autocrine fashion. However, prognostic impact of IDH mutations and high D-2HG levels remains controversial and might depend on the overall mutational context. An increasing number of studies focus on the permissive environment created by AML blasts to promote immune evasion. Impact of D-2HG on immune cells remains incompletely understood. Here, we sought out to investigate the effects of D-2HG on T-cells as key mediators of anti-AML immunity. D-2HG was efficiently taken up by T-cells in vitro, which is in line with high 2-HG levels measured in T-cells isolated from AML patients carrying IDH mutations. T-cell activation was slightly impacted by D-2HG. However, D-2HG triggered HIF-1a protein destabilization resulting in metabolic skewing towards oxidative phosphorylation, increased regulatory T-cell (Treg) frequency, and reduced T helper 17 (Th17) polarization. Our data suggest for the first time that D-2HG might contribute to fine tuning of immune responses.
EVALuna2:34274

DC subset–specific induction of T cell responses upon antigen uptake via Fcγ receptors in vivo - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Heger, Lukas; Neubert, Kirsten; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, Simone; Seeling, Michaela; Kießling, Melissa; et al. (Journal of Experimental Medicine, 2017)
Dendritic cells (DCs) are efficient antigen-presenting cells equipped with various cell surface receptors for the direct or indirect recognition of pathogenic microorganisms. Interestingly, not much is known about the specific expression pattern and function of the individual activating and inhibitory Fcγ receptors (FcγRs) on splenic DC subsets in vivo and how they contribute to the initiation of T cell responses. By targeting antigens to select activating and the inhibitory FcγR in vivo, we show that antigen uptake under steady-state conditions results in a short-term expansion of antigen-specific T cells, whereas under inflammatory conditions especially, the activating FcγRIV is able to induce superior CD4+ and CD8+ T cell responses. Of note, this effect was independent of FcγR intrinsic activating signaling pathways. Moreover, despite the expression of FcγRIV on both conventional splenic DC subsets, the induction of CD8+ T cell responses was largely dependent on CD11c+CD8+ DCs, whereas CD11c+CD8− DCs were critical for priming CD4+ T cell responses.<br
Keywords: Infectious disease and host defense; Innate immunity and inflammation; Tolerance

Deficiency of the Intramembrane Protease SPPL2a Alters Antimycobacterial Cytokine Responses of Dendritic Cells - Gradtke, Ann-Christine; Mentrup, Torben; Lehmann, Christian; Cabrera-Cabrera, Florencia; Desel, Christine; Okakpu, Darian; Assmann, Maike; Dalpke, Alexander; Schaible, Ulrich E.; Dudziak, Diana; Schroder, Bernd (Journal of Immunology, 2021)
Signal peptide peptidase-like 2a (SPPL2a) is an aspartyl intramembrane protease essential for degradation of the invariant chain CD74. In humans, absence of SPPL2a leads to Mendelian susceptibility to mycobacterial disease, which is attributed to a loss of the dendritic cell (DC) subset conventional DC2. In this study, we confirm depletion of conventional DC2 in lymphatic tissues of SPPL2a(-/-) mice and demonstrate dependence on CD74 using SPPL2a(-/-) CD74(-1-) mice. Upon contact with mycobacteria, SPPL2a(-/-) bone marrow-derived DCs show enhanced secretion of IL-1 beta, whereas production of IL-10 and IFN-beta is reduced. These effects correlated with modulated responses upon selective stimulation of the pattern recognition receptors TLR4 and Dectin-1. In SPPL2a(-/-) bone marrow-derived DCs, Dectin-1 is redistributed to endosomal compartments. Thus, SPPL2a deficiency alters pattern recognition receptor pathways in a CD74-dependent way, shifting the balance from anti- to proinflammatory cytokines in antimycobacterial responses. We propose that in addition to the DC reduction, this altered DC functionality contributes to Mendelian susceptibility to mycobacterial disease upon SPPL2a deficiency.
CRIS-Team WoS Importer:2021-01-15

De Novo Variants in the F-Box Protein FBXO11 in 20 Individuals with a Variable Neurodevelopmental Disorder - Gregor, Anne; Sadleir, Lynette G.; Asadollahi, Reza; Azzarello-Burri, Silvia; Battaglia, Agatino; Ousager, Lilian Bomme; Boonsawat, Paranchai; Bruel, Ange-Line; Buchert, Rebecca; Calpena, Eduardo; Cogne, Benjamin; Dallapiccola, Bruno; et al. (American Journal of Human Genetics, 2018)
Next-generation sequencing combined with international data sharing has enormously facilitated identification of new disease-associated genes and mutations. This is particularly true for genetically extremely heterogeneous entities such as neurodevelopmental disorders (NDDs). Through exome sequencing and world-wide collaborations, we identified and assembled 20 individuals with de novo variants in FBXO11. They present with mild to severe developmental delay associated with a range of features including short (4/20) or tall (2/20) stature, obesity (5/20), microcephaly (4/19) or macrocephaly (2/19), behavioral problems (17/20), seizures (5/20), cleft lip or palate or bifid uvula (3/20), and minor skeletal anomalies. FBXO11 encodes a member of the F-Box protein family, constituting a subunit of an E3-ubiquitin ligase complex. This complex is involved in ubiquitination and proteasomal degradation and thus in controlling critical biological processes by regulating protein turnover. The identified de novo aberrations comprise two large deletions, ten likely gene disrupting variants, and eight missense variants distributed throughout FBXO11. Structural modeling for missense variants located in the CASH or the Zinc-finger UBR domains suggests destabilization of the protein. This, in combination with the observed spectrum and localization of identified variants and the lack of apparent genotype-phenotype correlations, is compatible with loss of function or haploinsufficiency as an underlying mechanism. We implicate de novo missense and likely gene disrupting variants in FBXO11 in a neurodevelopmental disorder with variable intellectual disability and various other features.
EVALuna2:34619

Detection of collagens by multispectral optoacoustic tomography as an imaging biomarker for Duchenne muscular dystrophy - Regensburger, Adrian; Fonteyne, Lina M.; Jüngert, Jörg; Wagner, Anna; Gerhalter, Teresa; Nagel, Armin Michael; Heiß, Rafael; Flenkenthaler, Florian; Qurashi, Matthias; Neurath, Markus; Klymiuk, Nikolai; Kemter, Elisabeth; et al. (Nature Medicine, 2019)
Biomarkers for monitoring of disease progression and response to therapy are lacking for muscle diseases such as Duchenne muscular dystrophy. Noninvasive in vivo molecular imaging with multispectral optoacoustic tomography (MSOT) uses pulsed laser light to induce acoustic pressure waves, enabling the visualization of endogenous chromophores. Here we describe an application of MSOT, in which illumination in the near- and extended near-infrared ranges from 680–1,100 nm enables the visualization and quantification of collagen content. We first demonstrated the feasibility of this approach to noninvasive quantification of tissue fibrosis in longitudinal studies in a large-animal Duchenne muscular dystrophy model in pigs, and then applied this approach to pediatric patients. MSOT-derived collagen content measurements in skeletal muscle were highly correlated to the functional status of the patients and provided additional information on molecular features as compared to magnetic resonance imaging. This study highlights the potential of MSOT imaging as a noninvasive, age-independent biomarker for the implementation and monitoring of newly developed therapies in muscular diseases.
CRIS-Team Scopus Importer:2019-12-17

Detection radius of EMG for fasciculations: Empiric study combining ultrasonography and electromyography. - Regensburger, Martin; Tenner, Felix; Möbius, Cornelia; Schramm, A (Clinical Neurophysiology, 2017)
OBJECTIVE The aims of this study were to investigate the detection radius and sensitivity of EMG for fasciculations. METHODS Muscle ultrasonography was performed simultaneously to EMG recordings in patients with fasciculations in the context of amyotrophic lateral sclerosis. Ultrasonography and EMG parameters were analyzed for selected fasciculations. RESULTS A total of 381 fasciculations were detected by ultrasonography in 18 muscles of 10 patients. Out of these, 125 (33%) were EMG-negative. In contrast, none of the fasciculations detected by EMG were ultrasonography-negative. EMG detection probability decreased significantly with increasing distance from the center of the fasciculation. EMG detection rate was 98% when the EMG needle was located within the fasciculation and 50% at 7.75 mm distance from the fasciculation center. In addition, EMG detection depended significantly on cross-sectional area of the fasciculation and presence of neurogenic changes. CONCLUSIONS For detecting the same fasciculations, EMG is less sensitive than ultrasonography. EMG detection probability decreases sharply at a distance comparable to motor unit size. SIGNIFICANCE These results extend previous knowledge about superior sensitivity of ultrasonography for fasciculations. Moreover, our novel bimodal detection method provides first in vivo data about the EMG detection radius for fasciculations in a clinical setting.

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

Differential activity of transcription factor Sox9 in early and adult oligodendroglial progenitor cells - Hassel, Lisa; Fröb, Franziska; Küspert, Melanie; Hillgärtner, Simone; Arnold, Philipp; Huang, Wenhui; Kirchhoff, Frank; Wegner, Michael (Glia, 2023)
The high-mobility-group domain-containing transcription factor Sox9 confers glial competence to neuroepithelial precursors in the developing central nervous system and is an important determinant of astroglial and oligodendroglial specification. In oligodendroglial cells, it remains expressed in oligodendrocyte progenitor cells (OPCs) of the developing nervous system, but is shut off in differentiating oligodendrocytes as well as in OPCs that persist in the adult nervous system. To better understand the role of Sox9 in OPCs, we generated mouse models that allowed oligodendroglial expression of a Sox9 transgene during development or in the adult. With transgene expression beginning in the last trimester of pregnancy, the number of OPCs increased dramatically, followed by comparable gains in the number of pre-myelinating and myelinating oligodendrocytes as assessed by marker gene expression. This argues that Sox9 boosts oligodendrogenesis during ontogenetic development at all stages, including terminal oligodendrocyte differentiation. When Sox9 transgene expression started in the adult, many transgene-expressing OPCs failed to maintain their progenitor cell identity and instead converted into myelinating oligodendrocytes. As infrequent and inefficient differentiation of adult OPCs is one of the main obstacles to effective remyelination in demyelinating diseases such as Multiple Sclerosis, increased Sox9 levels in adult OPCs may substantially increase their remyelination capacity.
CRIS-Team Scopus Importer:2023-04-21
Keywords: glia; HMG; myelin; oligodendrocyte; Sox; Sry

Differential contribution of pyramidal cells and interneurons to activity-dependent gene transcription changes - Salar, Seda; Guhathakurta, Debarpan; Marx Hofmann, Lena (Journal of Neurophysiology, 2019)
The type of neuronal activity determines the outcome of gene expression. Hence, the characterization of underlying mechanisms in transcriptome alterations may serve as a biomarker and provide new intervention methods for the treatment of pathologic conditions. Parrish et al. (Parrish RR, Codadu NK, Racca C, Trevelyan AJ. J Neurophysiol 120: 2358-2367, 2018) show that the changes in interneuronal gene transcription are correlated with the type of the activated neuronal population and that the initiation route of Ras/ERK MAPK pathway determines the polarity of the gene expression.
CRIS-Team Scopus Importer:2019-12-10
Keywords: 0 Mg2+; 4AP; activity-dependent gene expression; Gad1; Pvalb

Differential Effects of Ontamalimab Versus Vedolizumab on Immune Cell Trafficking in Intestinal Inflammation and Inflammatory Bowel Disease - Schulze, Lisa; Becker, Emily; Dedden, Mark; Liu, Lijuan; Van Passen, Chiara; Mohamed Abdou, Mariam; Müller, Tanja; Wiendl, Maximilian; Ullrich, Karen; Atreya, Imke; Leppkes, Moritz; Ekici, Arif Bülent; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: The anti-MAdCAM-1 antibody ontamalimab demonstrated efficacy in a phase II trial in ulcerative colitis and results of early terminated phase III trials are pending, but its precise mechanisms of action are still unclear. Thus, we explored the mechanisms of action of ontamalimab and compared it to the anti-α4β7 antibody vedolizumab. Methods: We studied MAdCAM-1 expression with RNA sequencing and immunohistochemistry. The mechanisms of action of ontamalimab were assessed with fluorescence microscopy, dynamic adhesion and rolling assays. We performed in vivo cell trafficking studies in mice and compared ontamalimab and vedolizumab surrogate [-s] antibodies in experimental models of colitis and wound healing. We analysed immune cell infiltration under anti-MAdCAM-1 and anti-α4β7 treatment by single-cell transcriptomics and studied compensatory trafficking pathways. Results: MAdCAM-1 expression was increased in active inflammatory bowel disease. Binding of ontamalimab to MAdCAM-1 induced the internalization of the complex. Functionally, ontamalimab blocked T cell adhesion similar to vedolizumab, but also inhibited L-selectin-dependent rolling of innate and adaptive immune cells. Despite conserved mechanisms in mice, the impact of ontamalimab-s and vedolizumab-s on experimental colitis and wound healing was similar. Single-cell RNA sequencing demonstrated enrichment of ontamalimab-s-treated lamina propria cells in specific clusters, and in vitro experiments indicated that redundant adhesion pathways are active in these cells. Conclusions: Ontamalimab has unique and broader mechanisms of action compared to vedolizumab. However, this seems to be compensated for by redundant cell trafficking circuits and leads to similar preclinical efficacy of anti-α4β7 and anti-MAdCAM-1 treatment. These results will be important for the interpretation of pending phase III data.
CRIS-Team Scopus Importer:2023-12-15

Differential vulnerability of adult neurogenic niches to dosage of the neurodevelopmental-disorder linked gene Foxg1 - Schäffner, Iris; Wittmann, Marie-Theres; Vogel, Tanja; Lie, Dieter Chichung (Molecular Psychiatry, 2022)
The transcription factor FOXG1 serves pleiotropic functions in brain development ranging from the regulation of precursor proliferation to the control of cortical circuit formation. Loss-of-function mutations and duplications of FOXG1 are associated with neurodevelopmental disorders in humans illustrating the importance of FOXG1 dosage for brain development. Aberrant FOXG1 dosage has been found to disrupt the balanced activity of glutamatergic and GABAergic neurons, but the underlying mechanisms are not fully understood. We report that FOXG1 is expressed in the main adult neurogenic niches in mice, i.e. the hippocampal dentate gyrus and the subependymal zone/olfactory bulb system, where neurogenesis of glutamatergic and GABAergic neurons persists into adulthood. These niches displayed differential vulnerability to increased FOXG1 dosage: high FOXG1 levels severely compromised survival and glutamatergic dentate granule neuron fate acquisition in the hippocampal neurogenic niche, but left neurogenesis of GABAergic neurons in the subependymal zone/olfactory bulb system unaffected. Comparative transcriptomic analyses revealed a significantly higher expression of the apoptosis-linked nuclear receptor Nr4a1 in FOXG1-overexpressing hippocampal neural precursors. Strikingly, pharmacological interference with NR4A1 function rescued FOXG1-dependent death of hippocampal progenitors. Our results reveal differential vulnerability of neuronal subtypes to increased FOXG1 dosage and suggest that activity of a FOXG1/NR4A1 axis contributes to such subtype-specific response.
CRIS-Team WoS Importer:2022-04-08

Diffusion tensor imaging of the visual pathway in glaucomatous optic nerve atrophy - Engelhorn, Tobias; A. Schmidt, M.; Dörfler, Arnd; Michelson, Georg (Ophthalmologe, 2017)
In Germany more than one million inhabitants suffer from glaucoma, more than 100,000 are threatened with blindness because glaucoma is often diagnosed too late or not at all. Diagnosis and monitoring is usually carried out "only" by examination of the retina and not the whole visual pathway. However, the eye is just "the tip of the iceberg" of the actual visual pathway, which extends through the brain to the visual cortex. The interdisciplinary holistic assessment of the whole visual pathway in glaucoma is of crucial importance because glaucoma is a complex neurodegenerative disease. Subtypes, such as normal tension glaucoma (NTG), seem to originate from primary damage to the intracranial visual pathway with secondary retrograde retinal degeneration. Recent studies including glaucoma patients and healthy controls could show that diffusion tensor imaging with calculation of diffusion coefficients, i.e. fractional anisotropy (FA), mean and radial diffusivity (MD and RD) as markers of axonal integrity, provide the potential to assess the intracranial visual pathway with a high correlation to established ophthalmological examinations. In particular, calculation of FA maps of the visual pathway and accompanying voxel-based approaches, can be integrated into clinical routine. Thus, detection of glaucoma-related intracranial alterations, even in early stages of the disease, as well as differentiation of different glaucoma subtypes, is made possible. Furthermore, the diagnosis of normal tension glaucoma seems to be possible much earlier with these new imaging techniques compared to established ophthalmological work-up. Moreover, holistic imaging provides new insights into the pathophysiology of this form of glaucoma. This review article gives an overview of these novel magnetic resonance imaging techniques for assessment of the visual pathway in glaucomatous optic nerve atrophy and reveals the potential of an interdisciplinary approach.
EVALuna2:21333

Direct delivery of antigens to dendritic cells via antibodies specific for endocytic receptors as a promising strategy for future therapies - Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Dudziak, Diana (Vaccines, 2016)
Dendritic cells (DCs) are the most potent professional antigen presenting cells and are therefore indispensable for the control of immunity. The technique of antibody mediated antigen targeting to DC subsets has been the basis of intense research for more than a decade. Many murine studies have utilized this approach of antigen delivery to various kinds of endocytic receptors of DCs both in vitro and in vivo. Today, it is widely accepted that different DC subsets are important for the induction of select immune responses. Nevertheless, many questions still remain to be answered, such as the actual influence of the targeted receptor on the initiation of the immune response to the delivered antigen. Further efforts to better understand the induction of antigen-specific immune responses will support the transfer of this knowledge into novel treatment strategies for human diseases. In this review, we will discuss the state-of-the-art aspects of the basic principles of antibody mediated antigen targeting approaches. A table will also provide a broad overview of the latest studies using antigen targeting including addressed DC subset, targeted receptors, outcome, and applied coupling techniques.
Created from Fastlane, Scopus look-up
Keywords: Antigen targeting; Antigen targeting antibodies; Cancer; CLR; DC; DCIR; DEC205; Dendritic cell subsets; moDC; Vaccine

Disrupting sensitization of TRPV4 - Mack, Konrad; Fischer, Michael Jochen Marco (Neuroscience, 2017)
TRPV4 ion channels have a broad expression profile and were shown to contribute to enhanced pain sensation in inflammation. Directly blocking TRPV4 might run the risk of interfering with normal physiology, and has prompted to explore the interaction with the scaffolding protein AKAP79, an approach successfully used for TRPV1 channels. HEK293t cells express AKAP79, additional transfection did not sensitize human TRPV4. Application of trypsin facilitated responses to TRPV4 agonist GSK1016790A. Using a specific protease-activated receptor 2 agonist, involvement of an A-kinase anchoring protein in TRPV4 activation was demonstrated by inhibition with AKAP inhibitor peptide Ht31. TRPV4 has substantial sequence similarity to TRPV1 in the range interacting with AKAP79. A synthetic peptide, resembling these amino acids and extended by a positive region for transmembrane uptake, was tested. Sensitization of TRPV4 responses could be reduced after exposure to this 771–781::TAT peptide but not by a scrambled control peptide. This validates the concept of targeting the interaction between TRPV4 and AKAP79 and controlling increased TRPV4 activity.
Created from Fastlane, Scopus look-up
Keywords: AKAP; inflammation; protein–protein interaction; sensitization; TRP channel

Dissecting TSC2-mutated renal and hepatic angiomyolipomas in an individual with ARID1B-associated intellectual disability - Popp, Bernt; Agaimy, Abbas; Kraus, Cornelia; Knaup, Karl; Ekici, Arif Bülent; Uebe, Steffen; Reis, André; Wiesener, Michael; Zweier, Christiane (BMC Cancer, 2019)
Background: Several subunits of the SWI/SNF chromatin remodeling complex are implicated in both cancer and neurodevelopmental disorders (NDD). Though there is no clinical evidence for an increased tumor risk in individuals with NDDs due to germline mutations in most of these genes so far, this has been repeatedly proposed and discussed. A young woman with NDD due to a de novo mutation in ARID1B now presented with a large renal (> 19 cm in diameter) and multiple hepatic angiomyolipomas (AMLs) but no other signs of tuberous sclerosis complex. Methods: We analyzed tumor and healthy tissue samples with exome and panel sequencing. Results: Additionally to the previously known, germline ARID1B variant we identified a post-zygotic truncating TSC2 variant in both renal and hepatic AMLs but not in any of the healthy tissues. We did not detect any further, obvious tumor driver events. The identification of a passenger variant in SIPA1L3 in both AMLs points to a common clonal origin. Metastasis of the renal AML into the liver is unlikely on the basis of discordant histopathological features. Our findings therefore point to very low-grade mosaicism for the TSC2 variant, possibly in a yet unknown mesenchymal precursor cell that expanded clonally during tumor development. A possible contribution of the germline ARID1B variant to the tumorigenesis remains unclear but cannot be excluded given the absence of any other evident tumor drivers in the AMLs. Conclusion: This unique case highlights the blurred line between tumor genetics and post-zygotic events that can complicate exact molecular diagnoses in patients with rare manifestations. It also demonstrates the relevance of multiple disorders in a single individual, the challenges of detecting low-grade mosaicisms, and the importance of proper diagnosis for treatment and surveillance.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Angiomyolipoma; ARID1B; Mosaic; Neurodevelopmental disorders; TSC2; Tuberous sclerosis complex

Dissimilar Appearances Are Deceptive-Common microRNAs and Therapeutic Strategies in Liver Cancer and Melanoma - Linck-Paulus, Lisa; Hellerbrand, Claus; Boßerhoff, Anja Katrin; Dietrich, Peter (Cells, 2020)
: In this review, we summarize the current knowledge on miRNAs as therapeutic targets in two cancer types that were frequently described to be driven by miRNAs-melanoma and hepatocellular carcinoma (HCC). By focusing on common microRNAs and associated pathways in these-at first sight-dissimilar cancer types, we aim at revealing similar molecular mechanisms that are evolved in microRNA-biology to drive cancer progression. Thereby, we also want to outlay potential novel therapeutic strategies. After providing a brief introduction to general miRNA biology and basic information about HCC and melanoma, this review depicts prominent examples of potent oncomiRs and tumor-suppressor miRNAs, which have been proven to drive diverse cancer types including melanoma and HCC. To develop and apply miRNA-based therapeutics for cancer treatment in the future, it is essential to understand how miRNA dysregulation evolves during malignant transformation. Therefore, we highlight important aspects such as genetic alterations, miRNA editing and transcriptional regulation based on concrete examples. Furthermore, we expand our illustration by focusing on miRNA-associated proteins as well as other regulators of miRNAs which could also provide therapeutic targets. Finally, design and delivery strategies of miRNA-associated therapeutic agents as well as potential drawbacks are discussed to address the question of how miRNAs might contribute to cancer therapy in the future.
EVALuna2:212285

DNA methylation-based classification of malformations of cortical development in the human brain - Jabari, Samir; Kobow, Katja; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Polster, Tilman; Bien, Christian G.; Kalbhenn, Thilo; Simon, Matthias; Hamer, Hajo; Roessler, Karl; Feucht, Martha; et al. (Acta Neuropathologica, 2022)
Malformations of cortical development (MCD) comprise a broad spectrum of structural brain lesions frequently associated with epilepsy. Disease definition and diagnosis remain challenging and are often prone to arbitrary judgment. Molecular classification of histopathological entities may help rationalize the diagnostic process. We present a retrospective, multi-center analysis of genome-wide DNA methylation from human brain specimens obtained from epilepsy surgery using EPIC 850 K BeadChip arrays. A total of 308 samples were included in the study. In the reference cohort, 239 formalin-fixed and paraffin-embedded (FFPE) tissue samples were histopathologically classified as MCD, including 12 major subtype pathologies. They were compared to 15 FFPE samples from surgical non-MCD cortices and 11 FFPE samples from post-mortem non-epilepsy controls. We applied three different statistical approaches to decipher the DNA methylation pattern of histopathological MCD entities, i.e., pairwise comparison, machine learning, and deep learning algorithms. Our deep learning model, which represented a shallow neuronal network, achieved the highest level of accuracy. A test cohort of 43 independent surgical samples from different epilepsy centers was used to test the precision of our DNA methylation-based MCD classifier. All samples from the test cohort were accurately assigned to their disease classes by the algorithm. These data demonstrate DNA methylation-based MCD classification suitability across major histopathological entities amenable to epilepsy surgery and age groups and will help establish an integrated diagnostic classification scheme for epilepsy-associated MCD.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Brain development; Cortical malformation; Deep learning; Epigenetic; Epilepsy

DNMT targets MiRacle torching TORCh - Dietrich, Peter; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2016)
EVALuna2:4735

Domain II of Pseudomonas Exotoxin Is Critical for Efficacy of Bolus Doses in a Xenograft Model of Acute Lymphoblastic Leukemia - Müller, Fabian; Cunningham, Tyler; Beers, Richard; Bera, Tapan K.; Wayne, Alan S.; Pastan, Ira (Toxins, 2018)
Moxetumomab pasudotox is a fusion protein of a CD22-targeting antibody and Pseudomonas exotoxin. Minutes of exposure to Moxetumomab achieves similar cell killing than hours of exposure to a novel deimmunized variant against some acute lymphoblastic leukemia (ALL). Because blood levels fall quickly, Moxetumomab is more than 1000-fold more active than the deimmunized variant in vivo. We aimed to identify which part of Moxetumomab increases in vivo efficacy and generated five immunotoxins, tested time-dependent activity, and determined the efficacy in a KOPN-8 xenograft model. Full domain II shortened the time cells had to be exposed to die to only a few minutes for some ALL; deimmunized domain III consistently extended the time. Against KOPN-8, full domain II accelerated time to arrest protein synthesis by three-fold and tripled PARP-cleavage. In vivo efficacy was increased by more than 10-fold by domain II and increasing size, and therefore half-life enhanced efficacy two- to four-fold. In summary, in vivo efficacy is determined by the time cells have to be exposed to immunotoxin to die and serum half-life. Thus, domain II is most critical for activity against some ALL treated with bolus doses; however, immunotoxins lacking all but the furin-cleavage site of domain II may be advantageous when treating continuously.
EVALuna2:34276

Druggable transcriptomic pathways revealed in Parkinson’s patient-derived midbrain neurons - van den Hurk, Mark; Lau, Shong; Marchetto, Maria C.; Mertens, Jerome; Stern, Shani; Corti, Olga; Brice, Alexis; Winner, Beate; Winkler, Jürgen; Gage, Fred H.; Bardy, Cedric (npj Parkinson’s Disease, 2022)
Complex genetic predispositions accelerate the chronic degeneration of midbrain substantia nigra neurons in Parkinson’s disease (PD). Deciphering the human molecular makeup of PD pathophysiology can guide the discovery of therapeutics to slow the disease progression. However, insights from human postmortem brain studies only portray the latter stages of PD, and there is a lack of data surrounding molecular events preceding the neuronal loss in patients. We address this gap by identifying the gene dysregulation of live midbrain neurons reprogrammed in vitro from the skin cells of 42 individuals, including sporadic and familial PD patients and matched healthy controls. To minimize bias resulting from neuronal reprogramming and RNA-seq methods, we developed an analysis pipeline integrating PD transcriptomes from different RNA-seq datasets (unsorted and sorted bulk vs. single-cell and Patch-seq) and reprogramming strategies (induced pluripotency vs. direct conversion). This PD cohort’s transcriptome is enriched for human genes associated with known clinical phenotypes of PD, regulation of locomotion, bradykinesia and rigidity. Dysregulated gene expression emerges strongest in pathways underlying synaptic transmission, metabolism, intracellular trafficking, neural morphogenesis and cellular stress/immune responses. We confirmed a synaptic impairment with patch-clamping and identified pesticides and endoplasmic reticulum stressors as the most significant gene-chemical interactions in PD. Subsequently, we associated the PD transcriptomic profile with candidate pharmaceuticals in a large database and a registry of current clinical trials. This study highlights human transcriptomic pathways that can be targeted therapeutically before the irreversible neuronal loss. Furthermore, it demonstrates the preclinical relevance of unbiased large transcriptomic assays of reprogrammed patient neurons.
CRIS-Team Scopus Importer:2022-10-28

Dual ontogeny of disease-associated microglia and disease inflammatory macrophages in aging and neurodegeneration - Silvin, Aymeric; Uderhardt, Stefan; Piot, Cecile; Da Mesquita, Sandro; Yang, Katharine; Geirsdottir, Laufey; Mulder, Kevin; Eyal, David; Liu, Zhaoyuan; Bridlance, Cecile; Thion, Morgane Sonia; Zhang, Xiao Meng; et al. (Immunity, 2022)
Brain macrophage populations include parenchymal microglia, border-associated macrophages, and recruited monocyte-derived cells; together, they control brain development and homeostasis but are also implicated in aging pathogenesis and neurodegeneration. The phenotypes, localization, and functions of each population in different contexts have yet to be resolved. We generated a murine brain myeloid scRNA-seq integration to systematically delineate brain macrophage populations. We show that the previously identified disease-associated microglia (DAM) population detected in murine Alzheimer's disease models actually comprises two ontogenetically and functionally distinct cell lineages: embryonically derived triggering receptor expressed on myeloid cells 2 (TREM2)-dependent DAM expressing a neuroprotective signature and monocyte-derived TREM2-expressing disease inflammatory macrophages (DIMs) accumulating in the brain during aging. These two distinct populations appear to also be conserved in the human brain. Herein, we generate an ontogeny-resolved model of brain myeloid cell heterogeneity in development, homeostasis, and disease and identify cellular targets for the treatment of neurodegeneration.
CRIS-Team Scopus Importer:2022-09-02
Keywords: aging; Alzheimer's disease; disease inflammatory macrophages; disease-associated microglia; macrophage; microglia; neurodegeneration

Dual Specificity Phosphatases: From Molecular Mechanisms to Biological Function - Pulido, Rafael; Lang, Roland (International Journal of Molecular Sciences, 2019)
Dual specificity phosphatases (DUSPs) constitute a heterogeneous group of enzymes, relevant in human disease, which belong to the class I Cys-based group of protein tyrosine phosphatase (PTP) gene superfamily [...].
CRIS-Team Scopus Importer:2019-09-20

Dual-Specificity Phosphatases in Immunity and Infection: An Update - Lang, Roland; Raffi, Faizal A.M. (International Journal of Molecular Sciences, 2019)
Kinase activation and phosphorylation cascades are key to initiate immune cell activation in response to recognition of antigen and sensing of microbial danger. However, for balanced and controlled immune responses, the intensity and duration of phospho-signaling has to be regulated. The dual-specificity phosphatase (DUSP) gene family has many members that are differentially expressed in resting and activated immune cells. Here, we review the progress made in the field of DUSP gene function in regulation of the immune system during the last decade. Studies in knockout mice have confirmed the essential functions of several DUSP-MAPK phosphatases (DUSP-MKP) in controlling inflammatory and anti-microbial immune responses and support the concept that individual DUSP-MKP shape and determine the outcome of innate immune responses due to context-dependent expression and selective inhibition of different mitogen-activated protein kinases (MAPK). In addition to the canonical DUSP-MKP, several small-size atypical DUSP proteins regulate immune cells and are therefore also reviewed here. Unexpected and complex findings in DUSP knockout mice pose new questions regarding cell type-specific and redundant functions. Another emerging question concerns the interaction of DUSP-MKP with non-MAPK binding partners and substrate proteins. Finally, the pharmacological targeting of DUSPs is desirable to modulate immune and inflammatory responses.
CRIS-Team Scopus Importer:2019-06-21
Keywords: atypical DUSP; cytokines; inflammation; macrophage; MAPK phosphatase; T cell

Dynamic Adhesion Assay for the Functional Analysis of Anti-adhesion Therapies in Inflammatory Bowel Disease - Becker, Elisabeth; Schramm, Simon; Binder, Marie-Theres; Allner, Clarissa; Wiendl, Maximilian; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Journal of Visualized Experiments, 2018)
Gut homing of immune cells is important for the pathogenesis of inflammatory bowel diseases (IBD). Integrin-dependent cell adhesion to addressins is a crucial step in this process and therapeutic strategies interfering with adhesion have been successfully established. The anti-α4β7 integrin antibody, vedolizumab, is used for the clinical treatment of Crohn's disease (CD) and ulcerative colitis (UC) and further compounds are likely to follow. The details of the adhesion procedure and the action mechanisms of anti-integrin antibodies are still unclear in many regards due to the limited available techniques for the functional research in this field. Here, we present a dynamic adhesion assay for the functional analysis of human cell adhesion under flow conditions and the impact of anti-integrin therapies in the context of IBD. It is based on the perfusion of primary human cells through addressin-coated ultrathin glass capillaries with real-time microscopic analysis. The assay offers a variety of opportunities for refinements and modifications and holds potentials for mechanistic discoveries and translational applications.
EVALuna2:207768

Dynamic footprint based locomotion sway assessment in α-synucleinopathic mice using Fast Fourier Transform and Low Pass Filter - Timotius, Ivanna; Canneva, Fabio; Minakaki, Georgia; Pasluosta, Cristian Federico; Moceri, Sandra; Casadei, Nicolas; Riess, Olaf; Winkler, Jürgen; Klucken, Jochen; von Hörsten, Stephan; Eskofier, Björn (Journal of Neuroscience Methods, 2018)
Background Sway is a crucial gait characteristic tightly correlated with the risk of falling in patients with Parkinson´s disease (PD). So far, the swaying pattern during locomotion has not been investigated in rodent models using the analysis of dynamic footprint recording obtained from the CatWalk gait recording and analysis system. New Methods We present three methods for describing locomotion sway and apply them to footprint recordings taken from C57BL6/N wild-type mice and two different α-synuclein transgenic PD-relevant mouse models (α-synm-ko, α-synm-koxα-synh-tg). Individual locomotion data were subjected to three different signal processing analytical approaches: the first two methods are based on Fast Fourier Transform (FFT), while the third method uses Low Pass Filters (LPF). These methods use the information associated with the locomotion sway and generate sway-related parameters. Results The three proposed methods were successfully applied to the footprint recordings taken from all paws as well as from front/hind-paws separately. Nine resulting sway-related parameters were generated and successfully applied to differentiate between the mouse models under study. Namely, α-synucleinopathic mice revealed higher sway and sway itself was significantly higher in the α-synm-koxα-synh-tg mice compared to their wild-type littermates in eight of the nine sway-related parameters. Comparison with Existing Method Previous locomotion sway index computation is based on the estimated center of mass position of mice. Conclusions The methods presented in this study provide a sway-related gait characterization. Their application is straightforward and may lead to the identification of gait pattern derived biomarkers in rodent models of P
EVALuna2:32788
Keywords: Locomotion; sway; gait analysis; CatWalk system; Parkinson's disease; alpha-synuclein transgenic

Dynamic imaging of iel-iec co-cultures allows for quantification of cd103-dependent t cell migration - Enderle, Karin; Dinkel, Martin; Spath, Eva-Maria; Schmid, Benjamin; Zundler, Sebastian; Tripal, Philipp; Neurath, Markus; Hildner, Kai; Neufert, Clemens (International Journal of Molecular Sciences, 2021)
Intraepithelial lymphocytes (IEL) are widely distributed within the small intestinal epithelial cell (IEC) layer and represent one of the largest T cell pools of the body. While implicated in the pathogenesis of intestinal inflammation, detailed insight especially into the cellular cross-talk between IELs and IECs is largely missing in part due to lacking methodologies to monitor this interaction. To overcome this shortcoming, we employed and validated a murine IEL-IEC (organoids) ex vivo co-culture model system. Using livecell imaging we established a protocol to visualize and quantify the spatio-temporal migratory behavior of IELs within organoids over time. Applying this methodology, we found that IELs lacking CD103 (i.e., integrin alpha E, ITGAE) surface expression usually functioning as a retention receptor for IELs through binding to E-cadherin (CD324) expressing IECs displayed aberrant mobility and migration patterns. Specifically, CD103 deficiency affected the ability of IELs to migrate and reduced their speed during crawling within organoids. In summary, we report a new technology to monitor and quantitatively assess especially migratory characteristics of IELs communicating with IEC ex vivo. This approach is hence readily applicable to study the effects of targeted therapeutic interventions on IEL-IEC cross-talk.
CRIS-Team Scopus Importer:2021-05-21
Keywords: CD103; Intestinal organoids; Intraepithelial lymphocytes; Life cell imaging; Lympho-cyte migration

Dysregulated skin barrier function in Tmem79 mutant mice promotes IL-17A-dependent spontaneous skin and lung inflammation - Saunders, Sean P.; Floudas, Achilleas; Moran, Tara; Byrne, Ciara M.; Rooney, Michael D.; Fahy, Caoimhe M.R.; Geoghegan, Joan A.; Iwakura, Yoichiro; Fallon, Padraic G.; Schwartz, Christian (Allergy, 2020)
Background: Atopic dermatitis (AD) is associated with a dysregulation of the skin barrier and may predispose to the development of secondary allergic conditions, such as asthma. Tmem79ma/ma mice harbor a mutation in the gene encoding Transmembrane Protein 79 (or Mattrin), which has previously been associated with AD. As a result of the Tmem79 gene mutation, these mice have a defective skin barrier and develop spontaneous skin inflammation. In this study, Tmem79ma/ma mice were assessed for the underlying immunological response in the development of spontaneous skin and lung inflammation. Methods: Development of spontaneous skin and lung inflammation in Tmem79ma/ma mice was analyzed. We further investigated susceptibility to cutaneous Staphylococcus aureus infection. Tmem79ma/ma were crossed to IL-17A-deficient mice to address the contribution of IL-17A to spontaneous skin and lung disease. Results: Tmem79ma/ma mice developed IL-17A-dependent spontaneous AD-like inflammation and were refractory to S aureus infection. Mutant mice progressed to airway inflammation subsequent to the occurrence of dermatitis. The progression from skin to lung disease is dependent on adaptive immunity and is facilitated by cutaneous expansion of Th17 and TCRγδ T cells. Conclusion: Mice lacking Tmem79/Mattrin expression have a defective skin barrier. In adulthood, these mice develop dermatitis with secondary progression to lung inflammation. The development of skin and lung inflammation is IL-17A-dependent and mediated by TCRγδ T cells.
CRIS-Team Scopus Importer:2020-07-31
Keywords: cutaneous inflammation; interleukin-17A; lung inflammation; skin barrier; Tmem79

Early quantification of anti-CD19 CAR T cells by flow cytometry predicts response in R/R DLBCL - Blumenberg, Viktoria; Busch, Galina; Baumann, Stephan; Jitschin, Regina; Iacoboni, Gloria; Gallur, Laura; Iraola-Truchuelo, Josu; Hoster, Eva; Winkelmann, Michael; Hellwig, Konstantin; Schmidt, Christian; Frölich, Lisa; et al. (Blood Advances, 2023)
CRIS-Team Scopus Importer:2023-12-15

Editorial: Intracellular Mechanisms of α-Synuclein Processing. - Zunke, Friederike; Winner, Beate; Richter, Franziska; Caraveo, Gabriela (Frontiers in Cell and Developmental Biology, 2021)
CRIS-Team Scopus Importer:2021-10-08
Keywords: alpha-synuclein; lysosomes; neurodegeneration; protein misfolding; spread; synucleinopathies

Effect of mucosal adjuvant IL-1β on heterotypic immunity in a pig influenza model - Schmidt, Anna; Paudyal, Basudev; Villanueva-Hernández, Sonia; Mcnee, Adam; Vatzia, Eleni; Carr, Brigid Veronica; Schmidt, Selma; Mccarron, Amy; Martini, Veronica; Schroedel, Silke; Thirion, Christian; Waters, Ryan; et al. (Frontiers in Immunology, 2023)
T cell responses directed against highly conserved viral proteins contribute to the clearance of the influenza virus and confer broadly cross-reactive and protective immune responses against a range of influenza viruses in mice and ferrets. We examined the protective efficacy of mucosal delivery of adenoviral vectors expressing hemagglutinin (HA) and nucleoprotein (NP) from the H1N1 virus against heterologous H3N2 challenge in pigs. We also evaluated the effect of mucosal co-delivery of IL-1β, which significantly increased antibody and T cell responses in inbred Babraham pigs. Another group of outbred pigs was first exposed to pH1N1 as an alternative means of inducing heterosubtypic immunity and were subsequently challenged with H3N2. Although both prior infection and adenoviral vector immunization induced strong T-cell responses against the conserved NP protein, none of the treatment groups demonstrated increased protection against the heterologous H3N2 challenge. Ad-HA/NP+Ad-IL-1β immunization increased lung pathology, although viral load was unchanged. These data indicate that heterotypic immunity may be difficult to achieve in pigs and the immunological mechanisms may differ from those in small animal models. Caution should be applied in extrapolating from a single model to humans.
CRIS-Team Scopus Importer:2023-05-19
Keywords: heterotypic protection; IL-1β; influenza virus; lung-resident memory T-cells; mucosal immunity; pig; porcine B cells; porcine T-cells

Effects of the STAMP-inhibitor asciminib on T cell activation and metabolic fitness compared to tyrosine kinase inhibition by imatinib, dasatinib, and nilotinib - Häselbarth, Lukas; Karow, Axel; Mentz, Kristin; Böttcher, Martin; Roche-Lancaster, Oisin; Krumbholz, Manuela; Jitschin, Regina; Mougiakakos, Dimitrios; Metzler, Markus (Cancer Immunology, Immunotherapy, 2023)
T cell function is central to immune reconstitution and control of residual chronic myeloid leukemia (CML) cells after treatment initiation and is associated with achieving deep molecular response as a prerequisite for treatment-free remission, the ultimate therapeutic goal in CML. ATP-pocket-binding tyrosine kinase inhibitors (TKIs) like imatinib, dasatinib, and nilotinib are widely used for treating CML, but they have shown to inhibit T cell function as an “off-target” effect. Therefore, we tested asciminib, the first-in-class BCR::ABL1 fusion protein inhibitor specifically targeting the ABL myristoyl pocket (STAMP) and compared its effects on T cell function with imatinib, dasatinib, and nilotinib. Whereas all four TKIs inhibited the expression of the co-stimulatory protein CD28, the amino acid transporter CD98, proliferation, and secretion of pro-inflammatory cytokines IFNγ, IL-6, and IL-17A upon T cell stimulation, asciminib had less impact on PD-1, activation markers, and IL-2 secretion. T cells treated with asciminib and the other TKIs maintained their ability to mobilize their respiratory capacity and glycolytic reserve, which is an important surrogate for metabolic fitness and flexibility. Overall, we found milder inhibitory effects of asciminib on T cell activation, which might be beneficial for the immunological control of residual CML cells.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Activity; Asciminib; CML; Metabolism; T cell; TKI

Eight further individuals with intellectual disability and epilepsy carrying bi-allelic CNTNAP2 aberrations allow delineation of the mutational and phenotypic spectrum - Smogavec, Mateja; Cleall, Alison; Hoyer, Juliane; Lederer, Damien; Nassogne, Marie-Cecile; Palmer, Elizabeth E.; Deprez, Marie; Benoit, Valerie; Maystadt, Isabelle; Noakes, Charlotte; Leal-Esquivel, Alejandro; Shaw, Marie; et al. (Journal of Medical Genetics, 2016)
Heterozygous copy number variants (CNVs) or sequence variants in the contactin-associated protein 2 gene CNTNAP2 have been discussed as risk factors for a wide spectrum of neurodevelopmental and neuropsychiatric disorders. Bi-allelic aberrations in this gene are causative for an autosomal-recessive disorder with epilepsy, severe intellectual disability (ID) and cortical dysplasia (CDFES). As the number of reported individuals is still limited, we aimed at a further characterisation of the full mutational and clinical spectrum.Targeted sequencing, chromosomal microarray analysis or multigene panel sequencing was performed in individuals with severe ID and epilepsy.We identified homozygous mutations, compound heterozygous CNVs or CNVs and mutations in CNTNAP2 in eight individuals from six unrelated families. All aberrations were inherited from healthy, heterozygous parents and are predicted to be deleterious for protein function. Epilepsy occurred in all affected individuals with onset in the first 3.5 years of life. Further common aspects were ID (severe in 6/8), regression of speech development (5/8) and behavioural anomalies (7/8). Interestingly, cognitive impairment in one of two affected brothers was, in comparison, relatively mild with good speech and simple writing abilities. Cortical dysplasia that was previously reported in CDFES was not present in MRIs of six individuals and only suspected in one.By identifying novel homozygous or compound heterozygous, deleterious CNVs and mutations in eight individuals from six unrelated families with moderate-to-severe ID, early onset epilepsy and behavioural anomalies, we considerably broaden the mutational and clinical spectrum associated with bi-allelic aberrations in CNTNAP2.
EVALuna2:9347

Elevated levels of Bcl-3 inhibits Treg development and function resulting in spontaneous colitis - Reissig, Sonja; Tang, Yilang; Nikolaev, Alexei; Gerlach, Katharina; Wolf, Christine; Davari, Kathrin; Gallus, Christian; Masri, Joumana; Mufazalov, Ilgiz A.; Neurath, Markus; Wunderlich, F. Thomas; Schattenberg, Joern M.; et al. (Nature Communications, 2017)
Bcl-3 is an atypical NF-κB family member that regulates NF-κB-dependent gene expression in effector T cells, but a cell-intrinsic function in regulatory T (Treg) cells and colitis is not clear. Here we show that Bcl-3 expression levels in colonic T cells correlate with disease manifestation in patients with inflammatory bowel disease. Mice with T-cell-specific overexpression of Bcl-3 develop severe colitis that can be attributed to defective Treg cell development and function, leading to the infiltration of immune cells such as pro-inflammatory γδT cells, but not αβ T cells. In Treg cells, Bcl-3 associates directly with NF-κB p50 to inhibit DNA binding of p50/p50 and p50/p65 NF-κB dimers, thereby regulating NF-κB-mediated gene expression. This study thus reveals intrinsic functions of Bcl-3 in Treg cells, identifies Bcl-3 as a potential prognostic marker for colitis and illustrates the mechanism by which Bcl-3 regulates NF-κB activity in Tregs to prevent colitis.
EVALuna2:33818

Endogenous Opioid Levels Do Not Correlate With Itch Intensity and Therapeutic Interventions in Hepatic Pruritus - Düll, Miriam; Wolf, Katharina; Vetter, Marcel; Dietrich, Peter; Neurath, Markus; Kremer, Andreas (Frontiers in Medicine, 2021)
Background: Chronic pruritus affects up to 70% of patients with immune-mediated hepatobiliary disorders. Antagonists of the μ-opioid receptor (MOR) and agonists of the κ-opioid receptor (KOR) are used to treat hepatic itch, albeit with limited success. An imbalance between ligands of MOR and KOR receptors has recently been suggested as a potential mechanism of hepatic pruritus. In this study, we therefore investigated systemic levels of important endogenous opioids such as β-endorphin, dynorphin A, Leu- and Met-enkephalin in plasma of a large cohort of well-characterized patients with immune-mediated cholestatic disorders, including patients with liver cirrhosis, and during effective anti-pruritic therapy. Methods: Plasma samples and clinical data were prospectively collected from well-characterized patients with primary/secondary sclerosing cholangitis (PSC/SSC), primary biliary cholangitis (PBC) and overlap syndromes suffering from pruritus (n = 29) and age-, gender- and disease-matched controls without pruritus (n = 27) as well as healthy controls (n = 20). General laboratory testing for hepatobiliary and renal function was performed. Levels of β-endorphin, dynorphin A, Leu- and Met-enkephalin were quantified in plasma by ELISA. Intensity of pruritus over the last week was evaluated using a visual analog scale (VAS, 0–10). Results: PBC and PSC patients with or without pruritus did neither differ in disease entity, disease stage, nor in the presence of cirrhosis. While both dynorphin A and β-endorphin concentrations were lower in pruritic patients compared to those without pruritus and healthy controls, the MOR/KOR ligand ratio was unaltered. No significant differences were observed for Leu- and Met-enkephalin concentrations. Opioid levels correlated with neither itch intensity nor stage of disease. Cirrhotic patients displayed higher concentrations of MOR agonist Leu-enkephalin and KOR agonist dynorphin A. Endogenous opioid levels remained largely unchanged after successful treatment with the potent anti-pruritic drugs rifampicin and bezafibrate. Conclusions: Endogenous opioid levels and the MOR/KOR ligand ratio neither correlate with itch intensity nor differentiate pruritic from non-pruritic patients with immune-mediated liver diseases. Thus, endogenous opioids may modulate signaling pathways involved in hepatic pruritus, but are unlikely to represent the major pruritogens in liver disease.
CRIS-Team Scopus Importer:2021-05-14
Keywords: bezafibrate; cholestasis; dynorphin; endorphin; enkephalin; liver; rifampicin; therapy

Engrailed 1 coordinates cytoskeletal reorganization to induce myofibroblast differentiation - Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Fuchs, Maximilian; Liang, Chunguang; Rigau, Aleix; Hong, Xuezhi; Zhu, Honglin; Luber, Markus; Bergmann, Christina; Dees, Clara; Ludolph, Ingo; Horch, Raymund E.; et al. (Journal of Experimental Medicine, 2021)
Transforming growth factor-β (TGFβ) is a key mediator of fibroblast activation in fibrotic diseases, including systemic sclerosis. Here we show that Engrailed 1 (EN1) is reexpressed in multiple fibroblast subpopulations in the skin of SSc patients. We characterize EN1 as a molecular amplifier of TGFβ signaling in myofibroblast differentiation: TGFβ induces EN1 expression in a SMAD3-dependent manner, and in turn, EN1 mediates the profibrotic effects of TGFβ. RNA sequencing demonstrates that EN1 induces a profibrotic gene expression profile functionally related to cytoskeleton organization and ROCK activation. EN1 regulates gene expression by modulating the activity of SP1 and other SP transcription factors, as confirmed by ChIP-seq experiments for EN1 and SP1. Functional experiments confirm the coordinating role of EN1 on ROCK activity and the reorganization of cytoskeleton during myofibroblast differentiation, in both standard fibroblast culture systems and in vitro skin models. Consistently, mice with fibroblast-specific knockout of En1 demonstrate impaired fibroblast-to-myofibroblast transition and are partially protected from experimental skin fibrosis.
CRIS-Team Scopus Importer:2021-07-30

Engulfment of mast cell secretory granules on skin inflammation boosts dendritic cell migration and priming efficiency - Dudeck, Jan; Froebel, Julia; Kotrba, Johanna; Lehmann, Christian; Dudziak, Diana; Speier, Stephan; Nedospasov, Sergei A.; Schraven, Burkhart; Dudeck, Anne (Journal of Allergy and Clinical Immunology, 2019)
Background: Mast cells (MCs)are best known as key effector cells of allergic reactions, but they also play an important role in host defense against pathogens. Despite increasing evidence for a critical effect of MCs on adaptive immunity, the underlying mechanisms are poorly understood. Objective: Here we monitored MC intercellular communication with dendritic cells (DCs), MC activation, and degranulation and tracked the fate of exocytosed mast cell granules (MCGs)during skin inflammation. Methods: Using a strategy to stain intracellular MCGs in vivo, we tracked the MCG fate after skin inflammation–induced MC degranulation. Furthermore, exogenous MCGs were applied to MC-deficient mice by means of intradermal injection. MCG effects on DC functionality and adaptive immune responses in vivo were assessed by combining intravital multiphoton microscopy with flow cytometry and functional assays. Results: We demonstrate that dermal DCs engulf the intact granules exocytosed by MCs on skin inflammation. Subsequently, the engulfed MCGs are actively shuttled to skin-draining lymph nodes and finally degraded inside DCs within the lymphoid tissue. Most importantly, MCG uptake promotes DC maturation and migration to skin-draining lymph nodes, partially through MC-derived TNF, and boosts their T-cell priming efficiency. Surprisingly, exogenous MCGs alone are sufficient to induce a prominent DC activation and T-cell response. Conclusion: Our study highlights a unique feature of peripheral MCs to affect lymphoid tissue–borne adaptive immunity over distance by modifying DC functionality through delivery of granule-stored mediators.
CRIS-Team Scopus Importer:2019-05-03
Keywords: adaptive immune response; dendritic cells; Mast cells; skin inflammation; T-cell response

Environmental Microbial Factors Determine the Pattern of Inflammatory Lesions in a Murine Model of Crohn's Disease-Like Inflammation - Stolzer, Iris; Kaden-Volynets, Valentina; Ruder, Barbara; Letizia, Marilena; Bittel, Miriam; Rausch, Philipp; Basic, Marijana; Bleich, André; Baines, John F.; Neurath, Markus; Wirtz, Stefan; Weidinger, Carl; et al. (Inflammatory Bowel Diseases, 2019)
Crohn's disease (CD) patients can be grouped into patients suffering from ileitis, ileocolitis, jejunoileitis, and colitis. The pathophysiological mechanism underlying this regional inflammation is still unknown. Although most murine models of inflammatory bowel disease (IBD) develop inflammation in the colon, there is an unmet need for novel models that recapitulate the spontaneous and fluctuating nature of inflammation as seen in CD. Recently, mice with an intestinal epithelial cell-specific deletion for Caspase-8 (Casp8ΔIEC mice), which are characterized by cell death-driven ileitis and disrupted Paneth cell homeostasis, have been identified as a novel model of CD-like ileitis. Here we uncovered that genetic susceptibility alone is sufficient to drive ileitis in Casp8ΔIEC mice. In sharp contrast, environmental factors, such as a disease-relevant microbial flora, determine colonic inflammation. Accordingly, depending on the microbial environment, isogenic Casp8ΔIEC mice either exclusively developed ileitis or suffered from pathologies in several parts of the gastrointestinal tract. Colitis in these mice was characterized by massive epithelial cell death, leading to spread of commensal gut microbes to the extra-intestinal space and hence an aberrant activation of the systemic immunity. We further uncovered that Casp8ΔIEC mice show qualitative and quantitative changes in the intestinal microbiome associated with an altered mucosal and systemic immune response. In summary, we identified that inflammation in this murine model of CD-like inflammation is characterized by an immune reaction, presumably directed against a disease-relevant microbiota in a genetically susceptible host, with impaired mucosal barrier function and bacterial clearance at the epithelial interface.
Keywords: Crohn’s disease; Paneth cells; cell death; colitis; ileitis; microflora

Eosinophils are not essential for maintenance of murine plasma cells in the bone marrow - Haberland, Konrad; Ackermann, Jochen A.; Ipseiz, Natacha; Culemann, Stephan; Pracht, Katharina; Englbrecht, Matthias; Jäck, Hans-Martin; Schett, Georg; Schuh, Wolfgang; Krönke, Gerhard (European Journal of Immunology, 2018)
Eosinophils were reported to serve as an essential component of the plasma cell niche within the bone marrow. As the potential contribution of eosinophils to humoral immunity has remained incompletely understood, we aimed to further characterize their role during antibody responses and to additionally investigate their role in autoimmune disease. Contrary to our expectations and the currently prevailing paradigm, we found that eosinophils are fully dispensable for the survival of murine bone marrow plasma cells and accordingly do not contribute to antibody production and autoantibody-mediated disease. Littermate wild type and eosinophil-deficient ΔdblGATA-1 animals showed similar numbers and frequencies of plasma cells and did not differ in steady state levels of immunoglobulins or their ability to raise antigen-specific antibody responses. Eosinophils were likewise dispensable for autoantibody production or autoantibody-induced disease in a mouse model of systemic lupus erythematosus. Our findings thus argue against a role of eosinophils during the maintenance of the plasma cell pool and challenge the hitherto postulated concept of an eosinophil-sustained bone marrow niche.
EVALuna2:34472

Epithelial HIF2 alpha expression induces intestinal barrier dysfunction and exacerbation of arthritis - Wen, Jinming; Lyu, Pang; Stolzer, Iris; Xu, Jin; Gießl, Andreas; Lin, Zhen; Andreev, Darja; Kachler, Katerina; Song, Rui; Meng, Xianyi; Cao, Shan; Guggino, Giuliana; et al. (Annals of the Rheumatic Diseases, 2022)
To investigate how the mucosal barrier in the intestine influences the development of arthritis, considering that metabolic changes in the intestinal epithelium influence its barrier function. Intestinal HIF2α expression peaked at onset of experimental arthritis and RA. Conditionally, deletion of HIF2α in gut epithelial cells inhibited arthritis and was associated with improved intestinal barrier function and less intestinal and lymphatic Th1 and Th17 activation. Mechanistically, HIF2α induced the transcription of the pore-forming claudin (CLDN)-15, which inhibits intestinal barrier integrity. Furthermore, treatment with HIF2α inhibitor decreased claudin-15 expression in epithelial cells and inhibited arthritis and littermate control mice. The gut intestinal HIF2α target genes were delineated by chromatin immunoprecipitation and luciferase experiments. Furthermore, pharmacological HIF2α inhibitor PT2977 was used for inhibition of arthritis. These findings show that the HIF2α-CLDN15 axis is critical for the breakdown of intestinal barrier function at onset of arthritis, highlighting the functional link between intestinal homeostasis and arthritis.
CRIS-Team WoS Importer:2022-07-01
Keywords: Arthritis; Arthritis; Experimental; Inflammation.

Epithelial presenilin-1 drives colorectal tumour growth by controlling EGFR-COX2 signalling - Gámez Belmonte, Maria de los Reyes; Mahapatro, Mousumi; Erkert, Lena; Gonzalez Acera, Miguel; Naschberger, Elisabeth; Yu, Yuqiang; Tena-Garitaonaindia, Mireia; Patankar, Jay; Wagner, Yara; Podstawa, Eva; Schoedel, Lena; Bubeck, Marvin; et al. (Gut, 2022)
Objective Psen1 was previously characterised as a crucial factor in the pathogenesis of neurodegeneration in patients with Alzheimer's disease. Little, if any, is known about its function in the gut. Here, we uncovered an unexpected functional role of Psen1 in gut epithelial cells during intestinal tumourigenesis. Design Human colorectal cancer (CRC) and control samples were investigated for PSEN1 and proteins of the gamma-secretase complex. Tumour formation was analysed in the AOM-DSS and Apc (min/+) mouse models using newly generated epithelial-specific Psen1 deficient mice. Psen1 deficient human CRC cells were studied in a xenograft tumour model. Tumour-derived organoids were analysed for growth and RNA-Seq was performed to identify Psen1-regulated pathways. Tumouroids were generated to study EGFR activation and evaluation of the influence of prostanoids. Results PSEN1 is expressed in the intestinal epithelium and its level is increased in human CRC. Psen1-deficient mice developed only small tumours and human cancer cell lines deficient in Psen1 had a reduced tumourigenicity. Tumouroids derived from Psen1-deficient Apc (min/+) mice exhibited stunted growth and reduced cell proliferation. On a molecular level, PSEN1 potentiated tumour cell proliferation via enhanced EGFR signalling and COX-2 production. Exogenous administration of PGE(2) reversed the slow growth of PSEN1 deficient tumour cells via PGE(2) receptor 4 (EP4) receptor signalling. Conclusions Psen1 drives tumour development by increasing EGFR signalling via NOTCH1 processing, and by activating the COX-2-PGE(2) pathway. PSEN1 inhibition could be a useful strategy in treatment of CRC.
CRIS-Team WoS Importer:2022-11-04

ERK activation and autophagy impairment are central mediators of irinotecan-induced steatohepatitis - Mahli, Abdo; Saugspier, Michael; Koch, Andreas; Sommer, Judith; Dietrich, Peter; Lee, Seren; Thasler, Reinhard; Schulze-Luehrmann, Jan; Lührmann, Anja; Thasler, Wolfgang Erwin; Müller, Martina; Boßerhoff, Anja Katrin; et al. (Gut, 2017)
Preoperative chemotherapy with irinotecan is associated with the development of steatohepatitis, which increases the risk of perioperative morbidity and mortality for liver surgery. The molecular mechanisms of this chemotherapeutic complication are widely unknown.Mechanisms of irinotecan-induced steatohepatitis were studied in primary human hepatocytes in vitro, in mice treated with irinotecan and in liver specimens from irinotecan-treated compared with control patients.Irinotecan dose-dependently induced lipid accumulation and pro-inflammatory gene expression in hepatocytes. This was accompanied by an impairment of mitochondrial function with reduced expression of carnitine palmitoyltransferase I and an induction of acyl-coenzyme A oxidase-1 (ACOX1), oxidative stress and extracellular signal-regulated kinase (ERK) activation. ERK inhibition prevented irinotecan-induced pro-inflammatory gene expression but had only a slight effect on lipid accumulation. However, irinotecan also induced an impairment of the autophagic flux mediated by alkalisation of lysosomal pH. Re-acidification of lysosomal pH abolished irinotecan-induced autophagy impairment and lipid accumulation. Also in mice, irinotecan treatment induced hepatic ACOX1 expression, ERK phosphorylation and inflammation, as well as impairment of autophagy and significant steatosis. Furthermore, irinotecan-treated patients revealed higher hepatic ERK activity, expression of pro-inflammatory genes and markers indicative for a shift to peroxisomal fatty acid oxidation and an impaired autophagic flux. Pretreatment with the multityrosine kinase inhibitor sorafenib did not affect autophagy impairment and steatosis but significantly reduced ERK phosphorylation and inflammatory response in irinotecan-treated hepatocytes and murine livers.Irinotecan induces hepatic steatosis via autophagy impairment and inflammation via ERK activation. Sorafenib appears as a novel therapeutic option for the prevention and treatment of irinotecan-induced inflammation.
EVALuna2:4748

Estrogen-mediated downregulation of HIF-1 alpha signaling in B lymphocytes influences postmenopausal bone loss - Meng, Xianyi; Lin, Zhen; Cao, Shan; Janowska, Iga; Sonomoto, Koshiro; Andreev, Darja; Knab, Katharina; Wen, Jinming; Knaup, Karl; Krönke, Gerhard; Rizzi, Marta; Schett, Georg; et al. (Bone Research, 2022)
In the bone marrow, B cells and bone-resorbing osteoclasts colocalize and form a specific microenvironment. How B cells functionally influence osteoclasts and bone architecture is poorly understood. Using genetically modified mice and high-throughput analyses, we demonstrate that prolonged HIF-1 alpha signaling in B cells leads to enhanced RANKL production and osteoclast formation. In addition, deletion of HIF-1 alpha in B cells prevents estrogen deficiency-induced bone loss in mice. Mechanistically, estrogen controls HIF-1 alpha protein stabilization through HSP70-mediated degradation in bone marrow B cells. The stabilization of HIF-1 alpha protein in HSP70-deficient bone marrow B cells promotes RANKL production and osteoclastogenesis. Induction of HSP70 expression by geranylgeranylacetone (GGA) administration alleviates ovariectomy-induced osteoporosis. Moreover, RANKL gene expression has a positive correlation with HIF1A expression in human B cells. In conclusion, HIF-1 alpha signaling in B cells is crucial for the control of osteoclastogenesis, and the HSP70/HIF-1 alpha axis may serve as a new therapeutic target for osteoporosis.
CRIS-Team WoS Importer:2022-03-04

E-type prostanoid receptor 4 drives resolution of intestinal inflammation by blocking epithelial necroptosis - Patankar, Jay; Muller, Tanja M.; Kantham, Srinivas; Acera, Miguel Gonzalez; Mascia, Fabrizio; Scheibe, Kristina; Mahapatro, Mousumi; Heichler, Christina; Yu, Yuqiang; Li, Wei; Ruder, Barbara; Günther, Claudia; et al. (Nature Cell Biology, 2021)
Inflammatory bowel diseases present with elevated levels of intestinal epithelial cell (IEC) death, which compromises the gut barrier, activating immune cells and triggering more IEC death. The endogenous signals that prevent IEC death and break this vicious cycle, allowing resolution of intestinal inflammation, remain largely unknown. Here we show that prostaglandin E2 signalling via the E-type prostanoid receptor 4 (EP4) on IECs represses epithelial necroptosis and induces resolution of colitis. We found that EP4 expression correlates with an improved IBD outcome and that EP4 activation induces a transcriptional signature consistent with resolution of intestinal inflammation. We further show that dysregulated necroptosis prevents resolution, and EP4 agonism suppresses necroptosis in human and mouse IECs. Mechanistically, EP4 signalling on IECs converges on receptor-interacting protein kinase 1 to suppress tumour necrosis factor-induced activation and membrane translocation of the necroptosis effector mixed-lineage kinase domain-like pseudokinase. In summary, our study indicates that EP4 promotes the resolution of colitis by suppressing IEC necroptosis.
CRIS-Team WoS Importer:2021-07-23

Evaluation of wear behavior of dental restorative materials against zirconia in vitro - Maier, Eva; Grottschreiber, Christine-Maria; Knepper, Ines; Opdam, Niek; Petschelt, Anselm; Loomans, Bas; Lohbauer, Ulrich (Dental Materials, 2022)
Objectives: To evaluate two-body wear (2BW) and three-body wear (3BW) of different CAD/CAM and direct restorative materials against zirconia using a dual-axis chewing simulator and an ACTA wear machine. Methods: 3 CAD-CAM resin-based composite or polymer infiltrated ceramic network blocs, 1 lithium disilicate CAD-CAM ceramic (LS2), 3 direct resin composites, amalgam and bovine enamel were tested. For 2BW, 8 flat specimens per material were produced, grinded, polished, stored wet (37 °C, 28d) and tested (49 N, 37 °C, 1,200,000 cycles) against zirconia. For 3BW, specimens (n = 10) were stored accordingly, and tested against a zirconia antagonist wheel (3Y-TZP, d = 20 mm, h = 6 mm; 200,000 cycles, F = 15 N, f = 1 Hz, 15% slip) in millet seed suspension. Wear resistance was analysed in a 3D optical non-contact profilometer, measuring vertical wear depth and volume loss for 2BW and mean wear depth and roughness (Ra) for 3BW. Vickers hardness (15 s, HV2) was measured. Statistical analysis was performed using non-parametric tests (Mann-Whitney-U test, p < 0.05). Results: 2BW and 3BW have a different impact on material surfaces. Similar wear resistance was observed for direct and indirect resin based materials with analogous filler configurations in both methods. Bovine enamel exhibited the best wear resistance in 2BW, but the least wear resistance in 3BW against zirconia. Regarding 2BW, a direct/indirect composite material pair of the same manufacturer showed the significantly highest mean volume losses (2.72/2.85 mm³), followed by LS2 (1.41 mm³). LS2 presented the best wear resistance in 3BW (mean wear depth 2.85 µm), combined with the highest mean Vickers hardness (598 MPa). No linear correlation was found between Vickers hardness and both wear testing procedures. The zirconia antagonists showed no recordable signs of wear. Significance: Dental restorative materials behave differently in 2BW and 3BW laboratory testing. Vickers hardness testing alone cannot hold for a correlation with wear behavior of materials. Micromorphological investigation of material composition can reveal insights in wear mechanisms related to variations in filler technologies.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Abrasion; ACTA wear machine; CAD-CAM; Chewing simulator; Dental materials; Resin-based composite; Three-body wear; Two-body wear; Vickers hardness; Zirconia

Exome Pool-Seq in neurodevelopmental disorders - Popp, Bernt; Ekici, Arif Bülent; Thiel, Christian; Hoyer, Juliane; Wiesener, Antje; Kraus, Cornelia; Reis, André; Zweier, Christiane (European journal of human genetics, 2017)
High throughput sequencing has greatly advanced disease gene identification, especially in heterogeneous entities. Despite falling costs this is still an expensive and laborious technique, particularly when studying large cohorts. To address this problem we applied Exome Pool-Seq as an economic and fast screening technology in neurodevelopmental disorders (NDDs). Sequencing of 96 individuals can be performed in eight pools of 12 samples on less than one Illumina sequencer lane. In a pilot study with 96 cases we identified 27 variants, likely or possibly affecting function. Twenty five of these were identified in 923 established NDD genes (based on SysID database, status November 2016) (ACTB, AHDC1, ANKRD11, ATP6V1B2, ATRX, CASK, CHD8, GNAS, IFIH1, KCNQ2, KMT2A, KRAS, MAOA, MED12, MED13L, RIT1, SETD5, SIN3A, TCF4, TRAPPC11, TUBA1A, WAC, ZBTB18, ZMYND11), two in 543 (SysID) candidate genes (ZNF292, BPTF), and additionally a de novo loss-of-function variant in LRRC7, not previously implicated in NDDs. Most of them were confirmed to be de novo, but we also identified X-linked or autosomal-dominantly or autosomal-recessively inherited variants. With a detection rate of 28%, Exome Pool-Seq achieves comparable results to individual exome analyses but reduces costs by >85%. Compared with other large scale approaches using Molecular Inversion Probes (MIP) or gene panels, it allows flexible re-analysis of data. Exome Pool-Seq is thus well suited for large-scale, cost-efficient and flexible screening in characterized but heterogeneous entities like NDDs.
EVALuna2:9387

Expanding the Phenotype Associated with NAA10-Related N-Terminal Acetylation Deficiency - Saunier, Chloe; Stove, Svein Isungset; Popp, Bernt; Gerard, Benedicte; Blenski, Marina; Ahmew, Nicholas; De Bie, Charlotte; Goldenberg, Paula; Isidor, Bertrand; Keren, Boris; Leheup, Bruno; Lampert, Laetitia; et al. (Human Mutation, 2016)
N-terminal acetylation is a common protein modification in eukaryotes associated with numerous cellular processes. Inherited mutations in NAA10, encoding the catalytic subunit of the major N-terminal acetylation complex NatA have been associated with diverse, syndromic X-linked recessive disorders, whereas de novo missense mutations have been reported in one male and one female individual with severe intellectual disability but otherwise unspecific phenotypes. Thus, the full genetic and clinical spectrum of NAA10 deficiency is yet to be delineated. We identified three different novel and one known missense mutation in NAA10, de novo in 11 females, and due to maternal germ line mosaicism in another girl and her more severely affected and deceased brother. In vitro enzymatic assays for the novel, recurrent mutations p.(Arg83Cys) and p.(Phe128Leu) revealed reduced catalytic activity. X-inactivation was random in five females. The core phenotype of X-linked NAA10-related N-terminal-acetyltransferase deficiency in both males and females includes developmental delay, severe intellectual disability, postnatal growth failure with severe microcephaly, and skeletal or cardiac anomalies. Genotype-phenotype correlations within and between both genders are complex and may include various factors such as location and nature of mutations, enzymatic stability and activity, and X-inactivation in females.
EVALuna2:9314

Experimental Cutaneous Leishmaniasis: Mouse Models for Resolution of Inflammation Versus Chronicity of Disease - Bogdan, Christian; Debus, Andrea; Sebald, Heidi; Rai, Baplu; Schäfer, Johanna; Obermeyer, Stephanie; Schleicher, Ulrike (Leishmania, 2019)
Experimental cutaneous leishmaniasis of mice is a valuable model to study the immune response to the protozoan pathogen Leishmania and to define mechanisms of parasite control and resolution of inflammation as well as of parasite evasion and chronicity of disease. In addition, over many years Leishmania-infected mice have been successfully used to analyze the function of newly discovered immune cell types, transcription factors, cytokines, and effector mechanisms in vivo. In this chapter we present detailed protocols for the culture, propagation, and inoculation of Leishmania promastigotes, the monitoring of the course of cutaneous infection, the determination of the tissue parasite burden and for the phenotyping of the ensuing immune response. The focus lies on the L. major mouse model, but an overview on other established models of murine cutaneous leishmaniasis is also provided.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cutaneous leishmaniasis; Leishmania major; Mouse models

Explainable AI identifies diagnostic cells of genetic AML subtypes - Hehr, Matthias; Sadafi, Ario; Matek, Christian; Lienemann, Peter; Pohlkamp, Christian; Haferlach, Torsten; Spiekermann, Karsten; Marr, Carsten (PLOS Digital Health, 2023)
Explainable AI is deemed essential for clinical applications as it allows rationalizing model predictions, helping to build trust between clinicians and automated decision support tools. We developed an inherently explainable AI model for the classification of acute myeloid leukemia subtypes from blood smears and found that high-attention cells identified by the model coincide with those labeled as diagnostically relevant by human experts. Based on over 80,000 single white blood cell images from digitized blood smears of 129 patients diagnosed with one of four WHO-defined genetic AML subtypes and 60 healthy controls, we trained SCEMILA, a single-cell based explainable multiple instance learning algorithm. SCEMILA could perfectly discriminate between AML patients and healthy controls and detected the APL subtype with an F1 score of 0.86±0.05 (mean±s.d., 5-fold cross-validation). Analyzing a novel multi-attention module, we confirmed that our algorithm focused with high concordance on the same AML-specific cells as human experts do. Applied to classify single cells, it is able to highlight subtype specific cells and deconvolve the composition of a patient’s blood smear without the need of single-cell annotation of the training data. Our large AML genetic subtype dataset is publicly available, and an interactive online tool facilitates the exploration of data and predictions. SCEMILA enables a comparison of algorithmic and expert decision criteria and can present a detailed analysis of individual patient data, paving the way to deploy AI in the routine diagnostics for identifying hematopoietic neoplasms.<br

Extracellular acidosis triggers a senescence-like phenotype in human melanoma cells - Böhme, Ines; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2019)
Acidosis of the tumor microenvironment is a characteristic of solid tumors such as malignant melanoma. Main causes of the extracellular acidification are metabolic alterations in cancer cells. While numerous studies showed that acidosis promotes tumor invasiveness, metastasis, and neoangiogenesis resulting in malignant progression, contrary data reported that acidosis induces cell apoptosis, inhibits cell proliferation, and mediates cell autophagy. Here, we show that low pH (pH 6.7) induces senescent/quiescent phenotype in melanoma cells after long-time treatment defined by induction of SA-beta-galactosidase, upregulation of p21, G(1)/G(0) cell cycle arrest, and reduction of proliferation. Moreover, we revealed that extracellular acidosis triggers the inhibition of eIF2 alpha and subsequently the activation of ATF4 expression, a key component of the integrated stress response (ISR), indicating an acid-mediated translation reprogramming. Interestingly, we also demonstrated that acidosis represses microphthalmia-associated transcription factor (MITF) and activates the expression of the receptor tyrosine kinase AXL. This MITFlow/AXL(high) phenotype is correlated with drug resistance and therapeutic outcome in melanoma. Our results suggest that acidosis is an important microenvironmental factor triggering phenotypic plasticity and promoting tumor progression.
CRIS-Team WoS Importer:2019-08-20

Extracellular aggregated alpha synuclein primarily triggers lysosomal dysfunction in neural cells prevented by trehalose - Hoffmann, Anna-Carin; Minakaki, Georgia; Menges, Stefanie; Salvi, Rachele; Savitskiy, Sergey; Kazman, Aida; Miranda, Hugo Vicente; Mielenz, Dirk; Klucken, Jochen; Winkler, Jürgen; Xiang, Wei (Scientific Reports, 2019)
Cell-to-cell propagation of aggregated alpha synuclein (aSyn) has been suggested to play an important role in the progression of alpha synucleinopathies. A critical step for the propagation process is the accumulation of extracellular aSyn within recipient cells. Here, we investigated the trafficking of distinct exogenous aSyn forms and addressed the mechanisms influencing their accumulation in recipient cells. The aggregated aSyn species (oligomers and fibrils) exhibited more pronounced accumulation within recipient cells than aSyn monomers. In particular, internalized extracellular aSyn in the aggregated forms was able to seed the aggregation of endogenous aSyn. Following uptake, aSyn was detected along endosome-to-lysosome and autophagosome-to-lysosome routes. Intriguingly, aggregated aSyn resulted in lysosomal activity impairment, accompanied by the accumulation of dilated lysosomes. Moreover, analysis of autophagy-related protein markers suggested decreased autophagosome clearance. In contrast, the endocytic pathway, proteasome activity, and mitochondrial homeostasis were not substantially affected in recipient cells. Our data suggests that extracellularly added aggregated aSyn primarily impairs lysosomal activity, consequently leading to aSyn accumulation within recipient cells. Importantly, the autophagy inducer trehalose prevented lysosomal alterations and attenuated aSyn accumulation within aSyn-exposed cells. Our study underscores the importance of lysosomes for the propagation of aSyn pathology, thereby proposing these organelles as interventional targets.
EVALuna2:36381

Feedback regulation of mitochondrial homeostasis via Wnt/β-catenin signaling - Bernkopf, Dominic; Behrens, Jürgen (Molecular & Cellular Oncology, 2018)
Cellular abundance of mitochondria is dynamically regulated. We could recently show that dysfunctional mitochondria release the phosphatase PGAM family member 5 (PGAM5) into the cytosol, where it interacts with the Wnt signaling-component AXIN1 and dephosphorylates AXIN1-bound β-catenin (CTNNB1) thereby activating Wnt/β-catenin signaling. Because Wnt/β-catenin signaling induces mitochondrial biogenesis dysfunctional mitochondria trigger their own replacement by releasing PGAM5.
EVALuna2:34941

Fibroblast Growth Factor 9 is expressed by activated hepatic stellate cells and promotes progression of hepatocellular carcinoma - Seitz, Tatjana; Freese, Kim; Dietrich, Peter; Thasler, Wolfgang Erwin; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Scientific Reports, 2020)
Hepatocellular carcinoma (HCC) is closely associated with liver fibrosis. Hepatic stellate cells (HSC) and cancer-associated myofibroblasts are key players in liver fibrogenesis and hepatocarcinogenesis. Overexpression of fibroblast growth factor (FGF) receptors contributes to HCC development and progression. This study aimed to elucidate the role of FGFs in the HSC-HCC crosstalk. Analysis of the expression of the fifteen paracrine FGF-members revealed that FGF9 was only expressed by HSC but not by HCC cells. Also in human HCC tissues, HSC/stromal myofibroblasts were identified as cellular source of FGF9. High expression levels of FGF9 significantly correlated with poor patient survival. Stimulation with recombinant FGF9 induced ERK- and JNK-activation combined with significantly enhanced proliferation, clonogenicity, and migration of HCC cells. Moreover, FGF9 significantly reduced the sensitivity of HCC cells against sorafenib. Protumorigenic effects of FGF9 on HCC cells were almost completely abrogated by the FGFR1/2/3 inhibitor BGJ398, while the selective FGFR4 inhibitor BLU9931 had no significant effect. In conclusion, these data indicate that stroma-derived FGF9 promotes tumorigenicity and sorafenib resistance of HCC cells and FGF9 overexpression correlates with poor prognosis in HCC patients. Herewith, FGF9 appears as potential prognostic marker and novel therapeutic target in HCC.
CRIS-Team Scopus Importer:2020-03-27

Fibroblast growth factor receptor 3 activates a network of profibrotic signaling pathways to promote fibrosis in systemic sclerosis - Chakraborty, Debomita; Zhu, Honglin; Juengel, Astrid; Summa, Lena; Li, Yi-Nan; Matei, Alexandru-Emil; Zhou, Xiang; Huang, Jingang; Thuong Trinh-Minh,; Chen, Chih-Wei; Lafyatis, Robert; Dees, Clara; et al. (Science Translational Medicine, 2020)
Aberrant activation of fibroblasts with progressive deposition of extracellular matrix is a key feature of systemic sclerosis (SSc), a prototypical idiopathic fibrotic disease. Here, we demonstrate that the profibrotic cytokine transforming growth factor. selectively up-regulates fibroblast growth factor receptor 3 (FGFR3) and its ligand FGF9 to promote fibroblast activation and tissue fibrosis, leading to a prominent FGFR3 signature in the SSc skin. Transcriptome profiling, in silico analysis and functional experiments revealed that FGFR3 induces multiple profibrotic pathways including endothelin, interleukin-4, and connective tissue growth factor signaling mediated by transcription factor CREB (cAMP response element-binding protein). Inhibition of FGFR3 signaling by fibroblast-specific knockout of FGFR3 or FGF9 or pharmacological inhibition of FGFR3 blocked fibroblast activation and attenuated experimental skin fibrosis in mice. These findings characterize FGFR3 as an upstream regulator of a network of profibrotic mediators in SSc and as a potential target for the treatment of fibrosis.
CRIS-Team WoS Importer:2020-10-16

FLAIRfusion Processing with Contrast Inversion : Improving Detection and Reading Time of New Cerebral MS Lesions - Schmidt, Manuel; Linker, Ralf; Lang, S.; Lücking, Hannes; Engelhorn, Tobias; Kloska, Stephan; Uder, Michael; Dörfler, Arnd; Dankerl, Peter; Cavallaro, Alexander Josef (Clinical Neuroradiology, 2017)
To evaluate the performance of an innovative image processing approach for detection of T2-weighted hyperintense multiple sclerosis (MS) lesions.In this study 20 consecutive patients with inflammatory demyelinating lesions were retrospectively evaluated of whom 10 patients featured progressive disease and 10 a stable lesion load. 3 mm transversal FLAIRfusion imaging was processed and archived. Image processing was performed through landmark-based 3D co-registration of the previous and current isotropic FLAIR examination followed by inversion of image contrast. Thereby, the hyperintense signals of the unchanged MS plaques extinguish each other, while newly developed lesions appear bright on FLAIRfusion. Diagnostic performance was evaluated by 4 experienced readers. Consensus reading supplied the reference standard. Sensitivity, specificity, NPV (negative predictive value), PPV (positive predictive value), interreader agreement and reading time were the outcome measures analyzed.Combined sensitivity was 100% at a specificity of 88.2%, with PPV ranging from 83.3% to 90.1% and NPV at 100%. Reading time was nearly 5-fold faster than conventional side by side comparison (35.6 s vs. 163.7 s, p < 0.001). Cohen's kappa was excellent (>0.75; p < 0.001) and Cronbach's alpha was 0.994.FLAIRfusion provides reliable detection of newly developed MS lesions along with strong interreader agreement across all levels of expertise in 35 s of reading time.
EVALuna2:14615

Forecasting flu activity in the united states: Benchmarking an endemic-epidemic beta model - Lu, Junyi; Meyer, Sebastian (International Journal of Environmental Research and Public Health, 2020)
Accurate prediction of flu activity enables health officials to plan disease prevention and allocate treatment resources. A promising forecasting approach is to adapt the well-established endemic-epidemic modeling framework to time series of infectious disease proportions. Using U.S. influenza-like illness surveillance data over 18 seasons, we assessed probabilistic forecasts of this new beta autoregressive model with proper scoring rules. Other readily available forecasting tools were used for comparison, including Prophet, (S)ARIMA and kernel conditional density estimation (KCDE). Short-term flu activity was equally well predicted up to four weeks ahead by the beta model with four autoregressive lags and by KCDE; however, the beta model runs much faster. Non-dynamic Prophet scored worst. Relative performance differed for seasonal peak prediction. Prophet produced the best peak intensity forecasts in seasons with standard epidemic curves; otherwise, KCDE outperformed all other methods. Peak timing was best predicted by SARIMA, KCDE or the beta model, depending on the season. The best overall performance when predicting peak timing and intensity was achieved by KCDE. Only KCDE and naive historical forecasts consistently outperformed the equal-bin reference approach for all test seasons. We conclude that the endemic-epidemic beta model is a performant and easy-to-implement tool to forecast flu activity a few weeks ahead. Real-time forecasting of the seasonal peak, however, should consider outputs of multiple models simultaneously, weighing their usefulness as the season progresses.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Beta regression; Forecasting; Influenza; Seasonality; Time series

Four-and-a-Half LIM-Domain Protein 2 (FHL2) Induces Neuropeptide Y (NPY) in Macrophages in Visceral Adipose Tissue and Promotes Diet-Induced Obesity - Sommer, Judith; Ehnis, Hanna; Seitz, Tatjana; Schneider, Julia; Wild, Andreas; Moceri, Sandra; Buechler, Christa; Bozec, Aline; Weber, Georg; Merkel, Susanne; Beckervordersandforth, Ruth; Steinkasserer, Alexander; et al. (International Journal of Molecular Sciences, 2023)
Obesity is characterized by the expansion of the adipose tissue, usually accompanied by inflammation, with a prominent role of macrophages infiltrating the visceral adipose tissue (VAT). This chronic inflammation is a major driver of obesity-associated comorbidities. Four-and-a-half LIM-domain protein 2 (FHL2) is a multifunctional adaptor protein that is involved in the regulation of various biological functions and the maintenance of the homeostasis of different tissues. In this study, we aimed to gain new insights into the expression and functional role of FHL2 in VAT in diet-induced obesity. We found enhanced FHL2 expression in the VAT of mice with Western-type diet (WTD)-induced obesity and obese humans and identified macrophages as the cellular source of enhanced FHL2 expression in VAT. In mice with FHL2 deficiency (FHL2KO), WTD feeding resulted in reduced body weight gain paralleled by enhanced energy expenditure and uncoupling protein 1 (UCP1) expression, indicative of activated thermogenesis. In human VAT, FHL2 was inversely correlated with UCP1 expression. Furthermore, macrophage infiltration and the expression of the chemokine MCP-1, a known promotor of macrophage accumulation, was significantly reduced in WTD-fed FHL2KO mice compared with wild-type (wt) littermates. While FHL2 depletion did not affect the differentiation or lipid metabolism of adipocytes in vitro, FHL2 depletion in macrophages resulted in reduced expressions of MCP-1 and the neuropeptide Y (NPY). Furthermore, WTD-fed FHL2KO mice showed reduced NPY expression in VAT compared with wt littermates, and NPY expression was enhanced in VAT resident macrophages of obese individuals. Stimulation with recombinant NPY induced not only UCP1 expression and lipid accumulation but also MCP-1 expression in adipocytes. Collectively, these findings indicate that FHL2 is a positive regulator of NPY and MCP-1 expression in macrophages and herewith closely linked to the mechanism of obesity-associated lipid accumulation and inflammation in VAT. Thus, FHL2 appears as a potential novel target to interfere with the macrophage–adipocyte crosstalk in VAT for treating obesity and related metabolic disorders.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adipocytes; FHL2; macrophages; MCP-1; NPY; obesity; thermogenesis

Fourteen years clinical evaluation of leucite-reinforced ceramic inlays luted using two different adhesion strategies - Taschner, Michael; Stirnweiß, Anna; Frankenberger, Roland; Kramer, Norbert; Galler, Kerstin Martina; Maier, Eva (Journal of Dentistry, 2022)
Objectives: Aim of the present prospective study was to clinically evaluate the long-term performance of two different luting-materials for leucite-reinforced glass-ceramic inlays/onlays after 14 years. Methods: A total of 83 IPS-Empress-inlays/onlays were placed in 30 patients. Restorations were luted according to two different strategies: 43 restorations were fixed with a self-adhesive resin-cement (RelyXUnicem, RX), 40 restorations were inserted with VariolinkII-low (SV) after pretreatment with an etch-and-rinse multi-step adhesive. Recalls were performed after two weeks (n=83), two years (n= 82), four years (n=74) and 14 years (n=54). Two independent calibrated examiners evaluated all restorations using modified USPHS-criteria. Statistical analysis was performed using pairwise Mann-Whitney-U-test and Friedman-test (p < 0.05). Results: After 14 years, 54 restorations in 22 patients were evaluated (eight patients equalling 29 inlays not available). Ten restorations had to be replaced (failure rate 12%); four (SV-group) showed bulk fractures and two (RX-group) exhibited marginal fractures at the 14-year recall. Overall, the SV-group revealed significantly better results regarding discoloration of the luting gap (p<0.05) compared to the RX-group. No statistically significant differences were computed between SV and RX for the remaining criteria at the respective recalls (p>0.05). However, statistically significant deteriorations were detected for both luting procedures over 14 years regarding “colour match”, “marginal integrity” and “tooth integrity” (p<0.05). Conclusions: The self-adhesive resin-cement RelyXUnicem showed similar clinical performance to a conventional multi-step luting-procedure after 14 years for most of the test parameters with a slightly inferior performance of RelyXUnicem regarding discoloration of the luting gap. Clinical significance: The current study presents unique in-vivo long-term data on two adhesion-strategies for indirect ceramic single-tooth restorations. Differences in performance of the two luting methods after being challenged for 14 years in the oral environment are highlighted. However, the overarching survival rate justifies the recommendation of both methods for clinical routine.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Cement; Ceramic; Clinical trial; In vivo; Long-term; Self-adhesive

FoxO Function Is Essential for Maintenance of Autophagic Flux and Neuronal Morphogenesis in Adult Neurogenesis - Schäffner, Iris; Minakaki, Georgia; Khan, M. Amir; Balta, Elli-Anna; Schlötzer-Schrehardt, Ursula; Schwarz, Tobias J.; Beckervordersandforth, Ruth; Winner, Beate; Webb, Ashley E.; Depinho, Ronald A.; Paik, Jihye; Wurst, Wolfgang; et al. (Neuron, 2018)
Autophagy is a conserved catabolic pathway with emerging functions in mammalian neurodevelopment and human neurodevelopmental diseases. The mechanisms controlling autophagy in neuronal development are not fully understood. Here, we found that conditional deletion of the Forkhead Box O transcription factors FoxO1, FoxO3, and FoxO4 strongly impaired autophagic flux in developing neurons of the adult mouse hippocampus. Moreover, FoxO deficiency led to altered dendritic morphology, increased spine density, and aberrant spine positioning in adult-generated neurons. Strikingly, pharmacological induction of autophagy was sufficient to correct abnormal dendrite and spine development of FoxO-deficient neurons. Collectively, these findings reveal a novel link between FoxO transcription factors, autophagic flux, and maturation of developing neurons.
EVALuna2:34732

Fra-2 Expression in Osteoblasts Regulates Systemic Inflammation and Lung Injury through Osteopontin - Luo, Yubin; Grötsch, Bettina; Hannemann, Nicole; Jimenez, Maria; Ipseiz, Natacha; Uluckan, Ozge; Lin, Nengyu; Schett, Georg; Wagner, Erwin F.; Bozec, Aline (Molecular and Cellular Biology, 2018)
Inflammatory responses require mobilization of innate immune cells from the bone marrow. The functionality of this process depends on the state of the bone marrow microenvironment. We therefore hypothesized that molecular changes in osteoblasts, which are essential stromal cells of the bone marrow microenvironment, influence the inflammatory response. Here, we show that osteoblast-specific expression of the AP-1 transcription factor Fra-2 (Fra-2Ob-tet) induced a systemic inflammatory state with infiltration of neutrophils and proinflammatory macrophages into the spleen and liver as well as increased levels of proinflammatory cytokines, such as interleukin-1β (IL-1β), IL-6, and granulocyte-macrophage colony-stimulating factor (GM-CSF). By in vivo inhibition of osteopontin (OPN) in Fra-2Ob-tet mice, we demonstrated that this process was dependent on OPN expression, which mediates alterations of the bone marrow niche. OPN expression was transcriptionally enhanced by Fra-2 and stimulated mesenchymal stem cell (MSC) expansion. Furthermore, in a murine lung injury model, Fra-2Ob-tet mice showed increased inflammatory responses and more severe disease features via an enhanced and sustained inflammatory response to lipopolysaccharide (LPS). Our findings demonstrate for the first time that molecular changes in osteoblasts influence the susceptibility to inflammation by altering evasion of innate immune cells from the bone marrow space.
EVALuna2:34665
Keywords: Fra-2/AP-1; osteopontin; bone niche; systemic inflammation; lung injury; Fra-2; osteoblasts

Fra-2 regulates B cell development by enhancing IRF4 and Foxo1 transcription - Ubieta, Kenia; Garcia, Mireia; Groetsch, Bettina; Uebe, Steffen; Stein, Merle; Ekici, Arif Bülent; Schett, Georg; Mielenz, Dirk; Bozec, Aline; Weber, Georg (Journal of Experimental Medicine, 2017)
The role of AP-1 transcription factors in early B cell development and function is still incompletely characterized. Here we address the role of Fra-2 in B cell differentiation. Deletion of Fra-2 leads to impaired B cell proliferation in the bone marrow. In addition, IL-7-stimulated pro-B cell cultures revealed a reduced differentiation from large pre-B cells to small B cells and immature B cells. Gene profiling and chromatin immunoprecipitation sequencing analyses unraveled a transcriptional reduction of the transcription factors Foxo1, Irf4, Ikaros, and Aiolos in Fra-2-deficient B cells. Moreover, expression of IL7R? and Rag 1/2, downstream targets of Irf4 and Foxo1, were also reduced in the absence of Fra-2. Pro-B cell proliferation and small pre-B cell differentiation were fully rescued by expression of Foxo1 and Irf4 in Fra-2-deficient pro-B cells. Hence, Fra-2 is a key upstream regulator of Foxo1 and Irf4 expression and influences proliferation and differentiation of B cells at multiple stages.
EVALuna2:9366

Functional Relevance of the Interaction between Human Cyclins and the Cytomegalovirus-Encoded CDK-Like Protein Kinase pUL97 - Schütz, Martin; Steingruber, Mirjam; Socher, Eileen; Müller, Regina; Wagner, Sabrina; Kögel, Merle; Sticht, Heinrich; Marschall, Manfred (Viruses, 2021)
The replication of human cytomegalovirus (HCMV) is characterized by a complex network of virus–host interaction. This involves the regulatory viral protein kinase pUL97, which represents a viral cyclin-dependent kinase ortholog (vCDK) combining typical structural and functional features of host CDKs. Notably, pUL97 interacts with the three human cyclin types T1, H and B1, whereby the binding region of cyclin T1 and the region conferring oligomerization of pUL97 were both assigned to amino acids 231–280. Here, we addressed the question of whether recombinant HCMVs harboring deletions in this region were impaired in cyclin interaction, kinase functionality or viral replication. To this end, recombinant HCMVs were generated by traceless BACmid mutagenesis and were phenotypically characterized using a methodological platform based on qPCR, coimmunoprecipitation, in vitro kinase assay (IVKA), Phos-tag Western blot and confocal imaging analysis. Combined data illustrate the following: (i) infection kinetics of all three recombinant HCMVs, i.e., ORF-UL97 ∆231–255, ∆256–280 and ∆231–280, showed impaired replication efficiency compared to the wild type, amongst which the largest deletion exhibited the most pronounced defect; (ii) specifically, this mutant ∆231–280 showed a loss of interaction with cyclin T1, as demonstrated by CoIP and confocal imaging; (iii) IVKA and Phos-tag analyses revealed strongly affected kinase activity for ∆231–280, with strong impairment of both autophosphorylation and substrate phosphorylation, but less pronounced impairments for ∆231–255 and ∆256–280; and (iv) a bioinformatic assessment of the pUL97–cyclin T1 complex led to the refinement of our current binding model. Thus, the results provide initial evidence for the functional importance of the pUL97–cyclin interaction concerning kinase activity and viral replication fitness.<br
Keywords: human cytomegalovirus; virus-encoded kinase pUL97; viral CDK ortholog; interaction with human cyclin T1; replication-impaired viral mutants; defects in pUL97 activities; pUL97–cyclin functional importance

Function of Macrophage and Parasite Phosphatases in Leishmaniasis - Soulat, Didier; Bogdan, Christian (Frontiers in Immunology, 2017)
The kinetoplastid protozoan parasites belonging to the genusLeishmaniaare the causative agents of different clinical forms of leishmaniasis, a vector-borne infectious disease with worldwide prevalence. The protective host immune response againstLeishmaniaparasites relies on myeloid cells such as dendritic cells and macrophages in which upon stimulation by cytokines (e.g., interferon-γ) a complex network of signaling pathways is switched on leading to strong antimicrobial activities directed against the intracellular parasite stage. The regulation of these pathways classically depends on post-translational modifications of proteins, with phosphorylation events playing a cardinal role.Leishmaniaparasites deactivate their phagocytic host cells by inducing specific mammalian phosphatases that are capable to impede signaling. On the other hand, there is now also evidence thatLeishmaniaspp. themselves express phosphatases that might target host cell molecules and thereby facilitate the intracellular survival of the parasite. This review will present an overview on the modulation of host phosphatases byLeishmaniaparasites as well as on the known families ofLeishmaniaphosphatases and their possible function as virulence factors. A more detailed understanding of the role of phosphatases inLeishmania-host cell interactions might open new avenues for the treatment of non-healing, progressive forms of leishmaniasis.
EVALuna2:33306

Gait and cognition in Parkinson’s disease: cognitive impairment is inadequately reflected by gait performance during dual task - Gaßner, Heiko; Marxreiter, Franz; Steib, Simon; Kohl, Zacharias; Schlachetzki, Johannes; Adler, Werner; Eskofier, Björn; Pfeifer, Klaus; Winkler, Jürgen; Klucken, Jochen (Frontiers in Neurology, 2017)
Introduction: Cognitive and gait deficits are common symptoms in Parkinson's disease (PD). Motor-cognitive dual tasks (DTs) are used to explore the interplay between gait and cognition. However, it is unclear if DT gait performance is indicative for cognitive impairment. Therefore, the aim of this study was to investigate if cognitive deficits are reflected by DT costs of spatiotemporal gait parameters.Methods: Cognitive function, single task (ST) and DT gait performance were investigated in 67 PD patients. Cognition was assessed by the Montreal Cognitive Assessment (MoCA) followed by a standardized, sensor-based gait test and the identical gait test while subtracting serial 3's. Cognitive impairment was defined by a MoCA score <26. DT costs in gait parameters [(DT ST)/ST x 100] were calculated as a measure of DT effect on gait. Correlation analysis was used to evaluate the association between MoCA performance and gait parameters. In a linear regression model, DT gait costs and clinical confounders (age, gender, disease duration, motor impairment, medication, and depression) were correlated to cognitive performance. In a subgroup analysis, we compared matched groups of cognitively impaired and unimpaired PD patients regarding differences in ST, DT, and DT gait costs.Results: Correlation analysis revealed weak correlations between MoCA score and DT costs of gait parameters (r/r(Sp) <= 0.3). DT costs of stride length, swing time variability, and maximum toe clearance (vertical bar r/r(Sp)vertical bar > 0.2) were included in a regression analysis. The parameters only explain 8% of the cognitive variance. In combination with clinical confounders, regression analysis showed that these gait parameters explained 30% of MoCA performance. Group comparison revealed strong DT effects within both groups (large effect sizes), but significant between-group effects in DT gait costs were not observed.Conclusion: These findings suggest that DT gait performance is not indicative for cognitive impairment in PD. DT effects on gait parameters were substantial in cognitively impaired and unimpaired patients, thereby potentially overlaying the effect of cognitive impairment on DT gait costs. Limits of the MoCA in detecting motor-function specific cognitive performance or variable individual response to the DT as influencing factors cannot be excluded. Therefore, DT gait parameters as marker for cognitive performance should be carefully interpreted in the clinical context.
Keywords: Parkinson's disease; gait; cognition; dual task; gait analysis; Montreal Cognitive Assessment

Gammaherpesviral Tegument Proteins, PML-Nuclear Bodies and the Ubiquitin-Proteasome System - Full, Florian; Hahn, Alexander S.; Grosskopf, Anna K.; Enßer, Armin (Viruses, 2017)
Gammaherpesviruses like Epstein-Barr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (KSHV) subvert the ubiquitin proteasome system for their own benefit in order to facilitate viral gene expression and replication. In particular, viral tegument proteins that share sequence homology to the formylglycineamide ribonucleotide amidotransferase (FGARAT, or PFAS), an enzyme in the cellular purine biosynthesis, are important for disrupting the intrinsic antiviral response associated with Promyelocytic Leukemia (PML) protein-associated nuclear bodies (PML-NBs) by proteasome-dependent and independent mechanisms. In addition, all herpesviruses encode for a potent ubiquitin protease that can efficiently remove ubiquitin chains from proteins and thereby interfere with several different cellular pathways. In this review, we discuss mechanisms and functional consequences of virus-induced ubiquitination and deubiquitination for early events in gammaherpesviral infection.
EVALuna2:33753

Generation of a homozygous and a heterozygous SNCA gene knockout human-induced pluripotent stem cell line by CRISPR/Cas9 mediated allele-specific tuning of SNCA expression - Schneider, Yanni; Turan, Soeren; Koller, Aron; Krumbiegel, Mandy; Farrell, Michaela; Plotz, Sonja; Winkler, Jürgen; Xiang, Wei (Stem Cell Research, 2022)
Aggregation of alpha-synuclein (aSyn) is closely linked to Parkinson's disease, probably due to the loss of physiological functions and/or gain of toxic functions of aggregated aSyn. Significant efforts have been made elucidating the physiological structure and function of aSyn, however, with limited success thus far in human -derived cells, partly because of restricted resources. Here, we developed two human-induced pluripotent stem cell lines using CRISPR/Cas9-mediated allele-specific frame-shift deletion of the aSyn encoding gene SNCA, resulting in homo-and heterozygous SNCA knockout. The generated cell lines are promising cellular tools for studying aSyn dosage-dependent functions and structural alterations in human neural cells.
CRIS-Team WoS Importer:2022-11-18

Generation of Patient-Derived Podocytes from Skin Biopsies - Rose, Victoria; Müller-Deile, Janina (Journal of Visualized Experiments, 2023)
Podocytes are epithelial cells sitting on the urinary site of the glomerular filtration barrier that contribute to the selective filter function of the glomerulus. Mutations in podocyte-specific genes can cause focal segmental glomerulosclerosis (FSGS), and podocytes are also affected in many other primary and secondary nephropathies. Due to their differentiated nature, primary cell culture models are limited for podocytes. Therefore, commonly conditionally immortalized cells are used. However, these conditionally immortalized podocytes (ciPodocytes) have several limitations: the cells can dedifferentiate in culture, especially when they reach confluency, and several podocyte-specific markers are either only slightly or not expressed at all. This brings the use of ciPodocytes and their applicability for physiological, pathophysiological, and clinical reach into question. Here, we describe a protocol for the generation of human podocytes-including patient-specific podocytes-from a skin punch biopsy by episomal reprogramming of dermal fibroblasts into hiPSCs and subsequent differentiation into podocytes. These podocytes resemble in vivo podocytes much better in terms of morphological characteristics, like the development of foot processes and the expression of the podocyte-specific marker. Finally, yet importantly, these cells maintain patients' mutations, resulting in an improved ex vivo model to study podocyte diseases and potential therapeutic substances in an individualized approach.
CRIS-Team Scopus Importer:2023-06-30

Genetic ablation of cyp8b1 preserves host metabolic function by repressing steatohepatitis and altering gut microbiota composition - Patankar, Jay; Wong, Chi K.; Morampudi, Vijay; Gibson, William T.; Vallance, Bruce; Ioannou, George N.; Hayden, Michael R. (American Journal of Physiology-Endocrinology and Metabolism, 2018)
Genetic ablation of Cyp8b1 preserves host metabolic function by repressing steatohepatitis and altering gut microbiota composition. Am J Physiol Endocrinol Metab 314: E418–E432, 2018. First published October 24, 2017; doi:10.1152/ajpendo. 00172.2017.—Both type 2 diabetes (T2D) and nonalcoholic steatohepatitis (NASH) are associated with reduced hepatic mitochondrial respiratory capacity. Cholic acid (CA) is the predominant 12α-hy-droxylated bile acid that regulates hepatic lipid metabolism, and its circulating levels are negatively correlated with insulin resistance. Abolishing CA synthesis via the genetic disruption of the enzyme sterol 12α-hydroxylase (Cyp8b1-/-) leads in resistance to diabetes and hepatic steatosis. Here, we show that long-term stimulation of hepatic lipogenesis leads to a severe impairment in overall metabolic and respiratory function in control mice (Cyp8b1+/+) but strikingly not in Cyp8b1-/- mice. Cyp8b1-/- mice are protected from such metabolic impairments associated with T2D and NASH by inhibiting hepatic de novo lipogenic gene and protein expression and altering gut microbiota composition. The protective phenotype is compromised when NASH induction is independent of impairment in de novo lipogenesis (DNL). Consequently, Cyp8b1-/- mice also show a reduction in hepatic inflammation and fibrosis along with a shift in antimicrobial dynamics in the small intestine. Our data show that the altered bile acid composition of Cyp8b1-/- mice preserves metabolic and respiratory function by repressing hepatic DNL and driving favorable changes in gut antimicrobial responses.
Created from Fastlane, Scopus look-up
Keywords: 12α-hydroxylated bile acids; Cyp8b1; FXR; Gut microbiota; Nonalcoholic hepatic steatosis

Genetic Analysis of MPO Variants in Four Psoriasis Subtypes in Patients from Germany - Haskamp, Stefan; Horowitz, Joseph; Oji, Vinzenz; Philipp, Sandra; Sticherling, Michael; Schäkel, Knut; Schuhmann, Sarah; Prinz, Jörg C.; Burkhardt, Harald; Behrens, Frank; Böhm, Beate; Köhm, Michaela; et al. (Journal of Investigative Dermatology, 2021)
CRIS-Team Scopus Importer:2021-03-26

Genetic association study of exfoliation syndrome identifies a protective rare variant at LOXL1 and five new susceptibility loci - Aung, Tin; Ozaki, Mineo; Lee, Mei Chin; Schlötzer-Schrehardt, Ursula; Thorleifsson, Gudmar; Mizoguchi, Takanori; Igo, Robert P.; Haripriya, Aravind; Williams, Susan E.; Astakhov, Yury S.; Orr, Andrew C.; Burdon, Kathryn P.; et al. (Nature Genetics, 2017)
Exfoliation syndrome (XFS) is the most common known risk factor for secondary glaucoma and a major cause of blindness worldwide. Variants in two genes, LOXL1 and CACNA1A, have previously been associated with XFS. To further elucidate the genetic basis of XFS, we collected a global sample of XFS cases to refine the association at LOXL1, which previously showed inconsistent results across populations, and to identify new variants associated with XFS. We identified a rare protective allele at LOXL1 (p.Phe407, odds ratio (OR) = 25, P = 2.9 × 10(-14)) through deep resequencing of XFS cases and controls from nine countries. A genome-wide association study (GWAS) of XFS cases and controls from 24 countries followed by replication in 18 countries identified seven genome-wide significant loci (P < 5 × 10(-8)). We identified association signals at 13q12 (POMP), 11q23.3 (TMEM136), 6p21 (AGPAT1), 3p24 (RBMS3) and 5q23 (near SEMA6A). These findings provide biological insights into the pathology of XFS and highlight a potential role for naturally occurring rare LOXL1 variants in disease biolog
EVALuna2:9376

Genetic interaction screen for severe neurodevelopmental disorders reveals a functional link between Ube3a and Mef2 in Drosophila melanogaster - Straub, Jonas; Gregor, Anne; Sauerer, Tatjana; Fliedner, Anna; Distel, Laila; Suchy, Christine; Ekici, Arif Bülent; Ferrazzi, Fulvia; Zweier, Christiane (Scientific Reports, 2020)
Neurodevelopmental disorders (NDDs) are clinically and genetically extremely heterogeneous with shared phenotypes often associated with genes from the same networks. Mutations in TCF4, MEF2C, UBE3A, ZEB2 or ATRX cause phenotypically overlapping, syndromic forms of NDDs with severe intellectual disability, epilepsy and microcephaly. To characterize potential functional links between these genes/proteins, we screened for genetic interactions in Drosophila melanogaster. We induced ubiquitous or tissue specific knockdown or overexpression of each single orthologous gene (Da, Mef2, Ube3a, Zfh1, XNP) and in pairwise combinations. Subsequently, we assessed parameters such as lethality, wing and eye morphology, neuromuscular junction morphology, bang sensitivity and climbing behaviour in comparison between single and pairwise dosage manipulations. We found most stringent evidence for genetic interaction between Ube3a and Mef2 as simultaneous dosage manipulation in different tissues including glia, wing and eye resulted in multiple phenotype modifications. We subsequently found evidence for physical interaction between UBE3A and MEF2C also in human cells. Systematic pairwise assessment of the Drosophila orthologues of five genes implicated in clinically overlapping, severe NDDs and subsequent confirmation in a human cell line revealed interactions between UBE3A/Ube3a and MEF2C/Mef2, thus contributing to the characterization of the underlying molecular commonalities.<br
Keywords: Genetic interaction; Medical genetics; Molecular medicine; Neurodevelopmental disorders

Genetic Interaction screen for severe neurodevelopmental disorders reveals a functional link between Ube3a and Mef2 in Drosophila melanogaster - Straub, Jonas; Sauerer, Tatjana; Fliedner, Anna; Distel, Laila; Suchy, C.; Ekici, Arif Bülent; Ferrazzi, Fulvia; Gregor, Anne; Zweier, Christiane (52nd Conference of the European-Society-of-Human-Genetics (ESHG), 2019)
CRIS-Team WoS Importer:2019-10-25

Genome Sequence of the Alcelaphine Gammaherpesvirus 1 Attenuated Laboratory Strain WC11 - Enßer, Armin (Genome Announcements, 2017)
The complete genome sequence of the alcelaphine gammaherpesvirus 1 (AIHV-1) attenuated laboratory strain WC11 was determined from purified virion DNA. The viral light DNA (L-DNA) genome of 127,215 bp is mostly conserved compared to the pathogenic strain C500; however, 3.3 kb is deleted in two regions, affecting 4 of 10 AIHV-1-specific open reading frames.
EVALuna2:35814

Genome-wide identification of disease-causing copy number variations in 450 individuals with anorectal malformations - Fabian, Julia; Dworschak, Gabriel C.; Waffenschmidt, Lea; Schierbaum, Luca; Bendixen, Charlotte; Heilmann-Heimbach, Stefanie; Sivalingam, Sugirthan; Buness, Andreas; Schwarzer, Nicole; Boemers, Thomas M.; Schmiedeke, Eberhard; Neser, Jorg; et al. (European Journal of Human Genetics, 2022)
Anorectal malformations (ARM) represent a spectrum of rare malformations originating from a perturbated development of the embryonic hindgut. Approximately 60% occur as a part of a defined genetic syndrome or within the spectrum of additional congenital anomalies. Rare copy number variations (CNVs) have been associated with both syndromic and non-syndromic forms. The present study represents the largest study to date to explore the contribution of CNVs to the expression of ARMs. SNP-array-based molecular karyotyping was applied in 450 individuals with ARM and 4392 healthy controls. CNVs were identified from raw intensity data using PennCNV. Overlapping CNVs between cases and controls were discarded. Remaining CNVs were filtered using a stringent filter algorithm of nine filter steps. Prioritized CNVs were confirmed using qPCR. Filtering prioritized and qPCR confirmed four microscopic chromosomal anomalies and nine submicroscopic CNVs comprising seven microdeletions (del2p13.2, del4p16.2, del7q31.33, del9p24.1, del16q12.1, del18q32, del22q11.21) and two microduplications (dup2p13.2, dup17q12) in 14 individuals (12 singletons and one affected sib-pair). Within these CNVs, based on their embryonic expression data and function, we suggest FOXK2, LPP, and SALL3 as putative candidate genes. Overall, our CNV analysis identified putative microscopic and submicroscopic chromosomal rearrangements in 3% of cases. Functional characterization and re-sequencing of suggested candidate genes is warranted.
CRIS-Team Scopus Importer:2022-11-18

Glomerular Endothelial Cell-Derived microRNA-192 Regulates Nephronectin Expression in Idiopathic Membranous Glomerulonephritis. - Müller-Deile, Janina; Sopel, Nina; Ohs, Alexandra; Rose, Victoria; Gröner, Marwin; Wrede, Christoph; Hegermann, Jan; Daniel, Christoph; Amann, Kerstin Ute; Zahner, Gunther; Schiffer, Mario (Journal of the American Society of Nephrology, 2021)
BACKGROUND: Autoantibodies binding to podocyte antigens cause idiopathic membranous glomerulonephritis (iMGN). However, it remains elusive how autoantibodies reach the subepithelial space because the glomerular filtration barrier (GFB) is size selective and almost impermeable for antibodies. METHODS: Kidney biopsies from patients with iMGN, cell culture, zebrafish, and mouse models were used to investigate the role of nephronectin (NPNT) regulating microRNAs (miRs) for the GFB. RESULTS: Glomerular endothelial cell (GEC)-derived miR-192-5p and podocyte-derived miR-378a-3p are upregulated in urine and glomeruli of patients with iMGN, whereas glomerular NPNT is reduced. Overexpression of miR-192-5p and morpholino-mediated npnt knockdown induced edema, proteinuria, and podocyte effacement similar to podocyte-derived miR-378a-3p in zebrafish. Structural changes of the glomerular basement membrane (GBM) with increased lucidity, splitting, and lamellation, especially of the lamina rara interna, similar to ultrastructural findings seen in advanced stages of iMGN, were found. IgG-size nanoparticles accumulated in lucidity areas of the lamina rara interna and lamina densa of the GBM in npnt-knockdown zebrafish models. Loss of slit diaphragm proteins and severe structural impairment of the GBM were further confirmed in podocyte-specific Npnt knockout mice. GECs downregulate podocyte NPNT by transfer of miR-192-5p-containing exosomes in a paracrine manner. CONCLUSIONS: Podocyte NPNT is important for proper glomerular filter function and GBM structure and is regulated by GEC-derived miR-192-5p and podocyte-derived miR-378a-3p. We hypothesize that loss of NPNT in the GBM is an important part of the initial pathophysiology of iMGN and enables autoantigenicity of podocyte antigens and subepithelial immune complex deposition in iMGN.
EVALuna2:483425

GLUT1-mediated glucose import in B cells is critical for anaplerotic balance and humoral immunity - Bierling, Theresa; Gumann, Amelie; Ottmann, Shannon; Schulz, Sebastian; Weckwerth, Leonie; Thomas, Jana; Geßner, Arne; Wichert, Magdalena; Kuwert, Frederic; Rost, Franziska; Hauke, Manuela; Freudenreich, Tatjana; et al. (Cell Reports, 2024)
Glucose uptake increases during B cell activation and antibody-secreting cell (ASC) differentiation, but conflicting findings prevent a clear metabolic profile at different stages of B cell activation. Deletion of the glucose transporter type 1 (GLUT1) gene in mature B cells (GLUT1-cKO) results in normal B cell development, but it reduces germinal center B cells and ASCs. GLUT1-cKO mice show decreased antigen-specific antibody titers after vaccination. In vitro, GLUT1-deficient B cells show impaired activation, whereas established plasmablasts abolish glycolysis, relying on mitochondrial activity and fatty acids. Transcriptomics and metabolomics reveal an altered anaplerotic balance in GLUT1-deficient ASCs. Despite attempts to compensate for glucose deprivation by increasing mitochondrial mass and gene expression associated with glycolysis, the tricarboxylic acid cycle, and hexosamine synthesis, GLUT1-deficient ASCs lack the metabolites for energy production and mitochondrial respiration, limiting protein synthesis. We identify GLUT1 as a critical metabolic player defining the germinal center response and humoral immunity.
CRIS-Team Scopus Importer:2024-02-23
Keywords: adaptive immune response; antibody-secreting cell; CP: Immunology; CP: Metabolism; glucose transporter type 1; GLUT1; glycolysis; metabolism; mitochondrial respiration; plasma cell; plasmablast

Glutamic Acid Residues in HIV-1 p6 Regulate Virus Budding and Membrane Association of Gag - Friedrich, Melanie; Setz, Christian; Hahn, Friedrich; Matthaei, Alina; Fraedrich, Kirsten; Rauch, Pia; Henklein, Petra; Traxdorf, Maximilian; Fossen, Torgils; Schubert, Ulrich (Viruses, 2016)
The HIV-1 Gag p6 protein regulates the final abscission step of nascent virions from the cell membrane by the action of its two late (L-) domains, which recruit Tsg101 and ALIX, components of the ESCRT system. Even though p6 consists of only 52 amino acids, it is encoded by one of the most polymorphic regions of the HIV-1 gag gene and undergoes various posttranslational modifications including sumoylation, ubiquitination, and phosphorylation. In addition, it mediates the incorporation of the HIV-1 accessory protein Vpr into budding virions. Despite its small size, p6 exhibits an unusually high charge density. In this study, we show that mutation of the conserved glutamic acids within p6 increases the membrane association of Pr55 Gag followed by enhanced polyubiquitination and MHC-I antigen presentation of Gag-derived epitopes, possibly due to prolonged exposure to membrane bound E3 ligases. The replication capacity of the total glutamic acid mutant E0A was almost completely impaired, which was accompanied by defective virus release that could not be rescued by ALIX overexpression. Altogether, our data indicate that the glutamic acids within p6 contribute to the late steps of viral replication and may contribute to the interaction of Gag with the plasma membrane.
EVALuna2:8333

Guidelines for DC preparation and flow cytometric analysis of human lymphohematopoietic tissues - Heger, Lukas; Dudziak, Diana; Amon, Lukas; Hatscher, Lukas; Kaszubowski, Tomasz; Lehmann, Christian (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. Within this article, detailed protocols are presented that allow for the generation of single cell suspensions from human lymphohematopoietic tissues including blood, spleen, thymus, and tonsils with a focus on the subsequent analysis of DC via flow cytometry, as well as flow cytometric cell sorting of primary human DC. Further, prepared single cell suspensions as well as cell sorter-purified DC can be subjected to other applications including cellular enrichment procedures, RNA sequencing, functional assays, and many more. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
CRIS-Team WoS Importer:2023-01-13

Guidelines for DC preparation and flow cytometry analysis of mouse lymphohematopoietic tissues - Amon, Lukas; Dudziak, Diana; Backer, Ronald A. A.; Clausen, Bjoern E.; Gmeiner, Christina; Heger, Lukas; Jacobi, Lukas; Lehmann, Christian; Probst, Hans-Christian; Seichter, Anna; Tchitashvili, Giorgi; Tochoedo, Nounagnon Romaric; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human DC from lymphoid organs, and various non-lymphoid tissues. Within this chapter, detailed protocols are presented that allow for the generation of single-cell suspensions from mouse lymphohematopoietic tissues including spleen, peripheral lymph nodes, and thymus, with a focus on the subsequent analysis of DC by flow cytometry. However, prepared single-cell suspensions can be subjected to other applications including sorting and cellular enrichment procedures, RNA sequencing, Western blotting, and many more. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
Created from Fastlane, Scopus look-up
Keywords: dendritic cells; high-parameter flow cytometry; mouse lymphoid tissues; myeloid cells; single-cell suspension preparation

Guidelines for DC preparation and flow cytometry analysis of mouse nonlymphoid tissues - Probst, Hans Christian; Stoitzner, Patrizia; Amon, Lukas; Backer, Ronald A.; Brand, Anna; Chen, Jianzhou; Clausen, Björn E.; Dieckmann, Sophie; Dudziak, Diana; Heger, Lukas; Hodapp, Katrin; Hornsteiner, Florian; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various nonlymphoid tissues. DC are sentinels of the immune system present in almost every mammalian organ. Since they represent a rare cell population, DC need to be extracted from organs with protocols that are specifically developed for each tissue. This article provides detailed protocols for the preparation of single-cell suspensions from various mouse nonlymphoid tissues, including skin, intestine, lung, kidney, mammary glands, oral mucosa and transplantable tumors. Furthermore, our guidelines include comprehensive protocols for multiplex flow cytometry analysis of DC subsets and feature top tricks for their proper discrimination from other myeloid cells. With this collection, we provide guidelines for in-depth analysis of DC subsets that will advance our understanding of their respective roles in healthy and diseased tissues. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all coauthors, making it an essential resource for basic and clinical DC immunologists.
Created from Fastlane, Scopus look-up
Keywords: Dendritic cells; Discrimination of dendritic cell subsets; Mouse nonlymphoid tissue; Multiplex flow cytometry analysis; Tissue digestion protocols

Guidelines for mouse and human DC generation - Lutz, Manfred B.; Ali, Shafaqat; Audiger, Cindy; Autenrieth, Stella E.; Berod, Luciana; Bigley, Venetia; Cyran, Laura; Dalod, Marc; Dörrie, Jan; Dudziak, Diana; Florez-Grau, Georgina; Giusiano, Lucila; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. This article provides protocols with top ticks and pitfalls for preparation and successful generation of mouse and human DC from different cellular sources, such as murine BM and HoxB8 cells, as well as human CD34(+) cells from cord blood, BM, and peripheral blood or peripheral blood monocytes. We describe murine cDC1, cDC2, and pDC generation with Flt3L and the generation of BM-derived DC with GM-CSF. Protocols for human DC generation focus on CD34(+) cell culture on OP9 cell layers for cDC1, cDC2, cDC3, and pDC subset generation and DC generation from peripheral blood monocytes (MoDC). Additional protocols include enrichment of murine DC subsets, CRISPR/Cas9 editing, and clinical grade human DC generation. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
CRIS-Team WoS Importer:2022-11-11

Gαi2-induced conductin/axin2 condensates inhibit Wnt/β-catenin signaling and suppress cancer growth - Miete, Cezanne; Solis, Gonzalo P.; Koval, Alexey; Brückner, Martina; Katanaev, Vladimir L.; Behrens, Jürgen; Bernkopf, Dominic (Nature Communications, 2022)
Conductin/axin2 is a scaffold protein negatively regulating the pro-proliferative Wnt/β-catenin signaling pathway. Accumulation of scaffold proteins in condensates frequently increases their activity, but whether condensation contributes to Wnt pathway inhibition by conductin remains unclear. Here, we show that the Gαi2 subunit of trimeric G-proteins induces conductin condensation by targeting a polymerization-inhibiting aggregon in its RGS domain, thereby promoting conductin-mediated β-catenin degradation. Consistently, transient Gαi2 expression inhibited, whereas knockdown activated Wnt signaling via conductin. Colorectal cancers appear to evade Gαi2-induced Wnt pathway suppression by decreased Gαi2 expression and inactivating mutations, associated with shorter patient survival. Notably, the Gαi2-activating drug guanabenz inhibited Wnt signaling via conductin, consequently reducing colorectal cancer growth in vitro and in mouse models. In summary, we demonstrate Wnt pathway inhibition via Gαi2-triggered conductin condensation, suggesting a tumor suppressor function for Gαi2 in colorectal cancer, and pointing to the FDA-approved drug guanabenz for targeted cancer therapy.
CRIS-Team Scopus Importer:2022-02-11

Haploinsufficiency of NR4A2 is associated with a neurodevelopmental phenotype with prominent language impairment - Reuter, Miriam; Krumbiegel, Mandy; Schlueter, Gregor; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2017)
Non-recurrent deletions in 2q24.1, minimally overlapping two genes, NR4A2 and GPD2, were recently described in individuals with language impairment and behavioral and cognitive symptoms. We herewith report on a female patient with a similar phenotype of severe language and mild cognitive impairment, in whom we identified a de novo deletion covering only NR4A2. NR4A2 encodes a transcription factor highly expressed in brain regions critical for speech and language and implicated in dopaminergic neuronal development. Our findings of a de novo deletion of NR4A2 in an individual with mild intellectual disability and prominent speech and language impairment provides further evidence for NR4A2 haploinsufficiency being causative for neurodevelopmental and particularly language phenotypes.
EVALuna2:9359

Harnessing the complete repertoire of conventional dendritic cell functions for cancer immunotherapy - Amon, Lukas; Hatscher, Lukas; Heger, Lukas; Dudziak, Diana; Lehmann, Christian (Pharmaceutics, 2020)
The onset of checkpoint inhibition revolutionized the treatment of cancer. However, studies from the last decade suggested that the sole enhancement of T cell functionality might not suffice to fight malignancies in all individuals. Dendritic cells (DCs) are not only part of the innate immune system, but also generals of adaptive immunity and they orchestrate the de novo induction of tolerogenic and immunogenic T cell responses. Thus, combinatorial approaches addressing DCs and T cells in parallel represent an attractive strategy to achieve higher response rates across patients. However, this requires profound knowledge about the dynamic interplay of DCs, T cells, other immune and tumor cells. Here, we summarize the DC subsets present in mice and men and highlight conserved and divergent characteristics between different subsets and species. Thereby, we supply a resource of the molecular players involved in key functional features of DCs ranging from their sentinel function, the translation of the sensed environment at the DC:T cell interface to the resulting specialized T cell effector modules, as well as the influence of the tumor microenvironment on the DC function. As of today, mostly monocyte derived dendritic cells (moDCs) are used in autologous cell therapies after tumor antigen loading. While showing encouraging results in a fraction of patients, the overall clinical response rate is still not optimal. By disentangling the general aspects of DC biology, we provide rationales for the design of next generation DC vaccines enabling to exploit and manipulate the described pathways for the purpose of cancer immunotherapy in vivo. Finally, we discuss how DC-based vaccines might synergize with checkpoint inhibition in the treatment of malignant diseases.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Antigen targeting; Cancer therapy; Checkpoint inhibition; Dendritic cells; Pattern recognition receptors; T cells; Tumor microenvironment; Vaccination

Harnessing the Participation of Dendritic Cells in Immunity and Tolerance - Boscardin, Silvia Beatriz; Dudziak, Diana; Muenz, Christian; Rosa, Daniela Santoro (Frontiers in Immunology, 2020)
CRIS-Team Scopus Importer:2020-11-13
Keywords: antigen presentation; DC subtypes; dendritic cell; dendritic cell activation; dendritic cell vaccine therapy

HDAC inhibitors Panobinostat and Romidepsin enhance tax transcription in HTLV-1-infected cell lines and freshly isolated patients' T-cells - Schnell, Annika; Kohrt, Stephan; Aristodemou, Aris; Taylor, Graham P.; Bangham, Charles R. M.; Thoma-Kreß, Andrea (Frontiers in Immunology, 2022)
The viral transactivator Tax plays a key role in HTLV-1 reactivation and de novo infection. Previous approaches focused on the histone deacetylase inhibitor (HDACi) Valproate as a latency-reversing agent to boost Tax expression and expose infected cells to the host's immune response. However, following treatment with Valproate proviral load decreases in patients with HAM/TSP were only transient. Here, we hypothesize that other compounds, including more potent and selective HDACi, might prove superior to Valproate in manipulating Tax expression. Thus, a panel of HDACi (Vorinostat/SAHA/Zolinza, Panobinostat/LBH589/Farydak, Belinostat/PXD101/Beleodaq, Valproate, Entinostat/MS-275, Romidepsin/FK228/Istodax, and MC1568) was selected and tested for toxicity and potency in enhancing Tax expression. The impact of the compounds was evaluated in different model systems, including transiently transfected T-cells, chronically HTLV-1-infected T-cell lines, and freshly isolated PBMCs from HTLV-1 carriers ex vivo. We identified the pan-HDACi Panobinostat and class I HDACi Romidepsin as particularly potent agents at raising Tax expression. qRT-PCR analysis revealed that these inhibitors considerably boost tax and Tax-target gene transcription. However, despite this significant increase in tax transcription and histone acetylation, protein levels of Tax were only moderately enhanced. In conclusion, these data demonstrate the ability of Panobinostat and Romidepsin to manipulate Tax expression and provide a foundation for further research into eliminating latently infected cells. These findings also contribute to a better understanding of conditions limiting transcription and translation of viral gene products.
CRIS-Team WoS Importer:2022-09-16

HIF-1α promotes cyst progression in a mouse model of autosomal dominant polycystic kidney disease - Kraus, Andre; Peters, Dorien J. M.; Klanke, Bernd; Weidemann, Alexander; Willam, Carsten; Schley, Gunnar; Kunzelmann, Karl; Eckardt, Kai-Uwe; Buchholz, Björn (Kidney International, 2018)
Autosomal dominant polycystic kidney disease (ADPKD) is mainly caused by mutations of the PKD1 gene and characterized by growth of bilateral renal cysts. Cyst growth is accompanied by regional hypoxia and induction of hypoxia-inducible factor (HIF)-1α in cyst-lining epithelial cells. To determine the relevance of HIF-1α for cyst growth in vivo we used an inducible kidney epithelium-specific knockout mouse to delete Pkd1 at postnatal day 20 or 35 to induce polycystic kidney disease of different severity and analyzed the effects of Hif-1α co-deletion and HIF-1α stabilization using a prolyl-hydroxylase inhibitor. HIF-1α expression was enhanced in kidneys with progressive cyst growth induced by early Pkd1 deletion, but unchanged in the milder phenotype induced by later Pkd1 deletion. Hif-1α co-deletion significantly attenuated cyst growth in the severe, but not in the mild, phenotype. Application of a prolyl-hydroxylase inhibitor resulted in severe aggravation of the mild phenotype with rapid loss of renal function. HIF-1α expression was associated with induction of genes that mediate calcium-activated chloride secretion. Thus, HIF-1α does not seem to play a role in early cyst formation, but accelerates cyst growth during progressive polycystic kidney disease. This novel mechanism of cyst growth may qualify as a therapeutic target.
EVALuna2:215684
Keywords: hypoxia; hypoxia-inducible factor-1 alpha; polycystic kidney disease; prolyl-hydroxylase inhibitors

High fat diet increases melanoma cell growth in the bone marrow by inducing osteopontin and interleukin 6 - Chen, Guangliang; Luo, Yubin; Eriksson, Daniel; Meng, Xianyi; Qian, Cheng; Bäuerle, Tobias; Chen, Xiao-Xiang; Schett, Georg; Bozec, Aline (Oncotarget, 2016)
The impact of metabolic stress induced by obesity on the bone marrow melanoma niche is largely unknown. Here we employed diet induced obese mice model, where mice received high-fat (HFD) or normal diet (ND) for 6 weeks before challenge with B16F10 melanoma cells. Tumor size, bone loss and osteoclasts numbers were assessed histologically in the tibial bones. For defining the molecular pathway, osteopontin knock-out mice, interleukin 6 neutralizing antibody or Janus kinase 2 inhibition were carried out in the same model. Mechanistic studies such as adipocyte-melanoma co-cultures for defining adipocyte induced changes of tumor cell proliferation and expression profiles were also performed. As results, HFD enhanced melanoma burden in bone by increasing tumor area and osteoclast numbers. This process was associated with higher numbers of bone marrow adipocytes expressing IL-6 in direct vicinity to tumor cells. Inhibition of IL-6 or of downstream JAK2 blocked HFD-induced tumor progression. Furthermore, the phenotypic changes of melanoma cells triggered macrophage and osteoclast accumulation accompanied by increased osteopontin expression. Osteopontin triggered osteoclastogenesis and also exerted a positive feedback loop to tumor cells, which was abrogated in its absence. Metabolic stress by HFD promotes melanoma growth in the bone marrow by an increase in bone marrow adipocytes and IL-6-JAK2-osteopontin mediated activation of tumor cells and osteoclast differentiation.
EVALuna2:13267

Highly Conserved Interaction Profiles between Clinically Relevant Mutants of the Cytomegalovirus CDK-like Kinase pUL97 and Human Cyclins: Functional Significance of Cyclin H - Schütz, Martin; Müller, Regina; Socher, Eileen; Wangen, Christina; Full, Florian; Wyler, Emanuel; Wong, Diana D.; Scherer, Myriam; Stamminger, Thomas; Chou, Sunwen; Rawlinson, William D.; Hamilton, Stuart T.; et al. (International Journal of Molecular Sciences, 2022)
The complex host interaction network of human cytomegalovirus (HCMV) involves the regulatory protein kinase pUL97, which represents a viral cyclin-dependent kinase (CDK) ortholog. pUL97 interacts with the three human cyclin types T1, H, and B1, whereby the binding region of cyclin T1 and the pUL97 oligomerization region were both assigned to amino acids 231-280. We further addressed the question of whether HCMVs harboring mutations in ORF-UL97, i.e., short deletions or resistance-conferring point mutations, are affected in the interaction with human cyclins and viral replication. To this end, clinically relevant UL97 drug-resistance-conferring mutants were analyzed by whole-genome sequencing and used for genetic marker transfer experiments. The recombinant HCMVs indicated conservation of pUL97–cyclin interaction, since all viral UL97 point mutants continued to interact with the analyzed cyclin types and exerted wild-type-like replication fitness. In comparison, recombinant HCMVs UL97 Δ231-280 and also the smaler deletion Δ236-275, but not Δ241-270, lost interaction with cyclins T1 and H, showed impaired replication efficiency, and also exhibited reduced kinase activity. Moreover, a cellular knock-out of cyclins B1 or T1 did not alter HCMV replication phenotypes or pUL97 kinase activity, possibly indicating alternative, compensatory pUL97–cyclin interactions. In contrast, however, cyclin H knock-out, similar to virus deletion mutants in the pUL97–cyclin H binding region, exhibited strong defective phenotypes of HCMV replication, as supported by reduced pUL97 kinase activity in a cyclin H-dependent coexpression setting. Thus, cyclin H proved to be a very relevant determinant of pUL97 kinase activity and viral replication efficiency. As a conclusion, the results provide evidence for the functional importance of pUL97–cyclin interaction. High selective pressure on the formation of pUL97–cyclin complexes was identified by the use of clinically relevant mutants<br

High-resolution label-free mapping of murine kidney vasculature by raster-scanning optoacoustic mesoscopy: an ex vivo study - Goebel, Colin A.; Brown, Emma; Fahlbusch, Fabian; Wagner, Alexandra; Buehler, Adrian; Raupach, Thomas; Hohmann, Martin; Späth, Moritz; Burton, Neal; Wölfle, Joachim; Schmidt, Michael; Hartner, Andrea; et al. (Molecular and Cellular Pediatrics, 2022)
Background: Chronic kidney disease (CKD) is a global burden affecting both children and adults. Novel imaging modalities hold great promise to visualize and quantify structural, functional, and molecular organ damage. The aim of the study was to visualize and quantify murine renal vasculature using label-free raster scanning optoacoustic mesoscopy (RSOM) in explanted organs from mice with renal injury. Material and methods: For the experiments, freshly bisected kidneys of alpha 8 integrin knock-out (KO) and wildtype mice (WT) were used. A total of n=7 female (n=4 KO, n=3 WT) and n=6 male animals (n=2 KO, n=4 WT) aged 6 weeks were examined with RSOM optoacoustic imaging systems (RSOM Explorer P50 at SWL 532nm and/or ms-P50 imaging system at 532 nm, 555 nm, 579 nm, and 606 nm). Images were reconstructed using a dedicated software, analyzed for size and vascular area and compared to standard histologic sections. Results: RSOM enabled mapping of murine kidney size and vascular area, revealing differences between kidney sizes of male (m) and female (f) mice (merged frequencies (MF) f vs. m: 52.42±6.24 mm2 vs. 69.18±15.96 mm2, p=0.0156) and absolute vascular area (MF f vs. m: 35.67±4.22 mm2 vs. 49.07±13.48 mm2, p=0.0036). Without respect to sex, the absolute kidney area was found to be smaller in knock-out (KO) than in wildtype (WT) mice (WT vs. KO: MF: p=0.0255) and showed a similar trend for the relative vessel area (WT vs. KO: MF p=0.0031). Also the absolute vessel areas of KO compared to WT were found significantly different (MF p=0.0089). A significant decrease in absolute vessel area was found in KO compared to WT male mice (MF WT vs. KO: 54.37±9.35 mm2 vs. 34.93±13.82 mm2, p=0.0232). In addition, multispectral RSOM allowed visualization of oxygenated and deoxygenated parenchymal regions by spectral unmixing. Conclusion: This study demonstrates the capability of RSOM for label-free visualization of differences in vascular morphology in ex vivo murine renal tissue at high resolution. Due to its scalability optoacoustic imaging provides an emerging modality with potential for further preclinical and clinical imaging applications.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Chronic kidney disease; Ex vivo kidney imaging; msRSOM; Optoacoustic; Photoacoustic; Raster scanning optoacoustic mesoscopy; RSOM

HIV-1 viral protein R (Vpr) induces fatty liver in mice via LXRα and PPARα dysregulation: implications for HIV-specific pathogenesis of NAFLD - Agarwal, Neeti; Iyer, Dinakar; Gabbi, Chiara; Saha, Pradip; Patel, Sanjeet G; Mo, Qianxing; Chang, Benny; Goswami, Biman; Schubert, Ulrich; Kopp, Jeffrey B.; Lewis, Dorothy E; Balasubramanyam, Ashok (Scientific Reports, 2017)
HIV patients develop hepatic steatosis. We investigated hepatic steatosis in transgenic mice expressing the HIV-1 accessory protein Vpr (Vpr-Tg) in liver and adipose tissues, and WT mice infused with synthetic Vpr. Vpr-Tg mice developed increased liver triglyceride content and elevated ALT, bilirubin and alkaline phosphatase due to three hepatic defects: 1.6-fold accelerated de novo lipogenesis (DNL), 45% slower fatty acid ß-oxidation, and 40% decreased VLDL-triglyceride export. Accelerated hepatic DNL was due to coactivation by Vpr of liver X receptor-α (LXRα) with increased expression of its lipogenic targets Srebp1c, Chrebp, Lpk, Dgat, Fasn and Scd1, and intranuclear SREBP1c and ChREBP. Vpr enhanced association of LXRα with Lxrα and Srebp1c promoters, increased LXRE-LXRα binding, and broadly altered hepatic expression of LXRα-regulated lipid metabolic genes. Diminished hepatic fatty acid ß-oxidation was associated with decreased mRNA expression of Pparα and its targets Cpt1, Aox, Lcad, Ehhadh, Hsd10 and Acaa2, and blunted VLDL export with decreased expression of Mttp and its product microsomal triglyceride transfer protein. With our previous findings that Vpr circulates in HIV patients (including those with undetectable plasma HIV-1 RNA), co-regulates the glucocorticoid receptor and PPARγ and transduces hepatocytes, these data indicate a potential role for Vpr in HIV-associated fatty liver disease.
EVALuna2:35296

HIV Activates the Tyrosine Kinase Hck to Secrete ADAM Protease-Containing Extracellular Vesicles - Lee, J. H.; Zhao, Z.; Ostalecki, Christian; Kesti, T.; Bruns, Heiko; Simon, B.; Harrer, Thomas; Saksela, K.; Baur, A. S. (EBioMedicine, 2018)
EVALuna2:13527

Hobit- and Blimp-1-driven CD4(+) tissue-resident memory T cells control chronic intestinal inflammation - Zundler, Sebastian; Becker, Emily; Spocinska, Marta; Slawik, Monique; Parga-Vidal, Loreto; Stark, Regina; Wiendl, Maximilian; Atreya, Raja; Rath, Timo; Leppkes, Moritz; Hildner, Kai; Lopez Posadas, Rocío; et al. (Nature Immunology, 2019)
Although tissue-resident memory T cells (T-RM cells) have been shown to regulate host protection in infectious disorders, their function in inflammatory bowel disease (IBD) remains to be investigated. Here we characterized T-RM cells in human IBD and in experimental models of intestinal inflammation. Pro-inflammatory T-RM cells accumulated in the mucosa of patients with IBD, and the presence of CD4(+)CD69(+)CD103(+) T-RM cells was predictive of the development of flares. In vivo, functional impairment of T-RM cells in mice with double knockout of the T-RM-cell-associated transcription factors Hobit and Blimp-1 attenuated disease in several models of colitis, due to impaired cross-talk between the adaptive and innate immune system. Finally, depletion of T-RM cells led to a suppression of colitis activity. Together, our data demonstrate a central role for T-RM cells in the pathogenesis of chronic intestinal inflammation and suggest that these cells could be targets for future therapeutic approaches in IBD.
CRIS-Team WoS Importer:2019-03-06

Human alpha-synuclein overexpressing MBP29 mice mimic functional and structural hallmarks of the cerebellar subtype of multiple system atrophy - Mészáros, Lisa; Riemenschneider, Markus J.; Gaßner, Heiko; Marxreiter, Franz; von Hörsten, Stephan; Hoffmann, Alana; Winkler, Jürgen (Acta Neuropathologica Communications, 2021)
Multiple system atrophy (MSA) is a rare, but fatal atypical parkinsonian disorder. The prototypical pathological hallmark are oligodendroglial cytoplasmic inclusions (GCIs) containing alpha-synuclein (α-syn). Currently, two MSA phenotypes are classified: the parkinsonian (MSA-P) and the cerebellar subtype (MSA-C), clinically characterized by predominant parkinsonism or cerebellar ataxia, respectively. Previous studies have shown that the transgenic MSA mouse model overexpressing human α-syn controlled by the oligodendroglial myelin basic protein (MBP) promoter (MBP29-hα-syn mice) mirrors crucial characteristics of the MSA-P subtype. However, it remains elusive, whether this model recapitulates important features of the MSA-C-related phenotype. First, we examined MSA-C-associated cerebellar pathology using human post-mortem tissue of MSA-C patients and controls. We observed the prototypical GCI pathology and a preserved number of oligodendrocytes in the cerebellar white matter (cbw) accompanied by severe myelin deficit, microgliosis, and a profound loss of Purkinje cells. Secondly, we phenotypically characterized MBP29-hα-syn mice using a dual approach: structural analysis of the hindbrain and functional assessment of gait. Matching the neuropathological features of MSA-C, GCI pathology within the cbw of MBP29-hα-syn mice was accompanied by a severe myelin deficit despite an increased number of oligodendrocytes and a high number of myeloid cells even at an early disease stage. Intriguingly, MBP29-hα-syn mice developed a significant loss of Purkinje cells at a more advanced disease stage. Catwalk XT gait analysis revealed decreased walking speed, increased stride length and width between hind paws. In addition, less dual diagonal support was observed toward more dual lateral and three paw support. Taken together, this wide-based and unsteady gait reflects cerebellar ataxia presumably linked to the cerebellar pathology in MBP29-hα-syn mice. In conclusion, the present study strongly supports the notion that the MBP29-hα-syn mouse model mimics important characteristics of the MSA-C subtype providing a powerful preclinical tool for evaluating future interventional strategies.[Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-04-30
Keywords: Cerebellar ataxia; Cerebellar pathology; Gait analysis; Multiple system atrophy

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, Jil; Lehmann, Christian; Heger, Lukas; Eissing, Nathalie; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (Science immunology, 2016)
In mice, conventional and plasmacytoid dendritic cells (DCs) derive from separate hematopoietic precursors before they migrate to peripheral tissues. Moreover, two classes of conventional DCs (cDC1 and cDC2 DCs) and one class of plasmacytoid DCs (pDCs) have been shown to be transcriptionally and functionally distinct entities. In humans, these three DC subtypes can be identified using the cell surface markers CD1c (cDC2), CD141 (cDC1), and CD303 (pDCs), albeit it remains elusive whether DC functionality is mainly determined by ontogeny or the tissue microenvironment. By phenotypic and transcriptional profiling of these three DC subtypes in different human tissues derived from a large number of human individuals, we demonstrate that DC subpopulations in organs of the lymphohematopoietic system (spleen, thymus, and blood) are strongly defined by ontogeny rather than by signals from the microenvironment. In contrast, DC subsets derived from human lung or skin differed substantially, strongly arguing that DCs react toward modulatory signals from tissue microenvironments. Collectively, the data obtained in this study may serve as a major resource to guide further studies into human DC biology during homeostasis and inflammatio
EVALuna2:6852

Human sensory neurons derived from pluripotent stem cells for disease modelling and personalized medicine - Lampert, Angelika; Bennett, David L.; McDermott, Lucy A.; Neureiter, Anika; Eberhardt, Esther; Winner, Beate; Zenke, Martin (Neurobiology of pain (Cambridge, Mass.), 2020)
In this concise Mini-Review we will summarize ongoing developments of new techniques to study physiology and pathophysiology of the peripheral sensory nervous system in human stem cell derived models. We will focus on recent developments of reprogramming somatic cells into induced pluripotent stem cells, neural differentiation towards neuronal progenitors and human sensory neurons. We will sum up the high potential of this new technique for disease modelling of human neuropathies with a focus on genetic pain syndromes, such as gain- and loss-of-function mutations in voltage-gated sodium channels. The stem cell derived human sensory neurons are used for drug testing and we will summarize their usefulness for individualized treatment identification in patients with neuropathic pain. The review will give an outlook on potential application of this technique as companion diagnostics and for personalized medicine.
Created from Fastlane, Scopus look-up
Keywords: Disease modelling; iPSC; Pain; Peripheral neuron; Stem cell differentiation

Hurdling senescence: hur breaks braf-induced senescence in melanocytes and supports melanoma growth - Liebig, Janika; Kuphal, Silke; Boßerhoff, Anja Katrin (Cancers, 2020)
In addition to genetic changes, post-transcriptional events strongly contribute to the progression of malignant tumors. The RNA-binding protein HuR (ELAVL1) is able to bind and stabilize a large group of target mRNAs, which contain AU-rich elements (ARE) in their 3′- untranslated region. We found HuR to be upregulated in malignant melanoma in vitro and in vivo, significantly correlating with progression in vivo. Additionally, we could show that miR-194-5p can regulate HuR expression level. HuR knockdown in melanoma cells led to the suppression of proliferation and the induction of cellular senescence. Interestingly, HuR overexpression was sufficient to inhibit senescence in BRAFV600E -expressing melanocytes and to force their growth. Here, MITF (Microphthalmia-associated transcription factor), a key player in suppressing senescence and an ARE containing transcript, is positively regulated by HuR. Our results show for the first time that the overexpression of HuR is an important part of the regulatory pathway in the development of malignant melanoma and functions as a switch to overcome oncogene-induced senescence and to support melanoma formation. These newly defined alterations may provide possibilities for innovative therapeutic approaches.
CRIS-Team Scopus Importer:2020-06-02
Keywords: HuR; Malignant melanoma; Microphthalmia-associated transcription factor; MITF; Oncogene induced senescence

Hybrid reflected-ultrasound computed tomography versus B-mode-ultrasound for muscle scoring in spinal muscular atrophy - Danko, Vera; Jüngert, Jörg M.; Schüssler, Stephanie; Bühler, Adrian; Klett, Daniel; Federle, Anna; Roos, Andreas; Lochmüller, Hanns; Neurath, Markus; Wölfle, Joachim; Trollmann, Regina; Waldner, Maximilian; et al. (Journal of Neuroimaging, 2023)
Background and Purpose: Novel light- and sound-based technologies like multispectral optoacoustic tomography (MSOT) with co-registered reflected-ultrasound computed tomography (RUCT) could add additional value to conventional ultrasound (US) for disease phenotyping in pediatric spinal muscular atrophy (SMA). The aim of this study was to investigate the quality of RUCT compared to US for qualitative and quantitative assessment of imaging neuromuscular disorders. Methods: Subanalyzing the MSOT SMA study, 288 RUCT and 276 US images from 10 SMA patients (mean age 9.0 ± 3.7) and 10 gender- and age-matched healthy volunteers (HV; mean age 8.7 ± 4.3) were analyzed for quantitative (grayscale levels [GSLs]) and qualitative (echogenicity, distribution pattern, Heckmatt scale, and muscle texture) muscle changes. RUCT and US measures were further correlated with clinical standard motor outcomes. Results: Quantitative agreement using GSLs revealed significantly higher GSLs in muscles of SMA patients compared to healthy muscles in both techniques (US mean GSL [SD] SMA vs. HV: 110.70 [27.8] vs. 68.85 [19.2], p <.0001; RUCT mean GSL [SD] SMA vs. HV: 91.81 [21.8] vs. 59.86 [8.2], p <.0001) with good correlation with motor outcome tests, respectively. Qualitative agreement between methods for muscle composition was excellent for differentiation of pathological versus healthy muscles, echogenicity, and distribution pattern, moderate for Heckmatt scale, and poor for muscle texture. Conclusions: The data suggest that RUCT may allow the assessment of basic qualitative and quantitative measures for muscular diseases with comparable results to conventional US.
CRIS-Team Scopus Importer:2023-01-20
Keywords: neuromuscular disorders; optoacoustics; photoacoustics; spinal muscular atrophy; ultrasound

Hypoxia drives glucose transporter 3 expression through hypoxia-inducible transcription factor (HIF)-mediated induction of the long noncoding RNA NICI - Lauer, Victoria; Grampp, Steffen; Platt, James; Lafleur, Veronique; Lombardi, Olivia; Choudhry, Hani; Kranz, Franziska; Hartmann, Arndt; Wullich, Bernd; Yamamoto, Atsushi; Coleman, Mathew L.; Ratcliffe, Peter J.; et al. (Journal of Biological Chemistry, 2020)
Hypoxia-inducible transcription factors (HIFs) directly dictate the expression of multiple RNA species including novel and as yet uncharacterized long noncoding transcripts with unknown function. We used pan-genomic HIF-binding and transcriptomic data to identify a novel long noncoding RNA Noncoding Intergenic Co-Induced transcript (NICI) on chromosome 12p13.31 which is regulated by hypoxia via HIF-1 promoter-binding in multiple cell types. CRISPR/Cas9-mediated deletion of the hypoxia-response element revealed co-regulation of NICI and the neighboring protein-coding gene, solute carrier family 2 member 3 (SLC2A3) which encodes the high-affinity glucose transporter 3 (GLUT3). Knockdown or knockout of NICI attenuated hypoxic induction of SLC2A3, indicating a direct regulatory role of NICI in SLC2A3 expression, which was further evidenced by CRISPR/Cas9-VPR-mediated activation of NICI expression. We also demonstrate that regulation of SLC2A3 is mediated through transcriptional activation rather than posttranscriptional mechanisms because knockout of NICI leads to reduced recruitment of RNA polymerase 2 to the SLC2A3 promoter. Consistent with this we observe NICI-dependent regulation of glucose consumption and cell proliferation. Furthermore, NICI expression is regulated by the von Hippel-Lindau (VHL) tumor suppressor and is highly expressed in clear cell renal cell carcinoma (ccRCC), where SLC2A3 expression is associated with patient prognosis, implying an important role for the HIF/NICI/SLC2A3 axis in this malignancy.
CRIS-Team Scopus Importer:2020-04-07
Keywords: ChIP; ChIP-sequencing (ChIP-Seq); glucose transport; GLUT3; hypoxia; hypoxia-inducible factor (HIF); long noncoding RNA (long ncRNA; lncRNA)

Identification of Novel STAT6-Regulated Proteins in Mouse B Cells by Comparative Transcriptome and Proteome Analysis - Mokada Gopal, Lavanya; Boeser, Alexander; Lehmann, Christian; Drepper, Friedel; Dudziak, Diana; Warscheid, Bettina; Vöhringer, David (Journal of Immunology, 2017)
The transcription factor STAT6 plays a key role in mediating signaling downstream of the receptors for IL-4 and IL-13. In B cells, STAT6 is required for class switch recombination to IgE and for germinal center formation during type 2 immune responses directed against allergens or helminths. In this study, we compared the transcriptomes and proteomes of primary mouse B cells from wild-type and STAT6-deficient mice cultured for 4 d in the presence or absence of IL-4. Microarray analysis revealed that 214 mRNAs were upregulated and 149 were downregulated >3-fold by IL-4 in a STAT6-dependent manner. Across all samples, 5000 proteins were identified by label-free quantitative liquid chromatography/mass spectrometry. A total of 149 proteins was found to be differentially expressed >3-fold between IL-4-stimulated wild-type and STAT6(-/-) B cells (75 upregulated and 74 downregulated). Comparative analysis of the proteome and transcriptome revealed that expression of these proteins was mainly regulated at the transcriptional level, which argues against a major role for posttranscriptional mechanisms that modulate the STAT6-dependent proteome. Nine proteins were selected for confirmation by flow cytometry or Western blot. We show that CD30, CD79b, SLP-76, DEC205, IL-5R?, STAT5, and Thy1 are induced by IL-4 in a STAT6-dependent manner. In contrast, Syk and Fc receptor-like 1 were downregulated. This dataset provides a framework for further functional analysis of newly identified IL-4-regulated proteins in B cells that may contribute to germinal center formation and IgE switching in type 2 immunity.
EVALuna2:25886

Identification of novel targets of miR-622 in hepatocellular carcinoma reveals common regulation of cooperating genes and outlines the oncogenic role of zinc finger CCHC-type containing 11 - Gaza, Anne; Fritz, Valerie; Malek, Lara; Wormser, Laura; Treiber, Nora; Danner, Johannes; Kremer, Andreas E.; Thasler, Wolfgang E.; Siebler, Jürgen; Meister, Gunter; Neurath, Markus F.; Hellerbrand, Claus; et al. (Neoplasia, 2021)
The poor prognosis of advanced hepatocellular carcinoma (HCC) is driven by diverse features including dysregulated microRNAs inducing drug resistance and stemness. Lin-28 homolog A (LIN28A) and its partner zinc finger CCHC-type containing 11 (ZCCHC11) cooperate in binding, oligouridylation and subsequent degradation of tumorsuppressive let-7 precursor microRNAs. Functionally, activation of LIN28A was recently shown to promote stemness and chemoresistance in HCC. However, the expression and regulation of LIN28A in HCC had been unclear. Moreover, the expression, regulation and function of ZCCHC11 in liver cancer remained elusive. In contrast to "one-microRNA-one-target" interactions, we identified common binding sites for miR-622 in both LIN28A and ZCCHC11, suggesting miR-622 to function as a superior pathway regulator. Applying comprehensive microRNA database screening, human hepatocytes and HCC cell lines, patient-derived tissue samples as well as "The Cancer Genome Atlas" (TCGA) patient cohorts, we demonstrated that loss of tumorsuppressive miR-622 mediates derepression and overexpression of LIN28A in HCC. Moreover, the cooperator of LIN28A, ZCCHC11, was newly identified as a prognostic and therapeutic target of miR-622 in liver cancer. Together, identification of novel miR-622 target genes revealed common regulation of cooperating genes and outlines the previously unknown oncogenic role of ZCCHC11 in liver cancer.
CRIS-Team Scopus Importer:2021-05-07
Keywords: drug resistance; HCC; Hepatocellular carcinoma; microRNA; ZCCHC11

Identification of Predictive Markers for Response to Neoadjuvant Chemoradiation in Rectal Carcinomas by Proteomic Isotope Coded Protein Label (ICPL) Analysis - Croner, Roland S.; Sevim, Muezeyyen; Metodiev, Metodi V.; Jo, Peter; Ghadimi, Michael; Schellerer, Vera; Brunner, Michaela; Geppert, Carol-Immanuel; Rau, Tilman; Stürzl, Michael; Naschberger, Elisabeth; Matzel, Klaus E.; et al. (International Journal of Molecular Sciences, 2016)
Neoadjuvant chemoradiation (nCRT) is an established procedure in stage union internationale contre le cancer (UICC) II/III rectal carcinomas. Around 53% of the tumours present with good tumor regression after nCRT, and 8%-15% are complete responders. Reliable selection markers would allow the identification of poor or non-responders prior to therapy. Tumor biopsies were harvested from 20 patients with rectal carcinomas, and stored in liquid nitrogen prior to therapy after obtaining patients' informed consent (Erlangen-No.3784). Patients received standardized nCRT with 5-Fluoruracil (nCRT I) or 5-Fluoruracil ± Oxaliplatin (nCRT II) according to the CAO/ARO/AIO-04 protocol. After surgery, regression grading (Dworak) of the tumors was performed during histopathological examination of the specimens. Tumors were classified as poor (Dworak 1 + 2) or good (Dworak 3 + 4) responders. Laser capture microdissection (LCM) for tumor enrichment was performed on preoperative biopsies. Differences in expressed proteins between poor and good responders to nCRT I and II were identified by proteomic analysis (Isotope Coded Protein Label, ICPL(TM)) and selected markers were validated by immunohistochemistry. Tumors of 10 patients were classified as histopathologically poor (Dworak 1 or 2) and the other 10 tumor samples as histopathologically good (Dworak 3 or 4) responders to nCRT after surgery. Sufficient material in good quality was harvested for ICPL analysis by LCM from all biopsies. We identified 140 differentially regulated proteins regarding the selection criteria and the response to nCRT. Fourteen of these proteins were synchronously up-regulated at least 1.5-fold after nCRT I or nCRT II (e.g., FLNB, TKT, PKM2, SERINB1, IGHG2). Thirty-five proteins showed a complete reciprocal regulation (up or down) after nCRT I or nCRT II and the rest was regulated either according to nCRT I or II. The protein expression of regulated proteins such as PLEC1, TKT, HADHA and TAGLN was validated successfully by immunohistochemistry. ICPL is a valid method to identify differentially expressed proteins in rectal carcinoma tissue between poor vs. good responders to nCRT. The identified protein markers may act as selection criteria for nCRT in the future, but our preliminary findings must be reproduced and validated in a prospective cohort.
EVALuna2:6749

IFN-γ drives inflammatory bowel disease pathogenesis through VE-cadherin-directed vascular barrier disruption. - Langer, Victoria; Vivi, Eugenia; Regensburger, Daniela; Winkler, Thomas; Waldner, Maximilian; Rath, Timo; Schmid, Benjamin; Skottke, Lisa; Lee, Somin; Jeon, Noo Li; Wohlfahrt, Thomas; Kramer, Viktoria; et al. (Journal of Clinical Investigation, 2019)
Inflammatory bowel disease (IBD) is a chronic inflammatory disorder with rising incidence. Diseased tissues are heavily vascularized. Surprisingly, the pathogenic impact of the vasculature in IBD and the underlying regulatory mechanisms remain largely unknown. IFN-γ is a major cytokine in IBD pathogenesis, but in the context of the disease, it is almost exclusively its immune-modulatory and epithelial cell-directed functions that have been considered. Recent studies by our group demonstrated that IFN-γ also exerts potent effects on blood vessels. Based on these considerations, we analyzed the vessel-directed pathogenic functions of IFN-γ and found that it drives IBD pathogenesis through vascular barrier disruption. Specifically, we show that inhibition of the IFN-γ response in vessels by endothelial-specific knockout of IFN-γ receptor 2 ameliorates experimentally induced colitis in mice. IFN-γ acts pathogenic by causing a breakdown of the vascular barrier through disruption of the adherens junction protein VE-cadherin. Notably, intestinal vascular barrier dysfunction was also confirmed in human IBD patients, supporting the clinical relevance of our findings. Treatment with imatinib restored VE-cadherin/adherens junctions, inhibited vascular permeability, and significantly reduced colonic inflammation in experimental colitis. Our findings inaugurate the pathogenic impact of IFN-γ-mediated intestinal vessel activation in IBD and open new avenues for vascular-directed treatment of this disease.

IFN-γ-response mediator GBP-1 represses human cell proliferation by inhibiting the Hippo signaling transcription factor TEAD - Unterer, Bea; Wiesmann, Veit; Gunasekaran, Mekala; Sticht, Heinrich; Tenkerian, Clara; Behrens, Jürgen; Leone, Marina; Engel, Felix; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Wittenberg, Thomas; Stürzl, Michael (Biochemical Journal, 2018)
Interferon-gamma (IFN-γ) is a pleiotropic cytokine that exerts important functions in inflammation, infectious diseases, and cancer. The large GTPase human guanylate-binding protein 1 (GBP-1) is among the most strongly IFN-γ-induced cellular proteins. Previously, it has been shown that GBP-1 mediates manifold cellular responses to IFN-γ including the inhibition of proliferation, spreading, migration, and invasion and through this exerts anti-tumorigenic activity. However, the mechanisms of GBP-1 anti-tumorigenic activities remain poorly understood. Here, we elucidated the molecular mechanism of the human GBP-1-mediated suppression of proliferation by demonstrating for the first time a cross-talk between the anti-tumorigenic IFN-γ and Hippo pathways. The α9-helix of GBP-1 was found to be sufficient to inhibit proliferation. Protein-binding and molecular modeling studies revealed that the α9-helix binds to the DNA-binding domain of the Hippo signaling transcription factor TEA domain protein (TEAD) mediated by the 376VDHLFQK382 sequence at the N-terminus of the GBP-1-α9-helix. Mutation of this sequence resulted in abrogation of both TEAD interaction and suppression of proliferation. Further on, the interaction caused inhibition of TEAD transcriptional activity associated with the down-regulation of TEAD-target genes. In agreement with these results, IFN-γ treatment of the cells also impaired TEAD activity, and this effect was abrogated by siRNA-mediated inhibition of GBP-1 expression. Altogether, this demonstrated that the α9-helix is the proliferation inhibitory domain of GBP-1, which acts independent of the GTPase activity through the inhibition of the Hippo transcription factor TEAD in mediating the anti-proliferative cell response to IFN-γ.
EVALuna2:34818

IL-20 controls resolution of experimental colitis by regulating epithelial IFN/STAT2 signalling - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Günther, Claudia; Gonzalez Acera, Miguel; Atreya, Raja; Stolzer, Iris; Wittner, Leonie; Dressel, Anja; Schickedanz, Laura; Gámez Belmonte, Maria de los Reyes; Erkert, Lena; Hundorfean, Gheorghe; et al. (Gut, 2023)
Objective: We sought to investigate the role of interleukin (IL)-20 in IBD and experimental colitis. Design: Experimental colitis was induced in mice deficient in components of the IL-20 and signal transducer and activator of transcription (STAT)2 signalling pathways. In vivo imaging, high-resolution mini-endoscopy and histology were used to assess intestinal inflammation. We further used RNA-sequencing (RNA-Seq), RNAScope and Gene Ontology analysis, western blot analysis and co-immunoprecipitation, confocal microscopy and intestinal epithelial cell (IEC)-derived three-dimensional organoids to investigate the underlying molecular mechanisms. Results were validated using samples from patients with IBD and non-IBD control subjects by a combination of RNA-Seq, organoids and immunostainings. Results: In IBD, IL20 levels were induced during remission and were significantly higher in antitumour necrosis factor responders versus non-responders. IL-20RA and IL-20RB were present on IECs from patients with IBD and IL-20-induced STAT3 and suppressed interferon (IFN)-STAT2 signalling in these cells. In IBD, experimental dextran sulfate sodium (DSS)-induced colitis and mucosal healing, IECs were the main producers of IL-20. Compared with wildtype controls, Il20-/-, Il20ra-/- and Il20rb-/- mice were more susceptible to experimental DSS-induced colitis. IL-20 deficiency was associated with increased IFN/STAT2 activity in mice and IFN/STAT2-induced necroptotic cell death in IEC-derived organoids could be markedly blocked by IL-20. Moreover, newly generated Stat2ΔIEC mice, lacking STAT2 in IECs, were less susceptible to experimental colitis compared with wildtype controls and the administration of IL-20 suppressed colitis activity in wildtype animals. Conclusion: IL-20 controls colitis and mucosal healing by interfering with the IFN/STAT2 death signalling pathway in IECs. These results indicate new directions for suppressing gut inflammation by modulating IL-20-controlled STAT2 signals.
CRIS-Team Scopus Importer:2023-11-17
Keywords: experimental colitis; inflammatory bowel disease; interferon; interleukins; signal transduction

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

IL-3 receptor signalling suppresses chronic intestinal inflammation by controlling mechanobiology and tissue egress of regulatory T cells. - Ullrich, Karen; Derdau, Julia; Baltes, Carsten; Battistella, Alice; Rosso, Gonzalo; Uderhardt, Stefan; Schulze, Lisa; Liu, Lijuan; Dedden, Mark; Spocinska, Marta; Kainka, Lucina; Kubánková, Markéta; et al. (Gut, 2023)
IL-3 has been reported to be involved in various inflammatory disorders, but its role in inflammatory bowel disease (IBD) has not been addressed so far. Here, we determined IL-3 expression in samples from patients with IBD and studied the impact of Il3 or Il3r deficiency on T cell-dependent experimental colitis. We explored the mechanical, cytoskeletal and migratory properties of Il3r -/- and Il3r +/+ T cells using real-time deformability cytometry, atomic force microscopy, scanning electron microscopy, fluorescence recovery after photobleaching and in vitro and in vivo cell trafficking assays. We observed that, in patients with IBD, the levels of IL-3 in the inflamed mucosa were increased. In vivo, experimental chronic colitis on T cell transfer was exacerbated in the absence of Il-3 or Il-3r signalling. This was attributable to Il-3r signalling-induced changes in kinase phosphorylation and actin cytoskeleton structure, resulting in increased mechanical deformability and enhanced egress of Tregs from the inflamed colon mucosa. Similarly, IL-3 controlled mechanobiology in human Tregs and was associated with increased mucosal Treg abundance in patients with IBD. Collectively, our data reveal that IL-3 signaling exerts an important regulatory role at the interface of biophysical and migratory T cell features in intestinal inflammation and suggest that this might be an interesting target for future intervention.
EVALuna2:539503

Immune cell trafficking and retention in inflammatory bowel disease: Mechanistic insights and therapeutic advances - Zundler, Sebastian; Becker, Elisabeth; Schulze, Lisa; Neurath, Markus (Gut, 2019)
Intestinal immune cell trafficking has been identified as a central event in the pathogenesis of inflammatory bowel diseases (IBD). Intensive research on different aspects of the immune mechanisms controlling and controlled by T cell trafficking and retention has led to the approval of the anti-α4β7 antibody vedolizumab, the ongoing development of a number of further anti-trafficking agents (ATAs) such as the anti-β7 antibody etrolizumab or the anti-MAdCAM-1 antibody ontamalimab and the identification of potential future targets like G-protein coupled receptor 15. However, several aspects of the biology of immune cell trafficking and regarding the mechanism of action of ATAs are still unclear, for example, which impact these compounds have on the trafficking of non-lymphocyte populations like monocytes and how precisely these therapies differ with regard to their effect on immune cell subpopulations. This review will summarise recent advances of basic science in the field of intestinal immune cell trafficking and discuss these findings with regard to different pharmacological approaches from a translational perspective.
CRIS-Team Scopus Importer:2019-06-18
Keywords: cell adhesion; Crohn's disease; inflammatory bowel disease; integrins; ulcerative colitis

Immune modulation during anti-cancer radio(immuno)therapy - Irianto, Teresa Tamara; Gaipl, Udo; Rückert, Michael (International Review of Cell and Molecular Biology, 2023)
Cancer can affect all human organs and tissues and ranks as a prominent cause of death as well as an obstruction to increasing life expectancy. A notable breakthrough in oncology has been the inclusion of the immune system in fighting cancer, potentially prolonging life and providing long-term benefits. The concept of “immunotherapy” has been discussed from the 19th and early 20th centuries by Wilhelm Busch, William B. Coley and Paul Ehrlich. This involves distinct approaches, including vaccines, non-specific cytokines and adoptive cell therapies. However, despite the advances made in recent years, questions on how to select the best therapeutic options or how to select the best combinations to improve clinical outcomes are still relevant for scientists and clinicians. More than half of cancer patients receive radiotherapy (RT) as part of their treatment. With the advances in RT and immunotherapy approaches, it is reasonable to consider how to enhance immunotherapy with radiation and vice versa, and to investigate whether combinations of these therapies would be beneficial. In this chapter, we will discuss how the immune system responds to cancer cells and different cancer therapies with a focus on combination of RT and immunotherapy (radioimmunotherapy, RIT).
CRIS-Team Scopus Importer:2023-08-11
Keywords: Immune checkpoint molecules; Immune editing; Immunogenic cell death; Radioimmunotherapies; Radiotherapy

Impact of Plasma Membrane Domains on IgG Fc Receptor Function - Kara, Sibel; Amon, Lukas; Lühr, Jennifer; Nimmerjahn, Falk; Dudziak, Diana; Lux, Anja (Frontiers in Immunology, 2020)
Lipid cell membranes not only represent the physical boundaries of cells. They also actively participate in many cellular processes. This contribution is facilitated by highly complex mixtures of different lipids and incorporation of various membrane proteins. One group of membrane-associated receptors are Fc receptors (FcRs). These cell-surface receptors are crucial for the activity of most immune cells as they bind immunoglobulins such as immunoglobulin G (IgG). Based on distinct mechanisms of IgG binding, two classes of Fc receptors are now recognized: the canonical type I FcγRs and select C-type lectin receptors newly referred to as type II FcRs. Upon IgG immune complex induced cross-linking, these receptors are known to induce a multitude of cellular effector responses in a cell-type dependent manner, including internalization, antigen processing, and presentation as well as production of cytokines. The response is also determined by specific intracellular signaling domains, allowing FcRs to either positively or negatively modulate immune cell activity. Expression of cell-type specific combinations and numbers of receptors therefore ultimately sets a threshold for induction of effector responses. Mechanistically, receptor cross-linking and localization to lipid rafts, i.e., organized membrane microdomains enriched in intracellular signaling proteins, were proposed as major determinants of initial FcR activation. Given that immune cell membranes might also vary in their lipid compositions, it is reasonable to speculate, that the cell membrane and especially lipid rafts serve as an additional regulator of FcR activity. In this article, we aim to summarize the current knowledge on the interplay of lipid rafts and IgG binding FcRs with a focus on the plasma membrane composition and receptor localization in immune cells, the proposed mechanisms underlying this localization and consequences for FcR function with respect to their immunoregulatory capacity.
CRIS-Team Scopus Importer:2020-07-24
Keywords: cell membrane; CLR; FcγR; lipid rafts; membrane; membrane localization; type I FcR; type II FcR

Impaired Mitochondrial Transcription Factor A Expression Promotes Mitochondrial Damage to Drive Fibroblast Activation and Fibrosis in Systemic Sclerosis - Zhou, Xiang; Trinh, Minh Thuong; TRAN MANH, CUONG; Gießl, Andreas; Bergmann, Christina; Györfi, Andrea-Hermina; Schett, Georg; Distler, Jörg (Arthritis and Rheumatology, 2022)
Objective Mitochondrial transcription factor A (TFAM) controls the transcription of core proteins required for mitochondrial homeostasis. This study was undertaken to investigate changes in TFAM expression in systemic sclerosis (SSc), to analyze mitochondrial function, and to evaluate the consequences for fibroblast activation. Methods TFAM expression was analyzed by immunofluorescence and Western blotting. The effects of TFAM knockout were investigated in cultured fibroblasts and in murine models of bleomycin-induced skin fibrosis, bleomycin-induced lung fibrosis, and skin fibrosis induced by overexpression of constitutively active transforming growth factor beta type I receptor (TGF beta R Iota). Results TFAM expression was down-regulated in fibroblasts in SSc skin and in cultured SSc fibroblasts. The down-regulation of TFAM was associated with decreased mitochondrial number and accumulation of damaged mitochondria with release of mitochondrial DNA (mtDNA), accumulation of deletions in mtDNA, metabolic alterations with impaired oxidative phosphorylation, and release of the mitokine GDF15. Normal fibroblasts subjected to long-term, but not acute, exposure to TGF beta mimicked SSc fibroblasts, with down-regulation of TFAM and accumulation of mitochondrial damage. Down-regulation of TFAM promoted fibroblast activation with up-regulation of fibrosis-relevant Gene Ontology terms in RNA-Seq, partially in a reactive oxygen species-dependent manner. Mice with fibroblast-specific knockout of Tfam were prone to fibrotic tissue remodeling, with fibrotic responses even to NaCl instillation and enhanced sensitivity to bleomycin injection and overexpression of constitutively active TGF beta RI. TFAM knockout fostered Smad3 signaling to promote fibroblast activation. Conclusion Alterations in the key mitochondrial transcription factor TFAM in response to prolonged activation of TGF beta and associated mitochondrial damage induce transcriptional programs that promote fibroblast-to-myofibroblast transition and drive tissue fibrosis.
CRIS-Team WoS Importer:2022-04-15

Improved Bladder Tumor RNA Isolation from Archived Tissues Using Methylene Blue for Normalization, Multiplex RNA Hybridization, Sequencing and Subtyping - Köhler, Stefanie; Brandl, Lisa; Strissel, Pamela; Glossner, Laura; Ekici, Arif Bülent; Angeloni, Miriam; Ferrazzi, Fulvia; Bahlinger, Veronika; Hartmann, Arndt; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner (International Journal of Molecular Sciences, 2022)
Methylene blue (MB) is a dye used for histology with clinical importance and intercalates into nucleic acids. After MB staining of formalin fixed paraffin embedded (FFPE) muscle invasive bladder cancer (MIBC) and normal urothelium, specific regions could be microdissected. It is not known if MB influences RNA used for gene expression studies. Therefore, we analyzed MIBC using five different RNA isolation methods comparing patient matched FFPE and fresh frozen (FF) tissues pre-stained with or without MB. We demonstrate a positive impact of MB on RNA integrity with FF tissues using real time PCR with no interference of its chemical properties. FFPE tissues showed no improvement of RNA integrity, which we propose is due to formalin induced nucleotide crosslinks. Using direct multiplex RNA hybridization the best genes for normalization of MIBC and control tissues were identified from 34 reference genes. In addition, 5SrRNA and 5.8SrRNA were distinctive reference genes detecting <200 bp fragments important for mRNA analyses. Using these normalized RNAs from MB stained MIBC and applying multiplex RNA hybridization and mRNA sequencing, a minimal gene expression panel precisely identified luminal and basal MIBC tumor subtypes, important for diagnosis, prognosis and chemotherapy response.
CRIS-Team WoS Importer:2022-09-30

Increase of liver stiffness and altered bile acid metabolism after triple CFTR modulator initiation in children and young adults with cystic fibrosis - Schnell, Alexander; Jüngert, Jörg M.; Klett, Daniel; Hober, Hannah; Kaiser, Natalie; Ruppel, Renate; Geppert, Annika; Tremel, Christina; Sobel, Julia; Plattner, Erika; Schmitt-Grohe, Sabina; Zirlik, Sabine; et al. (Liver International, 2023)
Background: Novel cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies (elexacaftor/tezacaftor/ivacaftor—ETI) promise clinically significant and sustained improvements for patients with cystic fibrosis (CF). In this study, we investigated the impact of ETI therapy on liver stiffness and bile acid metabolism in a cohort of children and young adults with CF. Methods: A prospective observational study (NCT05576324) was conducted from September 2020 to November 2021 enrolling CF patients naive to ETI. Standard laboratory chemistry, sweat test, lung function, share wave velocity (SWV) derived by acoustic radiation force impulse imaging (ARFI) and serum bile acid profiles were assessed before and 6 months after induction of ETI therapy. Results: A total of 20 patients (10 aged <20 years) completed the study. While lung function and BMI improved after ETI therapy, ARFI SWV increased in CF patients <20 years of age (from 1.27 to 1.43 m/s, p = 0.023). Bile acid (BA) profiles revealed a decrease in unconjugated (5.75 vs 1.46, p = 0.007) and increase in glycine-conjugated derivatives (GCDCA) (4.79 vs 6.64 p = 0.016). There was a positive correlation between ARFI SWV values and GCDCA (r = 0.80, p < 0.0001). Glycine-conjugated BA provided high diagnostic accuracy to predict increased ARFI measurements (AUC 0.90) and clinical (Colombo) CFLD grading (AUC 0.97). Conclusions: ARFI SWV and bile acid profiles provide evidence for early increase in liver stiffness and altered bile acid metabolism in young CF patients after initiation of ETI and may serve as synergistic measures for detection of hepatic complications during ETI therapy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: ARFI; bile acids; CFLD; cystic fibrosis

Inflammasomes in dendritic cells: Friend or foe? - Hatscher, Lukas; Amon, Lukas; Heger, Lukas; Dudziak, Diana (Immunology Letters, 2021)
Inflammasomes are cytosolic multiprotein complexes that crucially contribute to host defense against pathogens but are also involved in the pathogenesis of autoinflammatory diseases. Inflammasome formation leads to activation of effector caspases (caspase-1, 4, 5, or 11), the proteolytic maturation of IL-1β and IL-18 as well as cleavage of the pore-forming protein Gasdermin D. Dendritic cells are major regulators of immune responses as they bridge innate and adaptive immunity. We here summarize the current knowledge on inflammasome expression and formation in murine bone marrow-, human monocyte-derived as well as murine and human primary dendritic cells. Further, we discuss both, the beneficial and detrimental, involvement of inflammasome activation in dendritic cells in cancer, infections, and autoimmune diseases. As inflammasome activation is typically accompanied by Gasdermin D-mediated pyroptosis, which is an inflammatory form of programmed cell death, inflammasome formation in dendritic cells seems ill-advised. Therefore, we propose that hyperactivation, which is inflammasome activation without the induction of pyroptosis, may be a general model of inflammasome activation in dendritic cells to enhance Th1, Th17 as well as cytotoxic T cell responses.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Dendritic cell; Hyperactivation; Inflammasome; NLRP3; T cell response; Vaccination

Inflammation-induced glycolytic switch controls suppressivity of mesenchymal stem cells via STAT1 glycosylation - Jitschin, R.; Böttcher, Martin; Saul, D.; Lukassen, Sören; Bruns, Heiko; Loschinski, Romy; Ekici, Arif Bülent; Reis, André; Mackensen, Andreas; Mougiakakos, Dimitrios (Leukemia, 2019)
Mesenchymal stem cells (MSCs) represent key contributors to tissue homeostasis and promising therapeutics for hyperinflammatory conditions including graft-versus-host disease. Their immunomodulatory effects are controlled by microenvironmental signals. The MSCs' functional response towards inflammatory cues is known as MSC-"licensing" and includes indoleamine 2,3-dioxygenase (IDO) upregulation. MSCs use tryptophan-depleting IDO to suppress T-cells. Increasing evidence suggests that several functions are (co-)determined by the cells' metabolic commitment. MSCs are capable of both, high levels of glycolysis and of oxidative phosphorylation. Although several studies have addressed alterations of the immune regulatory phenotype elicited by inflammatory priming metabolic mechanisms controlling this process remain unknown. We demonstrate that inflammatory MSC-licensing causes metabolic shifts including enhanced glycolysis and increased fatty acid oxidation. Yet, only interfering with glycolysis impacts IDO upregulation and impedes T-cell-suppressivity. We identified the Janus kinase (JAK)/signal transducer and activator of transcription (STAT)1 pathway as a regulator of both glycolysis and IDO, and show that enhanced glucose turnover is linked to abundant STAT1 glycosylation. Inhibiting the responsible O-acetylglucosamine (O-GlcNAc) transferase abolishes STAT1 activity together with IDO upregulation. Our data suggest that STAT1-O-GlcNAcylation increases its stability towards degradation thus sustaining downstream effects. This pathway could represent a target for interventions aiming to enhance the MSCs' immunoregulatory potency.
EVALuna2:35805

Inhibition of mTORC2/RICTOR Impairs Melanoma Hepatic Metastasis - Schmidt, Katharina M.; Dietrich, Peter; Hackl, Christina; Guenzle, Jessica; Bronsert, Peter; Wagner, Christine; Fichtner-Feigl, Stefan; Schlitt, Hans J.; Geissler, Edward K.; Hellerbrand, Claus; Lang, Sven A. (Neoplasia, 2018)
Mammalian target of rapamycin complex 2 (mTORC2) with its pivotal component rapamycin-insensitive companion of mTOR (RICTOR) is the major regulator of AKT phosphorylation and is increasingly implicated in tumor growth and progression. In cutaneous melanoma, an extremely aggressive and highly metastatic disease, RICTOR overexpression is involved in tumor development and invasiveness. Therefore, we investigated the impact of RICTOR inhibition in melanoma cells in vitro and in vivo with special emphasis on hepatic metastasis. Moreover, our study focused on the interaction of tumor cells and hepatic stellate cells (HSC) which play a crucial role in the hepatic microenvironment. In silico analysis revealed increased RICTOR expression in melanoma cells and tissues and indicated higher expression in advanced melanoma stages and metastases. In vitro, transient RICTOR knock-down via siRNA caused a significant reduction of tumor cell motility. Using a syngeneic murine splenic injection model, a significant decrease in liver metastasis burden was detected in vivo. Moreover, stimulation of melanoma cells with conditioned medium (CM) from activated HSC or hepatocyte growth factor (HGF) led to a significant induction of AKT phosphorylation and tumor cell motility. Blocking of RICTOR expression in cancer cells diminished constitutive and HGF-induced AKT phosphorylation as well as cell motility. Interestingly, RICTOR blockade also led to an abrogation of CM-induced effects on AKT phosphorylation and motility in melanoma cells. In conclusion, these results provide first evidence for a critical role of mTORC2/RICTOR in melanoma liver metastasis via cancer cell/HSC interactions.
EVALuna2:35129

Inhibition of Notch1 promotes hedgehog signalling in a HES1-dependent manner in chondrocytes and exacerbates experimental osteoarthritis - Lin, Neng-Yu; Distler, Alfiya; Beyer, Christian; Philipi-Schöbinger, Ariella; Breda, Silvia; Dees, Clara; Stock, Michael; Tomcik, Michal; Niemeier, Andreas; Dell'Accio, Francesco; Gelse, Kolja; Mattson, Mark P; et al. (Annals of the Rheumatic Diseases, 2016)
Notch ligands and receptors have recently been shown to be differentially expressed in osteoarthritis (OA). We aim to further elucidate the functional role of Notch signalling in OA using Notch1 antisense transgenic (Notch1 AS) mice.Notch and hedgehog signalling were analysed by real-time PCR and immunohistochemistry. Notch-1 AS mice were employed as a model of impaired Notch signalling in vivo. Experimental OA was induced by destabilisation of the medial meniscus (DMM). The extent of cartilage destruction and osteophyte formation was analysed by safranin-O staining with subsequent assessment of the Osteoarthritis Research Society International (OARSI) and Mankin scores and µCT scanning. Collagen X staining was used as a marker of chondrocyte hypertrophy. The role of hairy/enhancer of split 1 (Hes-1) was investigated with knockdown and overexpression experiments.Notch signalling was activated in human and murine OA with increased expression of Jagged1, Notch-1, accumulation of the Notch intracellular domain 1 and increased transcription of Hes-1. Notch1 AS mice showed exacerbated OA with increases in OARSI scores, osteophyte formation, increased subchondral bone plate density, collagen X and osteocalcin expression and elevated levels of Epas1 and ADAM-TS5 mRNA. Inhibition of the Notch pathway induced activation of hedgehog signalling with induction of Gli-1 and Gli-2 and increased transcription of hedgehog target genes. The regulatory effects of Notch signalling on Gli-expression were mimicked by Hes-1.Inhibition of Notch signalling activates hedgehog signalling, enhances chondrocyte hypertrophy and exacerbates experimental OA including osteophyte formation. These data suggest that the activation of the Notch pathway may limit aberrant hedgehog signalling in OA.
EVALuna2:13184

Inhibition of phosphodiesterase 4 (PDE4) reduces dermal fibrosis by interfering with the release of interleukin-6 from M2 macrophages - Maier, Christiane; Bergmann, Christina; Weinkam, Rita; Kittan, Nicolai; Schett, Georg; Distler, Jörg; Beyer, Christian; Ramming, Andreas (Annals of the Rheumatic Diseases, 2017)
To investigate the disease-modifying effects of phosphodiesterase 4 (PDE4) inhibition in preclinical models of systemic sclerosis (SSc).We studied the effects of PDE4 inhibition in a prevention and a treatment model of bleomycin-induced skin fibrosis, in the topoisomerase mouse model as well as in a model of sclerodermatous chronic graft-versus-host disease. To better understand the mode of action of PDE4 blockade in preclinical models of SSc, we investigated fibrosis-relevant mediators in fibroblasts and macrophages from healthy individuals and patients suffering from diffuse-cutaneous SSc on blockade of PDE4.Specific inhibition of PDE4 by rolipram and apremilast had potent antifibrotic effects in bleomycin-induced skin fibrosis models, in the topoisomerase I mouse model and in murine sclerodermatous chronic graft-versus-host disease. Fibroblasts were not the direct targets of the antifibrotic effects of PDE4 blockade. Reduced leucocyte infiltration in lesional skin on PDE4 blockade suggested an immune-mediated mechanism. Further analysis revealed that PDE4 inhibition decreased the differentiation of M2 macrophages and the release of several profibrotic cytokines, resulting in reduced fibroblast activation and collagen release. Within these profibrotic mediators, interleukin-6 appeared to play a central role.PDE4 inhibition reduces inflammatory cell activity and the release of profibrotic cytokines from M2 macrophages, leading to decreased fibroblast activation and collagen release. Importantly, apremilast is already approved for the treatment of psoriasis and psoriatic arthritis. Therefore, PDE4 inhibitors might be further developed as potential antifibrotic therapies for patients with SSc. Our findings suggest that particularly patients with inflammation-driven fibrosis might benefit from PDE4 blockade.
EVALuna2:13394

Inhibitors of Deubiquitinating Enzymes Block HIV-1 Replication and Augment the Presentation of Gag-Derived MHC-I Epitopes - Setz, Christian; Friedrich, Melanie; Rauch, Pia; Fraedrich, Kirsten; Matthaei, Alina; Traxdorf, Maximilian; Schubert, Ulrich (Viruses, 2017)
In recent years it has been well established that two major constituent parts of the ubiquitin proteasome system (UPS)-the proteasome holoenzymes and a number of ubiquitin ligases-play a crucial role, not only in virus replication but also in the regulation of the immunogenicity of human immunodeficiency virus type 1 (HIV-1). However, the role in HIV-1 replication of the third major component, the deubiquitinating enzymes (DUBs), has remained largely unknown. In this study, we show that the DUB-inhibitors (DIs) P22077 and PR-619, specific for the DUBs USP7 and USP47, impair Gag processing and thereby reduce the infectivity of released virions without affecting viral protease activity. Furthermore, the replication capacity of X4- and R5-tropic HIV-1NL4-3in human lymphatic tissue is decreased upon treatment with these inhibitors without affecting cell viability. Most strikingly, combinatory treatment with DIs and proteasome inhibitors synergistically blocks virus replication at concentrations where mono-treatment was ineffective, indicating that DIs can boost the therapeutic effect of proteasome inhibitors. In addition, P22077 and PR-619 increase the polyubiquitination of Gag and thus its entry into the UPS and the major histocompatibility complex (MHC)-I pathway. In summary, our data point towards a model in which specific inhibitors of DUBs not only interfere with virus spread but also increase the immune recognition of HIV-1 expressing cells.
EVALuna2:33758

Innate PD-L1 limits T cell-mediated adipose tissue inflammation and ameliorates diet-induced obesity - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, Heike C.; Hams, Emily; Bayerlein, Jasmin; Roeger, Ole; Bailer, Moritz; Krautz, Christian; Elgendy, Amr; Elshafei, Moustafa; Heneghan, Helen M.; et al. (Science Translational Medicine, 2022)
Obesity has become a major health problem in the industrialized world. Immune regulation plays an important role in adipose tissue homeostasis; however, the initial events that shift the balance from a noninflammatory homeostatic environment toward inflammation leading to obesity are poorly understood. Here, we report a role for the costimulatory molecule programmed death-ligand 1 (PD-L1) in the limitation of diet-induced obesity. Functional ablation of PD-L1 on dendritic cells (DCs) using conditional knockout mice increased weight gain and metabolic syndrome during diet-induced obesity, whereas PD-L1 expression on type 2 innate lymphoid cells (ILC2s), T cells, and macrophages was dispensable for obesity control. Using in vitro cocultures, DCs interacted with T cells and ILC2s via the PD-L1:PD-1 axis to inhibit T helper type 1 proliferation and promote type 2 polarization, respectively. A role for PD-L1 in adipose tissue regulation was also shown in humans, with a positive correlation between PD-L1 expression in visceral fat of people with obesity and elevated body weight. Thus, we define a mechanism of adipose tissue homeostasis controlled by the expression of PD-L1 by DCs, which may be a clinically relevant finding with regard to immune-related adverse events during immune checkpoint inhibitor therapy.
CRIS-Team Scopus Importer:2022-03-25

Interaction of Alpha Synuclein and Microtubule Organization Is Linked to Impaired Neuritic Integrity in Parkinson’s Patient-Derived Neuronal Cells - Schneider, Yanni; Drobny, Alice; Prots, Iryna; Zunke, Friederike; Xiang, Wei; Seebauer, Lukas; Schneider, Yanni; Drobny, Alice; Ploetz, Sonja; Koudelka, Tomas; Tholey, Andreas; Prots, Iryna; et al. (International Journal of Molecular Sciences, 2022)
Parkinson’s disease (PD) is neuropathologically characterized by the loss of dopaminergic neurons and the deposition of aggregated alpha synuclein (aSyn). Mounting evidence suggests that neuritic degeneration precedes neuronal loss in PD. A possible underlying mechanism could be the interference of aSyn with microtubule organization in the neuritic development, as implied by sev-eral studies using cell-free model systems. In this study, we investigate the impact of aSyn on mi-crotubule organization in aSyn overexpressing H4 neuroglioma cells and midbrain dopaminergic neuronal cells (mDANs) generated from PD patient-derived human induced pluripotent stem cells (hiPSCs) carrying an aSyn gene duplication (SNCADupl). An unbiased mass spectrometric analysis reveals a preferential binding of aggregated aSyn conformers to a number of microtubule elements. We confirm the interaction of aSyn with beta tubulin III in H4 and hiPSC-derived mDAN cell model systems, and demonstrate a remarkable redistribution of tubulin isoforms from the soluble to insoluble fraction, accompanied by a significantly increased insoluble aSyn level. Concordantly, SNCA-Dupl mDANs show impaired neuritic phenotypes characterized by perturbations in neurite initiation and outgrowth. In summary, our findings suggest a mechanistic pathway, through which aSyn aggregation interferes with microtubule organization and induces neurite impairments.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Alpha-synuclein; IPSC; Microtubule; Neurite; Neurodegeneration; Parkinson’s disease; SNCA duplication

Interferon Lambda Promotes Paneth Cell Death Via STAT1 Signaling in Mice and Is Increased in Inflamed Ileal Tissues of Patients With Crohn's Disease - Günther, Claudia; Ruder, Barbara; Stolzer, Iris; Dorner, Heidrun; He, Gui-Wei; Aden, Konrad; Strigli, Anne; Bittel, Miriam; Zeissig, Sebastian; Rosenstiel, Philip; Atreya, Raja; Neurath, Markus; et al. (Gastroenterology, 2019)
BACKGROUND & AIMS: Interferon lambda (IFNL) is expressed at high levels by intestinal epithelial cells (IECs) and mucosal immune cells in response to infection and inflammation. We investigated whether IFNL might contribute to pathogenesis of Crohn's disease (CD). METHODS: We obtained serum samples and terminal ileum biopsies from 47 patients with CD and 16 healthy individuals (controls). We measured levels of IFNL by enzyme-linked immunosorbent assay and immunohistochemistry and location of expression by confocal microscopy. Activation of IFNL signaling via STAT1 was measured in areas of no, mild, moderate, and severe inflammation and correlated with Paneth cell homeostasis and inflammation. IFNL expression and function were studied in wild-type mice and mice with intestinal epithelial cell-specific (Delta IEC) disruption or full-body disruption of specific genes (Mlkl(-/-), Stat1(Delta IEC), Casp8(Delta IEC), Casp8(Delta IEC)Ripk3(-/-), Casp8(Delta IEC)Tnfr(-/-), Casp8(Delta IEC)Mlkl(-/-), and Nod2(-/-) mice). Some mice were given tail vein injections of a vector encoding a secreted form of IFNL. Intestinal tissues were collected from mice and analyzed by immunohistochemistry and immunoblots. We generated 3-dimensional small intestinal organoids from mice and studied the effects of IFNL and inhibitors of STAT-signaling pathway. RESULTS: Patients with CD had significant increases in serum and ileal levels of IFNL compared with controls. Levels of IFNL were highest in ileum tissues with severe inflammation. High levels of IFNL associated with a reduced number of Paneth cells and increased cell death at the crypt bottom in inflamed ileum samples. Intestinal tissues from the ileum of wild-type mice injected with a vector expressing IFNL had reduced numbers of Paneth cells. IFNL-induced death of Paneth cells in mice did not occur via apoptosis, but required Mixed Lineage Kinase Domain Like (MLKL) and activation of Signal transducer and activator of transcription 1 (STAT1). In organoids, inhibitors of Janus kinase (JAK) signaling via STAT1 (glucocorticoids, tofacitinib, or filgotinib) reduced expression of proteins that mediate cell death and prevented Paneth cell death. CONCLUSIONS: Levels of IFNL are increased in serum and inflamed ileal tissues from patients with CD and associated with a loss of Paneth cells. Expression of a secreted form of IFNL in mice results in loss of Paneth cells from intestinal tissues, via STAT1 and MLKL, controlled by caspase 8. Strategies to reduce IFNL or block its effects might be developed for treatment of patients with CD affecting the terminal ileum.
Keywords: Inflammatory Bowel Diseases; Ileitis; Necroptosis; Cytokine

Interleukin 36 receptor-inducible matrix metalloproteinase 13 mediates intestinal fibrosis - Koop, Kristina; Enderle, Karin; Hillmann, Miriam; Ruspeckhofer, Laura; Vieth, Michael; Sturm, Gregor; Trajanoski, Zlatko; Kühl, Anja A.; Atreya, Raja; Leppkes, Moritz; Baum, Patrick; Roy, Janine; et al. (Frontiers in Immunology, 2023)
Background: Fibrostenotic disease is a common complication in Crohn’s disease (CD) patients hallmarked by transmural extracellular matrix (ECM) accumulation in the intestinal wall. The prevention and medical therapy of fibrostenotic CD is an unmet high clinical need. Although targeting IL36R signaling is a promising therapy option, downstream mediators of IL36 during inflammation and fibrosis have been incompletely understood. Candidate molecules include matrix metalloproteinases which mediate ECM turnover and are thereby potential targets for anti-fibrotic treatment. Here, we have focused on understanding the role of MMP13 during intestinal fibrosis. Methods: We performed bulk RNA sequencing of paired colon biopsies taken from non-stenotic and stenotic areas of patients with CD. Corresponding tissue samples from healthy controls and CD patients with stenosis were used for immunofluorescent (IF) staining. MMP13 gene expression was analyzed in cDNA of intestinal biopsies from healthy controls and in subpopulations of patients with CD in the IBDome cohort. In addition, gene regulation on RNA and protein level was studied in colon tissue and primary intestinal fibroblasts from mice upon IL36R activation or blockade. Finally, in vivo studies were performed with MMP13 deficient mice and littermate controls in an experimental model of intestinal fibrosis. Ex vivo tissue analysis included Masson’s Trichrome and Sirius Red staining as well as evaluation of immune cells, fibroblasts and collagen VI by IF analysis. Results: Bulk RNA sequencing revealed high upregulation of MMP13 in colon biopsies from stenotic areas, as compared to non-stenotic regions of patients with CD. IF analysis confirmed higher levels of MMP13 in stenotic tissue sections of CD patients and demonstrated αSMA+ and Pdpn+ fibroblasts as a major source. Mechanistic experiments demonstrated that MMP13 expression was regulated by IL36R signaling. Finally, MMP13 deficient mice, as compared to littermate controls, developed less fibrosis in the chronic DSS model and showed reduced numbers of αSMA+ fibroblasts. These findings are consistent with a model suggesting a molecular axis involving IL36R activation in gut resident fibroblasts and MMP13 expression during the pathogenesis of intestinal fibrosis. Conclusion: Targeting IL36R-inducible MMP13 could evolve as a promising approach to interfere with the development and progression of intestinal fibrosis.
CRIS-Team Scopus Importer:2023-06-02
Keywords: collagen type VI; collagenase 3; extracellular matrix (ECM); IL-36; il36 receptor; intestinal fibrosis; matrix metalloproteinase 13 (MMP13); αSMA+ fibroblasts

Interplay of GTPases and Cytoskeleton in Cellular Barrier Defects during Gut Inflammation - Lopez Posadas, Rocío; Stürzl, Michael; Atreya, Imke; Neurath, Markus; Britzen-Laurent, Nathalie (Frontiers in Immunology, 2017)
An essential role of the intestine is to build and maintain a barrier preventing the luminal gut microbiota from invading the host. This involves two coordinated physical and immunological barriers formed by single layers of intestinal epithelial and endothelial cells, which avoid the activation of local immune responses or the systemic dissemination of microbial agents, and preserve tissue homeostasis. Accordingly, alterations of epithelial and endothelial barrier functions have been associated with gut inflammation, for example during inflammatory bowel disease (IBD). The discriminative control of nutriment uptake and sealing toward potentially pathological microorganisms requires a profound regulation of para- and transcellular permeability. On the subcellular level, the cytoskeleton exerts key regulatory functions in the maintenance of cellular barriers. Increased epithelial/endothelial permeability occurs primarily as a result of a reorganization of cytoskeletal-junctional complexes. Pro-inflammatory mediators such as cytokines can induce cytoskeletal rearrangements, causing inflammation-dependent defects in gut barrier function. In this context, small GTPases of the Rho family and large GTPases from the Dynamin superfamily appear as major cellular switches regulating the interaction between intercellular junctions and actomyosin complexes, and in turn cytoskeleton plasticity. Strikingly, some of these proteins, such as RhoA or guanylate-binding protein-1 (GBP-1) have been associated with gut inflammation and IBD. In this review, we will summarize the role of small and large GTPases for cytoskeleton plasticity and epithelial/endothelial barrier in the context of gut inflammation.
EVALuna2:15286

Intestinal epithelial Caspase-8 signaling is essential to prevent necroptosis during Salmonella Typhimurium induced enteritis - Hefele, Manuela; Stolzer, Iris; Ruder, Barbara; He, Gui-Wei; Mahapatro, Mousumi; Wirtz, Stefan; Neurath, Markus; Günther, Claudia (Mucosal Immunology, 2018)
Although induction of host cell death is a pivotal step during bacteria-induced gastroenteritis, the molecular regulation remains to be fully characterized. To expand our knowledge, we investigated the role of the central cell death regulator Caspase-8 in response to Salmonella Typhimurium. Here, we uncovered that intestinal salmonellosis was associated with strong upregulation of members of the host cell death machinery in intestinal epithelial cells (IECs) as an early event, suggesting that elimination of infected IECs represents a host defense strategy. Indeed, Casp8∆IEC mice displayed severe tissue damage and high lethality after infection. Additional deletion of Ripk3 or Mlkl rescued epithelial cell death and lethality of Casp8∆IEC mice, demonstrating the crucial role of Caspase-8 as a negative regulator of necroptosis. While Casp8∆IECTnfr1-/- mice showed improved survival after infection, tissue destruction was similar to Casp8∆IEC mice, indicating that necroptosis partially depends on TNF-α signaling. Although there was no impairment in antimicrobial peptide secretion during the early phase of infection, functional Caspase-8 seems to be required to control pathogen colonization. Collectively, these results demonstrate that Caspase-8 is essential to prevent Salmonella Typhimurium induced enteritis and to ensure host survival by two different mechanisms: maintenance of intestinal barrier function and restriction of pathogen colonization.
EVALuna2:35156

Investigating Intestinal Barrier Breakdown in Living Organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Becker, Christoph; Palmisano, Ralf; Stürzl, Michael; Tripal, Philipp (Journal of Visualized Experiments, 2020)
Organoids and three-dimensional (3D) cell cultures allow the investigation of complex biological mechanisms and regulations in vitro, which previously was not possible in classical cell culture monolayers. Moreover, monolayer cell cultures are good in vitro model systems but do not represent the complex cellular differentiation processes and functions that rely on 3D structure. This has so far only been possible in animal experiments, which are laborious, time consuming, and hard to assess by optical techniques. Here we describe an assay to quantitatively determine the barrier integrity over time in living small intestinal mouse organoids. To validate our model, we applied interferon gamma (IFN-gamma) as a positive control for barrier destruction and organoids derived from IFN-gamma receptor 2 knock out mice as a negative control. The assay allowed us to determine the impact of IFN-gamma on the intestinal barrier integrity and the IFN-gamma induced degradation of the tight junction proteins claudin-2, -7, and -15. This assay could also be used to investigate the impact of chemical compounds, proteins, toxins, bacteria, or patient-derived probes on the intestinal barrier integrity.
CRIS-Team WoS Importer:2020-04-17

Investigational Antiviral Therapy Models for the Prevention and Treatment of Congenital Cytomegalovirus Infection during Pregnancy - Hamilton, Stuart T.; Marschall, Manfred; Rawlinson, William D. (Antimicrobial Agents and Chemotherapy, 2021)
Congenital cytomegalovirus (HCMV) infection may cause significant fetal malformation, lifelong disease, and, in severe cases, fetal or neonatal death. Placental infection with HCMV is the major mechanism of mother-to-child transmission (MTCT) and fetal injury. Thus, any pharmaceutical antiviral interference to reduce viral load may reduce placental damage, MTCT, and fetal disease. However, there is currently no licensed HCMV antiviral for use during pregnancy. In this study, aciclovir and the HCMV-specific antivirals letermovir, maribavir, and cidofovir were compared with ganciclovir for antiviral effects in model systems of pregnancy, including first-trimester TEV-1 trophoblast cell cultures and third-trimester ex vivo placental explant histocultures. HCMV-infected trophoblasts at 7 days postinfection (dpi) showed an EC50 of 21 mu M for aciclovir, 0.0007 mu M for letermovir, 0.11 mu M for maribavir, and 0.29 mu M for cidofovir, relative to 0.42 mu M for ganciclovir. Antivirals added at 10 mu M showed no cytotoxic effects and did not affect trophoblast cell proliferation (P > 0.9999). Multiple-round HCMV replication measured at 7 dpi showed letermovir, maribavir, and cidofovir treatment inhibited immediate early, early, and true late viral protein expression as assayed on Western blots. Antiviral treatment of HCMV-infected placental explants showed significant inhibition (P < 0.05) of viral replication with letermovir (83.3%), maribavir (83.6%), cidofovir (89.3%), and ganciclovir (82.4%), but not aciclovir (P > 0.9999). In ex vivo model systems, recently trialed HCMV antivirals letermovir and maribavir were effective at inhibiting HCMV replication. They partly fulfil requirements for use as safe and effective therapeutics during pregnancy to control congenital HCMV. Clinical trials of these newer agents would assist assessment of their utility in pregnancy.
CRIS-Team WoS Importer:2021-01-15

Investigation of lateral geniculate nucleus volume and diffusion tensor imaging in patients with normal tension glaucoma using 7 tesla magnetic resonance imaging - Schmidt, Manuel; Knott, Michael; Heidemann, Robin; Michelson, Georg; Kober, Tobias; Dörfler, Arnd; Engelhorn, Tobias (PLoS ONE, 2018)
BACKGROUND: There is evidence that glaucoma is a neurodegenerative disease involving the whole visual pathway. We prospectively examined potential benefits of volumetry of the lateral geniculate nucleus (LGN) and diffusion tensor imaging (DTI) using a new 7T scanner. METHODS: 20 patients with normal tension glaucoma and 16 control individuals were examined. LGN volume and fractional anisotropy (FA) of the optic tract (OT) and the optic radiation (OR) and their correlation with RNFL (retinal nerve fiber layer) thickness were analyzed. RESULTS: LGN volume was significantly reduced in NTG (60.9 vs 88.3; p < 0.05). FA of the OT (right: 0.35 vs 0.66, left: 0.36 vs 0.67; p < 0.05) and of the OR (right: 0.41 vs 0.70, left: 0.41 vs 0.69; p < 0.05) was also significantly reduced. Nasal RNFL thickness correlated with the volume of the contralateral LGN (r = 0.471, p = 0.05). Temporal RNFL thickness correlated with the volume of the ipsilateral LGN (r = 0.603, p = 0.015). CONCLUSION: NTG leads to significant atrophy of the LGN compared to controls. FA of the optic tract and the optic radiation is reduced in NTG as sign of axonal degeneration. RNFL thickness but not FA correlates with LGN volume.
EVALuna2:34502

Ion Channel Activity of Vpu Proteins Is Conserved throughout Evolution of HIV-1 and SIV - Greiner, Timo; Bolduan, Sebastian; Hertel, Brigitte; Gro, Christine; Hamacher, Kay; Schubert, Ulrich; Moroni, Anna; Thiel, Gerhard (Viruses, 2016)
The human immunodeficiency virus type 1 (HIV-1) protein Vpu is encoded exclusively by HIV-1 and related simian immunodeficiency viruses (SIVs). The transmembrane domain of the protein has dual functions: it counteracts the human restriction factor tetherin and forms a cation channel. Since these two functions are causally unrelated it remains unclear whether the channel activity has any relevance for viral release and replication. Here we examine structure and function correlates of different Vpu homologs from HIV-1 and SIV to understand if ion channel activity is an evolutionary conserved property of Vpu proteins. An electrophysiological testing of Vpus from different HIV-1 groups (N and P) and SIVs from chimpanzees (SIVcpz), and greater spot-nosed monkeys (SIVgsn) showed that they all generate channel activity in HEK293T cells. This implies a robust and evolutionary conserved channel activity and suggests that cation conductance may also have a conserved functional significance.
EVALuna2:32858

Isolation and sequence analysis of a novel rhesus macaque foamy virus isolate with a serotype-1-like env - Enßer, Armin; Grosskopf, Anna K.; Maetz-Rensing, Kerstin; Roos, Christian; Hahn, Alexander S. (Archives of Virology, 2018)
SFVmmu-DPZ9524 represents the third completely sequenced rhesus macaque simian foamy virus (SFV) isolate, alongside SFVmmu_K3T with a similar SFV-1-type env, and R289HybAGM with a SFV-2-like env. Sequence analysis demonstrates that, in gag and pol, SFVmmu-DPZ9524 is more closely related to R289HybAGM than to SFVmmu_K3T, which, outside of env, is more similar to a Japanese macaque isolate than to the other two rhesus macaque isolates SFVmmu-DPZ9524 and R289HybAGM. Further, we identify bel as another recombinant locus in R289HybAGM, confirming that recombination contributes to sequence diversity in SFV.
EVALuna2:35813

Isolation of Human Endothelial Cells from Normal Colon and Colorectal Carcinoma - An Improved Protocol - Naschberger, Elisabeth; Regensburger, Daniela; Tenkerian, Clara; Langheinrich, Melanie; Engel, Felix; Geppert, Carol-Immanuel; Hartmann, Arndt; Grützmann, Robert; Schellerer, Vera; Stürzl, Michael (Journal of Visualized Experiments, 2018)
Primary cells isolated from human carcinomas are valuable tools to identify pathogenic mechanisms contributing to disease development and progression. In particular, endothelial cells (EC) constituting the inner surface of vessels, directly participate in oxygen delivery, nutrient supply, and removal of waste products to and from tumors, and are thereby prominently involved in the constitution of the tumor microenvironment (TME). Tumor endothelial cells (TECs) can be used as cellular biosensors of the intratumoral microenvironment established by communication between tumor and stromal cells. TECs also serve as targets of therapy. Accordingly, in culture these cells allow studies on mechanisms of response or resistance to anti-angiogenic treatment. Recently, it was found that TECs isolated from human colorectal carcinoma (CRC) exhibit memory-like effects based on the specific TME they were derived from. Moreover, these TECs actively contribute to the establishment of a specific TME by the secretion of different factors. For example, TECs in a prognostically favorable Th1-TME secrete the anti-angiogenic tumor-suppressive factor secreted protein, acidic and rich in cysteine-like 1 (SPARCL1). SPARCL1 regulates vessel homeostasis and inhibits tumor cell proliferation and migration. Hence, cultures of pure, viable TECs isolated from human solid tumors are a valuable tool for functional studies on the role of the vascular system in tumorigenesis. Here, a new up-to-date protocol for the isolation of primary EC from the normal colon as well as CRC is described. The technique is based on mechanical and enzymatic tissue digestion, immunolabeling, and fluorescence activated cell sorting (FACS)-sorting of triple-positive cells (CD31, VE-cadherin, CD105). With this protocol, viable TEC or normal endothelial cell (NEC) cultures could be isolated from colon tissues with a success rate of 62.12% when subjected to FACS-sorting (41 pure EC cultures from 66 tissue samples). Accordingly, this protocol provides a robust approach to isolate human EC cultures from normal colon and CRC.
EVALuna2:34267

Isolation of human ventricular cardiomyocytes from vibratome-cut myocardial slices - Fiegle, Dominik; Volk, Tilmann; Seidel, Thomas (Journal of Visualized Experiments, 2020)
The isolation of ventricular cardiac myocytes from animal and human hearts is a fundamental method in cardiac research. Animal cardiomyocytes are commonly isolated by coronary perfusion with digestive enzymes. However, isolating human cardiomyocytes is challenging because human myocardial specimens usually do not allow for coronary perfusion, and alternative isolation protocols result in poor yields of viable cells. In addition, human myocardial specimens are rare and only regularly available at institutions with on-site cardiac surgery. This hampers the translation of findings from animal to human cardiomyocytes. Described here is a reliable protocol that enables efficient isolation of ventricular myocytes from human and animal myocardium. To increase the surface-to-volume ratio while minimizing cell damage, myocardial tissue slices 300 µm thick are generated from myocardial specimens with a vibratome. Tissue slices are then digested with protease and collagenase. Rat myocardium was used to establish the protocol and quantify yields of viable, calcium-tolerant myocytes by flow-cytometric cell counting. Comparison with the commonly used tissue-chunk method showed significantly higher yields of rod-shaped cardiomyocytes (41.5 ± 11.9 vs. 7.89 ± 3.6%, p < 0.05). The protocol was translated to failing and non-failing human myocardium, where yields were similar as in rat myocardium and, again, markedly higher than with the tissue-chunk method (45.0 ± 15.0 vs. 6.87 ± 5.23 cells/mg, p < 0.05). Notably, with the protocol presented it is possible to isolate reasonable numbers of viable human cardiomyocytes (9–200 cells/mg) from minimal amounts of tissue (<50 mg). Thus, the method is applicable to healthy and failing myocardium from both human and animal hearts. Furthermore, it is possible to isolate excitable and contractile myocytes from human tissue specimens stored for up to 36 h in cold cardioplegic solution, rendering the method particularly useful for laboratories at institutions without on-site cardiac surgery.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Biology; Calcium imaging; Cardiac excitation-contraction coupling; Cardiomyocyte isolation; Contractile myocytes; Heart failure; Human; Issue 159; Myocardial slices; Vibratome

JAK1-dependent transphosphorylation of JAK2 limits the antifibrotic effects of selective JAK2 inhibitors on long-term treatment - Zhang, Yun; Liang, Ruifang; Chen, Chih-Wei; Mallano, Tatjana; Dees, Clara; Distler, Alfiya; Reich, Adam; Bergmann, Christina; Ramming, Andreas; Gelse, Kolja; Mielenz, Dirk; Distler, Oliver; et al. (Annals of the Rheumatic Diseases, 2017)
Janus kinase 2 (JAK2) has recently been described as a novel downstream mediator of the pro-fibrotic effects of transforming growth factor-?. Although JAK2 inhibitors are in clinical use for myelodysplastic syndromes, patients often rapidly develop resistance. Tumour cells can escape the therapeutic effects of selective JAK2 inhibitors by mutation-independent transactivation of JAK2 by JAK1. Here, we used selective JAK2 inhibition as a model to test the hypothesis that chronic treatment may provoke resistance by facilitating non-physiological signalling pathways in fibroblasts.The antifibrotic effects of long-term treatment with selective JAK2 inhibitors and reactivation of JAK2 signalling by JAK1-dependent transphosphorylation was analysed in cultured fibroblasts and experimental dermal and pulmonary fibrosis. Combined JAK1/JAK2 inhibition and co-treatment with an HSP90 inhibitor were evaluated as strategies to overcome resistance.The antifibrotic effects of selective JAK2 inhibitors on fibroblasts decreased with prolonged treatment as JAK2 signalling was reactivated by JAK1-dependent transphosphorylation of JAK2. This reactivation could be prevented by HSP90 inhibition, which destabilised JAK2 protein, or with combined JAK1/JAK2 inhibitors. Treatment with combined JAK1/JAK2 inhibitors or with JAK2 inhibitors in combination with HSP90 inhibitors was more effective than monotherapy with JAK2 inhibitors in bleomycin-induced pulmonary fibrosis and in adTBR-induced dermal fibrosis.Fibroblasts can develop resistance to chronic treatment with JAK2 inhibitors by induction of non-physiological JAK1-dependent transactivation of JAK2 and that inhibition of this compensatory signalling pathway, for example, by co-inhibition of JAK1 or HSP90 is important to maintain the antifibrotic effects of JAK2 inhibition with long-term treatment.
EVALuna2:13270

Know your neighbors: microbial recognition at the intestinal barrier and its implications for gut homeostasis and inflammatory bowel disease - Iyer, Krishna; Erkert, Lena; Becker, Christoph (Frontiers in Cell and Developmental Biology, 2023)
Intestinal epithelial cells (IECs) perform several physiological and metabolic functions at the epithelial barrier. IECs also play an important role in defining the overall immune functions at the mucosal region. Pattern recognition receptors (PRRs) on the cell surface and in other cellular compartments enable them to sense the presence of microbes and microbial products in the intestinal lumen. IECs are thus at the crossroads of mediating a bidirectional interaction between the microbial population and the immune cells present at the intestinal mucosa. This communication between the microbial population, the IECs and the underlying immune cells has a profound impact on the overall health of the host. In this review, we focus on the various PRRs present in different cellular compartments of IECs and discuss the recent developments in the understanding of their role in microbial recognition. Microbial recognition and signaling at the epithelial barrier have implications in the maintenance of intestinal homeostasis, epithelial barrier function, maintenance of commensals, and the overall tolerogenic function of PRRs in the gut mucosa. We also highlight the role of an aberrant microbial sensing at the epithelial barrier in the pathogenesis of inflammatory bowel disease (IBD) and the development of colorectal cancer.
CRIS-Team Scopus Importer:2023-10-20
Keywords: inflammatory bowel disease (IBD); intestinal epithelial cells (IECs); intestinal homeostasis; microbiome; mucosal immunity; pattern recognition receptors (PRRs)

Künstliche Intelligenz für die computerunterstützte Leukämiediagnostik - Matek, Christian; Marr, Carsten; von Bergwelt-Baildon, Michael; Spiekermann, Karsten (Deutsche Medizinische Wochenschrift, 2023)
The manual examination of blood and bone marrow specimens for leukemia patients is time-consuming and limited by intra- and inter-observer variance. The development of AI algorithms for leukemia diagnostics requires high-quality sample digitization and reliable annotation of large datasets. Deep learning-based algorithms using these datasets attain human-level performance for some well-defined, clinically relevant questions such as the blast character of cells. Methods such as multiple - instance - learning allow predicting diagnoses from a collection of leukocytes, but are more data-intensive. Using "explainable AI" methods can make the prediction process more transparent and allow users to verify the algorithm's predictions. Stability and robustness analyses are necessary for routine application of these algorithms, and regulatory institutions are developing standards for this purpose. Integrated diagnostics, which link different diagnostic modalities, offer the promise of even greater accuracy but require more extensive and diverse datasets.
CRIS-Team Scopus Importer:2023-09-01

Label-Free Characterization and Quantification of Mucosal Inflammation in Common Murine Colitis Models With Multiphoton Imaging - Kreiß, Lucas; Thoma, Oana-Maria; Lemire, Sarah; Lechner, Kristina; Carlé, Birgitta-Elisabeth; Dilipkumar, Ashwathama; Kunert, Timo; Scheibe, Kristina; Heichler, Christina; Merten, Anna-Lena; Weigmann, Benno; Neufert, Clemens; et al. (Inflammatory Bowel Diseases, 2022)
Background Clinical challenges in inflammatory bowel diseases require microscopic in vivo evaluation of inflammation. Here, label-free imaging holds great potential, and recently, our group demonstrated the advantage of using in vivo multiphoton endomicroscopy for longitudinal animal studies. This article extends our previous work by in-depth analysis of label-free tissue features in common colitis models quantified by the multiphoton colitis score (MCS). Methods Fresh mucosal tissues were evaluated from acute and chronic dextran sulfate sodium (DSS), TNBS, oxazolone, and transfer colitis. Label-free imaging was performed by using second harmonic generation and natural autofluorescence. Morphological changes in mucosal crypts, collagen fibers, and cellularity in the stroma were analyzed and graded. Results Our approach discriminated between healthy (mean MCS = 2.5) and inflamed tissue (mean MCS > 5) in all models, and the MCS was validated by hematoxylin and eosin scoring of the same samples (85.2% agreement). Moreover, specific characteristics of each phenotype were identified. While TNBS, oxazolone, and transfer colitis showed high cellularity in stroma, epithelial damage seemed specific for chronic, acute DSS and transfer colitis. Crypt deformations were mostly observed in acute DSS. Conclusions Quantification of label-free imaging is promising for in vivo endoscopy. In the future, this could be valuable for monitoring of inflammatory pathways in murine models, which is highly relevant for the development of new inflammatory bowel disease therapeutics.
CRIS-Team WoS Importer:2022-10-07

L-Arginine metabolism inhibits arthritis and inflammatory bone loss - Cao, Shan; Li, Yixuan; Song, Rui; Meng, Xianyi; Fuchs, Maximilian; Liang, Chunguang; Kachler, Katerina; Meng, Xinyu; Wen, Jinming; Schlötzer-Schrehardt, Ursula; Taudte, Verena; Geßner, Arne; et al. (Annals of the Rheumatic Diseases, 2023)
Objectives: To investigate the effect of the L-Arginine metabolism on arthritis and inflammation-mediated bone loss. Methods: L-Arginine was applied to three arthritis models (collagen-induced arthritis, serum-induced arthritis and human TNF transgenic mice). Inflammation was assessed clinically and histologically, while bone changes were quantified by μCT and histomorphometry. In vitro, effects of L-Arginine on osteoclast differentiation were analysed by RNA-seq and mass spectrometry (MS). Seahorse, Single Cell ENergetIc metabolism by profilIng Translation inHibition and transmission electron microscopy were used for detecting metabolic changes in osteoclasts. Moreover, arginine-Associated metabolites were measured in the serum of rheumatoid arthritis (RA) and pre-RA patients. Results: L-Arginine inhibited arthritis and bone loss in all three models and directly blocked TNFα-induced murine and human osteoclastogenesis. RNA-seq and MS analyses indicated that L-Arginine switched glycolysis to oxidative phosphorylation in inflammatory osteoclasts leading to increased ATP production, purine metabolism and elevated inosine and hypoxanthine levels. Adenosine deaminase inhibitors blocking inosine and hypoxanthine production abolished the inhibition of L-Arginine on osteoclastogenesis in vitro and in vivo. Altered arginine levels were also found in RA and pre-RA patients. Conclusion: Our study demonstrated that L-Arginine ameliorates arthritis and bone erosion through metabolic reprogramming and perturbation of purine metabolism in osteoclasts.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Arthritis; Inflammation; Osteoporosis

Latency reversing agents: Kick and kill of htlv-1? - Schnell, Annika; Kohrt, Stephan; Thoma-Kreß, Andrea (International Journal of Molecular Sciences, 2021)
Human T-cell leukemia virus type 1 (HTLV-1), the cause of adult T-cell leukemia/lym-phoma (ATLL), is a retrovirus, which integrates into the host genome and persistently infects CD4+ T-cells. Virus propagation is stimulated by (1) clonal expansion of infected cells and (2) de novo infection. Viral gene expression is induced by the transactivator protein Tax, which recruits host factors like positive transcription elongation factor b (P-TEFb) to the viral promoter. Since HTLV-1 gene expression is repressed in vivo by viral, cellular, and epigenetic mechanisms in late phases of infection, HTLV-1 avoids an efficient CD8+ cytotoxic T-cell (CTL) response directed against the im-munodominant viral Tax antigen. Hence, therapeutic strategies using latency reversing agents (LRAs) sought to transiently activate viral gene expression and antigen presentation of Tax to enhance CTL responses towards HTLV-1, and thus, to expose the latent HTLV-1 reservoir to immune destruction. Here, we review strategies that aimed at enhancing Tax expression and Tax-specific CTL responses to interfere with HTLV-1 latency. Further, we provide an overview of LRAs including (1) histone deacetylase inhibitors (HDACi) and (2) activators of P-TEFb, that have mainly been studied in context of human immunodeficiency virus (HIV), but which may also be powerful in the context of HTLV-1.
CRIS-Team Scopus Importer:2021-06-04
Keywords: ATLL; HDAC-inhibitor (HDACi); HIV; HTLV-1; Kick and kill; Latency; Latency reversing agents (LRA); P-TEFb; Shock and kill; Tax

Latest perspectives on macrophages in bone homeostasis - Bozec, Aline; Soulat, Didier (Pflügers Archiv: European Journal of Physiology, 2017)
Knowledge about macrophages residing in the bone, also known as osteal macrophages or osteomacs, is still limited. A hallmark of this peculiar myeloid population is the expression of macrophage markers distinct from the markers found on osteoclast surface. In bone, osteomacs are in contact with osteoblasts, where they are involved in regulating bone homeostasis. However, additional macrophage subtypes already present in the bone marrow or recruited from the blood circulation could have further functions, which could be all important for the maintenance of the bone architecture and its associated functions. Indeed, bone marrow macrophages have been found to eliminate apoptotic cells, particularly apoptotic osteoblasts through a process named efferocytosis. This phagocytic process plays an essential role in bone tissue homeostasis and new bone formation. In addition, bone marrow macrophages can influence the hematopoietic stem cell (HSC) niches. They contribute to the regulation of the HSC progenitor cell maintenance, mobilization, and function. To do so, macrophages secrete cytokines in steady state or during stress conditions. These cytokines influence hematopoiesis either by a direct effect on HSCs or through the control of stromal cells that are essential for the HSC niches. Interestingly, the similarities between the niches for HSCs and the niche for metastatic tumor cells support the possibility that bone-resident macrophages could control the homing of tumor cells and their proliferation within the bone. In general, macrophage role during metastatic processes is well described; however, their direct involvement in bone metastasis is a rising research area. In this review, we will highlight the macrophage functions in the skeleton, in the maintenance of the HCS niches, and their importance in bone metastasis.
EVALuna2:7749

Lenalidomide enhances MOR202-dependent macrophage-mediated effector functions via the vitamin D pathway - Busch, Leonhard; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Müller, Miriam J.; Volmer, Dietrich A.; Bach, Christian; Fabri, Mario; Bittenbring, Jörg T.; Neumann, Frank; Boxhammer, Rainer; Nolting, Jens; Bisht, Savita; et al. (Leukemia, 2018)
Macrophages are key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD38 antibody MOR202, currently introduced in multiple myeloma (MM) therapy. Therefore, it is important to understand how antibody-mediated effector functions of myeloma-associated macrophages (MAMs) are regulated. Here, we focused on the effects of vitamin D, a known regulator of macrophage effector functions. Consequently, it was the aim of this study to assess whether modulation of the vitamin D pathway alters the tumoricidal activity of MAMs. Here, we demonstrate that MAMs display a defective vitamin D pathway with reduced expression level of CYP27B1 and limited tumoricidal activity which can be restored by the IMiD lenalidomide in vitro. Furthermore, our data indicate that the vitamin D pathway of MAMs from MM patients does recover during an IMiD-containing therapy shown by an improved MOR202-mediated cytotoxic activity of these MAMs against primary MM cells ex vivo. Here, the ex vivo cytotoxic activity could be further enhanced by vitamin D supplementation. These data suggest that vitamin D holds a key role for the effector functions of MAMs and that vitamin D supplementation in IMiD combination trials could further increase the therapeutic efficacy of anti-CD38 antibodies such as MOR202, which remains to be investigated in clinical studies.
EVALuna2:34165

Life style and Parkinson's disease - Reichmann, Heinz; Csoti, Ilona; Koschel, Jiri; Lorenzl, Stefan; Schrader, Christoph; Winkler, Jürgen; Wuellner, Ullrich (Journal of Neural Transmission, 2022)
The question whether life style may impair the advent or course of the disease in patients with Parkinsonism is of great importance for patients and physicians alike. We present here comprehensive information on the influence of the environment, diet (especially caffeine, nicotine, alcohol, chocolate and dairy products), physical activity and sleep on risk and course of Parkinson's disease.
CRIS-Team WoS Importer:2022-06-03

Lipid Peroxidation Drives Renal Cyst Growth In Vitro through Activation of TMEM16A - Schreiber, Rainer; Buchholz, Björn; Kraus, Andre; Schley, Gunnar; Scholz, Julia; Ousingsawat, Jiraporn; Kunzelmann, Karl (Journal of the American Society of Nephrology, 2019)
Background Transepithelial chloride2 secretion, through the chloride channels cystic fibrosis transmembrane conductance regulator (CFTR) and TMEM16A (anoctamin 1), drives cyst enlargement in polycystic kidney disease (PKD). Polycystic kidneys are hypoxic, and oxidative stress activates TMEM16A. However, mechanisms for channel activation in PKD remain obscure.Methods Using tissue samples from patients with autosomal dominant PKD, embryonic kidney cultures, and anMDCK in vitro cyst model, we assessed peroxidation of plasmamembrane phospholipids in human and mouse polycystic kidneys. We also used electrophysiologic Ussing chamber and patch clamp experiments to analyze activation of TMEM16A and growth of renal cysts.Results Peroxidation of phospholipids in human and mouse kidneys as well as MDCK cysts in vitro is probably due to enhanced levels of reactive oxygen species. Lipid peroxidation correlated with increased cyst volume as shown in renal cultures and MDCK cysts in three-dimensional cultures. Reactive oxygen species and lipid peroxidation strongly activated TMEM16A, leading to depletion of calciumion stores and store-operated calcium influx. Activation of TMEM16A-and CFTR-dependent chloride secretion strongly augmented cyst growth. Exposure to scavengers of reactive oxygen species, such as glutathione, coenzyme Q10, or idebenone (a synthetic coenzyme Q10 homolog), as well as inhibition of oxidative lipid damage by ferrostatin-1 largely reduced activation of TMEM16A. Inhibition of TMEM16A reduced proliferation and fluid secretion in vitro.Conclusions These findings indicate that activation of TMEM16A by lipid peroxidation drives growth of renal cysts. We propose direct inhibition of TMEM16A or inhibition of lipid peroxidation as potentially powerful therapeutic approaches to delay cyst development in PKD.
CRIS-Team WoS Importer:2019-02-27
Keywords: ADPKD; TMEM16A; reactive oxygen species; lipid peroxidation; ferroptosis; anoctamin 1

Loading of Primary Human T Lymphocytes with Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles Does Not Impair Their Activation after Polyclonal Stimulation - Mühlberger, Marina; Unterweger, Harald; Band, Julia; Lehmann, Christian; Heger, Lukas; Dudziak, Diana; Alexiou, Christoph; Lee, Geoffrey; Janko, Christina (Cells, 2020)
For the conversion of immunologically cold tumors, characterized by a low T cell infiltration, into hot tumors, it is necessary to enrich T cells in the tumor area. One possibility is the use of magnetic fields to direct T cells into the tumor. For this purpose, primary T cells that were freshly isolated from human whole blood were loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate). Cell toxicity and particle uptake were investigated by flow cytometry and atomic emission spectroscopy. The optimum loading of the T cells without any major effect on their viability was achieved with a particle concentration of 75 mu g Fe/mL and a loading period of 24 h. The cellular content of SPIONCitrate was sufficient to attract these T cells with a magnet which was monitored by live-cell imaging. The functionality of the T cells was only slightly influenced by SPIONCitrate, as demonstrated by in vitro stimulation assays. The proliferation rate as well as the expression of co-stimulatory and inhibitory surface molecules (programmed cell death 1 (PD-1), lymphocyte activation gene 3 (LAG-3), T cell immunoglobulin and mucin domain containing 3 (Tim-3), C-C motif chemokine receptor 7 (CCR7), CD25, CD45RO, CD69) was investigated and found to be unchanged. Our results presented here demonstrate the feasibility of loading primary human T lymphocytes with superparamagnetic iron oxide nanoparticles without influencing their viability and functionality while achieving sufficient magnetizability for magnetically controlled targeting. Thus, the results provide a strong fundament for the transfer to tumor models and ultimately for new immunotherapeutic approaches for cancer treatment.
CRIS-Team WoS Importer:2020-04-21

Localization of group II and III metabotropic glutamate receptors at pre- and postsynaptic sites of inner hair cell ribbon synapses - Klotz, Lisa; Wendler, Olaf; Frischknecht, Renato; Shigemoto, Ryuichi; Schulze, Holger; Enz, Ralf (The FASEB Journal, 2019)
Glutamate is the major excitatory neurotransmitter in the CNS binding to a variety of glutamate receptors. Metabotropic glutamate receptors (mGluR1 to mGluR8) can act excitatory or inhibitory, depending on associated signal cascades. Expression and localization of inhibitory acting mGluRs at inner hair cells (IHCs) in the cochlea are largely unknown. Here, we analyzed expression of mGluR2, mGluR3, mGluR4, mGluR6, mGluR7, and mGluR8 and investigated their localization with respect to the presynaptic ribbon of IHC synapses. We detected transcripts for mGluR2, mGluR3, and mGluR4 as well as for mGluR7a, mGluR7b, mGluR8a, and mGluR8b splice variants. Using receptor-specific antibodies in cochlear wholemounts, we found expression of mGluR2, mGluR4, and mGluR8b close to presynaptic ribbons. Super resolution and confocal microscopy in combination with 3-dimensional reconstructions indicated a postsynaptic localization of mGluR2 that overlaps with postsynaptic density protein 95 on dendrites of afferent type I spiral ganglion neurons. In contrast, mGluR4 and mGluR8b were expressed at the presynapse close to IHC ribbons. In summary, we localized in detail 3 mGluR types at IHC ribbon synapses, providing a fundament for new therapeutical strategies that could protect the cochlea against noxious stimuli and excitotoxicity.-Klotz, L., Wendler, O., Frischknecht, R., Shigemoto, R., Schulze, H., Enz, R. Localization of group II and III metabotropic glutamate receptors at pre- and postsynaptic sites of inner hair cell ribbon synapses.
CRIS-Team Scopus Importer:2019-12-17
Keywords: cochlea; IHC; mGlu receptor; mGluR

Locally renewing resident synovial macrophages provide a protective barrier for the joint - Culemann, Stephan; Grüneboom, Anika; Nicolás-Ávila, José Ángel; Weidner, Daniela; Lämmle, Katrin Franziska; Rothe, Tobias; Quintana, Juan A.; Kirchner, Philipp; Krljanac, Branislav; Eberhardt, Martin; Ferrazzi, Fulvia; Kretzschmar, Elke; et al. (Nature, 2019)
Macrophages are considered to contribute to chronic inflammatory diseases such as rheumatoid arthritis1. However, both the exact origin and the role of macrophages in inflammatory joint disease remain unclear. Here we use fate-mapping approaches in conjunction with three-dimensional light-sheet fluorescence microscopy and single-cell RNA sequencing to perform a comprehensive spatiotemporal analysis of the composition, origin and differentiation of subsets of macrophages within healthy and inflamed joints, and study the roles of these macrophages during arthritis. We find that dynamic membrane-like structures, consisting of a distinct population of CX3CR1+ tissue-resident macrophages, form an internal immunological barrier at the synovial lining and physically seclude the joint. These barrier-forming macrophages display features that are otherwise typical of epithelial cells, and maintain their numbers through a pool of locally proliferating CX3CR1− mononuclear cells that are embedded into the synovial tissue. Unlike recruited monocyte-derived macrophages, which actively contribute to joint inflammation, these epithelial-like CX3CR1+ lining macrophages restrict the inflammatory reaction by providing a tight-junction-mediated shield for intra-articular structures. Our data reveal an unexpected functional diversification among synovial macrophages and have important implications for the general role of macrophages in health and disease.
CRIS-Team Scopus Importer:2019-08-16

Macrophage migration inhibitory factor is regulated by HIF-1α and cAMP and promotes renal cyst cell proliferation in a macrophage-independent manner - Safi, Wajima; Kraus, Andre; Grampp, Steffen; Schödel, Johannes; Buchholz, Björn (Journal of Molecular Medicine, 2020)
Abstract: Progressive cyst growth leads to decline of renal function in polycystic kidney disease. Macrophage migration inhibitory factor (MIF) was found to be upregulated in cyst-lining cells in a mouse model of polycystic kidney disease and to promote cyst growth. In addition, MIF can be secreted by tubular cells and may contribute to cyst growth in an autocrine manner. However, the underlying mechanisms leading to induction of MIF in cyst-lining cells remained elusive. Here, we demonstrate that hypoxia-inducible transcription factor (HIF) 1α upregulates MIF in cyst-lining cells in a tubule-specific PKD1 knockout mouse. Pharmacological stabilization of HIF-1α resulted in significant increase of MIF in cyst epithelial cells whereas tubule-specific knockout of HIF-1α prevented MIF upregulation. Identical regulation could be found for ABCA1, which has been shown to act as a transport protein for MIF. Furthermore, we show that MIF and ABCA1 are direct target genes of HIF-1α in human primary tubular cells. Next to HIF-1α and hypoxia, we found MIF being additionally regulated by cAMP which is a strong promotor of cyst growth. In line with these findings, HIF-1α- and cAMP-dependent in vitro cyst growth could be decreased by the MIF-inhibitor ISO-1 which resulted in reduced cyst cell proliferation. In conclusion, HIF-1α and cAMP regulate MIF in primary tubular cells and cyst-lining epithelial cells, and MIF promotes cyst growth in the absence of macrophages. In line with these findings, the MIF inhibitor ISO-1 attenuates HIF-1α- and cAMP-dependent in vitro cyst enlargement. Key messages: • MIF is upregulated in cyst-lining cells in a polycystic kidney disease mouse model. • MIF upregulation is mediated by hypoxia-inducible transcription factor (HIF) 1α. • ABCA1, transport protein for MIF, is also regulated by HIF-1α in vitro and in vivo. • MIF is additionally regulated by cAMP, a strong promotor of cyst growth. • MIF-inhibitor ISO-1 reduces HIF-1α- and cAMP-dependent cyst growth.
CRIS-Team Scopus Importer:2020-09-11
Keywords: cAMP; Hypoxia-inducible factor 1α; Macrophage migration inhibitory factor; Polycystic kidney disease

Macrophage phosphoproteome analysis reveals MINCLE-dependent and-independent mycobacterial cord factor signaling - Hansen, Madlen; Peltier, Julian; Killy, Barbara; Amin, Bushra; Bodendorfer, Barbara; HäRtlova, Anetta; Uebel, Sebastian; Bosmann, Markus; Hofmann, Jörg; Büttner, Christian; Ekici, Arif Bülent; Kuttke, Mario; et al. (Molecular & Cellular Proteomics, 2019)
Immune sensing of Mycobacterium tuberculosis relies on recognition by macrophages. Mycobacterial cord factor, trehalose-6,6-dimycolate (TDM), is the most abundant cell wall glycolipid and binds to the C-type lectin receptor (CLR) MINCLE. To explore the kinase signaling linking the TDM-MINCLE interaction to gene expression, we employed quantitative phosphoproteome analysis. TDM caused upregulation of 6.7% and suppressed 3.8% of the 14,000 phospho-sites identified on 3727 proteins. MINCLE-dependent phosphorylation was observed for canonical players of CLR signaling (e.g. PLC, PKC), and was enriched for PKC and GSK3 kinase motifs. MINCLE-dependent activation of the PI3K-AKT-GSK3 pathway contributed to inflammatory gene expression and required the PI3K regulatory subunit p85. Unexpectedly, a substantial fraction of TDM-induced phosphorylation was MINCLE-independent, a finding paralleled by transcriptome data. Bioinformatics analysis of both data sets concurred in the requirement for MINCLE for innate immune response pathways and processes. In contrast, MINCLE-independent phosphorylation and transcriptome responses were linked to cell cycle regulation. Collectively, our global analyses show substantial reprogramming of macrophages by TDM and reveal a dichotomy of MINCLE-dependent and-independent signaling linked to distinct biological responses.
CRIS-Team Scopus Importer:2019-05-02

MAdCAM-1-Mediated Intestinal Lymphocyte Homing Is Critical for the Development of Active Experimental Autoimmune Encephalomyelitis - Kuhbandner, Kristina; Hammer, Anna; Haase, Stefanie; Terbrack, Elisa; Hoffmann, Alana; Schippers, Angela; Wagner, Norbert; Hussain, Rehana Z.; Miller-Little, William A.; Koh, Andrew Y.; Stoolman, Joshua S.; Segal, Benjamin M.; et al. (Frontiers in Immunology, 2019)
Lymphocyte homing into the intestine is mediated by binding of leukocytes to mucosal addressin cell adhesion molecule 1 (MAdCAM-1), expressed on endothelial cells. Currently, the immune system of the gut is considered a major modulator not only of inflammatory bowel disease, but also of extra-intestinal autoimmune disorders, including multiple sclerosis (MS). Despite of intense research in this field, the exact role of the intestine in the pathogenesis of (neuro-) inflammatory disease conditions remains to be clarified. This prompted us to investigate the role of MAdCAM-1 in immunological processes in the intestine during T cell-mediated autoimmunity of the central nervous system (CNS). Using the experimental autoimmune encephalomyelitis model of MS, we show that MAdCAM-1-deficient (MAdCAM-1-KO) mice are less susceptible to actively MOG35-55-induced disease. Protection from disease was accompanied by decreased numbers of immune cells in the lamina propria and Peyer's patches as well as reduced immune cell infiltration into the spinal cord. MOG35-55-recall responses were intact in other secondary lymphoid organs of MAdCAM-1-KO mice. The composition of specific bacterial groups within the microbiome did not differ between MAdCAM-1-KO mice and controls, while MAdCAM-1-deficiency severely impaired migration of MOG35-55-activated lymphocytes to the gut. Our data indicate a critical role of MAdCAM-1 in the development of CNS inflammation by regulating lymphocyte homing to the intestine, and may suggest a role for the intestinal tract in educating lymphocytes to become encephalitogenic.
CRIS-Team WoS Importer:2019-05-03

Management of Chronic Hepatic Itch - Düll, Miriam; Kremer, Andreas (Dermatologic Clinics, 2018)
Hepatic itch remains among the most agonizing symptoms for affected patients and a major clinical challenge for physicians. Pruritus may occur in almost all liver diseases, particularly those with cholestatic features. Hepatic itch arises irrespective of the severity of the underlying liver disease or extent of cholestasis. Antihistamines are ineffective in hepatic itch. Therapeutic recommendations consist of a guideline-based stepwise approach, starting with the anion exchange resin cholestyramine, followed by rifampicin, naltrexone, and sertraline. Bezafibrate and ileal bile acid transporter inhibitors are promising future treatment options. Experimental and invasive procedures should be reserved for refractory pruritus.
EVALuna2:35154

Mass spectrometry-based characterization of the virion proteome, phosphoproteome, and associated kinase activity of human cytomegalovirus - Couté, Yohann; Kraut, Alexandra; Zimmermann, Christine; Büscher, Nicole; Hesse, Anne Marie; Bruley, Christophe; De Andrea, Marco; Wangen, Christina; Hahn, Friedrich; Marschall, Manfred; Plachter, Bodo (Microorganisms, 2020)
The assembly of human cytomegalovirus (HCMV) virions is an orchestrated process that requires, as an essential prerequisite, the complex crosstalk between viral structural proteins. Currently, however, the mechanisms governing the successive steps in the constitution of virion protein complexes remain elusive. Protein phosphorylation is a key regulator determining the sequential changes in the conformation, binding, dynamics, and stability of proteins in the course of multiprotein assembly. In this review, we present a comprehensive map of the HCMV virion proteome, including a refined view on the virion phosphoproteome, based on previous publications supplemented by new results. Thus, a novel dataset of viral and cellular proteins contained in HCMV virions is generated, providing a basis for future analyses of individual phosphorylation steps and sites involved in the orchestrated assembly of HCMV virion-specific multiprotein complexes. Finally, we present the current knowledge on the activity of pUL97, the HCMV-encoded and virion-associated kinase, in phosphorylating viral and host proteins.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Human cytomegalovirus; Mass spectrometry-based proteomics; Phosphorylation; Proteins; Virion composition; Virionassociated kinase

Matricellular Protein SPARCL1 Regulates Blood Vessel Integrity and Antagonizes Inflammatory Bowel Disease - Regensburger, Daniela; Tenkerian, Clara; Pürzer, Victoria; Schmid, Benjamin; Wohlfahrt, Thomas; Stolzer, Iris; Lopez Posadas, Rocío; Günther, Claudia; Waldner, Maximilian; Becker, Christoph; Sticht, Heinrich; Petter, Katja; et al. (Inflammatory Bowel Diseases, 2021)
Background The understanding of vascular plasticity is key to defining the role of blood vessels in physiologic and pathogenic processes. In the present study, the impact of the vascular quiescence marker SPARCL1 on angiogenesis, capillary morphogenesis, and vessel integrity was evaluated. Methods Angiogenesis was studied using the metatarsal test, an ex vivo model of sprouting angiogenesis. In addition, acute and chronic dextran sodium sulfate colitis models with SPARCL1 knockout mice were applied. Results This approach indicated that SPARCL1 inhibits angiogenesis and supports vessel morphogenesis and integrity. Evidence was provided that SPARCL1-mediated stabilization of vessel integrity counteracts vessel permeability and inflammation in acute and chronic dextran sodium sulfate colitis models. Structure-function analyses of purified SPARCL1 identified the acidic domain of the protein necessary for its anti-angiogenic activity. Conclusions Our findings inaugurate SPARCL1 as a blood vessel–derived anti-angiogenic molecule required for vessel morphogenesis and integrity. SPARCL1 opens new perspectives as a vascular marker of susceptibility to colitis and as a therapeutic molecule to support blood vessel stability in this disease. <br
Keywords: angiogenesis; blood vessel; DSS colitis; endothelial cell; inflammatory bowel disease; permeability; SPARCL1

Matricellular protein SPARCL1 regulates tumor microenvironment-dependent endothelial cell heterogeneity in colorectal carcinoma - Naschberger, Elisabeth; Liebl, Andrea; Schellerer, Vera; Schütz, Manuela; Britzen-Laurent, Nathalie; Kölbel, Patrick; Schaal, Ute; Haep, Lisa; Regensburger, Daniela; Wittmann, Thomas; Klein-Hitpass, Ludger; Rau, Tilman; et al. (Journal of Clinical Investigation, 2016)
Different tumor microenvironments (TMEs) induce stromal cell plasticity that affects tumorigenesis. The impact of TME-dependent heterogeneity of tumor endothelial cells (TECs) on tumorigenesis is unclear. Here, we isolated pure TECs from human colorectal carcinomas (CRCs) that exhibited TMEs with either improved (Th1-TME CRCs) or worse clinical prognosis (control-TME CRCs). Transcriptome analyses identified markedly different gene clusters that reflected the tumorigenic and angiogenic activities of the respective TMEs. The gene encoding the matricellular protein SPARCL1 was most strongly upregulated in Th1-TME TECs. It was also highly expressed in ECs in healthy colon tissues and Th1-TME CRCs but low in control-TME CRCs. In vitro, SPARCL1 expression was induced in confluent, quiescent ECs and functionally contributed to EC quiescence by inhibiting proliferation, migration, and sprouting, whereas siRNA-mediated knockdown increased sprouting. In human CRC tissues and mouse models, vessels with SPARCL1 expression were larger and more densely covered by mural cells. SPARCL1 secretion from quiescent ECs inhibited mural cell migration, which likely led to stabilized mural cell coverage of mature vessels. Together, these findings demonstrate TME-dependent intertumoral TEC heterogeneity in CRC. They further indicate that TEC heterogeneity is regulated by SPARCL1, which promotes the cell quiescence and vessel homeostasis contributing to the favorable prognoses associated with Th1-TME CRCs.
EVALuna2:6838

Maturation of Monocyte-Derived DCs Leads to Increased Cellular Stiffness, Higher Membrane Fluidity, and Changed Lipid Composition - Luhr, Jennifer J.; Alex, Nils; Amon, Lukas; Krater, Martin; Kubankova, Marketa; Sezgin, Erdinc; Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Smith, Ana-Suncana; Zaburdaev, Vasily; Böckmann, Rainer; et al. (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are professional antigen-presenting cells of the immune system. Upon sensing pathogenic material in their environment, DCs start to mature, which includes cellular processes, such as antigen uptake, processing and presentation, as well as upregulation of costimulatory molecules and cytokine secretion. During maturation, DCs detach from peripheral tissues, migrate to the nearest lymph node, and find their way into the correct position in the net of the lymph node microenvironment to meet and interact with the respective T cells. We hypothesize that the maturation of DCs is well prepared and optimized leading to processes that alter various cellular characteristics from mechanics and metabolism to membrane properties. Here, we investigated the mechanical properties of monocyte-derived dendritic cells (moDCs) using real-time deformability cytometry to measure cytoskeletal changes and found that mature moDCs were stiffer compared to immature moDCs. These cellular changes likely play an important role in the processes of cell migration and T cell activation. As lipids constitute the building blocks of the plasma membrane, which, during maturation, need to adapt to the environment for migration and DC-T cell interaction, we performed an unbiased high-throughput lipidomics screening to identify the lipidome of moDCs. These analyses revealed that the overall lipid composition was significantly changed during moDC maturation, even implying an increase of storage lipids and differences of the relative abundance of membrane lipids upon maturation. Further, metadata analyses demonstrated that lipid changes were associated with the serum low-density lipoprotein (LDL) and cholesterol levels in the blood of the donors. Finally, using lipid packing imaging we found that the membrane of mature moDCs revealed a higher fluidity compared to immature moDCs. This comprehensive and quantitative characterization of maturation associated changes in moDCs sets the stage for improving their use in clinical application.
CRIS-Team Scopus Importer:2020-12-25
Keywords: cell mechanics; cellular stiffness; cholesterol; lipidomics; lipids; low-density lipoprotein; maturation; monocyte-derived dendritic cells

Mbd2 enables tumourigenesis within the intestine while preventing tumour-promoting inflammation - May, Stephanie; Owen, Heather; Phesse, Toby J.; Greenow, Kirsty R.; Jones, Gareth-Rhys; Blackwood, Adam; Cook, Peter C.; Towers, Christopher; Gallimore, Awen M.; Williams, Geraint T.; Stürzl, Michael; Britzen-Laurent, Nathalie; et al. (Journal of Pathology, 2018)
Epigenetic regulation plays a key role in the link between inflammation and cancer. Here we examine Mbd2, which mediates epigenetic transcriptional silencing by binding to methylated DNA. In separate studies the Mbd2-/- mouse has been shown (1) to be resistant to intestinal tumourigenesis and (2) to have an enhanced inflammatory/immune response, observations that are inconsistent with the links between inflammation and cancer. To clarify its role in tumourigenesis and inflammation, we used constitutive and conditional models of Mbd2 deletion to explore its epithelial and non-epithelial roles in the intestine. Using a conditional model, we found that suppression of intestinal tumourigenesis is due primarily to the absence of Mbd2 within the epithelia. Next, we demonstrated, using the DSS colitis model, that non-epithelial roles of Mbd2 are key in preventing the transition from acute to tumour-promoting chronic inflammation. Combining models revealed that prior to inflammation the altered Mbd2-/- immune response plays a role in intestinal tumour suppression. However, following inflammation the intestine converts from tumour suppressive to tumour promoting. To summarise, in the intestine the normal function of Mbd2 is exploited by cancer cells to enable tumourigenesis, while in the immune system it plays a key role in preventing tumour-enabling inflammation. Which role is dominant depends on the inflammation status of the intestine. As environmental interactions within the intestine can alter DNA methylation patterns, we propose that Mbd2 plays a key role in determining whether these interactions are anti- or pro-tumourigenic and this makes it a useful new epigenetic model for inflammation-associated carcinogenesis. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.
EVALuna2:210709

Melanoma sponge on pigmentation gene to reduce tumour-suppressive microRNAs - Dietrich, Peter; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2017)
EVALuna2:4760

Microglial expression of CD83 governs cellular activation and restrains neuroinflammation in experimental autoimmune encephalomyelitis - Sinner, Pia; Peckert-Maier, Katrin; Mohammadian, Hashem; Kuhnt, Christine; Draßner, Christina; Panagiotakopoulou, Vasiliki; Rauber, Simon; Linnerbauer, Mathias; Haimon, Zhana; Royzman, Dmytro; Kronenberg-Versteeg, Deborah; Ramming, Andreas; et al. (Nature Communications, 2023)
Microglial activation during neuroinflammation is crucial for coordinating the immune response against neuronal tissue, and the initial response of microglia determines the severity of neuro-inflammatory diseases. The CD83 molecule has been recently shown to modulate the activation status of dendritic cells and macrophages. Although the expression of CD83 is associated with early microglia activation in various disease settings, its functional relevance for microglial biology has been elusive. Here, we describe a thorough assessment of CD83 regulation in microglia and show that CD83 expression in murine microglia is not only associated with cellular activation but also with pro-resolving functions. Using single-cell RNA-sequencing, we reveal that conditional deletion of CD83 results in an over-activated state during neuroinflammation in the experimental autoimmune encephalomyelitis model. Subsequently, CD83-deficient microglia recruit more pathogenic immune cells to the central nervous system, deteriorating resolving mechanisms and exacerbating the disease. Thus, CD83 in murine microglia orchestrates cellular activation and, consequently, also the resolution of neuroinflammation.
CRIS-Team Scopus Importer:2023-08-11

Microphthalmia is not a mandatory finding in X-linked recessive syndromic microphthalmia caused by the recurrent BCOR variant p.Pro85Leu - Kraus, Cornelia; Uebe, Steffen; Thiel, Christian; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2018)
Mutations in BCOR cause X-linked dominant and X-linked recessive forms of syndromic microphthalmia. By exome sequencing, we identified the recurrent BCOR mutation p.Pro85Leu in two brothers and their unaffected mother. While the older brother's phenotype completely fits the described phenotypic spectrum of X-linked recessive BCOR-associated Lenz microphthalmia syndrome, the younger brother showed developmental delay, microcephaly, and skeletal anomalies, but not the key feature of microphthalmia. In contrast to the previously published families, our findings demonstrate a large variability of BCOR-associated, syndromic phenotypes, indicating incomplete penetrance of p.Pro85Leu with regards to microphthalmia in males.
EVALuna2:34843

MicroRNA-622 is a novel mediator of tumorigenicity in melanoma by targeting Kirsten rat sarcoma - Dietrich, Peter; Kuphal, Silke; Spruss, Thilo; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2018)
The network of molecular players is similar when comparing neural crest-derived, actively migrating melanoblasts to melanoma cells. However, melanoblasts are sensitive to differentiation-initiating signals at their target site (epidermis), while melanoma cells maintain migratory and undifferentiated features. We aimed at identifying downregulated genes in melanoma that are particularly upregulated in melanoblasts. Loss of such genes could contribute to stabilization of a dedifferentiated, malignant phenotype in melanoma. We determined that microRNA-622 (miR-622) expression was strongly downregulated in melanoma cells and tissues compared to melanocytes and melanoblast-related cells. miR-622 expression correlated with survival of patients with melanoma. miR-622 re-expression inhibited clonogenicity, proliferation, and migration in melanoma. Inhibition of miR-622 in melanocytes induced enhanced migration. Kirsten rat sarcoma (KRAS) was identified as a major functional target of miR-622 in melanoma. We conclude that miR-622 is a novel tumor suppressor in melanoma and identify the miR-622-KRAS axis as potential therapeutic target.
EVALuna2:34069

MiRNA-21 Expression Decreases from Primary Tumors to Liver Metastases in Colorectal Carcinoma - Feiersinger, Fabian; Nolte, Elke; Wach, Sven; Rau, Tilman; Vassos, Nikolaos; Geppert, Carol-Immanuel; Konrad, Andreas; Merkel, Susanne; Taubert, Helge; Stürzl, Michael; Croner, Roland S. (PLoS ONE, 2016)
Metastasis is the major cause of death in colorectal cancer patients. Expression of certain miRNAs in the primary tumors has been shown to be associated with progression of colorectal cancer and the initiation of metastasis. In this study, we compared miRNA expression in primary colorectal cancer and corresponding liver metastases in order to get an idea of the oncogenic importance of the miRNAs in established metastases.We analyzed the expression of miRNA-21, miRNA-31 and miRNA-373 in corresponding formalin-fixed paraffin-embedded (FFPE) tissue samples of primary colorectal cancer, liver metastasis and healthy tissues of 29 patients by quantitative real-time PCR.All three miRNAs were significantly up-regulated in the primary tumor tissues as compared to healthy colon mucosa of the respective patients (p < 0.01). MiRNA-21 and miRNA-31 were also higher expressed in liver metastases as compared to healthy liver tissues (p < 0.01). No significant difference of expression of miRNA-31 and miRNA-373 was observed between primary tumors and metastases. Of note, miRNA-21 expression was significantly reduced in liver metastases as compared to the primary colorectal tumors (p < 0.01).In the context of previous studies demonstrating increased miRNA-21 expression in metastatic primary tumors, our findings raise the question whether miRNA-21 might be involved in the initiation but not in the perpetuation and growth of metastases.
EVALuna2:6831

Missense Variants in RHOBTB2 Cause a Developmental and Epileptic Encephalopathy in Humans, and Altered Levels Cause Neurological Defects in Drosophila - Straub, Jonas; Konrad, Enrico; Grüner, Johanna; Toutain, Annick; Bok, Levinus A.; Cho, Megan T.; Crawford, Heather P.; Dubbs, Holly; Douglas, Ganka; Jobling, Rebekah; Johnson, Diana; Krock, Bryan; et al. (American Journal of Human Genetics, 2018)
Although the role of typical Rho GTPases and other Rho-linked proteins in synaptic plasticity and cognitive function and dysfunction is widely acknowledged, the role of atypical Rho GTPases (such as RHOBTB2) in neurodevelopment has barely been characterized. We have now identified de novo missense variants clustering in the BTB-domain-encoding region of RHOBTB2 in ten individuals with a similar phenotype, including early-onset epilepsy, severe intellectual disability, postnatal microcephaly, and movement disorders. Three of the variants were recurrent. Upon transfection of HEK293 cells, we found that mutant RHOBTB2 was more abundant than the wild-type, most likely because of impaired degradation in the proteasome. Similarly, elevated amounts of the Drosophila ortholog RhoBTB in vivo were associated with seizure susceptibility and severe locomotor defects. Knockdown of RhoBTB in the Drosophila dendritic arborization neurons resulted in a decreased number of dendrites, thus suggesting a role of RhoBTB in dendritic development. We have established missense variants in the BTB-domain-encoding region of RHOBTB2 as causative for a developmental and epileptic encephalopathy and have elucidated the role of atypical Rho GTPase RhoBTB in Drosophila neurological function and possibly dendrite development.
EVALuna2:33715

Modeling the spatial variability in the spread and correlation of childhood malnutrition in Nigeria - Gayawan, Ezra; Adebayo, Samson B.; Waldmann, Elisabeth (Statistics in Medicine, 2019)
The average nutritional status of children in Nigeria is, just as in most developing countries, still in an alarmingly bad condition. Prior studies have shown that this status relies on a series of different influences and can be measured by three anthropometric variables for stunting, wasting, and underweight. Different regression modeling techniques have been adopted over the years to explain the determinants and spatial clustering. Those indicators, however, show patterns that are not necessarily full filling requirements for ordinary regression models for the mean and are correlated among each other, a fact that has until now been ignored by most studies. Methods to model outcomes in the light of both, the whole distribution of and the correlation between two or more outcomes based on a set of covariates, have lately been developed. The aim of this paper is to make use of those methods to explain the underlying spatial structure in malnutrition in Nigeria. The study brings to limelight the pattern of spread as well as the interwoven relationships among childhood malnutrition indicators that would have otherwise remained unknown in Nigeria.
CRIS-Team WoS Importer:2019-05-07

Modulation of the extrinsic cell death signaling pathway by viral Flip induces acute-death mediated liver failure - Bittel, Miriam; Kremer, Andreas; Stürzl, Michael; Wirtz, Stefan; Stolzer, Iris; Neurath, Markus; Ballon, Gianna; Günther, Claudia (Cell Death & Disease, 2019)
During viral infections viruses express molecules that interfere with the host-cell death machinery and thus inhibit cell death responses. For example the viral FLIP (vFLIP) encoded by Kaposi’s sarcoma-associated herpesvirus interacts and inhibits the central cell death effector, Caspase-8. In order to analyze the impact of anti-apoptotic viral proteins, like vFlip, on liver physiology in vivo, mice expressing vFlip constitutively in hepatocytes (vFlipAlbCre+) were generated. Transgenic expression of vFlip caused severe liver tissue injury accompanied by massive hepatocellular necrosis and inflammation that finally culminated in early postnatal death of mice. On a molecular level, hepatocellular death was mediated by RIPK1-MLKL necroptosis driven by an autocrine TNF production. The loss of hepatocytes was accompanied by impaired bile acid production and disruption of the bile duct structure with impact on the liver-gut axis. Notably, embryonic development and tissue homeostasis were unaffected by vFlip expression. In summary our data uncovered that transgenic expression of vFlip can cause severe liver injury in mice, culminating in multiple organ insufficiency and death. These results demonstrate that viral cell death regulatory molecules exhibit different facets of activities beyond the inhibition of cell death that may merit more sophisticated in vitro and in vivo analysis.
CRIS-Team Scopus Importer:2019-12-03

Modulation of vaccine-induced HIV-1-specific immune responses by co-electroporation of PD-L1 encoding DNA - Tannig, Pierre; Peter, Antonia Sophia; Lapuente, Dennis; Klessing, Stephan; Damm, Dominik; Tenbusch, Matthias; Überla, Klaus; Temchura, Vladimir (Vaccines, 2020)
The importance of a balanced TH1/TH2 humoral immune response against the HIV-1 envelope protein (Env) for antibody-mediated HIV-1 control is increasingly recognized. However, there is no defined vaccination strategy to raise it. Since immune checkpoints are involved in the induction of adoptive immunity and their inhibitors (monoclonal antibodies) are licensed for cancer therapy, we investigated the effect of checkpoint blockade after HIV-1 genetic vaccination on enhancement and modulation of antiviral antibody responses. By intraperitoneal administration of checkpoint antibodies in mice we observed an induction of anti-drug antibodies which may interfere with immunomodulation by checkpoint inhibitors. Therefore, we blocked immune checkpoints locally by co-electroporation of DNA vaccines encoding the active soluble ectodomains of programmed cell death protein-1 (PD-1) or its ligand (PD-L1), respectively. Plasmid-encoded immune checkpoints did not elicit a detectable antibody response, suggesting no interference with their immunomodulatory effects. Co-electroporation of a HIV-1 DNA vaccine formulation with soluble PD-L1 ectodomain increased HIV-1 Env-specific TH1 CD4 T cell and IgG2a antibody responses. The overall antibody response was hereby shifted towards a more TH1/TH2 balanced subtype pattern. These findings indicate that co-electroporation of soluble checkpoint ectodomains together with DNA-based vaccines has modulatory effects on vaccine-induced immune responses that could improve vaccine efficacies.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Checkpoint blockade; Checkpoint inhibitors; HIV-1; Immunomodulation; Intramuscular electroporation; Soluble immune checkpoints

Molecular cross-talk between Y5-receptor and neuropeptide Y drives liver cancer - Dietrich, Peter; Wormser, Laura; Fritz, Valerie; Seitz, Tatjana; de Maria, Monica; Schambony, Alexandra; Kremer, Andreas; Günther, Claudia; Itzel, Timo; Thasler, Wolfgang E.; Teufel, Andreas; Trebicka, Jonel; et al. (Journal of Clinical Investigation, 2020)
Hepatocellular carcinoma (HCC) is clearly age-related and represents one of the deadliest cancer types worldwide. Due to globally increasing risk factors including metabolic disorders, the incidence rates of HCC are still rising. However, the molecular hallmarks of HCC remain poorly understood. Neuropeptide Y (NPY) and NPY-receptors represent a highly conserved, stress-activated system which is involved in diverse cancer-related hallmarks including aging and metabolic alterations, but its impact on liver cancer had been unclear. Here, we observed increased NPY5-receptor (Y5R) expression in HCC which correlated with tumor growth and survival. Furthermore, we found that its ligand NPY was secreted by peri-tumorous hepatocytes. Hepatocyte-derived NPY promoted HCC progression by Y5R-activation. Transforming growth factor beta 1 (TGFβ1) was identified as a regulator of NPY in hepatocytes and induced Y5R in invasive cancer cells. Moreover, NPY-conversion by dipeptidylpeptidase 4 (DPP4) augmented Y5R-activation and function in liver cancer. The TGFβ-NPY-Y5R-axis and DPP4 represent attractive therapeutic targets for controlling liver cancer progression.
EVALuna2:212290
Keywords: Aging; Cancer; Hepatology

Monocyte-Derived signals activate human natural Killer cells in response to Leishmania Parasites - Messlinger, Helena; Sebald, Heidi; Heger, Lukas; Dudziak, Diana; Bogdan, Christian; Schleicher, Ulrike (Frontiers in Immunology, 2018)
Activated natural killer (NK) cells release interferon (IFN)-gamma, which is crucial for the control of intracellular pathogens such as Leishmania. In contrast to experimental murine leishmaniasis, the human NK cell response to Leishmania is still poorly characterized. Here, we investigated the interaction of human blood NK cells with promastigotes of different Leishmania species (Leishmania major, Leishmania mexicana, Leishmania infantum, and Leishmania donovani). When peripheral blood mononuclear cells or purified NK cells and monocytes (all derived from healthy blood donors from Germany without a history of leishmaniasis) were exposed to promastigotes, NK cells showed increased surface expression of the activation marker CD69. The extent of this effect varied depending on the Leishmania species; differences between dermotropic and viscerotropic L. infantum strains were not observed. Upregulation of CD69 required direct contact between monocytes and Leishmania and was partly inhibitable by anti-interleukin (IL)-18. Unexpectedly, IL-18 was undetectable in most of the supernatants (SNs) of monocyte/parasite cocultures. Confocal fluorescence microscopy of non-permeabilized cells revealed that Leishmania-infected monocytes trans-presented IL-18 to NK cells. Native, but not heat-treated SNs of monocyte/Leishmania cocultures also induced CD69 on NK cells, indicating the involvement of a soluble heat-labile factor other than IL-18. A role for the NK cell-activating cytokines IL-1 beta, IL-2, IL-12, IL-15, IL-21, and IFN-alpha/beta was excluded. The increase of CD69 was not paralleled by NK cell IFN-gamma production or enhanced cytotoxicity. However, prior exposure of NK cells to Leishmania parasites synergistically increased their IFN-gamma release in response to IL-12, which was dependent on endogenous IL-18. CD1c(+) dendritic cells were identified as possible source of Leishmania-induced IL-12. Finally, we observed that direct contact between Leishmania and NK cells reduced the expression of CD56 mRNA and protein on NK cells. We conclude that Leishmania activate NK cells via trans-presentation of IL-18 by monocytes and by a monocyte-derived soluble factor. IL-12 is needed to elicit the IFN-gamma-response of NK cells, which is likely to be an important component of the innate control of the parasite.
EVALuna2:33305

Monocytes Elicit a Neutrophil-Independent Th1/Th17 Response Upon Immunization With a Mincle-Dependent Glycolipid Adjuvant - Desel, Christiane; Murray, Peter J.; Lehmann, Christian; Heger, Lukas; Christensen, Dennis; Andersen, Peter; Mack, Matthias; Dudziak, Diana; Lang, Roland (Frontiers in Immunology, 2022)
Successful subunit vaccination with recombinant proteins requires adjuvants. The glycolipid trehalose-dibehenate (TDB), a synthetic analog of the mycobacterial cord factor, potently induces Th1 and Th17 immune responses and is a candidate adjuvant for human immunization. TDB binds to the C-type lectin receptor Mincle and triggers Syk-Card9-dependent APC activation. In addition, interleukin (IL)-1 receptor/MyD88-dependent signaling is required for TDB adjuvanticity. The role of different innate immune cell types in adjuvant-stimulated Th1/Th17 responses is not well characterized. We investigated cell recruitment to the site of injection (SOI) and to the draining lymph nodes (dLNs) after immunization with the TDB containing adjuvant CAF01 in a protein-based vaccine. Recruitment of monocytes and neutrophils to the SOI and the dramatic increase in lymph node cellularity was partially dependent on both Mincle and MyD88. Despite their large numbers at the SOI, neutrophils were dispensable for the induction of Th1/Th17 responses. In contrast, CCR2-dependent monocyte recruitment was essential for the induction of Th1/Th17 cells. Transport of adjuvant to the dLN did not require Mincle, MyD88, or CCR2. Together, adjuvanticity conferred by monocytes can be separated at the cellular level from potential tissue damage by neutrophils.
CRIS-Team WoS Importer:2022-06-03

Monozygotic twins with a new compound heterozygous SPG11 mutation and different disease expression - Schneider-Gold, Christiane; Dekomien, Gabriele; Regensburger, Martin; Schneider, Ruth; Trampe, Nadine; Krogias, Christos; Lukas, Carsten; Bellenberg, Barbara (Journal of the Neurological Sciences, 2017)
BACKGROUND: A pair of monozygotic 22-year-old twins with complicated hereditary spastic paraplegia caused by a novel SPG11 mutation is described. METHODS: Genetic testing and thorough clinical examination, magnetic resonance imaging (MRI) and MR-spectroscopy were performed. RESULTS: The twins were compound heterozygous for a known frameshift as well as a novel splice site mutation in the SPG11 gene. Clinically the patients showed a similar spectrum of symptoms but different disease presentation. MRI studies including morphometry and regional microstructural analysis by diffusion tensor imaging (DTI) of the corpus callosum (CC) by 3T MRI revealed marked thinning and corresponding increases of radial diffusivity (RD) and apparent diffusion coefficient (ADC) and reduction of the fractional anisotropy (FA) as compared to controls in all CC sections, particularly in the anterior callosal body. There was marked mainly supratentorial white matter reduction and to a lesser extent grey matter reduction in both patients. Involvement of the cortico-spinal tracts was reflected by FA and RD alterations. The more strongly affected patient showed a higher degree of callosal microstructural damage and cervical cord atrophy. CONCLUSIONS: This study shows a similar symptom spectrum, but distinct clinical and imaging findings in monozygotic twins suffering from SPG 11, suggesting individual downstream genetic effects and/or non-genetic modifiers.
EVALuna2:35715

Multiomic spatial landscape of innate immune cells at human central nervous system borders - Sankowski, Roman; Süß, Patrick; Benkendorff, Alexander; Böttcher, Chotima; Fernandez-Zapata, Camila; Chhatbar, Chintan; Cahueau, Jonathan; Monaco, Gianni; Gasull, Adrià Dalmau; Khavaran, Ashkan; Grauvogel, Jürgen; Scheiwe, Christian; et al. (Nature Medicine, 2023)
The innate immune compartment of the human central nervous system (CNS) is highly diverse and includes several immune-cell populations such as macrophages that are frequent in the brain parenchyma (microglia) and less numerous at the brain interfaces as CNS-associated macrophages (CAMs). Due to their scantiness and particular location, little is known about the presence of temporally and spatially restricted CAM subclasses during development, health and perturbation. Here we combined single-cell RNA sequencing, time-of-flight mass cytometry and single-cell spatial transcriptomics with fate mapping and advanced immunohistochemistry to comprehensively characterize the immune system at human CNS interfaces with over 356,000 analyzed transcriptomes from 102 individuals. We also provide a comprehensive analysis of resident and engrafted myeloid cells in the brains of 15 individuals with peripheral blood stem cell transplantation, revealing compartment-specific engraftment rates across different CNS interfaces. Integrated multiomic and high-resolution spatial transcriptome analysis of anatomically dissected glioblastoma samples shows regionally distinct myeloid cell-type distributions driven by hypoxia. Notably, the glioblastoma-associated hypoxia response was distinct from the physiological hypoxia response in fetal microglia and CAMs. Our results highlight myeloid diversity at the interfaces of the human CNS with the periphery and provide insights into the complexities of the human brain’s immune system.
CRIS-Team Scopus Importer:2023-12-29

Multiplex gene analysis reveals T-cell and antibody-mediated rejection-specific upregulation of complement in renal transplants - Vonbrunn, Eva; Ries, Tajana; Söllner, Stefan; Müller-Deile, Janina; Büttner, Maike; Amann, Kerstin Ute; Daniel, Christoph (Scientific Reports, 2021)
In renal transplantation, complement is involved in ischemia reperfusion injury, graft rejection and dysfunction. However, it is still unclear how induction of complement and its activation are initiated. Using allograft biopsies of a well-characterized cohort of 28 renal transplant patients with no rejection (Ctrl), delayed graft function (DGF), acute T-cell-mediated (TCMR) or antibody-mediated rejection (ABMR) we analyzed differences in complement reaction. For that mRNA was isolated from FFPE sections, quantified with a multiplex gene expression panel and correlated with transplant conditions and follow-up of patients. Additionally, inflammatory cells were quantified by multiplex immunohistochemistry. In allograft biopsies with TCMR and ABMR gene expression of C1QB was 2-4 fold elevated compared to Ctrl. In TCMR biopsies, mRNA counts of several complement-related genes including C1S, C3, CFB and complement regulators CFH, CR1 and SERPING1 were significantly increased compared to Ctrl. Interestingly, expression levels of about 75% of the analyzed complement related genes correlated with cold ischemia time (CIT) and markers of inflammation. In conclusion, this study suggest an important role of complement in transplant pathology which seems to be at least in part triggered by CIT. Multiplex mRNA analysis might be a useful method to refine diagnosis and explore new pathways involved in rejection.
CRIS-Team Scopus Importer:2021-08-13

Multispectral Optoacoustic Tomography for Assessment of Crohn's Disease Activity - Knieling, Ferdinand; Neufert, Clemens; Hartmann, Arndt; Claussen, Jing; Urich, Alexander; Egger, Cornelia; Vetter, Marcel; Fischer, Sarah; Pfeifer, Lukas; Hagel, Alexander; Kielisch, Christian; Görtz, Rüdiger; et al. (New England Journal of Medicine, 2017)
EVALuna2:33821

Multispectral optoacoustic tomography for non-invasive disease phenotyping in pediatric spinal muscular atrophy patients - Regensburger, Adrian; Wagner, Alexandra; Danko, Vera; Jüngert, Jörg M.; Federle, Anna; Klett, Daniel; Schüssler, Stephanie; Buehler, Adrian; Neurath, Markus; Roos, Andreas; Lochmüller, Hanns; Wölfle, Joachim; et al. (Photoacoustics, 2022)
Proximal spinal muscular atrophy (SMA) is a rare progressive, life limiting genetic motor neuron disease. While promising causal therapies are available, meaningful prognostic biomarkers for therapeutic monitoring are missing. We demonstrate handheld Multispectral Optoacoustic Tomography (MSOT) as a novel non-invasive imaging approach to visualize and quantify muscle wasting in pediatric SMA. While MSOT signals were distributed homogeneously in muscles of healthy volunteers (HVs), SMA patients showed moth-eaten optoacoustic signal patterns. Further signal quantification revealed greatest differences between groups at the isosbestic point for hemoglobin (SWL 800 nm). The SWL 800 nm signal intensities further correlated with clinical phenotype tested by standard motor outcome measures. Therefore, handheld MSOT could enable non-invasive assessment of disease burden in SMA patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Multispectral optoacoustic tomography; Optoacoustics; Photoacoustics; Spinal muscular atrophie

Multispectral optoacoustic tomography of the human intestine – temporal precision and the influence of postprandial gastrointestinal blood flow - Paulus, Lars-Philip; Wagner, Alexandra; Buehler, Adrian; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Günther, Josefine; Rother, Ulrich; Lang, Werner; Hörning, André; et al. (Photoacoustics, 2023)
Multispectral optoacoustic tomography (MSOT) holds great promise as a non-invasive diagnostic tool for inflammatory bowel diseases. Yet, reliability and the impact of physiological processes during fasting and after food intake on optoacoustic signals have not been studied. In the present investigator initiated trial (NCT05160077) the intestines of ten healthy subjects were examined by MSOT at eight timepoints on two days, one fasting and one after food intake. While within-timepoint and within-day reproducibility were good for single wavelength 800 nm and total hemoglobin (ICC 0.722–0.956), between-day reproducibility was inferior (ICC −0.137 to 0.438). However, temporal variability was smaller than variation between individuals (coefficients of variation 8.9%−33.7% vs. 17.0%−48.5%). After food intake and consecutive increased intestinal circulation, indicated by reduced resistance index of simultaneous Doppler ultrasound, optoacoustic signals did not alter significantly. In summary, this study demonstrates high reliability and temporal stability of MSOT for imaging the human intestine during fasting and after food intake.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Gut; Inflammatory bowel disease; Intestinal blood flow; Multispectral optoacoustic imaging; Optoacoustic; Photoacoustic; Postprandial; Reliability; Reproducibility

Murine cytomegalovirus reactivation concomitant with acute graft-versus-host disease is controlled by antibodies. - Seefried, Martina; Hundhausen, Nadine; Kroeger, Irena; Büttner-Herold, Maike; Hoffmann, Petra; Edinger, Matthias; Ullrich, Evelyn; Berberich-Siebelt, Friederike; Britt, William J.; Mach, Michael; Winkler, Thomas (JCI Insight, 2023)
Reactivation of human cytomegalovirus (HCMV) from latency is a frequent complication following hematopoietic stem cell transplantation (HSCT). The development of acute graft-versus-host disease (GVHD) is a significant risk factor for HCMV disease. Using a murine GVHD model in animals latently infected with murine CMV (MCMV), we studied preventive and therapeutic interventions in this high-risk scenario of HSCT. Mice latently infected with MCMV experienced reactivated MCMV and developed disseminated MCMV infection concomitant with the manifestations of GVHD. Dissemination was accompanied by accelerated mortality. We demonstrate that MCMV reactivation and dissemination was modulated by MCMV-specific antibodies, thus demonstrating in vivo protective activity of antiviral antibodies. However, the efficacy of serum therapy required repetitive doses of high-titer immune serum secondary to the shortened serum half-life of IgG in animals with GVHD. In a complementary approach, treatment of GVHD by adoptive transfer of donor-derived Tregs facilitated production of MCMV-specific antibodies from newly developing donor-derived B cells. Together, our findings strongly suggest that antibodies play a major role in controlling recurrent MCMV infection that follows GVHD, and they argue for reassessing the potential of antibody treatments as well as therapeutic strategies that enhance de novo antibody development against HCMV.
EVALuna2:527934

Murine eosinophil development and allergic lung eosinophilia are largely dependent on the signaling adaptor GRB2 - Willebrand, Ralf; Dietschmann, Axel; Nitschke, Lars; Krappmann, Sven; Vöhringer, David (European Journal of Immunology, 2018)
Eosinophils are innate effector cells associated with allergic inflammation. Their development and survival is largely dependent on IL-5 and the common beta chain (βc ) of the IL-5 receptor that serves as docking site for several proteins that mediate down-stream signaling cascades including JAK/STAT, PI3 kinase, NFκB, and RAS-MAP kinase pathways. The relative contribution of these signaling pathways for eosinophil development and homeostasis in vivo are poorly understood. Here, we investigated the role of GRB2, an adaptor protein that binds to βc and other proteins and elicits the RAS-MAP kinase pathway. By using GRB2 inhibitors and inducible deletion of the Grb2 gene in mouse eosinophils we demonstrate that GRB2 plays a critical role for development of eosinophils from bone marrow precursors. Furthermore, Aspergillus fumigatus-induced allergic lung eosinophilia was significantly reduced in mice with induced genetic deletion of Grb2. Our results indicate that GRB2 is important for eosinophil development in steady-state conditions and during allergic inflammation. Based on these findings pharmacologic GRB2 inhibitors may have the potential to dampen tissue eosinophilia in various eosinophil-associated diseases.
EVALuna2:36387

Need for high-resolution Genetic Analysis in iPSC: Results and Lessons from the ForIPS Consortium - Popp, Bernt; Krumbiegel, Mandy; Grosch, Janina; Sommer, Annika; Uebe, Steffen; Kohl, Zacharias; Ploetz, Sonja; Farrell, Michaela; Trautmann, Udo; Kraus, Cornelia; Ekici, Arif Bülent; Asadollahi, Reza; et al. (Scientific Reports, 2018)
Genetic integrity of induced pluripotent stem cells (iPSCs) is essential for their validity as disease models and for potential therapeutic use. We describe the comprehensive analysis in the ForIPS consortium: an iPSC collection from donors with neurological diseases and healthy controls. Characterization included pluripotency confirmation, fingerprinting, conventional and molecular karyotyping in all lines. In the majority, somatic copy number variants (CNVs) were identified. A subset with available matched donor DNA was selected for comparative exome sequencing. We identified single nucleotide variants (SNVs) at different allelic frequencies in each clone with high variability in mutational load. Low frequencies of variants in parental fibroblasts highlight the importance of germline samples. Somatic variant number was independent from reprogramming, cell type and passage. Comparison with disease genes and prediction scores suggest biological relevance for some variants. We show that high-throughput sequencing has value beyond SNV detection and the requirement to individually evaluate each clone.
EVALuna2:34839

Neprilysin-dependent neuropeptide Y cleavage in the liver promotes fibrosis by blocking NPY-receptor 1 - Ortiz, Cristina; Klein, Sabine; Reul, Winfried H.; Magdaleno, Fernando; Groeschl, Stefanie; Dietrich, Peter; Schierwagen, Robert; Uschner, Frank E.; Torres, Sandra; Hieber, Christoph; Meier, Caroline; Kraus, Nico; et al. (Cell Reports, 2023)
Development of liver fibrosis is paralleled by contraction of hepatic stellate cells (HSCs), the main profibrotic hepatic cells. Yet, little is known about the interplay of neprilysin (NEP) and its substrate neuropeptide Y (NPY), a potent enhancer of contraction, in liver fibrosis. We demonstrate that HSCs are the source of NEP. Importantly, NPY originates majorly from the splanchnic region and is cleaved by NEP in order to termi-nate contraction. Interestingly, NEP deficiency (Nep-/-) showed less fibrosis but portal hypertension upon liver injury in two different fibrosis models in mice. We demonstrate the incremental benefit of Nep-/-in addi-tion to AT1R blocker (ARB) or ACE inhibitors for fibrosis and portal hypertension. Finally, oral administration of Entresto, a combination of ARB and NEP inhibitor, decreased hepatic fibrosis and portal pressure in mice. These results provide a mechanistic rationale for translation of NEP-AT1R-blockade in human liver fibrosis and portal hypertension.
CRIS-Team WoS Importer:2023-03-17

Neuroblastoma RAS Viral Oncogene Homolog (NRAS) Is a Novel Prognostic Marker and Contributes to Sorafenib Resistance in Hepatocellular Carcinoma - Dietrich, Peter; Gaza, Anne; Wormser, Laura; Fritz, Valerie; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Neoplasia, 2019)
Inhibition of the RAS-RAF-ERK-pathway using sorafenib as a first-line and regorafenib as a second-line treatment approach is the only effective therapeutic strategy for advanced hepatocellular carcinoma (HCC). Recent studies suggest that wild-type KRAS and HRAS isoforms could majorly contribute to HCC progression and sorafenib resistance. In contrast, the role of neuroblastoma RAS viral oncogene homolog (NRAS) in HCC remained elusive. In this study, wild-type NRAS was found to be overexpressed in HCC cell lines, preclinical HCC models, and human HCC tissues. Moreover, NRAS overexpression correlated with poor survival and proliferation in vivo. However, siRNA-pool-mediated NRAS knockdown showed only slight effects on HCC proliferation, clonogenicity, and AKT activity. We determined that KRAS upregulation served as a functional compensatory mechanism in the absence of NRAS, which was overcome by combined inhibition of NRAS and KRAS in HCC cells. Furthermore, NRAS expression was elevated in sorafenib-resistant compared to nonresistant HCC cells, and NRAS knockdown enhanced sorafenib efficacy in resistant cells. In summary, NRAS appears to be a prognostic marker in HCC and contributes to sorafenib resistance. Regarding potential therapeutic strategies, NRAS inhibition in HCC should be combined with KRAS inhibition to prevent KRAS-mediated rescue effects.
CRIS-Team WoS Importer:2019-03-20

Neurodegeneration Enhances the Development of Arthritis - Lang, Stefanie; Harre, Ulrike; Purohit, Pavitra; Dietel, Katharina; Kienhöfer, Deborah; Hahn, Jonas; Baum, Wolfgang; Herrmann, Martin; Schett, Georg; Mielenz, Dirk (Journal of Immunology, 2017)
The prevalence of neurodegenerative disease and arthritis increases with age. Despite both processes being associated with immune activation and inflammation, little is known about the mechanistic interactions between neurodegenerative disease and arthritis. In this article, we show that tau-transgenic (tau-tg) mice that develop neurodegenerative disease characterized by deposition of tau tangles in the brain are highly susceptible to developing arthritis. Already at steady-state conditions, tau-tg mice exhibit peripheral immune activation that is manifested by higher numbers of granulocytes, plasmablasts, and inflammatory Ly6C(hi) CCR2(+) monocytes, as well as increased levels of proinflammatory cytokines, such as TNF-? and IL-17. Upon induction of collagen-induced arthritis (CIA), tau-tg mice displayed an increased incidence and an earlier onset of CIA that was associated with a more pronounced inflammatory cytokine response. Furthermore, induction of CIA led to significantly elevated numbers of Iba-1-expressing cells in the brain, indicative of microglia activation, and the formation of anti-tau Abs in tau-tg mice. These changes were accompanied by the resolution of tau tangles and significantly decreased neurodegenerative pathology. In summary, these data show that neurodegenerative disease enhances the development of arthritis. In addition, arthritis, once induced, triggers innate immune responses in the brain, leading to resolution of neurodegenerative change
EVALuna2:13302

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.

Neutrophils prevent rectal bleeding in ulcerative colitis by peptidyl-arginine deiminase-4-dependent immunothrombosis - Leppkes, Moritz; Lindemann, Aylin; Goesswein, Stefanie; Paulus, Susanne; Roth, Dominik; Hartung, Anne; Liebing, Eva; Zundler, Sebastian; Gonzalez-Acera, Miguel; Patankar, Jay; Mascia, Fabrizio; Scheibe, Kristina; et al. (Gut, 2021)
Objective Bleeding ulcers and erosions are hallmarks of active ulcerative colitis (UC). However, the mechanisms controlling bleeding and mucosal haemostasis remain elusive. Design We used high-resolution endoscopy and colon tissue samples of active UC (n = 36) as well as experimental models of physical and chemical mucosal damage in mice deficient for peptidyl-arginine deiminase-4 (PAD4), gnotobiotic mice and controls. We employed endoscopy, histochemistry, live-cell microscopy and flow cytometry to study eroded mucosal surfaces during mucosal haemostasis. Results Erosions and ulcerations in UC were covered by fresh blood, haematin or fibrin visible by endoscopy. Fibrin layers rather than fresh blood or haematin on erosions were inversely correlated with rectal bleeding in UC. Fibrin layers contained ample amounts of neutrophils coaggregated with neutrophil extracellular traps (NETs) with detectable activity of PAD. Transcriptome analyses showed significantly elevated PAD4 expression in active UC. In experimentally inflicted wounds, we found that neutrophils underwent NET formation in a PAD4-dependent manner hours after formation of primary blood clots, and remodelled clots to immunothrombi containing citrullinated histones, even in the absence of microbiota. PAD4-deficient mice experienced an exacerbated course of dextrane sodium sulfate-induced colitis with markedly increased rectal bleeding (96 % vs 10 %) as compared with controls. PAD4-deficient mice failed to remodel blood clots on mucosal wounds eliciting impaired healing. Thus, NET-associated immunothrombi are protective in acute colitis, while insufficient immunothrombosis is associated with rectal bleeding. Conclusion Our findings uncover that neutrophils induce secondary immunothrombosis by PAD4-dependent mechanisms. Insufficient immunothrombosis may favour rectal bleeding in UC.
CRIS-Team WoS Importer:2021-12-17

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion

Nintedanib macrophage activation and ameliorates vascular and fibrotic manifestations in the Fra2 mouse model of systemic sclerosis - Huang, Jingang; Maier, Christiane; Zhang, Yun; Soare, Alina; Dees, Clara; Beyer, Christian; Harre, Ulrike; Chen, Chih-Wei; Distler, Oliver; Schett, Georg; Wollin, Lutz; Distler, Jörg (Annals of the Rheumatic Diseases, 2017)
Nintedanib is an inhibitor targeting platelet-derived growth factor receptor, fibroblast growth factor receptor and vascular endothelial growth factor receptor tyrosine kinases that has recently been approved for the treatment of idiopathic pulmonary fibrosis. The aim of this study was to analyse the effects of nintedanib in the fos-related antigen-2 (Fra2) mouse model of systemic sclerosis (SSc).The effects of nintedanib on pulmonary arterial hypertension with proliferation of pulmonary vascular smooth muscle cells (PVSMCs) and luminal occlusion, on microvascular disease with apoptosis of microvascular endothelial cells (MVECs) and on fibroblast activation with myofibroblast differentiation and accumulation of extracellular matrix were analysed. We also studied the effects of nintedanib on the levels of key mediators involved in the pathogenesis of SSc and on macrophage polarisation.Nintedanib inhibited proliferation of PVSMCs and prevented thickening of the vessel walls and luminal occlusion of pulmonary arteries. Treatment with nintedanib also inhibited apoptosis of MVECs and blunted the capillary rarefaction in Fra2-transgenic mice. These effects were associated with a normalisation of the serum levels of vascular endothelial growth factor in Fra2 mice on treatment with nintedanib. Nintedanib also effectively blocked myofibroblast differentiation and reduced pulmonary, dermal and myocardial fibrosis in Fra2-transgenic mice. The antifibrotic effects of nintedanib were associated with impaired M2 polarisation of monocytes and reduced numbers of M2 macrophages.Nintedanib targets core features of SSc in Fra2-transgenic mice and ameliorates histological features of pulmonary arterial hypertension, destructive microangiopathy and pulmonary and dermal fibrosis. These data might have direct implications for the ongoing phase III clinical trial with nintedanib in SSc-associated interstitial lung diseas
EVALuna2:13441

NLRP3 Inhibition Leads to Impaired Mucosal Fibroblast Function in Patients with Inflammatory Bowel Diseases - Weber, Simone; Sitte, Selina; Vögele, Anna-Lena; Sologub, Ludmilla; Wilfer, Angelika; Rath, Timo; Nägel, Andreas; Zundler, Sebastian; Franchi, Luigi; Opipari, Anthony W.; Sonnewald, Sophia; Reid, Stephen; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: Inflammatory bowel diseases (IBD) are characterized by mucosal inflammation and sequential fibrosis formation, but the exact role of the hyperactive NLRP3 inflammasome in these processes is unclear. Thus, we studied the expression and function of the NLRP3 inflammasome in the context of inflammation and fibrosis in IBD. Methods: We analysed intestinal NLRP3 expression in mucosal immune cells and fibroblasts from IBD patients and NLRP3-associated gene expression via single-cell RNA sequencing and microarray analyses. Furthermore, cytokine secretion of NLRP3 inhibitor treated blood and mucosal cells, as well as proliferation, collagen production, and cell death of NLRP3 inhibitor treated intestinal fibroblasts from IBD patients were studied. Results: We found increased NLRP3 expression in the inflamed mucosa of IBD patients and NLRP3 inhibition led to reduced IL-1β and IL-18 production in blood cells and diminished the bioactive form of mucosal IL-1β. Single cell analysis identified overlapping expression patterns of NLRP3 and IL-1β in classically activated intestinal macrophages and we also detected NLRP3 expression in CD163+ macrophages. In addition, NLRP3 expression was also found in intestinal fibroblasts from IBD patients. Inhibition of NLRP3 led to reduced proliferation of intestinal fibroblasts, which was associated with a marked decrease in production of collagen type I and type VI in IBD patients. Moreover, NLRP3 inhibition in intestinal fibroblasts induced autophagy, a cellular process involved in collagen degradation. Conclusions: In the presented study, we demonstrate that inhibiting NLRP3 might pave the way for novel therapeutic approaches in IBD, especially to prevent the severe complication of intestinal fibrosis formation.
CRIS-Team Scopus Importer:2023-11-17
Keywords: fibroblasts; fibrosis; IL-18; IL-1β; Inflammatory bowel diseases; mucosal immune system; NLRP3 inflammasome; small molecule inhibitor

Non-classical monocyte homing to the gut via α4β7 integrin mediates macrophage-dependent intestinal wound healing - Schleier, Lena; Wiendl, Maximilian; Heidbreder, Karin; Binder, Marie Theres; Atreya, Raja; Rath, Timo; Becker, Elisabeth; Schulz-Kuhnt, Anja; Stahl, Annette; Schulze, Lisa; Ullrich, Karen; Merz, Simon F.; et al. (Gut, 2019)
Objective: To study the role of α4β7 integrin for gut homing of monocytes and to explore the biological consequences of therapeutic α4β7 inhibition with regard to intestinal wound healing. Design: We studied the expression of homing markers on monocyte subsets in the peripheral blood and on macrophage subsets in the gut of patients with IBD and controls with flow cytometry and immunohistochemistry. Integrin function was addressed with dynamic adhesion assays and in vivo gut homing assays. In vivo wound healing was studied in mice deficient for or depleted of α4β7 integrin. Results: Classical and non-classical monocytes were clearly dichotomous regarding homing marker expression including relevant expression of α4β7 integrin on human and mouse non-classical monocytes but not on classical monocytes. Monocyte-expressed α4β7 integrin was functionally important for dynamic adhesion to mucosal vascular addressin cell adhesion molecule 1 and in vivo gut homing. Impaired α4β7-dependent gut homing was associated with reduced (effect size about 20%) and delayed wound healing and suppressed perilesional presence of wound healing macrophages. Non-classical monocytes in the peripheral blood were increased in patients with IBD under clinical treatment with vedolizumab. Conclusion: In addition to reported effects on lymphocytes, anti-α4β7 therapy in IBD also targets non-classical monocytes. Impaired gut homing of such monocytes might lead to a reduction of wound healing macrophages and could potentially explain increased rates of postoperative complications in vedolizumab-treated patients, which have been observed in some studies.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Crohn's disease; gut immunology; inflammatory bowel disease; surgery for IBD; ulcerative colitis

Non-invasive metabolic profiling of inflammation in joints and entheses by multispectral optoacoustic tomography - Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Bayat, Sara; Heidemann, Robert; Steiger, Florian; Krönke, Gerhard; Bohr, Daniela; Ramming, Andreas; Hartmann, Fabian; Klett, Daniel; Federle, Anna; et al. (Rheumatology, 2022)
Objective To explore the metabolic characteristics of arthritis and enthesitis using multispectral opto-acoustic tomography (MSOT), a technology using near-infrared multispectral laser to stimulate tissues and detect the emitted acoustic energy, enabling non-invasive quantification of tissue components in vivo based on differential absorbance at multiple wavelengths. Methods We performed a cross-sectional study in patients with RA or PsA and healthy controls (HCs). Participants underwent clinical, ultrasonographic and MSOT examination of MCP and wrist joints as well as the entheses of the common extensor tendon at the lateral humeral epicondyles and of the patellar, quadriceps and Achilles tendon. MSOT-measured haemoglobin (Hb), oxygen saturation, collagen and lipid levels were quantified and scaled mean differences between affected and unaffected joints and entheses were calculated as defined by clinical examination or ultrasonography using linear mixed effects models. Results We obtained 1535 MSOT and 982 ultrasonography scans from 87 participants (34 PsA, 17 RA, 36 HCs). Entheseal tenderness was not associated with significant metabolic changes, whereas enthesitis-related sonographic changes were associated with increased total Hb, oxygen saturation and collagen content. In contrast, the presence of arthritis-related clinical and sonographic findings showed increased Hb levels, reduced oxygen saturation and reduced collagen content. Synovial hypertrophy was associated with increased lipid content in the joints. Conclusion MSOT allows determination of distinct metabolic differences between arthritis and enthesitis in a non-invasive setting in humans in vivo.
CRIS-Team WoS Importer:2022-07-22

Non-redundant functions of EMT transcription factors - Stemmler, Marc; Eccles, Rebecca; Brabletz, Simone; Brabletz, Thomas (Nature Cell Biology, 2019)
Epithelial-mesenchymal transition (EMT) is a crucial embryonic programme that is executed by various EMT transcription factors (EMT-TFs) and is aberrantly activated in cancer and other diseases. However, the causal role of EMT and EMT-TFs in different disease processes, especially cancer and metastasis, continues to be debated. In this Review, we identify and describe specific, non-redundant functions of the different EMT-TFs and discuss the reasons that may underlie disputes about EMT in cancer.
EVALuna2:35254

Novel role of a triglyceride-synthesizing enzyme: DGAT1 at the crossroad between triglyceride and cholesterol metabolism - Sachdev, Vinay; Leopold, Christina; Bauer, Raimund; Patankar, Jay V.; Iqbal, Jahangir; Obrowsky, Sascha; Boverhof, Renze; Doktorova, Marcela; Scheicher, Bernhard; Goeritzer, Madeleine; Kolb, Dagmar; Turnbull, Andrew V.; et al. (Biochimica Et Biophysica Acta-Molecular and Cell Biology of Lipids, 2016)
Acyl-CoA:diacylglycerol acyltransferase 1 (DGAT1) is a key enzyme in triacylglycerol (TG) biosynthesis. Here we show that genetic deficiency and pharmacological inhibition of DGAT1 in mice alters cholesterol metabolism. Cholesterol absorption, as assessed by acute cholesterol uptake, was significantly decreased in the small intestine and liver upon DGAT1 deficiency/inhibition. Ablation of DGAT1 in the intestine (I-DGAT1−/−) alone is sufficient to cause these effects. Consequences of I-DGAT1 deficiency phenocopy findings in whole-body DGAT1−/− and DGAT1 inhibitor-treated mice. We show that deficiency/inhibition of DGAT1 affects cholesterol metabolism via reduced chylomicron size and increased trans-intestinal cholesterol excretion. These effects are independent of cholesterol uptake at the apical surface of enterocytes but mediated through altered dietary fatty acid metabolism. Our findings provide insight into a novel role of DGAT1 and identify a pathway by which intestinal DGAT1 deficiency affects whole-body cholesterol homeostasis in mice. Targeting intestinal DGAT1 may represent a novel approach for treating hypercholesterolemia.
Created from Fastlane, Scopus look-up
Keywords: Cholesterol absorption; Chylomicron size; DGAT1 inhibition; Intestinal DGAT1 deficiency; Trans-intestinal cholesterol excretion

Novel T cell/organoid culture system allows ex vivo modeling of intestinal graft-versus-host disease - Matthe, Diana; Dinkel, Martin; Schmid, Benjamin; Vogler, Tina; Neurath, Markus; Poeck, Hendrik; Neufert, Clemens; Büttner-Herold, Maike; Hildner, Kai (Frontiers in Immunology, 2023)
Acute graft-versus-host disease (GvHD) remains the biggest clinical challenge and prognosis-determining complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Donor T cells are acceptedly key mediators of alloreactivity against host tissues and here especially the gut. In support of previous studies, we found that the intestinal intra-epithelial lymphocyte (IEL) compartment was dynamically regulated in the course of MHC class I full mismatch allo-HSCT. However, while intestinal epithelial cell (IEC) damage endangers the integrity of the intestinal barrier and is a core signature of intestinal GvHD, the question whether and to what degree IELs are contributing to IEC dysregulation is poorly understood. To study lymphoepithelial interaction, we employed a novel ex vivo T cell/organoid co-culture model system. Here, allogeneic intra-epithelial T cells were superior in inducing IEC death compared to syngeneic IEL and allogeneic non-IEL T cells. The ability to induce IEC death was predominately confined to TCRβ+ T cells and was executed in a largely IFNγ-dependent manner. Alloreactivity required a diverse T cell receptor (TCR) repertoire since IELs genetically modified to express a TCR restricted to a single, non-endogenous antigen failed to mediate IEC pathology. Interestingly, minor histocompatibility antigen (miHA) mismatch was sufficient to elicit IEL-driven IEC damage. Finally, advanced live cell imaging analyses uncovered that alloreactive IELs patrolled smaller areas within intestinal organoids compared to syngeneic controls, indicating their unique migratory properties within allogeneic IECs. Together, we provide here experimental evidence for the utility of a co-culture system to model the cellular and molecular characteristics of the crosstalk between IELs and IEC in an allogeneic setting ex vivo. In the light of the emerging concept of dysregulated immune-epithelial homeostasis as a core aspect of intestinal GvHD, this approach represents a novel experimental system to e.g. screen therapeutic strategies for their potential to normalize T cell/IEC- interaction. Hence, analyses in pre-clinical in vivo allo-HSCT model systems may be restricted to hereby positively selected, promising approaches.
CRIS-Team Scopus Importer:2023-09-22
Keywords: allogeneic hematopoietic stem cell transplantation; alloreactive T cell; epithelial cell death; ex vivo model; graft-versus-host disease; GvHD; intestinal organoids; intraepithelial lymphocytes

NR4A1 Regulates Motility of Osteoclast Precursors and Serves as Target for the Modulation of Systemic Bone Turnover - Scholtysek, Carina; Ipseiz, Natacha; Böhm, Christina; Krishnacoumar, Brenda; Stenzel, Martin; Czerwinski, Tina; Palumbo-Zerr, Katrin; Rothe, Tobias; Weidner, Daniela; Klej, Alexandra; Stoll, Cornelia; Distler, Jörg; et al. (Journal of Bone and Mineral Research, 2018)
NR4A1 (Nur77 or NGFI-B), an orphan member of the nuclear receptor superfamily, has been identified as a key regulator of the differentiation and function of myeloid, lymphoid, and mesenchymal cells. The detailed role of NR4A1 in bone biology is incompletely understood. Here, we report a role for NR4A1 as novel factor controlling the migration and recruitment of osteoclast precursors during bone remodeling. Myeloid-specific but not osteoblast-specific deletion of NR4A1 resulted in osteopenia due to an increase in the number of bone-lining osteoclasts. Although NR4A1-deficient osteoclast precursors displayed a regular differentiation into mature osteoclasts, they showed a hyper-motile phenotype that was largely dependent on increased osteopontin expression, suggesting that expression of NR4A1 negatively controlled osteopontin-mediated recruitment of osteoclast precursors to the trabecular bone. Pharmacological activation of NR4A1, in turn, inhibited osteopontin expression and osteopontin-dependent migration of osteoclast precursors resulted in reduced abundance of bone-resorbing osteoclasts in vivo as well as in an ameliorated bone loss after ovariectomy in mice. This study identifies NR4A1 as a crucial player in the regulation of osteoclast biology and bone remodeling and highlights this nuclear receptor as a promising target for therapeutic intervention during the treatment of osteoporosis. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.
EVALuna2:34484

Nsp16 shields SARS–CoV-2 from efficient MDA5 sensing and IFIT1-mediated restriction - Ruß, Alina; Wittmann, Sabine; Tsukamoto, Yuta; Herrmann, Alexandra; Deutschmann, Janina; Lagisquet, Justine; Enßer, Armin; Kato, Hiroki; Gramberg, Thomas (EMBO Reports, 2022)
Methylation of the mRNA 5′ cap by cellular methyltransferases enables efficient translation and avoids recognition by innate immune factors. Coronaviruses encode viral 2′-O-methyltransferases to shield their RNA from host factors. Here, we generate recombinant SARS–CoV-2 harboring a catalytically inactive 2′-O-methyltransferase Nsp16, Nsp16mut, and analyze viral replication in human lung epithelial cells. Although replication is only slightly attenuated, we find SARS–CoV-2 Nsp16mut to be highly immunogenic, resulting in a strongly enhanced release of type I interferon upon infection. The elevated immunogenicity of Nsp16mut is absent in cells lacking the RNA sensor MDA5. In addition, we report that Nsp16mut is highly sensitive to type I IFN treatment and demonstrate that this strong antiviral effect of type I IFN is mediated by the restriction factor IFIT1. Together, we describe a dual role for the 2′-O-methyltransferase Nsp16 during SARS–CoV-2 replication in avoiding efficient recognition by MDA5 and in shielding its RNA from interferon-induced antiviral responses, thereby identifying Nsp16 as a promising target for generating attenuated and highly immunogenic SARS–CoV-2 strains and as a potential candidate for therapeutic intervention.
CRIS-Team Scopus Importer:2022-11-04
Keywords: 2′-O-methyltransferase; IFIT1; MDA5; Nsp16; SARS–CoV-2

Obesity-Mediated Immune Modulation: One Step Forward, (Th)2 Steps Back - Schmidt, Viviane; Hogan, Andrew E.; Fallon, Padraic G.; Schwartz, Christian (Frontiers in Immunology, 2022)
Over the past decades, the relationship between the immune system and metabolism has become a major research focus. In this arena of immunometabolism the capacity of adipose tissue to secrete immunomodulatory molecules, including adipokines, within the underlying low-grade inflammation during obesity brought attention to the impact obesity has on the immune system. Adipokines, such as leptin and adiponectin, influence T cell differentiation into different T helper subsets and their activation during immune responses. Furthermore, within the cellular milieu of adipose tissue nutrient availability regulates differentiation and activation of T cells and changes in cellular metabolic pathways. Upon activation, T cells shift from oxidative phosphorylation to oxidative glycolysis, while the differential signaling of the kinase mammalian target of rapamycin (mTOR) and the nuclear receptor PPAR gamma, amongst others, drive the subsequent T cell differentiation. While the mechanisms leading to a shift from the typical type 2-dominated milieu in lean people to a Th1-biased pro-inflammatory environment during obesity are the subject of extensive research, insights on its impact on peripheral Th2-dominated immune responses become more evident. In this review, we will summarize recent findings of how Th2 cells are metabolically regulated during obesity and malnutrition, and how these states affect local and systemic Th2-biased immune responses.
CRIS-Team WoS Importer:2022-07-29

Oligodendroglial α-synucleinopathy-driven neuroinflammation in multiple system atrophy - Hoffmann, Alana; Ettle, Benjamin; Battis, Kristina; Reiprich, Simone; Schlachetzki, Johannes; Masliah, Eliezer; Wegner, Michael; Kuhlmann, Tanja; Riemenschneider, Markus J.; Winkler, Jürgen (Brain Pathology, 2018)
Neuroinflammation and oligodendroglial cytoplasmic α-synuclein (α-syn) inclusions (GCIs) are important neuropathological characteristics of multiple system atrophy (MSA). GCIs are known to interfere with oligodendroglial maturation and consequently result in myelin loss. The neuroinflammatory phenotype in the context of MSA, however, remains poorly understood. Here, we demonstrate MSA-associated neuroinflammation being restricted to myeloid cells and tightly linked to oligodendroglial α-syncleinopathy. In human putaminal post-mortem tissue of MSA patients, neuroinflammation was observed in white matter regions only. This locally restricted neuroinflammation coincided with elevated numbers of α-syn inclusions, while gray matter with less α-synucleinopathy remained unaffected. In order to analyze the temporal pattern of neuroinflammation, a transgenic mouse model overexpressing human α-syn under the control of an oligodendrocyte-specific myelin basic protein (MBP) promoter (MBP29-hα-syn mice) was assessed in a pre-symptomatic and symptomatic disease stage. Strikingly, we detected an increased neuroinflammation in regions with a high α-syn load, the corpus callosum and the striatum, of MBP29-hα-syn mice, already at a pre-symptomatic stage. Furthermore, this inflammatory response was restricted to myeloid cells being highly proliferative and showing an activated, phagocytic phenotype. In contrast, severe astrogliosis was observed only in gray matter regions of MSA patients as well as MBP29-hα-syn mice. To further characterize the influence of oligodendrocytes on initiation of the myeloid immune response, we performed RNA sequencing analysis of α-syn overexpressing primary oligodendrocytes. A distinct gene expression profile including upregulation of cytokines important for myeloid cell attraction and proliferation was detected in α-syn overexpressing oligodendrocytes. Additionally, microdissected tissue of MBP29-hα-syn mice exhibited a similar cellular gene expression profile in white matter regions even pre-symptomatically. Collectively, these results imply an early crosstalk between neuroinflammation and oligodendrocytes containing α-syn inclusions leading to an immune response locally restricted to white matter regions in MSA.
EVALuna2:35751

Optoacoustic Imaging in Inflammation - Regensburger, Adrian; Brown, Emma; Krönke, Gerhard; Waldner, Maximilian; Knieling, Ferdinand (Biomedicines, 2021)
Optoacoustic or photoacoustic imaging (OAI/PAI) is a technology which enables non-invasive visualization of laser-illuminated tissue by the detection of acoustic signals. The combination of "light in" and "sound out" offers unprecedented scalability with a high penetration depth and resolution. The wide range of biomedical applications makes this technology a versatile tool for preclinical and clinical research. Particularly when imaging inflammation, the technology offers advantages over current clinical methods to diagnose, stage, and monitor physiological and pathophysiological processes. This review discusses the clinical perspective of using OAI in the context of imaging inflammation as well as in current and emerging translational applications.
CRIS-Team WoS Importer:2021-06-04

ORF3c is expressed in SARS-CoV-2-infected cells and inhibits innate sensing by targeting MAVS - Müller, Martin; Herrmann, Alexandra; Fujita, Shigeru; Uriu, Keiya; Kruth, Carolin; Strange, Adam; Kolberg, Jan E.; Schneider, Markus; Ito, Jumpei; Müller, Marcel A.; Drosten, Christian; Enßer, Armin; et al. (EMBO Reports, 2023)
Most SARS-CoV-2 proteins are translated from subgenomic RNAs (sgRNAs). While the majority of these sgRNAs are monocistronic, some viral mRNAs encode more than one protein. One example is the ORF3a sgRNA that also encodes ORF3c, an enigmatic 41-amino-acid peptide. Here, we show that ORF3c is expressed in SARS-CoV-2-infected cells and suppresses RIG-I- and MDA5-mediated IFN-β induction. ORF3c interacts with the signaling adaptor MAVS, induces its C-terminal cleavage, and inhibits the interaction of RIG-I with MAVS. The immunosuppressive activity of ORF3c is conserved among members of the subgenus sarbecovirus, including SARS-CoV and coronaviruses isolated from bats. Notably, however, the SARS-CoV-2 delta and kappa variants harbor premature stop codons in ORF3c, demonstrating that this reading frame is not essential for efficient viral replication in vivo and is likely compensated by other viral proteins. In agreement with this, disruption of ORF3c does not significantly affect SARS-CoV-2 replication in CaCo-2, CaLu-3, or Rhinolophus alcyone cells. In summary, we here identify ORF3c as an immune evasion factor of SARS-CoV-2 that suppresses innate sensing in infected cells.
CRIS-Team Scopus Importer:2023-11-03
Keywords: cryptic open reading frames; IFN antagonist; immune evasion; ORF3c; SARS-CoV-2

Osteocyte necrosis triggers osteoclast-mediated bone loss through macrophage-inducible C-type lectin - Andreev, Darja; Liu, Mengdan; Weidner, Daniela; Kachler, Katerina; Faas, Maria; Grüneboom, Anika; Schlötzer-Schrehardt, Ursula; Munoz, Luis Enrique; Steffen, Ulrike; Grötsch, Bettina; Killy, Barbara; Krönke, Gerhard; et al. (Journal of Clinical Investigation, 2020)
Although the control of bone-resorbing osteoclasts through osteocyte-derived RANKL is well defined, little is known about the regulation of osteoclasts by osteocyte death. Indeed, several skeletal diseases, such as bone fracture, osteonecrosis, and inflammation are characterized by excessive osteocyte death. Herein we show that osteoclasts sense damageassociated molecular patterns (DAMPs) released by necrotic osteocytes via macrophage-inducible C-type lectin (Mincle), which induced their differentiation and triggered bone loss. Osteoclasts showed robust Mincle expression upon exposure to necrotic osteocytes in vitro and in vivo. RNA sequencing and metabolic analyses demonstrated that Mincle activation triggers osteoclastogenesis via ITAM-based calcium signaling pathways, skewing osteoclast metabolism toward oxidative phosphorylation. Deletion of Mincle in vivo effectively blocked the activation of osteoclasts after induction of osteocyte death, improved fracture repair, and attenuated inflammation-mediated bone loss. Furthermore, in patients with osteonecrosis, Mincle was highly expressed at skeletal sites of osteocyte death and correlated with strong osteoclastic activity. Taken together, these data point to what we believe is a novel DAMP-mediated process that allows osteoclast activation and bone loss in the context of osteocyte death.
CRIS-Team Scopus Importer:2020-10-16

p21 Prevents the Exhaustion of CD4+ T Cells Within the Antitumor Immune Response Against Colorectal Cancer - Thoma, Oana-Maria; Naschberger, Elisabeth; Kubánková, Markéta; Larafa, Imen; Kramer, Viktoria; Menchicchi, Bianca; Merkel, Susanne; Britzen-Laurent, Nathalie; Jefremow, André; Grützmann, Robert; Koop, Kristina; Neufert, Clemens; et al. (Gastroenterology, 2024)
Background & Aims: T cells are crucial for the antitumor response against colorectal cancer (CRC). T-cell reactivity to CRC is nevertheless limited by T-cell exhaustion. However, molecular mechanisms regulating T-cell exhaustion are only poorly understood. Methods: We investigated the functional role of cyclin-dependent kinase 1a (Cdkn1a or p21) in cluster of differentiation (CD) 4+ T cells using murine CRC models. Furthermore, we evaluated the expression of p21 in patients with stage I to IV CRC. In vitro coculture models were used to understand the effector function of p21-deficient CD4+ T cells. Results: We observed that the activation of cell cycle regulator p21 is crucial for CD4+ T-cell cytotoxic function and that p21 deficiency in type 1 helper T cells (Th1) leads to increased tumor growth in murine CRC. Similarly, low p21 expression in CD4+ T cells infiltrated into tumors of CRC patients is associated with reduced cancer-related survival. In mouse models of CRC, p21-deficient Th1 cells show signs of exhaustion, where an accumulation of effector/effector memory T cells and CD27/CD28 loss are predominant. Immune reconstitution of tumor-bearing Rag1−/− mice using ex vivo-treated p21-deficient T cells with palbociclib, an inhibitor of cyclin-dependent kinase 4/6, restored cytotoxic function and prevented exhaustion of p21-deficient CD4+ T cells as a possible concept for future immunotherapy of human disease. Conclusions: Our data reveal the importance of p21 in controlling the cell cycle and preventing exhaustion of Th1 cells. Furthermore, we unveil the therapeutic potential of cyclin-dependent kinase inhibitors such as palbociclib to reduce T-cell exhaustion for future treatment of patients with colorectal cancer.
CRIS-Team Scopus Importer:2024-01-19
Keywords: CD4; Colorectal Cancer; p21; Palbociclib

P2Y2R is a direct target of HIF-1α and mediates secretion-dependent cyst growth of renal cyst-forming epithelial cells - Kraus, Andre; Grampp, Steffen; Goppelt-Strübe, Margarete; Schreiber, Rainer; Kunzelmann, Karl; Peters, Dorien J. M.; Leipziger, Jens; Schley, Gunnar; Schoedel, Johannes; Eckardt, Kai-Uwe; Buchholz, Björn (Purinergic Signalling, 2016)
Polycystic kidney diseases are characterized by numerous renal cysts that continuously enlarge resulting in compression of intact nephrons and tissue hypoxia. Recently, we have shown that hypoxia-inducible factor (HIF)-1 alpha promotes secretion-dependent cyst expansion, presumably by transcriptional regulation of proteins that are involved in calcium-activated chloride secretion. Here, we report that HIF-1 alpha directly activates expression of the purinergic receptor P2Y2R in human primary renal tubular cells. In addition, we found that P2Y2R is highly expressed in cyst-lining cells of human ADPKD kidneys as well as PKD1 orthologous mouse kidneys. Knockdown of P2Y2R in renal collecting duct cells inhibited calcium-dependent chloride secretion in Ussing chamber analyses. In line with these findings, knockdown of P2Y2R retarded cyst expansion in vitro and prevented ATP- and HIF-1 alpha-dependent cyst growth. In conclusion, P2Y2R mediates ATP-dependent cyst growth and is transcriptionally regulated by HIF-1 alpha. These findings provide further mechanistic evidence on how hypoxia promotes cyst growth.
EVALuna2:3913
Keywords: Polycystic kidney disease; Cyst growth; Chloride secretion; ATP; P2Y2R; Hypoxia; HIF-1 alpha

Paclitaxel synergizes with exposure time adjusted CD22-targeting immunotoxins against B-cell malignancies - Müller, Fabian; Stookey, Stephanie; Cunningham, Tyler; Pastan, Ira (Oncotarget, 2017)
CD22-targeted recombinant immunotoxins (rIT) are active in hairy cell leukemia or acute lymphoblastic leukemia (ALL), but not in mantle cell lymphoma (MCL) patients. The goal was to enhance rIT efficacy in vivo and to define a strong combination treatment. Activity of Moxetumomab pasudotox (Moxe) and LR combined with paclitaxel was tested against MCL cell lines in vitro and as bolus doses or continuous infusion in xenograft models. In the KOPN-8 ALL xenograft, Moxe or paclitaxel alone was active, but all mice died from leukemia; when combined, 60% of the mice achieved a sustained complete remission. Against MCL cells in vitro, LR was more active than Moxe and the cells had to be exposed to rIT for more than 24 hours for them to die. To maintain high blood levels in vivo, LR was administered continuously by 7-day pumps achieving a well-tolerated steady plasma concentration of 45 ng/ml. In JeKo-1 xenografts, continuously administered LR was 14-fold more active than bolus doses and the combination with paclitaxel additionally improved responses by 135-fold. Maintaining high rIT-plasma levels greatly improves responses in the JeKo-1 model and paclitaxel substantially enhances bolus and continuously infused rIT, supporting a clinical evaluation against B-cell malignancies.
EVALuna2:25765

Palmitoylated Proteins on AML-Derived Extracellular Vesicles Promote Myeloid-Derived Suppressor Cell Differentiation via TLR2/Akt/mTOR Signaling - Tohumeken, Sehmus; Böttcher, Martin; Stoll, Andrej; Loschinski, Romy; Panagiotidis, Konstantinos; Braun, Martina; Saul, Domenica; Baur, Andreas; Bruns, Heiko; Mackensen, Andreas; Jitschin, Regina; Mougiakakos, Dimitrios; et al. (Cancer Research, 2020)
Acute myeloid leukemia (AML) represents the most common acute leukemia among adults. Despite recent progress in diagnosis and treatment, long-term outcome remains unsatisfactory. The success of allogeneic stem cell transplantation underscores the immunoresponsive nature of AML, creating the basis for further exploiting immunotherapies. However, emerging evidence suggests that AML, similar to other malignant entities, employs a variety of mechanisms to evade immunosurveillance. In light of this, T-cell inhibitory myeloid-derived suppressor cells (MDSC) are gaining interest as key facilitators of immunoescape. Accumulation of CD14(+) HLA-DRlow monocyticMDSCs has been described in newly diagnosed AML patients, and deciphering the underlying mechanisms could help to improve anti-AML immunity. Here, we report that conventional monocytes readily takeup AML-derived extracellular vesicles (EV) and subsequently undergo MDSC differentiation. They acquired an CD14(+)HLA-DRlow phenotype, expressed the immunomodulatory indoleamine-2,3-dioxygenase, and upregulated expression of genes characteristic for MDSCs, such as S100A8/9 and cEBP beta. The Akt/mTOR pathway played a critical role in the AML-EV-induced phenotypical and functional transition of monocytes. Generated MDSCs displayed a glycolytic switch, which rendered them more susceptible toward glycolytic inhibitors. Furthermore, palmitoylated proteins on the AML-EV surface activated Toll-like receptor 2 as the initiating event of Akt/mTOR-dependent induction of MDSC. Therefore, targeting protein palmitoylation in AML blasts could block MDSC accumulation to improve immune responses.
CRIS-Team WoS Importer:2020-09-25

Partner, Neighbor, Housekeeper and Dimension: 3D versus 2D Glomerular Co-Cultures Reveal Drawbacks of Currently Used Cell Culture Models - Rederer, Anna; Rose, Victoria; Krüger, René; Schmittutz, Linda; Swierzy, Izabela; Fischer, Lena; Thievessen, Ingo; Bauer, Julian; Friedrich, Oliver; Schiffer, Mario; Müller-Deile, Janina (International Journal of Molecular Sciences, 2023)
Signaling-pathway analyses and the investigation of gene responses to different stimuli are usually performed in 2D monocultures. However, within the glomerulus, cells grow in 3D and are involved in direct and paracrine interactions with different glomerular cell types. Thus, the results from 2D monoculture experiments must be taken with caution. We cultured glomerular endothelial cells, podocytes and mesangial cells in 2D/3D monocultures and 2D/3D co-cultures and analyzed cell survival, self-assembly, gene expression, cell–cell interaction, and gene pathways using live/dead assay, time-lapse analysis, bulk-RNA sequencing, qPCR, and immunofluorescence staining. Without any need for scaffolds, 3D glomerular co-cultures self-organized into spheroids. Podocyte- and glomerular endothelial cell-specific markers and the extracellular matrix were increased in 3D co-cultures compared to 2D co-cultures. Housekeeping genes must be chosen wisely, as many genes used for the normalization of gene expression were themselves affected in 3D culture conditions. The transport of podocyte-derived VEGFA to glomerular endothelial cells confirmed intercellular crosstalk in the 3D co-culture models. The enhanced expression of genes important for glomerular function in 3D, compared to 2D, questions the reliability of currently used 2D monocultures. Hence, glomerular 3D co-cultures might be more suitable in the study of intercellular communication, disease modelling and drug screening ex vivo.
Created from Fastlane, Scopus look-up
Keywords: 3D co-culture; bulk-RNA sequencing; cell culture model; cell matrix; cell–cell communication; glomerular spheroids

Pathophysiological role of guanylate-binding proteins in gastrointestinal diseases - Britzen-Laurent, Nathalie; Herrmann, Christian; Naschberger, Elisabeth; Croner, Roland S.; Stürzl, Michael (World Journal of Gastroenterology, 2016)
Guanylate-binding proteins (GBPs) are interferon-stimulated factors involved in the defense against cellular pathogens and inflammation. These proteins, particularly GBP-1, the most prominent member of the family, have been established as reliable markers of interferon-?-activated cells in various diseases, including colorectal carcinoma (CRC) and inflammatory bowel diseases (IBDs). In CRC, GBP-1 expression is associated with a Th1-dominated angiostatic micromilieu and is correlated with a better outcome. Inhibition of tumor growth by GBP-1 is the result of its strong anti-angiogenic activity as well as its direct anti-tumorigenic effect on tumor cells. In IBD, GBP-1 mediates the anti-proliferative effects of interferon-? on intestinal epithelial cells. In addition, it plays a protective role on the mucosa by preventing cell apoptosis, by inhibiting angiogenesis and by regulating the T-cell receptor signaling. These functions rely to a large extent on the ability of GBP-1 to interact with and remodel the actin cytoskeleton.
EVALuna2:15238

Patients with immune-mediated inflammatory diseases receiving cytokine inhibitors have low prevalence of SARS-CoV-2 seroconversion - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (Nature Communications, 2020)
Immune-mediated inflammatory diseases (IMIDs) of the joints, gut and skin are treated with inhibitors of inflammatory cytokines. These cytokines are involved in the pathogenesis of coronavirus disease 2019 (COVID-19). Investigating anti-SARS-CoV-2 antibody responses in IMIDs we observe a reduced incidence of SARS-CoV-2 seroconversion in IMID patients treated with cytokine inhibitors compared to patients receiving no such inhibitors and two healthy control populations, despite similar social exposure. Hence, cytokine inhibitors seem to at least partially protect from SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2020-08-07

Pediatric Buried Bumper Syndrome: Diagnostic Validity of Transabdominal Ultrasound and Artificial Intelligence - Aguilar, Caroline; Regensburger, Adrian; Knieling, Ferdinand; Wagner, Alexandra; Siebenlist, Gregor; Wölfle, Joachim; Koehler, Henrik; Hörning, André; Jüngert, Jörg M. (Ultraschall in der Medizin, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-06-04

Permeability analyses and three dimensional imaging of interferon gamma-induced barrier disintegration in intestinal organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Schmid, Benjamin; Waldner, Maximilian; Naschberger, Elisabeth; Scharl, Michael; Mueller, Werner; Günther, Claudia; Becker, Christoph; Stürzl, Michael; Tripal, Philipp (Stem Cell Research, 2019)
The aberrant regulation of the epithelial barrier integrity is involved in many diseases of the digestive tract, including inflammatory bowel diseases and colorectal cancer. Intestinal epithelial cell organoid cultures provide new perspectives for analyses of the intestinal barrier in vitro. However, established methods of barrier function analyses from two dimensional cultures have to be adjusted to the analysis of three dimensional organoid structures. Here we describe the methodology for analysis of epithelial barrier function and molecular regulation in intestinal organoids. Barrier responses to interferon-y of intestinal organoids with and without epithelial cellspecific deletion of the interferon-y-receptor 2 gene were used as a model system. The established method allowed monitoring of the kinetics of interferon-y-induced permeability changes in living organoids. Proteolytic degradation and altered localization of the tight junction proteins claudin-2, -7, and - 15 was detected using confocal spinning disc microscopy with 3D reconstruction. Hessian analysis was used for quantification of relocalization of claudins. In summary, we provide a novel methodologic approach for quantitative analyses of intestinal epithelial barrier functions in the 3D organoid model.
CRIS-Team WoS Importer:2019-03-12

PGAM5-mediated programmed necrosis of hepatocytes drives acute liver injury - He, Gui-Wei; Günther, Claudia; Kremer, Andreas; Thonn, Veronika; Amann, Kerstin Ute; Poremba, Christopher; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Gut, 2016)
Autoimmune hepatitis (AIH) is a severe necroinflammatory liver disease associated with significant mortality. Although loss of hepatocytes is generally recognised as a key trigger of liver inflammation and liver failure, the regulation of hepatic cell death causing AIH remains poorly understood. The aim of this study was to identify molecular mechanisms that drive hepatocyte cell death in the pathogenesis of acute liver injury.Acute liver injury was modelled in mice by intravenous administration of concanavalin A (ConA). Liver injury was demonstrated by serum transaminases and histological assessment of liver sections. PGAM5-deficient mice (PGAM5-/-) were used to determine its role in experimental hepatitis. Mdivi-1 was used as an inhibitor of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission. Mitochondrial fission and the expression of PGAM5 were compared between liver biopsies derived from patients with AIH and control patients.PGAM5 was highly expressed in hepatocytes of patients with AIH and in mice with ConA-induced experimental hepatitis. Deficiency of PGAM5 protected mice from ConA-induced hepatocellular death and liver injury. PGAM5 regulated ConA-induced mitochondrial fission in hepatocytes. Administration of the Drp1-inhibitor Mdivi-1 blocked mitochondrial fission, diminished hepatocyte cell death and attenuated liver tissue damage induced by ConA.Our data demonstrate for the first time that PGAM5 plays an indispensable role in the pathogenesis of ConA-induced liver injury. Downstream of PGAM5, Drp1-mediated mitochondrial fission is an obligatory step that drives the execution of hepatic necrosis and tissue damage. Our data highlight the PGAM5-Drp1 axis as a potential therapeutic target for acute immune-mediated liver injury.
EVALuna2:2219

Pgam5 released from damaged mitochondria induces mitochondrial biogenesis via Wnt signaling - Bernkopf, Dominic; Jalal, Kowcee; Brückner, Martina; Knaup, Karl; Gentzel, Marc; Schambony, Alexandra; Behrens, Jürgen (The Journal of Cell Biology, 2018)
Mitochondrial abundance is dynamically regulated and was previously shown to be increased by Wnt/β-catenin signaling. Pgam5 is a mitochondrial phosphatase which is cleaved by the rhomboid protease presenilin-associated rhomboid-like protein (PARL) and released from membranes after mitochondrial stress. In this study, we show that Pgam5 interacts with the Wnt pathway component axin in the cytosol, blocks axin-mediated β-catenin degradation, and increases β-catenin levels and β-catenin-dependent transcription. Pgam5 stabilized β-catenin by inducing its dephosphorylation in an axin-dependent manner. Mitochondrial stress triggered by carbonyl cyanide m-chlorophenyl hydrazone (CCCP) treatment led to cytosolic release of endogenous Pgam5 and subsequent dephosphorylation of β-catenin, which was strongly diminished in Pgam5 and PARL knockout cells. Similarly, hypoxic stress generated cytosolic Pgam5 and led to stabilization of β-catenin, which was abolished by Pgam5 knockout. Cells stably expressing cytosolic Pgam5 exhibit elevated β-catenin levels and increased mitochondrial numbers. Our study reveals a novel mechanism by which damaged mitochondria might induce replenishment of the mitochondrial pool by cell-intrinsic activation of Wnt signaling via the Pgam5-β-catenin axis.
EVALuna2:34942

Pharmacological inhibition of porcupine induces regression of experimental skin fibrosis by targeting Wnt signalling - Chen, Chih-Wei; Beyer, Christian; Liu, Jun; Maier, Christiane; Li, Chun; Thuong Trinh-Minh,; Xu, Xiaohan; Cole, Stuart H.; Hsieh, Mindy H.; Ng, Nicholas; Althage, Alana; Meeusen, Shelly; et al. (Annals of the Rheumatic Diseases, 2017)
Wnt signalling has been implicated in activating a fibrogenic programme in fibroblasts in systemic sclerosis (SSc). Porcupine is an O-acyltransferase required for secretion of Wnt proteins in mammals. Here, we aimed to evaluate the antifibrotic effects of pharmacological inhibition of porcupine in preclinical models of SSc.The porcupine inhibitor GNF6231 was evaluated in the mouse models of bleomycin-induced skin fibrosis, in tight-skin-1 mice, in murine sclerodermatous chronic-graft-versus-host disease (cGvHD) and in fibrosis induced by a constitutively active transforming growth factor-?-receptor I.Treatment with pharmacologically relevant and well-tolerated doses of GNF6231 inhibited the activation of Wnt signalling in fibrotic murine skin. GNF6231 ameliorated skin fibrosis in all four models. Treatment with GNF6231 also reduced pulmonary fibrosis associated with murine cGvHD. Most importantly, GNF6231 prevented progression of fibrosis and showed evidence of reversal of established fibrosis.These data suggest that targeting the Wnt pathway through inhibition of porcupine provides a potential therapeutic approach to fibrosis in SSc. This is of particular interest, as a close analogue of GNF6231 has already demonstrated robust pathway inhibition in humans and could be available for clinical trials.
EVALuna2:13348

Phosphorylation of the neurogenic transcription factor SOX11 on serine 133 modulates neuronal morphogenesis - Balta, Elli-Anna; Schäffner, Iris; Wittmann, Marie-Theres; Sock, Elisabeth; Von Zweydorf, Felix; von Wittgenstein, Julia; Steib, Kathrin; Heim, Birgit; Kremmer, Elisabeth; Häberle, Benjamin; Ueffing, Marius; Lie, Dieter Chichung; et al. (Scientific Reports, 2018)
The intellectual disability gene, Sox11, encodes for a critical neurodevelopmental transcription factor with functions in precursor survival, neuronal fate determination, migration and morphogenesis. The mechanisms regulating SOX11's activity remain largely unknown. Mass spectrometric analysis uncovered that SOX11 can be post-translationally modified by phosphorylation. Here, we report that phosphorylatable serines surrounding the high-mobility group box modulate SOX11's transcriptional activity. Through Mass Spectrometry (MS), co-immunoprecipitation assays and in vitro phosphorylation assays followed by MS we verified that protein kinase A (PKA) interacts with SOX11 and phosphorylates it on S133. In vivo replacement of SoxC factors in developing adult-generated hippocampal neurons with SOX11 S133 phospho-mutants indicated that phosphorylation on S133 modulates dendrite development of adult-born dentate granule neurons, while reporter assays suggested that S133 phosphorylation fine-tunes the activation of select target genes. These data provide novel insight into the control of the critical neurodevelopmental regulator SOX11 and imply SOX11 as a mediator of PKA-regulated neuronal development.
EVALuna2:35738

Photosensitization of TRPA1 and TRPV1 by 7-dehydrocholesterol: implications for the Smith-Lemli-Opitz syndrome - Babes, Alexandru; Ciotu, Cosmin I.; Hoffmann, Tal; Kichko, Tetyana; Selescu, Tudor; Neacsu, Cristian; Sauer, Susanne; Reeh, Peter; Fischer, Michael (Pain, 2017)
Loss-of-function mutations in the enzyme 7-dehydrocholesterol reductase are responsible for the Smith-Lemli-Opitz syndrome, in which 7-dehydrocholesterol (7-DHC) levels are markedly increased in the plasma and tissues of patients. This increase in 7-DHC is probably associated with the painful and itchy photosensitivity reported by the majority of patients with Smith-Lemli-Opitz syndrome. To identify the molecular targets involved in the activation and photosensitization of primary afferents by 7-DHC, we focused on TRPA1 and TRPV1, two ion channels expressed in nociceptive nerve endings and previously shown to respond to ultraviolet and visible light under pathophysiological circumstances. Recombinant human TRPA1 is activated and photosensitized in the presence of 7-DHC. Prolonged preexposure to 7-DHC causes more pronounced photosensitization, and while TRPV1 contributes less to the acute effect, it too becomes highly photosensitive upon preincubation with 7-DHC for 1 to 15 hours. Dorsal root ganglion neurons in primary culture display acute sensitivity to 7-DHC in the dark and also light-evoked responses in the presence of 7-DHC, which are exclusively dependent on TRPA1 and TRPV1. Similarly, prolonged exposure of mouse dorsal root ganglion neurons to 7-DHC renders these cells photosensitive in a largely TRPA1- and TRPV1-dependent manner. Single-fiber recordings in mouse skin-nerve preparations demonstrate violet light-evoked activation and a sensitization to 7-DHC exposure. Vice versa, 7-DHC pretreatment of the isolated trachea leads to a TRPA1- and TRPV1-dependent increase of the light-induced calcitonin gene-related peptide release. Taken together, our results implicate TRPA1 and TRPV1 channels as potential pharmacological targets to address the 7-DHC-induced hypersensitivity to light in patients.
EVALuna2:33333

Plxdc family members are novel receptors for the rhesus monkey rhadinovirus (RRV) - Grosskopf, Anna K.; Schlagowski, Sarah; Fricke, Thomas; Enßer, Armin; Desrosiers, Ronald C.; Hahn, Alexander S. (PLoS Pathogens, 2021)
The rhesus monkey rhadinovirus (RRV), a gamma 2-herpesvirus of rhesus macaques, shares many biological features with the human pathogenic Kaposi's sarcoma-associated herpesvirus (KSHV). Both viruses, as well as the more distantly related Epstein-Barr virus, engage cellular receptors from the Eph family of receptor tyrosine kinases (Ephs). However, the importance of the Eph interaction for RRV entry varies between cell types suggesting the existence of Eph-independent entry pathways. We therefore aimed to identify additional cellular receptors for RRV by affinity enrichment and mass spectrometry. We identified an additional receptor family, the Plexin domain containing proteins 1 and 2 (Plxdc1/2) that bind the RRV gH/gL glycoprotein complex. Preincubation of RRV with soluble Plxdc2 decoy receptor reduced infection by similar to 60%, while overexpression of Plxdc1 and 2 dramatically enhanced RRV susceptibility and cell-cell fusion of otherwise marginally permissive Raji cells. While the Plxdc2 interaction is conserved between two RRV strains, 26-95 and 17577, Plxdc1 specifically interacts with RRV 26-95 gH. The Plxdc interaction is mediated by a short motif at the N-terminus of RRV gH that is partially conserved between isolate 26-95 and isolate 17577, but absent in KSHV gH. Mutation of this motif abrogated the interaction with Plxdc1/2 and reduced RRV infection in a cell type-specific manner. Taken together, our findings characterize Plxdc1/2 as novel interaction partners and entry receptors for RRV and support the concept of the N-terminal domain of the gammaherpesviral gH/gL complex as a multifunctional receptor-binding domain. Further, Plxdc1/2 usage defines an important biological difference between KSHV and RRV.
CRIS-Team WoS Importer:2021-04-16

Poly(ADP-ribose) polymerase-1 regulates fibroblast activation in systemic sclerosis - Zhang, Yun; Pötter, Sebastian; Chen, Chih-Wei; Liang, Ruifang; Gelse, Kolja; Ludolph, Ingo; Horch, Raymund E.; Distler, Oliver; Schett, Georg; Distler, Jörg; Dees, Clara (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: The enzyme poly(ADP-ribose) polymerase-1 (PARP-1) transfers negatively charged ADP-ribose units to target proteins. This modification can have pronounced regulatory effects on target proteins. Recent studies showed that PARP-1 can poly(ADP-ribosyl)ate (PARylate) Smad proteins. However, the role of PARP-1 in the pathogenesis of systemic sclerosis (SSc) has not been investigated. METHODS: The expression of PARP-1 was determined by quantitative PCR and immunohistochemistry. DNA methylation was analysed by methylated DNA immunoprecipitation assays. Transforming growth factor-β (TGFβ) signalling was assessed using reporter assays, chromatin immunoprecipitation assays and target gene analysis. The effect of PARP-1 inactivation was investigated in bleomycin-induced and topoisomerase-induced fibrosis as well as in tight-skin-1 (Tsk-1) mice. RESULTS: The expression of PARP-1 was decreased in patients with SSc, particularly in fibroblasts. The promoter of PARP-1 was hypermethylated in SSc fibroblasts and in TGFβ-stimulated normal fibroblasts. Inhibition of DNA methyltransferases (DNMTs) reduced the promoter methylation and reactivated the expression of PARP-1. Inactivation of PARP-1 promoted accumulation of phosphorylated Smad3, enhanced Smad-dependent transcription and upregulated the expression of TGFβ/Smad target genes. Inhibition of PARP-1 enhanced the effect of TGFβ on collagen release and myofibroblast differentiation in vitro and exacerbated experimental fibrosis in vivo. PARP-1 deficiency induced a more severe fibrotic response to bleomycin with increased dermal thickening, hydroxyproline content and myofibroblast counts. Inhibition of PARylation also exacerbated fibrosis in Tsk-1 mice and in mice with topoisomerase-induced fibrosis. CONCLUSION: PARP-1 negatively regulates canonical TGFβ signalling in experimental skin fibrosis. The downregulation of PARP-1 in SSc fibroblasts may thus directly contribute to hyperactive TGFβ signalling and to persistent fibroblast activation in SSc.
EVALuna2:34150

Poly I:C Pre-Treatment Induced the Anti-Viral Interferon Response in Airway Epithelial Cells - Mitländer, Hannah; Yang, Zuqin; Krammer, Susanne; Grund, Janina; Zirlik, Sabine; Finotto, Susetta (Viruses, 2023)
Type I and III interferons are among the most important antiviral mediators. Increased susceptibility to infections has been described as being associated with impaired interferon response in asthmatic patients. In this work, we focused on the modulation of interferon dysfunction after the rhinovirus infection of airway epithelial cells. Therefore, we tested polyinosinic:polycytidylic acid (poly I:C), a TLR3 agonist, as a possible preventive pre-treatment to improve this anti-viral response. In our human study on asthma, we found a deficiency in interferon levels in the nasal epithelial cells (NEC) from asthmatics at homeostatic level and after RV infection, which might contribute to frequent airway infection seen in asthmatic patients compared to healthy controls. Finally, pre-treatment with the immunomodulatory substance poly I:C before RV infection restored IFN responses in airway epithelial cells. Altogether, we consider poly I:C pre-treatment as a promising strategy for the induction of interferon response prior to viral infections. These results might help to improve current therapeutic strategies for allergic asthma exacerbations.
Created from Fastlane, Scopus look-up
Keywords: asthma; epithelial cells; interferons; poly I:C; rhinovirus

Posttranscriptional Regulation of LOXL1 Expression Via Alternative Splicing and Nonsense-Mediated mRNA Decay as an Adaptive Stress Response - Berner, Daniel; Zenkel, Matthias; Pasutto, Francesca; Hoja, Ursula; Liravi, Panah; Gusek-Schneider, Gabriele C.; Kruse, Friedrich; Schödel, Johannes; Reis, André; Schlötzer-Schrehardt, Ursula (Investigative Ophthalmology & Visual Science, 2017)
Alternative mRNA splicing coupled to nonsense-mediated decay (NMD) is a common mRNA surveillance pathway also known to dynamically modulate gene expression in response to cellular stress. Here, we investigated the involvement of this pathway in the regulation of lysyl oxidase-like 1 (LOXL1) expression in response to pseudoexfoliation (PEX)-associated pathophysiologic factors.Transcript levels of LOXL1 isoforms were determined in ocular tissues obtained from donor eyes without and with PEX syndrome. Pseudoexfoliation-relevant cell types, including human Tenon's capsule fibroblasts (hTCF) and trabecular meshwork cells (hTMC), were exposed to puromycin, caffeine, TGF-?1, homocysteine, IL-6, retinoic acid, UV-B radiation, oxidative stress, and mechanical stress for up to 48 hours. Western blot analysis was carried out using antibodies against LOXL1, (phosphorylated-) eukaryotic initiation factor 2-? (eIF2-?), and regulator of nonsense transcripts 2 (UPF2). RNA interference was used to knockdown UPF1-3 and Serine/threonine-protein kinase (SMG1).Constitutive expression of wild-type LOXL1 and alternatively spliced LOXL1-a transcripts was detected in all ocular tissues showing highest levels in trabecular meshwork and differential expression between PEX and control specimens. LOXL1-a transcripts were upregulated in hTCF and hTMC by NMD inhibitors puromycin and caffeine (>=6-fold; P < 0.01) or after knockdown of NMD core factors (>=2-fold; P < 0.05), whereas mRNA and protein levels of LOXL1 were reduced (<=0.8 fold; P < 0.05). Exposure of cells to various PEX-associated (stress) factors, including TGF-?1, UV-B light, oxidative stress, mechanical stress, and retinoic acid enhanced LOXL1-a transcript levels (>=1.5-fold; P < 0.05), while partially downregulating LOXL1 levels (<=0.7-fold; P < 0.05). Stress-induced inhibition of NMD was dependent on phosphorylation of eIF2?.These findings provide evidence for a functional role of alternative splicing coupled to NMD in the posttranscriptional regulation of LOXL1 gene expression and suggest this mechanism to represent a dynamic mode of adapting LOXL1 expression to PEX-associated environmental and nutritional cues.
EVALuna2:9393

Precision of handheld multispectral optoacoustic tomography for muscle imaging - Wagner, Anna; Danko, Vera; Federle, Anna; Klett, Daniel; Simon, David; Heiß, Rafael; Jüngert, Jörg M.; Uder, Michael; Schett, Georg; Neurath, Markus; Wölfle, Joachim; Waldner, Maximilian; et al. (Photoacoustics, 2021)
Photo-or optoacoustic imaging (OAI) allows quantitative imaging of target tissues. Using multi-wavelength illumination with subsequent ultrasound detection, it may visualize a variety of different chromophores at centimeter depth. Despite its non-invasive, label-free advantages, the precision of repeated measurements for clinical applications is still elusive. We present a multilayer analysis of n = 1920 imaging datasets obtained from a prospective clinical trial (NCT03979157) in n = 10 healthy adult volunteers. All datasets were analyzed for 13 single wavelengths (SWL) between 660 nm–1210 nm and five MSOT-parameters (deoxygenated/oxygenated/total hemoglobin, collagen and lipid) by a semi-automated batch mode software. Intraclass correlation coefficients (ICC) were good to excellent for intrarater (SWL: 0.82–0.92; MSOT-parameter: 0.72−0.92) and interrater reproducibility (SWL: 0.79−0.87; MSOT-parameter: 0.78−0.86), with the exception for MSOT-parameter lipid (interrater ICC: 0.56). Results were stable over time, but exercise-related effects as well as inter-and intramuscular variability were observed. The findings of this study provide a framework for further clinical OAI implementation.
CRIS-Team Scopus Importer:2020-12-25
Keywords: MSOT; Multispectral optoacoustic tomography; Muscle imaging; Optoacoustics; Photoacoustics

Predictive Modelling Based on Statistical Learning in Biomedicine - Gefeller, Olaf; Hofner, Benjamin; Mayr, Andreas; Waldmann, Elisabeth (Computational and Mathematical Methods in Medicine, 2017)
EVALuna2:34208

Prenatal androgen receptor activation determines adult alcohol and water drinking in a sex-specific way - Huber, Sabine; Zoicas, Iulia; Reichel, Martin; Mühle, Christiane; Büttner, Christian; Ekici, Arif Bülent; Eulenburg, Volker; Lenz, Bernd; Kornhuber, Johannes; Müller, Christian P. (Addiction Biology, 2017)
Alcohol use disorders are major psychiatric disorders. Correlational studies in humans suggested organizational hormonal effects during embryonic development as a risk factor for adult alcohol dependence. Permanent changes can be induced by the activity of sex hormones, like testosterone. Here, we demonstrate a relationship between prenatal androgen receptor (AR)-activation and adult alcohol as well as water drinking in mice in a sex-dependent fashion. Prenatal AR inhibition using the antagonist flutamide decreased adult male alcohol consumption. In contrast, prenatal AR activation by dihydrotestosterone (DHT) led to an increase in adult alcohol consumption in females. These effects were different in adult water drinking, flutamide increased water consumption in females and DHT increased water consumption in males. Prenatal flutamide reduced locomotion and anxiety in adult males but was ineffective in females. We found that prenatal AR activation controls adult levels of monoaminergic modulatory transmitters in the brain and blood hormone levels in a sex-specific way. RNA-Seq analysis confirmed a prenatal AR mediated control of adult expression of alcohol drinking-related genes like Bdnf and Per2. These findings demonstrate that prenatal androgen activity is a risk factor for the establishment of alcohol consumption in adults by its organizational effects.
EVALuna2:4035

Prenatal androgen-receptor activity has organizational morphological effects in mice - Huber, Sabine; Lenz, Bernd; Kornhuber, Johannes; Müller, Christian P. (PLoS ONE, 2017)
Prenatal sex hormones exert organizational effects. It has been suggested that prenatal sex hormones affect adult morphological parameters, such as the finger length. Especially the second-to-fourth finger length (2D:4D) ratio has been implicated to be modified when exposed to higher androgen levels in utero. Here we show in a mouse model that experimental manipulation of the prenatal androgen level, by blocking the androgen receptor with flutamide or activating the androgen receptor with dihydrotestosterone (DHT), leads to changes in the length of the fingers of all paws in males and females. In addition to that, also total paw length and the 2D:4D ratio was affected. In males treated with DHT, the 2D:4D ratio was increased, while flutamide-treatment in females led to a reduced 2D:4D ratio. We also measured other parameters, such as head size, body length and tail length and demonstrate that body morphology is affected by prenatal androgen exposure with more prominent effects in females. Another factor that is thought to be influenced by early androgens is handedness. We tested mice for handedness, but did not find a significant effect of the prenatal treatment. These findings demonstrate that prenatal androgen activity is involved in the development of body morphology and might be a useful marker for prenatal androgen exposure.
EVALuna2:33379

Processing and secretion of guanylate binding protein-1 depend on inflammatory caspase activity - Naschberger, Elisabeth; Geissdorfer, Walter; Bogdan, Christian; Tripal, Philipp; Kremmer, Elisabeth; Stürzl, Michael; Britzen-Laurent, Nathalie (Journal of Cellular and Molecular Medicine, 2017)
Human guanylate binding protein-1 (GBP-1) belongs to the family of large GTPases. The expression of GBP-1 is inducible by inflammatory cytokines, and the protein is involved in inflammatory processes and host defence against cellular pathogens. GBP-1 is the first GTPase which was described to be secreted by eukaryotic cells. Here, we report that precipitation of GBP-1 with GMP-agarose from cell culture supernatants co-purified a 47-kD fragment of GBP-1 (p47-GBP-1) in addition to the 67-kD full-length form. MALDI-TOF sequencing revealed that p47-GBP-1 corresponds to the C-terminal helical part of GBP-1 and lacks most of the globular GTPase domain. In silico analyses of protease target sites, together with cleavage experiments in vitro and in vivo, showed that p67-GBP-1 is cleaved by the inflammatory caspases 1 and 5, leading to the formation of p47-GBP-1. Furthermore, the secretion of p47-GBP-1 was found to occur via a non-classical secretion pathway and to be dependent on caspase-1 activity but independent of inflammasome activation. Finally, we showed that p47-GBP-1 represents the predominant form of secreted GBP-1, both in cell culture supernatants and, in vivo, in the cerebrospinal fluid of patients with bacterial meningitis, indicating that it may represent the biologically active form of extracellular GBP-1. These findings confirm the involvement of caspase-1 in non-classical secretion mechanisms and open novel perspectives for the extracellular function of secreted GBP-1.
EVALuna2:7752

Proposal for a Novel Histological Scoring System as a Potential Grading Approach for Muscle-invasive Urothelial Bladder Cancer Correlating with Disease Aggressiveness and Patient Outcomes. - Eckstein, Markus; Matek, Christian; Wagner, Paul; Erber, Ramona; Büttner-Herold, Maike; Wild, Peter J.; Taubert, Helge; Wach, Sven; Sikic, Danijel; Wullich, Bernd; Geppert, Carol-Immanuel; Compérat, Eva M.; et al. (European Urology Oncology, 2024)
BACKGROUND: Grading of muscle-invasive bladder cancer (MIBC) according to the current World Health Organization (WHO) criteria is controversial due to its limited prognostic value. All MIBC cases except a tiny minority are of high grade. OBJECTIVE: To develop a prognostic histological scoring system for MIBC integrating histomorphological phenotype, stromal tumor-infiltrating lymphocytes (sTILs), tumor budding, and growth and spreading patterns. DESIGN, SETTING, AND PARTICIPANTS: Tissue specimens and clinical data of 484 patients receiving cystectomy and lymphadenectomy with curative intent with or without adjuvant chemotherapy. Histomorphological phenotypes, sTILs, tumor budding, and growth and spreading patterns were evaluated and categorized into four grade groups (GGs). GGs were correlated with molecular subtypes, immune infiltration, immune checkpoint expression, extracellular matrix (ECM) remodeling, and epithelial-mesenchymal transition (EMT) activity. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: GGs were associated with overall (OS), disease-specific (DSS), and progression-free (PFS) survival in univariable and multivariable analyses. Association with biological features was analyzed with descriptive statistics. RESULTS AND LIMITATIONS: Integration of two histomorphological tumor groups, three sTILs groups, three tumor budding groups, and four growth/spread patterns yielded four novel GGs that had high significance in the univariable survival analysis (OS, DSS, and PFS). GGs were confirmed as independent prognostic predictors with the greatest effect in the multivariable Cox regression analysis. Correlation with molecular data showed a gradual transition from basal to luminal subtypes from GG1 to GG4; a gradual decrease in survival, immune infiltration, and immune checkpoint activity; and a gradual increase in ECM remodeling and EMT activity. CONCLUSIONS: We propose a novel, prognostically relevant, and biologically based scoring system for MIBC in cystectomies applicable to routine pathological sections. PATIENT SUMMARY: We developed a novel approach to assess the aggressiveness of advanced bladder cancer, which allows improved risk stratification compared with the method currently proposed by the World Health Organization.
EVALuna2:539845

Protective effect of the novel calcineurin inhibitor voclosporin in experimental colitis - Lindemann, Aylin; Roth, Dominik; Koop, Kristina; Neufert, Clemens; Zundler, Sebastian; Atreya, Raja; Neurath, Markus; Leppkes, Moritz (Frontiers in Medicine, 2023)
Background and aims: Acute severe steroid-refractory ulcerative colitis remains a medically challenging condition with frequent need of surgery. It can be treated with the calcineurin inhibitor cyclosporine A with the need for therapeutic drug monitoring and significant toxicity. Recently, a novel calcineurin inhibitor, voclosporin, has been approved for the treatment of lupus nephritis with no need for therapeutic drug monitoring and an improved long-term safety profile. However, the therapeutic effect of voclosporin in acute severe steroid-refractory ulcerative colitis is still uncertain. We aimed to assess the therapeutic potential of voclosporin to ameliorate inflammation in an experimental model of colitis. Methods: We used the dextran sodium sulfate-induced model of colitis in C57BL/6 J wildtype mice treated with either cyclosporine A, voclosporin or solvent control. We employed endoscopy, histochemistry, immunofluorescence, bead-based multiplex immunoassays and flow cytometry to study the therapeutic effect of calcineurin inhibitors in a preventive setting. Results: Acute colitis was induced by dextran sodium sulfate characterized by weight loss, diarrhea, mucosal erosions and rectal bleeding. Both cyclosporine A and voclosporin strongly ameliorated the course of disease and reduced colitis severity in a similar manner. Conclusion: Voclosporin was identified as biologically effective in a preclinical model of colitis and may be a potential therapeutic option in treating acute severe steroid-refractory ulcerative colitis.
CRIS-Team Scopus Importer:2023-07-28
Keywords: calcineurin inhibitors; IBD; steroid refractory colitis; ulcerative colitis; voclosporin

Protein kinases G are essential downstream mediators of the antifibrotic effects of sGC stimulators - Matei, Alexandru-Emil; Beyer, Christian; Gyoerfi, Andrea-Hermina; Soare, Alina; Chen, Chih-Wei; Dees, Clara; Bergmann, Christina; Friebe, Andreas; Hofmann, Franz; Distler, Oliver; Schett, Georg; Distler, Jörg; et al. (Annals of the Rheumatic Diseases, 2018)
Stimulators of soluble guanylate cyclase (sGC) are currently investigated in clinical trials for the treatment of fibrosis in systemic sclerosis (SSc). In this study, we aim to investigate the role of protein kinases G (PKG) as downstream mediators of sGC-cyclic guanosine monophosphate (cGMP) in SSc.Mice with combined knockout of PKG1 and 2 were challenged with bleomycin and treated with the sGC stimulator BAY 41-2272. Fibroblasts were treated with BAY 41-2272 and with the PKG inhibitor KT 5823.PKG1 and 2 are upregulated in SSc in a transforming growth factor-?1 (TGF?1)-dependent manner, as an attempt to compensate for the decreased signalling through the sGC-cGMP-PKG pathway. Inhibition or knockout of PKG1 and 2 abrogates the inhibitory effects of sGC stimulation on fibroblast activation in a SMAD-independent, but extracellular signal-regulated kinase (ERK)-dependent manner. In vivo, sGC stimulation fails to prevent bleomycin-induced fibrosis in PKG1 and 2 knockout mice.Our data provide evidence that PKGs are essential mediators of the antifibrotic effects of sGC stimulators through interfering with non-canonical TGF? signalling. TGF?1 promotes its profibrotic effects through inhibition of sGC-cGMP-PKG signalling, sGC stimulation exerts its antifibrotic effects by inhibition of TGF?1-induced ERK phosphorylation.
EVALuna2:13304

Proteolysis of mature HIV-1 p6 Gag protein by the insulin-degrading enzyme (IDE) regulates virus replication in an Env-dependent manner - Hahn, Friedrich; Schmalen, Adrian; Setz, Christian; Friedrich, Melanie; Schlößer, Stefan; Kölle, Julia; Sprenger, Robert; Rauch, Pia; Fraedrichl, Kirsten; Reif, Tatjana; Karius-Fischer, Julia; Balasubramanyam, Ashok; et al. (PLoS ONE, 2017)
There is a significantly higher risk for type II diabetes in HIV-1 carriers, albeit the molecular mechanism for this HIV-related pathology remains enigmatic. The 52 amino acid HIV-1 p6 Gag protein is synthesized as the C-terminal part of the Gag polyprotein Pr55. In this context, p6 promotes virus release by its two late (L-) domains, and facilitates the incorporation of the viral accessory protein Vpr. However, the function of p6 in its mature form, after proteolytic release from Gag, has not been investigated yet. We found that the mature p6 represents the first known viral substrate of the ubiquitously expressed cytosolic metalloendopeptidase insulin-degrading enzyme (IDE). IDE is sufficient and required for degradation of p6, and p6 is approximately 100-fold more efficiently degraded by IDE than its eponymous substrate insulin. This observation appears to be specific for HIV-1, as p6 proteins from HIV-2 and simian immunodeficiency virus, as well as the 51 amino acid p9 from equine infectious anaemia virus were insensitive to IDE degradation. The amount of virus-associated p6, as well as the efficiency of release and maturation of progeny viruses does not depend on the presence of IDE in the host cells, as it was shown by CRISPR/Cas9 edited IDE KO cells. However, HIV-1 mutants harboring IDE-insensitive p6 variants exhibit reduced virus replication capacity, a phenomenon that seems to depend on the presence of an X4-tropic Env. Furthermore, competing for IDE by exogenous insulin or inhibiting IDE by the highly specific inhibitor 6bK, also reduced virus replication. This effect could be specifically attributed to IDE since replication of HIV-1 variants coding for an IDE-insensitive p6 were inert towards IDE-inhibition. Our cumulative data support a model in which removal of p6 during viral entry is important for virus replication, at least in the case of X4 tropic HIV-1.
EVALuna2:33767

Pseudoexfoliation syndrome-associated genetic variants affect transcription factor binding and alternative splicing of LOXL1 - Pasutto, Francesca; Zenkel, Matthias; Hoja, Ursula; Berner, Daniel; Uebe, Steffen; Ferrazzi, Fulvia; Schoedel, Johannes; Liravi, Panah; Ozaki, Mineo; Paoli, Daniela; Frezzotti, Paolo; Mizoguchi, Takanori; et al. (Nature Communications, 2017)
Although lysyl oxidase-like 1 (LOXL1) is known as the principal genetic risk factor for pseudoexfoliation (PEX) syndrome, a major cause of glaucoma and cardiovascular complications, no functional variants have been identified to date. Here, we conduct a genome-wide association scan on 771 German PEX patients and 1,350 controls, followed by independent testing of associated variants in Italian and Japanese data sets. We focus on a 3.5-kb four-component polymorphic locus positioned spanning introns 1 and 2 of LOXL1 with enhancer-like chromatin features. We find that the rs11638944:C>G transversion exerts a cis-acting effect on the expression levels of LOXL1, mediated by differential binding of the transcription factor RXR? (retinoid X receptor alpha) and by modulating alternative splicing of LOXL1, eventually leading to reduced levels of LOXL1 mRNA in cells and tissues of risk allele carriers. These findings uncover a functional mechanism by which common noncoding variants influence LOXL1 expression.
EVALuna2:9367

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Pulmonary Dysfunction after Pediatric COVID-19 - Heiß, Rafael; Tan, Lina; Schmidt, Sandy; Regensburger, Adrian; Ewert, Franziska; Mammadova, Dilbar; Bühler, Adrian; Vogel-Claussen, Jens; Voskrebenzev, Andreas; Rauh, Manfred; Rompel, Oliver; Nagel, Armin Michael; et al. (Radiology, 2022)
Background Long COVID occurs in lower frequency in children and adolescents than in adults. Morphologic and free-breathing phase-resolved functional low-field MRI may identify persistent pulmonary manifestations after SARS-CoV-2 infection. Purpose To characterize both morphologic and functional changes of lung parenchyma on low-field MRI in children and adolescents with post COVID-19 compared with healthy controls. Materials and Methods Between August and December 2021, a cross-sectional, prospective clinical trial using low-field MRI was performed in children and adolescents from a single academic medical center. The primary outcome was the frequency of morphologic changes on MRI. Secondary outcomes included MRI-derived functional proton ventilation and perfusion parameters. Clinical symptoms, the duration from positive RT-PCR test and serological parameters were compared with imaging results. Nonparametric tests for pairwise and corrected tests for groupwise comparisons were applied to assess differences in healthy controls, recovered participants and with long COVID. Results A total of 54 participants post COVID-19 infection (mean age, 11 years ±3 [SD], 56 males) and 9 healthy controls (mean age, 10 years ±3 [SD], 70 males) were included: 29 (54%) in the COVID-19 group had recovered from infection and 25 (46%) were classified as having long COVID on the day of enrollment. Morphologic abnormality was identified in one recovered participant. Both ventilated and perfused lung parenchyma (V/Q match) was reduced from 81±6.1% in healthy controls to 62±19% (P =.006) in the recovered group and 60±20% (P=.003) in the long COVID group. V/Q match was lower in post COVID patients with infection less than 180 days (63±20%, P=.03), 180 to 360 days (63±18%, P=0.03) and 360 days ago (41±12%, P<.001) as compared with the never-infected healthy controls (81±6.1%). Conclusion Low-field MRI showed persistent pulmonary dysfunction in both children and adolescents recovered from COVID-19 and with long COVI

Quantile regression: A short story on how and why - Waldmann, Elisabeth (Statistical Modelling, 2018)
Quantile regression quantifies the association of explanatory variables with a conditional quantile of a dependent variable without assuming any specific conditional distribution. It hence models the quantiles, instead of the mean as done in standard regression. In cases where either the requirements for mean regression, such as homoscedasticity, are violated or interest lies in the outer regions of the conditional distribution, quantile regression can explain dependencies more accurately than classical methods. However, many quantile regression papers are rather theoretical so the method has still not become a standard tool in applications. In this article, we explain quantile regression from an applied perspective. In particular, we illustrate the concept, advantages and disadvantages of quantile regression using two datasets as examples.
EVALuna2:35669

Receptor-independent modulation of TGF-β-induced pro-fibrotic pathways by relaxin-2 in human primary tubular epithelial cells - Grampp, Steffen; Goppelt-Strübe, Margarete (Cell and Tissue Research, 2018)
Renal tubular epithelial cells actively contribute to the development of renal fibrosis and may be targeted by anti-fibrotic drugs. Relaxin-2 (RLX2) applied as recombinant protein is suggested to be renoprotective. Therefore, we investigated whether human primary tubular epithelial cells (hPTEC) obtained from various donors were target cells for the anti-fibrotic actions of RLX2. Treatment of hPTEC with RLX2 reduced the TGF-β1-induced secretion of the pro-fibrotic factor CTGF (connective tissue growth factor) and inhibited fibronectin synthesis and secretion. Furthermore, metalloproteinase MMP2 secretion was increased, with no effect on MMP9. Considerable differences were observed between hPTEC obtained from different donors. Therefore, expression of the relaxin family peptide receptor RXFP1, the major mediator of renal RLX2 effects, was analyzed. A validated antibody detected a double band of 80–90 kDa in cellular homogenates by Western blotting. Expression of the detected protein was not altered by incubation with TGF-β1 and RLX2-induced modulation of CTGF expression did not correlate with the putative receptor expression. Therefore, relaxin family receptors RXFP1–4 were assessed by RNA-seq analysis. No evidence was found for mRNA expression of any of these receptors in several hPTEC preparations. Lack of RXFP1 mRNA was confirmed by qPCR using mRNA obtained from THP-1 cells as positive control. Our data thus provide evidence for primary renal human tubular epithelial cells as targets for the anti-fibrotic actions of RLX2. However, anti-fibrotic effects were observed at micromolar concentrations of RLX2 and shown to be independent of RXFP1 expression.
Created from Fastlane, Scopus look-up
Keywords: CTGF; Fibronectin; Human primary renal epithelial cells; MMP; Relaxin-2; RXFP1; Transforming growth factor beta

Recombinant Human Cytomegalovirus Expressing an Analog-Sensitive Kinase pUL97 as Novel Tool for Functional Analyses - Krämer, Nadine; Schütz, Martin; Mato, Uxía Gestal; Herhaus, Lina; Marschall, Manfred; Zimmermann, Christine (Viruses, 2022)
The human cytomegalovirus (HCMV) is a member of the beta-herpesvirus family and inflicts life-long latent infections in its hosts. HCMV has been shown to manipulate and dysregulate many cellular processes. One major interactor with the cellular host is the viral kinase pUL97. The UL97 gene is essential for viral replication, and kinase-deficient mutants of pUL97 display a severe replication defect. Recently, another group established an analog-sensitive version of the pUL97 protein. This mutant kinase can be treated with a non-hydrolysable ATP analog, thereby inhibiting its kinase function. This process is reversible by removing the ATP analog by media change. We introduced this mutant version of the pUL97 protein into the laboratory strain Ad169 of HCMV, BADwt, creating a BAD-UL97-as1 viral mutant. This mutant virus replicated normally in infected cells in the absence of the ATP analog and maintained its ability to phosphorylate its cellular substrates. However, when treated with the ATP analog, BAD-UL97-as1 displayed a defect in the production of intra- and extracellular viral DNA and in the production of viral progeny. Furthermore, in the presence of 3MB-PP1, a well-established substrate of pUL97 was no longer hyperphosphorylated. This effect was detectable as early as 4 h post treatment, which allows for studies on pUL97 without the complication of low viral titers. Nevertheless, we observed off-target effects of 3MB-PP1 on several cellular processes, which should be considered with this approach.
CRIS-Team Scopus Importer:2022-11-04
Keywords: analog-sensitive pUL97 variant; BACmid-derived recombinant HCMV; functional analyses; human cytomegalovirus (HCMV); protein kinase pUL97; pUL97-specific inhibitors; viral kinase activity

Recombinant pro-CTSD (cathepsin D) enhances SNCA/α-Synuclein degradation in α-Synucleinopathy models. - Huarcaya, Alice Prieto; Drobny, Susy; Marques, Andre R. A.; Di Spiezio, Alessandro; Dobert, Jan; Balta, Denise; Werner, Christian; Rizo Garza, Tania; Gallwitz, Lisa; Bub, Simon; Stojkovska, Iva; Belur, Nandkishore R.; et al. (Autophagy, 2022)
Parkinson disease (PD) is a neurodegenerative disorder characterized by the abnormal intracellular accumulation of SNCA/α-synuclein. While the exact mechanisms underlying SNCA pathology are not fully understood, increasing evidence suggests the involvement of autophagy as well as lysosomal deficiencies. Because CTSD (cathepsin D) has been proposed to be the major lysosomal protease involved in SNCA degradation, its deficiency has been linked to the presence of insoluble SNCA conformers in the brain of mice and humans as well as to the transcellular transmission of SNCA aggregates. We here postulate that SNCA degradation can be enhanced by the application of the recombinant human proform of CTSD (rHsCTSD). Our results reveal that rHsCTSD is efficiently endocytosed by neuronal cells, correctly targeted to lysosomes and matured to an enzymatically active protease. In dopaminergic neurons derived from induced pluripotent stem cells (iPSC) of PD patients harboring the A53T mutation within the SNCA gene, we confirm the reduction of insoluble SNCA after treatment with rHsCTSD. Moreover, we demonstrate a decrease of pathological SNCA conformers in the brain and within primary neurons of a ctsd-deficient mouse model after dosing with rHsCTSD. Boosting lysosomal CTSD activity not only enhanced SNCA clearance in human and murine neurons as well as tissue, but also restored endo-lysosome and autophagy function. Our findings indicate that CTSD is critical for SNCA clearance and function. Thus, enzyme replacement strategies utilizing CTSD may also be of therapeutic interest for the treatment of PD and other synucleinopathies aiming to decrease the SNCA burden.Abbreviations: aa: amino acid; SNCA/α-synuclein: synuclein alpha; APP: amyloid beta precursor protein; BBB: blood brain barrier; BF: basal forebrain; CBB: Coomassie Brilliant Blue; CLN: neuronal ceroid lipofuscinosis; CNL10: neuronal ceroid lipofuscinosis type 10; Corr.: corrected; CTSD: cathepsin D; CTSB: cathepsin B; DA: dopaminergic; DA-iPSn: induced pluripotent stem cell-derived dopaminergic neurons; dox: doxycycline; ERT: enzyme replacement therapy; Fx: fornix, GBA/β-glucocerebrosidase: glucosylceramidase beta; h: hour; HC: hippocampus; HT: hypothalamus; i.c.: intracranially; IF: immunofluorescence; iPSC: induced pluripotent stem cell; KO: knockout; LAMP1: lysosomal associated membrane protein 1; LSDs: lysosomal storage disorders; MAPT: microtubule associated protein tau; M6P: mannose-6-phosphate; M6PR: mannose-6-phosphate receptor; MB: midbrain; mCTSD: mature form of CTSD; neurofil.: neurofilament; PD: Parkinson disease; proCTSD: proform of CTSD; PRNP: prion protein; RFU: relative fluorescence units; rHsCTSD: recombinant human proCTSD; SAPC: Saposin C; SIM: structured illumination microscopy; T-insol: Triton-insoluble; T-sol: Triton-soluble; TEM: transmission electron microscopy, TH: tyrosine hydroxylase; Thal: thalamus.
Keywords: alpha-synuclein; cathepsin D; lysosomal degradation; lysosomal storage disorders; parkinson disease; synucleinopathies

Rectal Delivery of a DNAzyme That Specifically Blocks the Transcription Factor GATA3 and Reduces Colitis in Mice - Popp, Vanessa; Gerlach, Katharina; Mott, Stefanie; Turowska, Agnieszka; Garn, Holger; Atreya, Raja; Lehr, Hans-Anton; Ho, I-Cheng; Renz, Harald; Weigmann, Benno; Neurath, Markus (Gastroenterology, 2017)
BACKGROUND & AIMS: GATA3 is a transcription factor that regulates T-cell production of cytokines. We investigated the role of GATA3 in development of colitis in mice. METHODS: We performed quantitative polymerase chain reaction and immunofluorescence analyses of colon tissues from patients with Crohn's disease (n = 61) or ulcerative colitis (UC, n = 74) or from patients without inflammatory bowel diseases (n = 22), to measure levels of GATA3. Colitis was induced by administration of oxazolone or 2,4,6-trinitrobenzenesulfonic acid to control mice, mice with T-cell-specific deletion of GATA3, and mice with deletion of tumor necrosis factor receptor (TNFR) 1 and TNFR2 (TNFR double knockouts); some mice were given a GATA3-specific DNAzyme (hgd40) or a control DNAzyme via intrarectal administration, or systemic injections of an antibody to TNF before or during sensitization and challenge phase of colitis induction. Colon tissues were collected and immunofluorescence and histochemical analyses were performed. Lamina propria mononuclear cells and T cells were isolated and analyzed by flow cytometry or cytokine assays. Colonic distribution of labeled DNAzyme and inflammation were monitored by in vivo imaging (endoscopy) of mice. RESULTS: Levels of GATA3 messenger RNA were higher in colon tissues from patients with UC, but not ileal Crohn's disease, than control tissues; levels of GATA3 correlated with levels of inflammatory cytokines (interleukin [IL] 9, IL17A, IL6, IL5, IL4, IL13, and TNF). We observed increased expression of GATA3 by lamina propria T cells from mice with colitis compared with controls. Mice with T-cell-specific deletion of GATA3 did not develop colitis and their colonic tissues did not produce inflammatory cytokines (IL6, IL9, or IL13). The DNAzyme hgd40 inhibited expression of GATA3 messenger RNA by unstimulated and stimulated T cells, and distributed throughout the inflamed colons of mice with colitis. Colon tissues from mice given hgd40 had reduced expression of GATA3 messenger RNA, compared with mice given a control DNAzyme. Mice given hgd40 did not develop colitis after administration of oxazolone or 2,4,6-trinitrobenzenesulfonic acid; lamina propria cells from these mice expressed lower levels of IL6, IL9, and IL13 than cells from mice given the control DNAzyme. Mini-endoscopic images revealed that hgd40 and anti-TNF reduced colon inflammation over 3 days; hgd40 reduced colitis in TNFR double-knockout mice. CONCLUSIONS: Levels of GATA3 are increased in patients with UC and correlate with production of inflammatory cytokines in mice and humans. A DNAzyme that prevents expression of GATA3 reduces colitis in mice, independently of TNF, and reduces levels of cytokines in the colon. This DNAzyme might be developed for treatment of patients with UC.
EVALuna2:33833

Reduced synaptic activity and dysregulated extracellular matrix pathways in midbrain neurons from Parkinson’s disease patients - Stern, Shani; Lau, Shong; Manole, Andreea; Rosh, Idan; Percia, Menachem Mendel; Ben Ezer, Ran; Shokhirev, Maxim N.; Qiu, Fan; Schafer, Simon; Mansour, Abed Alfatah; Mangan, Kile P.; Stern, Tchelet; et al. (npj Parkinson’s Disease, 2022)
Several mutations that cause Parkinson’s disease (PD) have been identified over the past decade. These account for 15–25% of PD cases; the rest of the cases are considered sporadic. Currently, it is accepted that PD is not a single monolithic disease but rather a constellation of diseases with some common phenotypes. While rodent models exist for some of the PD-causing mutations, research on the sporadic forms of PD is lagging due to a lack of cellular models. In our study, we differentiated PD patient-derived dopaminergic (DA) neurons from the induced pluripotent stem cells (iPSCs) of several PD-causing mutations as well as from sporadic PD patients. Strikingly, we observed a common neurophysiological phenotype: neurons derived from PD patients had a severe reduction in the rate of synaptic currents compared to those derived from healthy controls. While the relationship between mutations in genes such as the SNCA and LRRK2 and a reduction in synaptic transmission has been investigated before, here we show evidence that the pathogenesis of the synapses in neurons is a general phenotype in PD. Analysis of RNA sequencing results displayed changes in gene expression in different synaptic mechanisms as well as other affected pathways such as extracellular matrix-related pathways. Some of these dysregulated pathways are common to all PD patients (monogenic or idiopathic). Our data, therefore, show changes that are central and convergent to PD and suggest a strong involvement of the tetra-partite synapse in PD pathophysiology.
CRIS-Team Scopus Importer:2022-08-26

Regression of apoptosis-resistant colorectal tumors by induction of necroptosis in mice - He, Gui-Wei; Günther, Claudia; Thonn, Veronika; Yu, Yu-Qiang; Martini, Eva; Buchen, Barbara; Neurath, Markus; Stürzl, Michael; Becker, Christoph (Journal of Experimental Medicine, 2017)
Cancer cells often acquire capabilities to evade cell death induced by current chemotherapeutic treatment approaches. Caspase-8, a central initiator of death receptor-mediated apoptosis, for example, is frequently inactivated in human cancers via multiple mechanisms such as mutation. Here, we show an approach to overcome cell death resistance in caspase-8-deficient colorectal cancer (CRC) by induction of necroptosis. In both a hereditary and a xenograft mouse model of caspase-8-deficient CRC, second mitochondria-derived activator of caspase (SMAC) mimetic treatment induced massive cell death and led to regression of tumors. We further demonstrate that receptor-interacting protein kinase 3 (RIP3), which is highly expressed in mouse models of CRC and in a subset of human CRC cell lines, is the deciding factor of cancer cell susceptibility to SMAC mimetic-induced necroptosis. Thus, our data implicate that it may be worthwhile to selectively evaluate the efficacy of SMAC mimetic treatment in CRC patients with caspase-8 deficiency in clinical trials for the development of more effective personalized therapy.
EVALuna2:15307

Regulated on Activation, Normal T cell Expressed and Secreted (RANTES) drives the resolution of allergic asthma - Li, Nina; Mirzakhani, Hoomann; Kiefer, Alexander; Kölle, Julia; Vuorinen, Tytti; Rauh, Manfred; Yang, Zuqin; Krammer, Susanne; Xepapadaki, Paraskevi; Lewandowska-Polak, Anna; Lukkarinen, Heikki; Zhang, Nan; et al. (iScience, 2021)
RANTES is implicated in allergic asthma and in T cell-dependent clearance of infection. RANTES receptor family comprises CCR1, CCR3, and CCR5, which are G-protein-coupled receptors consisting of seven transmembrane helices. Infections with respiratory viruses like Rhinovirus cause induction of RANTES production by epithelial cells. Here, we studied the role of RANTES in the peripheral blood mononuclear cells in cohorts of children with and without asthma and validated and extended this study to the airways of adults with and without asthma. We further translated these studies to a murine model of asthma induced by house dust mite allergen in wild-type RANTES and CCR5-deficient mice. Here we show an unpredicted therapeutic role of RANTES in the resolution of allergen-induced asthma by orchestrating the transition of effector GATA-3+CD4+ T cells into immune-regulatory-type T cells and inflammatory eosinophils into resident eosinophils as well as increased IL-10 production in the lung.
CRIS-Team WoS Importer:2021-11-19

Regulation of autoantibody activity by the IL-23-TH17 axis determines the onset of autoimmune disease. - Pfeifle, René; Rothe, Tobias; Ipseiz, Natacha; Scherer, Hans U.; Culemann, Stephan; Harre, Ulrike; Ackermann, Jochen; Seefried, Martina; Kleyer, Arnd; Uderhardt, Stefan; Haugg, Benjamin; Huebert, Axel J.; et al. (Nature Immunology, 2017)
The checkpoints and mechanisms that contribute to autoantibody-driven disease are as yet incompletely understood. Here we identified the axis of interleukin 23 (IL-23) and the TH17 subset of helper T cells as a decisive factor that controlled the intrinsic inflammatory activity of autoantibodies and triggered the clinical onset of autoimmune arthritis. By instructing B cells in an IL-22- and IL-21-dependent manner, TH17 cells regulated the expression of β-galactoside α2,6-sialyltransferase 1 in newly differentiating antibody-producing cells and determined the glycosylation profile and activity of immunoglobulin G (IgG) produced by the plasma cells that subsequently emerged. Asymptomatic humans with rheumatoid arthritis (RA)-specific autoantibodies showed identical changes in the activity and glycosylation of autoreactive IgG antibodies before shifting to the inflammatory phase of RA; thus, our results identify an IL-23-TH17 cell-dependent pathway that controls autoantibody activity and unmasks a preexisting breach in immunotoleranc

Regulatory eosinophils induce the resolution of experimental arthritis and appear in remission state of human rheumatoid arthritis - Andreev, Darja; Liu, Mengdan; Kachler, Katerina; Llerins Perez, Mireia; Kirchner, Philipp; Kölle, Julia; Gießl, Andreas; Rauber, Simon; Song, Rui; Aust, Oliver; Grüneboom, Anika; Kleyer, Arnd; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives: Eosinophils possess pro-inflammatory functions in asthma. However, our recent studies have suggested that innate lymphoid cells type 2 (ILC2s) and eosinophils have proresolving properties in rheumatoid arthritis (RA). Nothing is known yet about the mechanisms determining the double-edged role of eosinophils. Therefore, we investigated whether asthma, a paradigm eosinophilic disease, can elicit resolution of chronic arthritis. Methods: Ovalbumin-triggered eosinophilic asthma was combined with K/BxN serum-induced arthritis, where lung and synovial eosinophil subsets were compared by single-cell RNA sequencing (scRNA-seq). To investigate the involvement of the ILC2-interleukin-5 (IL-5) axis, hydrodynamic injection (HDI) of IL-25 and IL-33 plasmids, IL-5 reporter mice and anti-IL-5 antibody treatment were used. In patients with RA, the presence of distinct eosinophil subsets was examined in peripheral blood and synovial tissue. Disease activity of patients with RA with concomitant asthma was monitored before and after mepolizumab (anti-IL-5 antibody) therapy. Results: The induction of eosinophilic asthma caused resolution of murine arthritis and joint tissue protection. ScRNA-seq revealed a specific subset of regulatory eosinophils (rEos) in the joints, distinct from inflammatory eosinophils in the lungs. Mechanistically, synovial rEos expanded on systemic upregulation of IL-5 released by lung ILC2s. Eosinophil depletion abolished the beneficial effect of asthma on arthritis. rEos were consistently present in the synovium of patients with RA in remission, but not in active stage. Remarkably, in patients with RA with concomitant asthma, mepolizumab treatment induced relapse of arthritis. Conclusion: These findings point to a hitherto undiscovered proresolving signature in an eosinophil subset that stimulates arthritis resolution.
CRIS-Team Scopus Importer:2020-11-20
Keywords: arthritis; autoimmune diseases; cytokines; immune system diseases; inflammation; rheumatoid

Resolution of Cutaneous Leishmaniasis and Persistence of Leishmania major in the Absence of Arginase 1 - Paduch, Katrin; Debus, Andrea; Rai, Baplu; Schleicher, Ulrike; Bogdan, Christian (Journal of Immunology, 2019)
Arginase (Arg) 1 is expressed by hematopoietic (e.g., macrophages) and nonhematopoietic cells (e.g., endothelial cells) and converts L-arginine into ornithine and urea. The enzyme is implicated in tissue repair but also antagonizes the production of NO by type 2 NO synthase in myeloid cells and thereby impedes the control of intracellular parasites such as Leishmania major. In this study, we tested whether Arg1 is required for spontaneous healing of acute cutaneous leishmaniasis in C57BL/6 mice and for lifelong parasite persistence in draining lymph nodes (dLNs) of healed mice. In vitro, bone marrow-derived macrophages and lymphoid endothelial cells readily expressed Arg1 in response to IL-4 and/or IL-13, whereas skin or dLN fibroblasts failed to do so, even during hypoxia. In vivo, Arg1 was found in skin lesions and, to a much lower extent, also in dLNs of acutely infected C57BL/6 mice but became undetectable at both sites after healing. Deletion of Arg1 in hematopoietic and endothelial cells using Tie2Cre(+/-) Arg1(fl/fl) C57BL/6 mice abolished the expression of Arg1 in skin lesions and dLNs but did not affect development and resolution of skin lesions, parasite burden, NO production, or host cell tropism of L. major during the acute or persistent phase of infection. Similar to wild-type controls, parasites persisting in Arg1-deficient mice favored NO synthase 2-negative areas and mainly resided in myeloid cells and fibroblasts. We conclude that Arg1 expression by hematopoietic and endothelial cells is completely dispensable for clinical resolution of cutaneous leishmaniasis and for long-term persistence of L. major.
CRIS-Team WoS Importer:2019-03-06

Resolution of inflammation by interleukin-9-producing type 2 innate lymphoid cells - Rauber, Simon; Luber, Markus; Weber, Stefanie; Maul, Lisa; Soare, Alina; Wohlfahrt, Thomas; Lin, Neng-Yu; Dietel, Katharina; Bozec, Aline; Herrmann, Martin; Kaplan, Mark H.; Weigmann, Benno; et al. (Nature Medicine, 2017)
Inflammatory diseases such as arthritis are chronic conditions that fail to resolve spontaneously. While the cytokine and cellular pathways triggering arthritis are well defined, those responsible for the resolution of inflammation are incompletely characterized. Here we identified interleukin (IL)-9-producing type 2 innate lymphoid cells (ILC2s) as the mediators of a molecular and cellular pathway that orchestrates the resolution of chronic inflammation. In mice, the absence of IL-9 impaired ILC2 proliferation and activation of regulatory T (Treg) cells, and resulted in chronic arthritis with excessive cartilage destruction and bone loss. In contrast, treatment with IL-9 promoted ILC2-dependent Treg activation and effectively induced resolution of inflammation and protection of bone. Patients with rheumatoid arthritis in remission exhibited high numbers of IL-9(+) ILC2s in joints and the circulation. Hence, fostering IL-9-mediated ILC2 activation may offer a novel therapeutic approach inducing resolution of inflammation rather than suppression of inflammatory responses.
EVALuna2:13255

Rheumatoid arthritis and osteoimmunology: The adverse impact of a deregulated immune system on bone metabolism - Andreev, Darja; Kachler, Katerina; Bozec, Aline; Schett, Georg (Bone, 2022)
The term osteoimmunology describes an interdisciplinary research field that links the investigation of osteology (bone cells) with immunology. The crosstalk between innate and adaptive immune cells and cells involved in bone remodeling, mainly bone-resorbing osteoclasts and bone-forming osteoblasts, becomes particularly obvious in the inflammatory autoimmune disease rheumatoid arthritis (RA). Besides striking inflammation of the joints, RA causes bone loss, leading to joint damage and disabilities as well as generalized osteoporosis. Mechanistically, RA-associated immune cells (macrophages, T cells, B cells etc.) produce high levels of pro-inflammatory cytokines, receptor activator of nuclear factor κB ligand (RANKL) and autoantibodies that promote bone degradation and at the same time counteract new bone formation. Today, antirheumatic therapy effectively ceases joint inflammation and arrests bone erosion. However, the repair of established bone lesions still presents a challenging task and requires improved treatment options. In this review, we outline the knowledge gained over the past years about the immunopathogenesis of RA and the impact of a dysregulated immune system on bone metabolism.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Bone erosion; Osteoblasts; Osteoclasts; Osteoimmunology; Rheumatoid arthritis

Rhinovirus Suppresses TGF-β-GARP Presentation by Peripheral NK Cells - Krammer, Susanne; Yang, Zuqin; Mitländer, Hannah; Grund, Janina; Trump, Sonja; Mittler, Susanne; Zirlik, Sabine; Neurath-Finotto, Susetta (Cells, 2023)
Asthma is a chronic airway disease whose exacerbations are often triggered by rhinovirus infection. TGF-β1 induces rhinovirus replication in infected cells. Moreover, TGF-β1 is a pleiotropic mediator that is produced by many immune cells in the latent, inactive form bound to the latency-associated peptide (LAP) and to the transmembrane protein glycoprotein A repetitions predominant (GARP). In this study we wanted to investigate the effect of rhinovirus infection on the TGF-β secretion and the downstream signaling via TGF-βRI/RII in peripheral blood mononuclear cells from control and asthmatic patients after rhinovirus infection ex vivo. Here, we found a significant upregulation of TGF-βRII in untouched PBMCs of asthmatics as well as a suppression of TGF-β release in the rhinovirus-infected PBMC condition. Moreover, consistent with an effect of TGF-β on Tregs, PBMCs infected with RV induced Tregs, and TGF-βRII directly correlated with RV1b mRNA. Finally, we found via flow cytometry that NK cells expressed less GARP surface-bound TGF-β, while cytokine-producing NKbright cells were induced. In summary, we show that rhinovirus infection inhibits TGF-β release in PBMCs, which results in the activation of both Treg and NK cells.
CRIS-Team Scopus Importer:2023-01-20
Keywords: asthma; NK cells; rhinovirus; TGF-β; TGF-β RI; TGF-β RII

Role of Mitochondrial Metabolism in the Control of Early Lineage Progression and Aging Phenotypes in Adult Hippocampal Neurogenesis - Beckervordersandforth, Ruth; Ebert, Birgit; Schäffner, Iris; Moss, Jonathan; Fiebig, Christian; Shin, Jaehoon; Moore, Darcie L.; Ghosh, Laboni; Trinchero, Mariela F.; Stockburger, Carola; Friedland, Kristina; Steib, Kathrin; et al. (Neuron, 2017)
EVALuna2:4763

Role of the IL23/IL17 Pathway in Crohn’s Disease - Schmitt, Heike; Neurath, Markus; Atreya, Raja (Frontiers in Immunology, 2021)
Crohn’s disease (CD) is a chronic relapsing disorder of the gastrointestinal tract and represents one of the main entities of inflammatory bowel disease (IBD). CD affects genetically susceptible patients that are influenced by environmental factors and the intestinal microbiome, which results in excessive activation of the mucosal immune system and aberrant cytokine responses. Various studies have implicated the pro-inflammatory cytokines IL17 and IL23 in the pathogenesis of CD. IL23 is a member of the IL12 family of cytokines and is able to enhance and affect the expansion of pathogenic T helper type 17 (Th17) cells through various mechanisms, including maintenance of Th17 signature genes, upregulation of effector genes or suppression of repressive factors. Moreover, IL17 and IL23 signaling is able to induce a cascade of pro-inflammatory molecules like TNF, IFNγ, IL22, lymphotoxin, IL1β and lipopolysaccharide (LPS). Here, IL17A and TNF are known to mediate signaling synergistically to drive expression of inflammatory genes. Recent advances in understanding the immunopathogenetic mechanisms underlying CD have led to the development of new biological therapies that selectively intervene and inhibit inflammatory processes caused by pro-inflammatory mediators like IL17 and IL23. Recently published data demonstrate that treatment with selective IL23 inhibitors lead to markedly high response rates in the cohort of CD patients that failed previous anti-TNF therapy. Macrophages are considered as a main source of IL23 in the intestine and are supposed to play a key role in the molecular crosstalk with T cell subsets and innate lymphoid cells in the gut. The following review focuses on mechanisms, pathways and specific therapies in Crohn’s disease underlying the IL23/IL17 pathway.
CRIS-Team Scopus Importer:2021-04-23
Keywords: anti-TNF therapy; Crohn’s disease; IL17/IL23 axis; inflammation; intestinal immunity; non-responder; resistance to apoptosis

Routine Surveillance of SARS-CoV-2 Serostatus in Pediatrics Allows Monitoring of Humoral Response - Wachter, Felix; Knieling, Ferdinand; Raming, Roman; Simon, David; Wölfle, Joachim; Hörning, André; Neubert, Antje; Rauh, Manfred; Regensburger, Adrian (Microorganisms, 2023)
The occurrence of SARS-CoV-2 infections during the pandemic was mainly based on PCR testing of symptomatic patients. However, with new variants, vaccinations, and the changing of the clinical disease severity, knowledge about general immunity is elusive. For public health systems, timely knowledge of these conditions is essential, but it is particularly scarce for the pediatric population. Therefore, in this study, we wanted to investigate the spike and nucleocapsid seroprevalence in pediatric patients using routine residual blood tests collected during the pandemic. This prospective observational study was conducted over seven one-month periods. Herein, the latest four time periods (November 2021, January 2022, March 2022, and May 2022) are depicted. Each patient of a tertiary-care center in Germany was anonymized after collection of clinical diagnosis (ICD-10) and then routinely tested for the respective spike and nucleocapsid SARS-CoV-2 antibody titer. A total of 3235 blood samples from four time periods were included. Spike seroprevalence rose from 37.6% to 51.9% to 70.5% to 85.1% and nucleocapsid seroprevalence from 11.6% to 17.0% to 36.7% to 58.1% in May 2022. In detail, significant changes in seroprevalence between age groups but not between sex or diagnosis groups were found. Quantitative measures revealed rising spike and constant nucleocapsid antibody levels over the pandemic with a half-life of 102 days for spike and 45 days for nucleocapsid antibodies. Routine laboratory assessment of SARS-CoV-2 in residual blood specimens of pediatric hospitals enables monitoring of the seroprevalence and may allow inferences about general immunity in this cohort.
EVALuna2:547467
Keywords: COVID-19; pediatrics; seroprevalence; SARS-CoV-2; Omicron; surveillance

Salvage therapy with Sodium chlorosum (formerly DAC N-055) for cases of refractory lupoid cutaneous leishmaniasis: Results from a compassionate use study with 0.09% Sodium chlorosum in amphiphilic basic cream - Molkara, Sara; Poursoltani, Elaheh; Stahl, Kurt Wilhelm; Maleki, Masoud; Khamesipour, Ali; Bogdan, Christian; Salehi, Maryam; Goyonlo, Vahid Mashayekhi (BMC Infectious Diseases, 2019)
Background: Lupoid cutaneous leishmaniasis (LCL) is known as a rare but serious complication of anthroponotic cutaneous leishmaniasis (ACL) resistant to conventional treatments. Sodium chlorosum, a pro-oxidative preparation of pharmaceutical sodium chlorite (NaClO2), has been successfully used for the treatment of Old World cutaneous leishmaniasis lesions (OWCL) and of some LCL cases in Afghanistan. This clinical trial study aimed to evaluate the effect of a last resort therapy with topical 0.09% sodium chlorosum on LCL in Iran. Methods: Twenty Iranian patients (12 women and 8 men) with LCL refractory to treatment were included in this salvage study. A magistral preparation of sodium chlorosum (10 mM NaClO2 in amphiphilic basic cream) was applied twice daily to the lesions for 6 weeks and continued up to 12 weeks in patients who showed a clinical response within the first 6 weeks. Responders were followed up for a maximum of 1 year. Lesions were photographed during weekly visits. Disappearance of erythema and indurated lesions were rated as complete clinical response. Results: Patients with a mean age of 28.6 (±24.3) and with an ACL proven lesion history of 3.8 (±1.4) years were treated for an average of 7.9 (±1.8) weeks. At the end of the treatment period (12th week), a complete response was observed in 9 of 20 patients (45%). During the one-year follow-up period, LCL lesions recurred in 4 of these 9 patients (with one patient showing only a tiny lesion) and one case lost to follow up whereas the other four remained completely lesion-free. Mild temporary side-effects such as erythema and itching were seen in 4 of 20 patients (20%). Conclusions: Topical sodium chlorosum showed promising therapeutic results and can be considered as safe, painless, and relatively effective treatment for LCL, an ethical prerequisite for a two-armed controlled trial. Trial registration: This study was registered in Iranian registry of clinical trials on 2019-02-02 with registration number IRCT20190114042356N1.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Lupoid cutaneous leishmaniasis; Sodium chlorosum (formerly DAC N-055); Treatment

SAMHD1 … and Viral Ways around It. - Deutschmann, Janina; Gramberg, Thomas (Viruses, 2021)
The SAM and HD domain-containing protein 1 (SAMHD1) is a dNTP triphosphohydrolase that plays a crucial role for a variety of different cellular functions. Besides balancing intracellular dNTP concentrations, facilitating DNA damage repair, and dampening excessive immune responses, SAMHD1 has been shown to act as a major restriction factor against various virus species. In addition to its well-described activity against retroviruses such as HIV-1, SAMHD1 has been identified to reduce the infectivity of different DNA viruses such as the herpesviruses CMV and EBV, the poxvirus VACV, or the hepadnavirus HBV. While some viruses are efficiently restricted by SAMHD1, others have developed evasion mechanisms that antagonize the antiviral activity of SAMHD1. Within this review, we summarize the different cellular functions of SAMHD1 and highlight the countermeasures viruses have evolved to neutralize the restriction factor SAMHD1.
CRIS-Team WoS Importer:2021-04-09

Select Clr-g Expression on Activated Dendritic Cells Facilitates Cognate Interaction with a Minor Subset of Splenic NK Cells Expressing the Inhibitory Nkrp1g Receptor - Friede, Miriam E.; Leibelt, Stefan; Dudziak, Diana; Steinle, Alexander (Journal of Immunology, 2018)
Natural killer gene complex-encoded immunomodulatory C-type lectin-like receptors include members of the NKRP1 and C-type lectin-like 2 (CLEC2) gene families, which constitute genetically linked receptor-ligand pairs and are thought to allow for NK cell-mediated immunosurveillance of stressed or infected tissues. The mouse C-type lectin-like receptor Nkrp1g was previously shown to form several receptor-ligand pairs with the CLEC2 proteins Clr-d, Clr-f, and Clr-g, respectively. However, the physiological expression of Nkrp1g and its CLEC2 ligands as well as their functional relevance remained poorly understood. Recently, we demonstrated a gut-restricted expression of Clr-f on intestinal epithelial cells that is spatially matched by Nkrp1g on subsets of intraepithelial lymphocytes. In this study, we investigated expression and ligand interaction of Nkrp1g in the splenic compartment, and found an exclusive expression on a small subset of NK cells that upregulates Nkrp1g after cytokine exposure. Whereas transcripts of Clr-d and Clr-f are virtually absent from the spleen, Clr-g transcripts were abundantly detected throughout different leukocyte populations and hematopoietic cell lines. However, a newly generated anti-Clr-g mAb detected only residual Clr-g surface expression on splenic monocytes, whereas many hematopoietic cell lines brightly display Clr-g. Clr-g surface expression was strongly upregulated on splenic CD8α+ conventional dendritic cells (DCs) and plasmacytoid DCs upon TLR-mediated activation and detectable by Nkrp1g, which dampens NK cell effector functions upon Clr-g engagement. Hence, different to the intestinal tract, in the spleen, Nkrp1g is selectively expressed by a subset of NK cells, thereby potentially allowing for an inhibitory engagement with Clr-g-expressing activated DCs during immune responses.
EVALuna2:34802

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, Chunguang; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, Olaf; Nimmerjahn, Falk; Burmazovic, Ivana Ivanovic; Kunz, Meik; et al. (Science Signaling, 2021)
The detection of microorganisms and danger signals by pattern recognition receptors on dendritic cells (DCs) and the consequent formation of inflammasomes are pivotal for initiating protective immune responses. Although the activation of inflammasomes leading to secretion of the cytokine IL-1 is typically accompanied by pyroptosis (an inflammatory form of lytic programmed cell death), some cells can survive and exist in a state of hyperactivation. Here, we found that the conventional type 2 DC (cDC2) subset is the major human DC subset that is transcriptionally and functionally poised for inflammasome formation and response without pyroptosis. When cDC2 were stimulated with ligands that relatively weakly activated the inflammasome, the cells did not enter pyroptosis but instead secreted IL-12 family cytokines and IL-1. These cytokines induced prominent T helper type 1 (TH1) and TH17 responses that were superior to those seen in response to Toll-like receptor (TLR) stimulation alone or to stronger, classical inflammasome ligands. These findings not only define the human cDC2 subpopulation as a prime target for the treatment of inflammasome-dependent inflammatory diseases but may also inform new approaches for adjuvant and vaccine development.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Dendritic cells; cDC2; CD1c; inflammasome; hyperactivation; L18-MDP; T cell differentiation

Sensor-based gait analysis of individualized improvement during apomorphine titration in Parkinson's disease - Marxreiter, Franz; Gaßner, Heiko; Borozdina, Olga; Barth, Jens; Kohl, Zacharias; Schlachetzki, Johannes; Thun-Hohenstein, Caroline; Volc, Dieter; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen (Journal of Neurology, 2018)
Mobile, sensor-based gait analysis in Parkinson's disease (PD) facilitates the objective measurement of gait parameters in cross-sectional studies. Besides becoming outcome measures for clinical studies, the application of gait parameters in personalized clinical decision support is limited. Therefore, the aim of this study was to evaluate whether the individual response of PD patients to dopaminergic treatment may be measured by sensor-based gait analysis. 13 PD patients received apomorphine every 15 min to incrementally increase the bioavailable apomorphine dose. Motor performance (UPDRS III) was assessed 10 min after each apomorphine injection. Gait parameters were obtained after each UPDRS III rating from a 2 × 10 m gait sequence, providing 41.2 ± 9.2 strides per patient and injection. Gait parameters and UPDRS III ratings were compared cross-sectionally after apomorphine titration, and more importantly between consecutive injections for each patient individually. For the individual response, the effect size Cohen's d for gait parameter changes was calculated based on the stride variations of each gait sequence after each injection. Cross-sectionally, apomorphine improved stride speed, length, gait velocity, maximum toe clearance, and toe off angle. Between injections, the effect size for individual changes in stride speed, length, and maximum toe clearance correlated to the motor improvement in each patient. In addition, significant changes of stride length between injections were significantly associated with UPDRS III improvements. We therefore show, that sensor-based gait analysis provides objective gait parameters that support clinical assessment of individual PD patients during dopaminergic treatment. We propose clinically relevant instrumented gait parameters for treatment studies and especially clinical care.
EVALuna2:36376

Sensor-based gait analysis of individualized improvement during apomorphine titration in Parkinson's disease - Marxreiter, Franz; Gaßner, Heiko; Borozdina, Olga; Barth, Jens; Kohl, Zacharias; Schlachetzki, Johannes; Thun-Hohenstein, Caroline; Volc, Dieter; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen (2019)
EVALuna2:213284

Serum Autotaxin is a Marker of the Severity of Liver Injury and Overall Survival in Patients with Cholestatic Liver Diseases - Wunsch, Ewa; Krawczyk, Marcin; Milkiewicz, Malgorzata; Trottier, Jocelyn; Barbier, Olivier; Neurath, Markus; Lammert, Frank; Kremer, Andreas; Milkiewicz, Piotr (Scientific Reports, 2016)
Autotaxin (ATX) is involved in the synthesis of lysophosphatidic acid. Both have recently been linked to cholestatic pruritus and liver injury. We aimed to investigate whether ATX is an indicator of cholestatic liver injury, health-related quality of life (HRQoL) and prognosis based on a group of 233 patients, 118 with primary biliary cholangitis (PBC) and 115 with primary sclerosing cholangitis (PSC). Patients were followed for 1-60 months, cumulative survival rates were calculated. ATX activity was significantly higher in both groups than in the 103 controls, particularly in patients with cirrhosis and in patients with longer disease duration. Ursodeoxycholic acid (UDCA) non-responders with PBC exhibited increased ATX activity. ATX activity was correlated with liver biochemistry, MELD, Mayo Risk scores and was associated with worse disease-specific HRQoL aspects. In both groups, Cox model analysis indicated that ATX was a negative predictor of survival. Increased ATX levels were associated with a 4-fold higher risk of death/liver transplantation in patients with PBC and a 2.6-fold higher risk in patients with PSC. We conclude that in patients with cholestatic conditions, ATX is not only associated with pruritus but also indicates impairment of other HRQoL aspects, liver dysfunction, and can serve as a predictor of survival.
EVALuna2:2194

Severe Acute Respiratory Syndrome Coronavirus 2 Attachment Receptor Angiotensin-Converting Enzyme 2 Is Decreased in Crohn's Disease and Regulated By Microbial and Inflammatory Signaling - Patankar, Jay Vasant; Lehmann, Malte; Kühl, Anja A.; Atreya, Raja; Becker, Christoph; Gonzalez-Acera, Miguel; Schmitt, Heike; Gamez-Belmonte, Reyes; Mahapatro, Mousumi; Diemand, Leonard; Hartmann, Leonie; Mascia, Fabrizio; et al. (Gastroenterology, 2021)
CRIS-Team Scopus Importer:2021-02-12

Severe T-System Remodeling in Pediatric Viral Myocarditis - Fiegle, Dominik; Schober, Martin; Dittrich, Sven; Cesnjevar, Robert; Klingel, Karin; Volk, Tilmann; Alkassar, Muhannad; Seidel, Thomas (Frontiers in Cardiovascular Medicine, 2021)
Chronic heart failure (HF) in adults causes remodeling of the cardiomyocyte transverse tubular system (t-system), which contributes to disease progression by impairing excitation-contraction (EC) coupling. However, it is unknown if t-system remodeling occurs in pediatric heart failure. This study investigated the t-system in pediatric viral myocarditis. The t-system and integrity of EC coupling junctions (co-localization of L-type Ca2+ channels with ryanodine receptors and junctophilin-2) were analyzed by 3D confocal microscopy in left-ventricular (LV) samples from 5 children with myocarditis (age 14 +/- 3 months), undergoing ventricular assist device (VAD) implantation, and 5 children with atrioventricular septum defect (AVSD, age 17 +/- 3 months), undergoing corrective surgery. LV ejection fraction (EF) was 58.4 +/- 2.3% in AVSD and 12.2 +/- 2.4% in acute myocarditis. Cardiomyocytes from myocarditis samples showed increased t-tubule distance (1.27 +/- 0.05 mu m, n = 34 cells) and dilation of t-tubules (volume-length ratio: 0.64 +/- 0.02 mu m(2)) when compared with AVSD (0.90 +/- 0.02 mu m, p < 0.001; 0.52 +/- 0.02 mu m(2), n = 61, p < 0.01). Intriguingly, 4 out of 5 myocarditis samples exhibited sheet-like t-tubules (t-sheets), a characteristic feature of adult chronic heart failure. The fraction of extracellular matrix was slightly higher in myocarditis (26.6 +/- 1.4%) than in AVSD samples (24.4 +/- 0.8%, p < 0.05). In one case of myocarditis, a second biopsy was taken and analyzed at VAD explantation after extensive cardiac recovery (EF from 7 to 56%) and clinical remission. When compared with pre-VAD, t-tubule distance and density were unchanged, as well as volume-length ratio (0.67 +/- 0.04 mu m(2) vs. 0.72 +/- 0.05 mu m(2), p = 0.5), reflecting extant t-sheets. However, junctophilin-2 cluster density was considerably higher (0.12 +/- 0.02 mu m(-3) vs. 0.05 +/- 0.01 mu m(-3), n = 9/10, p < 0.001), approaching values of AVSD (0.13 +/- 0.05 mu m(-3), n = 56), and the measure of intact EC coupling junctions showed a distinct increase (20.2 +/- 5.0% vs. 6.8 +/- 2.2%, p < 0.001). Severe t-system loss and remodeling to t-sheets can occur in acute HF in young children, resembling the structural changes of chronically failing adult hearts. T-system remodeling might contribute to cardiac dysfunction in viral myocarditis. Although t-system recovery remains elusive, recovery of EC coupling junctions may be possible and deserves further investigation.
CRIS-Team WoS Importer:2021-02-19

Shedding light on pediatric diseases: multispectral optoacoustic tomography at the doorway to clinical applications. - Regensburger, Adrian; Wagner, Alexandra; Claussen, Jing; Waldner, Maximilian; Knieling, Ferdinand (Molecular and Cellular Pediatrics, 2020)
Optoacoustic imaging (OAI), or photoacoustic imaging (PAI), has fundamentally influenced basic science by providing high-resolution visualization of biological mechanisms. With the introduction of multispectral optoacoustic tomography (MSOT), these technologies have now moved closer to clinical applications. MSOT utilizes short-pulsed near-infrared laser light to induce thermoelastic expansion in targeted tissues. This results in acoustic pressure waves, which are used to resolve specific endo- and exogenous chromophores. Especially in the pediatric population, this non-invasive imaging approach might hold fundamental advantages compared to conventional cross-sectional imaging modalities. As this technology allows the visualization of quantitative molecular tissue composition at high spatial resolution non-invasively in sufficient penetration depth, it paves the way to personalized medicine in pediatric diseases.
EVALuna2:383218

Similar Inhibition of Dynamic Adhesion of Lymphocytes From IBD Patients to MAdCAM-1 by Vedolizumab and Etrolizumab-s - Binder, Marie-Theres; Becker, Emily; Wiendl, Maximilian; Schleier, Lena; Fuchs, Florian; Leppkes, Moritz; Atreya, Raja; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Inflammatory Bowel Diseases, 2018)
Background: Although anti-adhesion therapies are a novel mainstay in the treatment of inflammatory bowel diseases (IBDs), the mechanisms controlling integrin-dependent gut homing are poorly elucidated, and the available techniques for translational functional investigations are limited. Methods: We used dynamic adhesion assays to study adhesion of CD4+ T cells, CD8+ T cells, CD19+ B cells, and granulocytes to the addressins MAdCAM-1, VCAM-1, and ICAM-1. The effects of vedolizumab, natalizumab, etrolizumab-s, anti-CD11a, and anti-CD18 antibodies were explored. Results: Adhesion of peripheral blood leukocytes from IBD patients and control donors could be validly assessed, and integrin-mediated addressin adhesion could be specifically inhibited by anti-integrin antibodies. Numbers of adhering cells were partly, but not completely, related to integrin expression. Vedolizumab and etrolizumab-s resulted in similar reduction of adhesion to MAdCAM-1, and preliminary data proposed an association of dynamic adhesion to MAdCAM-1 with response to vedolizumab therapy. Conclusions: Dynamic adhesion assays are an easy and broadly applicable method for IBD research that is useful for future translational studies and potentially also for supporting clinical treatment decisions. 10.1093/ibd/izy077_video1izy077_Video_15786486962001.
EVALuna2:35167

Six-Color Confocal Immunofluorescence Microscopy with 4-Laser Lines - Heger, Lukas; Lühr, Jennifer J.; Amon, Lukas; Smith, Ana-Suncana; Eissing, Nathalie; Dudziak, Diana (Methods in Molecular Biology, 2021)
Confocal immunofluorescence microscopy is an advanced imaging technique routinely applied in the laboratory and clinics. Histological analyses are performed from tissue material. In general, a single fluorochrome per laser is employed, limiting simultaneous analysis to four antigens in one staining with a conventional 4-laser line microscope. Here, we describe a protocol for combining fluorochromes with the same excitation but different emission properties that allows for the analysis of six different antigens in confocal immunofluorescence microscopy with a conventional 4-laser line microscope. The proposed multiplexed method permits the identification and characterization of complex cell populations in rare tissue material.
CRIS-Team Scopus Importer:2021-10-01
Keywords: DC; Dendritic cells; Fluorochrome; Histology; Multicolor imaging; Tissue

SMYD2 targets RIPK1 and restricts TNF-induced apoptosis and necroptosis to support colon tumor growth - Yu, Yidong; Thonn, Veronika; Patankar, Jay; Thoma, Oana-Maria; Waldner, Maximilian; Zielinska, Marta; Bao, Lili; Gonzalez Acera, Miguel; Wallmueller, Stefan; Engel, Felix; Stürzl, Michael; Neurath, Markus; et al. (Cell Death & Disease, 2022)
SMYD2 is a histone methyltransferase, which methylates both histone H3K4 as well as a number of non-histone proteins. Dysregulation of SMYD2 has been associated with several diseases including cancer. In the present study, we investigated whether and how SMYD2 might contribute to colorectal cancer. Increased expression levels of SMYD2 were detected in human and murine colon tumor tissues compared to tumor-free tissues. SMYD2 deficiency in colonic tumor cells strongly decreased tumor growth in two independent experimental cancer models. On a molecular level, SMYD2 deficiency sensitized colonic tumor cells to TNF-induced apoptosis and necroptosis without affecting cell proliferation. Moreover, we found that SMYD2 targeted RIPK1 and inhibited the phosphorylation of RIPK1. Finally, in a translational approach, pharmacological inhibition of SMYD2 attenuated colonic tumor growth. Collectively, our data show that SMYD2 is crucial for colon tumor growth and inhibits TNF-induced apoptosis and necroptosis.
CRIS-Team WoS Importer:2022-01-21

Soluble CD83 improves and accelerates wound healing by the induction of pro-resolving macrophages - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; König, Christina; Wild, Andreas; Tauchi, Miyuki; Ostalecki, Christian; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, Sabine A.; Fuchs, Maximilian; et al. (Frontiers in Immunology, 2022)
To facilitate the recovery process of chronic and hard-to-heal wounds novel pro-resolving treatment options are urgently needed. We investigated the pro-regenerative properties of soluble CD83 (sCD83) on cutaneous wound healing, where sCD83 accelerated wound healing not only after systemic but also after topical application, which is of high therapeutic interest. Cytokine profile analyses revealed an initial upregulation of inflammatory mediators such as TNFα and IL-1β, followed by a switch towards pro-resolving factors, including YM-1 and IL-10, both expressed by tissue repair macrophages. These cells are known to mediate resolution of inflammation and stimulate wound healing processes by secretion of growth factors such as epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF), which promote vascularization as well as fibroblast and keratinocyte differentiation. In conclusion, we have found strong wound healing capacities of sCD83 beyond the previously described role in transplantation and autoimmunity. This makes sCD83 a promising candidate for the treatment of chronic- and hard-to-heal wounds.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD83; macrophages; stem cells; therapy; tissue regeneration; wound healing

Soluble intercellular adhesion molecule-1 is a prognostic marker in colorectal carcinoma - Schellerer, Vera; Langheinrich, Melanie C.; Zver, Veronika; Grützmann, Robert; Stürzl, Michael; Gefeller, Olaf; Naschberger, Elisabeth; Merkel, Susanne (International Journal of Colorectal Disease, 2019)
PurposeSerological tumor markers are routinely used to monitor tumor onset and progression. In colorectal carcinoma (CRC), the carcinoembryonic antigen (CEA) is roughly elevated in 50% of patients at initial diagnosis. Soluble ICAM-1 (sICAM-1) is elevated in different cancers. The aim of this study was to evaluate the prognostic relevance of sICAM-1 combined with CEA in patients with CRC.MethodsIn blood samples of 297 CRC patients, sICAM-1 was determined by ELISA and CEA by microparticle enzyme immunoassay the day before oncologic resection. Separation in patients with sICAM-1(high) and sICAM-1(low) was performed by minimum p value approach; separation in CEA normal and elevated was performed according to the established diagnostic cutoff. Clinical data were obtained from the prospective collected data from the Erlangen Registry for Colorectal Carcinomas.ResultsCancer-related 5-year survival rate of patients with sICAM-1(low) (<290ng/ml, n=208) was significantly increased (83.4%) as compared to that of patients with sICAM-1(high) (290ng/ml, n=89) (66.2%; p<0.001). Patients with normal CEA concentrations (n=199; 90.8%) showed a significantly (p<0.001) improved cancer-related 5-year survival rate compared to patients with elevated CEA concentrations (n=98; 52.1%). Moreover, high sICAM-1 was an independent risk factor (hazard ratio 1.6) in multivariate analysis. Of note, increased sICAM-1 levels, either within normal or within elevated CEA, allowed to identify high-risk subgroups, both for overall (p<0.001) and cancer-related survival (p<0.001).ConclusionApplication of a novel risk score combining CEA/sICAM-1 serum concentrations allows the identification of high-risk groups for poor survival in CRC patients.
CRIS-Team WoS Importer:2019-02-21

SoxC transcription factors: multifunctional regulators of neurodevelopment - Kavyanifar, Atria; Turan, Sören; Lie, Dieter Chichung (Cell and Tissue Research, 2018)
During development, generation of neurons is coordinated by the sequential activation of gene expression programs by stage- and subtype-specific transcription factor networks. The SoxC group transcription factors, Sox4 and Sox11, have recently emerged as critical components of this network. Initially identified as survival and differentiation factors for neural precursors, SoxC factors have now been linked to a broader array of developmental processes including neuronal subtype specification, migration, dendritogenesis and establishment of neuronal projections, and are now being employed in experimental strategies for neuronal replacement and axonal regeneration in the diseased central nervous system. This review summarizes the current knowledge regarding SoxC factor function in CNS development and disease and their promise for regeneration.
EVALuna2:34133

SoxE factors: Transcriptional regulators of neural differentiation and nervous system development. - Weider, Matthias; Wegner, Michael (Seminars in Cell & Developmental Biology, 2017)
Sox8, Sox9 and Sox10 represent the three vertebrate members of the SoxE subclass of high-mobility-group domain containing Sox transcription factors. They play important roles in the peripheral and central nervous systems as regulators of stemness, specification, survival, lineage progression, glial differentiation and homeostasis. Functions are frequently overlapping, but sometimes antagonistic. SoxE proteins dynamically interact with transcriptional regulators, chromatin changing complexes and components of the transcriptional machinery. By establishing regulatory circuits with other transcription factors and microRNAs, SoxE proteins perform divergent functions in several cell lineages of the vertebrate nervous system, and at different developmental stages in the same cell lineage. The underlying molecular mechanisms are the topic of this review.<br
EVALuna2:33486
Keywords: Brain; Glia; Neural crest; Oligodendrocyte; Schwann cell; Transcriptional network

Species-, organ- and cell-type-dependent expression of SPARCL1 in human and mouse tissues. - Klingler, Anika; Regensburger, Daniela; Tenkerian, Clara; Britzen-Laurent, Nathalie; Hartmann, Arndt; Stürzl, Michael; Naschberger, Elisabeth (PLoS ONE, 2020)
SPARCL1 is a matricellular protein with anti-adhesive, anti-proliferative and anti-tumorigenic functions and is frequently downregulated in tumors such as colorectal carcinoma or non-small cell lung cancer. Studies have identified SPARCL1 as an angiocrine tumor suppressor secreted by tumor vessel endothelial cells, thereby exerting inhibitory activity on angiogenesis and tumor growth, in colorectal carcinoma. It is unknown whether SPARCL1 may exert these homeostatic functions in all organs and in other species. Therefore, SPARCL1 expression was comparatively analysed between humans and mice in a systematic manner. Murine Sparcl1 (mSparcl1) is most strongly expressed in the lung; expressed at an intermediate level in most organs, including the large intestine; and absent in the liver. In human tissues, SPARCL1 (hSPARCL1) was detected in all organs, with the strongest expression in the stomach, large intestine and lung, mostly consistent with the murine expression pattern. A striking difference between human and murine tissues was the absence of mSparcl1 expression in murine livers, while human livers showed moderate expression. Furthermore, mSparcl1 was predominantly associated with mural cells, whereas hSPARCL1 was detected in both mural and endothelial cells. Human SPARCL1 expression was downregulated in different carcinomas, including lung and colon cancers. In conclusion, this study revealed species-, organ- and cell-type-dependent expression of SPARCL1, suggesting that its function may not be similar between humans and mice.

Sphingolipid control of cognitive functions in health and disease - Kalinichenko, Liubov; Gulbins, Erich; Kornhuber, Johannes; Müller, Christian P. (Progress in Lipid Research, 2022)
Cognitive processes, particularly learning and memory, are crucial brain mechanisms mediating the successful adaptation of individuals to constantly changing environmental conditions. Impairments in memory performance during neurodegenerative disorders or dementias affect life quality of patients as well as their relatives and careers, and thus have a severe socio-economic impact. The last decades have viewed learning and memory as predominantly protein-mediated process at the synapses of brain neurons. However, recent developments propose a principally new, lipid-based mechanism that regulates cognition. Thereby, crucial members of cell membranes, the sphingolipids, emerged to play an outstanding role in learning and memory. The most abundant brain sphingolipids, ceramides and gangliosides, dynamically shape the composition of protein carrying cellular membranes. This, in turn, regulates protein signaling through the membranes and overall neuronal plasticity. An imbalance in sphingolipid composition and disrupted dynamics significantly affect normal functioning of cells and results in the development of multiple psychiatric and neurological disorders with cognitive impairments. Ceramides and gangliosides interact with a plethora of molecular pathways determining de novo learning and memory, as well as pathogenic pathways of neurodegenerative disorders and dementias of various origins. Considering sphingolipids as a trigger mechanism for learning and memory under physiological and pathological conditions, a principally new class of lipid-based preventive and therapeutic approaches to target cognitive impairments and dementias is emerging.
CRIS-Team Scopus Importer:2022-04-29

Spontaneous activity of specific C-nociceptor subtypes from diabetic patients and mice: Involvement of reactive dicarbonyl compounds and (sensitized) transient receptor potential channel A1 - Becker, Anna; Babes, Alexandru; Düll, Miriam; Khalil, Mohammad; Kender, Zoltan; Gröner, Jan; Namer, Barbara; Reeh, Peter; Sauer, Susanne (Journal of the Peripheral Nervous System, 2023)
Background: Diabetic metabolism causes changes of the chemical milieu including accumulation of reactive carbonyl species, for example, methylglyoxal (MGO). MGO activates chemosensitive TRPA1 on nociceptors, but the contribution to neuronal pathophysiology causing pain and hyperalgesia in diabetic neuropathy is not fully understood. Methods: We employed single-nerve-fiber recordings in type 2 diabetes patients with (spDN) and without cutaneous pain (DN) and in streptozotocin-diabetic and healthy mice. In mice, we measured Ca++ transients in cultured DRG neurons and stimulated CGRP release from hairy skin. Results: In diabetic patients, we recorded a large proportion of pathologically altered nerve C-fibers (79%). In spDN patients we found a higher percentage (72%) of spontaneously active C-nociceptors than in DN patients (15%). The proportion of spontaneous activity was highest among pathological fibers with mechanoinsensitive fiber properties which are particularly sensitive to MGO in contrast to mechanosensitive fibers. Mouse polymodal nociceptors, in contrast to purely mechanosensitive C-fibers, showed highest prevalence of TRPA1-related chemosensitivity. In diabetic mice about 37% of polymodal nociceptors developed spontaneous activity and exhibited significantly greater MGO responses, indicating sensitized TRPA1 receptors. Low-threshold mechanosensitive Aδ-fibers were vigorously activated by MGO but independently of TRPA1 activation. Interpretation: Our translational findings suggest that TRPA1-expressing C-nociceptors, which in human correspond to mechanoinsensitive and in mice to polymodal nociceptors, are especially vulnerable to develop spontaneous activity. Those two different nociceptor classes might share the functional role as dicarbonyl-sensitive chemosensors and represent the critical nociceptor population that support the development of pain and hyperalgesia in diabetic neuropathy.
CRIS-Team Scopus Importer:2023-05-19
Keywords: calcitonin gene-related peptide; cutaneous nociceptor; excitability; mechanoinsensitive C-fiber; methylglyoxal; microneurography; neuropathic pain

Sporadic Parkinson's disease derived neuronal cells show disease-specific mRNA and small RNA signatures with abundant deregulation of piRNAs - Schulze, Markus; Sommer, Annika; Plotz, Sonja; Farrell, Michaela; Winner, Beate; Grosch, Janina; Winkler, Jürgen; Riemenschneider, Markus J. (Acta Neuropathologica Communications, 2018)
Differentiated neurons established via iPSCs from patients that suffer from familial Parkinson's disease (PD) have allowed insights into the mechanisms of neurodegeneration. In the larger cohort of patients with sporadic PD, iPSC based information on disease specific cellular phenotypes is rare. We asked whether differences may be present on genomic and epigenomic levels and performed a comprehensive transcriptomic and epigenomic analysis of fibroblasts, iPSCs and differentiated neuronal cells of sporadic PD-patients and controls. We found that on mRNA level, although fibroblasts and iPSCs are largely indistinguishable, differentiated neuronal cells of sporadic PD patients show significant alterations enriched in pathways known to be involved in disease aetiology, like the CREB-pathway and the pathway regulating PGC1a. Moreover, miRNAs and piRNAs/piRNA-like molecules are largely differentially regulated in cells and post-mortem tissue samples between control-and PD-patients. The most striking differences can be found in piRNAs/piRNA-like molecules, with SINE-and LINE-derived piRNAs highly downregulated in a disease specific manner. We conclude that neuronal cells derived from sporadic PD-patients help to elucidate novel disease mechanisms and provide relevant insight into the epigenetic landscape of sporadic Parkinson's disease as particularly regulated by small RNAs.
EVALuna2:35781

STAT2 Controls Colorectal Tumorigenesis and Resistance to Anti-Cancer Drugs - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Becker, Christoph; Neurath, Markus (Cancers, 2023)
Colorectal cancer (CRC) is a significant socioeconomic burden in modern society and is accountable for millions of premature deaths each year. The role of signal transducer and activator of transcription 2 (STAT2)-dependent signaling in this context is not yet fully understood, and no therapies targeting this pathway are currently being pursued. We investigated the role of STAT2 in CRC using experimental mouse models coupled with RNA-sequencing (RNA-Seq) data and functional assays with anti-cancer agents in three-dimensional tumoroids. Stat2−/− mice showed greater resistance to the development of CRC in both inflammation-driven and inflammation-independent experimental CRC models. In ex vivo studies, tumoroids derived from Stat2−/− mice with the multiple intestinal neoplasia (Min) mutant allele of the adenomatous polyposis coli (Apc) locus exhibited delayed growth, were overall smaller and more differentiated as compared with tumoroids from ApcMin/+ wildtype (WT) mice. Notably, tumoroids from ApcMin/+ Stat2−/− mice were more susceptible to anti-cancer agents inducing cell death by different mechanisms. Our findings clearly indicated that STAT2 promotes CRC and suggested that interventions targeting STAT2-dependent signals might become an attractive therapeutic option for patients with CRC.
CRIS-Team Scopus Importer:2023-12-15
Keywords: anti-cancer therapy; Apc; colorectal cancer mouse model; STAT2; tumoroid

Store-operated calcium entry is reduced in spastin-linked hereditary spastic paraplegia - Winner, Beate; Rizo Garza, Tania; Gebhardt, Lisa; Riedlberger, Julia; Eberhardt, Esther; Fester, Lars; Alansary, Dalia; Winkler, Jürgen; Turan, Sören; Arnold, Philipp; Niemeyer, Barbara; Fischer, Michael (2022)
Pathogenic variants in SPAST, the gene coding for spastin, are the single most common cause of hereditary spastic paraplegia, a progressive motor neuron disease. Spastin regulates key cellular functions, including microtubule-severing and endoplasmic reticulum-morphogenesis. However, it remains unclear how alterations in these cellular functions due to SPAST pathogenic variants result in motor neuron dysfunction. Since spastin influences both microtubule network and endoplasmic reticulum structure, we hypothesized that spastin is necessary for the regulation of Ca2+ homeostasis via store-operated calcium entry. Here, we show that the lack of spastin enlarges the endoplasmic reticulum and reduces store-operated calcium entry. In addition, elevated levels of different spastin variants induced clustering of STIM1 within the endoplasmic reticulum, altered the transport of STIM1 to the plasma membrane and reduced store-operated calcium entry, which could be rescued by exogenous expression of STIM1. Importantly, store-operated calcium entry was strongly reduced in induced pluripotent stem cell-derived neurons from hereditary spastic paraplegia patients with pathogenic variants in SPAST resulting in spastin haploinsufficiency. These neurons developed axonal swellings in response to lack of spastin. We were able to rescue both store-operated calcium entry and axonal swellings in SPAST patient neurons by restoring spastin levels, using CRISPR/Cas9 to correct the pathogenic variants in SPAST. These findings demonstrate that proper amounts of spastin are a key regulatory component for store-operated calcium entry mediated Ca2+ homeostasis and suggest store-operated calcium entry as a disease relevant mechanism of spastin-linked motor neuron disease.Rizo et al. use iPSC-derived neurons from patients to investigate how pathogenic variants in SPAST give rise to hereditary spastic paraplegia. They show that dysregulation of spastin, a microtubule- and ER-remodelling protein encoded by SPAST, alters the dynamics of the ER, resulting in aberrant Ca2+ regulation.
Keywords: spastin; STIM1; microtubules; endoplasmic reticulum; store-operated calcium entry

Stunning of neutrophils accounts for the anti-inflammatory effects of clodronate liposomes - Culemann, Stephan; Knab, Katharina; Euler, Maximilien; Wegner, Anja; Garibagaoglu, Hilal; Ackermann, Jochen; Fischer, Kim; Kienhoefer, Deborah; Crainiciuc, Georgiana; Hahn, Jonas; Grüneboom, Anika; Nimmerjahn, Falk; et al. (Journal of Experimental Medicine, 2023)
The authors show that the anti-inflammatory effects of clodronate liposomes do not result from the depletion of mononuclear phagocytes but from a functional stunning of polymorphonuclear neutrophils. These findings necessitate a critical revision of the current literature on the role of monocytes and macrophages in inflammation.
CRIS-Team WoS Importer:2023-04-28

Subsets of CD1c+ DCs: Dendritic Cell Versus Monocyte Lineage - Heger, Lukas; Hofer, Thomas P.; Bigley, Venetia; de Vries, I. Jolanda M.; Dalod, Marc; Dudziak, Diana; Ziegler-Heitbrock, Loems (Frontiers in Immunology, 2020)
Currently three bona fide dendritic cell (DC) types are distinguished in human blood. Herein we focus on type 2 DCs (DC2s) and compare the three defining markers CD1c, CD172, and CD301. When using CD1c to define DC2s, a CD14+ and a CD14− subset can be detected. The CD14+ subset shares features with monocytes, and this includes substantially higher expression levels for CD64, CD115, CD163, and S100A8/9. We review the current knowledge of these CD1c+CD14+ cells as compared to the CD1c+CD14− cells with respect to phenotype, function, transcriptomics, and ontogeny. Here, we discuss informative mutations, which suggest that two populations have different developmental requirements. In addition, we cover subsets of CD11c+CD8− DC2s in the mouse, where CLEC12A+ESAMlow cells, as compared to the CLEC12A−ESAMhigh subset, also express higher levels of monocyte-associated markers CD14, CD3, and CD115. Finally, we summarize, for both man and mouse, the data on lower antigen presentation and higher cytokine production in the monocyte-marker expressing DC2 subset, which demonstrate that the DC2 subsets are also functionally distinct.
CRIS-Team Scopus Importer:2020-10-30
Keywords: CD14; CD172; CD1c; CD301; DC subsets; DC2; dendritic cells

Sulfasalazine impacts on ferroptotic cell death and alleviates the tumor microenvironment and glioma-induced brain edema. - Sehm, Tina; Fan, Zheng; Ghoochani, Ali; Rauh, Manfred; Engelhorn, Tobias; Minakaki, Georgia; Dörfler, Arnd; Klucken, Jochen; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai (Oncotarget, 2016)
The glutamate transporter xCT (SCL7a11, system Xc-, SXC) is an emerging key player in glutamate/cysteine/glutathione homeostasis in the brain and in cancer. xCT expression correlates with the grade of malignancy. Here, we report on the use of the U.S. Food and Drug Administration and EMA-approved xCT inhibitor, sulfasalazine (SAS) in gliomas. SAS does not affect cell viability in gliomas at concentrations below 200 µM. At higher concentrations SAS becomes gliomatoxic. Mechanistically SAS inhibits xCT and induces ferroptotic cell death in glioma cells. There is no evidence for impact on autophagic flux following SAS application. However, SAS can potentiate the efficacy of the standard chemotherapeutic and autophagy-inducing agent temozolomide (Temcat, Temodal or Temodar®). We also investigated SAS in non-transformed cellular constituents of the brain. Neurons and brain tissue are almost non-responding to SAS whereas isolated astrocytes are less sensitive towards SAS toxicity compared to gliomas. In vivo SAS treatment does not affect experimental tumor growth and treated animals revealed comparable tumor volume as untreated controls. However, SAS treatment resulted in reduced glioma-derived edema and, hence, total tumor volume burden as revealed by T2-weighted magnetic resonance imaging. Altogether, we show that SAS can be utilized for targeting the glutamate antiporter xCT activity as a tumor microenvironment-normalizing drug, while crucial cytotoxic effects in brain tumors are minor.

Sulforaphane inhibits growth and blocks Wnt/β-catenin signaling of colorectal cancer cells - Bernkopf, Dominic; Daum, Gabriele; Brückner, Martina; Behrens, Jürgen (Oncotarget, 2018)
The naturally occurring isothiocyanate sulforaphane (SFN) from cruciferous vegetables is associated with growth inhibition of various cancer types, including colorectal cancer. Colorectal cancer is most frequently driven by hyperactive Wnt/β-catenin signaling. Here, we show that SFN treatment reduced growth of three unrelated colorectal cancer cell lines (SW480, DLD1 and HCT116) via induction of cell death and inhibition of proliferation. Importantly, SFN inhibits Wnt/β-catenin signaling in colorectal cancer cells as shown by inhibition of β-catenin-dependent luciferase reporters and repression of β-catenin target genes (AXIN2, LGR5). SFN inhibits Wnt signaling downstream of β-catenin degradation and induces the formation of nuclear β-catenin structures associated with closed chromatin. Co-expression of the transcription factors LEF1 or TCF4 prevented formation of these structures and rescued inhibition of Wnt/β-catenin signaling by SFN. Our findings provide a molecular basis explaining SFN effects in colorectal cancer cells and underline its potential for prevention and therapy of colorectal cancer.
EVALuna2:34943

SUMOylation of IE2p86 is required for efficient autorepression of the human cytomegalovirus major immediate-early promoter - Reuter, Nina; Reichel, Anna; Stilp, Anne-Charlotte; Scherer, Myriam; Stamminger, Thomas (Journal of General Virology, 2018)
The human cytomegalovirus (HCMV) IE2p86 protein is pivotal for coordinated regulation of viral gene expression. Besides functioning as a promiscuous transactivator, IE2p86 is also known to negatively regulate its own transcription. This occurs via direct binding of IE2p86 to a 14-bp palindromic DNA element located between the TATA box and the transcription start site of the major immediate-early promoter (MIEP), which is referred to as the cis repression signal (CRS). However, the exact mechanism of IE2p86-based autorepression is still unclear. By testing a series of IE2p86 mutants in transient expression assays, we found that not only did a DNA binding-deficient mutant of IE2p86 fail to repress the MIEP, but SUMOylation-negative mutants also failed to repress it. This finding was further supported by infection studies with primary fibroblasts harbouring a MIEP-driven transgene as a reporter. Here, we observed that a recombinant HCMV expressing SUMOylation-negative IE2p86 was defective in transgene downregulation, in contrast to wild-type HCMV. Interestingly, however, a double-mutant virus in which both the SUMO acceptor sites and the SUMO interaction motif (SIM) of IE2p86 were inactivated regained the ability to silence the MIEP. This correlated with increased expression levels of the IE2 isoforms IE2p40 and IE2p60, suggesting that these late proteins may contribute to MIEP suppression, thus compensating for the loss of IE2p86 SUMOylation. In summary, our results show that autorepression of the MIEP is not only regulated by late isoforms of IE2, but also depends on posttranslational SUMO modification, revealing a novel mechanism to fine-tune the expression of this important viral gene region.
EVALuna2:35286

Sweet SIGNs: IgG glycosylation leads the way in IVIG-mediated resolution of inflammation - Brückner, Christin; Lehmann, Christian; Dudziak, Diana; Nimmerjahn, Falk (International Immunology, 2017)
A hallmark of many chronic inflammatory and autoimmune diseases is that there is an impaired resolution of inflammation and return to the steady state. The infusion of high doses of pooled serum IgG preparations from thousands of donors [intravenous immunoglobulin (IVIG) therapy] has been shown to induce resolution of inflammation in a variety of chronic inflammatory and autoimmune diseases, suggesting that IgG molecules can instruct the immune system to stop inflammatory processes and initiate the return to the steady state. The aim of this review is to discuss how insights into the mechanism of IVIG activity may help to understand the molecular and cellular pathways underlying resolution of inflammation. We will put a special emphasis on pathways dependent on the IgG FC domain and IgG sialylation, as several recent studies have provided new insights into how this glycosylation-dependent pathway modulates innate and adaptive immune responses through different sets of C-type or I-type lectins.
EVALuna2:34371

Swiprosin-1/ EFhd2: from Immune Regulator to Personality and Brain Disorders - Kogias, Georgios; Kornhuber, Johannes; Reimer, Dorothea; Mielenz, Dirk; Müller, Christian P. (Neurosignals, 2019)
BACKGROUND/AIMS: Swiprosin-1/ EF-hand domain 2 (EFhd2) is a Ca2+ sensor protein that plays an important role in the immune system. Its abundant expression in the brain, however, suggested also a role in neuronal circuits and behavior. METHODS: Here we review recent discoveries on the structure and molecular function, its role in immunity and its function in the brain regarding behavioral control and pathologies. RESULTS: While EFhd2 did not emerge as a vital protein for brain development, changes in its expression may nevertheless shape the adult behavioral repertoire significantly and contribute to adult personality traits. A defective function of EFhd2 may also render individuals more prone to the development of psychiatric disorders. Most prominently, EFhd2 proved to be a resilience factor protecting from fast establishment of drug addiction. Moreover, EFhd2 is critical for adult neurogenesis and as a modulator of monoaminergic systems. CONCLUSION: Dysregulated activity of EFhd2 is increasingly considered as a contributing factor for the development of numerous neurodegenerative disorders. Whether EFhd2 can be used as biomarker or in therapeutic approaches has to be addressed in future research.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Swiprosin-1; EFhd2; Immunity; Personality; Neurogenesis; Dopamine; Addiction; Neurodegenerative disorders

Swiprosin1/EFhd2 is involved in the monoaminergic and locomotor responses of psychostimulant drugs - Kogias, Georgios; Zheng, Fang; Kalinichenko, Liubov; Kornhuber, Johannes; Alzheimer, Christian; Mielenz, Dirk; Müller, Christian P. (Journal of Neurochemistry, 2020)
Psychostimulants are widely abused drugs that may cause addiction in vulnerable individuals. While the reward circuitry of the brain is involved in addiction establishment, various pathways in the brain may provide protection at the molecular level that limits the acute and chronic effects of drugs. These targets may be used for strategies designed to prevent and treat addiction. Swiprosin-1/EF hand domain 2 (EFhd2) is a Ca2+-binding cytoskeletal adaptor protein involved in sensation-seeking behaviour, anxiety and alcohol addiction. Here, we tested how EFhd2 contributes to the physiological and behavioural effects of the psychostimulant drugs methamphetamine (METH) and cocaine. An in vivo microdialysis study in EFhd2 knockout mice revealed that EFhd2 controls METH- and cocaine-induced changes in extracellular dopamine, serotonin and noradrenaline levels through different mechanisms in the nucleus accumbens and prefrontal cortex. Electrophysiological recordings in a slice preparation showed that a lack of EFhd2 increases dopaminergic neuronal activity in the ventral tegmental area and increases the sensitivity of neurons to stimulation. We report a role of EFhd2 in METH-induced locomotor activation and in the conditioned locomotor effects. No role, however, was observed in the establishment of METH- or cocaine-induced conditioned place preference. These findings may suggest that EFhd2 modulates the activity of the dopaminergic system and the neurochemical effects of METH and cocaine, which translate into a modulation of the behavioural effects of these drugs at the level of the acute and conditioned locomotor activity. (Figure presented.).
CRIS-Team Scopus Importer:2020-02-14
Keywords: cocaine; dopamine; EFhd2; methamphetamine; noradrenaline; serotonin; Swiprosin-1

Systematic data analysis and data mining in CatWalk gait analysis by heat mapping exemplified in rodent models for neurodegenerative diseases - Timotius, Ivanna; Canneva, Fabio; Minakaki, Georgia; Moceri, Sandra; Plank, Anne-Christine; Casadei, Nicolas; Riess, Olaf; Winkler, Jürgen; Klucken, Jochen; Eskofier, Björn; von Hörsten, Stephan (Journal of Neuroscience Methods, 2019)
Background Motor impairment appears as a characteristic symptom of several diseases and injuries. Therefore, tests for analyzing motor dysfunction are widely applied across preclinical models and disease stages. Among those, gait analysis tests are commonly used, but they generate a huge number of gait parameters. Thus, complications in data analysis and reporting raise, which often leads to premature parameter selection. New methods In order to avoid arbitrary parameter selection, we present here a systematic initial data analysis by utilizing heat-maps for data reporting. We exemplified this approach within an intervention study, as well as applied it to two longitudinal studies in rodent models related to Parkinson’s disease (PD) and Huntington disease (HD). Results The systematic initial data analysis (IDA) is feasible for exploring gait parameters, both in experimental and longitudinal studies. The resulting heat maps provided a visualization of gait parameters within a single chart, highlighting important clusters of differences. Comparison with existing method Often, premature parameter selection is practiced, lacking comprehensiveness. Researchers often use multiple separated graphs on distinct gait parameters for reporting. Additionally, negative results are often not reported. Conclusions Heat mapping utilized in initial data analysis is advantageous for reporting clustered gait parameter differences in one single chart and improves data mining.
Keywords: Gait analysis; CatWalk system; Heat map; Parkinson’s disease; Huntington disease; Rodent models

Targeted inhibition of the WEE1 kinase as a novel therapeutic strategy in neuroendocrine neoplasms - Weindl, Lena; Atreya, Imke; Dietrich, Peter; Neubeck, Sabine; Neurath, Markus; Pavel, Marianne Ellen (Endocrine-Related Cancer, 2021)
Neuroendocrine neoplasms (NENs) represent a rare and heterogeneous group of malignancies, sharing features of both neural and endocrine cells. NENs G3 appear as a highly aggressive subset with a poor prognosis and limited therapeutic options. The small-molecule inhibitor of the WEE1 tyrosine kinase, adavosertib (AZD1775), has previously demonstrated potent anti-tumor effects on various types of cancer in preclinical and clinical studies. However, the role of adavosertib in NENs G3 had remained elusive. We evaluated the effects of adavosertib on pancreatic (BON-1, QGP-1) and bronchopulmonary (NCI-H720) neuroendocrine tumor cell lines applying 2D and 3D spheroid models. We newly demonstrated that adavosertib is sufficient to reduce cell viability and proliferation in neuroendocrine cell lines with features of high-grade NENs. As underlying mechanisms, we identified adavosertib-mediated DNA double-strand breaks and a G2/M cell cycle checkpoint abrogation leading into mitotic catastrophe and cancer cell apoptosis. Silencing of WEE1 via siRNA transfection resulted in a phenotype similar to adavosertib treatment. Together, inhibition of the WEE1 tyrosine kinase applying adavosertib on NENs G3 outlines a promising novel therapeutic strategy.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D cell culture; Cell cycle; G3; Neuroendocrine neoplasm; WEE1

Targeting Immune Cell Trafficking – Insights From Research Models and Implications for Future IBD Therapy - Wiendl, Maximilian; Becker, Elisabeth; Müller, Tanja; Voskens, Caroline; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2021)
Inflammatory bowel diseases (IBDs), including Crohn’s disease (CD) and ulcerative colitis (UC) are multifactorial diseases with still unknown aetiology and an increasing prevalence and incidence worldwide. Despite plentiful therapeutic options for IBDs, the lack or loss of response in certain patients demands the development of further treatments to tackle this unmet medical need. In recent years, the success of the anti-α4β7 antibody vedolizumab highlighted the potential of targeting the homing of immune cells, which is now an important pillar of IBD therapy. Due to its complexity, leukocyte trafficking and the involved molecules offer a largely untapped resource for a plethora of potential therapeutic interventions. In this review, we aim to summarise current and future directions of specifically interfering with immune cell trafficking. We will comment on concepts of homing, retention and recirculation and particularly focus on the role of tissue-derived chemokines. Moreover, we will give an overview of the mode of action of drugs currently in use or still in the pipeline, highlighting their mechanisms and potential to reduce disease burden.
CRIS-Team Scopus Importer:2021-06-04
Keywords: homing; IBD; retention; T cell; therapy; trafficking

Targeting Immune Cell Wiring in Ulcerative Colitis - Neurath, Markus; Chiriac, Mircea T. (Immunity, 2019)
The cytokine TNF is thought to play a major role in the immunopathogenesis of ulcerative colitis, and anti-TNF antibodies are considered as cornerstones of clinical therapy. Two clinical trials published in The New England Journal of Medicine now challenge this paradigm and suggest new avenues for research. The cytokine TNF is thought to play a major role in the immunopathogenesis of ulcerative colitis, and anti-TNF antibodies are considered as cornerstones of clinical therapy. Two clinical trials published in The New England Journal of Medicine now challenge this paradigm and suggest new avenues for research.
CRIS-Team Scopus Importer:2019-11-19

Targeting Muscular Hemoglobin Content for Classification of Peripheral Arterial Disease by Noninvasive Multispectral Optoacoustic Tomography - Günther, Josefine; Knieling, Ferdinand; Träger, Anna P.; Lang, Werner; Meyer, Alexander; Regensburger, Adrian; Wagner, Alexandra; Trollmann, Regina; Wölfle, Joachim; Klett, Daniel; Uter, Wolfgang; Uder, Michael; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2023)
Created from Fastlane, Scopus look-up

Targeting of canonical WNT signaling ameliorates experimental sclerodermatous chronic graft-versus-host disease - Zhang, Yun; Shen, Lichong; Dreißigacker, Katja; Zhu, Honglin; Trinh, Minh Thuong; Meng, Xianyi; TRAN MANH, CUONG; Dees, Clara; Matei, Alexandru-Emil; Chen, Chih-Wei; Ditschkowski, Markus; Krauss, Stefan; et al. (Blood, 2021)
Chronic graft-versus-host disease (cGVHD) is a major life-threatening complication of allogeneic hematopoietic stem cell transplantation. The molecular mechanisms underlying cGVHD remain poorly understood, and targeted therapies for clinical use are not well established. Here, we examined the role of the canonical WNT pathway in sclerodermatous cGVHD (sclGVHD). WNT signaling was activated in human sclGVHD with increased nuclear accumulation of the transcription factor β-catenin and a WNT-biased gene expression signature in lesional skin. Treatment with the highly selective tankryase inhibitor G007-LK, the CK1α agonist pyrvinium, or the LRP6 inhibitor salinomycin abrogated the activation of WNT signaling and protected against experimental cGVHD, without a significant impact on graft-versus-leukemia effect (GVL). Treatment with G007-LK, pyrvinium, or salinomycin almost completely prevented the development of clinical and histological features in the B10.D2 (H-2d) → BALB/c (H-2d) and LP/J (H-2b) → C57BL/6 (H-2b) models of sclGVHD. Inhibition of canonical WNT signaling reduced the release of extracellular matrix from fibroblasts and reduced leukocyte influx, suggesting that WNT signaling stimulates fibrotic tissue remodeling by direct effects on fibroblasts and by indirect inflammation-dependent effects in sclGVHD. Our findings may have direct translational potential, because pyrvinium is in clinical use, and tankyrase inhibitors are in clinical trials for other indications.
CRIS-Team Scopus Importer:2021-05-28

Targeting STAT3 Signaling in COL1+ Fibroblasts Controls Colitis-Associated Cancer in Mice - Heichler, Christina; Schmied, Anabel; Enderle, Karin; Scheibe, Kristina; Murawska, Marta; Schmid, Benjamin; Waldner, Maximilian; Neurath, Markus; Neufert, Clemens (Cancers, 2022)
Colorectal cancer (CRC) is a common disease and has limited treatment options. The importance of cancer-associated fibroblasts (CAFs) within the tumor microenvironment (TME) in CRC has been increasingly recognized. However, the role of CAF subsets in CRC is hardly understood and opposing functions of type I (COL1+) vs. type VI (COL6+) collagen-expressing subsets were reported before with respect to NFκB-related signaling. Here, we have focused on COL1+ fibroblasts, which represent a frequent CAF population in CRC and studied their role upon STAT3 activation in vivo. Using a dual strategy with a conditional gain-of-function and a conditional loss-of-function approach in an in vivo model of colitis-associated cancer, tumor development was evaluated by different readouts, including advanced imaging methodologies, e.g., light sheet microscopy and CT-scan. Our data demonstrate that the inhibition of STAT3 activation in COL1+ fibroblasts reduces tumor burden, whereas the constitutive activation of STAT3 promotes the development of inflammation-driven CRC. In addition, our work characterizes the co-expression and distribution of type I and type VI collagen by CAFs in inflammation-associated colorectal cancer using reporter mice. This work indicates a critical contribution of STAT3 signaling in COL1+ CAFs, suggesting that the blockade of STAT3 activation in type I collagen-expressing fibroblasts could serve as promising therapeutic targets in colitis-associated CRC. In combination with previous work by others and us, our current findings highlight the context-dependent roles of COL1+ CAFs and COL6+ CAFs that might be variable according to the specific pathway activated.
CRIS-Team Scopus Importer:2022-03-25
Keywords: AOM/DSS model; Collagen; Colorectal cancer; Fibroblast; Inflammation; Tumorigenesis

TGFβ promotes fibrosis by MYST1-dependent epigenetic regulation of autophagy - Zehender, Ariella; Li, Yi-Nan; Lin, Neng Yu; Stefanica, Adrian; Nüchel, Julian; Chen, Chih-Wei; Hsu, Hsiao Han; Zhu, Honglin; Ding, Xiao; Huang, Jingang; Shen, Lichong; Györfi, Andrea-Hermina; et al. (Nature Communications, 2021)
Activation of fibroblasts is essential for physiological tissue repair. Uncontrolled activation of fibroblasts, however, may lead to tissue fibrosis with organ dysfunction. Although several pathways capable of promoting fibroblast activation and tissue repair have been identified, their interplay in the context of chronic fibrotic diseases remains incompletely understood. Here, we provide evidence that transforming growth factor-β (TGFβ) activates autophagy by an epigenetic mechanism to amplify its profibrotic effects. TGFβ induces autophagy in fibrotic diseases by SMAD3-dependent downregulation of the H4K16 histone acetyltransferase MYST1, which regulates the expression of core components of the autophagy machinery such as ATG7 and BECLIN1. Activation of autophagy in fibroblasts promotes collagen release and is both, sufficient and required, to induce tissue fibrosis. Forced expression of MYST1 abrogates the stimulatory effects of TGFβ on autophagy and re-establishes the epigenetic control of autophagy in fibrotic conditions. Interference with the aberrant activation of autophagy inhibits TGFβ-induced fibroblast activation and ameliorates experimental dermal and pulmonary fibrosis. These findings link uncontrolled TGFβ signaling to aberrant autophagy and deregulated epigenetics in fibrotic diseases and may contribute to the development of therapeutic interventions in fibrotic diseases.
CRIS-Team Scopus Importer:2021-08-06

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Maxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Graef, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2018)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive degeneration of midbrain neurons (MBNs). Recent evidence suggests contribution of the adaptive immune system in PD. Here, we show a role for human T lymphocytes as cell death inducers of induced pluripotent stem cell (iPSC)-derived MBNs in sporadic PD. Higher Th17 frequencies were found in the blood of PD patients and increased numbers of T lymphocytes were detected in postmortem PD brain tissues. We modeled this finding using autologous co-cultures of activated T lymphocytes and iPSC-derived MBNs of sporadic PD patients and controls. After co-culture with T lymphocytes or the addition of IL-17, PD iPSC-derived MBNs underwent increased neuronal death driven by upregulation of IL-17 receptor (IL-17R) and NF kappa B activation. Blockage of IL-17 or IL-17R, or the addition of the FDA-approved anti-IL-17 antibody, secukinumab, rescued the neuronal death. Our findings indicate a critical role for IL-17-producing T lymphocytes in sporadic PD.
EVALuna2:35782

Th2 cells promote eosinophil-independent pathology in a murine model of allergic bronchopulmonary aspergillosis - Dietschmann, Axel; Schruefer, Sebastian; Krappmann, Sven; Vöhringer, David (European Journal of Immunology, 2020)
Repeated inhalation of airborne conidia derived from the fungus Aspergillus fumigatus (Af) can lead to a severe eosinophil-dominated inflammatory condition of the lung termed allergic bronchopulmonary aspergillosis (ABPA). ABPA affects about 5 million individuals worldwide and the mechanisms regulating lung pathology in ABPA are poorly understood. Here, we used a mouse model of ABPA to investigate the role of eosinophils and T cell-derived IL-4/IL-13 for induction of allergic lung inflammation. Selective deletion of IL-4/IL-13 in T cells blunted the Af-induced lung eosinophilia and further resulted in lower expression of STAT6-regulated chemokines and effector proteins such as Arginase 1, Relm-α, Relm-β, and Muc5a/c. Eosinophil-deficient ΔdblGata mice showed lower IL-4 expression in the lung and the number of Th2 cells in the lung parenchyma was reduced. However, expression of the goblet cell markers Clca1 and Muc5a/c, abundance of mucin-positive cells, as well as weight gain of lungs were comparable between Af-challenged ΔdblGata and WT mice. Based on these results, we conclude that T cell-derived IL-4/IL-13 is essential for Af-induced lung eosinophilia and inflammation while eosinophils may play a more subtle immunomodulatory role and should not simply be regarded as pro-inflammatory effector cells in ABPA.
CRIS-Team Scopus Importer:2020-03-20
Keywords: allergy; Aspergillus fumigatus; eosinophils; IL-4/IL-13; lung inflammation

The AP-1 Transcription Factor c-Jun Promotes Arthritis by Regulating Cyclooxygenase-2 and Arginase-1 Expression in Macrophages - Hannemann, Nicole; Jordan, Jutta; Paul, Sushmita; Reid, Stephen; Baenkler, Hanns-Wolf; Sonnewald, Sophia; Bäuerle, Tobias; Vera, Julio; Schett, Georg; Bozec, Aline (Journal of Immunology, 2017)
Activation of proinflammatory macrophages is associated with the inflammatory state of rheumatoid arthritis. Their polarization and activation are controlled by transcription factors such as NF-?B and the AP-1 transcription factor member c-Fos. Surprisingly, little is known about the role of the AP-1 transcription factor c-Jun in macrophage activation. In this study, we show that mRNA and protein levels of c-Jun are increased in macrophages following pro- or anti-inflammatory stimulations. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment cluster analyses of microarray data using wild-type and c-Jun-deleted macrophages highlight the central function of c-Jun in macrophages, in particular for immune responses, IL production, and hypoxia pathways. Mice deficient for c-Jun in macrophages show an amelioration of inflammation and bone destruction in the serum-induced arthritis model. In vivo and in vitro gene profiling, together with chromatin immunoprecipitation analysis of macrophages, revealed direct activation of the proinflammatory factor cyclooxygenase-2 and indirect inhibition of the anti-inflammatory factor arginase-1 by c-Jun. Thus, c-Jun regulates the activation state of macrophages and promotes arthritis via differentially regulating cyclooxygenase-2 and arginase-1 levels.
EVALuna2:13412

The CD83 Molecule – An Important Immune Checkpoint - Grosche, Linda; Knippertz, Ilka; König, Christina; Royzman, Dmytro; Wild, Andreas; Zinser, Elisabeth; Sticht, Heinrich; Muller, Yves; Steinkasserer, Alexander; Lechmann, Matthias (Frontiers in Immunology, 2020)
The CD83 molecule has been identified to be expressed on numerous activated immune cells, including B and T lymphocytes, monocytes, dendritic cells, microglia, and neutrophils. Both isoforms of CD83, the membrane-bound as well as its soluble form are topic of intensive research investigations. Several studies revealed that CD83 is not a typical co-stimulatory molecule, but rather plays a critical role in controlling and resolving immune responses. Moreover, CD83 is an essential factor during the differentiation of T and B lymphocytes, and the development and maintenance of tolerance. The identification of its interaction partners as well as signaling pathways have been an enigma for the last decades. Here, we report the latest data on the expression, structure, and the signaling partners of CD83. In addition, we review the regulatory functions of CD83, including its striking modulatory potential to maintain the balance between tolerance versus inflammation during homeostasis or pathologies. These immunomodulatory properties of CD83 emphasize its exceptional therapeutic potential, which has been documented in specific preclinical disease models.
CRIS-Team Scopus Importer:2020-05-08
Keywords: autoimmunity; CD83; immune tolerance; Treg cells; viral escape mechanism

The Cortical Neuroimmune Regulator TANK Affects Emotional Processing and Enhances Alcohol Drinking: A Translational Study - Müller, Christian P.; Chu, Congying; Qin, Liya; Liu, Chunyu; Xu, Bing; Gao, He; Ruggeri, Barbara; Hieber, Saskia; Schneider, Julia; Jia, Tianye; Tay, Nicole; Akira, Shizuo; et al. (Cerebral Cortex, 2019)
Alcohol abuse is a major public health problem worldwide. Understanding the molecular mechanisms that control regular drinking may help to reduce hazards of alcohol consumption. While immunological mechanisms have been related to alcohol drinking, most studies reported changes in immune function that are secondary to alcohol use. In this report, we analyse how the gene "TRAF family member-associated NF-κB activator" (TANK) affects alcohol drinking behavior. Based on our recent discovery in a large GWAS dataset that suggested an association of TANK, SNP rs197273, with alcohol drinking, we report that SNP rs197273 in TANK is associated both with gene expression (P = 1.16 × 10-19) and regional methylation (P = 5.90 × 10-25). A tank knock out mouse model suggests a role of TANK in alcohol drinking, anxiety-related behavior, as well as alcohol exposure induced activation of insular cortex NF-κB. Functional and structural neuroimaging studies among up to 1896 adolescents reveal that TANK is involved in the control of brain activity in areas of aversive interoceptive processing, including the insular cortex, but not in areas related to reinforcement, reward processing or impulsiveness. Our findings suggest that the cortical neuroimmune regulator TANK is associated with enhanced aversive emotional processing that better protects from the establishment of alcohol drinking behavior.
CRIS-Team Scopus Importer:2019-05-02
Keywords: alcohol; anxiety; drinking; insular cortex; NF-κB; TANK

The Degree of t-System Remodeling Predicts Negative Force-Frequency Relationship and Prolonged Relaxation Time in Failing Human Myocardium - Abu-Khousa, Maha; Fiegle, Dominik; Sommer, Sophie T.; Minabari, Ghazali; Milting, Hendrik; Heim, Christian; Weyand, Michael; Tomasi, Roland; Dendorfer, Andreas; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2020)
The normally positive cardiac force-frequency relationship (FFR) becomes flat or negative in chronic heart failure (HF). Here we explored if remodeling of the cardiomyocyte transverse tubular system (t-system) is associated with alterations in FFR and contractile kinetics in failing human myocardium. Left-ventricular myocardial slices from 13 failing human hearts were mounted into a biomimetic culture setup. Maximum twitch force (F), 90% contraction duration (CD90), time to peak force (TTP) and time to relaxation (TTR) were determined at 37°C and 0.2–2 Hz pacing frequency. F1Hz/F0.5Hz and F2Hz/F0.5Hz served as measures of FFR, intracellular cardiomyocyte t-tubule distance (ΔTT) as measure of t-system remodeling. Protein levels of SERCA2, NCX1, and PLB were quantified by immunoblotting. F1Hz/F0.5Hz (R2 = 0.82) and F2Hz/F0.5Hz (R2 = 0.5) correlated negatively with ΔTT, i.e., samples with severe t-system loss exhibited a negative FFR and reduced myocardial wall tension at high pacing rates. PLB levels also predicted F1Hz/F0.5Hz, but to a lesser degree (R2 = 0.49), whereas NCX1 was not correlated (R2 = 0.02). CD90 correlated positively with ΔTT (R2 = 0.39) and negatively with SERCA2/PLB (R2 = 0.42), indicating that both the t-system and SERCA activity are important for contraction kinetics. Surprisingly, ΔTT was not associated with TTP (R2 = 0) but rather with TTR (R2 = 0.5). This became even more pronounced when interaction with NCX1 expression was added to the model (R2 = 0.79), suggesting that t-system loss impairs myocardial relaxation especially when NCX1 expression is low. The degree of t-system remodeling predicts FFR inversion and contraction slowing in failing human myocardium. Moreover, together with NCX, the t-system may be important for myocardial relaxation.
CRIS-Team Scopus Importer:2020-04-14
Keywords: cardiac excitation-contraction coupling; cardiac remodeling; force frequency relationship; heart failure; human heart; transverse tubular system

The gut-brain axis in inflammatory bowel disease—current and future perspectives - Günther, Claudia; Rothhammer, Veit; Karow, Marisa; Neurath, Markus; Winner, Beate (International Journal of Molecular Sciences, 2021)
The gut–brain axis is a bidirectional communication system driven by neural, hormonal, metabolic, immunological, and microbial signals. Signaling events from the gut can modulate brain function and recent evidence suggests that the gut–brain axis may play a pivotal role in linking gastrointestinal and neurological diseases. Accordingly, accumulating evidence has suggested a link between inflammatory bowel diseases (IBDs) and neurodegenerative, as well as neuroinflammatory diseases. In this context, clinical, epidemiological and experimental data have demonstrated that IBD predisposes a person to pathologies of the central nervous system (CNS). Likewise, a number of neurological disorders are associated with changes in the intestinal environment, which are indicative for disease-mediated gut–brain inter-organ communication. Although this axis was identified more than 20 years ago, the sequence of events and underlying molecular mechanisms are poorly defined. The emergence of precision medicine has uncovered the need to take into account non-intestinal symptoms in the context of IBD that could offer the opportunity to tailor therapies to individual patients. The aim of this review is to highlight recent findings supporting the clinical and biological link between the gut and brain, as well as its clinical significance for IBD as well as neurodegeneration and neuroinflammation. Finally, we focus on novel human-specific preclinical models that will help uncover disease mechanisms to better understand and modulate the function of this complex system.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Ex vivo organ models; Gut-brain axis; IBD; MS; PD

The Gut–Immune–Brain Axis: An Important Route for Neuropsychiatric Morbidity in Inflammatory Bowel Disease - Masanetz, Rebecca Katharina; Winkler, Jürgen; Winner, Beate; Günther, Claudia; Süß, Patrick (International Journal of Molecular Sciences, 2022)
Inflammatory bowel disease (IBD) comprises Crohn’s disease (CD) and ulcerative colitis (UC) and is associated with neuropsychiatric symptoms like anxiety and depression. Both conditions strongly worsen IBD disease burden. In the present review, we summarize the current understanding of the pathogenesis of depression and anxiety in IBD. We present a stepwise cascade along a gut–immune–brain axis initiated by evasion of chronic intestinal inflammation to pass the epithelial and vascular barrier in the gut and cause systemic inflammation. We then summarize different anatomical transmission routes of gut-derived peripheral inflammation into the central nervous system (CNS) and highlight the current knowledge on neuroinflammatory changes in the CNS of preclinical IBD mouse models with a focus on microglia, the brain-resident macrophages. Subsequently, we discuss how neuroinflammation in IBD can alter neuronal circuitry to trigger symptoms like depression and anxiety. Finally, the role of intestinal microbiota in the gut–immune–brain axis in IBD will be reviewed. A more comprehensive understanding of the interaction between the gastrointestinal tract, the immune system and the CNS accounting for the similarities and differences between UC and CD will pave the path for improved prediction and treatment of neuropsychiatric comorbidities in IBD and other inflammatory diseases.
Created from Fastlane, Scopus look-up
Keywords: Crohn’s disease; depression; gut microbiota; gut-brain axis; inflammatory bowel disease; neuroinflammation; systemic inflammation; ulcerative colitis

The human CIB1-EVER1-EVER2 complex governs keratinocyte-intrinsic immunity to beta-papillomaviruses - De Jong, Sarah Jill; Crequer, Amandine; Matos, Irina; Hum, David; Gunasekharan, Vignesh; Lorenzo, Lazaro; Jabot-Hanin, Fabienne; Imahorn, Elias; Arias, Andres A.; Vahidnezhad, Hassan; Youssefian, Leila; Markle, Janet G.; et al. (Journal of Experimental Medicine, 2018)
Patients with epidermodysplasia verruciformis (EV) and biallelic null mutations of TMC6 (encoding EVER1) or TMC8 (EVER2) are selectively prone to disseminated skin lesions due to keratinocyte-tropic human beta-papillomaviruses (beta-HPVs), which lack E5 and E8. We describe EV patients homozygous for null mutations of the CIB1 gene encoding calcium-and integrin-binding protein-1 (CIB1). CIB1 is strongly expressed in the skin and cultured keratinocytes of controls but not in those of patients. CIB1 forms a complex with EVER1 and EVER2, and CIB1 proteins are not expressed in EVER1- or EVER2-deficient cells. The known functions of EVER1 and EVER2 in human keratinocytes are not dependent on CIB1, and CIB1 deficiency does not impair keratinocyte adhesion or migration. In keratinocytes, the CIB1 protein interacts with the HPV E5 and E8 proteins encoded by alpha-HPV16 and gamma-HPV4, respectively, suggesting that this protein acts as a restriction factor against HPVs. Collectively, these findings suggest that the disruption of CIB1-EVER1-EVER2-dependent keratinocyte-intrinsic immunity underlies the selective susceptibility to beta-HPVs of EV patients.
EVALuna2:35267

The Induction of a Permissive Environment to Promote T Cell Immune Evasion in Acute Myeloid Leukemia: The Metabolic Perspective - Mougiakakos, Dimitrios (Frontiers in Oncology, 2019)
Acute myeloid leukemia (AML) is the acute leukemia with highest incidence amongst adults. Despite significant improvements in understanding the genomic landscape and the introduction of novel drugs, long-term outcome remains unsatisfactory. Recently, immunotherapeutic approaches have heralded a new era in cancer treatment. The success of allogeneic hematopoietic stem cell transplantation in AML highlights the disease's immunoresponsiveness. Several immunotherapeutic applications are currently under clinical evaluation and include immune checkpoint blockades, T cell-engaging antibodies, and genetically engineered T cells. However, immunoevasive mechanisms employed by AML blasts severely hamper our endeavors. A better understanding of the underlying mechanisms remains a prerequisite for improving treatment efficacy. One of the hallmarks of the cancer cells is metabolic reprogramming, introduced by Otto Warburg's seminal studies during the beginnings of the last century. Nowadays, it is well established that metabolic adaptation is not just an epiphenomenon during oncogenesis but rather a necessity for tumor development and progression. Furthermore, accumulating data suggest an important role of aberrant tumor cell metabolism for immune escape. AML blasts display a number of metabolic alterations that could be linked to immunoregulation, and these include competition over substrates, abundant release of bioactive metabolites, and an overall microenvironmental metabolic re-modeling that favors the induction or survival of immunoregulatory cell subsets such as regulatory T cells. In this review, we outline the immunoevasive character of the AML blasts' bioenergetics, set it into context with oncogenic mutations, and discuss potentially suitable countermeasures and their limitations.
CRIS-Team Scopus Importer:2019-12-03
Keywords: AML—acute myeloid leukemia; immunoescape mechanisms; immunotherapy; microenvironment; tumor metabolism

The Influence of MHC Class II on B Cell Defects Induced by Invariant Chain/CD74 N-Terminal Fragments - Schneppenheim, Janna; Loock, Ann-Christine; Huettl, Susann; Schweizer, Michaela; Luellmann-Rauch, Renate; Oberg, Hans-Heinrich; Arnold, Philipp; Lehmann, Christian; Dudziak, Diana; Kabelitz, Dieter; Lucius, Ralph; Lennon-Dumenil, Ana-Maria; et al. (Journal of Immunology, 2017)
The invariant chain (CD74) mediates assembly and targeting of MHC class II (MHCII) complexes. In endosomes, CD74 undergoes sequential degradation by different proteases, including cathepsin S (CatS) and the intramembrane protease signal peptide peptidase-like 2a (SPPL2a). In their absence, CD74 N-terminal fragments (NTFs) accumulate. In SPPL2a-/- B cells, such an NTF impairs endosomal trafficking and BCR signal transduction. In mice, this leads to a loss of splenic B cells beyond the transitional stage 1. To gain insight into CD74 determinants and the role of MHCII, we compared B cells from CatS-/- , SPPL2a-/- , and SPPL2a-MHCII double-deficient mice. We assessed differentiation of B cells in bone marrow and spleen and analyzed their endosomal morphology, BCR expression, and signal transduction. We demonstrate that MHCII is dispensable for the B cell phenotype of SPPL2a-/- mice, further supporting a CD74-intrinsic effect. Despite significant vacuolization of endosomal compartments similar to SPPL2a-/- B cells, CatS-/- traditional stage 1 B cells show unimpaired degradation of endocytic cargo, have intact BCR signaling, and do not exhibit any relevant defects in maturation. This could indicate that CD74 NTF-induced structural changes of endosomes are not directly involved in these processes. We further found that the block of CD74 degradation in CatS-/- B cells is incomplete, so that NTF levels are significantly lower than in SPPL2a-/- B cells. This suggests a dose dependency and threshold for the CD74 NTF-associated impairment of B cell signaling and maturation. In addition, different functional properties of the longer, MHCII-bound CD74 NTF could contribute to the milder phenotype of CatS-/- B cells.
EVALuna2:34373

The Interactive Complex between Cytomegalovirus Kinase vCDK/pUL97 and Host Factors CDK7-Cyclin H Determines Individual Patterns of Transcription in Infected Cells. - Schütz, Martin; Cordsmeier, Arne; Wangen, Christina; Horn, Anselm; Wyler, Emanuel; Enßer, Armin; Sticht, Heinrich; Marschall, Manfred (International Journal of Molecular Sciences, 2023)
The infection of human cytomegalovirus (HCMV) is strongly determined by the host-cell interaction in a way that the efficiency of HCMV lytic replication is dependent on the regulatory interplay between viral and cellular proteins. In particular, the activities of protein kinases, such as cyclin-dependent kinases (CDKs) and the viral CDK ortholog (vCDK/pUL97), play an important role in both viral reproduction and virus-host interaction. Very recently, we reported on the complexes formed between vCDK/pUL97, human cyclin H, and CDK7. Major hallmarks of this interplay are the interaction between cyclin H and vCDK/pUL97, which is consistently detectable across various conditions and host cell types of infection, the decrease or increase in pUL97 kinase activity resulting from cyclin H knock-down or elevated levels, respectively, and significant trans-stimulation of human CDK7 activity by pUL97 in vitro. Due to the fact that even a ternary complex of vCDK/pUL97-cyclin H-CDK7 can be detected by coimmunoprecipitation and visualized by bioinformatic structural modeling, we postulated a putative impact of the respective kinase activities on the patterns of transcription in HCMV-infected cells. Here, we undertook a first vCDK/pUL97-specific transcriptomic analysis, which combined conditions of fully lytic HCMV replication with those under specific vCDK/pUL97 or CDK7 drug-mediated inhibition or transient cyclin H knockout. The novel results were further strengthened using bioinformatic modeling of the involved multi-protein complexes. Our data underline the importance of these kinase activities for the C-terminal domain (CTD) phosphorylation-driven activation of host RNA polymerase in HCMV-infected cells. The impact of the individual experimental conditions on differentially expressed gene profiles is described in detail and discussed.
EVALuna2:545510

The involvement of Toll-like receptor 9 in the pathogenesis of erosive autoimmune arthritis - Fischer, Anita; Abdollahi-Roodsaz, Shahla; Boehm, Christina; Niederreiter, Birgit; Meyer, Brigitte; Yau, Anthony C. Y.; Lonnblom, Erik; Joosten, Leo A. B.; Koenders, Marije; Lehmann, Christian; Dudziak, Diana; Krönke, Gerhard; et al. (Journal of Cellular and Molecular Medicine, 2018)
Endogenous nucleic acids and their receptors may be involved in the initiation of systemic autoimmune diseases including rheumatoid arthritis (RA). As the role of the DNA sensing Toll-like receptor (TLR) 9 in RA is unclear, we aimed to investigate its involvement in the pathogenesis of autoimmune arthritis using three different experimental models of RA. The data obtained revealed involvement of TLR9 in the T cell-dependent phase of inflammatory arthritis. In rats with pristane-induced arthritis (PIA), TLR9 inhibition before disease onset reduced arthritis significantly and almost completely abolished bone erosion. Accordingly, serum levels of IL-6, α-1-acid-glycoprotein and rheumatoid factor were reduced. Moreover, in TLR9-/- mice, streptococcal cell wall (SCW)-induced arthritis was reduced in the T cell-dependent phase, whereas T cell-independent serum-transfer arthritis was not affected. Remarkably, while TLR7 expression did not change during in vitro osteoclastogenesis, TLR9 expression was higher in precursor cells than in mature osteoclasts and partial inhibition of osteoclastogenesis was achieved only by the TLR9 antagonist. These results demonstrate a pivotal role for TLR9 in the T cell-dependent phases of inflammatory arthritis and additionally suggest some role during osteoclastogenesis. Hence, endogenous DNA seems to be crucially involved in the pathophysiology of inflammatory autoimmune arthritis.
EVALuna2:34780

The large GTPase AtGBPL3 links nuclear envelope formation and morphogenesis to transcriptional repression - Reimann, Theresa; Müdsam, Christina; Schachtler, Christina; Ince, Semra; Sticht, Heinrich; Herrmann, Christian; Stürzl, Michael; Kost, Benedikt (Nature Plants, 2023)
Guanylate binding proteins (GBPs) are prominent regulators of immunity not known to be required for nuclear envelope formation and morphogenesis. Here we identify the Arabidopsis GBP orthologue AtGBPL3 as a lamina component with essential functions in mitotic nuclear envelope reformation, nuclear morphogenesis and transcriptional repression during interphase. AtGBPL3 is preferentially expressed in mitotically active root tips, accumulates at the nuclear envelope and interacts with centromeric chromatin as well as with lamina components transcriptionally repressing pericentromeric chromatin. Reduced expression of AtGBPL3 or associated lamina components similarly altered nuclear morphology and caused overlapping transcriptional deregulation. Investigating the dynamics of AtGBPL3-GFP and other nuclear markers during mitosis (1) revealed that AtGBPL3 accumulation on the surface of daughter nuclei precedes nuclear envelope reformation and (2) uncovered defects in this process in roots of AtGBPL3 mutants, which cause programmed cell death and impair growth. AtGBPL3 functions established by these observations are unique among dynamin-family large GTPases.
CRIS-Team WoS Importer:2023-05-26

The N-Terminus of the HIV-1 p6 Gag Protein Regulates Susceptibility to Degradation by IDE - Schmalen, Adrian; Karius-Fischer, Julia; Rauch, Pia; Setz, Christian; Korn, Klaus; Henklein, Petra; Fossen, Torgils; Schubert, Ulrich (Viruses, 2018)
As part of the Pr55(Gag) polyprotein, p6 fulfills an essential role in the late steps of the replication cycle. However, almost nothing is known about the functions of the mature HIV-1 p6 protein. Recently, we showed that p6 is a bona fide substrate of the insulin-degrading enzyme (IDE), a ubiquitously expressed zinc metalloprotease. This phenomenon appears to be specific for HIV-1, since p6 homologs of HIV-2, SIV and EIAV were IDE-insensitive. Furthermore, abrogation of the IDE-mediated degradation of p6 reduces the replication capacity of HIV-1 in an Env-dependent manner. However, it remained unclear to which extent the IDE mediated degradation is phylogenetically conserved among HIV-1. Here, we describe two HIV-1 isolates with IDE resistant p6 proteins. Sequence comparison allowed deducing one single amino acid regulating IDE sensitivity of p6. Exchanging the N-terminal leucine residue of p6 derived from the IDE sensitive isolate HIV-1(NL4-3) with proline enhances its stability, while replacing Pro-1 of p6 from the IDE insensitive isolate SG3 with leucine restores susceptibility towards IDE. Phylogenetic analyses of this natural polymorphism revealed that the N-terminal leucine is characteristic for p6 derived from HIV-1 group M except for subtype A, which predominantly expresses p6 with an N-terminal proline. Consequently, p6 peptides derived from subtype A are not degraded by IDE. Thus, IDE mediated degradation of p6 is specific for HIV-1 group M isolates and not occasionally distributed among HIV-1.
EVALuna2:35256

The Number of Colon Crypts in Digital Mucosal Samples: A New Independent Parameter for Diagnosing Ulcerative Colitis - Rubio, Carlos A.; Lang-Schwarz, Corinna; Matek, Christian; Kamaradova, Katerina; Vieth, Michael (Cancer Diagnosis & Prognosis, 2023)
Background/Aim: It has been demonstrated that most routine biopsies from the colon and rectum display cross-cut crypts (CCC). The aim was to assess the number of CCC in microscopic isometric digital samples (0.500 mm2) from routine colon biopsies. Patients and Methods: Colon biopsies from 224 patients were investigated: 99 in patients with ulcerative colitis (UC), 31 UC in remission (UCR), 28 infectious colitis (IC), 7 resolved IC (RIC), 19 diverticular sigmoiditis (DS), and 40 normal colon mucosa (NCM). Results: A total of 8,024 CCC were registered: 2,860 (35.6%) in UC, 1,319 UCR (16.4%), 849 (10.6%) in IC, 340 (4.2%) in RIC, 795 (9.9%) in DS, and 1,861 (23.2%) in NCM. The CCC frequencies in UC and IC were significantly lower (p<0.05) than those in UCR, RIC, DS, and NCM. Conclusion: By the simple algorithm of counting CCC in standardized isometric microscopic digital circles measuring 0.500 mm2, it was possible to differentiate between UC (long-lasting inflammation) and IC (short-lasting inflammation) on the one hand, and UCR, RIC, DS (persistent inflammation), and NCM, on the other. The counting of CCC in the algorithm by five pathologists working in three disparate European Countries, was found to be reproducible.<br
Keywords: ulcerative colitis; colon crypts; frequency; digital samples

The ontogenetic path of human dendritic cells - Amon, Lukas; Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Dudziak, Diana (Molecular Immunology, 2020)
Dendritic cells (DCs) orchestrate adaptive immune responses. In healthy individuals, DCs are drivers and fine-tuners of T cell responses directed against invading pathogens or cancer cells. In parallel, DCs control autoreactive T cells, thereby maintaining T cell tolerance. Under various disease conditions, a disruption of this delicate balance can lead to chronic infections, tumor evasion, or autoimmunity. While great efforts have been made to unravel the origin and development of this powerful cell type in mice, only little is known about the ontogeny of human DCs. Here, we summarize the current understanding of the developmental path of DCs from hematopoietic stem cells to fully functional DCs in their local tissue environment and provide a template for the identification of DCs across various tissues.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Conventional; DC; Human; Ontogeny; Progeny; Transcription factor

The peptidyl-prolyl cis/trans isomerase Pin1 interacts with three early regulatory proteins of human cytomegalovirus - Schütz, Martin; Thomas, Marco; Wangen, Christina; Wagner, Sabrina; Rauschert, Luisa; Errerd, Theresa; Kießling, Melissa; Sticht, Heinrich; Milbradt, Jens; Marschall, Manfred (Virus Research, 2020)
Human cytomegalovirus (HCMV) is a ubiquitous human pathogen of high clinical relevance. Despite intensive research of virus-host interaction, crucial details still remain unknown. In this study, the role of the cellular peptidyl-prolyl cis/trans isomerase Pin1 during HCMV infection was investigated. Pin1 is able to recognize phosphorylated serine/threonine-proline motifs and regulates the structural conformation, stability and function of its substrates. Concerning HCMV replication, our recent studies revealed that Pin1 plays an important role in viral nuclear egress by contributing to the depletion of the nuclear lamina at distinct sites through the cis/trans conversion of lamin proteins. Here, novel data illustrate the HCMV-induced upregulation of Pin1 including various cell types being permissive, semi-permissive or non-permissive for productive HCMV replication. Addressing the question of functional impact, Pin1 knock-out (KO) did not show a measurable effect on viral protein expression, at least when assessed by Western blot analysis. Applying highly sensitive methods of qPCR and plaque titration, a pharmacological inhibition of Pin1 activity, however, led to a significant decrease of viral genome equivalents and production of infectious virus, respectively. When focusing on the identification of viral proteins interacting with Pin1 by various coimmunoprecipitation (CoIP) settings, we obtained positive signals for (i) the core nuclear egress complex protein pUL50, (ii) the viral mRNA export factor pUL69 and (iii) the viral DNA polymerase processivity factor pUL44. Confocal immunofluorescence analysis focusing on partial colocalization between Pin1 and the coexpressed viral proteins pUL50, pUL69 or pUL44, respectively, was consistent with the CoIP experiments. Mapping experiments, using transient expression constructs for a series of truncated protein versions and specific replacement mutants, revealed a complex pattern of Pin1 interaction with these three early regulatory HCMV proteins. Data suggest a combination of different modes of Pin1 interactions, involving both classical phosphorylation-dependent Pin1 binding motifs and additional phosphorylation-independent binding sites. Combined, these results support the concept that Pin1 may play an important role in several stages of HCMV infection, thus determining viral replicative efficiency.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Cytomegalovirus replication; Phosphorylation-independent interaction; Pin1 inhibitor-mediated viral replication block; Pin1 interaction with pUL50; Pin1 upregulation; Prolyl cis/trans isomerase Pin1; pUL44; pUL69

The PPARα Agonist Fenofibrate Prevents Formation of Protein Aggregates (Mallory-Denk bodies) in a Murine Model of Steatohepatitis-like Hepatotoxicity - Nikam, Aniket; Patankar, Jay; Somlapura, Meghana; Lahiri, Pooja; Sachdev, Vinay; Kratky, Dagmar; Denk, Helmut; Zatloukal, Kurt; Abuja, Peter M. (Scientific Reports, 2018)
Chronic intoxication of mice with the porphyrinogenic compound 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) leads to morphological and metabolic changes closely resembling steatohepatitis, a severe form of metabolic liver disease in humans. Since human steatohepatitis (both the alcoholic and non-alcoholic type) is characterized by reduced expression of PPARα and disturbed lipid metabolism we investigated the role of this ligand-activated receptor in the development of DDC-induced liver injury. Acute DDC-intoxication was accompanied by early significant downregulation of Pparα mRNA expression along with PPARα-controlled stress-response and lipid metabolism genes that persisted in the chronic stage. Administration of the specific PPARα agonist fenofibrate together with DDC prevented the downregulation of PPARα-associated genes and also improved the stress response of Nrf2-dependent redox-regulating genes. Moreover, oxidative stress and inflammation were strongly reduced by DDC/fenofibrate co-treatment. In addition, fenofibrate prevented the disruption of hepatocyte intermediate filament cytoskeleton and the formation of Mallory-Denk bodies at late stages of DDC intoxication. Our findings show that, like in human steatohepatitis, PPARα is downregulated in the DDC model of steatohepatitis-like hepatocellular damage. Its downregulation and the pathomorphologic features of steatohepatitis are prevented by co-administration of fenofibrate.
Created from Fastlane, Scopus look-up

The pseudokinase MLKL mediates programmed hepatocellular necrosis independently of RIPK3 during hepatitis - Lopez Posadas, Rocío; Becker, Christoph; Günther, Claudia; Tenzer, Stefan; Amann, Kerstin Ute; Billmeier, Ulrike; Atreya, Raja; Fiorino, Gionata; Vetrano, Stefania; Danese, Silvio; Ekici, Arif Bülent; Wirtz, Stefan; et al. (Journal of Clinical Investigation, 2016)
Although necrosis and necroinflammation are central features of many liver diseases, the role of programmed necrosis in the context of inflammation-dependent hepatocellular death remains to be fully determined. Here, we have demonstrated that the pseudokinase mixed lineage kinase domain-like protein (MLKL), which plays a key role in the execution of receptor-interacting protein (RIP) kinase-dependent necroptosis, is upregulated and activated in human autoimmune hepatitis and in a murine model of inflammation-dependent hepatitis. Using genetic and pharmacologic approaches, we determined that hepatocellular necrosis in experimental hepatitis is driven by an MLKL-dependent pathway that occurs independently of RIPK3. Moreover, we have provided evidence that the cytotoxic activity of the proinflammatory cytokine IFN-? in hepatic inflammation is strongly connected to induction of MLKL expression via activation of the transcription factor STAT1. In summary, our results reveal a pathway for MLKL-dependent programmed necrosis that is executed in the absence of RIPK3 and potentially drives the pathogenesis of severe liver diseases.
EVALuna2:2178

The Quest for Anti-α-Synuclein Antibody Specificity—Lessons Learnt From Flow Cytometry Analysis - Leupold, Lukas; Sigutova, Veronika; Gerasimova, Elizaveta; Regensburger, Martin; Zundler, Sebastian; Zunke, Friederike; Xiang, Wei; Winner, Beate; Prots, Iryna (Frontiers in Neurology, 2022)
The accumulation of alpha-synuclein (aSyn) is the hallmark of a group of neurodegenerative conditions termed synucleopathies. Physiological functions of aSyn, including those outside of the CNS, remain elusive. However, a reliable and reproducible evaluation of aSyn protein expression in different cell types and especially in low-expressing cells is impeded by the existence of a huge variety of poorly characterized anti-aSyn antibodies and a lack of a routinely used sensitive detection methods. Here, we developed a robust flow cytometry-based workflow for aSyn detection and antibody validation. We test our workflow using three commercially available antibodies (MJFR1, LB509, and 2A7) in a variety of human cell types, including induced pluripotent stem cells, T lymphocytes, and fibroblasts, and provide a cell- and antibody-specific map for aSyn expression. Strikingly, we demonstrate a previously unobserved unspecificity of the LB509 antibody, while the MJFR1 clone revealed specific aSyn binding however with low sensitivity. On the other hand, we identified an aSyn-specific antibody clone 2A7 with an optimal sensitivity for detecting aSyn in a range of cell types, including those with low aSyn expression. We further utilize our workflow to demonstrate the ability of the 2A7 antibody to distinguish between physiological differences in aSyn expression in neuronal and non-neuronal cells from the cortical organoids, and in neural progenitors and midbrain dopaminergic neurons from healthy controls and in patients with Parkinson's disease who have aSyn gene locus duplication. Our results provide a proof of principle for the use of high-throughput flow cytometry-based analysis of aSyn and highlight the necessity of rigorous aSyn antibody validation to facilitate the research of aSyn physiology and patholog
Keywords: alpha-synuclein; antibodies; synuclein antibodies; T cell; antibody specificity; flow cytometry; α-synuclein expression

Therapeutic modulation of the bile acid pool by cyp8b1 knockdown protects against nonalcoholic fatty liver disease in mice - Chevre, Raphael; Trigueros-Motos, Laia; Castano, David; Chua, Tricia; Corliano, Maria; Patankar, Jay; Sng, Lareina; Sim, Lauren; Juin, Tan Liang; Carissimo, Guillaume; Ng, Lisa F. P.; Yi, Cheryl Neo Jia; et al. (The FASEB Journal, 2018)
Bile acids (BAs) are surfactant molecules that regulate the intestinal absorption of lipids. Thus, the modulation of BAs represents a potential therapy for nonalcoholic fatty liver disease (NAFLD), which is characterized by hepatic accumulation of fat and is a major cause of liver disease worldwide. Cyp8b1 is a critical modulator of the hydrophobicity index of the BA pool. As a therapeutic proof of concept, we aimed to determine the impact of Cyp8b1 inhibition in vivo on BA pool composition and as protection against NAFLD. Inhibition of Cyp8b1 expression in mice led to a remodeling of the BA pool, which altered its signaling properties and decreased intestinal fat absorption. In a model of cholesterol-induced NAFLD, Cyp8b1 knockdown significantly decreased steatosis and hepatic lipid content, which has been associated with an increase in fecal lipid and BA excretion. Moreover, inhibition of Cyp8b1 not only decreased hepatic lipid accumulation, but also resulted in the clearance of previously accumulated hepatic cholesterol, which led to a regression in hepatic steatosis. Taken together, our data demonstrate that Cyp8b1 inhibition is a viable therapeutic target of crucial interest for metabolic diseases, such as NAFLD.—Chevre, R., Trigueros-Motos, L., Castaño, D., Chua, T., Corlianò, M., Patankar, J. V., Sng, L., Sim, L., Juin, T. L., Carissimo, G., Ng, L. F. P., Yi, C. N. J., Eliathamby, C. C., Groen, A. K., Hayden, M. R., Singaraja, R. R. Therapeutic modulation of the bile acid pool by Cyp8b1 knockdown protects against nonalcoholic fatty liver disease in mice.
Created from Fastlane, Scopus look-up
Keywords: Intestinal cholesterol absorption; Liver targeting; NAFLD therapeutics; SiRNA delivery; Steatosis

The Regulation of Intestinal Inflammation and Cancer Development by Type 2 Immune Responses - Gamez-Belmonte, Reyes; Erkert, Lena; Wirtz, Stefan; Becker, Christoph (International Journal of Molecular Sciences, 2020)
The gut is among the most complex organs of the human body. It has to exert several functions including food and water absorption while setting up an efficient barrier to the outside world. Dysfunction of the gut can be life-threatening. Diseases of the gastrointestinal tract such as inflammatory bowel disease, infections, or colorectal cancer, therefore, pose substantial challenges to clinical care. The intestinal epithelium plays an important role in intestinal disease development. It not only establishes an important barrier against the gut lumen but also constantly signals information about the gut lumen and its composition to immune cells in the bowel wall. Such signaling across the epithelial barrier also occurs in the other direction. Intestinal epithelial cells respond to cytokines and other mediators of immune cells in the lamina propria and shape the microbial community within the gut by producing various antimicrobial peptides. Thus, the epithelium can be considered as an interpreter between the microbiota and the mucosal immune system, safeguarding and moderating communication to the benefit of the host. Type 2 immune responses play important roles in immune-epithelial communication. They contribute to gut tissue homeostasis and protect the host against infections with helminths. However, they are also involved in pathogenic pathways in inflammatory bowel disease and colorectal cancer. The current review provides an overview of current concepts regarding type 2 immune responses in intestinal physiology and pathophysiology.
CRIS-Team WoS Importer:2021-01-15

The renal cancer risk allele at 14q24.2 activates a novel hypoxia-inducible transcription factor-binding enhancer of DPF3 expression - Protze, Johanna; Naas, Stephanie; Krüger, René; Stöhr, Christine; Kraus, Andre; Grampp, Steffen; Schiffer, Mario; Hartmann, Arndt; Wullich, Bernd; Schödel, Johannes; Wiesener, Michael (Journal of Biological Chemistry, 2022)
Evolution of clear cell renal cell carcinoma is guided by dysregulation of hypoxia-inducible transcription factor (HIF) pathways following loss of the von Hippel-Lindau tumor suppressor protein. Renal cell carcinoma (RCC)-associated polymorphisms influence HIF–DNA interactions at enhancers of important oncogenes thereby modulating the risk of developing renal cancer. A strong signal of genome-wide association with RCC was determined for the single nucleotide polymorphism (SNP) rs4903064, located on chr14q.24.2 within an intron of DPF3, encoding for Double PHD Fingers 3, a member of chromatin remodeling complexes; however, it is unclear how the risk allele operates in renal cells. In this study, we used tissue specimens and primary renal cells from a large cohort of RCC patients to examine the function of this polymorphism. In clear cell renal cell carcinoma tissue, isolated tumor cells as well as in primary renal tubular cells, in which HIF was stabilized, we determined genotype-specific increases of DPF3 mRNA levels and identified that the risk SNP resides in an active enhancer region, creating a novel HIF-binding motif. We then confirmed allele-specific HIF binding to this locus using chromatin immunoprecipitation of HIF subunits. Consequentially, HIF-mediated DPF3 regulation was dependent on the presence of the risk allele. Finally, we show that DPF3 deletion in proximal tubular cells retarded cell growth, indicating potential roles for DPF3 in cell proliferation. Our analyses suggest that the HIF pathway differentially operates on a SNP-induced hypoxia-response element at 14q24.2, thereby affecting DPF3 expression, which increases the risk of developing renal cancer.
CRIS-Team Scopus Importer:2022-03-18

The role of sphingolipids in psychoactive drug use and addiction - Kalinichenko, Liubov; Gulbins, Erich; Kornhuber, Johannes; Müller, Christian P. (Journal of Neural Transmission, 2018)
Psychoactive drug use is a common behavior in many societies worldwide, frequently associated with drug instrumentalization. Regular use may develop into drug addiction, which is a severe psychiatric disorder with multiple pathological effects to virtually all organ systems. Treatment strategies for addiction are often insufficient with no broadly working pharmaco-treatment available. Recently, lipids, and particularly sphingolipids, have been considered as new mediators in the pathogenic pathways and as possible therapeutic targets for the treatment of addictive states. In our review, we discuss the contribution of sphingolipids in the development of addictive states including alcohol consumption, nicotine, amphetamine, morphine, and cocaine dependencies. Recent data show that the involvement of various classes of sphingolipids, such as sphingomyelins, ceramides, globosides, sulfatides, and cerebrosides, might explain the development of some specific features of addictive states, for example, apoptotic neurodegeneration induced by psychoactive substances. On the other hand, protective effects of sphingolipids are discussed. Sphingolipids might be a key mechanism in the development of beneficial effects of moderate alcohol consumption. Therefore, sphingolipid systems emerge as possible new pathways involved in the development of addiction and its pathophysiological consequences. However, further analysis is still needed to investigate the exact mechanisms of sphingolipid contribution and possibility of using of sphingolipids as new therapeutic targets.
EVALuna2:211638

The selective FKBP51 inhibitor SAFit2 reduces alcohol consumption and reinstatement of conditioned alcohol effects in mice - König, Loretta; Kalinichenko, Liubov; Huber, Sabine; Voll, Andreas M.; Bauder, Michael; Kornhuber, Johannes; Hausch, Felix; Müller, Christian P. (Addiction Biology, 2019)
There is still no widely effective pharmacotherapy for alcohol addiction available in the clinic. FK506-binding protein 51 (FKBP51) is a negative regulator of the glucocorticoid receptor signaling pathway that regulates the stress-induced glucocorticoid feedback circuit. Here we asked whether selective inhibitors of FKBP51, exemplified by SAFit2, may serve as a new pharmacological strategy to reduce alcohol consumption and conditioned alcohol effects in a mouse model. We report that a relatively short treatment with SAFit2 (20 mg/kg, ip) reduces ongoing 16 vol% alcohol consumption when administered during free access to alcohol in a two-bottle free-choice test. SAFit2 was also able to reduce alcohol consumption when given during an abstinence period immediately before relapse. In contrast, SAFit2 did not affect alcohol consumption when given during a relapse period after repeated withdrawal from alcohol. SAFit2 (10 and 20 mg/kg, ip) showed no effects when used in an intermittent drinking schedule. When 20 vol% alcohol was only available every other day, SAFit2 had no effect on drinking, no matter whether given during a drinking episode or the day before. SAFit2 (2 and 20 mg/kg, ip) did not affect the expression of an alcohol-induced conditioned place preference (CPP). However, SAFit2 was able to inhibit alcohol-induced reinstatement of an extinguished CPP in a dose-dependent way. Altogether, these data may suggest pharmacological inhibition of FKBP51 as a viable strategy to reduce alcohol seeking and consumption.
CRIS-Team Scopus Importer:2019-06-25
Keywords: alcohol; conditioned place preference; drinking; FKBP51; SAFit2

The soluble CD83 protein prevents bone destruction by inhibiting the formation of osteoclasts and inducing resolution of inflammation in arthritis - Royzman, Dmytro; Andreev, Darja; Stich, Lena; Peckert, Katrin; Wild, Andreas; Zinser, Elisabeth; Mühl-Zürbes, Petra; Jones, Evan; Adam, Susanne; Frey, Silke; Fuchs, Maximilian; Kunz, Meik; et al. (Frontiers in Immunology, 2022)
Here we show that soluble CD83 induces the resolution of inflammation in an antigen-induced arthritis (AIA) model. Joint swelling and the arthritis-related expression levels of IL-1 beta, IL-6, RANKL, MMP9, and OC-Stamp were strongly reduced, while Foxp3 was induced. In addition, we observed a significant inhibition of TRAP(+) osteoclast formation, correlating with the reduced arthritic disease score. In contrast, cell-specific deletion of CD83 in human and murine precursor cells resulted in an enhanced formation of mature osteoclasts. RNA sequencing analyses, comparing sCD83- with mock treated cells, revealed a strong downregulation of osteoclastogenic factors, such as Oc-Stamp, Mmp9 and Nfatc1, Ctsk, and Trap. Concomitantly, transcripts typical for pro-resolving macrophages, e.g., Mrc1/2, Marco, Klf4, and Mertk, were upregulated. Interestingly, members of the metallothionein (MT) family, which have been associated with a reduced arthritic disease severity, were also highly induced by sCD83 in samples derived from RA patients. Finally, we elucidated the sCD83-induced signaling cascade downstream to its binding to the Toll-like receptor 4/(TLR4/MD2) receptor complex using CRISPR/Cas9-induced knockdowns of TLR4/MyD88/TRIF and MTs, revealing that sCD83 acts via the TRIF-signaling cascade. In conclusion, sCD83 represents a promising therapeutic approach to induce the resolution of inflammation and to prevent bone erosion in autoimmune arthritis.
CRIS-Team WoS Importer:2022-09-09

The Tip60/Ep400 chromatin remodeling complex impacts basic cellular functions in cranial neural crest-derived tissue during early orofacial development - Gehlen-Breitbach, Sebastian; Schmid, Theresa; Fröb, Franziska; Rodrian, Gabriele; Weider, Matthias; Wegner, Michael; Gölz, Lina (International Journal of Oral Science, 2023)
The cranial neural crest plays a fundamental role in orofacial development and morphogenesis. Accordingly, mutations with impact on the cranial neural crest and its development lead to orofacial malformations such as cleft lip and palate. As a pluripotent and dynamic cell population, the cranial neural crest undergoes vast transcriptional and epigenomic alterations throughout the formation of facial structures pointing to an essential role of factors regulating chromatin state or transcription levels. Using CRISPR/Cas9-guided genome editing and conditional mutagenesis in the mouse, we here show that inactivation of Kat5 or Ep400 as the two essential enzymatic subunits of the Tip60/Ep400 chromatin remodeling complex severely affects carbohydrate and amino acid metabolism in cranial neural crest cells. The resulting decrease in protein synthesis, proliferation and survival leads to a drastic reduction of cranial neural crest cells early in fetal development and a loss of most facial structures in the absence of either protein. Following heterozygous loss of Kat5 in neural crest cells palatogenesis was impaired. These findings point to a decisive role of the Tip60/Ep400 chromatin remodeling complex in facial morphogenesis and lead us to conclude that the orofacial clefting observed in patients with heterozygous KAT5 missense mutations is at least in part due to disturbances in the cranial neural crest.
CRIS-Team Scopus Importer:2023-04-21

The transcriptional co-activator Yap1 promotes adult hippocampal neural stem cell activation - Fan, Wenqiang; Jurado-Arjona, Jerónimo; Alanis-Lobato, Gregorio; Péron, Sophie; Berger, Christian; Andrade-Navarro, Miguel A.; Falk, Sven; Berninger, Benedikt (EMBO Journal, 2023)
Most adult hippocampal neural stem cells (NSCs) remain quiescent, with only a minor portion undergoing active proliferation and neurogenesis. The molecular mechanisms that trigger the transition from quiescence to activation are still poorly understood. Here, we found the activity of the transcriptional co-activator Yap1 to be enriched in active NSCs. Genetic deletion of Yap1 led to a significant reduction in the relative proportion of active NSCs, supporting a physiological role of Yap1 in regulating the transition from quiescence to activation. Overexpression of wild-type Yap1 in adult NSCs did not induce NSC activation, suggesting tight upstream control mechanisms, but overexpression of a gain-of-function mutant (Yap1-5SA) elicited cell cycle entry in NSCs and hilar astrocytes. Consistent with a role of Yap1 in NSC activation, single cell RNA sequencing revealed a partial induction of an activated NSC gene expression program. Furthermore, Yap1-5SA expression also induced expression of Taz and other key components of the Yap/Taz regulon that were previously identified in glioblastoma stem cell-like cells. Consequently, dysregulated Yap1 activity led to repression of hippocampal neurogenesis, aberrant cell differentiation, and partial acquisition of a glioblastoma stem cell-like signature.
CRIS-Team Scopus Importer:2023-05-05
Keywords: hippocampus; neurogenesis; quiescence; radial glia; single cell RNA sequencing

The transcription factor GLI2 as a downstream mediator of transforming growth factor-?-induced fibroblast activation in SSc - Liang, Ruifang; Sumova, Barbora; Cordazzo, Cinzia; Mallano, Tatjana; Zhang, Yun; Wohlfahrt, Thomas; Dees, Clara; Krasowska, Dorota; Michalska-Jakubus, Malgorzata; Distler, Oliver; Schett, Georg; Senolt, Ladislav; et al. (Annals of the Rheumatic Diseases, 2016)
Hedgehog signalling plays a critical role during the pathogenesis of fibrosis in systemic sclerosis (SSc). Besides canonical hedgehog signalling with smoothened (SMO)-dependent activation of GLI transcription factors, GLI can be activated independently of classical hedgehog ligands and receptors (so-called non-canonical pathways). Here, we aimed to evaluate the role of non-canonical hedgehog signalling in SSc and to test the efficacy of direct GLI inhibitors that target simultaneously canonical and non-canonical hedgehog pathways.The GLI inhibitor GANT-61 was used to inhibit canonical as well as non-canonical hedgehog signalling, while the SMO inhibitor vismodegib was used to selectively target canonical hedgehog signalling. Furthermore, GLI2 was selectively depleted in fibroblasts using the Cre-LoxP system. The effects of pharmacological or genetic of GLI2 on transforming growth factor-? (TGF-?) signalling were analysed in cultured fibroblasts, in bleomycin-induced pulmonary fibrosis and in mice with overexpression of a constitutively active TGF-? receptor I.TGF-? upregulated GLI2 in a Smad3-dependent manner and induced nuclear accumulation and DNA binding of GLI2. Fibroblast-specific knockout of GLI2 protected mice from TBR(act)-induced fibrosis. Combined targeting of canonical and non-canonical hedgehog signalling with direct GLI inhibitors exerted more potent antifibrotic effects than selective targeting of canonical hedgehog signalling with SMO inhibitors in experimental dermal and pulmonary fibrosis.Our data demonstrate that hedgehog pathways and TGF-? signalling both converge to GLI2 and that GLI2 integrates those signalling to promote tissue fibrosis. These findings may have translational implications as non-selective inhibitors of GLI2 are in clinical use and selective molecules are currently in development.
EVALuna2:13344

The tyrosine phosphatase SHP2 controls TGFβ-induced STAT3 signaling to regulate fibroblast activation and fibrosis - Zehender, Ariella; Huang, Jingang; Gyoerfi, Andrea-Hermina; Matei, Alexandru-Emil; Thuong Trinh-Minh,; Xu, Xiaohan; Li, Yi-Nan; Chen, Chih-Wei; Lin, Jianping; Dees, Clara; Beyer, Christian; Gelse, Kolja; et al. (Nature Communications, 2018)
Uncontrolled activation of TGFβ signaling is a common denominator of fibrotic tissue remodeling. Here we characterize the tyrosine phosphatase SHP2 as a molecular checkpoint for TGFβ-induced JAK2/STAT3 signaling and as a potential target for the treatment of fibrosis. TGFβ stimulates the phosphatase activity of SHP2, although this effect is in part counterbalanced by inhibitory effects on SHP2 expression. Stimulation with TGFβ promotes recruitment of SHP2 to JAK2 in fibroblasts with subsequent dephosphorylation of JAK2 at Y570 and activation of STAT3. The effects of SHP2 on STAT3 activation translate into major regulatory effects of SHP2 on fibroblast activation and tissue fibrosis. Genetic or pharmacologic inactivation of SHP2 promotes accumulation of JAK2 phosphorylated at Y570, reduces JAK2/STAT3 signaling, inhibits TGFβ-induced fibroblast activation and ameliorates dermal and pulmonary fibrosis. Given the availability of potent SHP2 inhibitors, SHP2 might thus be a potential target for the treatment of fibrosis.
EVALuna2:34477

The Use of Digital Technology and Media in German Parkinson's Disease Patients - Marxreiter, Franz; Buttler, Ulrike; Gaßner, Heiko; Gandor, Florin; Gladow, Till; Eskofier, Björn; Winkler, Jürgen; Ebersbach, Georg; Klucken, Jochen (Journal of Parkinson's Disease, 2020)
BACKGROUND: Parkinson's disease (PD) is an age dependent neurodegenerative disorder with increasing prevalence. Digital technologies like computers and smartphones offer mobile telecommunication, diagnostic and monitoring and may connect the patient continuously with his healthcare team, providing disease related information, and support healthcare. Since the use of these technologies in western civilization is age dependent, possession and usage cannot be regarded as given in PD. In contrast to increasing efforts to implement digital technology into PD patient care, little is known about the use of computers, smartphones, and internet-affinity in PD patients. OBJECTIVE: We evaluated the use of digital technologies in different age groups of PD patients. METHODS: We developed a questionnaire adapted to the annual German microcensus on "use of digital communication technologies", allowing a comparison to the general population in Germany. RESULTS: 190 PD patients completed the questionnaire. About 75% of PD patients access disease related information on the internet. Patients across all age groups used computers and the internet as frequent or more frequently compared to the German population. Use of computers, smartphones, and the internet in PD was age dependent. Advanced PD patients with higher motor impairment used smartphones less often, while mobile phone usage was not reduced. CONCLUSION: The adoption of a digital lifestyle is present in the PD population, apart from smartphone usage, which is impaired by motor symptoms. Thus, future healthcare technologies are not hampered by the inability of PD patients to use the necessary tools, however, fine motor-skill requirements have to be acknowledged.
EVALuna2:213360
Keywords: Smartphones; digital media; Parkinson's disease; movement disorder; digital healthcare

Tideglusib Rescues Neurite Pathology of SPG11 iPSC Derived Cortical Neurons. - Pozner, Tatyana; Schray, Annika; Regensburger, Martin; Lie, Dieter Chichung; Schlötzer-Schrehardt, Ursula; Winkler, Jürgen; Turan, Sören; Winner, Beate (Frontiers in Neuroscience, 2018)
Mutations in SPG11 cause a complicated autosomal recessive form of hereditary spastic paraplegia (HSP). Mechanistically, there are indications for the dysregulation of the GSK3 beta/beta Cat signaling pathway in SPG11. In this study, we tested the therapeutic potential of the GSK3 beta inhibitor, tideglusib, to rescue neurodegeneration associated characteristics in an induced pluripotent stem cells (iPSCs) derived neuronal model from SPG11 patients and matched healthy controls as well as a CRISPR-Cas9 mediated SPG11 knock-out line and respective control. SPG11-iPSC derived cortical neurons, as well as the genome edited neurons exhibited shorter and less complex neurites than controls. Administration of tideglusib to these lines led to the rescue of neuritic impairments. Moreover, the treatment restored increased cell death and ameliorated the membranous inclusions in iPSC derived SPG11 neurons. Our results provide a first evidence for the rescue of neurite pathology in SPG11-HSP by tideglusib. The current lack of disease-modifying treatments for SPG11 and related types of complicated HSP renders tideglusib a candidate compound for future clinical application.
EVALuna2:35778
Keywords: CRISPR knock-out; GSK3β inhibitor; SPG11; hereditary spastic paraplegia; induced pluripotent stem cell; neuronal culture; tideglusib

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triplenegative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype 'lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach. (C) 2018 S. Karger GmbH, Freiburg
EVALuna2:34061
Keywords: Tumor-infiltrating lymphocytes; Response; Neoadjuvant chemotherapy; TILGen study

TILGen study-immunological targets in patients with breast cancer : Influence of tumor-infiltrating lymphocytes - Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Mackensen, Andreas; Kremer, Anita; Reimann, Hannah; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Häberle, Lothar; Gaß, Paul; et al. (Pathologe, 2018)
BACKGROUND: The interaction of our immune system with breast cancer (BC) cells prompted the investigation of tumor-infiltrating lymphocytes (TILs) and targeted, tumor antigen-specific immunotherapy. OBJECTIVES: Correlation between TILs and pathological complete response (pCR) after neoadjuvant systemic therapy (NACT). Tumor-specific antigens (TSAs) in HER2+ and triple negative BC and establishment of TSA-specific therapies within the interdisciplinary TILGen study. METHODS: Illustration of the TILGen study design. Assessment of TILs and correlation with pCR within this BC study. RESULTS: pCR was achieved in 38.4% (56/146) and associated with estrogen receptor/progesterone receptor negative (ER-/PR-) and HER2+ tumors. Lymphocytic predominant BC (LPBC) was found in 16.4% (24/146), particularly in ER-/PR- (ER-: 27.3% vs. ER+: 9.9%, PR-: 22.3% vs. PR+: 8.2%), large, and poorly differentiated BC. TILs were significantly correlated with pCR in multivariate analysis. In LPBC, pCR was achieved in 66.7%, whereas it was 32.8% in non-LPBC. CONCLUSIONS: First results confirm the influence of the human immune system on the response to NACT in HER2+ and triple negative BC. TSA-specific immunotherapy might improve the outcome in BC patients but there is an urgent need for comprehensive studies to further investigate this issue.
EVALuna2:35097

Time Tracking of Standard Ultrasound Examinations in Pediatric Hospitals and Pediatric Medical Practices - A Multicenter Study by the Pediatric Section of the German Society of Ultrasound in Medicine (DEGUM) - Regensburger, Adrian; Knieling, Ferdinand; Feldkamp, Axel; Rascher, Wolfgang; Diesch, Katharina; Wölfle, Joachim; Prokosch, Hans-Ulrich; Jüngert, Jörg M. (Ultraschall in der Medizin, 2019)
PURPOSE: Ultrasonography is the primary imaging modality in pediatrics but still lacks sufficient reimbursement in Germany. In this multicenter study, national data for the duration of standard ultrasound in pediatrics were systematically documented in order to specify the actual time required. MATERIALS AND METHODS: N = 10 hospitals (N = 5 university hospitals, N = 5 non-university hospitals) and N = 3 medical practices in Germany recorded the entire process of an ultrasound examination in a special protocol developed by the Pediatric Section of the DEGUM. The duration of each of seven single steps during ultrasonography (from data input to final discussion of the results) of different organ systems was logged. RESULTS: In total, N = 2118 examinations from different organ systems were recorded. N = 10 organ systems were examined frequently (> 30 times). The total duration of an ultrasound examination was statistically significantly longer in hospitals compared to medical practices (median (IQR) 27 min. (18-38) vs. 12 min. (9-17), p < 0.001). The "hands-on" patient time was approximately one half of the total required time in both settings (49.9 % vs. 48.9 %). Ultrasonography of the abdomen and brain lasted longer in university hospitals than in non-university hospitals (p < 0.001, and p = 0.04, respectively). Cooperation and age did not uniformly correlate with the total duration. CONCLUSION: This study provides novel comprehensive national data for the duration of standardized ultrasound examinations of children and adolescents in Germany. These data are essential for a further evaluation of the economic costs and should support better remuneration in the future.
EVALuna2:209480

TNF-Mediated Restriction of Arginase 1 Expression in Myeloid Cells Triggers Type 2 NO Synthase Activity at the Site of Infection - Schleicher, Ulrike; Paduch, Katrin; Debus, Andrea; Obermeyer, Stephanie; Koenig, Till; Kling, Jessica C.; Ribechini, Eliana; Dudziak, Diana; Mougiakakos, Dimitrios; Murray, Peter J.; Ostuni, Renato; Koerner, Heinrich; et al. (Cell Reports, 2016)
Neutralization or deletion of tumor necrosis factor (TNF) causes loss of control of intracellular pathogens in mice and humans, but the underlying mechanisms are incompletely understood. Here, we found that TNF antagonized alternative activation of macrophages and dendritic cells by IL-4. TNF inhibited IL-4-induced arginase 1 (Arg1) expression by decreasing histone acetylation, without affecting STAT6 phosphorylation and nuclear translocation. In Leishmania major-infected C57BL/6 wild-type mice, type 2 nitric oxide (NO) synthase (NOS2) was detected in inflammatory dendritic cells or macrophages, some of which co-expressed Arg1. In TNF-deficient mice, Arg1 was hyperexpressed, causing an impaired production of NO in situ. A similar phenotype was seen in L. major-infected BALB/c mice. Arg1 deletion in hematopoietic cells protected these mice from an otherwise lethal disease, although their disease-mediating T cell response (Th2, Treg) was maintained. Thus, deletion or TNF-mediated restriction of Arg1 unleashes the production of NO by NOS2, which is critical for pathogen control.
EVALuna2:7700

Total Recall: Intestinal T-RM Cells in Health and Disease - Paap, Eva-Maria; Müller, Tanja; Sommer, Katrin; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2021)
Tissue-resident memory T cells (T-RM cells) have crucial functions in host defense in mucosal tissues. They provide local adaptive immune surveillance and allow the fast initiation of targeted adaptive immune responses in case of antigen re-exposure. Recently, an aberrant activation in the case of immunologically mediated diseases has been increasingly acknowledged. As the organ with the largest interface to the environment, the gastrointestinal tract faces billions of antigens every day. Tightly balanced processes are necessary to ensure tolerance towards non-hazardous antigens, but to set up a powerful immune response against potentially dangerous ones. In this complex nexus of immune cells and their mediators, T-RM cells play a central role and have been shown to promote both physiological and pathological events. In this review, we will summarize the current knowledge on the homeostatic functions of T-RM cells and delineate their implication in infection control in the gut. Moreover, we will outline their commitment in immune dysregulation in gastrointestinal chronic inflammatory conditions and shed light on T-RM cells as current and potential future therapeutic targets.
CRIS-Team WoS Importer:2021-02-19

Transcriptional control of dendritic cell development and functions - Amon, Lukas; Lehmann, Christian; Baranska, Anna; Schoen, Janina; Heger, Lukas; Dudziak, Diana (Immunobiology of Dendritic Cells Part B, 2019)
Dendritic cells (DCs) are major regulators of adaptive immunity, as they are not only capable to induce efficient immune responses, but are also crucial to maintain peripheral tolerance and thereby inhibit autoimmune reactions. DCs bridge the innate and the adaptive immune system by presenting peptides of self and foreign antigens as peptide MHC complexes to T cells. These properties render DCs as interesting target cells for immunomodulatory therapies in cancer, but also autoimmune diseases. Several subsets of DCs with special properties and functions have been described. Recent achievements in understanding transcriptional programs on single cell level, together with the generation of new murine models targeting specific DC subsets, advanced our current understanding of DC development and function. Thus, DCs arise from precursor cells in the bone marrow with distinct progenitor cell populations splitting the monocyte populations and macrophage populations from the DC lineage, which upon lineage commitment can be separated into conventional cDC1, cDC2, and plasmacytoid DCs (pDCs). The DC populations harbor intrinsic programs enabling them to react for specific pathogens in dependency on the DC subset, and thereby orchestrate T cell immune responses. Similarities, but also varieties, between human and murine DC subpopulations are challenging, and will require further investigation of human specimens under consideration of the influence of the tissue micromilieu and DC subset localization in the future.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Antigen presentation; BatF3; CDP; Cross-presentation; DC; Dendritic cell; IRF; Lineage commitment; Ontogeny; Progenitor; Transcription factor; Zbtb46

Transcription factor Fra-1 targets arginase-1 to enhance macrophage-mediated inflammation in arthritis - Hannemann, Nicole; Cao, Shan; Eriksson, Daniel; Schnelzer, Anne; Jordan, Jutta; Eberhardt, Martin; Schleicher, Ulrike; Rech, Jürgen; Uebe, Steffen; Ekici, Arif Bülent; Canete, Juan D.; Chen, Xiaoxiang; et al. (Journal of Clinical Investigation, 2019)
The polarization of macrophages is regulated by transcription factors, such as NF-κB and activator protein 1 (AP-1). In this manuscript, we delineated the role of the transcription factor Fos-related antigen 1 (Fra-1) during macrophage activation and development of arthritis. Network level interaction analysis of microarray data derived from Fra-1- or Fra-2-deficient macrophages revealed a central role of Fra-1, but not of Fra-2, in orchestrating the expression of genes related to wound response, Toll-like receptor activation, and interleukin signaling. ChIP sequencing and standard ChIP analyses of macrophages identified arginase 1 (Arg1) as a target of Fra-1. Luciferase reporter assays revealed that Fra-1 downregulated Arg1 expression by direct binding to the promoter region. Using macrophage-specific Fra-1- or Fra-2-deficient mice, we observed enhanced expression and activity of Arg1 and a reduction of arthritis in the absence of Fra-1, but not of Fra-2. This phenotype was reversed by treatment with the arginase inhibitor Nω-hydroxy-nor-arginine, while -arginine supplementation increased arginase activity and alleviated arthritis, supporting the notion that reduced arthritis in macrophage-specific Fra-1-deficient mice resulted from enhanced Arg1 expression and activity. Moreover, patients with active rheumatoid arthritis (RA) showed increased Fra-1 expression in the peripheral blood and elevated Fra-1 protein in synovial macrophages compared with RA patients in remission. In addition, the Fra-1/ARG1 ratio in synovial macrophages was related to RA disease activity. In conclusion, these data suggest that Fra-1 orchestrates the inflammatory state of macrophages by inhibition of Arg1 expression and thereby impedes the resolution of inflammation.
CRIS-Team Scopus Importer:2019-07-16

Transfer of htlv-1 p8 and gag to target t-cells depends on vasp, a novel interaction partner of p8 - Donhauser, Norbert; Socher, Eileen; Millen, Sebastian; Heym, Stefanie; Sticht, Heinrich; Thoma-Kreß, Andrea (PLoS Pathogens, 2020)
The Human T-cell leukemia virus type 1 (HTLV-1) orf I-encoded accessory protein p8 is cleaved from its precursor p12, and both proteins contribute to viral persistence. p8 induces cellular protrusions, which are thought to facilitate transfer of p8 to target cells and virus transmission. Host factors interacting with p8 and mediating p8 transfer are unknown. Here, we report that vasodilator-stimulated phosphoprotein (VASP), which promotes actin filament elongation, is a novel interaction partner of p8 and important for p8 and HTLV-1 Gag cell-to-cell transfer. VASP contains an Ena/VASP homology 1 (EVH1) domain that targets the protein to focal adhesions. Bioinformatics identified a short stretch in p8 (amino acids (aa) 24-45) which may mediate interactions with the EVH1 domain of VASP. Co-immunoprecipitations confirmed interactions of VASP:p8 in 293T, Jurkat and HTLV-1-infected MT-2 cells. Co-precipitation of VASP:p8 could be significantly blocked by peptides mimicking aa 26-37 of p8. Mutational studies revealed that the EVH1-domain of VASP is necessary, but not sufficient for the interaction with p8. Further, deletion of the VASP G- and F-actin binding domains significantly diminished co-precipitation of p8. Imaging identified areas of partial co-localization of VASP with p8 at the plasma membrane and in protrusive structures, which was confirmed by proximity ligation assays. Co-culture experiments revealed that p8 is transferred between Jurkat T-cells via VASP-containing conduits. Imaging and flow cytometry revealed that repression of both endogenous and overexpressed VASP by RNA interference or by CRISPR/Cas9 reduced p8 transfer to the cell surface and to target Jurkat T-cells. Stable repression of VASP by RNA interference in chronically infected MT-2 cells impaired both p8 and HTLV-1 Gag transfer to target Jurkat T-cells, while virus release was unaffected. Thus, we identified VASP as a novel interaction partner of p8, which is important for transfer of HTLV-1 p8 and Gag to target T-cells.
CRIS-Team Scopus Importer:2020-10-16

Transfontanellar Contrast-Enhanced Ultrasound for Monitoring Brain Perfusion During Neonatal Heart Surgery - Knieling, Ferdinand; Rüffer, André; Cesnjevar, Robert; Regensburger, Adrian; Purbojo, Ariawan; Dittrich, Sven; Münch, Frank; Neubert, Antje; Meyer, Sebastian; Strobel, Deike; Rascher, Wolfgang; Wölfle, Joachim; et al. (Circulation: Cardiovascular Imaging, 2020)
CRIS-Team Scopus Importer:2020-03-13

Transfontanellar Contrast-enhanced US for Intraoperative Imaging of Cerebral Perfusion during Neonatal Arterial Switch Operation - Knieling, Ferdinand; Cesnjevar, Robert; Regensburger, Adrian; Wagner, Alexandra; Purbojo, Ariawan; Dittrich, Sven; Münch, Frank; Neubert, Antje; Wölfle, Joachim; Jüngert, Jörg M.; Rüffer, André (Radiology, 2022)
Background Brain injury and subsequent neurodevelopmental disorders are major determinants for later-life outcomes in neonates with transposition of the great arteries (TGA). Purpose To quantitatively assess cerebral perfusion in neonates with TGA undergoing arterial switch operation (ASO) using transfontanellar contrast-enhanced US (T-CEUS). Materials and Methods In a prospective single-center cross-sectional diagnostic study, neonates with TGA scheduled for ASO were recruited from February 2018 to February 2020. Measurements were performed at five time points before, during, and after surgery (T1-T5), and 11 perfusion parameters were derived per cerebral hemisphere. Neonate clinical characteristics, heart rate, mean arterial pressure, central venous pressure, near-infrared spectroscopy, blood gas analyses, ventilation time, time spent in the pediatric intensive care unit, and time in hospital were correlated with imaging parameters. Analysis of variance or a mixed-effects model were used for groupwise comparisons. Results A total of 12 neonates (mean gestational age, 39 6/7 weeks ± 1/7 [SD]) were included and underwent ASO a mean of 6.9 days ± 3.4 after birth. When compared with baseline values, T-CEUS revealed a longer mean time-to-peak (right hemisphere, 4.3 seconds ± 2.1 vs 17 seconds ± 6.4 [P < .001]; left hemisphere, 4.0 seconds ± 2.3 vs 21 seconds ± 8.7 [P < .001]) and rise time (right hemisphere, 3.5 seconds ± 1.7 vs 11 seconds ± 5.1 [P = .002]; left hemisphere, 3.4 seconds ± 2.0 vs 22 seconds ± 7.8 [P = .004]) in both cerebral hemispheres during low-flow cardiopulmonary bypass and hypothermia (T4) for all neonates. Neonate age at surgery negatively correlated with T-CEUS parameters during ASO, as calculated with the area under the flow curve (AUC) during wash-in (R = -0.60, P = .020), washout (R = -0.82, P = .002), and both wash-in and washout (R = -0.79, P = .004). Mean AUC values were lower in neonates older than 7 days compared with younger neonates during wash-in ([87 arbitrary units au ± 77] × 102 vs [270 au ± 164] × 102, P = .049]), washout ([15 au ± 11] × 103 vs [65 au ± 38] × 103, P = .020]) and both wash-in and washout ([24 au ± 18] × 103 vs [92 au ± 53] × 103, P = .023). Conclusion Low-flow hypothermic conditions resulted in reduced cerebral perfusion, as measured with transfontanellar contrast-enhanced US, which inversely correlated with age at surgery. Clinical trial registration no. NCT03215628 © RSNA, 2022 Online supplemental material is available for this article.
CRIS-Team Scopus Importer:2022-07-01

Transformer-based biomarker prediction from colorectal cancer histology: A large-scale multicentric study - Wagner, Sophia J.; Reisenbüchler, Daniel; West, Nicholas P.; Niehues, Jan Moritz; Zhu, Jiefu; Foersch, Sebastian; Veldhuizen, Gregory Patrick; Quirke, Philip; Grabsch, Heike I.; van den Brandt, Piet A.; Hutchins, Gordon G.A.; Richman, Susan D.; et al. (Cancer Cell, 2023)
Deep learning (DL) can accelerate the prediction of prognostic biomarkers from routine pathology slides in colorectal cancer (CRC). However, current approaches rely on convolutional neural networks (CNNs) and have mostly been validated on small patient cohorts. Here, we develop a new transformer-based pipeline for end-to-end biomarker prediction from pathology slides by combining a pre-trained transformer encoder with a transformer network for patch aggregation. Our transformer-based approach substantially improves the performance, generalizability, data efficiency, and interpretability as compared with current state-of-the-art algorithms. After training and evaluating on a large multicenter cohort of over 13,000 patients from 16 colorectal cancer cohorts, we achieve a sensitivity of 0.99 with a negative predictive value of over 0.99 for prediction of microsatellite instability (MSI) on surgical resection specimens. We demonstrate that resection specimen-only training reaches clinical-grade performance on endoscopic biopsy tissue, solving a long-standing diagnostic problem.
CRIS-Team Scopus Importer:2023-09-15
Keywords: artificial intelligence; biomarker; colorectal cancer; deep learning; microsatellite instability; multiple instance learning; transformer

Transient naming deficits associated with insular lesions in a patient with encephalitis - Marxreiter, Franz; Utz, Kathrin; Schlachetzki, Johannes; Seifert, Frank; Schmidt, Manuel; Dörfler, Arnd; Schwab, Stefan; Schenk, Thomas (Neurocase, 2019)
We describe a patient with acute herpes simplex encephalitis with left-hemispheric hippocampal, parahippocampal and insular lesions. Although prototypic language areas were unaffected, the patient suffered from an inability to name objects or animals displayed on pictures. This deficit was transient and gradually disappeared 8 weeks after the initial diagnosis. Our findings are in line with a previous report showing similar deficits in a patient with a comparable lesion pattern and support the hypothesis that left insular lesions can produce severe naming deficits. Using FDG-PET we ruled out that functional deactivation in classical language areas account for the observed naming deficits.
EVALuna2:204482

Transrectal Absorber Guide Raster-Scanning Optoacoustic Mesoscopy for Label-Free In Vivo Assessment of Colitis - Bühler, Adrian; Brown, Emma; Paulus, Lars-Philip; Eckstein, Markus; Thoma, Oana-Maria; Oraiopoulou, Mariam-Eleni; Rother, Ulrich; Hörning, André; Hartmann, Arndt; Neurath, Markus; Wölfle, Joachim; Friedrich, Oliver; et al. (Advanced Science, 2023)
Optoacoustic imaging (OAI) enables microscale imaging of endogenous chromophores such as hemoglobin at significantly higher penetration depths compared to other optical imaging technologies. Raster-scanning optoacoustic mesoscopy (RSOM) has recently been shown to identify superficial microvascular changes associated with human skin pathologies. In animal models, the imaging depth afforded by RSOM can enable entirely new capabilities for noninvasive imaging of vascular structures in the gastrointestinal tract, but exact localization of intra-abdominal organs is still elusive. Herein the development and application of a novel transrectal absorber guide for RSOM (TAG-RSOM) is presented to enable accurate transabdominal localization and assessment of colonic vascular networks in vivo. The potential of TAG-RSOM is demonstrated through application during mild and severe acute colitis in mice. TAG-RSOM enables visualization of transmural vascular networks, with changes in colon wall thickness, blood volume, and OAI signal intensities corresponding to colitis-associated inflammatory changes. These findings suggest TAG-RSOM can provide a novel monitoring tool in preclinical IBD models, refining animal procedures and underlines the capabilities of such technologies to address inflammatory bowel diseases in humans.
CRIS-Team WoS Importer:2023-05-12

Treadmill exercise intervention improves gait and postural control in alpha-synuclein mouse models without inducing cerebral autophagy - Minakaki, Georgia; Canneva, Fabio; Chevessier, Frederic; Bode, Frederik; Menges, Stefanie; Timotius, Ivanna; Kalinichenko, Liubov; Meixner, Holger; Müller, Christian P.; Eskofier, Björn; Casadei, Nicolas; Riess, Olaf; et al. (Behavioural Brain Research, 2019)
Gait and postural control dysfunction are prototypical symptoms compromising quality of life for patients with Parkinson’s disease (PD). Hallmarks of cellular pathology are dopaminergic degeneration and accumulation of the cytosolic protein alpha-synuclein, linked to impaired autophagy-lysosome pathway (ALP) clearance. Physical exercise improves gait in PD patients and motor function in rodent lesion models. Moreover, exercise is considered neuroprotective and ALP induction has been reported, e.g. in human skeletal muscle, rodent peripheral and cerebral tissues. A combined analysis of how distinct exercise paradigms affect motor and central biochemical aspects of PD could maximize benefits for patients. Here we examine the effect of 4 weeks treadmill exercise intervention in 7-8 month non-lesioned mice on a) distinct gait categories, b) ALP activity, c) dopaminergic and alpha-synuclein homeostasis. The study includes wild type, alpha-synuclein knockout, and mice exclusively expressing human alpha-synuclein. Parameters of gait regularity and stability, activity, and dynamic postural control during unforced walk, were assessed by an automated system (CatWalk XT). At baseline, alpha-synuclein mouse models exhibited irregular and less active gait, with impaired dynamic postural control, compared to wild type mice. Treadmill exercise particularly improved speed and stride length, while increasing dual diagonal versus three-paw body support in both the alpha-synuclein knockout and transgenic mice. Biochemical analyses showed higher striatal tyrosine hydroxylase immuno-reactivity and reduced higher-order alpha-synuclein species in the cerebral cortex. However, no significant cerebral ALP induction was measured. In summary, treadmill exercise improved gait activity and postural stability, and promoted dopaminergic and alpha-synuclein homeostasis, without robustly inducing cerebral ALP.<br
Keywords: alpha-synuclein; autophagy; instrumented gait analysis; mouse gait pattern; Parkinson´s disease; treadmill exercise

Treatment of a patient with severe systemic sclerosis (SSc) using CD19-targeted CAR T cells. - Bergmann, Christina; Müller, Fabian; Distler, Jörg; Györfi, Andrea Hermina; Völkl, Simon; Aigner, Michael; Kretschmann, Sascha; Reimann, Hannah; Harrer, Thomas; Bayerl, Nadine; Böltz, Sebastian; Wirsching, Andreas; et al. (Annals of the Rheumatic Diseases, 2023)
EVALuna2:537682

Treatment of severe traumatic brain injury in German pediatric intensive care units—a survey of current practice - Regensburger, Adrian; Konrad, V.; Trollmann, Regina; Eyüpoglu, Ilker Yasin; Huebner, H.; Zierk, Jakob; Voelkl, T. M. K.; Fahlbusch, F. B. (Childs Nervous System, 2019)
Purpose: German pediatric guidelines for severe traumatic brain injury (TBI) management expired in 2011. Thus, divergent evidence-based institutional protocols are predominantly being followed. We performed a survey of current Pediatric Intensive Care Unit (PICU) management of isolated severe TBI in Germany to reveal potential varying practices. Methods: Seventy German PICUs were invited to join an anonymous online survey from February to May 2017. Twenty-nine participants (41.4%) successfully completed the survey (17 university hospitals and 12 district hospitals). The majority of items were polar (yes/no) or scaled (e.g., never - always). Main topics were imaging, neurosurgery, neuromonitoring, adjuvant therapy, and medication. Severity of TBI was defined via Glasgow Coma Scale. Results: The majority of respondents (93.1%) had internal TBI standards, and patients were mainly administered to interdisciplinary trauma units. The use of advanced neuromonitoring techniques, intracranial hypertension management, and drug treatment differed between PICUs. Routine administration of hypertonic saline in TBI-associated cerebral edema was performed by 3.4%, while it was never an option for 31.0% of the participants. Prophylactic anticonvulsive therapy was restrictively performed. If indicated, the main anticonvulsive drugs used were phenobarbital and levetiracetam. Neuroendocrine follow-up was recommended/performed by 58.6% of the PICUs. Conclusions: This survey provides an overview of the current PICU practices of isolated severe TBI management in Germany and demonstrates a wide instrumental and therapeutical range, revealing an unmet need for the revised national guideline and further (international) clinical trials for the treatment of severe TBI in pediatrics.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Adjuvant therapy; ICP; Neuroimaging; Neuromonitoring

TRPA1 and TRPV1 Antagonists Do Not Inhibit Human Acidosis-Induced Pain - Schwarz, Matthias G.; Namer, Barbara; Reeh, Peter; Fischer, Michael (Journal of Pain, 2017)
Acidosis occurs in a variety of pathophysiological and painful conditions where it is thought to excite or contribute to excitation of nociceptive neurons. Despite potential clinical relevance the principal receptor for sensing acidosis is unclear, but several receptors have been proposed. We investigated the contribution of the acid-sensing ion channels, transient receptor potential vanilloid type 1 (TRPV1) and transient receptor potential ankyrin type 1 (TRPA1) to peripheral pain signaling. We first established a human pain model using intraepidermal injection of the TRPA1 agonist carvacrol. This resulted in concentration-dependent pain sensations, which were reduced by experimental TRPA1 antagonist A-967079. Capsaicin-induced pain was reduced by the TRPV1 inhibitor BCTC. Amiloride was used to block acid-sensing ion channels. Testing these antagonists in a double-blind and randomized experiment, we probed the contribution of the respective channels to experimental acidosis-induced pain in 15 healthy human subjects. A continuous intraepidermal injection of pH 4.3 was used to counter the buffering capacity of tissue and generate a prolonged painful stimulation. In this model, addition of A-967079, BCTC or amiloride did not reduce the reported pain. In conclusion, target-validated antagonists, applied locally in human skin, have excluded the main hypothesized targets and the mechanism of the human acidosis-induced pain remains unclear. PERSPECTIVE: An acidic milieu is a trigger of pain in many clinical conditions. The aim of this study was to identify the contribution of the currently hypothesized sensors of acid-induced pain in humans. Surprisingly, inhibition of these receptors did not alter acidosis-induced pain.
EVALuna2:33346

Tumor location determines tissue-specific recruitment of tumor-associated macrophages and antibody-dependent immunotherapy response - Lehmann, Birgit; Biburger, Markus; Brückner, Christin; Ipsen Escobedo, Andrea; Gordan, Sina; Lehmann, Christian; Vöhringer, David; Winkler, Thomas; Schaft, Niels; Dudziak, Diana; Sirbu, Horia; Nimmerjahn, Falk; et al. (Science immunology, 2017)
Despite recent advances in activating immune cells to target tumors, the presence of some immune cells, such as tumor-associated macrophages (TAMs) or tumor-associated neutrophils (TANs), may promote rather than inhibit tumor growth. However, it remains unclear how antibody-dependent tumor immunotherapies, such as cytotoxic or checkpoint control antibodies, affect different TAM or TAN populations, which abundantly express activating Fcγ receptors. In this study, we show that the tissue environment determines which cellular effector pathways are responsible for antibody-dependent tumor immunotherapy. Although TAMs derived from Ly6Chigh monocytes recruited by the CCL2-CCR2 axis were critical for tumor immunotherapy of skin tumors, the destruction of lung tumors was CCL2-independent and required the presence of colony-stimulating factor 2–dependent tissue-resident macrophages. Our findings suggest that TAMs may have a dual role not only in promoting tumor growth in certain tissue environments on the one hand but also in contributing to tumor cell destruction during antibody-mediated immunotherapy on the other hand.
EVALuna2:15237
Keywords: Cancer; Macrophages; Tumor associated macrophages; Antibodies; Tumor therapy; Immunotherapy

Tumor–Stroma Ratio in Colorectal Cancer—Comparison between Human Estimation and Automated Assessment - Firmbach, Daniel; Benz, Michaela; Kuritcyn, Petr; Bruns, Volker; Lang-Schwarz, Corinna; Stübs, Frederik; Merkel, Susanne; Leikauf, Leah-Sophie; Braunschweig, Anna Lea; Oldenburger, Angelika; Gloßner, Laura; Abele, Niklas; et al. (Cancers, 2023)
The tumor–stroma ratio (TSR) has been repeatedly shown to be a prognostic factor for survival prediction of different cancer types. However, an objective and reliable determination of the tumor–stroma ratio remains challenging. We present an easily adaptable deep learning model for accurately segmenting tumor regions in hematoxylin and eosin (H&E)-stained whole slide images (WSIs) of colon cancer patients into five distinct classes (tumor, stroma, necrosis, mucus, and background). The tumor–stroma ratio can be determined in the presence of necrotic or mucinous areas. We employ a few-shot model, eventually aiming for the easy adaptability of our approach to related segmentation tasks or other primaries, and compare the results to a well-established state-of-the art approach (U-Net). Both models achieve similar results with an overall accuracy of 86.5% and 86.7%, respectively, indicating that the adaptability does not lead to a significant decrease in accuracy. Moreover, we comprehensively compare with TSR estimates of human observers and examine in detail discrepancies and inter-rater reliability. Adding a second survey for segmentation quality on top of a first survey for TSR estimation, we found that TSR estimations of human observers are not as reliable a ground truth as previously thought.
CRIS-Team Scopus Importer:2023-06-09
Keywords: colorectal cancer; deep learning; few-shot learning; image analysis; segmentation; tumor–stroma ratio; U-Net

Turning the tables on cytomegalovirus: targeting viral Fc receptors by CARs containing mutated CH2-CH3 IgG spacer domains - Proff, Julia; Brey, Charlotte U.; Enßer, Armin; Holter, Wolfgang; Lehner, Manfred (Journal of Translational Medicine, 2018)
Background: During infection with human cytomegalovirus (HCMV) several viral proteins occur on cell surfaces in high quantity. We thus pursue an HLA-independent approach for immunotherapy of HCMV using chimeric antigen receptors (CARs) and bispecific -BiTE (R) antibody constructs. In this context, HCMV-encoded proteins that mediate viral immune evasion and bind human IgG might represent particularly attractive target antigens. Unlike in observations of similar approaches for HIV and hepatitis B and C viruses, however, HCMV-infected cells develop a striking resistance to cytotoxic effector functions at later stages of the replication cycle. In our study we therefore wanted to test two hypotheses: (1) CAR T cells can efficiently inhibit HCMV replication independently from cytotoxic effector functions, and (2) HCMV can be targeted by CH2-CH3 IgG spacer domains that contain mutations previously reported to prevent exhaustion and to rescue CAR T cell function in vivo. Methods: Replication of GFP-encoding recombinant HCMV in fibroblasts in the presence and absence of supernatants from T cell co-cultures plus/minus cytokine neutralizing antibodies was analyzed by flow cytometry. CARs with wild type and mutated CH2-CH3 domains were expressed in human T cells by mRNA electroporation, and the function of the CARs was assessed by quantifying T cell cytokine secretion. Results: We confirm and extend previous evidence of antiviral cytokine effects and demonstrate that CAR T cells strongly block HCMV replication in fibroblasts mainly by combined secretion of IFN-gamma and TNF. Furthermore, we show that fibroblasts infected with HCMV strains AD169 and Towne starting from day 3 have a high capacity for binding of human IgG1 and also strongly activate T cells expressing a CAR with CH2-CH3 domain. Importantly, we further show that mutations in the CH2-CH3 domain of IgG1 and IgG4, which were previously reported to rescue CAR T cell function by abrogating interaction with endogenous Fc receptors (FcRs), still enable recognition of FcRs encoded by HCMV. Conclusions: Our findings identify HCMV-encoded FcRs as an attractive additional target for HCMV immunotherapy by CARs and possibly bispecific antibodies. The use of specifically mutated IgG domains that bind to HCMV-FcRs without recognizing endogenous FcRs may supersede screening for novel binders directed against individual HCMV-FcRs.
EVALuna2:35288

Type I Interferon Signaling Is Required for CpG-Oligodesoxynucleotide-Induced Control ofLeishmania major, but Not for Spontaneous Cure of Subcutaneous Primary or SecondaryL. majorInfection - Schleicher, Ulrike; Liese, Jan; Justies, Nicole; Mischke, Thomas; Haeberlein, Simone; Sebald, Heidi; Kalinke, Ulrich; Weiss, Siegfried; Bogdan, Christian (Frontiers in Immunology, 2018)
We previously showed that in mice infected withLeishmania majortype I interferons (IFNs) initiate the innate immune response to the parasite at day 1 and 2 of infection. Here, we investigated which type I IFN subtypes are expressed during the first 8 weeks ofL. majorinfection and whether type I IFNs are essential for a protective immune response and clinical cure of the disease. In self-healing C57BL/6 mice infected with a high dose ofL. major, IFN-α4, IFN-α5, IFN-α11, IFN-α13, and IFN-β mRNA were most prominently regulated during the course of infection. In C57BL/6 mice deficient for IFN-β or the IFN-α/β-receptor chain 1 (IFNAR1), development of skin lesions and parasite loads in skin, draining lymph node, and spleen was indistinguishable from wild-type (WT) mice. In line with the clinical findings, C57BL/6 IFN-β-/-, IFNAR1-/-, and WT mice exhibited similar mRNA expression levels of IFN-γ, interleukin (IL)-4, IL-12, IL-13, inducible nitric oxide synthase, and arginase 1 during the acute and late phase of the infection. Also, myeloid dendritic cells from WT and IFNAR1-/-mice produced comparable amounts of IL-12p40/p70 protein upon exposure toL. major in vitro. In non-healing BALB/c WT mice, the mRNAs of IFN-α subtypes (α2, α4, α5, α6, and α9) were rapidly induced after high-doseL. majorinfection. However, genetic deletion of IFNAR1 or IFN-β did not alter the progressive course of infection seen in WT BALB/c mice. Finally, we tested whether type I IFNs and/or IL-12 are required for the prophylactic effect of CpG-oligodesoxynucleotides (ODN) in BALB/c mice. Local and systemic administration of CpG-ODN 1668 protected WT and IFN-β-/-mice equally well from progressive leishmaniasis. By contrast, the protective effect of CpG-ODN 1668 was lost in BALB/c IFNAR1-/-(despite a sustained suppression of IL-4) and in BALB/c IL-12p35-/-mice. From these data, we conclude that IFN-β and IFNAR1 signaling are dispensable for a curative immune response toL. majorin C57BL/6 mice and irrelevant for disease development in BALB/c mice, whereas IL-12 and IFN-α subtypes are essential for the disease prevention by CpG-ODNs in this mouse strain.
EVALuna2:33302

Ultra high-field SWI of the substantia nigra at 7T: reliability and consistency of the swallow-tail sign - Schmidt, Manuel; Engelhorn, Tobias; Marxreiter, Franz; Winkler, Jürgen; Lang, Stefan; Kloska, Stephan; Gölitz, Philipp; Dörfler, Arnd (BMC Neurology, 2017)
BACKGROUND: The loss of the swallow-tail sign of the substantia nigra has been proposed for diagnosis of Parkinson's disease. Aim was to evaluate, if the sign occurs consistently in healthy subjects and if it can be reliably detected with high-resolution 7T susceptibility weighted imaging (SWI). METHODS: Thirteen healthy adults received SWI at 7T. 3 neuroradiologists, who were blinded to patients' diagnosis, independently classified subjects regarding the swallow-tail sign to be present or absent. Accuracy, positive and negative predictive values (PPV and NPV) as well as inter- and intra-rater reliability and internal consistency were analyzed. RESULTS: The sign could be detected in 81% of the cases in consensus reading. Accuracy to detect the sign compared to the consensus was 100, 77 and 96% for the three readers with PPV reader 1/2/3 = 1/0.45/0.83 and NPV = 1/1/1. Inter-rater reliability was excellent (inter-class correlation coefficient = 0.844, alpha = 0.871). Intra-rater reliability was good to excellent (reader 1 R/L = 0.625/0.786; reader 2 = 0.7/0.64; reader 3 = 0.9/1). CONCLUSION: The swallow-tail sign can be reliably detected. However, our data suggest its occurrence is not consistent in healthy subjects. It may be possible that one reason is an individually variable molecular organization of nigrosome 1 so that it does not return a uniform signal in SWI.
EVALuna2:33135

Ultra-high-frequency ultrasound in patients with spinal muscular atrophy: A retrospective feasibility study - Regensburger, Adrian; Wagner, Anna; Hanslik, Gregor; Schuessler, Stephanie C.; Fahlbusch, Fabian; Wölfle, Joachim; Juengert, Joerg; Trollmann, Regina; Knieling, Ferdinand (Muscle & Nerve, 2020)
CRIS-Team WoS Importer:2020-01-17

Uncovering the role of Sox2 in oligodendroglia - Kuhbandner, Kristina (Journal of Neuroscience, 2018)
Created from Fastlane, Scopus look-up

Variants in SCAF4 Cause a Neurodevelopmental Disorder and Are Associated with Impaired mRNA Processing - Fliedner, Anna; Kirchner, Philipp; Wiesener, Antje; van de Beek, Irma; Waisfisz, Quinten; van Haelst, Mieke; Scott, Daryl A.; Lalani, Seema R.; Rosenfeld, Jill A.; Azamian, Mahshid S.; Xia, Fan; Dutra-Clarke, Marina; et al. (American Journal of Human Genetics, 2020)
RNA polymerase II interacts with various other complexes and factors to ensure correct initiation, elongation, and termination of mRNA transcription. One of these proteins is SR-related CTD-associated factor 4 (SCAF4), which is important for correct usage of polyA sites for mRNA termination. Using exome sequencing and international matchmaking, we identified nine likely pathogenic germline variants in SCAF4 including two splice-site and seven truncating variants, all residing in the N-terminal two thirds of the protein. Eight of these variants occurred de novo, and one was inherited. Affected individuals demonstrated a variable neurodevelopmental disorder characterized by mild intellectual disability, seizures, behavioral abnormalities, and various skeletal and structural anomalies. Paired-end RNA sequencing on blood lymphocytes of SCAF4-deficient individuals revealed a broad deregulation of more than 9,000 genes and significant differential splicing of more than 2,900 genes, indicating an important role of SCAF4 in mRNA processing. Knockdown of the SCAF4 ortholog CG4266 in the model organism Drosophila melanogaster resulted in impaired locomotor function, learning, and short-term memory. Furthermore, we observed an increased number of active zones in larval neuromuscular junctions, representing large glutamatergic synapses. These observations indicate a role of CG4266 in nervous system development and function and support the implication of SCAF4 in neurodevelopmental phenotypes. In summary, our data show that heterozygous, likely gene-disrupting variants in SCAF4 are causative for a variable neurodevelopmental disorder associated with impaired mRNA processing.
CRIS-Team Scopus Importer:2020-08-21
Keywords: epilepsy; intellectual disability; mRNA processing; neurodevelopmental disorder; SCAF4; seizures

VCP-related multisystem proteinopathy presenting as early-onset Parkinson disease - Regensburger, Martin; Türk, Matthias; Pagenstecher, Axel; Schröder, Rolf; Winkler, Jürgen (Neurology, 2017)
EVALuna2:7395

Viral FLIP blocks Caspase-8 driven apoptosis in the gut in vivo - Ruder, Barbara; Günther, Claudia; Stürzl, Michael; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; Becker, Christoph (PLoS ONE, 2020)
A strict cell death control in the intestinal epithelium is indispensable to maintain barrier integrity and homeostasis. In order to achieve a balance between cell proliferation and cell death, a tight regulation of Caspase-8, which is a key player in controlling apoptosis, is required. Caspase-8 activity is regulated by cellular FLIP proteins. These proteins are expressed in different isoforms (cFLIPlong and cFLIPshort) which determine cell death and survival. Interestingly, several viruses encode FLIP proteins, homologous to cFLIPshort, which are described to regulate Caspase-8 and the host cell death machinery. In the current study a mouse model was generated to show the impact of viral FLIP (vFLIP) from Kaposi's Sarcoma-associated Herpesvirus (KSHV)/ Human Herpesvirus-8 (HHV-8) on cell death regulation in the gut. Our results demonstrate that expression of vFlip in intestinal epithelial cells suppressed cFlip expression, but protected mice from lethality, tissue damage and excessive apoptotic cell death induced by genetic cFlip deletion. Finally, our model shows that vFlip expression decreases cFlip mediated Caspase-8 activation in intestinal epithelial cells. In conclusion, our data suggests that viral FLIP neutralizes and compensates for cellular FLIP, efficiently counteracting host cell death induction and facilitating further propagation in the host organism.
CRIS-Team Scopus Importer:2020-02-11

Wild-type KRAS is a novel therapeutic target for melanoma contributing to primary and acquired resistance to BRAF inhibition - Dietrich, Peter; Kuphal, Silke; Spruss, T.; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Oncogene, 2017)
Malignant melanoma reveals rapidly increasing incidence and mortality rates worldwide. By now, BRAF inhibition is the standard therapy for advanced melanoma in patients carrying BRAF mutations. However, only approximately 50% of melanoma patients harbor therapeutically attackable BRAF mutations, and overall survival after treatment with BRAF inhibitors is modest. KRAS (Kirsten Rat sarcoma) proteins are acting upstream of BRAF and have a major role in human cancer. Recent approaches awaken the hope to use KRAS inhibition (KRASi) as a clinical tool. In this study, we identified wild-type KRAS as a novel therapeutic target in melanoma. KRASi functions synergistically with BRAF inhibition to reduce melanoma proliferation and to induce apoptosis independently of BRAF mutational status. Moreover, acquired resistance to BRAF inhibitors in melanoma is dependent on dynamic regulation of KRAS expression with subsequent AKT and extracellular-signal regulated kinase activation and can be overcome by KRASi. This suggests KRASi as novel approach in melanoma-alone or in combination with other therapeutic regimes.Oncogene advance online publication, 23 October 2017; doi:10.1038/onc.2017.391.
EVALuna2:4759

Xanthohumol, a prenylated chalcone derived from hops, inhibits growth and metastasis of melanoma cells - Seitz, Tatjana; Hackl, Christina; Freese, Kim; Dietrich, Peter; Mahli, Abdo; Thasler, Reinhard Manfred; Thasler, Wolfgang Erwin; Lang, Sven Arke; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cancers, 2021)
Melanoma is one of the most aggressive and lethal cancers worldwide. Despite recent progress in melanoma therapy, the prognosis for metastasized melanoma continues to be poor. Xan-thohumol (XN), a prenylated chalcone derived from hop cones, is known to possess a broad spectrum of chemopreventive and anticancer activities. However, few studies have analyzed functional XN effects on melanoma cells and there have been no previous in vivo studies of its effects on metastasis. The aim of this study was to investigate the impact of XN on the tumorigenic and liver metastatic activity of melanoma cells. XN exhibited dose-dependent cytotoxic effects on human melanoma cell lines (Mel Ju; Mel Im) in vitro. Functional analysis in the subtoxic dose-range revealed that XN dose-dependently inhibited proliferation, colony formation, and migratory activity of melanoma cells. Subtoxic XN doses also induced markers of endoplasmic reticulum stress but inhibited the phosphorylation of the protumorigenic c-Jun N-terminal kinases (JNK). Furthermore, XN effects on hepatic metastasis were analyzed in a syngeneic murine model (splenic injection of murine B16 melanoma cells in C57/BL6 mice). Here, XN significantly reduced the formation of hepatic metastasis. Metastases formed in the liver of XN-treated mice revealed significantly larger areas of central necrosis and lower Ki67 expression scores compared to that of control mice. In conclusion, XN inhibits tumorigenicity of melanoma cells in vitro and significantly reduced hepatic metastasis of melanoma cells in mice. These data, in conjunction with an excellent safety profile that has been confirmed in previous studies, indicate XN as a promising novel agent for the treatment of hepatic (melanoma) metastasis.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Melanoma; Metastasis; Xanthohumol

Zooming in on Cryopreservation of hiPSCs and Neural Derivatives: A Dual-Center Study Using Adherent Vitrification - Kaindl, Johanna; Meiser, Ina; Majer, Julia; Sommer, Annika; Krach, Florian; Katsen-Globa, Alisa; Winkler, Jürgen; Zimmermann, Heiko; Neubauer, Julia C.; Winner, Beate (Stem Cells Translational Medicine, 2019)
Human induced pluripotent stem cells (hiPSCs) are an important tool for research and regenerative medicine, but their efficient cryopreservation remains a major challenge. The current gold standard is slow-rate freezing of dissociated colonies in suspension, but low recovery rates limit immediate post-thawing applicability. We tested whether ultrafast cooling by adherent vitrification improves post-thawing survival in a selection of hiPSCs and small molecule neural precursor cells (smNPCs) from Parkinson's disease and controls. In a dual-center study, we compared the results by immunocytochemistry (ICC), fluorescence-activated cell sorting analysis, and RNA-sequencing (RNA-seq). Adherent vitrification was achieved in the so-called TWIST substrate, a device combining cultivation, vitrification, storage, and post-thawing cultivation. Adherent vitrification resulted in preserved confluency and significantly higher cell numbers, and viability at day 1 after thawing, while results were not significantly different at day 4 after thawing. RNA-seq and ICC of hiPSCs revealed no change in gene expression and pluripotency markers, indicating that physical damage of slow-rate freezing disrupts cellular membranes. Scanning electron microscopy showed preserved colony integrity by adherent vitrification. Experiments using smNPCs demonstrated that adherent vitrification is also applicable to neural derivatives of hiPSCs. Our data suggest that, compared to the state-of-the-art slow-rate freezing in suspension, adherent vitrification is an improved cryopreservation technique for hiPSCs and derivatives. Stem Cells Translational Medicine 2019;8:247&259.
EVALuna2:36383

α-Synuclein oligomers induce early axonal dysfunction in human iPSC-based models of synucleinopathies - Prots, Iryna; Grosch, Janina; Brazdis, Razvan-Marius; Simmnacher, Katrin; Veber, Vanesa; Havlicek, Steven; Hannappel, Christian; Krach, Florian; Krumbiegel, Mandy; Schuetz, Oliver; Reis, André; Wrasidlo, Wolfgang; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
α-Synuclein (α-Syn) aggregation, proceeding from oligomers to fibrils, is one central hallmark of neurodegeneration in synucleinopathies. α-Syn oligomers are toxic by triggering neurodegenerative processes in in vitro and in vivo models. However, the precise contribution of α-Syn oligomers to neurite pathology in human neurons and the underlying mechanisms remain unclear. Here, we demonstrate the formation of oligomeric α-Syn intermediates and reduced axonal mitochondrial transport in human neurons derived from induced pluripotent stem cells (iPSC) from a Parkinson's disease patient carrying an α-Syn gene duplication. We further show that increased levels of α-Syn oligomers disrupt axonal integrity in human neurons. We apply an α-Syn oligomerization model by expressing α-Syn oligomer-forming mutants (E46K and E57K) and wild-type α-Syn in human iPSC-derived neurons. Pronounced α-Syn oligomerization led to impaired anterograde axonal transport of mitochondria, which can be restored by the inhibition of α-Syn oligomer formation. Furthermore, α-Syn oligomers were associated with a subcellular relocation of transport-regulating proteins Miro1, KLC1, and Tau as well as reduced ATP levels, underlying axonal transport deficits. Consequently, reduced axonal density and structural synaptic degeneration were observed in human neurons in the presence of high levels of α-Syn oligomers. Together, increased dosage of α-Syn resulting in α-Syn oligomerization causes axonal transport disruption and energy deficits, leading to synapse loss in human neurons. This study identifies α-Syn oligomers as the critical species triggering early axonal dysfunction in synucleinopathies.
EVALuna2:34623
Keywords: alpha-synuclein; oligomers; axonal transport; synucleinopathies; neurodegeneration

β1 and β3 subunits amplify mechanosensitivity of the cardiac voltage-gated sodium channel Nav1.5 - Maroni, Michele; Körner, Jannis; Schüttler, Jürgen; Winner, Beate; Lampert, Angelika; Eberhardt, Esther (Pflügers Archiv: European Journal of Physiology, 2019)
In cardiomyocytes, electrical activity is coupled to cellular contraction, thus exposing all proteins expressed in the sarcolemma to mechanical stress. The voltage-gated sodium channel Nav1.5 is the main contributor to the rising phase of the action potential in the heart. There is growing evidence that gating and kinetics of Nav1.5 are modulated by mechanical forces and pathogenic variants that affect mechanosensitivity have been linked to arrhythmias. Recently, the sodium channel β1 subunit has been described to stabilise gating against mechanical stress of Nav1.7 expressed in neurons. Here, we tested the effect of β1 and β3 subunits on mechanosensitivity of the cardiac Nav1.5. β1 amplifies stress-induced shifts of V1/2 of steady-state fast inactivation to hyperpolarised potentials (ΔV1/2: 6.2 mV without and 10.7 mV with β1 co-expression). β3, on the other hand, almost doubles stress-induced speeding of time to sodium current transient peak (Δtime to peak at − 30 mV: 0.19 ms without and 0.37 ms with β3 co-expression). Our findings may indicate that in cardiomyocytes, the interdependence of electrical activity and contraction is used as a means of fine tuning cardiac sodium channel function, allowing quicker but more strongly inactivating sodium currents under conditions of increased mechanical stress. This regulation may help to shorten action potential duration during tachycardia, to prevent re-entry phenomena and thus arrhythmias.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Cardiac ion channel; Mechanosensitivity; Patch-clamp; Sodium channel

β-Arrestin2 is increased in liver fibrosis in humans and rodents - Schierwagen, Robert; Dietrich, Peter; Klein, Sabine; Uschner, Frank Erhard; Ortiz, Cristina; Tyc, Olaf; Torres, Sandra; Hellerbrand, Claus; Sauerbruch, Tilman; Trebicka, Jonel (Proceedings of the National Academy of Sciences of the United States of America, 2020)
CRIS-Team Scopus Importer:2020-11-13